Prospects in Mycobacterium bovis Bacille Calmette et Guérin (BCG) Vaccine Diversity and Delivery: Why does BCG fail to protect against Tuberculosis? - Moliva, Juan I.; Turner, Joanne; Torrelles, Jordi B. (Vaccine, 2015)
Mycobacterium tuberculosis (M.tb) infection leads to active tuberculosis (TB), a disease that kills one human every 18 seconds. Current therapies available to combat TB include chemotherapy and the preventative vaccine Mycobacterium bovis Bacille Calmette et Guérin (BCG). Increased reporting of drug resistant M.tb strains worldwide indicates that drug development cannot be the primary mechanism for eradication. BCG vaccination has been used globally for protection against childhood and disseminated TB, however, its efficacy at protecting against pulmonary TB in adult and aging populations is highly variable. In this regard, the immune response generated by BCG vaccination is incapable of sterilizing the lung post M.tb infection as indicated by the large proportion of individuals with latent TB infection that have received BCG. Although many new TB vaccine candidates have entered the development pipeline, only a few have moved to human clinical trials; where they showed no efficacy and/or were withdrawn due to safety regulations. These trials highlight our limited understanding of protective immunity against the development of active TB. Here, we discuss current vaccination strategies and their impact on the generation and sustainability of protective immunity against TB.

Mycobacterium tuberculosis Rv2536 protein implicated in specific binding to human cell lines - García, Javier; Puentes, Alvaro; Rodríguez, Luis; Ocampo, Marisol; Curtidor, Hernando; Vera, Ricardo; Lopez, Ramses; Valbuena, John; Cortes, Jimena; Vanegas, Magnolia; Barrero, Carlos; Patarroyo, Manuel A.; et al. (Protein Science : A Publication of the Protein Society, 2005)
The gene encoding the Mycobacterium tuberculosis Rv2536 protein is present in the Mycobacterium tuberculosis complex (as assayed by PCR) and transcribed (as determined by RT-PCR) in M. tuberculosis H37Rv, M. tuberculosis H37Ra, M. bovis BCG, and M. africanum strains. Rabbits immunized with synthetic polymer peptides from this protein produced antibodies specifically recognizing a 25-kDa band in mycobacterial sonicate. U937 and A549 cells were used in binding assays involving 20-amino-acid-long synthetic peptides covering the whole Rv2536 protein sequence. Peptide 11207 (161DVFSAVRADDSPTGEMQVAQY180) presented high specific binding to both types of cells; the binding was saturable and presented nanomolar affinity constants. Cross-linking assays revealed that this peptide specifically binds to 50 kDa U937 cell membrane and 45 kDa A549 cell membrane proteins.

Identifying putative Mycobacterium tuberculosis Rv2004c protein sequences that bind specifically to U937 macrophages and A549 epithelial cells - Forero, Martha; Puentes, Álvaro; Cortés, Jimena; Castillo, Fabio; Vera, Ricardo; Rodríguez, Luis E.; Valbuena, John; Ocampo, Marisol; Curtidor, Hernando; Rosas, Jaiver; García, Javier; Barrera, Gloria; et al. (Protein Science : A Publication of the Protein Society, 2005)
Virulence and immunity are still poorly understood in Mycobacterium tuberculosis. The H37Rv M. tuberculosis laboratory strain genome has been completely sequenced, and this along with proteomic technology represent powerful tools contributing toward studying the biology of target cell interaction with a facultative bacillus and designing new strategies for controlling tuberculosis. Rv2004c is a putative M. tuberculosis protein that could have specific mycobacterial functions. This study has revealed that the encoding gene is present in all mycobacterium species belonging to the M. tuberculosis complex. Rv2004c gene transcription was observed in all of this complex’s strains except Mycobacterium bovis and Mycobacterium microti. Rv2004c protein expression was confirmed by using antibodies able to recognize a 54-kDa molecule by immunoblotting, and its location was detected on the M. tuberculosis surface by transmission electron microscopy, suggesting that it is a mycobacterial surface protein. Binding assays led to recognizing high activity binding peptides (HABP); five HABPs specifically bound to U937 cells, and six specifically bound to A549 cells. HABP circular dichroism suggested that they had an α-helical structure. HABP–target cell interaction was determined to be specific and saturable; some of them also displayed greater affinity for A549 cells than U937 cells. The critical amino acids directly involved in their interaction with U937 cells were also determined. Two probable receptor molecules were found on U937 cells and five on A549 for the two HABPs analyzed. These observations have important biological significance for studying bacillus–target cell interactions and implications for developing strategies for controlling this disease.

Characterising Mycobacterium tuberculosis Rv1510c protein and determining its sequences that specifically bind to two target cell lines - Vera-Bravo, Ricardo; Torres, Elizabeth; Valbuena, John J.; Ocampo, Marisol; Rodríguez, Luis E.; Puentes, Alvaro; García, Javier E.; Curtidor, Hernando; Cortés, Jimena; Vanegas, Magnolia; Rivera, Zuly J.; Díaz, Andrea; et al. (Biochemical and Biophysical Research Communications, 2005)
The process of Mycobacterium tuberculosis infection of the macrophage implies a very little-known initial recognition and adherence step, important for mycobacterial survival; many proteins even remain like hypothetical. The Rv1510c gene, encoding a putatively conserved membrane protein, was investigated by analysing the M. tuberculosis genome sequence data reported by Cole et al. and a previous report that used PCR assays to show that the Rv1510 gene was only present in M. tuberculosis. This article confirmed all the above and identified the transcribed gene in M. tuberculosis, Mycobacterium africanum, and in M. tuberculosis clinical isolates. Antibodies raised against peptides from this protein recognised a 44 kDa band, corresponding to Rv1510c theoretical mass (44,294 Da). Assays involving synthetic peptides covering the whole protein binding to U937 and A549 cell lines led to recognising five high activity binding peptides in the Rv1510 protein: 11094, 11095, 11105, 11108, and 11111. Their affinity constants and Hill coefficients were determined by using U937 cells. Cross-linking assays performed with some of these HABPs showed that they specifically bound to a U937 cell line 51 kDa protein, but not to Hep G2 or red blood cell proteins, showing this interaction's specificity.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Base Sequence; Binding Sites; Cell Line; Circular Dichroism; Cross-Linking Reagents; DNA, Bacterial; Genes, Bacterial; Humans; Kinetics; Membrane Proteins; Molecular Sequence Data; Molecular Weight; Mycobacterium tuberculosis; Peptide Fragments; U937 Cells

Characterizing the Mycobacterium tuberculosis Rv2707 protein and determining its sequences which specifically bind to two human cell lines - Chapeton-Montes, Julie A.; Plaza, David F.; Curtidor, Hernando; Forero, Martha; Vanegas, Magnolia; Patarroyo, Manuel E.; Patarroyo, Manuel A. (Protein Science : A Publication of the Protein Society, 2008)
The Rv2707 gene encoding a putative alanine- and leucine-rich protein was found to be present in all Mycobacterium tuberculosis complex strains (by PCR) and its transcription was shown by RT-PCR in all but M. bovis and M. microti. Antibodies raised against Rv2707 peptides specifically recognized the native protein by Western blot and were able to locate this protein on the M. tuberculosis membrane by immunoelectron microscopy. A549 and U937 cells lines were used in binding assays involving synthetic peptides covering the whole Rv2707 protein. High A549 cell-binding peptide 16083 (281QEEWPAPATHAHRLGNWLKAY300) was identified. Peptides 16072 (61LFGPDTLPAIEKSALSTAHSY80) and 16084 (301RIGVGTTTYSSTAQHSAVAA320) presented high specific binding to both A549 and U937 cells. Cross-linking assays revealed that peptide 16084 specifically bound to a 40-kDa and a 50-kDa U937 cell membrane protein. High activity binding peptides (HABPs) 16083 and 16084 were able to inhibit M. tuberculosis invasion of A549 cells. Our results suggest that these sequences could be part of the binding sites used by the bacillus for interacting with target cells, and thus represent good candidates to be tested in a future subunit-based, multiepitope, antituberculosis vaccine.

Mycobacterium tuberculosis Rv0679c protein sequences involved in host-cell infection: Potential TB vaccine candidate antigen - Cifuentes, Diana P; Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Forero, Martha; Patarroyo, Manuel E; Patarroyo, Manuel A (BMC Microbiology, 2010)
Background To date, the function of many hypothetical membrane proteins of Mycobacterium tuberculosis is still unknown and their involvement in pathogen-host interactions has not been yet clearly defined. In this study, the biological activity of peptides derived from the hypothetical membrane protein Rv0679c of M. tuberculosis and their involvement in pathogen-host interactions was assessed. Transcription of the Rv0679c gene was studied in 26 Mycobacterium spp. Strains. Antibodies raised against putative B-cell epitopes of Rv0679c were used in Western blot and immunoelectron microscopy assays. Synthetic peptides spanning the entire length of the protein were tested for their ability to bind to A549 and U937 cells. High-activity binding peptides (HABPs) identified in Rv0679c were tested for their ability to inhibit mycobacterial invasion into cells. Results The gene encoding Rv0679c was detected in all strains of the M. tuberculosis complex (MTC), but was only transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra and M. africanum. Anti-Rv0679c antibodies specifically recognized the protein in M. tuberculosis H37Rv sonicate and showed its localization on mycobacterial surface. Four HABPs inhibited invasion of M. tuberculosis to target cells by up to 75%. Conclusions The results indicate that Rv0679c HABPs and in particular HABP 30979 could be playing an important role during M. tuberculosis invasion of host cells, and therefore could be interesting research targets for studies aimed at developing strategies to control tuberculosis.

Functional characterization of Mycobacterium tuberculosis Rv2969c membrane protein - Patarroyo, Manuel A.; Plaza, David F.; Ocampo, Marisol; Curtidor, Hernando; Forero, Martha; Rodriguez, Luis E.; Patarroyo, Manuel E. (Biochemical and Biophysical Research Communications, 2008)
Identifying Mycobacterium tuberculosis membrane proteins involved in binding to and invasion of host cells is important in designing subunit-based anti-tuberculosis vaccines. The Rv2969c gene sequence was identified by PCR in M. tuberculosis complex strains, being transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra, and M. bovis BCG. Rabbits immunized with synthetic peptides from highly specific conserved regions of this protein produced antibodies recognizing 27 and 29 kDa bands in M. tuberculosis lysate, which is consistent with the molecular weight of the Rv2969c gene product in M. tuberculosis H37Rv. Immunoelectron microscopy revealed the protein was localized on the bacillus surface. Four and three specific high activity binding peptides (HABPs) to the A549 alveolar epithelial and U937 monocyte cell lines were found, respectively. Two of the HABPs found inhibited M. tuberculosis invasion of A549 cells, suggesting that these peptides might be good candidates to be included in a multiepitopic, subunit-based anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Cell Line; Genes, Bacterial; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Tuberculosis Vaccines

Specific interaction between Mycobacterium tuberculosis lipoprotein-derived peptides and target cells inhibits mycobacterial entry in vitro - Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Chemical Biology & Drug Design, 2014)
Tuberculosis (TB) continues being one of the diseases having the greatest mortality rates around the world, 8.7 million cases having been reported in 2011. An efficient vaccine against TB having a great impact on public health is an urgent need. Usually, selecting antigens for vaccines has been based on proteins having immunogenic properties for patients suffering TB and having had promising results in mice and non-human primates. Our approach has been based on a functional approach involving the pathogen-host interaction in the search for antigens to be included in designing an efficient, minimal, subunit-based anti-TB vaccine. This means that Mycobacterium tuberculosis has mainly been involved in studies and that lipoproteins represent an important kind of protein on the cell envelope which can also contribute towards this pathogen's virulence. This study has assessed the expression of four lipoproteins from M. tuberculosis H37Rv, that is, Rv1411c (LprG), Rv1911c (LppC), Rv2270 (LppN) and Rv3763 (LpqH), and the possible biological activity of peptides derived from these. Five peptides were found for these proteins which had high specific binding to both alveolar A549 epithelial cells and U937 monocyte-derived macrophages which were able to significantly inhibit mycobacterial entry to these cells in vitro.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Peptides; Antibodies; antituberculosis vaccine; Cell Line, Tumor; Computational Biology; high activity binding peptide; Host-Pathogen Interactions; Lipoproteins; Microspheres; multi-epitope vaccine; Protein Binding; Protein Structure, Secondary; synthetic peptide

Functional, biochemical and 3D studies of Mycobacterium tuberculosis protein peptides for an effective anti-tuberculosis vaccine - Ocampo, Marisol; Patarroyo, Manuel A.; Vanegas, Magnolia; Alba, Martha P.; Patarroyo, Manuel E. (Critical Reviews in Microbiology, 2014)
Tuberculosis (TB) is an air-born, transmissible disease, having an estimated 9.4 million new TB cases worldwide in 2009. Eventual control of this disease by developing a safe and efficient new vaccine able to detain its spread will have an enormous impact on public health policy. Selecting potential antigens to be included in a multi-epitope, minimal subunit-based, chemically-synthesized vaccine containing the minimum sequences needed for blocking mycobacterial interaction with host cells is a complex task due to the multiple mechanisms involved in M. tuberculosis infection and the mycobacterium's immune evasion mechanisms. Our methodology, described here takes into account a highly robust, specific, sensitive and functional approach to the search for potential epitopes to be included in an anti-TB vaccine; it has been based on identifying short mycobacterial protein fragments using synthetic peptides having high affinity interaction with alveolar epithelial cells (A549) and monocyte-derived macrophages (U937) which are able to block the microorganism's entry to target cells in in vitro assays. This manuscript presents a review of the results obtained with some of the MTB H37Rv proteins studied to date, aimed at using these high activity binding peptides (HABPs) as platforms to be included in a minimal subunit-based, multiepitope, chemically-synthesized, antituberculosis vaccine.
Keywords: Bacterial Proteins; Cell Line; Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Antigens, Bacterial; Bacterial Adhesion; Epithelial Cells; Macrophages

Antibodies targeting Mycobacterium tuberculosis peptides inhibit mycobacterial entry to infection target cells - Carabali-Isajar, Mary L.; Ocampo, Marisol; Varela, Yahson; Díaz-Arévalo, Diana; Patarroyo, Manuel A.; Patarroyo, Manuel E. (International Journal of Biological Macromolecules, 2020)
The humoral immunity regarding tuberculosis can contribute towards controlling the mycobacteria and the disease. Antigens mediating such type of immunity should thus be evaluated for formulating anti-tuberculosis vaccines. The antigen recognition of seven peptides derived from proteins on Mtb H37Rv envelope and a further seven peptides modified from them was evaluated in sera taken from people suffering Mtb infection and others free from it. Peptide sequences' ability to inhibit Mtb entry to human macrophages was determined in vitro and, after isolating peptide-specific IgG antibodies, it was ascertained which ones were exercising such inhibitory function. Aotus were inoculated with the modified peptides for evaluating the activity of the antibodies so produced. Human QTF+ and QTF- sera recognised some of the peptides and inhibited Mtb entry. The same effect was seen with peptide-specific IgG regarding all the native sequences and modified ones. Sera taken from inoculated Aotus was also able to reduce the pathogen's entry. The data showed that some peptides evaluated in this study could induce antibodies able to inhibit the pathogen's entry to human macrophages, i.e. they could represent candidates for part of an anti-tuberculosis vaccine. The methodology used here complements the evaluation of promising antigens for designing effective vaccines.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; U937 Cells; Animals; Peptides; Antibodies; Macrophages; Aotidae; HABPs; Immunoglobulin G; Inhibition assay; Tuberculosis; Vacccine

Mycobacterium tuberculosis Rv0679c protein sequences involved in host-cell infection: potential TB vaccine candidate antigen - Cifuentes, Diana P.; Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Forero, Martha; Patarroyo, Manuel E.; Patarroyo, Manuel A. (BMC microbiology, 2010)
BACKGROUND: To date, the function of many hypothetical membrane proteins of Mycobacterium tuberculosis is still unknown and their involvement in pathogen-host interactions has not been yet clearly defined. In this study, the biological activity of peptides derived from the hypothetical membrane protein Rv0679c of M. tuberculosis and their involvement in pathogen-host interactions was assessed. Transcription of the Rv0679c gene was studied in 26 Mycobacterium spp. Strains. Antibodies raised against putative B-cell epitopes of Rv0679c were used in Western blot and immunoelectron microscopy assays. Synthetic peptides spanning the entire length of the protein were tested for their ability to bind to A549 and U937 cells. High-activity binding peptides (HABPs) identified in Rv0679c were tested for their ability to inhibit mycobacterial invasion into cells. RESULTS: The gene encoding Rv0679c was detected in all strains of the M. tuberculosis complex (MTC), but was only transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra and M. africanum. Anti-Rv0679c antibodies specifically recognized the protein in M. tuberculosis H37Rv sonicate and showed its localization on mycobacterial surface. Four HABPs inhibited invasion of M. tuberculosis to target cells by up to 75%. CONCLUSIONS: The results indicate that Rv0679c HABPs and in particular HABP 30979 could be playing an important role during M. tuberculosis invasion of host cells, and therefore could be interesting research targets for studies aimed at developing strategies to control tuberculosis.
Keywords: Antibodies, Bacterial; Bacterial Proteins; Cell Line; Humans; Mycobacterium tuberculosis; Microscopy, Immunoelectron; Tuberculosis Vaccines; Host-Pathogen Interactions; Protein Binding; Antigens, Bacterial; Epithelial Cells; Blotting, Western; Epitopes, B-Lymphocyte; Gene Expression Profiling; Monocytes; Virulence Factors

Cell-Peptide Specific Interaction Can Inhibit Mycobacterium tuberculosis H37Rv Infection - Rodríguez, Deisy Carolina; Ocampo, Marisol; Reyes, Cesar; Arévalo-Pinzón, Gabriela; Munoz, Marina; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Journal of Cellular Biochemistry, 2016)
Studying proteins from the M. tuberculosis H37Rv envelop is important for understanding host-pathogen interaction regarding bacterial infection and survival within a host; such knowledge is indispensable regarding studies aimed at developing drugs or vaccines against tuberculosis, a disease which continues to cause more than one million deaths worldwide every year. The present work presents a study of the Rv3705c protein which has been described as being an outer protein. Several servers and bioinformatics' tools were used for predicting its location on mycobacterial surface and a 3D model of the protein was obtained which was then compared to experimental circular dichroism results for its peptides. PCR assays were used for corroborating rv3705c gene presence and transcription in a laboratory strain and immunoblotting and electron microscopy were used for confirming protein localisation on cell envelop. Receptor-ligand assays revealed two peptides having high specific binding (HABPs); peptide 38485 ((121)DRAFHRVVDRTVGTSGQTTA(140)) bound to both cell lines used as infection target (U937 and A549 epithelial cell line-derived macrophages) and 38488 ((181)RLRENVLLQAKVTQSGNAGP(200)) bound to U937 cells. It was found that peptide 38485 provided significant inhibition regarding mycobacterial entry to both cell lines in in vitro assays. These results led to proposing peptide 38485 as one of the epitopes to be used in future studies aimed at characterising the immune response of functionally important synthetic peptides which could be included in developing a synthetic anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Peptides; Cell Line, Tumor; Host-Pathogen Interactions; Protein Binding; Protein Structure, Secondary; Antigens, Bacterial; Epithelial Cells; Macrophages; Anti-Bacterial Agents; Bacterial Outer Membrane Proteins; BIOINFORMATICS; Cell Differentiation; CIRCULAR DICHROISM; Gene Expression; HIGH ACTIVITY BINDING PEPTIDE (HABP); INHIBITION ASSAY; Models, Molecular; RECEPTOR-LIGAND ASSAY; Transcription, Genetic

Towards designing a synthetic antituberculosis vaccine: The Rv3587c peptide inhibits mycobacterial entry to host cells - Carabali-Isajar, Mary Lilian; Ocampo, Marisol; Rodriguez, Deisy Carolina; Vanegas, Magnolia; Curtidor, Hernando; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Bioorganic & Medicinal Chemistry, 2018)
Mycobacterium tuberculosis is considered one of the most successful pathogens in the history of mankind, having caused 1.7 million deaths in 2016. The amount of resistant and extensively resistant strains has increased; BCG has been the only vaccine to be produced in more than 100 years though it is still unable to prevent the disease's most disseminated form in adults; pulmonary tuberculosis. The search is thus still on-going for candidate antigens for an antituberculosis vaccine. This paper reports the use of a logical and rational methodology for finding such antigens, this time as peptides derived from the Rv3587c membrane protein. Bioinformatics tools were used for predicting mycobacterial surface location and Rv3587c protein structure whilst circular dichroism was used for determining its peptides' secondary structure. Receptor-ligand assays identified 4 high activity binding peptides (HABPs) binding specifically to A549 alveolar epithelial cells and U937 monocyte-derived macrophages, covering the region between amino acids 116 and 193. Their capability for inhibiting Mtb H37Rv invasion was evaluated. The recognition of antibodies from individuals suffering active and latent tuberculosis and from healthy individuals was observed in HABPs capable of avoiding mycobacterial entry to host cells. The results showed that 8 HABPs inhibited such invasion, two of them being common for both cell lines: 39265 (155VLAAYVYSLDNKRLWSNLDT173) and 39266 (174APSNETLVKTFSPGEQVTTY192). Peptide 39265 was the least recognised by antibodies from the individuals' sera evaluated in each group. According to the model proposed by FIDIC regarding synthetic vaccine development, peptide 39265 has become a candidate antigen for an antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; Peptide Fragments; Tuberculosis Vaccines; Cell Line, Tumor; Computational Biology; Host-Pathogen Interactions; Protein Structure, Secondary; Antigens, Bacterial; HABPs; Bioinformatics; Drug Design; Invasion assay; Protein Structure, Tertiary; Receptors, Cell Surface; Rv3587c; Vaccine; Vaccines, Synthetic

Identifying and characterising PPE7 (Rv0354c) high activity binding peptides and their role in inhibiting cell invasion - Díaz, Diana P.; Ocampo, Marisol; Varela, Yahson; Curtidor, Hernando; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Molecular and Cellular Biochemistry, 2017)
This study was aimed at characterising the PPE7 protein from the PE/PPE protein family. The presence and transcription of the rv0354c gene in the Mycobacterium tuberculosis complex was determined and the subcellular localisation of the PPE7 protein on mycobacterial membrane was confirmed by immunoelectron microscope. Two peptides were identified as having high binding activity (HABPs) and were tested in vitro regarding the invasion of Mycobacterium tuberculosis H37Rv. HABP 39224 inhibited invasion in A549 epithelial cells and U937 macrophages by more than 50%, whilst HABP 39225 inhibited invasion by 40% in U937 cells. HABP 39224, located in the protein's C-terminal region, has a completely conserved amino acid sequence in M. tuberculosis complex species and could be selected as a base peptide when designing a subunit-based, anti-tuberculosis vaccine.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; U937 Cells; Tuberculosis Vaccines; A549 Cells; Cell Membrane; High activity binding peptide; Mycobacterium tuberculosis H37Rv; PPE7 protein; Synthetic peptide

Mce4F Mycobacterium tuberculosis protein peptides can inhibit invasion of human cell lines - Rodríguez, Deisy Carolina; Ocampo, Marisol; Varela, Yahson; Curtidor, Hernando; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Pathogens and Disease, 2015)
This work was aimed at studying the Mycobacterium tuberculosis H37Rv Rv3494c protein, taking into account that it belongs to the mammalian cell entry family (mce) which is thought to have important functions in the disease's pathogenesis. The protein was characterized in silico; its presence on mycobacterial surface was confirmed by immunoelectron microscopy. High-activity binding peptides (HABPs) were identified by binding assays with (125)I; their ability to inhibit mycobacterial entry to two cell lines (U937 alveolar macrophages and A549 epithelial cells) was ascertained and their role in bacterial entry was confirmed by fluorescent microsphere internalization assay. This protein's predicted alpha-helix structure was confirmed by circular dichroism of its peptides. All HABPs inhibited mycobacterial entry to cells and that the 38379 peptide ((201)IDQAGPFLQAQIRAGGDIKSY(220)) had high binding ability and inhibited the mycobacterial entry to both cell lines assayed here. Rv3494c peptides 38370 ((21)LSVMAIFYLRLPATFGIGTY(40)), 38373 ((81)HMRLNSGTAIPSNVTATVRSY(100)) and 38379 ((201)IDQAGPFLQAQIRAGGDIKSY(220)) showed to be HABP and inhibited mycobacterial entry to A549 cells and peptide 38382 ((261)RPSFPALAASLANLGRVGVIY(280)) bind to U937 and inhibited the mycobacterial entry to this cell line; all of these sequences play an important role in cell line recognition and invasion, and may thus be considered in the search for prophylactic candidates against tuberculosis.
Keywords: Cell Line; Circular Dichroism; Humans; Membrane Proteins; Mycobacterium tuberculosis; Microscopy, Immunoelectron; Protein Binding; Antigens, Bacterial; Epithelial Cells; Macrophages; Anti-Bacterial Agents; Mycobacterium tuberculosis H37Rv; Biological Products; Endocytosis; HABP; inhibition and invasion assay; Protein Conformation; Rv3494c protein; tuberculosis

Validating subcellular localization prediction tools with mycobacterial proteins - Restrepo-Montoya, Daniel; Vizcaíno, Carolina; Niño, Luis F.; Ocampo, Marisol; Patarroyo, Manuel E.; Patarroyo, Manuel A. (BMC bioinformatics, 2009)
BACKGROUND: The computational prediction of mycobacterial proteins' subcellular localization is of key importance for proteome annotation and for the identification of new drug targets and vaccine candidates. Several subcellular localization classifiers have been developed over the past few years, which have comprised both general localization and feature-based classifiers. Here, we have validated the ability of different bioinformatics approaches, through the use of SignalP 2.0, TatP 1.0, LipoP 1.0, Phobius, PA-SUB 2.5, PSORTb v.2.0.4 and Gpos-PLoc, to predict secreted bacterial proteins. These computational tools were compared in terms of sensitivity, specificity and Matthew's correlation coefficient (MCC) using a set of mycobacterial proteins having less than 40% identity, none of which are included in the training data sets of the validated tools and whose subcellular localization have been experimentally confirmed. These proteins belong to the TBpred training data set, a computational tool specifically designed to predict mycobacterial proteins. RESULTS: A final validation set of 272 mycobacterial proteins was obtained from the initial set of 852 mycobacterial proteins. According to the results of the validation metrics, all tools presented specificity above 0.90, while dispersion sensitivity and MCC values were above 0.22. PA-SUB 2.5 presented the highest values; however, these results might be biased due to the methodology used by this tool. PSORTb v.2.0.4 left 56 proteins out of the classification, while Gpos-PLoc left just one protein out. CONCLUSION: Both subcellular localization approaches had high predictive specificity and high recognition of true negatives for the tested data set. Among those tools whose predictions are not based on homology searches against SWISS-PROT, Gpos-PLoc was the general localization tool with the best predictive performance, while SignalP 2.0 was the best tool among the ones using a feature-based approach. Even though PA-SUB 2.5 presented the highest metrics, it should be taken into account that this tool was trained using all proteins reported in SWISS-PROT, which includes the protein set tested in this study, either as a BLAST search or as a training model.
Keywords: Bacterial Proteins; Computational Biology; Algorithms; Databases, Protein; Mycobacterium; Software

Rv1268c protein peptide inhibiting Mycobacterium tuberculosis H37Rv entry to target cells - Ocampo, Marisol; Rodríguez, Deisy Carolina; Rodríguez, Jorge; Bermúdez, Maritza; Muñoz, Claudia Marina; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Bioorganic & Medicinal Chemistry, 2013)
Tuberculosis (TB) remains one of the most worrying infectious diseases affecting public health around the world; 8.7 million new TB cases were reported in 2011. The search for an Mycobacterium tuberculosis H37Rv protein sequence which is functionally important in host-pathogen interaction has been proposed for developing a new vaccine which will allow efficient and safe control of the spread of this disease. The present study thus reports the results obtained for the Rv1268c protein described in the M. tuberculosis H37Rv genome as a hypothetical unknown, probably secreted, protein based on a highly robust, specific, sensitive and functional approach to the search for potential epitopes to be included in an anti-tuberculosis vaccine. Rv1268c presence was determined by immunoblotting after obtaining polyclonal sera against mycobacterial total sonicate or subcellular fractions. Such sera were used in electron immunomicroscopy (EIM) for confirming protein localisation on the M. tuberculosis envelop by recognising colloidal gold-labelled immunoglobulin. Screening assays revealed the presence of two sequences having high binding activity: one binding A549 alveolar epithelial cells ((141)TGMAALEQYLGSGHAVIVSI(160)) and other binding U937 monocyte-derived macrophages ((21)AVALGLASPADAAAGTMYGD(40)). Such sequences' ability to inhibit mycobacterial entry during in vitro assays was analysed. The structure of synthetic peptides binding to target cells was also determined, bearing in mind the structure-function relationship. These results, together with those obtained for other proteins, have been involved in selecting peptides which might be included in a subunit-based anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Circular Dichroism; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Peptides; Rabbits; Cell Line, Tumor; Host-Pathogen Interactions; Anti-tuberculosis vaccine; Entry inhibition; Gold; Immunoglobulins; Receptor–ligand interaction; Recombinant Proteins; Rv1268c; Sub-cellular localization; Synthetic peptides; Target cell

Mycobacterium tuberculosis PE9 protein has high activity binding peptides which inhibit target cell invasion - Díaz, Diana P.; Ocampo, Marisol; Pabón, Laura; Herrera, Chonny; Patarroyo, Manuel A.; Munoz, Marina; Patarroyo, Manuel E. (International Journal of Biological Macromolecules, 2016)
PE/PPE proteins are involved in several processes during Mycobacterium tuberculosis (Mtb) infection of target cells; studying them is extremely interesting as they are the only ones from the Mycobacterium genus, they abound in pathogenic species such as Mtb and their function remains yet unknown. The PE9 protein (Rv1088) was characterised, the rv1088 gene was identified by PCR in Mtb complex strains and its expression and localisation on mycobacterial surface was confirmed by Western blot and immunoelectron microscopy. Bioinformatics tools were used for predicting PE9 protein structural aspects and experimental study involved the circular dichroism of synthetic peptides. The peptides were tested in binding assays involving U937 and A549 cells; two high activity binding peptides (HABPs) were found for both cell lines (39226-(1)MSYMIATPAALTAAATDIDGI(21) and 39232-(125)YQRHFGTGGQPEFRQHSEHRR(144)), one for U937 (39231-(104)YAGAGRRQRRRRSGDGQWRLRQ(124)) and one for A549 (39230-(83)YGTGVFRRRRGRQTVTAAEHRA(103)). HABP 39232 inhibited mycobacterial entry to A549 cells (∼70%) and U937 cells (∼50%), peptides 39226 and 39231 inhibited entry to U937 cells (∼60% and 80%, respectively) and peptide 39230 inhibited entry to A549 cells (∼60%). This emphasised HABPs' functional importance in recognition between Mtb H37Rv and target cell receptors. These peptide sequences could be involved in invasion and were recognised by the host's immune system, thereby highlighting their use when designing an efficient anti-tuberculosis multiantigenic vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Mycobacterium tuberculosis; Peptides; Computational Biology; Protein Binding; Epithelial Cells; Macrophages; Tuberculosis; Models, Molecular; Transcription, Genetic; A549 Cells; Synthetic peptide; Protein Conformation; PE9 protein; Protein Transport; Substrate Specificity

The Mycobacterium tuberculosis membrane protein Rv0180c: Evaluation of peptide sequences implicated in mycobacterial invasion of two human cell lines - Cáceres, Silvia Marcela; Ocampo, Marisol; Arévalo-Pinzón, Gabriela; Jimenez, Ronald Andrés; Patarroyo, Manuel Elkin; Patarroyo, Manuel Alfonso (Peptides, 2011)
The identification and characterization of hypothetical membrane proteins from Mycobacterium tuberculosis have led to a better understanding of the mechanisms used by this pathogen to invade and survive inside host cells. This study assessed the presence, transcription, localization and possible biological activity of the conserved hypothetical protein Rv0180c from M. tuberculosis. Bioinformatics analyses indicated that Rv0180c contains a signal peptide, six possible transmembrane helices and a Plasmodium Export Element (PEXEL)-like motif. PCR analyses showed the presence of the Rv0180c gene in strains from the M. tuberculosis complex; but transcription was not detected in Mycobacterium microti. Sera against synthetic peptides of Rv0180c recognized two protein bands in M. tuberculosis H37Rv sonicate: a ∼48-kDa band close to the predicted molecular mass of Rv0180c (47.6 kDa), and a 63-kDa band probably caused by protein modifications. Moreover, the same sera located the protein on the surface of M. tuberculosis H37Rv bacilli by immunoelectron microscopy. Twenty-three synthetic peptides spanning the entire length of Rv0180c were tested for their ability to bind to U937 and A549 cells, finding nine high-activity binding peptides (HABPs) specific for both cell types, two HABPs specific for A549 cells (namely 31032 and 31044) and two HABPs specific for U937 cells (namely 31025 and 31041). HABPs inhibited invasion of M. tuberculosis H37Rv into A549 or U937 cells by significant percentages and facilitated internalization of latex beads in A549 cells. The Rv0180c HABPs herein reported could be preliminary candidates to be assessed as components of a multiepitope, chemically synthesized, subunit-based vaccine against tuberculosis.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Circular Dichroism; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Microscopy, Immunoelectron; Peptides; Transcription, Genetic

Mycobacterium tuberculosis surface protein Rv0227c contains high activity binding peptides which inhibit cell invasion - Rodríguez, Diana Marcela; Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel Elkin; Patarroyo, Manuel Alfonso (Peptides, 2012)
Mycobacterium tuberculosis surface proteins involved in target cell invasion may be identified as a strategy for developing subunit-based, chemically-synthesized vaccines. The Rv0227c protein was thus selected to assess its role in the invasion and infection of Mycobacterium tuberculosis target cells. Results revealed Rv0227c localization on mycobacterial surface by immunoelectron microscopy and Western blot. Receptor-ligand assays using 20-mer, non-overlapping peptides covering the complete Rv0227c protein sequence revealed three high activity binding peptides for U937 phagocytic cells and seven for A549 cells. Peptide 16944 significantly inhibited mycobacterial entry to both cell lines while 16943 and 16949 only managed to inhibit entrance to U937 cells and 16951 to A549 cells. The Jnet bioinformatics tool predicted secondary structure elements for the complete protein, agreeing with elements determined for such chemically-synthesized peptides. It was thus concluded that high activity binding peptides which were able to inhibit mycobacterial entry to target cells are of great importance when selecting peptide candidates for inclusion in an anti-tuberculosis vaccine.
Keywords: Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; U937 Cells; Microscopy, Immunoelectron; Peptides; Blotting, Western; Bacterial Vaccines; Cell Survival; Dose-Response Relationship, Drug; Reverse Transcriptase Polymerase Chain Reaction; Structure-Activity Relationship; Tumor Cells, Cultured

Computational prediction and experimental assessment of secreted/surface proteins from Mycobacterium tuberculosis H37Rv - Vizcaíno, Carolina; Restrepo-Montoya, Daniel; Rodríguez, Diana; Niño, Luis F.; Ocampo, Marisol; Vanegas, Magnolia; Reguero, María T.; Martínez, Nora L.; Patarroyo, Manuel E.; Patarroyo, Manuel A. (PLoS computational biology, 2010)
The mycobacterial cell envelope has been implicated in the pathogenicity of tuberculosis and therefore has been a prime target for the identification and characterization of surface proteins with potential application in drug and vaccine development. In this study, the genome of Mycobacterium tuberculosis H37Rv was screened using Machine Learning tools that included feature-based predictors, general localizers and transmembrane topology predictors to identify proteins that are potentially secreted to the surface of M. tuberculosis, or to the extracellular milieu through different secretory pathways. The subcellular localization of a set of 8 hypothetically secreted/surface candidate proteins was experimentally assessed by cellular fractionation and immunoelectron microscopy (IEM) to determine the reliability of the computational methodology proposed here, using 4 secreted/surface proteins with experimental confirmation as positive controls and 2 cytoplasmic proteins as negative controls. Subcellular fractionation and IEM studies provided evidence that the candidate proteins Rv0403c, Rv3630, Rv1022, Rv0835, Rv0361 and Rv0178 are secreted either to the mycobacterial surface or to the extracellular milieu. Surface localization was also confirmed for the positive controls, whereas negative controls were located on the cytoplasm. Based on statistical learning methods, we obtained computational subcellular localization predictions that were experimentally assessed and allowed us to construct a computational protocol with experimental support that allowed us to identify a new set of secreted/surface proteins as potential vaccine candidates.
Keywords: Antibodies, Bacterial; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Computational Biology; Epitopes, B-Lymphocyte; Bacterial Outer Membrane Proteins; Artificial Intelligence; Cell Fractionation; Electrophoresis, Polyacrylamide Gel; Escherichia coli; Immunoblotting; Models, Statistical; Mycobacterium smegmatis; Sonication; Subcellular Fractions

Peptides derived from the Mycobacterium tuberculosis Rv1490 surface protein implicated in inhibition of epithelial cell entry: potential vaccine candidates? - Patarroyo, Manuel A.; Curtidor, Hernando; Plaza, David F.; Ocampo, Marisol; Reyes, Claudia; Saboya, Obeimar; Barrera, Gloria; Patarroyo, Manuel E. (Vaccine, 2008)
This study reports the Rv1490 gene presence and transcription in members of the Mycobacterium tuberculosis complex, and characterises the encoded Rv1490 putative membrane protein in M. tuberculosis H37Rv. Rv1490 derived peptides were synthesised and their A549 and U937 cell binding ability was tested, finding five high activity binding peptides (HABPs) for A549 and five for U937. Only two HABPs (11060 and 11073) were shared by both cell lines, both of which affected M. tuberculosis' invading ability to target cells, thus indicating an important role for these sequences in M. tuberculosis entry to A549 alveolar epithelial cells and supporting their inclusion in further studies on the development of a subunit-based multi-epitopic, chemically synthesised anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Peptides; Rabbits; Protein Binding; Bacterial Adhesion; Epithelial Cells; Microscopy, Electron, Transmission

Peptides from the Mycobacterium tuberculosis Rv1980c protein involved in human cell infection: insights into new synthetic subunit vaccine candidates - Rodríguez, Diana; Vizcaíno, Carolina; Ocampo, Marisol; Curtidor, Hernando; Pinto, Marta; Elkin Patarroyo, Manuel; Alfonso Patarroyo, Manuel (Biological Chemistry, 2010)
Mycobacterium tuberculosis infection continues to be a major cause of morbidity and mortality throughout the world. The vast complexity of the intracellular pathogen M. tuberculosis and the diverse mechanisms by which it can invade host cells highlight the importance of developing a fully protective vaccine. Our vaccine development strategy consists of including fragments from multiple mycobacterial proteins involved in cell invasion. The aim of this study was to identify high activity binding peptides (HABPs) in the immunogenic protein Rv1980c from M. tuberculosis H37Rv with the ability to inhibit mycobacterial invasion into U937 monocyte-derived macrophages and A549 cells. The presence and transcription of the Rv1980c gene was assessed in members belonging to the M. tuberculosis complex and other nontuberculous mycobacteria by PCR and RT-PCR, respectively. Cell surface localization was confirmed by immuno-electron microscopy. Three peptides binding with high activity to U937 cells and one to A549 cells were identified. HABPs 31100, 31101, and 31107 inhibited invasion of M. tuberculosis into A549 and U937 cells and therefore could be promising candidates for the design of a subunit-based antituberculous vaccine.
Keywords: Bacterial Proteins; Binding Sites; Humans; Mycobacterium tuberculosis; Peptide Fragments; Blotting, Western; Models, Molecular; Transcription, Genetic; Vaccines, Synthetic; Bacterial Vaccines; Alveolar Epithelial Cells; Cells, Cultured

Identifying putative Mycobacterium tuberculosis Rv2004c protein sequences that bind specifically to U937 macrophages and A549 epithelial cells - Forero, Martha; Puentes, Alvaro; Cortés, Jimena; Castillo, Fabio; Vera, Ricardo; Rodríguez, Luis E.; Valbuena, John; Ocampo, Marisol; Curtidor, Hernando; Rosas, Jaiver; García, Javier; Barrera, Gloria; et al. (Protein Science: A Publication of the Protein Society, 2005)
Virulence and immunity are still poorly understood in Mycobacterium tuberculosis. The H37Rv M. tuberculosis laboratory strain genome has been completely sequenced, and this along with proteomic technology represent powerful tools contributing toward studying the biology of target cell interaction with a facultative bacillus and designing new strategies for controlling tuberculosis. Rv2004c is a putative M. tuberculosis protein that could have specific mycobacterial functions. This study has revealed that the encoding gene is present in all mycobacterium species belonging to the M. tuberculosis complex. Rv2004c gene transcription was observed in all of this complex's strains except Mycobacterium bovis and Mycobacterium microti. Rv2004c protein expression was confirmed by using antibodies able to recognize a 54-kDa molecule by immunoblotting, and its location was detected on the M. tuberculosis surface by transmission electron microscopy, suggesting that it is a mycobacterial surface protein. Binding assays led to recognizing high activity binding peptides (HABP); five HABPs specifically bound to U937 cells, and six specifically bound to A549 cells. HABP circular dichroism suggested that they had an alpha-helical structure. HABP-target cell interaction was determined to be specific and saturable; some of them also displayed greater affinity for A549 cells than U937 cells. The critical amino acids directly involved in their interaction with U937 cells were also determined. Two probable receptor molecules were found on U937 cells and five on A549 for the two HABPs analyzed. These observations have important biological significance for studying bacillus-target cell interactions and implications for developing strategies for controlling this disease.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Binding Sites; Cell Line; Circular Dichroism; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Peptides; Epithelial Cells; Macrophages; Receptors, Cell Surface; Reverse Transcriptase Polymerase Chain Reaction; Cell Wall; Sequence Analysis, Protein

The role of Mycobacterium tuberculosis Rv3166c protein-derived high-activity binding peptides in inhibiting invasion of human cell lines - Ocampo, Marisol; Aristizábal-Ramírez, Daniel; Rodríguez, Diana M.; Muñoz, Marina; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Protein engineering, design & selection: PEDS, 2012)
Given the urgent need for designing a new antituberculosis vaccine conferring total protection on patients of all ages, following the line of research adopted by our institute, this work has identified Mycobacterium tuberculosis (Mtb) Rv3166c protein high-activity binding peptides (HABPs) which are able to inhibit bacterial invasion of U937 (monocyte-derived macrophages) and A549 (type II alveolar epithelial cells) cell lines. The presence and transcription of the rv3166c gene in the Mtb species complex was confirmed by polymerase chain reaction (PCR) and reverse transcriptase-PCR; Rv3166c expression was evaluated by western blot and cellular localisation confirmed by immunoelectron microscopy. Its presence was mainly determined on cell surface. Sixteen peptides covering its entire length were chemically synthesised and tested for their ability to bind to U937 and A549 cells. Two U937 HABPs were identified and three for A549, one of them being shared by both cell lines. The four HABPs found inhibited Mtb entry by 15.07-94.06%. These results led us to including Rv3166c HABPs as candidates for further studies contributing towards the search for a multiepitope, chemically synthesised, subunit-based antituberculosis vaccine.
Keywords: Antibodies, Bacterial; Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; U937 Cells; Animals; Microscopy, Immunoelectron; Rabbits; Tuberculosis Vaccines; Macrophages; Pulmonary Alveoli

Peptides derived from Mycobacterium tuberculosis Rv2301 protein are involved in invasion to human epithelial cells and macrophages - Ocampo, M.; Rodríguez, D. M.; Curtidor, H.; Vanegas, M.; Patarroyo, M. A.; Patarroyo, M. E. (Amino Acids, 2012)
The specific function of putative cut2 protein (or CFP25), encoded by the Rv2301 gene from Mycobacterium tuberculosis H37Rv, has not been identified yet. The aim of this study was to assess some of CFP25 characteristics and its possible biological role in Mycobacterium tuberculosis H37Rv invasion process to target cells. Molecular assays indicated that the gene encoding Rv2301 is present and transcribed in M. tuberculosis complex strains. The presence of Rv2301 protein over the bacilli surface was confirmed by Western blot and immunoelectron microscopy analyses, using goats sera inoculated with synthetic peptides derived from Rv2301 protein. Receptor-ligand binding assays with carcinomic human alveolar basal epithelial cells (A549) and macrophages derived from human histolytic lymphoma monocytes (U937) allowed us to identify five high activity binding peptides (HABPs) in both cell lines, and two additional HABPs only in A549 cells. U937 HABPs binding interactions were characterized by saturation assays, finding dissociation constants (Kd) within the nanomolar range and positive cooperativity (nH>1). Inhibition assays were performed to assess the possible biological role of Rv2301 identified HABPs, finding that some of them were able to inhibit invasion at a 5 μM concentration, compared with the cytochalasin control. On the other hand, HABPs, and especially HABP 36507 located at the N-terminus of the protein, facilitated the internalization of fluorescent latex beads into A549 cells. These findings are of vital importance for the rational selection of Rv2301 HABPs, to be included as components of an antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Binding Sites; Humans; Kinetics; Molecular Sequence Data; Mycobacterium tuberculosis; Microscopy, Immunoelectron; Peptides; Cell Line, Tumor; Protein Binding; Antigens, Bacterial; Epithelial Cells; Macrophages; Blotting, Western; Cytochalasins; Organ Specificity; Tuberculosis, Pulmonary

Mycobacterium tuberculosis Rv2536 protein implicated in specific binding to human cell lines - García, Javier; Puentes, Alvaro; Rodríguez, Luis; Ocampo, Marisol; Curtidor, Hernando; Vera, Ricardo; Lopez, Ramses; Valbuena, John; Cortes, Jimena; Vanegas, Magnolia; Barrero, Carlos; Patarroyo, Manuel A.; et al. (Protein Science: A Publication of the Protein Society, 2005)
The gene encoding the Mycobacterium tuberculosis Rv2536 protein is present in the Mycobacterium tuberculosis complex (as assayed by PCR) and transcribed (as determined by RT-PCR) in M. tuberculosis H37Rv, M. tuberculosis H37Ra, M. bovis BCG, and M. africanum strains. Rabbits immunized with synthetic polymer peptides from this protein produced antibodies specifically recognizing a 25-kDa band in mycobacterial sonicate. U937 and A549 cells were used in binding assays involving 20-amino-acid-long synthetic peptides covering the whole Rv2536 protein sequence. Peptide 11207 (161DVFSAVRADDSPTGEMQVAQY180) presented high specific binding to both types of cells; the binding was saturable and presented nanomolar affinity constants. Cross-linking assays revealed that this peptide specifically binds to 50 kDa U937 cell membrane and 45 kDa A549 cell membrane proteins.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Cell Line; Circular Dichroism; Cross-Linking Reagents; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Animals; Rabbits; Gene Expression Regulation, Bacterial; Immune Sera

The Mycobacterium tuberculosis membrane protein Rv2560--biochemical and functional studies - Plaza, David F.; Curtidor, Hernando; Patarroyo, Manuel A.; Chapeton-Montes, Julie A.; Reyes, Claudia; Barreto, Jose; Patarroyo, Manuel E. (The FEBS journal, 2007)
The characterization of membrane proteins having no identified function in Mycobacterium tuberculosis is important for a better understanding of the biology of this pathogen. In this work, the biological activity of the Rv2560 protein was characterized and evaluated. Primers used in PCR and RT-PCR assays revealed that the gene encoding protein Rv2560 is present in M. tuberculosis complex strains, but transcribed in only some of them. Sera obtained from rabbits inoculated with polymer peptides from this protein recognized a 33 kDa band in the M. tuberculosis lysate and a membrane fraction corresponding to the predicted molecular mass (33.1 kDa) of this protein. Immunoelectron microscopy analysis found this protein on the mycobacterial membrane. Sixteen peptides covering its entire length were chemically synthesized and tested for their ability to bind to A549 and U937 cells. Peptide 11024 (121VVALSDRATTAYTNTSGVSS140) showed high specific binding to both cell types (dissociation constants of 380 and 800 nm, respectively, and positive receptor-ligand interaction cooperativity), whereas peptide 11033 (284LIGIPVAALIHVYTYRKLSGG304) displayed high binding activity to A549 cells only. Cross-linking assays showed the specific binding of peptide 11024 to a 54 kDa membrane protein on U937. Invasion inhibition assays, in the presence of shared high-activity binding peptide identified for U937 and A549 cells, presented maximum inhibition percentages of 50.53% and 58.27%, respectively. Our work highlights the relevance of the Rv2560 protein in the M. tuberculosis invasion process of monocytes and epithelial cells, and represents a fundamental step in the rational selection of new antigens to be included as components in a multiepitope, subunit-based, chemically synthesized, antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Circular Dichroism; DNA, Bacterial; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Animals; Microscopy, Immunoelectron; Rabbits; Cell Line, Tumor; Protein Binding; Blotting, Western; Sequence Analysis, Protein; Immune Sera; Flow Cytometry; Immunization; Polymerase Chain Reaction; Sequence Analysis, DNA; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

Characterizing the Mycobacterium tuberculosis Rv2707 protein and determining its sequences which specifically bind to two human cell lines - Chapeton-Montes, Julie A.; Plaza, David F.; Curtidor, Hernando; Forero, Martha; Vanegas, Magnolia; Patarroyo, Manuel E.; Patarroyo, Manuel A. (Protein Science: A Publication of the Protein Society, 2008)
The Rv2707 gene encoding a putative alanine- and leucine-rich protein was found to be present in all Mycobacterium tuberculosis complex strains (by PCR) and its transcription was shown by RT-PCR in all but M. bovis and M. microti. Antibodies raised against Rv2707 peptides specifically recognized the native protein by Western blot and were able to locate this protein on the M. tuberculosis membrane by immunoelectron microscopy. A549 and U937 cells lines were used in binding assays involving synthetic peptides covering the whole Rv2707 protein. High A549 cell-binding peptide 16083 (281 QEEWPAPATHAHRLGNWLKAY 300) was identified. Peptides 16072 (61 LFGPDTLPAIEKSALSTAHSY 80) and 16084 (301 RIGVGTTTYSSTAQHSAVAA 320) presented high specific binding to both A549 and U937 cells. Cross-linking assays revealed that peptide 16084 specifically bound to a 40-kDa and a 50-kDa U937 cell membrane protein. High activity binding peptides (HABPs) 16083 and 16084 were able to inhibit M. tuberculosis invasion of A549 cells. Our results suggest that these sequences could be part of the binding sites used by the bacillus for interacting with target cells, and thus represent good candidates to be tested in a future subunit-based, multiepitope, antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Peptide Fragments; U937 Cells; Microscopy, Immunoelectron; Cell Line, Tumor; Computational Biology; Protein Binding

Peptides derived from the Mycobacterium tuberculosis Rv1490 surface protein implicated in inhibition of epithelial cell entry: potential vaccine candidates? - Patarroyo, Manuel A.; Curtidor, Hernando; Plaza, David F.; Ocampo, Marisol; Reyes, Claudia; Saboya, Obeimar; Barrera, Gloria; Patarroyo, Manuel E. (Vaccine, 2008)
This study reports the Rv1490 gene presence and transcription in members of the Mycobacterium tuberculosis complex, and characterises the encoded Rv1490 putative membrane protein in M. tuberculosis H37Rv. Rv1490 derived peptides were synthesised and their A549 and U937 cell binding ability was tested, finding five high activity binding peptides (HABPs) for A549 and five for U937. Only two HABPs (11060 and 11073) were shared by both cell lines, both of which affected M. tuberculosis' invading ability to target cells, thus indicating an important role for these sequences in M. tuberculosis entry to A549 alveolar epithelial cells and supporting their inclusion in further studies on the development of a subunit-based multi-epitopic, chemically synthesised anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Peptides; Rabbits; Protein Binding; Bacterial Adhesion; Epithelial Cells; Microscopy, Electron, Transmission

Functional characterization of Mycobacterium tuberculosis Rv2969c membrane protein - Patarroyo, Manuel A.; Plaza, David F.; Ocampo, Marisol; Curtidor, Hernando; Forero, Martha; Rodriguez, Luis E.; Patarroyo, Manuel E. (Biochemical and Biophysical Research Communications, 2008)
Identifying Mycobacterium tuberculosis membrane proteins involved in binding to and invasion of host cells is important in designing subunit-based anti-tuberculosis vaccines. The Rv2969c gene sequence was identified by PCR in M. tuberculosis complex strains, being transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra, and M. bovis BCG. Rabbits immunized with synthetic peptides from highly specific conserved regions of this protein produced antibodies recognizing 27 and 29 kDa bands in M. tuberculosis lysate, which is consistent with the molecular weight of the Rv2969c gene product in M. tuberculosis H37Rv. Immunoelectron microscopy revealed the protein was localized on the bacillus surface. Four and three specific high activity binding peptides (HABPs) to the A549 alveolar epithelial and U937 monocyte cell lines were found, respectively. Two of the HABPs found inhibited M. tuberculosis invasion of A549 cells, suggesting that these peptides might be good candidates to be included in a multiepitopic, subunit-based anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Cell Line; Genes, Bacterial; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Tuberculosis Vaccines

The Mycobacterium tuberculosis membrane protein Rv0180c: Evaluation of peptide sequences implicated in mycobacterial invasion of two human cell lines - Cáceres, Silvia Marcela; Ocampo, Marisol; Arévalo-Pinzón, Gabriela; Jimenez, Ronald Andrés; Patarroyo, Manuel Elkin; Patarroyo, Manuel Alfonso (Peptides, 2011)
The identification and characterization of hypothetical membrane proteins from Mycobacterium tuberculosis have led to a better understanding of the mechanisms used by this pathogen to invade and survive inside host cells. This study assessed the presence, transcription, localization and possible biological activity of the conserved hypothetical protein Rv0180c from M. tuberculosis. Bioinformatics analyses indicated that Rv0180c contains a signal peptide, six possible transmembrane helices and a Plasmodium Export Element (PEXEL)-like motif. PCR analyses showed the presence of the Rv0180c gene in strains from the M. tuberculosis complex; but transcription was not detected in Mycobacterium microti. Sera against synthetic peptides of Rv0180c recognized two protein bands in M. tuberculosis H37Rv sonicate: a ∼48-kDa band close to the predicted molecular mass of Rv0180c (47.6 kDa), and a 63-kDa band probably caused by protein modifications. Moreover, the same sera located the protein on the surface of M. tuberculosis H37Rv bacilli by immunoelectron microscopy. Twenty-three synthetic peptides spanning the entire length of Rv0180c were tested for their ability to bind to U937 and A549 cells, finding nine high-activity binding peptides (HABPs) specific for both cell types, two HABPs specific for A549 cells (namely 31032 and 31044) and two HABPs specific for U937 cells (namely 31025 and 31041). HABPs inhibited invasion of M. tuberculosis H37Rv into A549 or U937 cells by significant percentages and facilitated internalization of latex beads in A549 cells. The Rv0180c HABPs herein reported could be preliminary candidates to be assessed as components of a multiepitope, chemically synthesized, subunit-based vaccine against tuberculosis.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Circular Dichroism; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Microscopy, Immunoelectron; Peptides; Transcription, Genetic

Specific interaction between Mycobacterium tuberculosis lipoprotein-derived peptides and target cells inhibits mycobacterial entry in vitro - Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Chemical Biology & Drug Design, 2014)
Tuberculosis (TB) continues being one of the diseases having the greatest mortality rates around the world, 8.7 million cases having been reported in 2011. An efficient vaccine against TB having a great impact on public health is an urgent need. Usually, selecting antigens for vaccines has been based on proteins having immunogenic properties for patients suffering TB and having had promising results in mice and non-human primates. Our approach has been based on a functional approach involving the pathogen-host interaction in the search for antigens to be included in designing an efficient, minimal, subunit-based anti-TB vaccine. This means that Mycobacterium tuberculosis has mainly been involved in studies and that lipoproteins represent an important kind of protein on the cell envelope which can also contribute towards this pathogen's virulence. This study has assessed the expression of four lipoproteins from M. tuberculosis H37Rv, that is, Rv1411c (LprG), Rv1911c (LppC), Rv2270 (LppN) and Rv3763 (LpqH), and the possible biological activity of peptides derived from these. Five peptides were found for these proteins which had high specific binding to both alveolar A549 epithelial cells and U937 monocyte-derived macrophages which were able to significantly inhibit mycobacterial entry to these cells in vitro.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Peptides; Antibodies; antituberculosis vaccine; Cell Line, Tumor; Computational Biology; high activity binding peptide; Host-Pathogen Interactions; Lipoproteins; Microspheres; multi-epitope vaccine; Protein Binding; Protein Structure, Secondary; synthetic peptide

Mycobacterium tuberculosis H37Rv LpqG Protein Peptides Can Inhibit Mycobacterial Entry through Specific Interactions - Sánchez-Barinas, Christian David; Ocampo, Marisol; Vanegas, Magnolia; Castañeda-Ramirez, Jeimmy Johana; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Molecules (Basel, Switzerland), 2018)
Mycobacterium tuberculosis is the causative agent of tuberculosis, a disease causing major mortality worldwide. As part of a systematic methodology for studying M. tuberculosis surface proteins which might be involved in host-pathogen interactions, our group found that LpqG surface protein (Rv3623) found in M. tuberculosis complex strains was located on the mycobacterial envelope and that peptide 16661 (21SGCDSHNSGSLGADPRQVTVY40) had high specific binding to U937 monocyte-derived macrophages and inhibited mycobacterial entry to such cells in a concentration-dependent way. A region having high specific binding to A549 alveolar epithelial cells was found which had low mycobacterial entry inhibition. As suggested in previous studies, relevant sequences in the host-pathogen interaction do not induce an immune response and peptides characterised as HABPs are poorly recognised by sera from individuals regardless of whether they have been in contact with M. tuberculosis. Our approach to designing a synthetic, multi-epitope anti-tuberculosis vaccine has been based on identifying sequences involved in different proteins' mycobacteria-target cell interaction and modifying their sequence to improve their immunogenic characteristics, meaning that peptide 16661 sequence should be considered in such design.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Mycobacterium tuberculosis; Peptide Fragments; Cell Line, Tumor; Computational Biology; Protein Binding; synthetic peptide; Macrophages; Models, Molecular; Transcription, Genetic; Protein Conformation; Gene Expression Regulation, Bacterial; Antitubercular Agents; lipoprotein; LpqG; mycobacterial entry inhibition; Rv3623; vaccine

Peptides from the Mycobacterium tuberculosis Rv1980c protein involved in human cell infection: insights into new synthetic subunit vaccine candidates - Rodríguez, Diana; Vizcaíno, Carolina; Ocampo, Marisol; Curtidor, Hernando; Pinto, Marta; Elkin Patarroyo, Manuel; Alfonso Patarroyo, Manuel (Biological Chemistry, 2010)
Mycobacterium tuberculosis infection continues to be a major cause of morbidity and mortality throughout the world. The vast complexity of the intracellular pathogen M. tuberculosis and the diverse mechanisms by which it can invade host cells highlight the importance of developing a fully protective vaccine. Our vaccine development strategy consists of including fragments from multiple mycobacterial proteins involved in cell invasion. The aim of this study was to identify high activity binding peptides (HABPs) in the immunogenic protein Rv1980c from M. tuberculosis H37Rv with the ability to inhibit mycobacterial invasion into U937 monocyte-derived macrophages and A549 cells. The presence and transcription of the Rv1980c gene was assessed in members belonging to the M. tuberculosis complex and other nontuberculous mycobacteria by PCR and RT-PCR, respectively. Cell surface localization was confirmed by immuno-electron microscopy. Three peptides binding with high activity to U937 cells and one to A549 cells were identified. HABPs 31100, 31101, and 31107 inhibited invasion of M. tuberculosis into A549 and U937 cells and therefore could be promising candidates for the design of a subunit-based antituberculous vaccine.
Keywords: Bacterial Proteins; Binding Sites; Humans; Mycobacterium tuberculosis; Peptide Fragments; Blotting, Western; Models, Molecular; Transcription, Genetic; Vaccines, Synthetic; Bacterial Vaccines; Alveolar Epithelial Cells; Cells, Cultured

Mycobacterium tuberculosis H37Rv LpqG Protein Peptides Can Inhibit Mycobacterial Entry through Specific Interactions - Sánchez-Barinas, Christian David; Ocampo, Marisol; Vanegas, Magnolia; Castañeda-Ramirez, Jeimmy Johana; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Molecules (Basel, Switzerland), 2018)
Mycobacterium tuberculosis is the causative agent of tuberculosis, a disease causing major mortality worldwide. As part of a systematic methodology for studying M. tuberculosis surface proteins which might be involved in host-pathogen interactions, our group found that LpqG surface protein (Rv3623) found in M. tuberculosis complex strains was located on the mycobacterial envelope and that peptide 16661 (21SGCDSHNSGSLGADPRQVTVY40) had high specific binding to U937 monocyte-derived macrophages and inhibited mycobacterial entry to such cells in a concentration-dependent way. A region having high specific binding to A549 alveolar epithelial cells was found which had low mycobacterial entry inhibition. As suggested in previous studies, relevant sequences in the host-pathogen interaction do not induce an immune response and peptides characterised as HABPs are poorly recognised by sera from individuals regardless of whether they have been in contact with M. tuberculosis. Our approach to designing a synthetic, multi-epitope anti-tuberculosis vaccine has been based on identifying sequences involved in different proteins' mycobacteria-target cell interaction and modifying their sequence to improve their immunogenic characteristics, meaning that peptide 16661 sequence should be considered in such design.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Mycobacterium tuberculosis; Peptide Fragments; Cell Line, Tumor; Computational Biology; Protein Binding; synthetic peptide; Macrophages; Models, Molecular; Transcription, Genetic; Protein Conformation; Gene Expression Regulation, Bacterial; Antitubercular Agents; lipoprotein; LpqG; mycobacterial entry inhibition; Rv3623; vaccine

Characterising Mycobacterium tuberculosis Rv1510c protein and determining its sequences that specifically bind to two target cell lines - Vera-Bravo, Ricardo; Torres, Elizabeth; Valbuena, John J.; Ocampo, Marisol; Rodríguez, Luis E.; Puentes, Alvaro; García, Javier E.; Curtidor, Hernando; Cortés, Jimena; Vanegas, Magnolia; Rivera, Zuly J.; Díaz, Andrea; et al. (Biochemical and Biophysical Research Communications, 2005)
The process of Mycobacterium tuberculosis infection of the macrophage implies a very little-known initial recognition and adherence step, important for mycobacterial survival; many proteins even remain like hypothetical. The Rv1510c gene, encoding a putatively conserved membrane protein, was investigated by analysing the M. tuberculosis genome sequence data reported by Cole et al. and a previous report that used PCR assays to show that the Rv1510 gene was only present in M. tuberculosis. This article confirmed all the above and identified the transcribed gene in M. tuberculosis, Mycobacterium africanum, and in M. tuberculosis clinical isolates. Antibodies raised against peptides from this protein recognised a 44 kDa band, corresponding to Rv1510c theoretical mass (44,294 Da). Assays involving synthetic peptides covering the whole protein binding to U937 and A549 cell lines led to recognising five high activity binding peptides in the Rv1510 protein: 11094, 11095, 11105, 11108, and 11111. Their affinity constants and Hill coefficients were determined by using U937 cells. Cross-linking assays performed with some of these HABPs showed that they specifically bound to a U937 cell line 51 kDa protein, but not to Hep G2 or red blood cell proteins, showing this interaction's specificity.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Base Sequence; Binding Sites; Cell Line; Circular Dichroism; Cross-Linking Reagents; DNA, Bacterial; Genes, Bacterial; Humans; Kinetics; Membrane Proteins; Molecular Sequence Data; Molecular Weight; Mycobacterium tuberculosis; Peptide Fragments; U937 Cells

A review of preclinical animal models utilised for TB vaccine evaluation in the context of recent human efficacy data - McShane, Helen; Williams, Ann (Tuberculosis (Edinburgh, Scotland), 2014)
There is an urgent need for an improved TB vaccine. Vaccine development is hindered by the lack of immune correlates and uncertain predictive value of preclinical animal models. As data become available from human efficacy trials, there is an opportunity to evaluate the predictive value of the criteria used to select candidate vaccines. Here we review the efficacy in animal models of the MVA85A candidate vaccine in light of recent human efficacy data and propose refinements to the preclinical models with the aim of increasing their predictive value for human efficacy.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Drug Design; Vaccine; BCG Vaccine; Cattle; Clinical; Drug Evaluation, Preclinical; Efficacy; Guinea Pigs; Mice; Models, Animal; MVA85A; Practice Guidelines as Topic; Pre-clinical; Primates; Vaccines, DNA

Mouse models of human TB pathology: roles in the analysis of necrosis and the development of host-directed therapies - Kramnik, Igor; Beamer, Gillian (Seminars in Immunopathology, 2016)
A key aspect of TB pathogenesis that maintains Mycobacterium tuberculosis in the human population is the ability to cause necrosis in pulmonary lesions. As co-evolution shaped M . tuberculosis (M.tb) and human responses, the complete TB disease profile and lesion manifestation are not fully reproduced by any animal model. However, animal models are absolutely critical to understand how infection with virulent M.tb generates outcomes necessary for the pathogen transmission and evolutionary success. In humans, a wide spectrum of TB outcomes has been recognized based on clinical and epidemiological data. In mice, there is clear genetic basis for susceptibility. Although the spectra of human and mouse TB do not completely overlap, comparison of human TB with mouse lesions across genetically diverse strains firmly establishes points of convergence. By embracing the genetic heterogeneity of the mouse population, we gain tremendous advantage in the quest for suitable in vivo models. Below, we review genetically defined mouse models that recapitulate a key element of M.tb pathogenesis-induction of necrotic TB lesions in the lungs-and discuss how these models may reflect TB stratification and pathogenesis in humans. The approach ensures that roles that mouse models play in basic and translational TB research will continue to increase allowing researchers to address fundamental questions of TB pathogenesis and bacterial physiology in vivo using this well-defined, reproducible, and cost-efficient system. Combination of the new generation mouse models with advanced imaging technologies will also allow rapid and inexpensive assessment of experimental vaccines and therapies prior to testing in larger animals and clinical trials.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Antitubercular Agents; Mice; Animal models; Disease Models, Animal; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Granuloma; Host-directed therapies; Inbred mice; Mechanisms; Necrosis; Neutrophils; Receptors, Somatostatin; sst1

Replacing, reducing and refining the use of animals in tuberculosis vaccine research - Tanner, Rachel; McShane, Helen (ALTEX, 2017)
Tuberculosis (TB) remains a serious global health threat and an improved vaccine is urgently needed. New candidate TB vaccines are tested using preclinical animal models such as mice, guinea pigs, cattle and non-human primates. Animals are routinely infected with virulent Mycobacterium tuberculosis (Mtb) in challenge experiments to evaluate protective efficacy, raising ethical issues regarding the procedure of infection itself, symptoms of disease and humane end-points. We summarize the importance and limitations of animal models in TB vaccine research and review current alternatives and modifications in the context of the NC3Rs framework for replacing, reducing and refining the use of animals for scientific purposes.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; vaccine; BCG Vaccine; Cattle; Guinea Pigs; Mice; Primates; Disease Models, Animal; 3Rs; animal models; Animal Testing Alternatives; Mtb challenge; Research

Beijing sublineages of Mycobacterium tuberculosis differ in pathogenicity in the guinea pig - Kato-Maeda, Midori; Shanley, Crystal A.; Ackart, David; Jarlsberg, Leah G.; Shang, Shaobin; Obregon-Henao, Andres; Harton, Marisabel; Basaraba, Randall J.; Henao-Tamayo, Marcela; Barrozo, Joyce C.; Rose, Jordan; Kawamura, L. Masae; et al. (Clinical and vaccine immunology: CVI, 2012)
The Beijing family of Mycobacterium tuberculosis strains is part of lineage 2 (also known as the East Asian lineage). In clinical studies, we have observed that isolates from the sublineage RD207 of lineage 2 were more readily transmitted among humans. To investigate the basis for this difference, we tested representative strains with the characteristic Beijing spoligotype from four of the five sublineages of lineage 2 in the guinea pig model and subjected these strains to comparative whole-genome sequencing. The results of these studies showed that all of the clinical strains were capable of growing and causing lung pathology in guinea pigs after low-dose aerosol exposure. Differences between the abilities of the four sublineages to grow in the lungs of these animals were not overt, but members of RD207 were significantly more pathogenic, resulting in severe lung damage. The RD207 strains also induced much higher levels of markers associated with regulatory T cells and showed a significant loss of activated T cells in the lungs over the course of the infections. Whole-genome sequencing of the strains revealed mutations specific for RD207 which may explain this difference. Based on these data, we hypothesize that the sublineages of M. tuberculosis are associated with distinct pathological and clinical phenotypes and that these differences influence the transmissibility of particular M. tuberculosis strains in human populations.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Sequence Analysis, DNA; Guinea Pigs; Disease Models, Animal; Female; Genome, Bacterial; Genotype; Histocytochemistry; Lung; Molecular Typing; Virulence

The guinea pig as a model of infectious diseases - Padilla-Carlin, Danielle J.; McMurray, David N.; Hickey, Anthony J. (Comparative Medicine, 2008)
The words 'guinea pig' are synonymous with scientific experimentation, but much less is known about this species than many other laboratory animals. This animal model has been used for approximately 200 y and was the first to be used in the study of infectious diseases such as tuberculosis and diphtheria. Today the guinea pig is used as a model for a number of infectious bacterial diseases, including pulmonary, sexually transmitted, ocular and aural, gastrointestinal, and other infections that threaten the lives of humans. Most studies on the immune response to these diseases, with potential therapies and vaccines, have been conducted in animal models (for example, mouse) that may have less similarity to humans because of the large number of immunologic reagents available for these other species. This review presents some of the diseases for which the guinea pig is regarded as the premier model to study infections because of its similarity to humans with regard to symptoms and immune response. Furthermore, for diseases in which guinea pigs share parallel pathogenesis of disease with humans, they are potentially the best animal model for designing treatments and vaccines. Future studies of immune regulation of these diseases, novel therapies, and preventative measures require the development of new immunologic reagents designed specifically for the guinea pig.
Keywords: Humans; Animals; Guinea Pigs; Disease Models, Animal; Communicable Diseases

Animal Models of Tuberculosis: Guinea Pigs - Clark, Simon; Hall, Yper; Williams, Ann (Cold Spring Harbor Perspectives in Medicine, 2015)
The progression of the disease that follows infection of guinea pigs with Mycobacterium tuberculosis displays many features of human tuberculosis (TB), and the guinea pig model of TB has been used for more than 100 years as a research tool to understand and describe disease mechanisms. Changes in the bacterial burden and pathology following infection can be readily monitored and used to evaluate the impact of TB interventions. Demonstration of the protective efficacy of vaccines in the low-dose aerosol guinea pig model is an important component of the preclinical data package for novel vaccines in development, and there is a continual need to improve the model to facilitate progression of vaccines to the clinic. Development of better tools with which to dissect the immune responses of guinea pigs is a focus of current research., Guinea pigs have been used for more than 100 years in tuberculosis research and display many characteristics of the human disease. They continue to play an important role in the development of new drugs and vaccines.

Testing the H56 Vaccine Delivered in 4 Different Adjuvants as a BCG-Booster in a Non-Human Primate Model of Tuberculosis - Billeskov, Rolf; Tan, Esterlina V.; Cang, Marjorie; Abalos, Rodolfo M.; Burgos, Jasmin; Pedersen, Bo Vestergaard; Christensen, Dennis; Agger, Else Marie; Andersen, Peter (PloS One, 2016)
The search for new and improved tuberculosis (TB) vaccines has focused on IFN-γ both for selecting antigens and for evaluating vaccine delivery strategies. The essential role of IFN-γ in endogenous host protection is well established, but it is still uncertain whether this also holds true for vaccine protection. Here we evaluate the H56 fusion protein vaccine as a BCG booster in a non-human primate (NHP) model of TB that closely recapitulates human TB pathogenesis. To date, only a handful of novel adjuvants have been tested in the NHP model of TB, and therefore we administered H56 in 3 novel cationic liposome adjuvants of increasing immunogenicity (CAF01, CAF04, CAF05) and compared them to H56 in the IC31® adjuvant previously reported to promote protection in this model. The individual clinical parameters monitored during infection (weight, ESR, X-ray) all correlated with survival, and boosting BCG with H56 in all adjuvants resulted in better survival rates compared to BCG alone. The adjuvants promoted IFN-γ-responses of increasing intensity as measured by ELISPOT in the peripheral blood, but the level of vaccine-specific IFN-γ production did not correlate with or predict disease outcome. This study's main outcome underscores the importance of the choice of adjuvant for TB subunit vaccines, and secondly it highlights the need for better correlates of protection in preclinical models of TB.
Keywords: Animals; Tuberculosis; BCG Vaccine; Disease Models, Animal; Adjuvants, Immunologic; Immunization, Secondary; Interferon-gamma; Macaca fascicularis; Recombinant Fusion Proteins; Survival Analysis

Immunology studies in non-human primate models of tuberculosis - Flynn, JoAnne L.; Gideon, Hannah P.; Mattila, Joshua T.; Lin, Philana Ling (Immunological Reviews, 2015)
Non-human primates, primarily macaques, have been used to study tuberculosis for decades. However, in the last 15 years, this model has been refined substantially to allow careful investigations of the immune response and host-pathogen interactions in Mycobacterium tuberculosis infection. Low-dose challenge with fully virulent strains in cynomolgus macaques result in the full clinical spectrum seen in humans, including latent and active infection. Reagents from humans are usually cross-reactive with macaques, further facilitating the use of this model system to study tuberculosis. Finally, macaques develop the spectrum of granuloma types seen in humans, providing a unique opportunity to investigate bacterial and host factors at the local (lung and lymph node) level. Here, we review the past decade of immunology and pathology studies in macaque models of tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; tuberculosis; Primates; Disease Models, Animal; Granuloma; Adaptive Immunity; Cytokines; granuloma; Immunity, Innate; immunology; Immunomodulation; lymph node; Lymph Nodes; Macaca; macaque; non-human primate; Patient Outcome Assessment; Positron-Emission Tomography; T-Lymphocyte Subsets; Tomography, X-Ray Computed

Computational and Empirical Studies Predict Mycobacterium tuberculosis-Specific T Cells as a Biomarker for Infection Outcome - Marino, Simeone; Gideon, Hannah P.; Gong, Chang; Mankad, Shawn; McCrone, John T.; Lin, Philana Ling; Linderman, Jennifer J.; Flynn, JoAnne L.; Kirschner, Denise E. (PLoS computational biology, 2016)
Identifying biomarkers for tuberculosis (TB) is an ongoing challenge in developing immunological correlates of infection outcome and protection. Biomarker discovery is also necessary for aiding design and testing of new treatments and vaccines. To effectively predict biomarkers for infection progression in any disease, including TB, large amounts of experimental data are required to reach statistical power and make accurate predictions. We took a two-pronged approach using both experimental and computational modeling to address this problem. We first collected 200 blood samples over a 2- year period from 28 non-human primates (NHP) infected with a low dose of Mycobacterium tuberculosis. We identified T cells and the cytokines that they were producing (single and multiple) from each sample along with monkey status and infection progression data. Machine learning techniques were used to interrogate the experimental NHP datasets without identifying any potential TB biomarker. In parallel, we used our extensive novel NHP datasets to build and calibrate a multi-organ computational model that combines what is occurring at the site of infection (e.g., lung) at a single granuloma scale with blood level readouts that can be tracked in monkeys and humans. We then generated a large in silico repository of in silico granulomas coupled to lymph node and blood dynamics and developed an in silico tool to scale granuloma level results to a full host scale to identify what best predicts Mycobacterium tuberculosis (Mtb) infection outcomes. The analysis of in silico blood measures identifies Mtb-specific frequencies of effector T cell phenotypes at various time points post infection as promising indicators of infection outcome. We emphasize that pairing wetlab and computational approaches holds great promise to accelerate TB biomarker discovery.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Computational Biology; Algorithms; Tuberculosis, Pulmonary; Lung; Macaca fascicularis; Cytokines; Biomarkers; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Computer Simulation; Databases, Factual; Models, Immunological; T-Lymphocytes

Non-Human Primate Models of Tuberculosis - Peña, Juliet C.; Ho, Wen-Zhe (Microbiology Spectrum, 2016)
Among the animal models of tuberculosis (TB), the non-human primates, particularly rhesus macaques (Macaca fascicularis) and cynomolgus macaques (Macaca mulatta), share the greatest anatomical and physiological similarities with humans. Macaques are highly susceptible to Mycobacterium tuberculosis infection and manifest the complete spectrum of clinical and pathological manifestations of TB as seen in humans. Therefore, the macaque models have been used extensively for investigating the pathogenesis of M. tuberculosis infection and for preclinical testing of drugs and vaccines against TB. This review focuses on published major studies that exemplify how the rhesus and cynomolgus macaques have enhanced and may continue to advance global efforts in TB research.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; Antitubercular Agents; Drug Evaluation, Preclinical; Disease Models, Animal; Macaca fascicularis; Macaca mulatta

Non-tuberculous mycobacteria have diverse effects on BCG efficacy against Mycobacterium tuberculosis - Poyntz, Hazel C.; Stylianou, Elena; Griffiths, Kristin L.; Marsay, Leanne; Checkley, Anna M.; McShane, Helen (Tuberculosis (Edinburgh, Scotland), 2014)
The efficacy of Bacillus Calmette-Guerin (BCG) vaccination in protection against pulmonary tuberculosis (TB) is highly variable between populations. One possible explanation for this variability is increased exposure of certain populations to non-tuberculous mycobacteria (NTM). This study used a murine model to determine the effect that exposure to NTM after BCG vaccination had on the efficacy of BCG against aerosol Mycobacterium tuberculosis challenge. The effects of administering live Mycobacterium avium (MA) by an oral route and killed MA by a systemic route on BCG-induced protection were evaluated. CD4+ and CD8+ T cell responses were profiled to define the immunological mechanisms underlying any effect on BCG efficacy. BCG efficacy was enhanced by exposure to killed MA administered by a systemic route; T helper 1 and T helper 17 responses were associated with increased protection. BCG efficacy was reduced by exposure to live MA administered by the oral route; T helper 2 cells were associated with reduced protection. These findings demonstrate that exposure to NTM can induce opposite effects on BCG efficacy depending on route of exposure and viability of NTM. A reproducible model of NTM exposure would be valuable in the evaluation of novel TB vaccine candidates.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Tuberculosis, Pulmonary; BCG Vaccine; Female; Adjuvants, Immunologic; Cytokines; Lymph Nodes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Administration, Inhalation; Administration, Oral; Aerosols; Bacillus Calmette-Geurin; Immunity, Cellular; Mice, Inbred C57BL; Mouse model; Mycobacterium avium; Mycobacterium avium Complex; Non-tuberculous mycobacteria; Spleen; Th1 Cells; Vaccines, Attenuated; Vaccines, Live, Unattenuated

Development of a murine mycobacterial growth inhibition assay for evaluating vaccines against Mycobacterium tuberculosis - Parra, Marcela; Yang, Amy L.; Lim, JaeHyun; Kolibab, Kristopher; Derrick, Steven; Cadieux, Nathalie; Perera, Liyanage P.; Jacobs, William R.; Brennan, Michael; Morris, Sheldon L. (Clinical and vaccine immunology: CVI, 2009)
The development and characterization of new tuberculosis (TB) vaccines has been impeded by the lack of reproducible and reliable in vitro assays for measuring vaccine activity. In this study, we developed a murine in vitro mycobacterial growth inhibition assay for evaluating TB vaccines that directly assesses the capacity of immune splenocytes to control the growth of Mycobacterium tuberculosis within infected macrophages. Using this in vitro assay, protective immune responses induced by immunization with five different types of TB vaccine preparations (Mycobacterium bovis BCG, an attenuated M. tuberculosis mutant strain, a DNA vaccine, a modified vaccinia virus strain Ankara [MVA] construct expressing four TB antigens, and a TB fusion protein formulated in adjuvant) can be detected. Importantly, the levels of vaccine-induced mycobacterial growth-inhibitory responses seen in vitro after 1 week of coculture correlated with the protective immune responses detected in vivo at 28 days postchallenge in a mouse model of pulmonary tuberculosis. In addition, similar patterns of cytokine expression were evoked at day 7 of the in vitro culture by immune splenocytes taken from animals immunized with the different TB vaccines. Among the consistently upregulated cytokines detected in the immune cocultures are gamma interferon, growth differentiation factor 15, interleukin-21 (IL-21), IL-27, and tumor necrosis factor alpha. Overall, we have developed an in vitro functional assay that may be useful for screening and comparing new TB vaccine preparations, investigating vaccine-induced protective mechanisms, and assessing manufacturing issues, including product potency and stability.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Macrophages; Tuberculosis; Mice; Cytokines; Coculture Techniques; Leukocytes, Mononuclear

Human isotype-dependent inhibitory antibody responses against Mycobacterium tuberculosis - Zimmermann, Natalie; Thormann, Verena; Hu, Bo; Köhler, Anne-Britta; Imai-Matsushima, Aki; Locht, Camille; Arnett, Eusondia; Schlesinger, Larry S.; Zoller, Thomas; Schürmann, Mariana; Kaufmann, Stefan He; Wardemann, Hedda (EMBO molecular medicine, 2016)
Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B-cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB-exposed healthcare workers. The data suggest that the acute plasmablast response to MTB originates from reactivated memory B cells and indicates a mucosal origin. Through functional analyses, we identified MTB inhibitory antibodies against mycobacterial antigens including virulence factors that play important roles in host cell infection. The inhibitory activity of anti-MTB antibodies was directly linked to their isotype. Monoclonal as well as purified serum IgA antibodies showed MTB blocking activity independently of Fc alpha receptor expression, whereas IgG antibodies promoted the host cell infection. Together, the data provide molecular insights into the human antibody response to MTB and may thereby facilitate the design of protective vaccination strategies.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; antibodies; Antibodies, Monoclonal; Antibody Formation; B cells; B-Lymphocytes; Immunoglobulin Isotypes; infection; isotype

A Functional Role for Antibodies in Tuberculosis - Lu, Lenette L.; Chung, Amy W.; Rosebrock, Tracy R.; Ghebremichael, Musie; Yu, Wen Han; Grace, Patricia S.; Schoen, Matthew K.; Tafesse, Fikadu; Martin, Constance; Leung, Vivian; Mahan, Alison E.; Sips, Magdalena; et al. (Cell, 2016)
While a third of the world carries the burden of tuberculosis, disease control has been hindered by a lack of tools, including a rapid, point-of-care diagnostic and a protective vaccine. In many infectious diseases, antibodies (Abs) are powerful biomarkers and important immune mediators. However, in Mycobacterium tuberculosis (Mtb) infection, a discriminatory or protective role for humoral immunity remains unclear. Using an unbiased antibody profiling approach, we show that individuals with latent tuberculosis infection (Ltb) and active tuberculosis disease (Atb) have distinct Mtb-specific humoral responses, such that Ltb infection is associated with unique Ab Fc functional profiles, selective binding to FcγRIII, and distinct Ab glycosylation patterns. Moreover, compared to Abs from Atb, Abs from Ltb drove enhanced phagolysosomal maturation, inflammasome activation, and, most importantly, macrophage killing of intracellular Mtb. Combined, these data point to a potential role for Fc-mediated Ab effector functions, tuned via differential glycosylation, in Mtb control.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; tuberculosis; Female; antibodies; Adult; Fc-receptors; Glycosylation; Immunity, Humoral; Immunoglobulin Fc Fragments; inflammasome; innate immunity; Latent Tuberculosis; Macrophage Activation; Male; Middle Aged; Polysaccharides; Protein Array Analysis; Receptors, IgG; Young Adult

OX40 Ligand Contributes to Human Lupus Pathogenesis by Promoting T Follicular Helper Response - Jacquemin, Clément; Schmitt, Nathalie; Contin-Bordes, Cécile; Liu, Yang; Narayanan, Priya; Seneschal, Julien; Maurouard, Typhanie; Dougall, David; Davizon, Emily Spence; Dumortier, Hélène; Douchet, Isabelle; Raffray, Loïc; et al. (Immunity, 2015)
Increased activity of T follicular helper (Tfh) cells plays a major pathogenic role in systemic lupus erythematosus (SLE). However, the mechanisms that cause aberrant Tfh cell responses in SLE remain elusive. Here we showed the OX40 ligand (OX40L)-OX40 axis contributes to the aberrant Tfh response in SLE. OX40L was expressed by myeloid antigen-presenting cells (APCs), but not B cells, in blood and in inflamed tissues in adult and pediatric SLE patients. The frequency of circulating OX40L-expressing myeloid APCs positively correlated with disease activity and the frequency of ICOS(+) blood Tfh cells in SLE. OX40 signals promoted naive and memory CD4(+) T cells to express multiple Tfh cell molecules and were sufficient to induce them to become functional B cell helpers. Immune complexes containing RNA induced OX40L expression on myeloid APCs via TLR7 activation. Our study provides a rationale to target the OX40L-OX40 axis as a therapeutic modality for SLE.
Keywords: Humans; Cell Differentiation; Cells, Cultured; Female; Cytokines; B-Lymphocytes; Adult; Male; Middle Aged; Young Adult; Adolescent; Aged; Antigen Presentation; Disease Progression; Immunologic Memory; Inducible T-Cell Co-Stimulator Protein; Lupus Erythematosus, Systemic; Lymphocyte Activation; Molecular Targeted Therapy; Myeloid Cells; OX40 Ligand; Receptors, OX40; RNA; Signal Transduction; T-Lymphocytes, Helper-Inducer; Toll-Like Receptor 7

Targeting dendritic cells to accelerate T-cell activation overcomes a bottleneck in tuberculosis vaccine efficacy - Griffiths, Kristin L.; Ahmed, Mushtaq; Das, Shibali; Gopal, Radha; Horne, William; Connell, Terry D.; Moynihan, Kelly D.; Kolls, Jay K.; Irvine, Darrell J.; Artyomov, Maxim N.; Rangel-Moreno, Javier; Khader, Shabaana A. (Nature Communications, 2016)
The development of a tuberculosis (TB) vaccine that induces sterilizing immunity to Mycobacterium tuberculosis infection has been elusive. Absence of sterilizing immunity induced by TB vaccines may be due to delayed activation of mucosal dendritic cells (DCs), and subsequent delay in antigen presentation and activation of vaccine-induced CD4+ T-cell responses. Here we show that pulmonary delivery of activated M. tuberculosis antigen-primed DCs into vaccinated mice, at the time of M. tuberculosis exposure, can overcome the delay in accumulation of vaccine-induced CD4+ T-cell responses. In addition, activating endogenous host CD103+ DCs and the CD40-CD40L pathway can similarly induce rapid accumulation of vaccine-induced lung CD4+ T-cell responses and limit early M. tuberculosis growth. Thus, our study provides proof of concept that targeting mucosal DCs can accelerate vaccine-induced T-cell responses on M. tuberculosis infection, and provide insights to overcome bottlenecks in TB vaccine efficacy.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis, Pulmonary; Mice; Female; CD4-Positive T-Lymphocytes; Mice, Inbred C57BL; Male; Antigen Presentation; Lymphocyte Activation; Adoptive Transfer; Antigens, CD; Dendritic Cells; Integrin alpha Chains; Mice, 129 Strain; Mice, Knockout; Mice, Transgenic

Mycobacterium tuberculosis: ecology and evolution of a human bacterium - Bañuls, Anne-Laure; Sanou, Adama; Van Anh, Nguyen Thi; Godreuil, Sylvain (Journal of Medical Microbiology, 2015)
Some species of the Mycobacterium tuberculosis complex (MTBC), particularly Mycobacterium tuberculosis, which causes human tuberculosis (TB), are the first cause of death linked to a single pathogen worldwide. In the last decades, evolutionary studies have much improved our knowledge on MTBC history and have highlighted its long co-evolution with humans. Its ability to remain latent in humans, the extraordinary proportion of asymptomatic carriers (one-third of the entire human population), the deadly epidemics and the observed increasing level of resistance to antibiotics are proof of its evolutionary success. Many MTBC molecular signatures show not only that these bacteria are a model of adaptation to humans but also that they have influenced human evolution. Owing to the unbalance between the number of asymptomatic carriers and the number of patients with active TB, some authors suggest that infection by MTBC could have a protective role against active TB disease and also against other pathologies. However, it would be inappropriate to consider these infectious pathogens as commensals or symbionts, given the level of morbidity and mortality caused by TB.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Biological Evolution; Phylogeny

Molecular basis of mycobacterial survival in macrophages - Awuh, Jane Atesoh; Flo, Trude Helen (Cellular and molecular life sciences: CMLS, 2017)
Macrophages play an essential role in the immune system by ingesting and degrading invading pathogens, initiating an inflammatory response and instructing adaptive immune cells, and resolving inflammation to restore homeostasis. More interesting is the fact that some bacteria have evolved to use macrophages as a natural habitat and tools of spread in the host, e.g., Mycobacterium tuberculosis (Mtb) and some non-tuberculous mycobacteria (NTM). Mtb is considered one of humanity's most successful pathogens and is the causal agent of tuberculosis, while NTMs cause opportunistic infections all of which are of significant public health concern. Here, we describe mechanisms by which intracellular pathogens, with an emphasis on mycobacteria, manipulate macrophage functions to circumvent killing and live inside these cells even under considerable immunological pressure. Such macrophage functions include the selective evasion or engagement of pattern recognition receptors, production of cytokines, reactive oxygen and nitrogen species, phagosome maturation, as well as other killing mechanisms like autophagy and cell death. A clear understanding of host responses elicited by a specific pathogen and strategies employed by the microbe to evade or exploit these is of significant importance for the development of effective vaccines and targeted immunotherapy against persistent intracellular infections like tuberculosis.
Keywords: Humans; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Mycobacterium; Immune evasion; Inflammatory signaling; Intracellular pathogens; Microbial Viability; Phagocytosis; Phagosome maturation; Phagosomes

Evasion of Innate and Adaptive Immunity by Mycobacterium tuberculosis - Goldberg, Michael F.; Saini, Neeraj K.; Porcelli, Steven A. (Microbiology Spectrum, 2014)
Through thousands of years of reciprocal coevolution, Mycobacterium tuberculosis has become one of humanity's most successful pathogens, acquiring the ability to establish latent or progressive infection and persist even in the presence of a fully functioning immune system. The ability of M. tuberculosis to avoid immune-mediated clearance is likely to reflect a highly evolved and coordinated program of immune evasion strategies that interfere with both innate and adaptive immunity. These include the manipulation of their phagosomal environment within host macrophages, the selective avoidance or engagement of pattern recognition receptors, modulation of host cytokine production, and the manipulation of antigen presentation to prevent or alter the quality of T-cell responses. In this article we review an extensive array of published studies that have begun to unravel the sophisticated program of specific mechanisms that enable M. tuberculosis and other pathogenic mycobacteria to persist and replicate in the face of considerable immunological pressure from their hosts. Unraveling the mechanisms by which M. tuberculosis evades or modulates host immune function is likely to be of major importance for the development of more effective new vaccines and targeted immunotherapy against tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Adaptive Immunity; Immunity, Innate; Phagosomes; Immune Evasion

"The Impact of Mycobacterium tuberculosis Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" - Meeting report - Boggiano, Cesar; Eichelberg, Katrin; Ramachandra, Lakshmi; Shea, Jaqueline; Ramakrishnan, Lalita; Behar, Samuel; Ernst, Joel D.; Porcelli, Steven A.; Maeurer, Markus; Kornfeld, Hardy (Vaccine, 2017)
Tuberculosis (TB) is the major cause of death from infectious diseases around the world, particularly in HIV infected individuals. TB vaccine design and development have been focused on improving Bacille Calmette-Guérin (BCG) and evaluating recombinant and viral vector expressed Mycobacterium tuberculosis (Mtb) proteins, for boosting BCG-primed immunity, but these approaches have not yet yielded significant improvements over the modest effects of BCG in protecting against infection or disease. On March 7-8, 2016, the National Institute of Allergy and Infectious Diseases (NIAID) convened a workshop on "The Impact of Mtb Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" with the goal of defining immune mechanisms that could be targeted through novel research approaches, to inform vaccine design and immune therapeutic interventions for prevention of TB. The workshop addressed early infection events, the impact of Mtb evolution on the development and maintenance of an adaptive immune response, and the factors that influence protection against and progression to active disease. Scientific gaps and areas of study to revitalize and accelerate TB vaccine design were discussed and prioritized. These included a comprehensive evaluation of innate and Mtb-specific adaptive immune responses in the lung at different stages of disease; determining the role of B cells and antibodies (Abs) during Mtb infection; development of better assays to measure Mtb burden following exposure, infection, during latency and after treatment, and approaches to improving current animal models to study Mtb immunogenicity, TB disease and transmission.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; Vaccine; Immune evasion; Immune Evasion; Drug Discovery

Optimisation of a murine splenocyte mycobacterial growth inhibition assay using virulent Mycobacterium tuberculosis - Jensen, Christina; Lindebo Holm, Line; Svensson, Erik; Aagaard, Claus; Ruhwald, Morten (Scientific Reports, 2017)
In the absence of a validated correlate of protection or robust animal models for human tuberculosis, Mycobacterial growth inhibition assays (MGIAs) aim to assess vaccines ability to inhibit mycobacterial growth in-vitro. We optimised a reproducible murine splenocyte MGIA based on in-vitro infection with ﻿virulent Mycobacterium tuberculosis (M.tb) Erdman. We identified splenocyte viability as a problem in state-of-art MGIA protocols, which can be improved by simple changes in culture conditions (viability increase from 21% to 46% at last day of culture). The growth inhibitory potential in mice immunised with either BCG, H56:CAF01 or H56:CAF01 administered side-by-side with BCG was significantly better compared to placebo in all groups (0.3 log10 CFU [±0.2, p = 0.049], 0.5 [±0.2, p = 0.016] and 0.6 [±0.1, p = 0.0007], respectively) corresponding to the levels of in-vivo protection. Unexpectedly the CAF01 adjuvant control group also induced significant growth inhibition of 0.3 log10 CFU (±0.2, p = 0.047). Finally, we explored vaccine-associated T cell effector functions. Despite presence of high levels of vaccine-specific T cells, we found no increase in CD4+ T cell number or cytokine expression profile, nor a difference in cytokine levels in the supernatant after four days culture with or without M.tb. Spontaneous IFN-γ release correlated with growth inhibition levels (p = 0.02), however the cellular source was not found.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Mice; Female; Virulence; Cytokines; T-Lymphocytes; Spleen; Mycobacterium bovis; Vaccination

Mycobacterial growth inhibition in murine splenocytes as a surrogate for protection against Mycobacterium tuberculosis (M. tb) - Marsay, Leanne; Matsumiya, Magali; Tanner, Rachel; Poyntz, Hazel; Griffiths, Kristin L.; Stylianou, Elena; Marsh, Philip D.; Williams, Ann; Sharpe, Sally; Fletcher, Helen; McShane, Helen (Tuberculosis (Edinburgh, Scotland), 2013)
Development of an improved vaccine against tuberculosis (TB) is hindered by the lack of a surrogate of protection. Efficacy of new TB vaccines in humans can only be evaluated by expensive and time consuming efficacy trials within TB endemic areas. It is critical that vaccines with the greatest potential to protect are selected for these trials. Mycobacterial growth inhibition assays (MGIAs) have been developed with the hope that these in-vitro functional assays will correlate with protection, which could aid in the selection of the best vaccine candidates. The present study describes the use of the BACTEC system to perform MGIAs in mice. We demonstrate reproducible mycobacterial growth inhibition in splenocytes from BCG immunised mice compared with unimmunised mice (P < 0.023), which corresponded with in-vivo efficacy against Mycobacterium tuberculosis (M. tb) challenge. Microarray data showed extensive differential gene expression in splenocyte responses to ex-vivo BCG stimulation between unimmunised and BCG-immunised mice. TH1 responses, including IFN-γ, nitric oxide synthase (NOS2) and Interleukin -17 (IL-17) expression were enhanced in BCG immunised mice, indicating a possible mechanism for mycobacterial growth inhibition. Further investigation into whether the BACTEC MGIA can be used as a surrogate of protection in humans and preclinical animal models is now warranted.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Vaccine; Cells, Cultured; BCG Vaccine; Mice; Disease Models, Animal; Female; Cytokines; Mice, Inbred C57BL; Spleen; Mycobacterium bovis; BCG; Colony Count, Microbial; Gene expression; Gene Expression Regulation; In-vitro assay; Inflammation Mediators

In vitro mycobacterial growth inhibition assays: A tool for the assessment of protective immunity and evaluation of tuberculosis vaccine efficacy - Tanner, Rachel; O'Shea, Matthew K.; Fletcher, Helen A.; McShane, Helen (Vaccine, 2016)
Tuberculosis (TB) continues to pose a serious global health threat, and the current vaccine, BCG, has variable efficacy. However, the development of a more effective vaccine is severely hampered by the lack of an immune correlate of protection. Candidate vaccines are currently evaluated using preclinical animal models, but experiments are long and costly and it is unclear whether the outcomes are predictive of efficacy in humans. Unlike measurements of single immunological parameters, mycobacterial growth inhibition assays (MGIAs) represent an unbiased functional approach which takes into account a range of immune mechanisms and their complex interactions. Such a controlled system offers the potential to evaluate vaccine efficacy and study mediators of protective immunity against Mycobacterium tuberculosis (M.tb). This review discusses the underlying principles and relative merits and limitations of the different published MGIAs, their demonstrated abilities to measure mycobacterial growth inhibition and vaccine efficacy, and what has been learned about the immune mechanisms involved.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Vaccine; Bacteriological Techniques; Immunity; MGIA; Mycobacterial growth inhibition assay

Structural and immunological principles leading to chemically synthesized, multiantigenic, multistage, minimal subunit-based vaccine development - Patarroyo, Manuel Elkin; Bermúdez, Adriana; Patarroyo, Manuel Alfonso (Chemical Reviews, 2011)
Keywords: Humans; Models, Molecular; Immunization; Vaccines; Vaccines, Subunit

Towards the development of a fully protective Plasmodium falciparum antimalarial vaccine - Patarroyo, Manuel E.; Bermúdez, Adriana; Moreno-Vranich, Armando (Expert Review of Vaccines, 2012)
If ever there were a truism then it would be that a completely protective Plasmodium falciparum malaria vaccine is desperately needed. Our institute has devoted all its efforts during the last 30 years to developing a fully protective, minimal subunit-based, multiepitope, multistage (targeting sporozoite and merozoite proteins), chemically synthesized antimalarial vaccine, given that peptides with high binding activity to their corresponding host cells (liver cells or red blood cells) form the springboard for vaccine design. However, such conserved high activity binding peptides have to be specifically modified to render them into highly immunogenic and protection-inducing peptides since they are immunologically silent. These modifications, analyzed at the 3D structural level by (1)H-NMR, allow them a better fit into the MHC II-peptide-T-cell receptor complex to induce an appropriate immune response, providing a rational and logical approach (analyzed at the single atom level) for vaccine development, particularly in the field of malaria.
Keywords: Humans; Protein Conformation; Drug Discovery; Vaccines, Subunit; Magnetic Resonance Spectroscopy; Malaria Vaccines; Malaria, Falciparum; Plasmodium falciparum

Tuberculosis - OPS/OMS | Organización Panamericana de la Salud (2022)
La tuberculosis (TB) es una enfermedad infecciosa que suele afectar a los pulmones y es causada por una bacteria (Mycobacterium tuberculosis). Se transmite de una persona a otra a través de gotitas de aerosol suspendidas en el aire expulasadas por personas con enfermedad pulmonar activa. La infección por M. tuberculosis suele ser asintomática en personas sanas, dado que su sistema inmunitario actúa formando una barrera alrededor de la bacteria.

INS. Instituto Nacional de Salud. Boletín Informativo Semanal Semana Epi : 46. 2022.

Overview and phylogeny of Mycobacterium tuberculosis complex organisms: implications for diagnostics and legislation of bovine tuberculosis - Rodriguez-Campos, Sabrina; Smith, Noel H.; Boniotti, Maria B.; Aranaz, Alicia (Research in Veterinary Science, 2014)
Members of the Mycobacterium tuberculosis complex (MTBC) cause a serious disease with similar pathology, tuberculosis; in this review, bovine tuberculosis will be considered as disease caused by any member of the MTBC in bovids. Bovine tuberculosis is responsible for significant economic loss due to costly eradication programs and trade limitations and poses a threat to both endangered and protected species as well as to public health. We here give an overview on all members of the MTBC, focusing on their isolation from different animal hosts. We also review the recent advances made in elucidating the evolutionary and phylogenetic relationships of members of the MTBC. Because the nomenclature of the MTBC is controversial, its members have been considered species, subspecies or ecotypes, this review discusses the possible implications for diagnostics and the legal consequences of naming of new species.
Keywords: Mycobacterium tuberculosis; Animals; Cattle; Phylogeny; Mycobacterium bovis; Bovine tuberculosis; Europe; Legislation; Legislation, Veterinary; Mycobacterium caprae; Mycobacterium tuberculosis complex; Phenotype; Terminology as Topic; Tuberculosis, Bovine

Diagnosis of Mycobacterium microti infections among humans by using novel genetic markers - van Soolingen, D.; van der Zanden, A. G.; de Haas, P. E.; Noordhoek, G. T.; Kiers, A.; Foudraine, N. A.; Portaels, F.; Kolk, A. H.; Kremer, K.; van Embden, J. D. (Journal of Clinical Microbiology, 1998)
As a result of DNA typing of Mycobacterium microti isolates from animals in the United Kingdom and The Netherlands, we diagnosed four human M. microti infections. These are the first M. microti infections among humans to be reported. Three of the patients were immunocompromised and suffered from generalized forms of tuberculosis. The fourth patient was a 34-year-old immunocompetent male with a persistent cough and undefined X-ray abnormalities. Two of the M. microti infections were recognized by their IS6110 restriction fragment length polymorphism (RFLP) patterns, which showed a high degree of similarity with those of M. microti strains isolated from a pig and a ferret in The Netherlands. The two other human M. microti infections were recognized by using the recently developed DNA fingerprinting method, "spoligotyping," directly on clinical material. All M. microti isolates from the United Kingdom and The Netherlands were found to contain an exceptionally short genomic direct repeat region, resulting in identical two-spacer sequence reactions in spoligotyping. In contrast, the highly similar IS6110 RFLP patterns of the vole strains from the United Kingdom differed considerably from the RFLPs of all M. microti strains isolated in The Netherlands, suggesting that geographic isolation led to divergent strains in the United Kingdom and on the continent.
Keywords: DNA, Bacterial; Humans; Animals; Tuberculosis; Mycobacterium; Polymerase Chain Reaction; Mice; Adult; Male; Bacterial Typing Techniques; Child; DNA Fingerprinting; Genetic Markers; Immunocompromised Host; Netherlands; Polymorphism, Restriction Fragment Length

Two cases of Mycobacterium microti derived tuberculosis in HIV-negative immunocompetent patients - Niemann, S.; Richter, E.; Dalügge-Tamm, H.; Schlesinger, H.; Graupner, D.; Königstein, B.; Gurath, G.; Greinert, U.; Rüsch-Gerdes, S. (Emerging Infectious Diseases, 2000)
We describe two cases of Mycobacterium microti infection causing pulmonary tuberculosis (TB) in HIV-seronegative immunocompetent patients in Germany. The isolates were identified as M. microti of the llama and vole types, according to spoligotype patterns. Our data demonstrate that M. microti can cause severe pulmonary TB in immunocompetent patients.
Keywords: Humans; Mycobacterium; Tuberculosis, Pulmonary; Antitubercular Agents; Male; Middle Aged; Germany; HIV Seronegativity; Immunocompetence; Microbial Sensitivity Tests; Radiography

Human and animal infections with Mycobacterium microti, Scotland - Xavier Emmanuel, Francis; Seagar, Amie-Louise; Doig, Christine; Rayner, Alan; Claxton, Pauline; Laurenson, Ian (Emerging Infectious Diseases, 2007)
During 1994-2005, we isolated Mycobacterium microti from 5 animals and 4 humans. Only 1 person was immunocompromised. Spoligotyping showed 3 patterns: vole type, llama type, and a new variant llama type.
Keywords: Humans; Animals; Anti-Bacterial Agents; Mycobacterium; Female; Adult; Male; Middle Aged; Aged; Polymorphism, Restriction Fragment Length; Camelids, New World; Cats; Drug Resistance; Ferrets; Mustelidae; Mycobacterium Infections, Nontuberculous; Scotland

Morphological characterization of Mycobacterium tuberculosis in a MODS culture for an automatic diagnostics through pattern recognition - Alva, Alicia; Aquino, Fredy; Gilman, Robert H.; Olivares, Carlos; Requena, David; Gutiérrez, Andrés H.; Caviedes, Luz; Coronel, Jorge; Larson, Sandra; Sheen, Patricia; Moore, David A. J.; Zimic, Mirko (PloS One, 2013)
Tuberculosis control efforts are hampered by a mismatch in diagnostic technology: modern optimal diagnostic tests are least available in poor areas where they are needed most. Lack of adequate early diagnostics and MDR detection is a critical problem in control efforts. The Microscopic Observation Drug Susceptibility (MODS) assay uses visual recognition of cording patterns from Mycobacterium tuberculosis (MTB) to diagnose tuberculosis infection and drug susceptibility directly from a sputum sample in 7-10 days with a low cost. An important limitation that laboratories in the developing world face in MODS implementation is the presence of permanent technical staff with expertise in reading MODS. We developed a pattern recognition algorithm to automatically interpret MODS results from digital images. The algorithm using image processing, feature extraction and pattern recognition determined geometrical and illumination features used in an object-model and a photo-model to classify TB-positive images. 765 MODS digital photos were processed. The single-object model identified MTB (96.9% sensitivity and 96.3% specificity) and was able to discriminate non-tuberculous mycobacteria with a high specificity (97.1% M. avium, 99.1% M. chelonae, and 93.8% M. kansasii). The photo model identified TB-positive samples with 99.1% sensitivity and 99.7% specificity. This algorithm is a valuable tool that will enable automatic remote diagnosis using Internet or cellphone telephony. The use of this algorithm and its further implementation in a telediagnostics platform will contribute to both faster TB detection and MDR TB determination leading to an earlier initiation of appropriate treatment.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Algorithms; Antitubercular Agents; Bacteriological Techniques; Microbial Sensitivity Tests; Microscopy; Pattern Recognition, Automated; Sensitivity and Specificity

How sisters grow apart: mycobacterial growth and division - Kieser, Karen J.; Rubin, Eric J. (Nature Reviews. Microbiology, 2014)
Mycobacterium tuberculosis, which is the aetiological agent of tuberculosis, owes much of its success as a pathogen to its unique cell wall and unusual mechanism of growth, which facilitate its adaptation to the human host and could have a role in clinical latency. Asymmetric growth and division increase population heterogeneity, which may promote antibiotic tolerance and the fitness of single cells. In this Review, we describe the unusual mechanisms of mycobacterial growth, cell wall biogenesis and division, and discuss how these processes might affect the survival of M. tuberculosis in vivo and contribute to the persistence of infection.
Keywords: Mycobacterium tuberculosis; Mycobacterium; Cell Wall; Cell Division; Peptidoglycan

Dissecting the mycobacterial cell envelope and defining the composition of the native mycomembrane - Chiaradia, Laura; Lefebvre, Cyril; Parra, Julien; Marcoux, Julien; Burlet-Schiltz, Odile; Etienne, Gilles; Tropis, Maryelle; Daffé, Mamadou (Scientific Reports, 2017)
The mycobacterial envelope is unique, containing the so-called mycomembrane (MM) composed of very-long chain fatty acids, mycolic acids (MA). Presently, the molecular composition of the MM remains unproven, due to the diversity of methods used for determining its composition. The plasma membranes (PM) and the native MM-containing cell walls (MMCW) of two rapid-growing mycobacterial species, Mycobacterium aurum and M. smegmatis, were isolated from their cell lysates by differential ultracentrifugation. Transmission electron microscopy and biochemical analyses demonstrated that the two membranes were virtually pure. Bottom-up quantitative proteomics study indicated a different distribution of more than 2,100 proteins between the PM and MMCW. Among these, the mannosyltransferase PimB, galactofuranosyltransferase GlfT2, Cytochrome p450 and ABC transporter YjfF, were most abundant in the PM, which also contain lipoglycans, phospholipids, including phosphatidylinositol mannosides, and only a tiny amount of other glycolipids. Antigen85 complex proteins, porins and the putative transporters MCE protein family were mostly found in MMCW fraction that contains MA esterifying arabinogalactan, constituting the inner leaflet of MM. Glycolipids, phospholipids and lipoglycans, together with proteins, presumably composed the outer leaflet of the MM, a lipid composition that differs from that deduced from the widely used extraction method of mycobacterial cells with dioctylsulfosuccinate sodium.
Keywords: Bacterial Proteins; Membrane Proteins; Cell Membrane; Mycobacterium; Cell Wall; Biomarkers; Lipopolysaccharides; Membrane Lipids; Models, Biological; Multienzyme Complexes; NADH, NADPH Oxidoreductases; Proteomics

Tuberculosis - Pai, Madhukar; Behr, Marcel A.; Dowdy, David; Dheda, Keertan; Divangahi, Maziar; Boehme, Catharina C.; Ginsberg, Ann; Swaminathan, Soumya; Spigelman, Melvin; Getahun, Haileyesus; Menzies, Dick; Raviglione, Mario (Nature Reviews. Disease Primers, 2016)
Tuberculosis (TB) is an airborne infectious disease caused by organisms of the Mycobacterium tuberculosis complex. Although primarily a pulmonary pathogen, M. tuberculosis can cause disease in almost any part of the body. Infection with M. tuberculosis can evolve from containment in the host, in which the bacteria are isolated within granulomas (latent TB infection), to a contagious state, in which the patient will show symptoms that can include cough, fever, night sweats and weight loss. Only active pulmonary TB is contagious. In many low-income and middle-income countries, TB continues to be a major cause of morbidity and mortality, and drug-resistant TB is a major concern in many settings. Although several new TB diagnostics have been developed, including rapid molecular tests, there is a need for simpler point-of-care tests. Treatment usually requires a prolonged course of multiple antimicrobials, stimulating efforts to develop shorter drug regimens. Although the Bacillus Calmette-Guérin (BCG) vaccine is used worldwide, mainly to prevent life-threatening TB in infants and young children, it has been ineffective in controlling the global TB epidemic. Thus, efforts are underway to develop newer vaccines with improved efficacy. New tools as well as improved programme implementation and financing are necessary to end the global TB epidemic by 2035.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Antitubercular Agents; BCG Vaccine

How can immunology contribute to the control of tuberculosis? - Kaufmann, S. H. (Nature Reviews. Immunology, 2001)
Tuberculosis poses a significant threat to mankind. Multidrug-resistant strains are on the rise, and Mycobacterium tuberculosis infection is often associated with human immunodeficiency virus infection. Satisfactory control of tuberculosis can only be achieved using a highly efficacious vaccine. Tuberculosis is particularly challenging for the immune system. The intracellular location of the pathogen shields it from antibodies, and a variety of T-cell subpopulations must be activated to challenge the bacterium's resistance to antibacterial defence mechanisms. A clear understanding of the immune responses that control the pathogen will be important for achieving optimal immunity, and information provided by functional genome analysis of M. tuberculosis will be vital in the design of a future vaccine.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; BCG Vaccine; Mice; Disease Models, Animal; Models, Immunological; T-Lymphocytes

Tuberculosis pathogenesis and immunity - Philips, Jennifer A.; Ernst, Joel D. (Annual Review of Pathology, 2012)
Despite the development of potentially curative chemotherapy, tuberculosis (TB) continues to cause increasing worldwide morbidity and is a leading cause of human mortality in the developing world. Recent advances in bacterial molecular genetics, immunology, and human genetics have yielded insight into the molecular determinants of virulence, the immune responses that are essential for restricting progressive disease, and the determinants of immunopathology in TB. Despite these advances, a large knowledge gap still exists that limits the development and testing of new interventions, including novel drugs and efficacious vaccines. This review focuses on our current knowledge of TB pathogenesis and immunity that has been derived from in vitro and in vivo studies. In addition, it highlights topics that need to be better understood to provide improved means of controlling TB worldwide.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; Adaptive Immunity; Immunity, Innate

The tuberculous granuloma: an unsuccessful host defence mechanism providing a safety shelter for the bacteria? - Silva Miranda, Mayra; Breiman, Adrien; Allain, Sophie; Deknuydt, Florence; Altare, Frederic (Clinical & Developmental Immunology, 2012)
One of the main features of the immune response to M. Tuberculosis is the formation of an organized structure called granuloma. It consists mainly in the recruitment at the infectious stage of macrophages, highly differentiated cells such as multinucleated giant cells, epithelioid cells and Foamy cells, all these cells being surrounded by a rim of lymphocytes. Although in the first instance the granuloma acts to constrain the infection, some bacilli can actually survive inside these structures for a long time in a dormant state. For some reasons, which are still unclear, the bacilli will reactivate in 10% of the latently infected individuals, escape the granuloma and spread throughout the body, thus giving rise to clinical disease, and are finally disseminated throughout the environment. In this review we examine the process leading to the formation of the granulomatous structures and the different cell types that have been shown to be part of this inflammatory reaction. We also discuss the different in vivo and in vitro models available to study this fascinating immune structure.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Disease Models, Animal; Granuloma

Apoptotic vesicles crossprime CD8 T cells and protect against tuberculosis - Winau, Florian; Weber, Stephan; Sad, Subash; de Diego, Juana; Hoops, Silvia Locatelli; Breiden, Bernadette; Sandhoff, Konrad; Brinkmann, Volker; Kaufmann, Stefan H. E.; Schaible, Ulrich E. (Immunity, 2006)
CD8 T lymphocytes are important effectors in protective immunity against Mycobacterium tuberculosis. We recently characterized the detour pathway of CD8 T cell activation in tuberculosis mediated by apoptotic vesicles from infected cells that transport mycobacterial antigens to dendritic cells (DCs). Here we demonstrate that apoptotic vesicles from mycobacteria-infected macrophages stimulate CD8 T cells in vivo. Homing of DCs to draining lymph nodes was critically required for effective crosspriming. Subsequent fate of vesicle-associated antigens in recipient DCs was characterized by endosomal mechanisms predominating over proteasomal processing. In addition, vesicle processing depended on the presence of saposins to disintegrate apoptotic membranes. Apoptotic vesicles displayed potent adjuvant activity by stimulating through Toll-like receptors (TLR). Ultimately, vaccination with vesicles from infected cells induced protection against M. tuberculosis infection. Taken together, we propose the detour pathway to represent a genuine immunological mechanism mediating crosspriming of CD8 T cells in vivo and protection against tuberculosis.
Keywords: Animals; Macrophages; Tuberculosis; BCG Vaccine; Mice; Adjuvants, Immunologic; CD8-Positive T-Lymphocytes; Dendritic Cells; Mycobacterium bovis; Vaccination; Apoptosis; Cross-Priming; Endosomes; Saposins; Toll-Like Receptors

The role of the granuloma in expansion and dissemination of early tuberculous infection - Davis, J. Muse; Ramakrishnan, Lalita (Cell, 2009)
Granulomas, organized aggregates of immune cells, form in response to persistent stimuli and are hallmarks of tuberculosis. Tuberculous granulomas have long been considered host-protective structures formed to contain infection. However, work in zebrafish infected with Mycobacterium marinum suggests that granulomas contribute to early bacterial growth. Here we use quantitative intravital microscopy to reveal distinct steps of granuloma formation and assess their consequence for infection. Intracellular mycobacteria use the ESX-1/RD1 virulence locus to induce recruitment of new macrophages to, and their rapid movement within, nascent granulomas. This motility enables multiple arriving macrophages to efficiently find and phagocytose infected macrophages undergoing apoptosis, leading to rapid, iterative expansion of infected macrophages and thereby bacterial numbers. The primary granuloma then seeds secondary granulomas via egress of infected macrophages. Our direct observations provide insight into how pathogenic mycobacteria exploit the granuloma during the innate immune phase for local expansion and systemic dissemination.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Virulence Factors; Granuloma; Phagocytosis; Mycobacterium Infections, Nontuberculous; Apoptosis; Chemotaxis; Mycobacterium Infections; Mycobacterium marinum; Zebrafish

Revisiting the role of the granuloma in tuberculosis - Ramakrishnan, Lalita (Nature Reviews. Immunology, 2012)
The granuloma, which is a compact aggregate of immune cells, is the hallmark structure of tuberculosis. It is historically regarded as a host-protective structure that 'walls off' the infecting mycobacteria. This Review discusses surprising new discoveries--from imaging studies coupled with genetic manipulations--that implicate the innate immune mechanisms of the tuberculous granuloma in the expansion and dissemination of infection. It also covers why the granuloma can fail to eradicate infection even after adaptive immunity develops. An understanding of the mechanisms and impact of tuberculous granuloma formation can guide the development of therapies to modulate granuloma formation. Such therapies might be effective for tuberculosis as well as for other granulomatous diseases.
Keywords: Humans; Animals; Tuberculosis; Granuloma; Immunity, Innate

Acid resistance in Mycobacterium tuberculosis - Vandal, Omar H.; Nathan, Carl F.; Ehrt, Sabine (Journal of Bacteriology, 2009)
Keywords: Mycobacterium tuberculosis; Macrophages; Phagosomes; Models, Biological; Hydrogen-Ion Concentration

Mycobacterium tuberculosis inhibits neutrophil apoptosis, leading to delayed activation of naive CD4 T cells - Blomgran, Robert; Desvignes, Ludovic; Briken, Volker; Ernst, Joel D. (Cell Host & Microbe, 2012)
Mycobacterium tuberculosis promotes its replication by inhibiting the apoptosis of infected macrophages. A proapoptotic M. tuberculosis mutant lacking nuoG, a subunit of the type I NADH dehydrogenase complex, exhibits attenuated growth in vivo, indicating that this virulence mechanism is essential. We show that M. tuberculosis also suppresses neutrophil apoptosis. Compared to wild-type, the nuoG mutant spread to a larger number of lung phagocytic cells. Consistent with the shorter lifespan of infected neutrophils, infection with the nuoG mutant resulted in fewer bacteria per infected neutrophil, accelerated bacterial acquisition by dendritic cells, earlier trafficking of these dendritic cells to lymph nodes, and faster CD4 T cell priming. Neutrophil depletion abrogated accelerated CD4 T cell priming by the nuoG mutant, suggesting that inhibiting neutrophil apoptosis delays adaptive immunity in tuberculosis. Thus, pathogen modulation of apoptosis is beneficial at multiple levels, and enhancing phagocyte apoptosis promotes CD4 as well as CD8 T cell responses.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Virulence Factors; Neutrophils; Lymph Nodes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Lymphocyte Activation; Dendritic Cells; Immune Evasion; Apoptosis; Bacterial Load; Gene Deletion

Neutrophils in tuberculosis--first line of defence or booster of disease and targets for host-directed therapy? - Dallenga, Tobias; Schaible, Ulrich E. (Pathogens and Disease, 2016)
Necrotizing granulomas, exacerbating pathogenesis and neutrophil influx at the site of infection are hallmarks of active pulmonary tuberculosis (TB) in humans. The role of polymorphonuclear neutrophils (PMN) in host defence and TB pathogenesis has recently attracted broader interest. Association of infiltrating PMN, enhanced mycobacterial load and disease exacerbation in both, mice susceptible to experimental TB as well as in TB patients, link PMN to exacerbated pathology. Targeting PMN resulted in smaller lung lesions and reduced mycobacterial burden. Therefore, PMN-associated molecules represent interesting biomarkers to determine TB severity and treatment success. More importantly, PMN are putative targets for host-directed therapies (HDT) in TB. Due to the rise of multi- and extensively drug-resistant Mycobacterium tuberculosis isolates, HDT represent adjunct measures to support antibiotic treatment by ameliorating pathology and local host defences.
Keywords: Humans; Mycobacterium tuberculosis; Animals; tuberculosis; Tuberculosis, Pulmonary; Mice; Neutrophils; Cytokines; Bacterial Load; host-directed therapy; Inflammation; neutrophils; polymorphonuclear cells

Effector Mechanisms of Neutrophils within the Innate Immune System in Response to Mycobacterium tuberculosis Infection - Warren, Eric; Teskey, Garrett; Venketaraman, Vishwanath (Journal of Clinical Medicine, 2017)
Neutrophils have a significant yet controversial role in the innate immune response to Mycobacterium tuberculosis (M. tb) infection, which is not yet fully understood. In addition to neutrophils' well-known effector mechanisms, they may also help control infection of M. tb through the formation of neutrophil extracellular traps (NETs), which are thought to further promote the killing of M. tb by resident alveolar macrophages. Cytokines such as IFN-γ have now been shown to serve an immunomodulatory role in neutrophil functioning in conjunction to its pro-inflammatory function. Additionally, the unique transcriptional changes of neutrophils may be used to differentiate between infection with M. tb and other bacterial and chronic rheumatological diseases such as Systemic Lupus Erythematosus. Adversely, during the innate immune response to M. tb, inappropriate phagocytosis of spent neutrophils can result in nonspecific damage to host cells due to necrotic lysis. Furthermore, some individuals have been shown to be more genetically susceptible to tuberculosis (TB) due to a "Trojan Horse" phenomenon whereby neutrophils block the ability of resident macrophages to kill M. tb. Despite these aforementioned negative consequences, through the scope of this review we will provide evidence to support the idea that neutrophils, while sometimes damaging, can also be an important component in warding off M. tb infection. This is exemplified in immunocompromised individuals, such as those with human immunodeficiency virus (HIV) infection or Type 2 diabetes mellitus. These individuals are at an increased risk of developing tuberculosis (TB) due to a diminished innate immune response associated with decreased levels of glutathione. Consequently, there has been a worldwide effort to limit and contain M. tb infection through the use of antibiotics and vaccinations. However, due to several significant limitations, the current bacille Calmette-Guerin vaccine (BCG, vaccine against TB) does not meet the criteria for universal utilization for all ages and populations across the globe. New research involving neutrophils has yielded a new vaccine called M. smegmatis-Ag85C-MPT51-HspX (mc²-CMX) that has been shown to elicit a humoral and cellular response against M. tb in mice that is superior to the BCG vaccine.
Keywords: Mycobacterium tuberculosis; Tuberculosis; Neutrophils; Cytokines; Innate immunity; M. tb; NETs; Phagocytosis-induced cell death; PMN; polymorphonuclear leukocytes; TB

Modulation of human neutrophil apoptosis by immune complexes - Gamberale, R.; Giordano, M.; Trevani, A. S.; Andonegui, G.; Geffner, J. R. (Journal of Immunology (Baltimore, Md.: 1950), 1998)
In the present study we examined whether immune complexes (IC) are able to modulate human neutrophil apoptosis. We observed different effects depending on the type of IC employed. Precipitating IC (pIC) and Ab-coated erythrocytes (E-IgG) triggered a marked stimulation of apoptosis, while heat-aggregated IgG and soluble IC, significantly delayed spontaneous apoptosis. Blocking Abs directed to Fcgamma receptor type II (FcgammaRII), but not to FcgammaRIII, markedly diminished the acceleration of apoptosis triggered by either pIC or E-IgG, supporting a critical role for FcgammaRII in apoptosis stimulation. This phenomenon, on the other hand, does not appear to involve IC phagocytosis or the participation of CR3. Acceleration of neutrophil apoptosis triggered by either pIC or E-IgG seems to require the activation of the respiratory burst, as suggested by 1) the ability of catalase to prevent apoptosis stimulation; 2) the effect of azide, an heme enzyme inhibitor, which dramatically enhanced apoptosis induced by pIC or E-IgG; and 3) the inability of pIC or E-IgG to accelerate apoptosis of neutrophils isolated from CGD patients. It is well established that IC affect the course of inflammation by inducing the release of inflammatory cytokines, proteolytic enzymes, oxidative agents, and other toxic molecules. Our results suggest that IC may also affect the course of inflammation by virtue of their ability to modulate neutrophil apoptosis.
Keywords: Humans; Immunoglobulin G; Neutrophils; Receptors, IgG; Phagocytosis; Apoptosis; Antigen-Antibody Complex; Calcium; Chemical Precipitation; Cytosol; Erythrocytes; Fas Ligand Protein; fas Receptor; Granulomatous Disease, Chronic; Hot Temperature; Ligands; Macrophage-1 Antigen; Membrane Glycoproteins; Neutrophil Activation; Reactive Oxygen Species; Respiratory Burst; Solubility

CD4+ T cells contain early extrapulmonary tuberculosis (TB) dissemination and rapid TB progression and sustain multieffector functions of CD8+ T and CD3- lymphocytes: mechanisms of CD4+ T cell immunity - Yao, Shuyu; Huang, Dan; Chen, Crystal Y.; Halliday, Lisa; Wang, Richard C.; Chen, Zheng W. (Journal of Immunology (Baltimore, Md.: 1950), 2014)
The possibility that CD4(+) T cells can act as "innate-like" cells to contain very early Mycobacterium tuberculosis dissemination and function as master helpers to sustain multiple effector functions of CD8(+) T cells and CD3(-) lymphocytes during development of adaptive immunity against primary tuberculosis (TB) has not been demonstrated. We showed that pulmonary M. tuberculosis infection of CD4-depleted macaques surprisingly led to very early extrapulmonary M. tuberculosis dissemination, whereas CD4 deficiency clearly resulted in rapid TB progression. CD4 depletion during M. tuberculosis infection revealed the ability of CD8(+) T cells to compensate and rapidly differentiate to Th17-like/Th1-like and cytotoxic-like effectors, but these effector functions were subsequently unsustainable due to CD4 deficiency. Whereas CD3(-) non-T lymphocytes in the presence of CD4(+) T cells developed predominant Th22-like and NK-like (perforin production) responses to M. tuberculosis infection, CD4 depletion abrogated these Th22-/NK-like effector functions and favored IL-17 production by CD3(-) lymphocytes. CD4-depleted macaques exhibited no or few pulmonary T effector cells constitutively producing IFN-γ, TNF-α, IL-17, IL-22, and perforin at the endpoint of more severe TB, but they presented pulmonary IL-4(+) T effectors. TB granulomas in CD4-depleted macaques contained fewer IL-22(+) and perforin(+) cells despite the presence of IL-17(+) and IL-4(+) cells. These results implicate a previously unknown innate-like ability of CD4(+) T cells to contain extrapulmonary M. tuberculosis dissemination at very early stage. Data also suggest that CD4(+) T cells are required to sustain multiple effector functions of CD8(+) T cells and CD3(-) lymphocytes and to prevent rapid TB progression during M. tuberculosis infection of nonhuman primates.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Macaca fascicularis; Cytokines; CD8-Positive T-Lymphocytes; Th1 Cells; Th17 Cells

Genetic dissection of immunity to mycobacteria: the human model - Casanova, Jean-Laurent; Abel, Laurent (Annual Review of Immunology, 2002)
Humans are exposed to a variety of environmental mycobacteria (EM), and most children are inoculated with live Bacille Calmette-Guérin (BCG) vaccine. In addition, most of the world's population is occasionally exposed to human-borne mycobacterial species, which are less abundant but more virulent. Although rarely pathogenic, mildly virulent mycobacteria, including BCG and most EM, may cause a variety of clinical diseases. Mycobacterium tuberculosis, M. leprae, and EM M. ulcerans are more virulent, causing tuberculosis, leprosy, and Buruli ulcer, respectively. Remarkably, only a minority of individuals develop clinical disease, even if infected with virulent mycobacteria. The interindividual variability of clinical outcome is thought to result in part from variability in the human genes that control host defense. In this well-defined microbiological and clinical context, the principles of mouse immunology and the methods of human genetics can be combined to facilitate the genetic dissection of immunity to mycobacteria. The natural infections are unique to the human model, not being found in any of the animal models of experimental infection. We review current genetic knowledge concerning the simple and complex inheritance of predisposition to mycobacterial diseases in humans. Rare patients with Mendelian disorders have been found to be vulnerable to BCG, a few EM, and M. tuberculosis. Most cases of presumed Mendelian susceptibility to these and other mycobacterial species remain unexplained. In the general population leprosy and tuberculosis have been shown to be associated with certain human genetic polymorphisms and linked to certain chromosomal regions. The causal vulnerability genes themselves have yet to be identified and their pathogenic alleles immunologically validated. The studies carried out to date have been fruitful, initiating the genetic dissection of protective immunity against a variety of mycobacterial species in natural conditions of infection. The human model has potential uses beyond the study of mycobacterial infections and may well become a model of choice for the investigation of immunity to infectious agents.
Keywords: Humans; Mycobacterium; Virulence; Interferon-gamma; Models, Immunological; Mycobacterium bovis; Immunity; Mycobacterium Infections; Environmental Microbiology; Immunologic Deficiency Syndromes; Interleukin-12

IFN-γ from CD4 T cells is essential for host survival and enhances CD8 T cell function during Mycobacterium tuberculosis infection - Green, Angela M.; Difazio, Robert; Flynn, Joanne L. (Journal of Immunology (Baltimore, Md.: 1950), 2013)
IFN-γ is necessary in both humans and mice for control of Mycobacterium tuberculosis. CD4 T cells are a significant source of IFN-γ during acute infection in mice and are required for control of bacterial growth and host survival. However, several other types of cells can and do produce IFN-γ during the course of the infection. We sought to determine whether IFN-γ from sources other than CD4 T cells was sufficient to control M. tuberculosis infection and whether CD4 T cells had a role in addition to IFN-γ production. To investigate the role of IFN-γ from CD4 T cells, a murine adoptive transfer model was developed in which all cells were capable of producing IFN-γ, with the exception of CD4 T cells. Our data in this system support that CD4 T cells are essential for control of infection, but also that IFN-γ from CD4 T cells is necessary for host survival and optimal long-term control of bacterial burden. In addition, IFN-γ from CD4 T cells was required for a robust CD8 T cell response. IFN-γ from T cells inhibited intracellular replication of M. tuberculosis in macrophages, suggesting IFN-γ may be necessary for intracellular bactericidal activity. Thus, although CD4 T cells play additional roles in the control of M. tuberculosis infection, IFN-γ is a major function by which these cells participate in resistance to tuberculosis.
Keywords: Mycobacterium tuberculosis; Animals; Cells, Cultured; Tuberculosis, Pulmonary; Mice; Interferon-gamma; Survival Analysis; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Mice, Inbred C57BL; Adoptive Transfer; Mice, 129 Strain; Mice, Knockout; Mice, Transgenic; Disease Resistance; Up-Regulation

Role of Interferons in the Development of Diagnostics, Vaccines, and Therapy for Tuberculosis - Chin, Kai Ling; Anis, Fadhilah Zulkipli; Sarmiento, Maria E.; Norazmi, Mohd Nor; Acosta, Armando (Journal of Immunology Research, 2017)
Tuberculosis (TB) is an airborne infection caused by Mycobacterium tuberculosis (Mtb). About one-third of the world's population is latently infected with TB and 5-15% of them will develop active TB in their lifetime. It is estimated that each case of active TB may cause 10-20 new infections. Host immune response to Mtb is influenced by interferon- (IFN-) signaling pathways, particularly by type I and type II interferons (IFNs). The latter that consists of IFN-γ has been associated with the promotion of Th1 immune response which is associated with protection against TB. Although this aspect remains controversial at present due to the lack of established correlates of protection, currently, there are different prophylactic, diagnostic, and immunotherapeutic approaches in which IFNs play an important role. This review summarizes the main aspects related with the biology of IFNs, mainly associated with TB, as well as presents the main applications of these cytokines related to prophylaxis, diagnosis, and immunotherapy of TB.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; Antitubercular Agents; Mice; Interferon-gamma; Cytokines; Immunotherapy; Interferons

Life and death in the granuloma: immunopathology of tuberculosis - Saunders, Bernadette M.; Britton, Warwick J. (Immunology and Cell Biology, 2007)
During tuberculosis (TB) infection, the granuloma provides the microenvironment in which antigen-specific T cells colocate with and activate infected macrophages to inhibit the growth of Mycobacterium tuberculosis. Although the granuloma is the site for mycobacterial killing, virulent mycobacteria have developed a variety of mechanisms to resist this macrophage-mediated killing. These surviving mycobacteria become dormant, however, if host cellular immunity or the signals maintaining granuloma structure wane, or if mycobacteria resume replication, leading to reactivation of TB. This balance of life and death applies not only to the mycobacterium but also to the host macrophages that may undergo apoptosis or necrosis, leading to the characteristic caseous necrosis within the granuloma, and the potential spread of TB infection. The immunological factors controlling the development and maintenance of the granuloma will be reviewed.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Granuloma; CD4-Positive T-Lymphocytes; Immunity, Cellular; Microbial Viability; Models, Biological; Inflammation; Adaptation, Biological; Chemokines; Species Specificity; Tumor Necrosis Factor-alpha; Virus Latency

Phenotype and functions of memory Tfh cells in human blood - Schmitt, Nathalie; Bentebibel, Salah-Eddine; Ueno, Hideki (Trends in Immunology, 2014)
Keywords: human blood; subsets; T follicular helper cells

Virulence factors of the Mycobacterium tuberculosis complex - Forrellad, Marina A.; Klepp, Laura I.; Gioffré, Andrea; Sabio y García, Julia; Morbidoni, Hector R.; Santangelo, María de la Paz; Cataldi, Angel A.; Bigi, Fabiana (Virulence, 2013)
The Mycobacterium tuberculosis complex (MTBC) consists of closely related species that cause tuberculosis in both humans and animals. This illness, still today, remains to be one of the leading causes of morbidity and mortality throughout the world. The mycobacteria enter the host by air, and, once in the lungs, are phagocytated by macrophages. This may lead to the rapid elimination of the bacillus or to the triggering of an active tuberculosis infection. A large number of different virulence factors have evolved in MTBC members as a response to the host immune reaction. The aim of this review is to describe the bacterial genes/proteins that are essential for the virulence of MTBC species, and that have been demonstrated in an in vivo model of infection. Knowledge of MTBC virulence factors is essential for the development of new vaccines and drugs to help manage the disease toward an increasingly more tuberculosis-free world.
Keywords: Mycobacterium tuberculosis; pathogen; virulence; virulence factors; virulence genes

CXCR5⁺ T helper cells mediate protective immunity against tuberculosis - Slight, Samantha R.; Rangel-Moreno, Javier; Gopal, Radha; Lin, Yinyao; Fallert Junecko, Beth A.; Mehra, Smriti; Selman, Moises; Becerril-Villanueva, Enrique; Baquera-Heredia, Javier; Pavon, Lenin; Kaushal, Deepak; Reinhart, Todd A.; et al. (The Journal of Clinical Investigation, 2013)
One third of the world's population is infected with Mycobacterium tuberculosis (Mtb). Although most infected people remain asymptomatic, they have a 10% lifetime risk of developing active tuberculosis (TB). Thus, the current challenge is to identify immune parameters that distinguish individuals with latent TB from those with active TB. Using human and experimental models of Mtb infection, we demonstrated that organized ectopic lymphoid structures containing CXCR5+ T cells were present in Mtb-infected lungs. In addition, we found that in experimental Mtb infection models, the presence of CXCR5+ T cells within ectopic lymphoid structures was associated with immune control. Furthermore, in a mouse model of Mtb infection, we showed that activated CD4+CXCR5+ T cells accumulated in Mtb-infected lungs and produced proinflammatory cytokines. Mice deficient in Cxcr5 had increased susceptibility to TB due to defective T cell localization within the lung parenchyma. We demonstrated that CXCR5 expression in T cells mediated correct T cell localization within TB granulomas, promoted efficient macrophage activation, protected against Mtb infection, and facilitated lymphoid follicle formation. These data demonstrate that CD4+CXCR5+ T cells play a protective role in the immune response against TB and highlight their potential use for future TB vaccine design and therapy.
Keywords: Humans; Animals; Tuberculosis, Pulmonary; Mice; Disease Models, Animal; Female; Lung; Cytokines; T-Lymphocyte Subsets; Latent Tuberculosis; Macrophage Activation; Male; Lymphocyte Activation; T-Lymphocytes, Helper-Inducer; Mice, Knockout; Mice, Transgenic; Inflammation Mediators; Granuloma, Respiratory Tract; Lymphoid Tissue; Receptors, CXCR5

Alternative activation of macrophages: mechanism and functions - Gordon, Siamon; Martinez, Fernando O. (Immunity, 2010)
The concept of an alternative pathway of macrophage activation has stimulated interest in its definition, mechanism, and functional significance in homeostasis and disease. We assess recent research in this field, argue for a restricted definition, and explore pathways by which the T helper 2 (Th2) cell cytokines interleukin-4 (IL-4) and IL-13 mediate their effects on macrophage cell biology, their biosynthesis, and responses to a normal and pathological microenvironment. The stage is now set to gain deeper insights into the role of alternatively activated macrophages in immunobiology.
Keywords: Humans; Animals; Macrophages; Cytokines; Macrophage Activation; Signal Transduction; Models, Biological; Neoplasms; Receptors, Interleukin

T helper 2 cytokines inhibit autophagic control of intracellular Mycobacterium tuberculosis - Harris, James; De Haro, Sergio A.; Master, Sharon S.; Keane, Joseph; Roberts, Esteban A.; Delgado, Monica; Deretic, Vojo (Immunity, 2007)
Autophagy is a recently recognized immune effector mechanism against intracellular pathogens. The role of autophagy in innate immunity has been well established, but the extent of its regulation by the adaptive immune response is less well understood. The T helper 1 (Th1) cell cytokine IFN-gamma induces autophagy in macrophages to eliminate Mycobacterium tuberculosis. Here, we report that Th2 cytokines affect autophagy in macrophages and their ability to control intracellular M. tuberculosis. IL-4 and IL-13 abrogated autophagy and autophagy-mediated killing of intracellular mycobacteria in murine and human macrophages. Inhibition of starvation-induced autophagy by IL-4 and IL-13 was dependent on Akt signaling, whereas the inhibition of IFN-gamma-induced autophagy was Akt independent and signal transducer and activator of transcription 6 (STAT6) dependent. These findings establish a mechanism through which Th1-Th2 polarization differentially affects the immune control of intracellular pathogens.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Animals; Macrophages; Immunoblotting; Flow Cytometry; Mice; Interferon-gamma; Cytokines; Phagosomes; Autophagy; Interleukin-13; Interleukin-4; Microscopy, Confocal; Proto-Oncogene Proteins c-akt; STAT6 Transcription Factor; Th2 Cells; Transfection

An antimicrobial activity of cytolytic T cells mediated by granulysin - Stenger, S.; Hanson, D. A.; Teitelbaum, R.; Dewan, P.; Niazi, K. R.; Froelich, C. J.; Ganz, T.; Thoma-Uszynski, S.; Melián, A.; Bogdan, C.; Porcelli, S. A.; Bloom, B. R.; et al. (Science (New York, N.Y.), 1998)
Cytolytic T lymphocytes (CTLs) kill intracellular pathogens by a granule-dependent mechanism. Granulysin, a protein found in granules of CTLs, reduced the viability of a broad spectrum of pathogenic bacteria, fungi, and parasites in vitro. Granulysin directly killed extracellular Mycobacterium tuberculosis, altering the membrane integrity of the bacillus, and, in combination with perforin, decreased the viability of intracellular M. tuberculosis. The ability of CTLs to kill intracellular M. tuberculosis was dependent on the presence of granulysin in cytotoxic granules, defining a mechanism by which T cells directly contribute to immunity against intracellular pathogens.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Macrophages; Cell Membrane; Recombinant Proteins; Cells, Cultured; Membrane Glycoproteins; Microscopy, Confocal; Antigens, Differentiation, T-Lymphocyte; Cytoplasmic Granules; Cytotoxicity, Immunologic; Microscopy, Electron, Scanning; Perforin; Pore Forming Cytotoxic Proteins; T-Lymphocytes, Cytotoxic

Th1 and Th17 Cells in Tuberculosis: Protection, Pathology, and Biomarkers - Lyadova, I. V.; Panteleev, A. V. (Mediators of Inflammation, 2015)
The outcome of Mycobacterium tuberculosis (Mtb) infection ranges from a complete pathogen clearance through asymptomatic latent infection (LTBI) to active tuberculosis (TB) disease. It is now understood that LTBI and active TB represent a continuous spectrum of states with different degrees of pathogen "activity," host pathology, and immune reactivity. Therefore, it is important to differentiate LTBI and active TB and identify active TB stages. CD4(+) T cells play critical role during Mtb infection by mediating protection, contributing to inflammation, and regulating immune response. Th1 and Th17 cells are the main effector CD4(+) T cells during TB. Th1 cells have been shown to contribute to TB protection by secreting IFN-γ and activating antimycobacterial action in macrophages. Th17 induce neutrophilic inflammation, mediate tissue damage, and thus have been implicated in TB pathology. In recent years new findings have accumulated that alter our view on the role of Th1 and Th17 cells during Mtb infection. This review discusses these new results and how they can be implemented for TB diagnosis and monitoring.
Keywords: Humans; Animals; Host-Pathogen Interactions; Cell Differentiation; Tuberculosis, Pulmonary; Mice; Interferon-gamma; Cytokines; Biomarkers; Th1 Cells; Latent Tuberculosis; Lymphocyte Activation; Th17 Cells; Interleukin-17

Mycobacterium tuberculosis-specific CD8+ T cells require perforin to kill target cells and provide protection in vivo - Woodworth, Joshua S.; Wu, Ying; Behar, Samuel M. (Journal of Immunology (Baltimore, Md.: 1950), 2008)
Optimal immunity to Mycobacterium tuberculosis (Mtb) infection requires CD8(+) T cells, and several current Mtb vaccine candidates are being engineered to elicit enhanced CD8(+) T cell responses. However, the function of these T cells and the mechanism by which they provide protection is still unknown. We have previously shown that CD8(+) T cells specific for the mycobacterial Ags CFP10 and TB10.4 accumulate in the lungs of mice following Mtb infection and have cytolytic activity in vivo. In this study, we determine which cytolytic pathways are used by these CD8(+) T cells during Mtb infection. We find that Mtb-specific CD8(+) T cells lacking perforin have reduced cytolytic capacity in vivo. In the absence of perforin, the residual cytolytic activity is CD95 and TNFR dependent. This is particularly true in Mtb-infected lung tissue where disruption of both perforin and CD95 eliminates target cell lysis. Moreover, adoptive transfer of immune CD8(+) T cells isolated from wild-type, but not perforin-deficient mice, protect recipient mice from Mtb infection. We conclude that CD8(+) T cells elicited following Mtb infection use several cytolytic pathways in a hierarchical and compensatory manner dominated by perforin-mediated cytolysis. Finally, although several cytolytic pathways are available, adoptively transferred Mtb-specific CD8(+) T cells require perforin-mediated cytolysis to protect animals from infection. These data show that CD8(+) T cell-mediated protection during Mtb infection requires more than the secretion of IFN-gamma and specifically defines the CD8(+) cytolytic mechanisms utilized and required in vivo.
Keywords: Amino Acid Sequence; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Mice; Female; CD4-Positive T-Lymphocytes; Mice, Inbred C57BL; Adoptive Transfer; Mice, Knockout; Mice, Transgenic; Perforin; T-Lymphocytes, Cytotoxic; Cytotoxicity Tests, Immunologic; Epitopes, T-Lymphocyte; Histocompatibility Antigens Class I

CD8- and CD95/95L-dependent mechanisms of resistance in mice with chronic pulmonary tuberculosis - Turner, J.; D'Souza, C. D.; Pearl, J. E.; Marietta, P.; Noel, M.; Frank, A. A.; Appelberg, R.; Orme, I. M.; Cooper, A. M. (American Journal of Respiratory Cell and Molecular Biology, 2001)
The role of CD8 T lymphocytes in the immune response to Mycobacterium tuberculosis infection remains enigmatic, with persuasive reports of both cytolytic and noncytolytic (cytokine-mediated) responses to infection. To address the importance of the cytolytic mechanisms, mice with targeted disruptions for CD8 and perforin or with gene mutations in the CD95/ CD95L signaling pathway were exposed to pulmonary infection. All mice tested showed no differences in their ability to contain the growth of infection during the early phase of disease. As the chronic phase of the disease ensued, however, both CD8- and CD95/CD95L-deficient mice gradually lost their ability to limit bacterial growth. This was associated with a tendency toward pyogenic inflammation in the lung. This tendency was not seen in the perforin gene-disrupted mice. In CD8 gene-disrupted mice, the ability to generate interferon-gamma secreting T cells was unimpaired. Although these cells were capable of entering the lung they were unable to influence the increasing bacterial load in this organ.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Flow Cytometry; Mice; Lung; Interferon-gamma; Immunity, Innate; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Mice, Inbred C57BL; Signal Transduction; Mice, Knockout; Fas Ligand Protein; fas Receptor; Ligands; Membrane Glycoproteins; CD4 Antigens; Chronic Disease; Enzyme-Linked Immunosorbent Assay

Pro- and anti-apoptotic CD95 signaling in T cells - Paulsen, Maren; Janssen, Ottmar (Cell communication and signaling: CCS, 2011)
The TNF receptor superfamily member CD95 (Fas, APO-1, TNFRSF6) is known as the prototypic death receptor in and outside the immune system. In fact, many mechanisms involved in apoptotic signaling cascades were solved by addressing consequences and pathways initiated by CD95 ligation in activated T cells or other "CD95-sensitive" cell populations. As an example, the binding of the inducible CD95 ligand (CD95L) to CD95 on activated T lymphocytes results in apoptotic cell death. This activation-induced cell death was implicated in the control of immune cell homeostasis and immune response termination. Over the past years, however, it became evident that CD95 acts as a dual function receptor that also exerts anti-apoptotic effects depending on the cellular context. Early observations of a potential non-apoptotic role of CD95 in the growth control of resting T cells were recently reconsidered and revealed quite unexpected findings regarding the costimulatory capacity of CD95 for primary T cell activation. It turned out that CD95 engagement modulates TCR/CD3-driven signal initiation in a dose-dependent manner. High doses of immobilized CD95 agonists or cellular CD95L almost completely silence T cells by blocking early TCR-induced signaling events. In contrast, under otherwise unchanged conditions, lower amounts of the same agonists dramatically augment TCR/CD3-driven activation and proliferation. In the present overview, we summarize these recent findings with a focus on the costimulatory capacity of CD95 in primary T cells and discuss potential implications for the T cell compartment and the interplay between T cells and CD95L-expressing cells including antigen-presenting cells.

CD4(+)CD25(+)FoxP3(+) regulatory T cells suppress Mycobacterium tuberculosis immunity in patients with active disease - Chen, Xinchun; Zhou, Boping; Li, Meizhong; Deng, Qunyi; Wu, Xueqiong; Le, Xiaohua; Wu, Chi; Larmonier, Nicolas; Zhang, Wei; Zhang, Hongmei; Wang, Huosheng; Katsanis, Emmanuel (Clinical Immunology (Orlando, Fla.), 2007)
CD4(+)CD25(+) regulatory T cells (Treg) play a central role in the prevention of autoimmunity and in the control of immune responses by down-regulating the function of effector CD4(+) or CD8(+) T cells. The role of Treg in Mycobacterium tuberculosis infection and persistence is inadequately documented. Therefore, the current study was designed to determine whether CD4(+)CD25(+)FoxP3(+) regulatory T cells may modulate immunity against human tuberculosis (TB). Our results indicate that the number of CD4(+)CD25(+)FoxP3(+) Treg increases in the blood or at the site of infection in active TB patients. The frequency of CD4(+)CD25(+)FoxP3(+) Treg in pleural fluid inversely correlates with local MTB-specific immunity (p<0.002). These CD4(+)CD25(+)FoxP3(+) T lymphocytes isolated from the blood and pleural fluid are capable of suppressing MTB-specific IFN-gamma and IL-10 production in TB patients. Therefore, CD4(+)CD25(+)FoxP3(+) Treg expanded in TB patients suppress M. tuberculosis immunity and may therefore contribute to the pathogenesis of human TB.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; Flow Cytometry; Antitubercular Agents; Cytokines; T-Lymphocyte Subsets; Adult; Middle Aged; Enzyme-Linked Immunosorbent Assay; Forkhead Transcription Factors; Immunohistochemistry; Interleukin-2 Receptor alpha Subunit; Pleural Effusion; T-Lymphocytes, Regulatory; Tuberculosis, Pleural

Tuberculosis vaccine: A journey from BCG to present - Fatima, Samreen; Kumari, Anjna; Das, Gobardhan; Dwivedi, Ved Prakash (Life Sciences, 2020)
Tuberculosis (TB) is the leading cause of death worldwide due to an infectious disease, causing around 1.6 million deaths each year. This situation has become more complicated by the emergence of drug-resistant Mycobacterium tuberculosis (M.tb) and HIV-TB co-infection, which has significantly worsened TB prognosis and treatment. Despite years of intensive research, Bacille Calmette-Guerin (BCG) remains the only licensed vaccine and has variable efficacy. It provides protection against childhood TB but is not effective in adult pulmonary TB. As a result of intense research in understanding TB vaccinology, there are many new vaccine candidates in clinical development and many more in pre-clinical trials which aim either to replace or boost BCG vaccine. This review discusses the history of BCG vaccine development and summarizes limitations of the current vaccine strategy and recent advances in improving BCG immunization along with other new vaccines in clinical trials which are promising candidates for the future tuberculosis vaccinology program.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; Vaccine; BCG Vaccine; Cytokines; Adult; Vaccination; BCG; Child; Age Factors; Memory cells; T helper cells

New vaccines for tuberculosis - Kaufmann, Stefan H. E.; Hussey, Gregory; Lambert, Paul-Henri (Lancet (London, England), 2010)
New vaccines are urgently needed if we want to reach the goal of substantially reducing the incidence of tuberculosis by 2050. Despite a steady increase in funding over the past decade, there is still a striking financial shortfall for vaccine research and development for tuberculosis. Yet, around ten vaccine candidates have left the laboratory stage and entered clinical trials. These vaccines are either aimed at replacing the present vaccine, BCG, or at enhancing immunity induced by BCG. However, these pre-exposure candidates are designed for prevention of disease and will therefore neither eradicate the pathogen, nor prevent stable infection. Long-term vaccination strategies need to target these more ambitious goals. Even though vaccine development will have a price, the return of investment will greatly exceed original costs.
Keywords: Humans; Tuberculosis Vaccines; Tuberculosis; BCG Vaccine

New tuberculosis vaccines - Martín Montañés, Carlos; Gicquel, Brigitte (Enfermedades Infecciosas Y Microbiologia Clinica, 2011)
The current tuberculosis (TB) vaccine, bacille Calmette-Guerin (BCG), is a live vaccine used worldwide, as it protects against severe forms of the disease, saving thousands of lives every year, but its efficacy against pulmonary forms of TB, responsible for transmission of the diseases, is variable. For more than 80 years now no new TB vaccines have been successfully developed. Over the last decade the effort of the scientific community has resulted in the design and construction of promising vaccine candidates. The goal is to develop a new generation of vaccines effective against respiratory forms of the disease. We will focus this review on new prophylactic vaccine candidates that aim to prevent TB diseases. Two are the main strategies used to improve the immunity conferred by the current BCG vaccine, by boosting it with new subunit vaccines, and a second strategy is focused on the construction of new more effective live vaccines, capable to replace the current BCG and to be used as prime vaccines. After rigorous preclinical studies in different animal models new TB vaccine candidates enter in clinical trials in humans. First, a small Phase I for safety followed by immunological evaluation in Phase II trials and finally evaluated in large population Phase III efficacy trials in endemic countries. At present BCG prime and boost with different subunit vaccine candidates are the more advanced assessed in Phase II. Two prime vaccines (based on recombinant BCG) have been successfully evaluated for safety in Phase I trials. A short number of live attenuated vaccines are in advance preclinical studies and the candidates ready to enter Phase I safety trials are produced under current good manufacturing practices.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Drug Design; BCG Vaccine; Drug Evaluation, Preclinical; Practice Guidelines as Topic; Vaccines, Attenuated; Adult; Vaccination; Vaccines, Subunit; Child; Clinical Trials as Topic; Consensus Development Conferences as Topic

Trained immunity contributes to the prevention of Mycobacterium tuberculosis infection, a novel role of autophagy - Zhou, Jie; Lv, Jingzhu; Carlson, Chelsea; Liu, Hui; Wang, Hongtao; Xu, Tao; Wu, Fengjiao; Song, Chuanwang; Wang, Xiaojing; Wang, Ting; Qian, Zhongqing (Emerging Microbes & Infections, 2021)
Mycobacterium tuberculosis (M. tuberculosis) is the pathogen which causes tuberculosis (TB), a significant human public health threat. Co-infection of M. tuberculosis and the human immunodeficiency virus (HIV), emergence of drug resistant M. tuberculosis, and failure to develop highly effective TB vaccines have limited control of the TB epidemic. Trained immunity is an enhanced innate immune response which functions independently of the adaptive/acquired immune system and responds non-specifically to reinfection with invading agents. Recently, several studies have found trained immunity has the capability to control and eliminate M. tuberculosis infection. Over the past decades, however, the consensus was adaptive immunity is the only protective mechanism by which hosts inhibit M. tuberculosis growth. Furthermore, autophagy plays an essential role in the development of trained immunity. Further investigation of trained immunity, M. tuberculosis infection, and the role of autophagy in this process provide new possibilities for vaccine development. In this review, we present the general characteristics of trained immunity and autophagy. We additionally summarize several examples where initiation of trained immunity contributes to the prevention of M. tuberculosis infection and propose future directions for research in this area.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; vaccine; Adaptive Immunity; Immunity, Innate; Immunologic Memory; Vaccination; Autophagy; autophagy; epigenetic reprogramming; mycobacterium tuberculosis; trained immunity

Towards new TB vaccines: What are the challenges? - Dockrell, Hazel M. (Pathogens and Disease, 2016)
New and effective tuberculosis (TB) vaccines are urgently needed to control pulmonary TB, and in particular to prevent the spread of drug-resistant strains of Mycobacterium tuberculosis. These drug-resistant strains can range from those resistant to first-line drugs to those that are almost impossible to treat. To develop new and effective vaccines for HIV and malaria has been difficult and it is proving to be just as challenging for TB. TB is a complicated disease with a spectrum from apparently controlled latent infection to active clinical disease and so different types of preventive or post-exposure vaccine may be needed. Identifying the most promising vaccine candidates to move into clinical trials is difficult, as we lack biomarker signatures that can predict protective efficacy. There is a risk that the failure of the MVA-85A vaccine to show efficacy when given to previously BCG-vaccinated South African infants will impact on the resources available for the development and trials of other candidate TB vaccines. Continued support for the development of new TB vaccines should remain a priority as an effective vaccine would bring huge public health benefits.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; BCG Vaccine; Clinical Trials as Topic; Outcome Assessment, Health Care; Tuberculosis, Multidrug-Resistant

The methodology for determining the efficacy of antibody-mediated immunity - Casadevall, Arturo (Journal of Immunological Methods, 2004)
The basic method for evaluating the efficacy of antibody-mediated immunity (AMI) dates from the 1890s and involves the administration of specific Ab to an immunologically naïve host followed by microbial or toxin challenge. Other methods used to evaluate AMI involve correlating the presence of specific Ab with resistance to microbial disease and associating susceptibility to certain microbes with host immunoglobulin deficits. Unfortunately, each method has theoretical and practical problems that limit their usefulness when negative results are obtained. The application of hybridoma technology to investigate the efficacy of AMI has shown that it is possible to generate protective monoclonal antibodies even to microbes for which the standard methodologies indicate no role for AMI. Furthermore, studies with monoclonal antibodies suggest various explanations for the inability of standard methods to demonstrate the potential efficacy of AMI for certain pathogens.
Keywords: Humans; Animals; Antibodies; Models, Immunological; Antibody Formation; Bacteria; Time Factors

The role of B cells and humoral immunity in Mycobacterium tuberculosis infection - Chan, John; Mehta, Simren; Bharrhan, Sushma; Chen, Yong; Achkar, Jacqueline M.; Casadevall, Arturo; Flynn, JoAnne (Seminars in Immunology, 2014)
Mycobacterium tuberculosis remains a major public health burden. It is generally thought that while B cell- and antibody-mediated immunity plays an important role in host defense against extracellular pathogens, the primary control of intracellular microbes derives from cellular immune mechanisms. Studies on the immune regulatory mechanisms during infection with M. tuberculosis, a facultative intracellular organism, has established the importance of cell-mediated immunity in host defense during tuberculous infection. Emerging evidence suggest a role for B cell and humoral immunity in the control of intracellular pathogens, including obligatory species, through interactions with the cell-mediated immune compartment. Recent studies have shown that B cells and antibodies can significantly impact on the development of immune responses to the tubercle bacillus. In this review, we present experimental evidence supporting the notion that the importance of humoral and cellular immunity in host defense may not be entirely determined by the niche of the pathogen. A comprehensive approach that examines both humoral and cellular immunity could lead to better understanding of the immune response to M. tuberculosis.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Antibodies; Host-Pathogen Interactions; Tuberculosis; Tuberculosis, Pulmonary; Mice; Granuloma; Lung; Cytokines; Immunity, Cellular; B cells; B-Lymphocytes; Immunity, Humoral; Receptors, IgG; Antigen Presentation; FcγR; Immunoglobulin M

B cells and antibodies in the defense against Mycobacterium tuberculosis infection - Achkar, Jacqueline M.; Chan, John; Casadevall, Arturo (Immunological Reviews, 2015)
Better understanding of the immunological components and their interactions necessary to prevent or control Mycobacterium tuberculosis (Mtb) infection in humans is critical for tuberculosis (TB) vaccine development strategies. Although the contributory role of humoral immunity in the protection against Mtb infection and disease is less defined than the role of T cells, it has been well-established for many other intracellular pathogens. Here we update and discuss the increasing evidence and the mechanisms of B cells and antibodies in the defense against Mtb infection. We posit that B cells and antibodies have a variety of potential protective roles at each stage of Mtb infection and postulate that such roles should be considered in the development strategies for TB vaccines and other immune-based interventions.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; tuberculosis; Immunity, Innate; Immunity, Cellular; antibodies; B-Lymphocytes; Immunity, Humoral; B lymphocytes; Cell Communication; immunity; immunoglobulins

Antibodies and tuberculosis: finally coming of age? - Li, Hao; Javid, Babak (Nature Reviews. Immunology, 2018)
Are antibodies important for protection against tuberculosis? The jury has been out for more than 100 years. B cell depletion in experimental Mycobacterium tuberculosis infection failed to identify a major role for these cells in immunity to tuberculosis. However, recent identification of naturally occurring antibodies in humans that are protective during M. tuberculosis infection has reignited the debate. Here, we discuss the evidence for a protective role for antibodies in tuberculosis and consider the feasibility of designing novel tuberculosis vaccines targeting humoral immunity.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; Immunity, Innate; Models, Immunological; B-Lymphocytes; Immunity, Humoral

Lipoproteins are major targets of the polyclonal human T cell response to Mycobacterium tuberculosis - Seshadri, Chetan; Turner, Marie T.; Lewinsohn, David M.; Moody, D. Branch; Van Rhijn, Ildiko (Journal of Immunology (Baltimore, Md.: 1950), 2013)
Most vaccines and basic studies of T cell epitopes in Mycobacterium tuberculosis emphasize water-soluble proteins that are secreted into the extracellular space and presented in the context of MHC class II. Much less is known about the role of Ags retained within the cell wall. We used polyclonal T cells from infected humans to probe for responses to immunodominant Ags in the M. tuberculosis cell wall. We found that the magnitude of response to secreted or cell wall intrinsic compounds was similar among healthy controls, patients with latent tuberculosis, and patients with active tuberculosis. Individual responses to secreted Ags and cell wall extract were strongly correlated (r(2) = 0.495, p = 0.001), suggesting that T cells responding to cell wall and secreted Ags are present at similar frequency. Surprisingly, T cell stimulatory factors intrinsic to the cell wall partition into organic solvents; however, these responses are not explained by CD1-mediated presentation of lipids. Instead, we find that molecules soluble in organic solvents are dependent upon MHC class II and recognized by IFN-γ-secreting CD4(+) T cells. We reasoned that MHC class II-dependent Ags extracting into lipid mixtures might be found among triacylated lipoproteins present in mycobacteria. We used M. tuberculosis lacking prolipoprotein signal peptidase A (lspA), an enzyme required for lipoprotein synthesis, to demonstrate loss of polyclonal T cell responses. Our results demonstrate the use of bacterial genetics to identify lipoproteins as an unexpected and immunodominant class of cell wall-associated Ags targeted by the polyclonal human T cell response to M. tuberculosis.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Lipoproteins; Antigens, Bacterial; Cell Wall; Female; Adjuvants, Immunologic; T-Lymphocyte Subsets; Adult; Male; Middle Aged; Lymphocyte Activation; Clone Cells; Immunodominant Epitopes

CD1b Tetramers Identify T Cells that Recognize Natural and Synthetic Diacylated Sulfoglycolipids from Mycobacterium tuberculosis - James, Charlotte A.; Yu, Krystle K. Q.; Gilleron, Martine; Prandi, Jacques; Yedulla, Vijayendar R.; Moleda, Zuzanna Z.; Diamanti, Eleonora; Khan, Momin; Aggarwal, Varinder K.; Reijneveld, Josephine F.; Reinink, Peter; Lenz, Stefanie; et al. (Cell Chemical Biology, 2018)
Mycobacterial cell wall lipids bind the conserved CD1 family of antigen-presenting molecules and activate T cells via their T cell receptors (TCRs). Sulfoglycolipids (SGLs) are uniquely synthesized by Mycobacterium tuberculosis, but tools to study SGL-specific T cells in humans are lacking. We designed a novel hybrid synthesis of a naturally occurring SGL, generated CD1b tetramers loaded with natural or synthetic SGL analogs, and studied the molecular requirements for TCR binding and T cell activation. Two T cell lines derived using natural SGLs are activated by synthetic analogs independently of lipid chain length and hydroxylation, but differentially by saturation status. By contrast, two T cell lines derived using an unsaturated SGL synthetic analog were not activated by the natural antigen. Our data provide a bioequivalence hierarchy of synthetic SGL analogs and SGL-loaded CD1b tetramers. These reagents can now be applied to large-scale translational studies investigating the diagnostic potential of SGL-specific T cell responses or SGL-based vaccines.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Models, Molecular; tuberculosis; T-Lymphocytes; Lymphocyte Activation; Acylation; antigen-presentation; Antigens, CD1; CD1; Glycolipids; human; lipid antigen; mycobacteria; Protein Multimerization; T cell receptor; T cells

CD1b Tetramers Broadly Detect T Cells That Correlate With Mycobacterial Exposure but Not Tuberculosis Disease State - Lopez, Kattya; Iwany, Sarah K.; Suliman, Sara; Reijneveld, Josephine F.; Ocampo, Tonatiuh A.; Jimenez, Judith; Calderon, Roger; Lecca, Leonid; Murray, Megan B.; Moody, D. Branch; Van Rhijn, Ildiko (Frontiers in Immunology, 2020)
The non-polymorphic nature of CD1 proteins creates a situation in which T cells with invariant T cell receptors (TCRs), like CD1d-specific NKT cells, are present in all humans. CD1b is an abundant protein on human dendritic cells that presents M. tuberculosis (Mtb) lipid antigens to T cells. Analysis of T cell clones suggested that semi-invariant TCRs exist in the CD1b system, but their prevalence in humans is not known. Here we used CD1b tetramers loaded with mycolic acid or glucose monomycolate to study polyclonal T cells from 150 Peruvian subjects. We found that CD1b tetramers loaded with mycolic acid or glucose monomycolate antigens stained TRAV1-2+ GEM T cells or TRBV4-1+ LDN5-like T cells in the majority of subjects tested, at rates ~10-fold lower than NKT cells. Thus, GEM T cells and LDN5-like T cells are a normal part of the human immune system. Unlike prior studies measuring MHC- or CD1b-mediated activation, this large-scale tetramer study found no significant differences in rates of CD1b tetramer-mycobacterial lipid staining of T cells among subjects with Mtb exposure, latent Mtb infection or active tuberculosis (TB) disease. In all subjects, including "uninfected" subjects, CD1b tetramer+ T cells expressed memory markers at high levels. However, among controls with lower mycobacterial antigen exposure in Boston, we found significantly lower frequencies of T cells staining with CD1b tetramers loaded with mycobacterial lipids. These data link CD1b-specific T cell detection to mycobacterial exposure, but not TB disease status, which potentially explains differences in outcomes among CD1-based clinical studies, which used control subjects with low Mtb exposure.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; tuberculosis; Female; T-Lymphocytes; Adult; Male; Middle Aged; Antigens, CD1; Glycolipids; mycobacteria; T cell receptor; CD1b; glycolipids; Leukocyte Common Antigens; Mycolic Acids; Receptors, Antigen, T-Cell; tetramer

Deciphering the biology of Mycobacterium tuberculosis from the complete genome sequence - Cole, S. T.; Brosch, R.; Parkhill, J.; Garnier, T.; Churcher, C.; Harris, D.; Gordon, S. V.; Eiglmeier, K.; Gas, S.; Barry, C. E.; Tekaia, F.; Badcock, K.; et al. (Nature, 1998)
Countless millions of people have died from tuberculosis, a chronic infectious disease caused by the tubercle bacillus. The complete genome sequence of the best-characterized strain of Mycobacterium tuberculosis, H37Rv, has been determined and analysed in order to improve our understanding of the biology of this slow-growing pathogen and to help the conception of new prophylactic and therapeutic interventions. The genome comprises 4,411,529 base pairs, contains around 4,000 genes, and has a very high guanine + cytosine content that is reflected in the biased amino-acid content of the proteins. M. tuberculosis differs radically from other bacteria in that a very large portion of its coding capacity is devoted to the production of enzymes involved in lipogenesis and lipolysis, and to two new families of glycine-rich proteins with a repetitive structure that may represent a source of antigenic variation.
Keywords: Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Tuberculosis; Sequence Analysis, DNA; Genome, Bacterial; Chromosome Mapping; Chromosomes, Bacterial; Drug Resistance, Microbial; Lipid Metabolism

TB Vaccine Pipeline - WGNV (Working Group on New TB Vaccines, 2022)
TB Vaccine Pipeline TB Vaccine Pipeline Sortable Pipeline This Pipeline currently provides information on vaccine candidates in clinical development. Information on candidates in preclinical developments is currently being collected. These candidates will be added to the Pipeline when the information is available. If you would like to submit a vaccine candidate for inclusion in the…

Tuberculosis vaccines: Opportunities and challenges - Zhu, Bingdong; Dockrell, Hazel M.; Ottenhoff, Tom H. M.; Evans, Thomas G.; Zhang, Ying (Respirology (Carlton, Vic.), 2018)
Tuberculosis (TB) is a serious disease around the world. Bacillus Calmette-Guérin (BCG) is the only TB vaccine licensed for use in human beings, and is effective in protecting infants and children against severe miliary and meningeal TB. However, BCG's protective efficacy is variable in adults. Novel TB vaccine candidates being developed include whole-cell vaccines (recombinant BCG (rBCG), attenuated Mycobacterium tuberculosis, killed M. tuberculosis or Mycobacterium vaccae), adjuvanted protein subunit vaccines, viral vector-delivered subunit vaccines, plasmid DNA vaccines, RNA-based vaccines etc. At least 12 novel TB vaccine candidates are now in clinical trials, including killed M. vaccae, rBCG ΔureC::hly, adjuvanted fusion proteins M72 and H56 and viral vectored MVA85A. Unfortunately, in TB, there are no correlates of vaccine-induced protection, although cell-mediated immune responses such as interferon-gamma (IFN-γ) production are widely used to assess vaccine's immunogenicity. Recent studies suggested that central memory T cells and local secreted IgA correlated with protection against TB disease. Clinical TB vaccine efficacy trials should invest in identifying correlates of protection, and evaluate new TB biomarkers emerging from human and animal studies. Accumulating new knowledge on M. tuberculosis antigens and immune profiles correlating with protection or disease risk will be of great help in designing next generation of TB vaccines.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; tuberculosis; BCG Vaccine; Vaccines, DNA; Adjuvants, Immunologic; Biomarkers; Vaccines, Attenuated; Clinical Trials as Topic; immunity; biomarkers; clinical trials; Immunogenicity, Vaccine; vaccines; Vaccines, Inactivated

Validating subcellular localization prediction tools with mycobacterial proteins - Restrepo-Montoya, Daniel; Vizcaíno, Carolina; Niño, Luis F.; Ocampo, Marisol; Patarroyo, Manuel E.; Patarroyo, Manuel A. (BMC bioinformatics, 2009)
BACKGROUND: The computational prediction of mycobacterial proteins' subcellular localization is of key importance for proteome annotation and for the identification of new drug targets and vaccine candidates. Several subcellular localization classifiers have been developed over the past few years, which have comprised both general localization and feature-based classifiers. Here, we have validated the ability of different bioinformatics approaches, through the use of SignalP 2.0, TatP 1.0, LipoP 1.0, Phobius, PA-SUB 2.5, PSORTb v.2.0.4 and Gpos-PLoc, to predict secreted bacterial proteins. These computational tools were compared in terms of sensitivity, specificity and Matthew's correlation coefficient (MCC) using a set of mycobacterial proteins having less than 40% identity, none of which are included in the training data sets of the validated tools and whose subcellular localization have been experimentally confirmed. These proteins belong to the TBpred training data set, a computational tool specifically designed to predict mycobacterial proteins. RESULTS: A final validation set of 272 mycobacterial proteins was obtained from the initial set of 852 mycobacterial proteins. According to the results of the validation metrics, all tools presented specificity above 0.90, while dispersion sensitivity and MCC values were above 0.22. PA-SUB 2.5 presented the highest values; however, these results might be biased due to the methodology used by this tool. PSORTb v.2.0.4 left 56 proteins out of the classification, while Gpos-PLoc left just one protein out. CONCLUSION: Both subcellular localization approaches had high predictive specificity and high recognition of true negatives for the tested data set. Among those tools whose predictions are not based on homology searches against SWISS-PROT, Gpos-PLoc was the general localization tool with the best predictive performance, while SignalP 2.0 was the best tool among the ones using a feature-based approach. Even though PA-SUB 2.5 presented the highest metrics, it should be taken into account that this tool was trained using all proteins reported in SWISS-PROT, which includes the protein set tested in this study, either as a BLAST search or as a training model.
Keywords: Bacterial Proteins; Computational Biology; Algorithms; Databases, Protein; Mycobacterium; Software

Computational prediction and experimental assessment of secreted/surface proteins from Mycobacterium tuberculosis H37Rv - Vizcaíno, Carolina; Restrepo-Montoya, Daniel; Rodríguez, Diana; Niño, Luis F.; Ocampo, Marisol; Vanegas, Magnolia; Reguero, María T.; Martínez, Nora L.; Patarroyo, Manuel E.; Patarroyo, Manuel A. (PLoS computational biology, 2010)
The mycobacterial cell envelope has been implicated in the pathogenicity of tuberculosis and therefore has been a prime target for the identification and characterization of surface proteins with potential application in drug and vaccine development. In this study, the genome of Mycobacterium tuberculosis H37Rv was screened using Machine Learning tools that included feature-based predictors, general localizers and transmembrane topology predictors to identify proteins that are potentially secreted to the surface of M. tuberculosis, or to the extracellular milieu through different secretory pathways. The subcellular localization of a set of 8 hypothetically secreted/surface candidate proteins was experimentally assessed by cellular fractionation and immunoelectron microscopy (IEM) to determine the reliability of the computational methodology proposed here, using 4 secreted/surface proteins with experimental confirmation as positive controls and 2 cytoplasmic proteins as negative controls. Subcellular fractionation and IEM studies provided evidence that the candidate proteins Rv0403c, Rv3630, Rv1022, Rv0835, Rv0361 and Rv0178 are secreted either to the mycobacterial surface or to the extracellular milieu. Surface localization was also confirmed for the positive controls, whereas negative controls were located on the cytoplasm. Based on statistical learning methods, we obtained computational subcellular localization predictions that were experimentally assessed and allowed us to construct a computational protocol with experimental support that allowed us to identify a new set of secreted/surface proteins as potential vaccine candidates.
Keywords: Antibodies, Bacterial; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Computational Biology; Epitopes, B-Lymphocyte; Bacterial Outer Membrane Proteins; Artificial Intelligence; Cell Fractionation; Electrophoresis, Polyacrylamide Gel; Escherichia coli; Immunoblotting; Models, Statistical; Mycobacterium smegmatis; Sonication; Subcellular Fractions

Recent advances in the development of a chemically synthesised anti-malarial vaccine - Curtidor, Hernando; Patarroyo, Manuel E.; Patarroyo, Manuel A. (Expert Opinion on Biological Therapy, 2015)
INTRODUCTION: Obtaining an effective antimalarial vaccine has represented one of the biggest public health challenges over the last 50 years. Despite efforts by many laboratories around the world using whole-organism, recombinant proteins and genome-based approaches, the results have been disappointing. One of the main problems when designing an antimalarial vaccine is the poor immunogenicity induced by the functionally relevant and conserved protein regions of the parasite. AREAS COVERED: This review focuses on the logical and rational methodology followed to identify Plasmodium falciparum conserved functional regions with the ability to bind to target cells conserved high activity binding peptides (cHABPs) and the physicochemical and immunological characteristics that should be taken into account for modifying them into highly immunogenic and protection-inducing peptides (mHABPs) into highly immunogenic and protection-inducing in Aotus monkeys. EXPERT OPINION: The functional approach taken to develop a fully protective, minimal subunit-based, multiantigenic, multistage and synthetic peptide-based antimalarial vaccine has shown promising results. The clear relationship observed between mHABPs structure and their immunological properties highlights the challenges and opportunities arising from this methodology, as well as the universal principles and rules derived therefrom.
Keywords: Humans; Peptides; Protein Binding; Vaccines, Synthetic; Recombinant Proteins; vaccine; Vaccines, Subunit; Malaria Vaccines; Plasmodium falciparum; malaria; Malaria; Plasmodium; Protozoan Proteins; rational design; synthetic peptides

Steric-electronic effects in malarial peptides inducing sterile immunity - Moreno-Vranich, Armando; Patarroyo, Manuel E. (Biochemical and Biophysical Research Communications, 2012)
Conserved Plasmodium falciparum high activity binding peptides' (HABPs) most relevant proteins involved in malaria parasite invasion are immunologically silent; critical binding residues must therefore be specifically replaced to render them highly immunogenic and protection-inducing. Such changes have a tremendous impact on these peptides' steric-electronic effects, such as modifications to peptide length peptide bonds and electronic orbitals' disposition, to allow a better fit into immune system MHCII molecules and better interaction with the TCR which might account for the final immunological outcome.
Keywords: Animals; Peptides; Protein Conformation; Immunity; Plasmodium falciparum; Receptors, Antigen, T-Cell; Malaria; Aotus trivirgatus; Electrons; Immune System

Double dimer peptide constructs are immunogenic and protective against Plasmodium falciparum in the experimental Aotus monkey model - Rivera, Z.; Granados, G.; Pinto, M.; Varón, D.; Carvajal, C.; Chaves, F.; Calvo, J.; Rodríguez, R.; Guzmán, F.; Patarroyo, M. E. (The Journal of Peptide Research: Official Journal of the American Peptide Society, 2002)
Multiple antigen peptide constructs (MAPs) have been used to obtain defined multimeric peptide molecules useful in the development of possible synthetic malaria vaccines. In this context, a method was developed, named double dimer constructs (DDCs), involving the direct synthesis of a dimeric peptide with a C-terminal cysteine. A tetrameric molecule was then obtained by oxidation of sulfhydryl groups. Dimer synthesis was optimized using a Fmoc/tBu strategy, dimers were purified by HPLC, oxidized with DMSO and characterized by HPLC and MALDI-TOF-MS. The tetramers or DDCs obtained by this method were used as immunogens in the search for a possible malaria vaccine. It was found that they were immunogenic in the experimental Aotus monkey model, and were able to induce protective immunity when challenged experimentally with a highly infective Plasmodium falciparum malaria strain.
Keywords: Amino Acid Sequence; Molecular Sequence Data; Animals; Plasmodium falciparum; Aotus trivirgatus; Antigens, Protozoan; Dimerization; Fluorescent Antibody Technique, Indirect

Structural Insights Into HLA-DM Mediated MHC II Peptide Exchange - Painter, Corrie A.; Stern, Lawrence J. (Current Topics in Biochemical Research, 2011)
Antigen presentation by class II MHC proteins (MHC-II) is a critical component of the adaptive immune response to foreign pathogens. Our understanding of how antigens are presented has been greatly enhanced by crystallographic studies of MHC-II-peptide complexes, which have shown a canonical extended conformation of peptide antigens within the peptide-binding domain of MHC-II. However, a detailed understanding of the peptide loading process, which is mediated by the accessory molecule HLA-DM (DM), remains unresolved. MHC-II proteins appear to undergo conformational changes during the peptide loading/exchange process that have not been clearly described in a structural context. In the absence of a crystal structure for the DM-MHC-II complex, mutational studies have provided a low resolution understanding as to how these molecules interact. This review will focus on structural and biochemical studies of the MHC-II-peptide interaction, and on studies of the DM-MHC-II interaction, with an emphasis on identifying structural features important for the mechanism of DM mediated peptide catalysis.
Keywords: Antigen Presentation; H2-M; HLA-DP; HLA-DQ; HLA-DR; I-A; I-E; Immune Response; MHC protein

Structural analysis of the HLA-DR, -DQ, and -DP alleles on the celiac disease-associated HLA-DR3 (DRw17) haplotype - Kagnoff, M. F.; Harwood, J. I.; Bugawan, T. L.; Erlich, H. A. (Proceedings of the National Academy of Sciences of the United States of America, 1989)
Celiac disease is strongly associated with the HLA class II D-region serologic markers DR3 (DRw17) and DQw2. Moreover, by restriction fragment length polymorphism analysis, greater than 90% of DR3 (DRw17), DQw2 celiac disease patients have a polymorphic 4.0-kilobase Rsa I DP B gene DNA fragment. The present study sought to determine if there is a unique HLA class II D-region A or B gene structural variant on the DR3 (DRw17) haplotype found in celiac disease. The polymorphic second exons of the coding DRB, DQA and DQB, and DPA and DPB genes in celiac disease patients with the DR3 (DRw17) haplotype were sequenced after amplification by the polymerase chain reaction. To define the DP B genes associated with celiac disease, the second exons of the coding DP B genes from 27 celiac disease patients were amplified similarly and probed by using a panel of sequence specific oligonucleotides. The HLA-DR, -DQ, and -DP A and B gene second exon sequences of celiac disease patients were noted to be identical to sequences that can be found also, although at a significantly lower frequency, in unaffected individuals. This is compatible with a disease model wherein the HLA class II genes on the DR3 (DRw17) haplotype are necessary, but not sufficient, for the phenotypic expression of celiac disease. Analysis of the DP B genes revealed a significant increase in the frequency of the alleles DPB1 and DPB3 in celiac disease. Furthermore, the increased frequency of the 4.0-kilobase Rsa I DP B gene restriction fragment length polymorphism in celiac disease can be accounted for by the overrepresentation in disease of the alleles DPB1 and DPB3. The HLA-associated susceptibility to celiac disease appears to be multigenic, with specific, but structurally normal, allelic variants in the DP and DQ/DR subregions contributing to disease susceptibility.
Keywords: Amino Acid Sequence; Cell Line; Humans; Molecular Sequence Data; Genetic Variation; Alleles; Celiac Disease; DNA-Directed DNA Polymerase; Gene Amplification; Haplotypes; HLA-DP Antigens; HLA-DQ Antigens; HLA-DR Antigens; HLA-DR3 Antigen; Major Histocompatibility Complex

Crystal structure of the HLA-DM-HLA-DR1 complex defines mechanisms for rapid peptide selection - Pos, Wouter; Sethi, Dhruv K.; Call, Melissa J.; Schulze, Monika-Sarah E. D.; Anders, Anne-Kathrin; Pyrdol, Jason; Wucherpfennig, Kai W. (Cell, 2012)
HLA-DR molecules bind microbial peptides in an endosomal compartment and present them on the cell surface for CD4 T cell surveillance. HLA-DM plays a critical role in the endosomal peptide selection process. The structure of the HLA-DM-HLA-DR complex shows major rearrangements of the HLA-DR peptide-binding groove. Flipping of a tryptophan away from the HLA-DR1 P1 pocket enables major conformational changes that position hydrophobic HLA-DR residues into the P1 pocket. These conformational changes accelerate peptide dissociation and stabilize the empty HLA-DR peptide-binding groove. Initially, incoming peptides have access to only part of the HLA-DR groove and need to compete with HLA-DR residues for access to the P2 site and the hydrophobic P1 pocket. This energetic barrier creates a rapid and stringent selection process for the highest-affinity binders. Insertion of peptide residues into the P2 and P1 sites reverses the conformational changes, terminating selection through DM dissociation.
Keywords: Amino Acid Sequence; Humans; Molecular Sequence Data; Animals; Models, Molecular; Protein Conformation; Crystallography, X-Ray; HLA-D Antigens; HLA-DR1 Antigen; Hydrophobic and Hydrophilic Interactions; Protein Interaction Domains and Motifs; Sequence Alignment

Human Leukocyte Antigen (HLA)-DRB1*15:01 and HLA-DRB5*01:01 Present Complementary Peptide Repertoires - Scholz, Erika Margaret; Marcilla, Miguel; Daura, Xavier; Arribas-Layton, David; James, Eddie A.; Alvarez, Iñaki (Frontiers in Immunology, 2017)
Human leukocyte antigen (HLA)-DR15 is a haplotype associated with multiple sclerosis. It contains the two DRB* genes DRB1*1501 (DR2b) and DRB5*0101 (DR2a). The reported anchor motif of the corresponding HLA-DR molecules was determined in 1994 based on a small number of peptide ligands and binding assays. DR2a could display a set of peptides complementary to that presented by DR2b or, alternatively, a similar peptide repertoire but recognized in a different manner by T cells. It is known that DR2a and DR2b share some peptide ligands, although the degree of similarity of their associated peptidomes remains unclear. In addition, the contribution of each molecule to the global peptide repertoire presented by the HLA-DR15 haplotype has not been evaluated. We used mass spectrometry to analyze the peptide pools bound to DR2a and DR2b, identifying 169 and 555 unique peptide ligands of DR2a and DR2b, respectively. The analysis of these sets of peptides allowed the refinement of the corresponding binding motifs revealing novel anchor residues that had been overlooked in previous analyses. Moreover, the number of shared ligands between both molecules was low, indicating that DR2a and DR2b present complementary peptide repertoires to T cells. Finally, our analysis suggests that, quantitatively, both molecules contribute to the peptide repertoire presented by cells expressing the HLA-DR15 haplotype.
Keywords: binding motif; human leukocyte antigen-DR; mass spectrometry; multiple sclerosis; peptidome

A new tool for tuberculosis vaccine screening: Ex vivo Mycobacterial Growth Inhibition Assay indicates BCG-mediated protection in a murine model of tuberculosis - Zelmer, Andrea; Tanner, Rachel; Stylianou, Elena; Damelang, Timon; Morris, Sheldon; Izzo, Angelo; Williams, Ann; Sharpe, Sally; Pepponi, Ilaria; Walker, Barry; Hokey, David A.; McShane, Helen; et al. (BMC infectious diseases, 2016)
BACKGROUND: In the absence of a validated animal model and/or an immune correlate which predict vaccine-mediated protection, large-scale clinical trials are currently the only option to prove efficacy of new tuberculosis candidate vaccines. Tools to facilitate testing of new tuberculosis (TB) vaccines are therefore urgently needed. METHODS: We present here an optimized ex vivo mycobacterial growth inhibition assay (MGIA) using a murine Mycobacterium tuberculosis infection model. This assay assesses the combined ability of host immune cells to inhibit mycobacterial growth in response to vaccination. C57BL/6 mice were immunized with Bacillus Calmette-Guérin (BCG) and growth inhibition of mycobacteria by splenocytes was assessed. Mice were also challenged with Mycobacterium tuberculosis Erdman, and bacterial burden was assessed in lungs and spleen. RESULTS: Using the growth inhibition assay, we find a reduction in BCG CFU of 0.3-0.8 log10 after co-culture with murine splenocytes from BCG vaccinated versus naïve C57BL/6 mice. BCG vaccination in our hands led to a reduction in bacterial burden after challenge with Mycobacterium tuberculosis of approx. 0.7 log10 CFU in lung and approx. 1 log10 CFU in spleen. This effect was also seen when using Mycobacterium smegmatis as the target of growth inhibition. An increase in mycobacterial numbers was found when splenocytes from interferon gamma-deficient mice were used, compared to wild type controls, indicating that immune mechanisms may also be investigated using this assay. CONCLUSIONS: We believe that the ex vivo mycobacterial growth inhibition assay could be a useful tool to help assess vaccine efficacy in future, alongside other established methods. It could also be a valuable tool for determination of underlying immune mechanisms.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Mycobacterium smegmatis; BCG Vaccine; Drug Evaluation, Preclinical; Mice; Disease Models, Animal; Female; Interferon-gamma; Mice, Inbred C57BL; Spleen; Coculture Techniques; Mycobacterium bovis; Vaccination; Colony Count, Microbial; Vaccines; Growth inhibition assay; Mice, Mutant Strains; Mycobacteria

A practical in vitro growth inhibition assay for the evaluation of TB vaccines - Kolibab, Kristopher; Parra, Marcela; Yang, Amy L.; Perera, Liyanage P.; Derrick, Steven C.; Morris, Sheldon L. (Vaccine, 2009)
New vaccines and novel immunization strategies are needed to improve the control of the global tuberculosis epidemic. To facilitate vaccine development, we have been creating in vitro mycobacterial intra-macrophage growth inhibition assays. Here we describe the development of an in vitro assay designed for BSL-2 laboratories which measures the capacity of vaccine-induced immune splenocytes to control the growth of isoniazid-resistant Mycobacterium bovis BCG (INH(r) BCG). The use of the INH(r) BCG as the infecting organism allows the discrimination of BCG bacilli used in murine vaccinations from BCG used in the in vitro assay. In this study, we showed that protective immune responses evoked by four different types of Mycobacterium tuberculosis vaccines [BCG, an ESAT6/Antigen 85B fusion protein formulated in DDA/MPL adjuvant, a DNA vaccine expressing the same fusion protein, and a TB Modified Vaccinia Ankara construct expressing four TB antigens (MVA-4TB)] were detected. Importantly, the levels of vaccine-induced protective immunity seen in the in vitro assay correlated with the results from in vivo protection studies in the mouse model of pulmonary tuberculosis. Furthermore, the growth inhibition data for the INH(r) BCG assay was similar to the previously reported results for a M. tuberculosis infection assay. The cytokine expression profiles at day 7 of the INH(r) BCG growth inhibition studies were also similar but not identical to the cytokine patterns detected in earlier M. tuberculosis co-culture assays. Overall, we have shown that a BSL-2 compatible in vitro growth inhibition assay using INH(r) BCG as the intra-macrophage target organism should be useful in developing and evaluating new TB immunization strategies.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Mice; Vaccines, DNA; Female

In vitro measurement of protective mycobacterial immunity: antigen-specific expansion of T cells capable of inhibiting intracellular growth of bacille Calmette-Guérin - Worku, S.; Hoft, D. F. (Clinical Infectious Diseases: An Official Publication of the Infectious Diseases Society of America, 2000)
We investigated the ability of T cells expanded with mycobacterial antigens from healthy purified protein derivative-reactive donors and bacille Calmette-Guérin (BCG)-vaccinated volunteers to inhibit intracellular growth of BCG. Peripheral blood mononuclear cells were incubated for 7 days with mycobacterial whole lysate, live BCG, tetanus toxoid as control antigen, or medium alone. Autologous monocytes were separated by plastic adherence, allowed to mature for 6 days, and infected with BCG before serving as target cells. Expanded effector cells were cocultured with target cells for 72 h. Cocultures were then treated with 0.2% saponin to lyse infected monocytes and release intracellular BCG. Quantities of viable BCG present in these lysates were studied by colony-forming unit counting and radiometric labeling. We reproducibly found that lymphocytes expanded with mycobacterial whole lysate or live BCG significantly inhibited the intracellular growth of BCG, compared with lymphocytes expanded with tetanus toxoid or rested in medium. In addition, BCG vaccination enhanced the ability of T cells to inhibit intracellular mycobacterial growth in 3 of 5 volunteers. This assay may be useful for estimates of protective immunity induced by tuberculosis vaccines in human trials.
Keywords: Humans; Antigens, Bacterial; Monocytes; BCG Vaccine; T-Lymphocytes; Male; Immunologic Memory; Lymphocyte Activation; Mycobacterium bovis; Vaccination; Tuberculin; Tuberculin Test

Inhibition of mycobacterial growth in vitro following primary but not secondary vaccination with Mycobacterium bovis BCG - Fletcher, Helen A.; Tanner, Rachel; Wallis, Robert S.; Meyer, Joel; Manjaly, Zita-Rose; Harris, Stephanie; Satti, Iman; Silver, Richard F.; Hoft, Dan; Kampmann, Beate; Walker, K. Barry; Dockrell, Hazel M.; et al. (Clinical and vaccine immunology: CVI, 2013)
Despite the widespread use of the Mycobacterium bovis BCG vaccine, there are more than 9 million new cases of tuberculosis (TB) every year, and there is an urgent need for better TB vaccines. TB vaccine candidates are selected for evaluation based in part on the detection of an antigen-specific gamma interferon (IFN-γ) response. The measurement of mycobacterial growth in blood specimens obtained from subjects immunized with investigational TB vaccines may be a better in vitro correlate of in vivo vaccine efficacy. We performed a clinical study with 30 United Kingdom adults who were followed for 6 months to evaluate the abilities of both a whole-blood- and a novel peripheral blood mononuclear cell (PBMC)-based mycobacterial growth inhibition assay to measure a response to primary vaccination and revaccination with BCG. Using cryopreserved PBMCs, we observed a significant improvement in mycobacterial growth inhibition following primary vaccination but no improvement in growth inhibition following revaccination with BCG (P < 0.05). Mycobacterial growth inhibition following primary BCG vaccination was not correlated with purified protein derivative (PPD) antigen-specific IFN-γ enzyme-linked immunospot (ELISPOT) responses. We demonstrate that a mycobacterial growth inhibition assay can detect improved capacity to control growth following primary immunization, but not revaccination, with BCG. This is the first study to demonstrate that an in vitro growth inhibition assay can identify a difference in vaccine responses by comparing both primary and secondary BCG vaccinations, suggesting that in vitro growth inhibition assays may serve as better surrogates of clinical efficacy than the assays currently used for the assessment of candidate TB vaccines.
Keywords: Humans; BCG Vaccine; Female; Leukocytes, Mononuclear; Adult; Male; Middle Aged; Young Adult; Adolescent; Mycobacterium bovis; Vaccination; Healthy Volunteers; United Kingdom

Domain enhanced lookup time accelerated BLAST - Boratyn, Grzegorz M.; Schäffer, Alejandro A.; Agarwala, Richa; Altschul, Stephen F.; Lipman, David J.; Madden, Thomas L. (Biology Direct, 2012)
BACKGROUND: BLAST is a commonly-used software package for comparing a query sequence to a database of known sequences; in this study, we focus on protein sequences. Position-specific-iterated BLAST (PSI-BLAST) iteratively searches a protein sequence database, using the matches in round i to construct a position-specific score matrix (PSSM) for searching the database in round i + 1. Biegert and Söding developed Context-sensitive BLAST (CS-BLAST), which combines information from searching the sequence database with information derived from a library of short protein profiles to achieve better homology detection than PSI-BLAST, which builds its PSSMs from scratch. RESULTS: We describe a new method, called domain enhanced lookup time accelerated BLAST (DELTA-BLAST), which searches a database of pre-constructed PSSMs before searching a protein-sequence database, to yield better homology detection. For its PSSMs, DELTA-BLAST employs a subset of NCBI's Conserved Domain Database (CDD). On a test set derived from ASTRAL, with one round of searching, DELTA-BLAST achieves a ROC5000 of 0.270 vs. 0.116 for CS-BLAST. The performance advantage diminishes in iterated searches, but DELTA-BLAST continues to achieve better ROC scores than CS-BLAST. CONCLUSIONS: DELTA-BLAST is a useful program for the detection of remote protein homologs. It is available under the "Protein BLAST" link at http://blast.ncbi.nlm.nih.gov.
Keywords: Computational Biology; Protein Structure, Tertiary; Algorithms; Databases, Protein; Software; Sequence Analysis, Protein; Sensitivity and Specificity; Time Factors; Sequence Alignment; Internet; Reproducibility of Results; ROC Curve; Search Engine; Sequence Homology, Amino Acid

PSORTb v.2.0: expanded prediction of bacterial protein subcellular localization and insights gained from comparative proteome analysis - Gardy, J. L.; Laird, M. R.; Chen, F.; Rey, S.; Walsh, C. J.; Ester, M.; Brinkman, F. S. L. (Bioinformatics (Oxford, England), 2005)
MOTIVATION: PSORTb v.1.1 is the most precise bacterial localization prediction tool available. However, the program's predictive coverage and recall are low and the method is only applicable to Gram-negative bacteria. The goals of the present work are as follows: increase PSORTb's coverage while maintaining the existing precision level, expand it to include Gram-positive bacteria and then carry out a comparative analysis of localization. RESULTS: An expanded database of proteins of known localization and new modules using frequent subsequence-based support vector machines was introduced into PSORTb v.2.0. The program attains a precision of 96% for Gram-positive and Gram-negative bacteria and predictive coverage comparable to other tools for whole proteome analysis. We show that the proportion of proteins at each localization is remarkably consistent across species, even in species with varying proteome size. AVAILABILITY: Web-based version: http://www.psort.org/psortb. Standalone version: Available through the website under GNU General Public License. CONTACT: psort-mail@sfu.ca, brinkman@sfu.ca SUPPLEMENTARY INFORMATION: http://www.psort.org/psortb/supplementaryinfo.html.
Keywords: Bacterial Proteins; Gene Expression Profiling; Algorithms; Software; Subcellular Fractions; Sequence Analysis, Protein; Sequence Alignment; Gram-Negative Bacteria; Gram-Positive Bacteria; Proteome

Support Vector Machine-based method for predicting subcellular localization of mycobacterial proteins using evolutionary information and motifs - Rashid, Mamoon; Saha, Sudipto; Raghava, Gajendra Ps (BMC bioinformatics, 2007)
BACKGROUND: In past number of methods have been developed for predicting subcellular location of eukaryotic, prokaryotic (Gram-negative and Gram-positive bacteria) and human proteins but no method has been developed for mycobacterial proteins which may represent repertoire of potent immunogens of this dreaded pathogen. In this study, attempt has been made to develop method for predicting subcellular location of mycobacterial proteins. RESULTS: The models were trained and tested on 852 mycobacterial proteins and evaluated using five-fold cross-validation technique. First SVM (Support Vector Machine) model was developed using amino acid composition and overall accuracy of 82.51% was achieved with average accuracy (mean of class-wise accuracy) of 68.47%. In order to utilize evolutionary information, a SVM model was developed using PSSM (Position-Specific Scoring Matrix) profiles obtained from PSI-BLAST (Position-Specific Iterated BLAST) and overall accuracy achieved was of 86.62% with average accuracy of 73.71%. In addition, HMM (Hidden Markov Model), MEME/MAST (Multiple Em for Motif Elicitation/Motif Alignment and Search Tool) and hybrid model that combined two or more models were also developed. We achieved maximum overall accuracy of 86.8% with average accuracy of 89.00% using combination of PSSM based SVM model and MEME/MAST. Performance of our method was compared with that of the existing methods developed for predicting subcellular locations of Gram-positive bacterial proteins. CONCLUSION: A highly accurate method has been developed for predicting subcellular location of mycobacterial proteins. This method also predicts very important class of proteins that is membrane-attached proteins. This method will be useful in annotating newly sequenced or hypothetical mycobacterial proteins. Based on above study, a freely accessible web server TBpred http://www.imtech.res.in/raghava/tbpred/ has been developed.
Keywords: Amino Acid Sequence; Bacterial Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Databases, Protein; Artificial Intelligence; Subcellular Fractions; Sequence Analysis, Protein; Pattern Recognition, Automated; Sequence Alignment; Amino Acid Motifs

Evaluation of methods for the prediction of membrane spanning regions - Möller, S.; Croning, M. D.; Apweiler, R. (Bioinformatics (Oxford, England), 2001)
MOTIVATION: A variety of tools are available to predict the topology of transmembrane proteins. To date no independent evaluation of the performance of these tools has been published. A better understanding of the strengths and weaknesses of the different tools would guide both the biologist and the bioinformatician to make better predictions of membrane protein topology. RESULTS: Here we present an evaluation of the performance of the currently best known and most widely used methods for the prediction of transmembrane regions in proteins. Our results show that TMHMM is currently the best performing transmembrane prediction program.
Keywords: Membrane Proteins; Computational Biology; Models, Molecular; Protein Conformation; Software; Solubility; Databases as Topic; Protein Sorting Signals

Laboratory maintenance of Mycobacterium tuberculosis - Larsen, Michelle H.; Biermann, Karolin; Jacobs, William R. (Current Protocols in Microbiology, 2007)
This unit includes protocols for the laboratory maintenance of Mycobacterium tuberculosis, including growth on liquid and solid media as well as recommendations for long-term strain storage. Considerations for working with M. tuberculosis at Biosafety Level 3 containment are also discussed.
Keywords: Humans; Mycobacterium tuberculosis; Bacteriological Techniques; Clinical Laboratory Techniques; Containment of Biohazards; Culture Media; Specimen Handling

General method for the rapid solid-phase synthesis of large numbers of peptides: specificity of antigen-antibody interaction at the level of individual amino acids - Houghten, R. A. (Proceedings of the National Academy of Sciences of the United States of America, 1985)
A novel yet simple method is described that facilitates the synthesis of large numbers of peptides to the extent that the synthesis process need no longer be the limiting factor in many studies involving peptides. By using the methods described, 10-20 mg of 248 different 13-residue peptides representing single amino acid variants of a segment of the hemagglutinin protein (HA1) have been prepared and characterized in less than 4 weeks. Through examination of the binding of these analogs to monoclonal antibodies raised against residues 75-110 of HA1, it was found that a single amino acid, aspartic acid at position 101, is of unique importance to the interaction. Two other residues, aspartic acid-104 and alanine-106, were found to play a lesser but significant role in the binding interaction. Other single positional residue variations appear to be of little or no importance.
Keywords: Amino Acid Sequence; Structure-Activity Relationship; Antibodies, Monoclonal; Enzyme-Linked Immunosorbent Assay; Antibody Specificity; Antigens, Viral; Epitopes; Oligopeptides; Orthomyxoviridae

Solid Phase Peptide Synthesis. I. The Synthesis of a Tetrapeptide - Merrifield, R. B. (Journal of the American Chemical Society, 1963)

B-Pred, a structure based B-cell epitopes prediction server - Giacò, Luciano; Amicosante, Massimo; Fraziano, Maurizio; Gherardini, Pier Federico; Ausiello, Gabriele; Helmer-Citterich, Manuela; Colizzi, Vittorio; Cabibbo, Andrea (Advances and applications in bioinformatics and chemistry: AABC, 2012)
The ability to predict immunogenic regions in selected proteins by in-silico methods has broad implications, such as allowing a quick selection of potential reagents to be used as diagnostics, vaccines, immunotherapeutics, or research tools in several branches of biological and biotechnological research. However, the prediction of antibody target sites in proteins using computational methodologies has proven to be a highly challenging task, which is likely due to the somewhat elusive nature of B-cell epitopes. This paper proposes a web-based platform for scoring potential immunological reagents based on the structures or 3D models of the proteins of interest. The method scores a protein's peptides set, which is derived from a sliding window, based on the average solvent exposure, with a filter on the average local model quality for each peptide. The platform was validated on a custom-assembled database of 1336 experimentally determined epitopes from 106 proteins for which a reliable 3D model could be obtained through standard modeling techniques. Despite showing poor sensitivity, this method can achieve a specificity of 0.70 and a positive predictive value of 0.29 by combining these two simple parameters. These values are slightly higher than those obtained with other established sequence-based or structure-based methods that have been evaluated using the same epitopes dataset. This method is implemented in a web server called B-Pred, which is accessible at http://immuno.bio.uniroma2.it/bpred. The server contains a number of original features that allow users to perform personalized reagent searches by manipulating the sliding window's width and sliding step, changing the exposure and model quality thresholds, and running sequential queries with different parameters. The B-Pred server should assist experimentalists in the rational selection of epitope antigens for a wide range of applications.
Keywords: B-cell epitopes; bioinformatics; epitope prediction; immunoinformatics; web server

Estimation of globular protein secondary structure from circular dichroism - Provencher, S. W.; Glöckner, J. (Biochemistry, 1981)
A new method is developed in which a circular dichroism (CD) spectrum is analyzed directly as a linear combination of the CD spectra (from 190 to 240 nm) of 16 proteins whose secondary structures are known from X-ray crystallography. This avoids the dilemma encountered in previous methods of trying to define single reference CD spectra that were supposed to characterize such broad and variable classes as helix, beta sheet, beta turn, and "remainder". It also permits a more accurate and flexible analysis. The usual instability in using so many parameters is automatically controlled by a simple constrained statistical regularization procedure (similar to ridge regression). Sixteen tests were made by removing 1 spectrum at a time from the set of 16 and analyzing it in terms of the other 15. The product moment correlation coefficients between the computed fractions of helix, beta sheet, beta turn, and remainder and the fractions from the X-ray data were 0.96, 0.94, 0.31,, and 0.49, respectively. Thus, the helix and beta-sheet accuracy is very good. (The corresponding values calculated by a previous method with four reference spectra were 0.85, 0.25, --0.31, and 0.46.).
Keywords: Circular Dichroism; Protein Conformation; Globulins; Spectrophotometry, Ultraviolet; X-Ray Diffraction

Estimation of the number of alpha-helical and beta-strand segments in proteins using circular dichroism spectroscopy - Sreerama, N.; Venyaminov, S. Y.; Woody, R. W. (Protein Science: A Publication of the Protein Society, 1999)
A simple approach to estimate the number of alpha-helical and beta-strand segments from protein circular dichroism spectra is described. The alpha-helix and beta-sheet conformations in globular protein structures, assigned by DSSP and STRIDE algorithms, were divided into regular and distorted fractions by considering a certain number of terminal residues in a given alpha-helix or beta-strand segment to be distorted. The resulting secondary structure fractions for 29 reference proteins were used in the analyses of circular dichroism spectra by the SELCON method. From the performance indices of the analyses, we determined that, on an average, four residues per alpha-helix and two residues per beta-strand may be considered distorted in proteins. The number of alpha-helical and beta-strand segments and their average length in a given protein were estimated from the fraction of distorted alpha-helix and beta-strand conformations determined from the analysis of circular dichroism spectra. The statistical test for the reference protein set shows the high reliability of such a classification of protein secondary structure. The method was used to analyze the circular dichroism spectra of four additional proteins and the predicted structural characteristics agree with the crystal structure data.
Keywords: Circular Dichroism; Animals; Protein Structure, Secondary; Computer Simulation; Databases, Factual; Crystallography, X-Ray; Colicins; Green Fluorescent Proteins; Luminescent Proteins; Rats

Analyzing protein circular dichroism spectra for accurate secondary structures - Johnson, W. C. (Proteins, 1999)
We have developed an algorithm to analyze the circular dichroism of proteins for secondary structure. Its hallmark is tremendous flexibility in creating the basis set, and it also combines the ideas of many previous workers. We also present a new basis set containing the CD spectra of 22 proteins with secondary structures from high quality X-ray diffraction data. High flexibility is obtained by doing the analysis with a variable selection basis set of only eight proteins. Many variable selection basis sets fail to give a good analysis, but good analyses can be selected without any a priori knowledge by using the following criteria: (1) the sum of secondary structures should be close to 1.0, (2) no fraction of secondary structure should be less than -0.03, (3) the reconstructed CD spectrum should fit the original CD spectrum with only a small error, and (4) the fraction of alpha-helix should be similar to that obtained using all the proteins in the basis set. This algorithm gives a root mean square error for the predicted secondary structure for the proteins in the basis set of 3.3% for alpha-helix, 2.6% for 3(10)-helix, 4.2% for beta-strand, 4.2% for beta-turn, 2.7% for poly(L-proline) II type 3(1)-helix, and 5.1% for other structures when compared with the X-ray structure.
Keywords: Circular Dichroism; Protein Structure, Secondary; Algorithms; X-Ray Diffraction

Emerging rules for subunit-based, multiantigenic, multistage chemically synthesized vaccines - Patarroyo, Manuel E.; Patarroyo, Manuel A. (Accounts of Chemical Research, 2008)
Seventeen million people die of transmittable diseases and 2/3 of the world's population suffer them annually. Malaria, tuberculosis, AIDS, hepatitis, and reemerging and new diseases are a great threat to humankind. A logical and rational approach for vaccine development is thus desperately needed. Protein chemistry provides the best tools for tackling these problems. The tremendous complexity of microbes, the different pathways they use for invading host cells, and the immune responses they induce can only be resolved by using the minimum subunit-based (chemically produced approximately 20-mer peptides), multiantigenic (most proteins involved in invasion), multistage (different invasion mechanisms) vaccine development approach. The most lethal form of malaria caused by Plasmodium falciparum (killing 3 million and affecting 500 million people worldwide annually) was used as target disease since many of its proteins, its invasion pathways, and its genome have been described recently. A New World primate (the Aotus monkey) is highly susceptibly to human malaria; its immune system molecules are 80-100% identical to those of its human counterpart, making it an excellent model for vaccine development. Chemically synthesized approximately 20-mer peptides, covering all the P. falciparum malaria proteins involved in red blood cell (RBC) invasion were synthesized by the classical t-Boc technology (based on synthetic SPf66 antimalarial vaccine information for identifying targets) and assayed in a highly sensitive, specific, and robust test for detecting receptor-ligand interactions between high-activity binding peptides (HABPs) and RBCs. HABPs were identified, some in which the molecule displays genetic variability (to be discarded due to their tremendous complexity) and elicits a strain-specific immune response and others that are conserved (no amino acid sequence variation). Conserved HABPs were synthesized in a polymeric form by adding cysteines at their N- and C-terminal ends to be used for monkey immunization. They became nonimmunogenic (no antibodies were induced) nonprotection inducers (monkeys were not protected against P. falciparum malaria challenge with a highly infective strain) suggesting a code of immunological silence or nonresponsiveness for these conserved HABPs. A large number of monkey trials involving a considerable number of Aotus monkeys were performed to break this code of immunological silence by replacing critical residues (determined by glycine peptide analogue scanning) to find that the following amino acid changes had to be made to render them antibody and protection inducing: F<-->R; W<-->Y; L<-->H; I<-->N; M<-->K; P<-->D; Q<-->E; C<-->T. The three-dimensional (3D) structure of >100 of these native modified HABPs (determined by (1)H NMR) revealed that the following structural changes had all to be achieved to allow a better fit into the major histocompatibility complex class II (MHC II)-peptide-TCR complex to properly activate the immune system: alpha-helix shortening, modifying their beta-turn, adopting segmental alpha-helix configuration, changing residue orientation, and increasing the distance of those residues fitting into the MHC II molecules from antigen-presenting cells. More than 100 such highly immunogenic, protection-inducing (against P. falciparum malaria) modified HABPs have been identified to date with this methodology, showing that it could lead to developing a highly effective subunit-based, multiantigenic, multistage synthetic vaccine against diseases scourging humankind, malaria being one of them.
Keywords: Humans; Animals; Vaccines, Subunit; Malaria Vaccines; Malaria, Falciparum; Plasmodium falciparum; Aotus trivirgatus; Antigens, Protozoan

Improved methods for predicting peptide binding affinity to MHC class II molecules - Jensen, Kamilla Kjaergaard; Andreatta, Massimo; Marcatili, Paolo; Buus, Søren; Greenbaum, Jason A.; Yan, Zhen; Sette, Alessandro; Peters, Bjoern; Nielsen, Morten (Immunology, 2018)
Major histocompatibility complex class II (MHC-II) molecules are expressed on the surface of professional antigen-presenting cells where they display peptides to T helper cells, which orchestrate the onset and outcome of many host immune responses. Understanding which peptides will be presented by the MHC-II molecule is therefore important for understanding the activation of T helper cells and can be used to identify T-cell epitopes. We here present updated versions of two MHC-II-peptide binding affinity prediction methods, NetMHCII and NetMHCIIpan. These were constructed using an extended data set of quantitative MHC-peptide binding affinity data obtained from the Immune Epitope Database covering HLA-DR, HLA-DQ, HLA-DP and H-2 mouse molecules. We show that training with this extended data set improved the performance for peptide binding predictions for both methods. Both methods are publicly available at www.cbs.dtu.dk/services/NetMHCII-2.3 and www.cbs.dtu.dk/services/NetMHCIIpan-3.2.
Keywords: Amino Acid Sequence; Humans; Computational Biology; Protein Binding; Databases, Protein; Epitopes, T-Lymphocyte; Reproducibility of Results; Epitopes; Oligopeptides; affinity predictions; Epitope Mapping; Histocompatibility Antigens Class II; immunogenic peptides; MHC binding specificity; peptide-MHC binding; T-cell epitope

The use of carboxyfluorescein diacetate succinimidyl ester (CFSE) to monitor lymphocyte proliferation - Quah, Benjamin J. C.; Parish, Christopher R. (Journal of Visualized Experiments: JoVE, 2010)
Carboxyfluorescein succinimidyl ester (CFSE) is an effective and popular means to monitor lymphocyte division. CFSE covalently labels long-lived intracellular molecules with the fluorescent dye, carboxyfluorescein. Thus, when a CFSE-labeled cell divides, its progeny are endowed with half the number of carboxyfluorescein-tagged molecules and thus each cell division can be assessed by measuring the corresponding decrease in cell fluorescence via Flow cytometry. The capacity of CFSE to label lymphocyte populations with a high fluorescent intensity of exceptionally low variance, coupled with its low cell toxicity, make it an ideal dye to measure cell division. Since it is a fluorescein-based dye it is also compatible with a broad range of other fluorochromes making it applicable to multi-color flow cytometry. This article describes the procedures typically used for labeling mouse lymphocytes for the purpose of monitoring up to 8 cell divisions. These labeled cells can be used both for in vitro and in vivo studies.
Keywords: Animals; Flow Cytometry; Mice; Cell Division; Fluoresceins; Fluorescent Dyes; Lymphocytes; Succinimides

Bacterial Ghosts of Escherichia coli Drive Efficient Maturation of Bovine Monocyte-Derived Dendritic Cells - Hajam, Irshad Ahmed; Dar, Pervaiz Ahmad; Appavoo, Elamurugan; Kishore, Subodh; Bhanuprakash, Veerakyathappa; Ganesh, Kondabattula (PloS One, 2015)
Bacterial ghosts (BGs) are empty cell envelopes derived from Gram-negative bacteria. They not only represent a potential platform for development of novel vaccines but also provide a tool for efficient adjuvant and antigen delivery system. In the present study, we investigated the interaction between BGs of Escherichia coli (E. coli) and bovine monocyte-derived dendritic cells (MoDCs). MoDCs are highly potent antigen-presenting cells and have the potential to act as a powerful tool for manipulating the immune system. We generated bovine MoDCs in vitro from blood monocytes using E. coli expressed bovine GM-CSF and IL-4 cytokines. These MoDCs displayed typical morphology and functions similar to DCs. We further investigated the E. coli BGs to induce maturation of bovine MoDCs in comparison to E. coli lipopolysaccharide (LPS). We observed the maturation marker molecules such as MHC-II, CD80 and CD86 were induced early and at higher levels in BG stimulated MoDCs as compared to the LPS stimulated MoDCs. BG mediated stimulation induced significantly higher levels of cytokine expression in bovine MoDCs than LPS. Both pro-inflammatory (IL-12 and TNF-α) and anti-inflammatory (IL-10) cytokines were induced in MoDCs after BGs stimulation. We further analysed the effects of BGs on the bovine MoDCs in an allogenic mixed lymphocyte reaction (MLR). We found the BG-treated bovine MoDCs had significantly (p<0.05) higher capacity to stimulate allogenic T cell proliferation in MLR as compared to the LPS. Taken together, these findings demonstrate the E. coli BGs induce a strong activation and maturation of bovine MoDCs.
Keywords: Kinetics; Animals; Monocytes; Cell Differentiation; Transcription, Genetic; Escherichia coli; Cattle; Cytokines; Antigen Presentation; Dendritic Cells; Phenotype; Lipopolysaccharides; Lymphocyte Culture Test, Mixed; Plasmids; RNA, Messenger

Large-scale in vitro expansion of polyclonal human switched-memory B lymphocytes - Néron, Sonia; Roy, Annie; Dumont, Nellie (PloS One, 2012)
Polyclonal preparations of therapeutic immunoglobulins, namely intravenous immunoglobulins (IVIg), are essential in the treatment of immunodeficiency and are increasingly used for the treatment of autoimmune and inflammatory diseases. Currently, patients' accessibility to IVIg depends exclusively upon volunteer blood donations followed by the fractionation of pooled human plasma obtained from thousands of individuals. Presently, there are no in vitro cell culture procedures allowing the preparation of polyclonal human antibodies. All in vitro human therapeutic antibodies that are currently generated are based on monoclonal antibodies, which are mostly issued from genetic engineering or single cell antibody technologies. Here, we describe an in vitro cell culture system, using CD40-CD154 interactions, that leads to a 1×10(6)-fold expansion of switched memory B lymphocytes in approximately 50 days. These expanded cells secrete polyclonal IgG, which distribution into IgG(1), IgG(2), IgG(3) and IgG(4) is similar to that of normal human serum. Such in vitro generated IgG showed relatively low self-reactivity since they interacted moderately with only 24 human antigens among a total of 9484 targets. Furthermore, up to one liter of IgG secreting cells can be produced in about 40 days. This experimental model, providing large-scale expansion of human B lymphocytes, represents a critical step toward the in vitro production of polyclonal human IgG and a new method for the ex vivo expansion of B cells for therapeutic purposes.
Keywords: Humans; Immunoglobulin G; B-Lymphocytes; Immunologic Memory; Reproducibility of Results; CD40 Antigens; CD40 Ligand; Cell Culture Techniques; Immunoglobulin A; Immunoglobulin Class Switching; Immunoglobulin E; Immunoglobulin gamma-Chains

Induction of apoptosis in human neutrophils by Mycobacterium tuberculosis is dependent on mature bacterial lipoproteins - Persson, Alexander; Blomgran-Julinder, Robert; Eklund, Daniel; Lundström, Charlotte; Stendahl, Olle (Microbial Pathogenesis, 2009)
Modulation of immune cell apoptosis is a key evasion strategy utilized by Mycobacterium tuberculosis (Mtb). To be able to multiply within macrophages, the bacterium delays apoptosis and down-regulates pro-inflammatory activation in these cells, whereas apoptosis is rapidly induced in the potently bactericidal neutrophils. Initial host-pathogen interactions between neutrophils and Mtb, subsequently leading to apoptosis, need to be investigated to understand the early features during Mtb infections. Opsonized Mtb were readily phagocytosed, and the immuno-mediated phagocytosis triggered early activation of anti-apoptotic Akt in the neutrophils but the bacteria still induced apoptosis to the same extent as non-phagocytosed Mtb. Mtb-induced apoptosis was strictly dependent on NADPH oxidase-generated reactive oxygen species, compounds shown to damage lysosomal granules. Despite this, we found no involvement of damaged azurophilic granules in Mtb-induced apoptosis in human neutrophils. Instead, the Mtb-induced apoptosis was p38 MAPK dependent and induced through the mitochondrial pathway. Moreover, Mtb deficient of mature lipoproteins lacked the determinants required for induction of neutrophil apoptosis. These results show that Mtb exert a strong intrinsic capacity to induce apoptosis in neutrophils that is capable of overcoming the anti-apoptotic signaling in the cell.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Lipoproteins; Tuberculosis; Cells, Cultured; Neutrophils; Phagocytosis; Apoptosis; p38 Mitogen-Activated Protein Kinases

Allele frequency net 2015 update: new features for HLA epitopes, KIR and disease and HLA adverse drug reaction associations - González-Galarza, Faviel F.; Takeshita, Louise Y. C.; Santos, Eduardo J. M.; Kempson, Felicity; Maia, Maria Helena Thomaz; da Silva, Andrea Luciana Soares; Teles e Silva, André Luiz; Ghattaoraya, Gurpreet S.; Alfirevic, Ana; Jones, Andrew R.; Middleton, Derek (Nucleic Acids Research, 2015)
It has been 12 years since the Allele Frequency Net Database (AFND; http://www.allelefrequencies.net) was first launched, providing the scientific community with an online repository for the storage of immune gene frequencies in different populations across the world. There have been a significant number of improvements from the first version, making AFND a primary resource for many clinical and scientific areas including histocompatibility, immunogenetics, pharmacogenetics and anthropology studies, among many others. The most widely used part of AFND stores population frequency data (alleles, genes or haplotypes) related to human leukocyte antigens (HLA), killer-cell immunoglobulin-like receptors (KIR), major histocompatibility complex class I chain-related genes (MIC) and a number of cytokine gene polymorphisms. AFND now contains >1400 populations from more than 10 million healthy individuals. Here, we report how the main features of AFND have been updated to include a new section on 'HLA epitope' frequencies in populations, a new section capturing the results of studies identifying HLA associations with adverse drug reactions (ADRs) and one for the examination of infectious and autoimmune diseases associated with KIR polymorphisms-thus extending AFND to serve a new user base in these growing areas of research. New criteria on data quality have also been included.
Keywords: Humans; Histocompatibility Antigens Class I; Internet; Epitopes; Databases, Genetic; Disease; Drug-Related Side Effects and Adverse Reactions; Gene Frequency; HLA Antigens; Receptors, KIR

Plasmodium vivax Pv12 B-cell epitopes and HLA-DRβ1*-dependent T-cell epitopes in vitro antigenicity - Yepes-Pérez, Yoelis; López, Carolina; Suárez, Carlos Fernando; Patarroyo, Manuel Alfonso (PloS One, 2018)
Malaria is an infectious disease caused by parasites from the genus Plasmodium (P. falciparum and P. vivax are responsible for 90% of all clinical cases); it is widely distributed throughout the world's tropical and subtropical regions. The P. vivax Pv12 protein is involved in invasion, is expressed on merozoite surface and has been recognised by antibodies from individuals exposed to the disease. In this study, B- and T-cell epitopes from Pv12 were predicted and characterised to advance in the design of a peptide-based vaccine against malaria. For evaluating the humoral response of individuals exposed to natural P. vivax infection from two endemic areas in Colombia, BepiPred-1.0 software was used for selecting B-cell epitopes. B-cell epitope 39038 displayed the greatest recognition by naturally-acquired antibodies and induced an IgG2/IgG4 response. NetMHCIIpan-3.1 prediction software was used for selecting peptides having high affinity binding for HLA-DRβ1* allele lineages and this was confirmed by in-vitro binding assays. T-epitopes 39113 and 39117 triggered a memory T-cell response (Stimulation Index≥2) and significant cytokine production. Combining in-silico, in-vitro and functional assays, two Pv12 protein regions (containing peptides 39038, 39040, 39113 and 39117) have thus been characterised as promising vaccine candidates against P. vivax malaria.
Keywords: Humans; Computational Biology; Epitopes, B-Lymphocyte; Immunity, Humoral; Epitopes, T-Lymphocyte; Enzyme-Linked Immunosorbent Assay; Colombia; HLA-DR beta-Chains; Plasmodium vivax

T cell ageing: effects of age on development, survival & function - Salam, Nasir; Rane, Sanket; Das, Rituparna; Faulkner, Matthew; Gund, Rupali; Kandpal, Usha; Lewis, Virginia; Mattoo, Hamid; Prabhu, Savit; Ranganathan, Vidya; Durdik, Jeannine; George, Anna; et al. (The Indian Journal of Medical Research, 2013)
Age associated decline of the immune system continues to be a major health concern. All components of innate and adaptive immunity are adversely affected to lesser or greater extent by ageing resulting in an overall decline of immunocompetence. As a result in the aged population, there is increased susceptibility to infection, poor responses to vaccination, and increased incidence of autoreactivity. There is an increasing focus on the role of T cells during ageing because of their impact on the overall immune responses. A steady decline in the production of fresh naïve T cells, more restricted T cell receptor (TCR) repertoire and weak activation of T cells are some of the effects of ageing. In this review we summarize our present understanding of the effects of ageing on naïve CD4 T cells and potential approaches for therapeutic interventions to restore protective immunity in the aged population.
Keywords: Humans; Adaptive Immunity; Immunity, Innate; CD4-Positive T-Lymphocytes; Receptors, Antigen, T-Cell; Aging; Cellular Senescence; Hematopoietic Stem Cells; Thymus Gland

Patho-Physiology of Aging and Immune-Senescence: Possible Correlates With Comorbidity and Mortality in Middle-Aged and Old COVID-19 Patients - Farheen, Saba; Agrawal, Sudhanshu; Zubair, Swaleha; Agrawal, Anshu; Jamal, Fauzia; Altaf, Ishrat; Kashif Anwar, Abu; Umair, Syed Mohammad; Owais, Mohammad (Frontiers in Aging, 2021)
During the last 2 years, the entire world has been severely devastated by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic (COVID-19) as it resulted in several million deaths across the globe. While the virus infects people indiscriminately, the casualty risk is higher mainly in old, and middle-aged COVID-19 patients. The incidences of COVID-19 associated co-morbidity and mortality have a great deal of correlation with the weakened and malfunctioning immune systems of elderly people. Presumably, due to the physiological changes associated with aging and because of possible comorbidities such as diabetes, hypertension, obesity, cardiovascular, and lung diseases, which are more common in elderly people, may be considered as the reason making the elderly vulnerable to the infection on one hand, and COVID-19 associated complications on the other. The accretion of senescent immune cells not only contributes to the deterioration of host defense, but also results in elevated inflammatory phenotype persuaded immune dysfunction. In the present review, we envisage to correlate functioning of the immune defense of older COVID-19 patients with secondary/super infection, increased susceptibility or aggravation against already existing cancer, infectious, autoimmune, and other chronic inflammatory diseases. Moreover, we have discussed how age-linked modulations in the immune system affect therapeutic response against administered drugs as well as immunological response to various prophylactic measures including vaccination in the elderly host. The present review also provides an insight into the intricate pathophysiology of the aging and the overall immune response of the host to SARS-CoV-2 infection. A better understanding of age-related immune dysfunction is likely to help us in the development of targeted preemptive strategies for deadly COVID-19 in elderly patients.
Keywords: comorbidities; COVID-19; immunosenescence; inflammaging; innate and adaptive immune system; SARS-CoV-2

Quantitative predictions of peptide binding to any HLA-DR molecule of known sequence: NetMHCIIpan - Nielsen, Morten; Lundegaard, Claus; Blicher, Thomas; Peters, Bjoern; Sette, Alessandro; Justesen, Sune; Buus, Søren; Lund, Ole (PLoS computational biology, 2008)
CD4 positive T helper cells control many aspects of specific immunity. These cells are specific for peptides derived from protein antigens and presented by molecules of the extremely polymorphic major histocompatibility complex (MHC) class II system. The identification of peptides that bind to MHC class II molecules is therefore of pivotal importance for rational discovery of immune epitopes. HLA-DR is a prominent example of a human MHC class II. Here, we present a method, NetMHCIIpan, that allows for pan-specific predictions of peptide binding to any HLA-DR molecule of known sequence. The method is derived from a large compilation of quantitative HLA-DR binding events covering 14 of the more than 500 known HLA-DR alleles. Taking both peptide and HLA sequence information into account, the method can generalize and predict peptide binding also for HLA-DR molecules where experimental data is absent. Validation of the method includes identification of endogenously derived HLA class II ligands, cross-validation, leave-one-molecule-out, and binding motif identification for hitherto uncharacterized HLA-DR molecules. The validation shows that the method can successfully predict binding for HLA-DR molecules-even in the absence of specific data for the particular molecule in question. Moreover, when compared to TEPITOPE, currently the only other publicly available prediction method aiming at providing broad HLA-DR allelic coverage, NetMHCIIpan performs equivalently for alleles included in the training of TEPITOPE while outperforming TEPITOPE on novel alleles. We propose that the method can be used to identify those hitherto uncharacterized alleles, which should be addressed experimentally in future updates of the method to cover the polymorphism of HLA-DR most efficiently. We thus conclude that the presented method meets the challenge of keeping up with the MHC polymorphism discovery rate and that it can be used to sample the MHC "space," enabling a highly efficient iterative process for improving MHC class II binding predictions.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Protein Binding; Algorithms; Databases, Protein; Sequence Analysis, Protein; Alleles; HLA-DR Antigens; Major Histocompatibility Complex; Sequence Alignment; Reproducibility of Results; Predictive Value of Tests; Protein Interaction Mapping

Crystal structure of a superantigen bound to MHC class II displays zinc and peptide dependence - Petersson, K.; Håkansson, M.; Nilsson, H.; Forsberg, G.; Svensson, L. A.; Liljas, A.; Walse, B. (The EMBO journal, 2001)
The three-dimensional structure of a bacterial superantigen, Staphylococcus aureus enterotoxin H (SEH), bound to human major histocompatibility complex (MHC) class II (HLA-DR1) has been determined by X-ray crystallography to 2.6 A resolution (1HXY). The superantigen binds on top of HLA-DR1 in a completely different way from earlier co-crystallized superantigens from S.aureus. SEH interacts with high affinity through a zinc ion with the beta1 chain of HLA-DR1 and also with the peptide presented by HLA-DR1. The structure suggests that all superantigens interacting with MHC class II in a zinc-dependent manner present the superantigen in a common way. This suggests a new model for ternary complex formation with the T-cell receptor (TCR), in which a contact between the TCR and the MHC class II is unlikely.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Protein Structure, Secondary; Models, Molecular; Protein Structure, Tertiary; Protein Conformation; Recombinant Proteins; Crystallography, X-Ray; HLA-DR1 Antigen; Sequence Alignment; Sequence Homology, Amino Acid; Cloning, Molecular; Enterotoxins; Staphylococcus aureus; Superantigens; Zinc; Zinc Fingers

How Superantigens Bind MHC - Van Kaer, Luc (Journal of Immunology (Baltimore, Md.: 1950), 2018)
Keywords: Humans; Peptide Fragments; Animals; Protein Binding; Antigens, Bacterial; T-Lymphocytes; Lymphocyte Activation; Enterotoxins; Superantigens; Clonal Deletion; Histocompatibility Antigens; Minor Lymphocyte Stimulatory Antigens; Receptors, Antigen, T-Cell, alpha-beta

Signaling and Function of Interleukin-2 in T Lymphocytes - Ross, Sarah H.; Cantrell, Doreen A. (Annual Review of Immunology, 2018)
The discovery of interleukin-2 (IL-2) changed the molecular understanding of how the immune system is controlled. IL-2 is a pleiotropic cytokine, and dissecting the signaling pathways that allow IL-2 to control the differentiation and homeostasis of both pro- and anti-inflammatory T cells is fundamental to determining the molecular details of immune regulation. The IL-2 receptor couples to JAK tyrosine kinases and activates the STAT5 transcription factors. However, IL-2 does much more than control transcriptional programs; it is a key regulator of T cell metabolic programs. The development of global phosphoproteomic approaches has expanded the understanding of IL-2 signaling further, revealing the diversity of phosphoproteins that may be influenced by IL-2 in T cells. However, it is increasingly clear that within each T cell subset, IL-2 will signal within a framework of other signal transduction networks that together will shape the transcriptional and metabolic programs that determine T cell fate.
Keywords: Humans; Animals; Cell Differentiation; Cytokines; T-Lymphocyte Subsets; Biomarkers; T-Lymphocytes; Lymphocyte Activation; Signal Transduction; cytokine signaling; interleukin-2; Interleukin-2; JAK1/3; Janus Kinases; Phosphatidylinositol 3-Kinases; PI3K; STAT5 Transcription Factor

IL-2 Restores T-Cell Dysfunction Induced by Persistent Mycobacterium tuberculosis Antigen Stimulation - Liu, Xun; Li, Fei; Niu, Hongxia; Ma, Lan; Chen, Jianzhu; Zhang, Ying; Peng, Liang; Gan, Chao; Ma, Xingming; Zhu, Bingdong (Frontiers in Immunology, 2019)
Tuberculosis (TB) is a chronic disease mainly caused by Mycobacterium tuberculosis. The function of T cells usually decreased and even exhausted in severe TB such as multiple drug resistant TB (MDR-TB), which might lead to the failure of treatment in return. The mechanism of T cell dysfunction in TB is still not clear. In this study we set up a mouse model of T cell dysfunction by persistent M. tuberculosis antigen stimulation and investigated the therapeutic role of interleukin 2 (IL-2) in it. C57BL/6 mice were primed with Mycobacterium bovis Bacillus Calmette-Guérin (BCG) and boosted repeatedly with a combination of M. tuberculosis fusion proteins Mtb10.4-HspX (MH) plus ESAT6-Ag85B-MPT64 <190-198>-Mtb8.4-Rv2626c (LT70) or MH plus ESAT6 and CFP10 with adjuvant of N, N'-dimethyl-N, N'-dioctadecylammonium bromide (DDA) plus polyinosinic-polycytidylic acid (Poly I:C). Following persistent antigen stimulation, the mice were treated with IL-2 and the therapeutic effects were analyzed. The results showed that compared with the mice that received transient antigen stimulation (boost twice), persistent antigen stimulation (boost more than 10 times) resulted in decrease of antigen specific IFN-γ and IL-2 production, reduction of memory CD8+ T cells, over-expression of immune checkpoint programmed cell death protein 1 (PD-1), and impaired the protective immunity against bacterial challenge. Treating the T cell functionally exhausted mice with IL-2 restored antigen-specific T cell responses and protective efficacy. In conclusion, persistent stimulation with M. tuberculosis antigens induced T cell dysfunction, which could be restored by complement of IL-2.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Animals; Antigens, Bacterial; Mice; Female; Interferon-gamma; Recombinant Fusion Proteins; CD8-Positive T-Lymphocytes; Mycobacterium bovis; Tuberculosis, Multidrug-Resistant; Interleukin-2; antigen persistence; IL-2; T cell dysfunction; T cell exhaustion

Vitamin D is required for IFN-gamma-mediated antimicrobial activity of human macrophages - Fabri, Mario; Stenger, Steffen; Shin, Dong-Min; Yuk, Jae-Min; Liu, Philip T.; Realegeno, Susan; Lee, Hye-Mi; Krutzik, Stephan R.; Schenk, Mirjam; Sieling, Peter A.; Teles, Rosane; Montoya, Dennis; et al. (Science Translational Medicine, 2011)
Control of tuberculosis worldwide depends on our understanding of human immune mechanisms, which combat the infection. Acquired T cell responses are critical for host defense against microbial pathogens, yet the mechanisms by which they act in humans remain unclear. We report that T cells, by the release of interferon-γ (IFN-γ), induce autophagy, phagosomal maturation, the production of antimicrobial peptides such as cathelicidin, and antimicrobial activity against Mycobacterium tuberculosis in human macrophages via a vitamin D-dependent pathway. IFN-γ induced the antimicrobial pathway in human macrophages cultured in vitamin D-sufficient sera, but not in sera from African-Americans that have lower amounts of vitamin D and who are more susceptible to tuberculosis. In vitro supplementation of vitamin D-deficient serum with 25-hydroxyvitamin D3 restored IFN-γ-induced antimicrobial peptide expression, autophagy, phagosome-lysosome fusion, and antimicrobial activity. These results suggest a mechanism in which vitamin D is required for acquired immunity to overcome the ability of intracellular pathogens to evade macrophage-mediated antimicrobial responses. The present findings underscore the importance of adequate amounts of vitamin D in all human populations for sustaining both innate and acquired immunity against infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Tuberculosis; Monocytes; Interferon-gamma; Lymphocyte Activation; Models, Biological; Autophagy; Anti-Infective Agents; Antimicrobial Cationic Peptides; Calcifediol; Vitamin D

Induction of nitric oxide release from the human alveolar epithelial cell line A549: an in vitro correlate of innate immune response to Mycobacterium tuberculosis - Roy, Sugata; Sharma, Sadhna; Sharma, Monika; Aggarwal, Ramesh; Bose, Mridula (Immunology, 2004)
In view of the presence of a large number of epithelial cells in the alveoli of the lung and their ability to produce various cytokines and chemokines, the possible role of alveolar epithelial cells in the innate immune response to tuberculosis was examined. The human alveolar epithelial cell line A549 was used as a model. The ability of A549 cells to induce nitric oxide (NO) in response to Mycobacterium tuberculosis infection was taken as an in vitro correlate of innate immunity. M. tuberculosis infection induced A549 cells to produce significant levels of NO and to express inducible nitric oxide synthase mRNA at 48 hr of infection. However, the amount of NO released at this point was not mycobactericidal. Cytokine stimulation (interferon-γ, tumour necrosis factor-α, interleukin-1β, alone or in combination) of the infected A549 cells induced a higher concentration of NO. The study of colony-forming units (CFU) as a measure of the mycobactericidal capacity of A549 cells revealed a reduction in CFU of M. tuberculosis by 39·29% (from 10·62 ± 0·48 – 6·392 ± 0·54) following cytokine stimulation of the infected cells. Interestingly γ-irradiated M. tuberculosis H37Rv could also induce higher than basal level of NO. Therefore we examined mycobacterial antigenic components for their possible role in NO production. We observed that A549 cells produced significantly higher amounts of NO at 48 hr when treated with mycobacterial whole cell lysates, cell wall or cell membrane preparations. The release of NO and the resultant mycobactericidal activity could be further enhanced by simultaneously conditioning the M. tuberculosis infected A549 cells with cytokine and mycobacterial components. These results suggest that alveolar epithelial cells respond to their microenvironment, which is constituted of various cytokines and macrophage-processed antigens and may contribute to the innate immune response to tuberculosis.

Pulmonary epithelial cells are a source of interferon-gamma in response to Mycobacterium tuberculosis infection - Sharma, Monika; Sharma, Sadhna; Roy, Sugata; Varma, Saurabh; Bose, Mridula (Immunology and Cell Biology, 2007)
Recent report from our laboratory showed that A549 cells representing alveolar epithelial cells produce chemokine interleukin-8 and nitric oxide (NO) when challenged with Mycobacterium tuberculosis. Interferon-gamma (IFN-gamma) played a critical role in priming these cells to generate NO in vitro. In the present study, we report that M. tuberculosis-infected A549 cells are capable of elaborating IFN-gamma as shown by enzyme-linked immunosorbent assay and intracellular staining for IFN-gamma. Secretion profile indicated that M. tuberculosis-infected A549 released significantly high concentration of IFN-gamma at 48 and 72 h post-infection. Low level of IFN-gamma release was also seen to be induced by gamma-irradiated M. tuberculosis and subcellular components of M. tuberculosis. Cell surface receptor analysis showed that the M. tuberculosis-infected A549 cells expressed enhanced levels of IFN-gamma receptors. This observation suggests that the endogenously produced IFN-gamma in response to M. tuberculosis infection plays a role in intracellular regulation of innate immunity against intracellular pathogen such as M. tuberculosis. This observation is further strengthened by the fact that infected A549 cells expressed signal transducer and activator of transcription 1 (STAT1), an important mediator for IFN-gamma signaling pathway, leading to expression of inducible NO synthase and subsequent release of NO in sufficient concentration to be mycobactericidal. Our results show that production of IFN-gamma and enhanced expression of IFN-gamma receptors by infected A549 cells is a local phenomenon occurring as de novo intracellular activity, in response to M. tuberculosis infection. To the best of our knowledge, this is the first report to show that A549 cells interact actively with M. tuberculosis to produce IFN-gamma that might play an important role in innate immunity against tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Epithelial Cells; Pulmonary Alveoli; Tuberculosis, Pulmonary; Lung; Interferon-gamma; Nitric Oxide; STAT1 Transcription Factor

Ubiquilin 1 Promotes IFN-γ-Induced Xenophagy of Mycobacterium tuberculosis - Sakowski, Erik T.; Koster, Stefan; Portal Celhay, Cynthia; Park, Heidi S.; Shrestha, Elina; Hetzenecker, Stefanie E.; Maurer, Katie; Cadwell, Ken; Philips, Jennifer A. (PLoS pathogens, 2015)
The success of Mycobacterium tuberculosis (Mtb) as a pathogen rests upon its ability to grow intracellularly in macrophages. Interferon-gamma (IFN-γ) is critical in host defense against Mtb and stimulates macrophage clearance of Mtb through an autophagy pathway. Here we show that the host protein ubiquilin 1 (UBQLN1) promotes IFN-γ-mediated autophagic clearance of Mtb. Ubiquilin family members have previously been shown to recognize proteins that aggregate in neurodegenerative disorders. We find that UBQLN1 can interact with Mtb surface proteins and associates with the bacilli in vitro. In IFN-γ activated macrophages, UBQLN1 co-localizes with Mtb and promotes the anti-mycobacterial activity of IFN-γ. The association of UBQLN1 with Mtb depends upon the secreted bacterial protein, EsxA, which is involved in permeabilizing host phagosomes. In autophagy-deficient macrophages, UBQLN1 accumulates around Mtb, consistent with the idea that it marks bacilli that traffic through the autophagy pathway. Moreover, UBQLN1 promotes ubiquitin, p62, and LC3 accumulation around Mtb, acting independently of the E3 ligase parkin. In summary, we propose a model in which UBQLN1 recognizes Mtb and in turn recruits the autophagy machinery thereby promoting intracellular control of Mtb. Thus, polymorphisms in ubiquilins, which are known to influence susceptibility to neurodegenerative illnesses, might also play a role in host defense against Mtb.
Keywords: Mycobacterium tuberculosis; Animals; Macrophages; Mice; Interferon-gamma; Phagosomes; Autophagy; Adaptor Proteins, Signal Transducing; Adaptor Proteins, Vesicular Transport; Autophagy-Related Proteins

The Role of Tumor Necrosis Factor Alpha (TNF-α) in Autoimmune Disease and Current TNF-α Inhibitors in Therapeutics - Jang, Dan-In; Lee, A.-Hyeon; Shin, Hye-Yoon; Song, Hyo-Ryeong; Park, Jong-Hwi; Kang, Tae-Bong; Lee, Sang-Ryong; Yang, Seung-Hoon (International Journal of Molecular Sciences, 2021)
Tumor necrosis factor alpha (TNF-α) was initially recognized as a factor that causes the necrosis of tumors, but it has been recently identified to have additional important functions as a pathological component of autoimmune diseases. TNF-α binds to two different receptors, which initiate signal transduction pathways. These pathways lead to various cellular responses, including cell survival, differentiation, and proliferation. However, the inappropriate or excessive activation of TNF-α signaling is associated with chronic inflammation and can eventually lead to the development of pathological complications such as autoimmune diseases. Understanding of the TNF-α signaling mechanism has been expanded and applied for the treatment of immune diseases, which has resulted in the development of effective therapeutic tools, including TNF-α inhibitors. Currently, clinically approved TNF-α inhibitors have shown noticeable potency in a variety of autoimmune diseases, and novel TNF-α signaling inhibitors are being clinically evaluated. In this review, we briefly introduce the impact of TNF-α signaling on autoimmune diseases and its inhibitors, which are used as therapeutic agents against autoimmune diseases.
Keywords: Humans; Animals; Signal Transduction; Tumor Necrosis Factor-alpha; Chronic Disease; autoimmune diseases; Autoimmune Diseases; Immunologic Factors; inflammatory bowel disease; psoriatic arthritis; rheumatoid arthritis; TNF-α; TNF-α inhibitors

Tumor necrosis factor-alpha is required in the protective immune response against Mycobacterium tuberculosis in mice - Flynn, J. L.; Goldstein, M. M.; Chan, J.; Triebold, K. J.; Pfeffer, K.; Lowenstein, C. J.; Schreiber, R.; Mak, T. W.; Bloom, B. R. (Immunity, 1995)
Understanding the immunological mechanisms of protection and pathogenesis in tuberculosis remains problematic. We have examined the extent to which tumor necrosis factor-alpha (TNF alpha) contributes to this disease using murine models in which the action of TNF alpha is inhibited. TNF alpha was neutralized in vivo by monoclonal antibody; in addition, a mouse strain with a disruption in the gene for the 55 kDa TNF receptor was used. The data from both models established that TNF alpha and the 55 kDa TNF receptor are essential for protection against tuberculosis in mice, and for reactive nitrogen production by macrophages early in infection. Granulomas were formed in equal numbers in control and experimental mice, but necrosis was observed only in mice deficient in TNF alpha or TNF receptor. TNF alpha and the 55 kDa TNF receptor are necessary conditions for protection against murine M. tuberculosis infection, but are not solely responsible for the tissue damage observed.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Immunization; Polymerase Chain Reaction; BCG Vaccine; Mice; Granuloma; Female; Lung; Mice, Inbred C57BL; Antibodies, Monoclonal; Tumor Necrosis Factor-alpha; Immunohistochemistry; Amino Acid Oxidoreductases; Nitric Oxide Synthase; Receptors, Tumor Necrosis Factor

Tumor necrosis factor neutralization results in disseminated disease in acute and latent Mycobacterium tuberculosis infection with normal granuloma structure in a cynomolgus macaque model - Lin, Philana Ling; Myers, Amy; Smith, Le'Kneitah; Bigbee, Carolyn; Bigbee, Matthew; Fuhrman, Carl; Grieser, Heather; Chiosea, Ion; Voitenek, Nikolai N.; Capuano, Saverio V.; Klein, Edwin; Flynn, JoAnne L. (Arthritis and Rheumatism, 2010)
OBJECTIVE: An increased risk of tuberculosis has been documented in humans treated with tumor necrosis factor alpha (TNFalpha)-neutralizing agents. In murine models, impaired signaling by TNF causes exacerbation of both acute and chronic infection associated with aberrant granuloma formation and maintenance. This study was undertaken to investigate immune modulation in the setting of TNF neutralization in primary and latent tuberculosis in a non-human primate model. METHODS: Cynomolgus macaques 4 years of age or older were infected with Mycobacterium tuberculosis and subjected to clinical, microbiologic, immunologic, and radiographic examinations. Monkeys were classified as having active or latent disease 6-8 months after infection, based on clinical criteria. Monkeys used in acute infection studies were randomized to receive either adalimumab (prior to and during infection) or no treatment. Monkeys with latent infection that were randomized to receive TNF-neutralizing agent were given either an inhibitor of soluble TNF, recombinant methionyl human soluble TNF receptor I (p55-TNFRI), or adalimumab. Control monkeys with latent infection were given no treatment or saline. Data from previously studied monkeys with active or latent disease were also used for comparison. RESULTS: Administration of TNF-neutralizing agents prior to M tuberculosis infection resulted in fulminant and disseminated disease by 8 weeks after infection. Neutralization of TNF in latently infected cynomolgus macaques caused reactivation in a majority of animals as determined by gross pathologic examination and bacterial burden. A spectrum of dissemination was noted, including extrapulmonary disease. Surprisingly, monkeys that developed primary and reactivation tuberculosis after TNF neutralization had similar granuloma structure and composition to that of control monkeys with active disease. TNF neutralization was associated with increased levels of interleukin-12, decreased levels of CCL4, increased chemokine receptor expression, and reduced mycobacteria-induced interferon-gamma production in blood but not in the affected mediastinal lymph nodes. Finally, the first signs of reactivation often occurred in thoracic lymph nodes. CONCLUSION: These findings have important clinical implications for determining the mechanism of TNF neutralization-related tuberculosis.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Disease Models, Animal; Granuloma; Interferon-gamma; Macaca fascicularis; Antibodies, Monoclonal; Interleukin-12; Tumor Necrosis Factor-alpha; Chronic Disease; Interleukin-2; Acute Disease; Adalimumab; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Chemokine CCL4; Immunosuppression Therapy; Interleukin-8; Tuberculosis, Lymph Node

Tuberculosis associated with tumor necrosis factor-α antagonists, case description and analysis of reported cases in Colombia - Galvis, Leandro; Sánchez, Ángel Y.; Jurado, Leonardo F.; Murcia, Martha I. (Biomédica, 2018)
Tumor necrosis factor-α (TNF-α) is an important fundamental cytokine during the immune response against cancer and infections such as tuberculosis. This molecule also plays a key pathogenic role in complex and difficult-to-treat diseases such as rheumatoid arthritis, ankylosing spondylitis, Crohn’s disease, psoriasis and ulcerative colitis. The treatment of these diseases frequently needs TNF-α antagonists, which has been related to an increased risk of developing tuberculosis, mycoses, and other severe infections.We report the case of a 68-year-old man with Crohn’s disease, who developed  disseminated tuberculosis due to anti-TNF-α immunosuppressive therapy. The diagnosis was based on the histopathological findings and molecular biology assays.We discuss the clinical presentation and workup of this case, and we present a comparative analysis of tuberculosis cases associated with anti-TNF-α reported in Colombia during the last 10 years emphasizing on the diagnosis and treatment of latent tuberculosis.
Keywords: Mycobacterium tuberculosis; Colombia; Anti TNF; Artritis Reumatoide; Enfermedad de Crohn; Espondilitis Anquilosante; Síndrome de Sjögren; Tuberculosis Latente

IL-4 subverts mycobacterial containment in Mycobacterium tuberculosis-infected human macrophages - Pooran, Anil; Davids, Malika; Nel, Andrew; Shoko, Aubrey; Blackburn, Jonathan; Dheda, Keertan (The European Respiratory Journal, 2019)
Protective immunity against Mycobacterium tuberculosis is poorly understood. The role of interleukin (IL)-4, the archetypal T-helper type 2 (Th2) cytokine, in the immunopathogenesis of human tuberculosis remains unclear.Blood and/or bronchoalveolar lavage fluid (BAL) were obtained from participants with pulmonary tuberculosis (TB) (n=23) and presumed latent TB infection (LTBI) (n=22). Messenger RNA expression levels of interferon (IFN)-γ, IL-4 and its splice variant IL-4δ2 were determined by real-time PCR. The effect of human recombinant (hr)IL-4 on mycobacterial survival/containment (CFU·mL-1) was evaluated in M. tuberculosis-infected macrophages co-cultured with mycobacterial antigen-primed effector T-cells. Regulatory T-cell (Treg) and Th1 cytokine levels were evaluated using flow cytometry.In blood, but not BAL, IL-4 mRNA levels (p=0.02) and the IL-4/IFN-γ ratio (p=0.01) was higher in TB versus LTBI. hrIL-4 reduced mycobacterial containment in infected macrophages (p<0.008) in a dose-dependent manner and was associated with an increase in Tregs (p<0.001), but decreased CD4+Th1 cytokine levels (CD4+IFN-γ+ p<0.001; CD4+TNFα+ p=0.01). Blocking IL-4 significantly neutralised mycobacterial containment (p=0.03), CD4+IFNγ+ levels (p=0.03) and Treg expression (p=0.03).IL-4 can subvert mycobacterial containment in human macrophages, probably via perturbations in Treg and Th1-linked pathways. These data may have implications for the design of effective TB vaccines and host-directed therapies.
Keywords: Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Macrophages; Recombinant Proteins; Cells, Cultured; Tuberculosis, Pulmonary; Interferon-gamma; Cytokines; CD4-Positive T-Lymphocytes; Th1 Cells; Coculture Techniques; Latent Tuberculosis; Inflammation; Immunotherapy; Interleukin-4; Th2 Cells; T-Lymphocytes, Regulatory; RNA, Messenger; Bronchoalveolar Lavage Fluid

T Follicular Helper Cell Biology: A Decade of Discovery and Diseases - Crotty, Shane (Immunity, 2019)
Helping B cells and antibody responses is a major function of CD4+ T cells. It has been 10 years since the publication of Bcl6 as the lineage-defining transcription factor for T follicular helper (Tfh) differentiation and the requirement of Tfh cells as the specialized subset of CD4+ T cells needed for germinal centers (the microanatomical sites of B cell mutation and antibody affinity maturation) and related B cell responses. A great deal has been learned about Tfh cells in the past 10 years, particularly regarding their roles in a surprising range of diseases. Advances in the understanding of Tfh cell differentiation and function are discussed, as are the understanding of Tfh cells in infectious diseases, vaccines, autoimmune diseases, allergies, atherosclerosis, organ transplants, and cancer. This includes discussion of Tfh cells in the human immune system. Based on the discoveries to date, the next decade of Tfh research surely holds many more surprises. VIDEO ABSTRACT.
Keywords: Humans; Cell Differentiation; Communicable Diseases; B-Lymphocytes; T-Lymphocytes, Helper-Inducer; Autoimmune Diseases; Atherosclerosis; Germinal Center; Hypersensitivity; Proto-Oncogene Proteins c-bcl-6

The biological functions of T helper 17 cell effector cytokines in inflammation - Ouyang, Wenjun; Kolls, Jay K.; Zheng, Yan (Immunity, 2008)
T helper 17 (Th17) cells belong to a recently identified T helper subset, in addition to the traditional Th1 and Th2 subsets. These cells are characterized as preferential producers of interleukin-17A (IL-17A), IL-17F, IL-21, and IL-22. Th17 cells and their effector cytokines mediate host defensive mechanisms to various infections, especially extracellular bacteria infections, and are involved in the pathogenesis of many autoimmune diseases. The receptors for IL-17 and IL-22 are broadly expressed on various epithelial tissues. The effector cytokines of Th17 cells, therefore, mediate the crucial crosstalk between immune system and tissues, and play indispensable roles in tissue immunity.
Keywords: Humans; Animals; Cytokines; T-Lymphocyte Subsets; Signal Transduction; T-Lymphocytes, Helper-Inducer; Inflammation Mediators; Interleukin-17; Lymphocyte Cooperation

Th17 and regulatory T cells in mediating and restraining inflammation - Littman, Dan R.; Rudensky, Alexander Y. (Cell, 2010)
The vertebrate immune system is poised in a state of equilibrium that permits accurate and rapid protective responses against pathogens but curtails potential for causing harm to the host through targeting of "self" and provoking overexuberant inflammatory processes. In this Review we discuss this balance achieved in large part by interactions of different classes of T lymphocytes that have potent pro- or anti-inflammatory activity in the context of genetic and environmental factors, particularly the commensal microbiota.
Keywords: T-Lymphocytes, Helper-Inducer; Inflammation; T-Lymphocytes, Regulatory; Bacteria; Immune Tolerance; Intestinal Mucosa

Mycobacterium bovis BCG-specific Th17 cells confer partial protection against Mycobacterium tuberculosis infection in the absence of gamma interferon - Wozniak, Teresa M.; Saunders, Bernadette M.; Ryan, Anthony A.; Britton, Warwick J. (Infection and Immunity, 2010)
Protective immunity against tuberculosis (TB) requires the integrated response of a network of lymphocytes. Both gamma interferon (IFN-γ)- and interleukin 17 (IL-17)-secreting CD4(+) T cells have been identified in subjects with latent TB infection and during experimental Mycobacterium tuberculosis infection, but the contribution of Th17 cells to protective immunity is unclear. To examine their protective effects in vivo, we transferred mycobacterium-specific IL-17- and IFN-γ-secreting CD4(+) T cells isolated from M. tuberculosis BCG-immunized IL-12p40(-/-) and IFN-γ(-/-) or wild-type mice, respectively, into M. tuberculosis-infected IL-12p40(-/-) or RAG(-/-) mice. In the absence of IL-12 and IL-23, neither IL-17-secreting (Th17) nor IFN-γ-secreting (Th1) BCG-specific T cells expanded or provided protection against M. tuberculosis. In RAG(-/-) recipients with an intact IL-12/IL-23 axis, both Th17 and Th1 cells were activated and induced significant protection against M. tuberculosis. The reduction in the bacterial load following transfer of IFN-γ(-/-) Th17 cells was associated with significant prolongation of survival compared to recipients of naïve IFN-γ(-/-) T cells. This effect was at the cost of an increased inflammatory infiltrate characterized by an excess of neutrophils. Therefore, Th17 cells can provide IFN-γ-independent protection against M. tuberculosis, and this effect may contribute to the early control of M. tuberculosis infection.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; BCG Vaccine; Mice; Female; Interferon-gamma; Mice, Inbred C57BL; Mice, Knockout; Mycobacterium bovis; Gene Expression Regulation; Th2 Cells; Interleukin-17

The wolf in sheep's clothing: the role of interleukin-6 in immunity, inflammation and cancer - Naugler, Willscott E.; Karin, Michael (Trends in Molecular Medicine, 2008)
Recent discoveries involving the cytokine interleukin (IL)-6 have originated from diverse disciplines, revealing roles in biological processes that are likewise varied. The most novel findings suggest a connection between inflammation and diseases, such as insulin resistance associated with diabetes mellitus and cancer, which had not or only weakly been appreciated previously. The IL-6 pathway is one of the mechanisms linking inflammation to these disease processes. In addition, new evidence points toward IL-6 as one of the mediators coordinating the interface between adaptive and innate immunity. Here, we review the evidence linking IL-6 to inflammatory diseases and cancer.
Keywords: Humans; Animals; Mice; Immunity, Innate; Signal Transduction; Inflammation; Neoplasms; Aging; Inflammatory Bowel Diseases; Insulin Resistance; Interleukin-6; Obesity; Rheumatic Fever

Stat3 activation is responsible for IL-6-dependent T cell proliferation through preventing apoptosis: generation and characterization of T cell-specific Stat3-deficient mice - Takeda, K.; Kaisho, T.; Yoshida, N.; Takeda, J.; Kishimoto, T.; Akira, S. (Journal of Immunology (Baltimore, Md.: 1950), 1998)
Stat3, a member of STAT, is activated by a variety of cytokines such as IL-6 family of cytokines, granulocyte CSF, epidermal growth factor, and leptin. A recent study with mice genetically deficient in the Stat3 gene has revealed its important role in the early embryogenesis. To assess the function of Stat3 in adult tissues, we disrupted the Stat3 gene specifically in T cells by conditional gene targeting using Cre-loxP system. In Stat3-deficient T cells, IL-6-induced proliferation was severely impaired. IL-6 did not enhance cell cycle progression, but prevented apoptosis of normal T cells. In contrast, IL-6 did not prevent apoptosis of Stat3-deficient T cells. Antiapoptotic protein, Bcl-2, was normally up-regulated in response to IL-6 even in Stat3-deficient T cells. These results demonstrate that Stat3 activation is involved in IL-6-dependent T cell proliferation through prevention of apoptosis independently of Bcl-2.
Keywords: Amino Acid Sequence; Base Sequence; Molecular Sequence Data; Animals; Organ Specificity; Mice; Recombinant Fusion Proteins; Cytokines; T-Lymphocytes; Lymphocyte Activation; Mice, Knockout; Cell Division; Apoptosis; Interleukin-6; Cell Cycle; DNA-Binding Proteins; Gene Expression Regulation, Developmental; Gene Targeting; Genes, bcl-2; Integrases; Lymphocyte Specific Protein Tyrosine Kinase p56(lck); Phosphorylation; Promoter Regions, Genetic; Protein Processing, Post-Translational; Proto-Oncogene Proteins c-bcl-2; STAT3 Transcription Factor; Trans-Activators; Viral Proteins

Activation-induced inhibition of interleukin 6-mediated T cell survival and signal transducer and activator of transcription 1 signaling - Teague, T. K.; Schaefer, B. C.; Hildeman, D.; Bender, J.; Mitchell, T.; Kappler, J. W.; Marrack, P. (The Journal of Experimental Medicine, 2000)
The cytokines interleukin (IL)-2, IL-4, IL-6, IL-7, and IL-15 have all previously been shown to inhibit resting T cell death in vitro. We have found a difference in the response of T cells to IL-6, depending on the activation status of the cells. IL-6 inhibited the death of naive T cells, but had no effect on the death of either superantigen-activated T cells, or T cells bearing memory markers. This was true even when the resting and activated T cells were isolated from the same animal; thus, the determining factor for IL-6 insensitivity was the activation status or activation history of the cell, and not the milieu in the animal from which the cells were isolated. Activated T cells expressed lower levels of IL-6 receptors on their surfaces, yet there were sufficient levels of receptors for signaling, as we observed similar levels of signal transducer and activator of transcription (Stat)3 phosphorylation in resting and activated T cells treated with IL-6. However, there was profound inhibition of IL-6-induced Stat1 phosphorylation in activated T cells compared with resting T cells. These data suggest that there is activation-induced inhibition of IL-6 receptor signaling in T cells. This inhibition appears to be specific for some but not all of the IL-6-mediated signaling cascades in these cells.
Keywords: Animals; Cell Survival; Cells, Cultured; Mice; Female; Cytokines; T-Lymphocyte Subsets; Mice, Inbred C57BL; Immunologic Memory; Lymphocyte Activation; Signal Transduction; Mice, Transgenic; STAT1 Transcription Factor; Interleukin-6; DNA-Binding Proteins; Phosphorylation; STAT3 Transcription Factor; Trans-Activators; Carrier Proteins; Cell Death; Dose-Response Relationship, Immunologic; Down-Regulation; Immunophenotyping; Interphase; Mice, Inbred BALB C; Receptors, Interleukin-6; Repressor Proteins; Suppressor of Cytokine Signaling 1 Protein; Suppressor of Cytokine Signaling Proteins; Transcription Factor AP-1

Transforming growth factor-beta induces development of the T(H)17 lineage - Mangan, Paul R.; Harrington, Laurie E.; O'Quinn, Darrell B.; Helms, Whitney S.; Bullard, Daniel C.; Elson, Charles O.; Hatton, Robin D.; Wahl, Sharon M.; Schoeb, Trenton R.; Weaver, Casey T. (Nature, 2006)
A new lineage of effector CD4+ T cells characterized by production of interleukin (IL)-17, the T-helper-17 (T(H)17) lineage, was recently described based on developmental and functional features distinct from those of classical T(H)1 and T(H)2 lineages. Like T(H)1 and T(H)2, T(H)17 cells almost certainly evolved to provide adaptive immunity tailored to specific classes of pathogens, such as extracellular bacteria. Aberrant T(H)17 responses have been implicated in a growing list of autoimmune disorders. T(H)17 development has been linked to IL-23, an IL-12 cytokine family member that shares with IL-12 a common subunit, IL-12p40 (ref. 8). The IL-23 and IL-12 receptors also share a subunit, IL-12Rbeta1, that pairs with unique, inducible components, IL-23R and IL-12Rbeta2, to confer receptor responsiveness. Here we identify transforming growth factor-beta (TGF-beta) as a cytokine critical for commitment to T(H)17 development. TGF-beta acts to upregulate IL-23R expression, thereby conferring responsiveness to IL-23. Although dispensable for the development of IL-17-producing T cells in vitro and in vivo, IL-23 is required for host protection against a bacterial pathogen, Citrobacter rodentium. The action of TGF-beta on naive T cells is antagonized by interferon-gamma and IL-4, thus providing a mechanism for divergence of the T(H)1, T(H)2 and T(H)17 lineages.
Keywords: Animals; Cell Differentiation; Mice; Interferon-gamma; Th1 Cells; Receptors, Interleukin; Interleukin-4; Th2 Cells; Interleukin-17; Forkhead Transcription Factors; Cell Lineage; Interleukin-23; Interleukin-23 Subunit p19; Interleukins; Transforming Growth Factor beta

Role of interleukin 6 in innate immunity to Mycobacterium tuberculosis infection - Martinez, Alejandra N.; Mehra, Smriti; Kaushal, Deepak (The Journal of Infectious Diseases, 2013)
BACKGROUND: Mycobacterium tuberculosis can grow in the hostile intracellular environment of macrophages by actively evading macrophage-associated antibacterial activities. The stress response factor SigH contributes to this process by modulating β-chemokine and interleukin 6 (Il6) expression. Hence, Il6 is of critical importance for acquired immunity against M. tuberculosis infection. Here, we attempted to better characterize the role of Il6 in the immune response to M. tuberculosis infection. METHODS: A small interfering RNA-based approach was used to silence expression of the Il6 transcript in host macrophages infected with a wild-type strain of M. tuberculosis or an attenuated mutant strain of M. tuberculosis (Mtb:Δ-sigH). The outcome was measured by the analysis of bacterial burden and transcriptome-wide analysis of host gene expression. Transcriptome results were confirmed via quantitative polymerase chain reaction and enzyme-linked immunosorbent assay. RESULTS: Wild type and Mtb:Δ-sigH infection of host macrophages in which Il6 had been silenced resulted in increased expression of interferon-inducible genes, especially those involved in type I interferon signaling. The expression of Ly-6 genes was significantly higher in cells infected with Mtb:Δ-sigH, compared with those infected with the wild-type strain (P < .05). CONCLUSIONS: M. tuberculosis regulates host Il6 production to inhibit type I interferon signaling and, consequently, disease progression. Mtb:Δ-sigH is associated with delayed activation of macrophages, compared with the wild-type strain, and with delayed inflammatory stimuli as consequence. These findings have important implications for improving understanding of the mechanisms behind M. tuberculosis virulence and pathogenesis and provide an initial road map to further investigate the mechanisms that may account for the deleterious effects of type I interferons in M. tuberculosis infection.
Keywords: Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis; Mice; Immunity, Innate; Mice, Inbred C57BL; Macrophage Activation; Gene Expression Regulation; Bacterial Load; Inflammation; Transfection; Enzyme-Linked Immunosorbent Assay; RNA, Messenger; Interleukin-6; Chemokine CXCL2; Gene Silencing; Interferon Type I; Oligonucleotide Array Sequence Analysis; Real-Time Polymerase Chain Reaction; RNA, Small Interfering; Toll-Like Receptor 2; Transcriptome

Lethal tuberculosis in interleukin-6-deficient mutant mice - Ladel, C. H.; Blum, C.; Dreher, A.; Reifenberg, K.; Kopf, M.; Kaufmann, S. H. (Infection and Immunity, 1997)
Tuberculosis is a chronic infectious disease which causes major health problems globally. Acquired resistance is mediated by T lymphocytes and executed by activated macrophages. In vitro studies have emphasized the importance of macrophage activation for mycobacterial growth inhibition. In vivo, the protective host response is focused on granulomatous lesions in which Mycobacterium tuberculosis is contained. A cellular immune response of the T helper 1 (Th1) type is considered central for control of tuberculosis. Using interleukin-6 (IL-6)-deficient mice, we here demonstrate a crucial role of this pluripotent cytokine in protection against M. tuberculosis but not against Mycobacterium bovis BCG. Infection with M. tuberculosis was lethal for the IL-6-deficient mice at inocula that were still controlled by IL-6-competent mice. Spleen cells from M. tuberculosis-infected IL-6-/- mouse mutants produced elevated levels of IL-4 and reduced levels of gamma interferon compared to the control levels. Cytofluorometric analyses of spleen cells from M. tuberculosis-infected mice revealed more-profound alterations in T-cell ratios in IL-6-/- mice than in control mice. We assume that IL-6 contributes to host resistance by its proinflammatory activity and by its influence on cytokine secretion.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Mice; Female; Interferon-gamma; Mice, Inbred C57BL; Male; Mycobacterium bovis; Interleukin-12; Tumor Necrosis Factor-alpha; Interleukin-4; Interleukin-6; Immunophenotyping

Relevance of TNF-α, IL-6 and IRAK1 gene expression for assessing disease severity and therapy effects in tuberculosis patients - Buha, Ivana; Škodrić-Trifunović, Vesna; Adžić-Vukičević, Tatjana; Ilić, Aleksandra; Blanka-Protić, Ana; Stjepanovic, Mihailo; Anđelković, Marina; Vreća, Miša; Milin-Lazović, Jelena; Spasovski, Vesna; Pavlović, Sonja (Journal of Infection in Developing Countries, 2019)
INTRODUCTION: Tuberculosis (TBC) is a contagious chronic respiratory disease which despite the known cause, Mycobacterium tuberculosis (Mtb), and many decades of successful therapy, remains one of the leading global health problems. Immune responses against Mtb infection involve both of types of immunity, but cellular immunity, in which certain cytokines and Th1 cells play a key role, is crucial. A better understanding of the functions of the cytokine network involved in the state and progression of TBC could identify specific molecular markers for monitoring of disease activity as well as therapy outcomes in TBC patients. METHODOLOGY: We investigated expression of TNF-α, IL-6 and IRAK1 genes using an RT-qPCR technique in peripheral blood mononuclear cells of 33 TBC patients and 10 healthy individuals. RESULTS: Comparison between TBC patients and healthy individuals revealed statistically significant differences for all analyzed genes. The levels of expression of TNF-α and IL-6 mRNA were higher, while the level of IRAK1 mRNA was lower in the TBC group compared to controls. Moreover, a strong positive correlation was observed between TNF-α and IL-6 gene expression. When clinical parameters were analyzed, increased levels of TNF-α mRNA were detected in patients with a longer duration of therapy (>2 months) compared to those with a shorter therapy duration (< 2 months), and in patients without anemia. CONCLUSIONS: Our results indicate that the inflammatory genes we examined play a crucial role in the pathogenesis of tuberculosis, and that the expression of the TNF-α gene could be a marker for monitoring the clinical effect of the ant-tuberculosis drugs during therapy.
Keywords: Humans; Tuberculosis, Pulmonary; Female; Biomarkers; Adult; Male; Middle Aged; Aged; Inflammation Mediators; Tumor Necrosis Factor-alpha; Interleukin-6; Real-Time Polymerase Chain Reaction; Transcriptome; cytokines; gene expression; Interleukin-1 Receptor-Associated Kinases; monitoring therapy; pulmonary tuberculosis

Early IL-10 promotes vasculature-associated CD4+ T cells unable to control Mycobacterium tuberculosis infection - Ferreira, Catarina M.; Barbosa, Ana Margarida; Barreira-Silva, Palmira; Silvestre, Ricardo; Cunha, Cristina; Carvalho, Agostinho; Rodrigues, Fernando; Correia-Neves, Margarida; Castro, António G.; Torrado, Egídio (JCI insight, 2021)
Cytokine-producing CD4+ T cells play a crucial role in the control of Mycobacterium tuberculosis infection; however, there is a delayed appearance of effector T cells in the lungs following aerosol infection. The immunomodulatory cytokine IL-10 antagonizes control of M. tuberculosis infection through mechanisms associated with reduced CD4+ T cell responses. Here, we show that IL-10 overexpression only before the onset of the T cell response impaired control of M. tuberculosis growth; during chronic infection, IL-10 overexpression reduced the CD4+ T cell response without affecting the outcome of infection. IL-10 overexpression early during infection did not, we found, significantly impair the kinetics of CD4+ T cell priming and effector differentiation. However, CD4+ T cells primed and differentiated in an IL-10-enriched environment displayed reduced expression of CXCR3 and, because they did not migrate into the lung parenchyma, their ability to control infection was limited. Importantly, these CD4+ T cells maintained their vasculature phenotype and were unable to control infection, even after adoptive transfer into low IL-10 settings. Together our data support a model wherein, during M. tuberculosis infection, IL-10 acts intrinsically on T cells, impairing their parenchymal migratory capacity and ability to engage with infected phagocytic cells, thereby impeding control of infection.
Keywords: Humans; Animals; Tuberculosis; Mice; Female; Cytokines; CD4-Positive T-Lymphocytes; Male; Adaptive immunity; Immunology; Infectious disease; Interleukin-10

Pleiotropic Effect of IL-6 Produced by B-Lymphocytes During Early Phases of Adaptive Immune Responses Against TB Infection - Linge, Irina; Tsareva, Anastasiya; Kondratieva, Elena; Dyatlov, Alexander; Hidalgo, Juan; Zvartsev, Ruslan; Apt, Alexander (Frontiers in Immunology, 2022)
The role of B cells migrating to the lung and forming follicles during tuberculosis (TB) inflammation is still the subject of debate. In addition to their antibody production and antigen-presenting functions, B cells secrete different cytokines and chemokines, thus participating in complex networks of innate and adaptive immunity. Importantly, lung B-cells produce high amounts of the pleiotropic gp130 cytokine IL-6. Its role during TB infection remains controversial, partly due to the fact that IL-6 is produced by different cell types. To investigate the impact of IL-6 produced by B cells on TB susceptibility and immune responses, we established a mouse strain with specific IL-6 deficiency in B cells (CD19cre-IL-6fl/fl, B-IL-6KO) on the B6 genetic background. Selective abrogation of IL-6 in B cells resulted in shortening the lifespan of TB-infected B-IL-6KO mice compare to the wild-type controls. We provide evidence that at the initial TB stages B cells serve as a critical source of IL-6. In the lung, the effect of IL-6 deficiency in B cells is associated rather with B and T cell functioning, than with macrophage polarization. TB-infected B-IL-6KO mice displayed diminished sizes of B cells themselves, CD4+IFN-γ+, Th17+, and CD4+CXCR5+ follicular T cell populations. The pleiotropic effect of B-cell-derived IL-6 on T-cells demonstrated in our study bridges two major lymphocyte populations and sheds some light on B- and T-cells interactions during the stage of anti-TB response when the host switches on a plethora of acquired immune reactions.
Keywords: Mycobacterium tuberculosis; Animals; tuberculosis; Tuberculosis, Pulmonary; Mice; Female; Adaptive Immunity; Mice, Inbred C57BL; B-Lymphocytes; T cells; Interleukin-6; Ablation Techniques; B-cells; IL-6; lung inflammation

Interleukin-10 promotes Mycobacterium tuberculosis disease progression in CBA/J mice - Beamer, Gillian L.; Flaherty, David K.; Assogba, Barnabe D.; Stromberg, Paul; Gonzalez-Juarrero, Mercedes; de Waal Malefyt, Rene; Vesosky, Bridget; Turner, Joanne (Journal of Immunology (Baltimore, Md.: 1950), 2008)
IL-10 is a potent immunomodulatory cytokine that affects innate and acquired immune responses. The immunological consequences of IL-10 production during pulmonary tuberculosis (TB) are currently unknown, although IL-10 has been implicated in reactivation TB in humans and with TB disease in mice. Using Mycobacterium tuberculosis-susceptible CBA/J mice, we show that blocking the action of IL-10 in vivo during chronic infection stabilized the pulmonary bacterial load and improved survival. Furthermore, this beneficial outcome was highly associated with the recruitment of T cells to the lungs and enhanced T cell IFN-gamma production. Our results indicate that IL-10 promotes TB disease progression. These findings have important diagnostic and/or therapeutic implications for the prevention of reactivation TB in humans.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Mice; Female; Lung; Interferon-gamma; T-Lymphocytes; Chronic Disease; Interleukin-10

Apoptotic vesicles crossprime CD8 T cells and protect against tuberculosis - Winau, Florian; Weber, Stephan; Sad, Subash; de Diego, Juana; Hoops, Silvia Locatelli; Breiden, Bernadette; Sandhoff, Konrad; Brinkmann, Volker; Kaufmann, Stefan H. E.; Schaible, Ulrich E. (Immunity, 2006)
CD8 T lymphocytes are important effectors in protective immunity against Mycobacterium tuberculosis. We recently characterized the detour pathway of CD8 T cell activation in tuberculosis mediated by apoptotic vesicles from infected cells that transport mycobacterial antigens to dendritic cells (DCs). Here we demonstrate that apoptotic vesicles from mycobacteria-infected macrophages stimulate CD8 T cells in vivo. Homing of DCs to draining lymph nodes was critically required for effective crosspriming. Subsequent fate of vesicle-associated antigens in recipient DCs was characterized by endosomal mechanisms predominating over proteasomal processing. In addition, vesicle processing depended on the presence of saposins to disintegrate apoptotic membranes. Apoptotic vesicles displayed potent adjuvant activity by stimulating through Toll-like receptors (TLR). Ultimately, vaccination with vesicles from infected cells induced protection against M. tuberculosis infection. Taken together, we propose the detour pathway to represent a genuine immunological mechanism mediating crosspriming of CD8 T cells in vivo and protection against tuberculosis.
Keywords: Animals; Macrophages; Tuberculosis; BCG Vaccine; Mice; Adjuvants, Immunologic; CD8-Positive T-Lymphocytes; Dendritic Cells; Mycobacterium bovis; Vaccination; Apoptosis; Cross-Priming; Endosomes; Saposins; Toll-Like Receptors

CD4CD8 Double Positive T cell responses during Mycobacterium tuberculosis infection in cynomolgus macaques - Diedrich, Collin Richard; Gideon, Hannah Priyadarshini; Rutledge, Tara; Baranowski, Tonilynn Marie; Maiello, Pauline; Myers, Amy J.; Lin, Philana Ling (Journal of Medical Primatology, 2019)
BACKGROUND: Tuberculosis (TB) kills millions of people every year. CD4 and CD8 T cells are critical in the immune response against TB. T cells expressing both CD4 and CD8 (CD4CD8 T cells) are functionally active and have not been examined in the context of TB. METHODS: We examine peripheral blood mononuclear cells (PBMC) and bronchoalveolar lavage cells (BAL) and lung granulomas from 28 cynomolgus macaques during Mycobacterium tuberculosis (Mtb) infection. RESULTS: CD4CD8 T cells increase in frequency during early Mtb infection in PBMC and BAL from pre-infection. Peripheral, airway, and lung granuloma CD4CD8 T cells have distinct patterns and greater cytokine production than CD4 or CD8 T cells. CONCLUSION: Our data suggest that CD4CD8 T cells transient the blood and airways early during infection to reach the granulomas where they are involved directly in the host response to Mtb.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; tuberculosis; Disease Models, Animal; Granuloma; Macaca fascicularis; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; mycobacteria; T cells; CD4CD8; Leukocytes

CD4+/CD8+ double-positive T cells: more than just a developmental stage? - Overgaard, Nana H.; Jung, Ji-Won; Steptoe, Raymond J.; Wells, James W. (Journal of Leukocyte Biology, 2015)
CD4(+)/CD8(+) DP thymocytes are a well-described T cell developmental stage within the thymus. However, once differentiated, the CD4(+) lineage or the CD8(+) lineage is generally considered to be fixed. Nevertheless, mature CD4(+)/CD8(+) DP T cells have been described in the blood and peripheral lymphoid tissues of numerous species, as well as in numerous disease settings, including cancer. The expression of CD4 and CD8 is regulated by a very strict transcriptional program involving the transcription factors Runx3 and ThPOK. Initially thought to be mutually exclusive within CD4(+) and CD8(+) T cells, CD4(+)/CD8(+) T cell populations, outside of the thymus, have recently been described to express concurrently ThPOK and Runx3. Considerable heterogeneity exists within the CD4(+)/CD8(+) DP T cell pool, and the function of CD4(+)/CD8(+) T cell populations remains controversial, with conflicting reports describing cytotoxic or suppressive roles for these cells. In this review, we describe how transcriptional regulation, lineage of origin, heterogeneity of CD4 and CD8 expression, age, species, and specific disease settings influence the functionality of this rarely studied T cell population.
Keywords: Humans; Animals; Cell Differentiation; T-Lymphocyte Subsets; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; cytotoxic potential; immune regulation; T cell plasticity

B-Cells and Antibodies as Contributors to Effector Immune Responses in Tuberculosis - Rijnink, Willemijn F.; Ottenhoff, Tom H. M.; Joosten, Simone A. (Frontiers in Immunology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is still a major threat to mankind, urgently requiring improved vaccination and therapeutic strategies to reduce TB-disease burden. Most present vaccination strategies mainly aim to induce cell-mediated immunity (CMI), yet a series of independent studies has shown that B-cells and antibodies (Abs) may contribute significantly to reduce the mycobacterial burden. Although early studies using B-cell knock out animals did not support a major role for B-cells, more recent studies have provided new evidence that B-cells and Abs can contribute significantly to host defense against Mtb. B-cells and Abs exist in many different functional subsets, each equipped with unique functional properties. In this review, we will summarize current evidence on the contribution of B-cells and Abs to immunity toward Mtb, their potential utility as biomarkers, and their functional contribution to Mtb control.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; antibodies; B-Lymphocytes; Immunity, Humoral; B-cells; biomarker; humoral immunity

Macrophage Heterogeneity in the Immunopathogenesis of Tuberculosis - Marakalala, Mohlopheni J.; Martinez, Fernando O.; Plüddemann, Annette; Gordon, Siamon (Frontiers in Microbiology, 2018)
Macrophages play a central role in tuberculosis, as the site of primary infection, inducers and effectors of inflammation, innate and adaptive immunity, as well as mediators of tissue destruction and repair. Early descriptions by pathologists have emphasized their morphological heterogeneity in granulomas, followed by delineation of T lymphocyte-dependent activation of anti-mycobacterial resistance. More recently, powerful genetic and molecular tools have become available to describe macrophage cellular properties and their role in host-pathogen interactions. In this review we discuss aspects of macrophage heterogeneity relevant to the pathogenesis of tuberculosis and, conversely, lessons that can be learnt from mycobacterial infection, with regard to the immunobiological functions of macrophages in homeostasis and disease.
Keywords: Mycobacterium tuberculosis; tuberculosis; immunopathogenesis; macrophage; macrophage heterogeneity4; pulmonary

The in vitro direct mycobacterial growth inhibition assay (MGIA) for the early evaluation of TB vaccine candidates and assessment of protective immunity: a protocol for non-human primate cells - Tanner, Rachel; Hoogkamer, Emily; Bitencourt, Julia; White, Andrew; Boot, Charelle; Sombroek, Claudia C.; Harris, Stephanie A.; O'Shea, Matthew K.; Wright, Daniel; Wittenberg, Rachel; Sarfas, Charlotte; Satti, Iman; et al. (F1000Research, 2021)
The only currently available approach to early efficacy testing of tuberculosis (TB) vaccine candidates is in vivo preclinical challenge models. These typically include mice, guinea pigs and non-human primates (NHPs), which must be exposed to virulent M.tb in a 'challenge' experiment following vaccination in order to evaluate protective efficacy. This procedure results in disease development and is classified as 'Moderate' in severity under EU legislation and UK ASPA licensure. Furthermore, experiments are relatively long and animals must be maintained in high containment level facilities, making them relatively costly. We describe an in vitro protocol for the direct mycobacterial growth inhibition assay (MGIA) for use in the macaque model of TB vaccine development with the aim of overcoming some of these limitations. Importantly, using an in vitro assay in place of in vivo M.tb challenge represents a significant refinement to the existing procedure for early vaccine efficacy testing. Peripheral blood mononuclear cell and autologous serum samples collected from vaccinated and unvaccinated control animals are co-cultured with mycobacteria in a 48-well plate format for 96 hours. Adherent monocytes are then lysed to release intracellular mycobacteria which is quantified using the BACTEC MGIT system and colony-forming units determined relative to an inoculum control and stock standard curve. We discuss related optimisation and characterisation experiments, and review evidence that the direct NHP MGIA provides a biologically relevant model of vaccine-induced protection. The potential end-users of the NHP MGIA are academic and industry organisations that conduct the assessment of TB vaccine candidates and associated protective immunity using the NHP model. This approach aims to provide a method for high-throughput down-selection of vaccine candidates going forward to in vivo efficacy testing, thus expediting the development of a more efficacious TB vaccine and offering potential refinement and reduction to the use of NHPs for this purpose.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; Guinea Pigs; Mice; Primates; 3Rs; macaque; non-human primate; Leukocytes, Mononuclear; vaccines; mycobacterial growth inhibition assay; refinement

Intracellular growth of Mycobacterium tuberculosis after macrophage cell death leads to serial killing of host cells - Mahamed, Deeqa; Boulle, Mikael; Ganga, Yashica; Mc Arthur, Chanelle; Skroch, Steven; Oom, Lance; Catinas, Oana; Pillay, Kelly; Naicker, Myshnee; Rampersad, Sanisha; Mathonsi, Colisile; Hunter, Jessica; et al. (eLife, 2017)
A hallmark of pulmonary tuberculosis is the formation of macrophage-rich granulomas. These may restrict Mycobacterium tuberculosis (Mtb) growth, or progress to central necrosis and cavitation, facilitating pathogen growth. To determine factors leading to Mtb proliferation and host cell death, we used live cell imaging to track Mtb infection outcomes in individual primary human macrophages. Internalization of Mtb aggregates caused macrophage death, and phagocytosis of large aggregates was more cytotoxic than multiple small aggregates containing similar numbers of bacilli. Macrophage death did not result in clearance of Mtb. Rather, it led to accelerated intracellular Mtb growth regardless of prior activation or macrophage type. In contrast, bacillary replication was controlled in live phagocytes. Mtb grew as a clump in dead cells, and macrophages which internalized dead infected cells were very likely to die themselves, leading to a cell death cascade. This demonstrates how pathogen virulence can be achieved through numbers and aggregation states.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Endocytosis; Cells, Cultured; human; Cell Death; computational biology; human macrophages; infection dynamics; infectious disease; Intravital Microscopy; live cell imaging; microbiology; necrosis; systems biology

Intracellular growth of Mycobacterium tuberculosis after macrophage cell death leads to serial killing of host cells - Mahamed, Deeqa; Boulle, Mikael; Ganga, Yashica; Mc Arthur, Chanelle; Skroch, Steven; Oom, Lance; Catinas, Oana; Pillay, Kelly; Naicker, Myshnee; Rampersad, Sanisha; Mathonsi, Colisile; Hunter, Jessica; et al. (eLife, 2017)
A hallmark of pulmonary tuberculosis is the formation of macrophage-rich granulomas. These may restrict Mycobacterium tuberculosis (Mtb) growth, or progress to central necrosis and cavitation, facilitating pathogen growth. To determine factors leading to Mtb proliferation and host cell death, we used live cell imaging to track Mtb infection outcomes in individual primary human macrophages. Internalization of Mtb aggregates caused macrophage death, and phagocytosis of large aggregates was more cytotoxic than multiple small aggregates containing similar numbers of bacilli. Macrophage death did not result in clearance of Mtb. Rather, it led to accelerated intracellular Mtb growth regardless of prior activation or macrophage type. In contrast, bacillary replication was controlled in live phagocytes. Mtb grew as a clump in dead cells, and macrophages which internalized dead infected cells were very likely to die themselves, leading to a cell death cascade. This demonstrates how pathogen virulence can be achieved through numbers and aggregation states.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Endocytosis; Cells, Cultured; human; Cell Death; computational biology; human macrophages; infection dynamics; infectious disease; Intravital Microscopy; live cell imaging; microbiology; necrosis; systems biology

Whole genome profiling refines a panel of correlates to predict vaccine efficacy against Mycobacterium tuberculosis - Kurtz, Sherry L.; Gardina, Paul J.; Myers, Timothy G.; Rydén, Patrik; Elkins, Karen L. (Tuberculosis (Edinburgh, Scotland), 2020)
New vaccines are needed to combat the public health threat posed by M. tuberculosis (M. tb), but no correlates have been defined to aid vaccine development. Using mouse models, we previously developed an in vitro system that measures the ability of M. tb-immune lymphocytes to control bacterial replication during co-culture with M. tb-infected macrophages. We demonstrated that the degree of in vitro growth control by lymphocytes from mice given vaccines of varying efficacy reflected the relative degree of in vivo protection against lethal challenge. Further, using targeted analyses of gene expression in lymphocytes recovered from co-cultures, we found mediators whose relative expression also correlated with in vitro and in vivo outcomes. Here we advanced those findings by employing genome-wide expression analyses. We first screened splenocytes recovered from co-cultures by microarray, revealing additional genes whose expression correlated with protection. After applying pathway analyses to down-select gene candidates, we used both splenocytes and peripheral blood lymphocytes to validate microarray findings by qRT-PCR. We then subjected data from top candidates to rigorous statistical analyses. Resulting correlate candidates, including CXCL9, IFN-γ, and CCL5, significantly predicted protection with high specificity. These findings therefore refine and extend a panel of relevant immune correlates to advance vaccine development.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Macrophages; Gene Expression Profiling; Vaccine; Cells, Cultured; Interferon-gamma; Biomarkers; T-Lymphocytes; Mice, Inbred C57BL; Coculture Techniques; Male; Vaccination; Gene expression; Oligonucleotide Array Sequence Analysis; Transcriptome; Chemokine CCL5; Chemokine CXCL9; Correlates; Genome-Wide Association Study; T lymphocytes

A Case for Antibodies as Mechanistic Correlates of Immunity in Tuberculosis - Kawahara, Jeffrey Y.; Irvine, Edward B.; Alter, Galit (Frontiers in Immunology, 2019)
Tuberculosis infects one quarter of the world's population and is the leading cause of death by a single infectious agent, responsible for a reported 1.3 million deaths in 2017. While Mycobacterium tuberculosis is treatable with antibiotic therapy, the increased prevalence of drug resistance, coupled with the variable efficacy of the only widely approved vaccine, has highlighted the need for creative approaches to therapeutic and vaccine development. Historically, a productive immune response to M. tuberculosis has been thought to be nearly entirely cell-mediated, with humoral immunity being largely dismissed. However, in this review, we will discuss the historical skepticism surrounding the role of the humoral immune response to M. tuberculosis, and examine more recent evidence suggesting that antibodies may play a valuable role in host defense against the pathogen. Despite the amount of data portraying antibodies in a negative light, emerging data have begun to highlight the unexpected role of antibodies in M. tuberculosis control. Specifically, it has become clear that antibody features of both the variable and constant domain (Fc) ultimately determine the extent to which antibodies modulate disease. Thus, a more precise definition of the antigen-binding and innate immune recruiting functions of antibodies that contribute to M. tuberculosis restriction, are sure to help guide the development of next-generation therapeutics and vaccines to curb this global epidemic.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; Immunity, Innate; antibodies; Immunity, Humoral; Immunoglobulin Fc Fragments; Antigen Presentation; humoral immunity; cell-mediated immunity; Fc effector function; innate immune system

Mycobacterium Growth Inhibition Assay of Human Alveolar Macrophages as a Correlate of Immune Protection Following Mycobacterium bovis Bacille Calmette-Guérin Vaccination - Radloff, Juliane; Heyckendorf, Jan; van der Merwe, Lize; Sanchez Carballo, Patricia; Reiling, Norbert; Richter, Elvira; Lange, Christoph; Kalsdorf, Barbara (Frontiers in Immunology, 2018)
BACKGROUND: In order to eliminate tuberculosis (TB), an effective vaccine is urgently needed to prevent infection with Mycobacterium tuberculosis. A key obstacle for the development of novel TB vaccines is the lack of surrogate markers for immune protection against M. tuberculosis. METHODS: We investigated growth rates of M. tuberculosis in the mycobacterial growth inhibition assay (MGIA) as a marker for mycobacterial growth control of human bronchoalveolar lavage (BALC) and peripheral blood mononuclear cells (PBMC) before and after vaccination with Mycobacterium bovis Bacille Calmette-Guérin (BCG) of healthy adult volunteers. RESULTS: Vaccination induced a positive response (p < 0.001) to purified protein derivate (PPD) in 58.8% of the individuals in an interferon-γ release assay-ELISpot. Intraindividual evaluation of the MGIA growth rates before and after M. bovis BCG-vaccination revealed no significant difference in time to culture positivity before and after vaccination in BALC (p = 0.604) and PBMC (p = 0.199). The magnitude of the PPD-response induced by M. bovis BCG-vaccination did not correlate with growth control in BALC and PBMC (correlation = 0.468, 95% CI: -0.016 to 0.775). CONCLUSION: In conclusion, M. bovis BCG-vaccination-induced mycobacterial-specific cytokine immune response does not result in functional immune control against M. tuberculosis in the MGIA.
Keywords: tuberculosis; vaccine; mycobacterial growth inhibition assay; Bacille Calmette–Guérin; interferon-γ release assay immune response; vitamin D

The Role of Nitric Oxide in Mycobacterial Infections - Yang, Chul-Su; Yuk, Jae-Min; Jo, Eun-Kyeong (Immune Network : Official Journal of the Korean Society for Immunology and Biological Response Modifiers, 2009)
Although tuberculosis poses a significant health threat to the global population, it is a challenge to develop new and effective therapeutic strategies. Nitric oxide (NO) and inducible NO synthase (iNOS) are important in innate immune responses to various intracellular bacterial infections, including mycobacterial infections. It is generally recognized that reactive nitrogen intermediates play an effective role in host defense mechanisms against tuberculosis. In a murine model of tuberculosis, NO plays a crucial role in antimycobacterial activity; however, it is controversial whether NO is critically involved in host defense against Mycobacterium tuberculosis in humans. Here, we review the roles of NO in host defense against murine and human tuberculosis. We also discuss the specific roles of NO in the central nervous system and lung epithelial cells during mycobacterial infection. A greater understanding of these defense mechanisms in human tuberculosis will aid in the development of new strategies for the treatment of disease.

Nitric Oxide in the Pathogenesis and Treatment of Tuberculosis - Jamaati, Hamidreza; Mortaz, Esmaeil; Pajouhi, Zeinab; Folkerts, Gert; Movassaghi, Mehrnaz; Moloudizargari, Milad; Adcock, Ian M.; Garssen, Johan (Frontiers in Microbiology, 2017)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is globally known as one of the most important human pathogens. Mtb is estimated to infect nearly one third of the world's population with many subjects having a latent infection. Thus, from an estimated 2 billion people infected with Mtb, less than 10% may develop symptomatic TB. This indicates that the host immune system may constrain pathogen replication in most infected individuals. On entering the lungs of the host, Mtb initially encounters resident alveolar macrophages which can engulf and subsequently eliminate intracellular microbes via a plethora of bactericidal mechanisms including the generation of free radicals such as reactive oxygen and nitrogen species. Nitric oxide (NO), a key anti-mycobacterial molecule, is detected in the exhaled breath of patients infected with Mtb. Recent knowledge regarding the regulatory role of NO in airway function and Mtb proliferation paves the way of exploiting the beneficial effects of this molecule for the treatment of airway diseases. Here, we discuss the importance of NO in the pathogenesis of TB, the diagnostic use of exhaled and urinary NO in Mtb infection and the potential of NO-based treatments.
Keywords: Mycobacterium; drug-resistance; macrophages; nitric oxide; nitric oxide donors; non-tuberculous mycobacteria

Mycobacterium tuberculosis (MTB)-stimulated production of nitric oxide by human alveolar macrophages and relationship of nitric oxide production to growth inhibition of MTB - Rich, E. A.; Torres, M.; Sada, E.; Finegan, C. K.; Hamilton, B. D.; Toossi, Z. (Tubercle and Lung Disease: The Official Journal of the International Union Against Tuberculosis and Lung Disease, 1997)
SETTING: Although nitric oxide (NO) is a major proximate mediator of microbicidal activity in murine macrophages against intracellular pathogens including mycobacteria, its production by and effector role in human macrophages is not clear. OBJECTIVE: To determine the capacity of Mycobacterium tuberculosis (MTB) to stimulate NO in human monocytes (MN) and alveolar macrophages (AM) and to assess the relationship between NO production and intracellular growth of MTB. DESIGN: NO production (measured as nitrite) by MTB (H37Ra)-infected macrophages and intracellular growth of MTB were measured in cells from 17 healthy subjects. RESULTS: MTB (5:1, MTB:cells) stimulated little to no NO by MN, but induced NO in AM at days 4 and 7 after infection. There was, however, variability in the response by AM to MTB: among seven subjects MTB-induced NO was low (4 +/- 2 microM, mean +/- SE); six subjects were moderate (56 +/- 11); four subjects were high (502 +/- 167). NO synthase inhibitors inhibited the production of NO by AM but did not significantly affect the intracellular growth of MTB, although a trend towards increased intracellular growth was seen on day 4 of culture. Intracellular growth of MTB in AM from low NO producers was significantly higher than that in AM from moderate NO producers, P < or = 0.05. Inducible NO synthase (iNOS) mRNA by RT-PCR was constitutively expressed by both MN and AM, but was further stimulated by MTB in AM > MN; MTB-induced iNOS protein was present in both MN and AM by Western blot analysis. CONCLUSION: Thus, MTB-infected human AM are capable of producing NO and NO production correlates with intracellular growth inhibition of MTB in AM suggesting that NO may serve either directly or indirectly as a mycobactericidal mediator in human tissue macrophages.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Reverse Transcriptase Polymerase Chain Reaction; Female; Adult; Male; Middle Aged; Colony Count, Microbial; RNA, Messenger; Cell Culture Techniques; Nitric Oxide; Nitric Oxide Synthase; Enzyme Inhibitors; Macrophages, Alveolar

Host-directed therapy to combat mycobacterial infections - Kilinç, Gül; Saris, Anno; Ottenhoff, Tom H. M.; Haks, Mariëlle C. (Immunological Reviews, 2021)
Upon infection, mycobacteria, such as Mycobacterium tuberculosis (Mtb) and nontuberculous mycobacteria (NTM), are recognized by host innate immune cells, triggering a series of intracellular processes that promote mycobacterial killing. Mycobacteria, however, have developed multiple counter-strategies to persist and survive inside host cells. By manipulating host effector mechanisms, including phagosome maturation, vacuolar escape, autophagy, antigen presentation, and metabolic pathways, pathogenic mycobacteria are able to establish long-lasting infection. Counteracting these mycobacteria-induced host modifying mechanisms can be accomplished by host-directed therapeutic (HDT) strategies. HDTs offer several major advantages compared to conventional antibiotics: (a) HDTs can be effective against both drug-resistant and drug-susceptible bacteria, as well as potentially dormant mycobacteria; (b) HDTs are less likely to induce bacterial drug resistance; and (c) HDTs could synergize with, or shorten antibiotic treatment by targeting different pathways. In this review, we will explore host-pathogen interactions that have been identified for Mtb for which potential HDTs impacting both innate and adaptive immunity are available, and outline those worthy of future research. We will also discuss possibilities to target NTM infection by HDT, although current knowledge regarding host-pathogen interactions for NTM is limited compared to Mtb. Finally, we speculate that combinatorial HDT strategies can potentially synergize to achieve optimal mycobacterial host immune control.
Keywords: Mycobacterium tuberculosis; Host-Pathogen Interactions; Anti-Bacterial Agents; Mycobacterium avium; host-directed therapy; Autophagy; drug resistance; nontuberculous mycobacteria; Nontuberculous Mycobacteria

Preexisting Heterogeneity of Inducible Nitric Oxide Synthase Expression Drives Differential Growth of Mycobacterium tuberculosis in Macrophages - Rutschmann, Ophélie; Toniolo, Chiara; McKinney, John D. (mBio, 2022)
Mycobacterium tuberculosis infection is initiated by the inhalation and implantation of bacteria in the lung alveoli, where they are phagocytosed by macrophages. Even a single bacterium may be sufficient to initiate infection. Thereafter, the clinical outcome is highly variable between individuals, ranging from sterilization to active disease, for reasons that are not well understood. Here, we show that the rate of intracellular bacterial growth varies markedly between individual macrophages, and this heterogeneity is driven by cell-to-cell variation of inducible nitric oxide synthase (iNOS) activity. At the single-cell level, iNOS expression fluctuates over time, independent of infection or activation with gamma interferon. We conclude that chance encounters between individual bacteria and host cells randomly expressing different levels of an antibacterial gene can determine the outcome of single-cell infections, which may explain why some exposed individuals clear the bacteria while others develop progressive disease. IMPORTANCE In this report, we demonstrate that fluctuations in the expression of antimicrobial genes can define how single host cells control bacterial infections. We show that preexisting cell-to-cell variation in the expression of a single gene, that for inducible nitric oxide synthase, is sufficient to explain why some macrophages kill intracellular M. tuberculosis while others fail to control bacterial replication, possibly leading to disease progression. We introduce the concept that chance encounters between heterogeneous bacteria and host cells can determine the outcome of a host-pathogen interaction. This concept is particularly relevant for all the infectious diseases in which the number of interacting pathogens and host cells is small at some point during the infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Anti-Bacterial Agents; Interferon-gamma; innate immunity; Nitric Oxide; Nitric Oxide Synthase; macrophages; gamma interferon (IFN-γ); heterogeneity; inducible nitric oxide synthase (iNOS); microscopy; Nitric Oxide Synthase Type II; single-cell; time-lapse

The Immune Escape Mechanisms of Mycobacterium Tuberculosis - Zhai, Weijie; Wu, Fengjuan; Zhang, Yiyuan; Fu, Yurong; Liu, Zhijun (International Journal of Molecular Sciences, 2019)
Epidemiological data from the Center of Disease Control (CDC) and the World Health Organization (WHO) statistics in 2017 show that 10.0 million people around the world became sick with tuberculosis. Mycobacterium tuberculosis (MTB) is an intracellular parasite that mainly attacks macrophages and inhibits their apoptosis. It can become a long-term infection in humans, causing a series of pathological changes and clinical manifestations. In this review, we summarize innate immunity including the inhibition of antioxidants, the maturation and acidification of phagolysosomes and especially the apoptosis and autophagy of macrophages. Besides, we also elaborate on the adaptive immune response and the formation of granulomas. A thorough understanding of these escape mechanisms is of major importance for the prevention, diagnosis and treatment of tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; immunology; Phagosomes; Immune Evasion; Apoptosis; Autophagy; macrophages; apoptosis; immune escape; Oxidative Stress

Stealth Strategies of Mycobacterium tuberculosis for Immune Evasion - Naeem, Muhammad Ahsan; Ahmad, Waqas; Tyagi, Rohit; Akram, Qaiser; Younus, Muhammad; Liu, Xilin (Current Issues in Molecular Biology, 2021)
Tuberculosis is a devastating disease causing high mortality all over the world, especially in the developing countries. Mycobacterium tuberculosis (M. tb) is the causative agent of tuberculosis which replicates in the intracellular environment of host macrophages. Although the host immune system is capable of completely eliminating the pathogen, co-evolution of M. tb with humans has resulted in its ability to hijack the host innate and adaptive immune systems in numerous ways. Limited recent progress has been made in the understanding of M. tb immune escape mechanisms, hence exploration of survival strategies of M. tb has been critically reviewed with an insight into understanding its pathogenesis. We summarized the recent studies regarding the modulation of innate immune response, adaptive immune response, epigenetics and the role of miRNA. All of these advancements suggest that M. tb is well-familiarize with the host immune system and possess the ability to hijack it for intracellular survival.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Adaptive Immunity; Immunity, Innate; Immune Evasion; MicroRNAs

Mycobacterium Tuberculosis and Interactions with the Host Immune System: Opportunities for Nanoparticle Based Immunotherapeutics and Vaccines - Bekale, Raymonde B.; Du Plessis, Su-Mari; Hsu, Nai-Jen; Sharma, Jyoti R.; Sampson, Samantha L.; Jacobs, Muazzam; Meyer, Mervin; Morse, Gene D.; Dube, Admire (Pharmaceutical Research, 2018)
Tuberculosis (TB) caused by Mycobacterium tuberculosis remains a deadly infectious disease. The thin pipeline of new drugs for TB, the ineffectiveness in adults of the only vaccine available, i.e. the Bacillus Calmette-Guerin vaccine, and increasing global antimicrobial resistance, has reinvigorated interest in immunotherapies. Nanoparticles (NPs) potentiate the effect of immune modulating compounds (IMC), enabling cell targeting, improved transfection of antigens, enhanced compound stability and provide opportunities for synergistic action, via delivery of multiple IMCs. In this review we describe work performed in the application of NPs towards achieving immune modulation for TB treatment and vaccination. Firstly, we present a comprehensive review of M. tuberculosis and how the bacterium modulates the host immune system. We find that current work suggest great promise of NP based immunotherapeutics as novel treatments and vaccination systems. There is need to intensify research efforts in this field, and rationally design novel NP immunotherapeutics based on current knowledge of the mycobacteriology and immune escape mechanisms employed by M. tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Tuberculosis; Vaccination; Immunotherapy; Immune System; immunotherapeutic nanoparticles; immunotherapy for tuberculosis; nanoparticle based host directed therapy; Nanoparticles; nanoparticles and vaccination

Mycobacterium tuberculosis SufR responds to nitric oxide via its 4Fe-4S cluster and regulates Fe-S cluster biogenesis for persistence in mice - Anand, Kushi; Tripathi, Ashutosh; Shukla, Kaustubh; Malhotra, Nitish; Jamithireddy, Anil Kumar; Jha, Rajiv Kumar; Chaudhury, Susmit Narayan; Rajmani, Raju S.; Ramesh, Arati; Nagaraja, Valakunja; Gopal, Balasubramanian; Nagaraju, Ganesh; et al. (Redox Biology, 2021)
The persistence of Mycobacterium tuberculosis (Mtb) is a major problem in managing tuberculosis (TB). Host-generated nitric oxide (NO) is perceived as one of the signals by Mtb to reprogram metabolism and respiration for persistence. However, the mechanisms involved in NO sensing and reorganizing Mtb's physiology are not fully understood. Since NO damages iron-sulfur (Fe-S) clusters of essential enzymes, the mechanism(s) involved in regulating Fe-S cluster biogenesis could help Mtb persist in host tissues. Here, we show that a transcription factor SufR (Rv1460) senses NO via its 4Fe-4S cluster and promotes persistence of Mtb by mobilizing the Fe-S cluster biogenesis system; suf operon (Rv1460-Rv1466). Analysis of anaerobically purified SufR by UV-visible spectroscopy, circular dichroism, and iron-sulfide estimation confirms the presence of a 4Fe-4S cluster. Atmospheric O2 and H2O2 gradually degrade the 4Fe-4S cluster of SufR. Furthermore, electron paramagnetic resonance (EPR) analysis demonstrates that NO directly targets SufR 4Fe-4S cluster by forming a protein-bound dinitrosyl-iron-dithiol complex. DNase I footprinting, gel-shift, and in vitro transcription assays confirm that SufR directly regulates the expression of the suf operon in response to NO. Consistent with this, RNA-sequencing of MtbΔsufR demonstrates deregulation of the suf operon under NO stress. Strikingly, NO inflicted irreversible damage upon Fe-S clusters to exhaust respiratory and redox buffering capacity of MtbΔsufR. Lastly, MtbΔsufR failed to recover from a NO-induced non-growing state and displayed persistence defect inside immune-activated macrophages and murine lungs in a NO-dependent manner. Data suggest that SufR is a sensor of NO that supports persistence by reprogramming Fe-S cluster metabolism and bioenergetics.
Keywords: Mycobacterium tuberculosis; Animals; Mice; Nitric Oxide; Dinitrosyl-iron-dithiol complex; Electron Spin Resonance Spectroscopy; Gene regulation; Hydrogen Peroxide; Inducible nitric oxide synthase; Iron-Sulfur Proteins; Operon; Redox potential; Spare respiratory capacity; Transcriptomics

Plasma levels of tumor necrosis factor-alpha, interferon-gamma, inducible nitric oxide synthase, and 3-nitrotyrosine in drug-resistant and drug-sensitive pulmonary tuberculosis patients, Ibadan, Nigeria - Bolajoko, Elizabeth Bosede; Arinola, Olatunbosun Ganiyu; Odaibo, Georgina Njideka; Maiga, Mamoudou (International Journal of Mycobacteriology, 2020)
BACKGROUND: Nigeria is one of the countries with a high burden of tuberculosis (TB) in the world. TB associated inflammation is reported to be central to progression from latent TB to active TB or drug sensitive TB (DSTB) to drug resistant TB (DRTB). Inflammatory cytokines, especially interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α), act synergistically in the control of TB infection. They activate macrophages to produce effector molecules such as inducible nitric oxide synthase (iNOS), nitric oxide, and ultimately 3-nitrotyrosines(3-NTs), which are involved in the control of TB. This study investigated the potential involvement of TNF-α, IFN-γ, iNOS, and 3-NT in differentiating DRTB and DSTB in Ibadan, Nigeria. METHODS: One hundred participants above 18 years were recruited into this study and were grouped as follows: 32 DRTB, 34 DSTB, and 34 apparently healthy controls. Plasma from the patients was used for the analyses of inflammatory (TNF α and IFN-γ) and oxidative stress (iNOS and 3-NT) biomarkers using the ELISA. Mann-Whitney test was applied for the statistical test. RESULTS: Mean levels of plasma TNF-α, IFN-γ, iNOS, and 3-NT were higher in DRTB (19.74 ± 3.62 pg/mL, 4.41 ± 0.96 pg/mL, 1791.07 ± 419.42 pg/mL, and 20.27 ± 1.80 ng/mL, respectively) and DSTB (17.02 ± 1.84 pg/mL, 5.59 ± 1.40 pg/mL, 2823.42 ± 685.32 pg/mL, and 25.06 ± 2.15 ng/mL, respectively) compared with controls (12.18 ± 0.92 pg/mL, 1.58 ± 0.21 pg/mL, 1275.86 ± 166.12 pg/mL, and 19.98 ± 1.23 ng/mL, respectively). In addition, higher plasma levels of IFN-γ (P > 0.05), iNOS (P > 0.05), and 3-NT (P < 0.05) were observed in DSTB compared with DRTB patients. CONCLUSION: The 3-NT may be used as differentiating markers of DSTB from DRTB.
Keywords: Humans; Tuberculosis, Pulmonary; Interferon-gamma; Biomarkers; Adult; Middle Aged; Young Adult; Adolescent; Aged; Inflammation; Tumor Necrosis Factor-alpha; Tuberculosis, Multidrug-Resistant; pulmonary tuberculosis; Nitric Oxide Synthase Type II; Oxidative Stress; 3-nitrotyrosine; inducible nitric oxide synthase; inflammatory cytokines; Nigeria; Tyrosine

Mycobacterium tuberculosis induces high production of nitric oxide in coordination with production of tumour necrosis factor-alpha in patients with fresh active tuberculosis but not in MDR tuberculosis - Sharma, Sadhna; Sharma, Monika; Roy, Sugata; Kumar, Praveen; Bose, Mridula (Immunology and Cell Biology, 2004)
Mycobacterium tuberculosis is an intracellular pathogen that readily survives and replicates in human macrophages. Host cells have developed various mycobactericidal and immunoregulatory mechanisms, such as the production of nitric oxide and inflammatory cytokines to control intracellular replication of M. tuberculosis. Inducible nitric oxide synthase (iNOS) is transcriptionally under the control of IFN-gamma and TNF-alpha. IL-12 provides a crucial link between activated mononuclear phagocytes and T cells by regulating the production of IFN-gamma. In this study, we investigated the production of nitric oxide (NO), TNF-alpha and IL-12 by the peripheral blood monocytes (PB Mn) of patients suffering from multidrug-resistant tuberculosis (MDR-TB). The cells were infected with M. tuberculosis and stimulated with IFN-gamma or activated with mycobacterial subcellular components. The results were compared with those from cases of newly diagnosed TB and healthy controls. Nitric oxide production was significantly depressed in PB Mn from MDR-TB patients. Infected monocytes from newly diagnosed TB patients produced significantly higher levels of NO as compared to those from MDR-TB patients or normal controls. The subcellular fraction of M. tuberculosis-like whole cell lysate (WCL), culture filtrate protein (CFP) and lipoarabinomannan (LAM) induced higher concentrations of NO release in PB Mn from newly diagnosed TB patients as compared to those from MDR-TB patients. Cell culture supernatant from PB Mn assayed at 48 h after infection or stimulation demonstrated significantly depressed release of TNF-alpha and IL-12 from MDR-TB cases as compared to the fresh cases. We observed a definite correlation between nitric oxide release and TNF-alpha production, irrespective of low or high production in MDR-TB or fresh cases, respectively. The present data suggest that peripheral blood monocytes of MDR-TB patients typically show signs of immunosuppression. Whether such immunodepression is the cause or the effect of MDR-TB merits further investigation.
Keywords: Humans; Mycobacterium tuberculosis; Monocytes; Tuberculosis, Pulmonary; Female; Interferon-gamma; Adult; Male; Interleukin-12; Tumor Necrosis Factor-alpha; Tuberculosis, Multidrug-Resistant; Nitric Oxide

Susceptibility to Intracellular Infections: Contributions of TNF to Immune Defense - Li, Xinying; Körner, Heinrich; Liu, Xiaoying (Frontiers in Microbiology, 2020)
An interesting puzzle is the fact that an infection of a tumor necrosis factor α (TNF)-deficient host with pathogens such as bacteria or parasites that reside intracellularly inevitably ends fatally. Is this due to one specific role of TNF in the immune defense or are different functions responsible for this outcome? In this review we provide an update of the functions of TNF in the defense against the intracellular pathogens Listeria monocytogenes, Mycobacterium tuberculosis, and Leishmania major. Furthermore, we discuss the role of TNF in the generation of proinflammatory macrophages in mouse models of infection and summarize briefly the potential consequences of anti-TNF treatment for infectious diseases.
Keywords: Mycobacterium tuberculosis; Leishmania major; Listeria monocytogenes; macrophage polarization; TNF

CD4 T Cell-Derived IFN-γ Plays a Minimal Role in Control of Pulmonary Mycobacterium tuberculosis Infection and Must Be Actively Repressed by PD-1 to Prevent Lethal Disease - Sakai, Shunsuke; Kauffman, Keith D.; Sallin, Michelle A.; Sharpe, Arlene H.; Young, Howard A.; Ganusov, Vitaly V.; Barber, Daniel L. (PLoS pathogens, 2016)
IFN-γ-producing CD4 T cells are required for protection against Mycobacterium tuberculosis (Mtb) infection, but the extent to which IFN-γ contributes to overall CD4 T cell-mediated protection remains unclear. Furthermore, it is not known if increasing IFN-γ production by CD4 T cells is desirable in Mtb infection. Here we show that IFN-γ accounts for only ~30% of CD4 T cell-dependent cumulative bacterial control in the lungs over the first six weeks of infection, but >80% of control in the spleen. Moreover, increasing the IFN-γ-producing capacity of CD4 T cells by ~2 fold exacerbates lung infection and leads to the early death of the host, despite enhancing control in the spleen. In addition, we show that the inhibitory receptor PD-1 facilitates host resistance to Mtb by preventing the detrimental over-production of IFN-γ by CD4 T cells. Specifically, PD-1 suppressed the parenchymal accumulation of and pathogenic IFN-γ production by the CXCR3+KLRG1-CX3CR1- subset of lung-homing CD4 T cells that otherwise mediates control of Mtb infection. Therefore, the primary role for T cell-derived IFN-γ in Mtb infection is at extra-pulmonary sites, and the host-protective subset of CD4 T cells requires negative regulation of IFN-γ production by PD-1 to prevent lethal immune-mediated pathology.
Keywords: Mycobacterium tuberculosis; Animals; Blotting, Western; Tuberculosis, Pulmonary; Flow Cytometry; Mice; Disease Models, Animal; Interferon-gamma; Cytokines; CD4-Positive T-Lymphocytes; Mice, Inbred C57BL; Adoptive Transfer; Mice, Knockout; Enzyme-Linked Immunosorbent Assay; Programmed Cell Death 1 Receptor

IFN-γ-independent control of M. tuberculosis requires CD4 T cell-derived GM-CSF and activation of HIF-1α - Van Dis, Erik; Fox, Douglas M.; Morrison, Huntly M.; Fines, Daniel M.; Babirye, Janet Peace; McCann, Lily H.; Rawal, Sagar; Cox, Jeffery S.; Stanley, Sarah A. (PLoS pathogens, 2022)
The prevailing model of protective immunity to tuberculosis is that CD4 T cells produce the cytokine IFN-γ to activate bactericidal mechanisms in infected macrophages. Although IFN-γ-independent CD4 T cell based control of M. tuberculosis infection has been demonstrated in vivo it is unclear whether CD4 T cells are capable of directly activating macrophages to control infection in the absence of IFN-γ. We developed a co-culture model using CD4 T cells isolated from the lungs of infected mice and M. tuberculosis-infected murine bone marrow-derived macrophages (BMDMs) to investigate mechanisms of CD4 dependent control of infection. We found that even in the absence of IFN-γ signaling, CD4 T cells drive macrophage activation, M1 polarization, and control of infection. This IFN-γ-independent control of infection requires activation of the transcription factor HIF-1α and a shift to aerobic glycolysis in infected macrophages. While HIF-1α activation following IFN-γ stimulation requires nitric oxide, HIF-1α-mediated control in the absence of IFN-γ is nitric oxide-independent, indicating that distinct pathways can activate HIF-1α during infection. We show that CD4 T cell-derived GM-CSF is required for IFN-γ-independent control in BMDMs, but that recombinant GM-CSF is insufficient to control infection in BMDMs or alveolar macrophages and does not rescue the absence of control by GM-CSF-deficient T cells. In contrast, recombinant GM-CSF controls infection in peritoneal macrophages, induces lipid droplet biogenesis, and also requires HIF-1α for control. These results advance our understanding of CD4 T cell-mediated immunity to M. tuberculosis, reveal important differences in immune activation of distinct macrophage types, and outline a novel mechanism for the activation of HIF-1α. We establish a previously unknown functional link between GM-CSF and HIF-1α and provide evidence that CD4 T cell-derived GM-CSF is a potent bactericidal effector.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Mice; Interferon-gamma; CD4-Positive T-Lymphocytes; Nitric Oxide; Granulocyte-Macrophage Colony-Stimulating Factor; Hypoxia-Inducible Factor 1, alpha Subunit

Antigen-Specific IFN-γ/IL-17-Co-Producing CD4+ T-Cells Are the Determinants for Protective Efficacy of Tuberculosis Subunit Vaccine - Choi, Han-Gyu; Kwon, Kee Woong; Choi, Seunga; Back, Yong Woo; Park, Hye-Soo; Kang, Soon Myung; Choi, Eunsol; Shin, Sung Jae; Kim, Hwa-Jung (Vaccines, 2020)
The antigen-specific Th17 responses in the lungs for improved immunity against Mycobacterium tuberculosis (Mtb) infection are incompletely understood. Tuberculosis (TB) vaccine candidate HSP90-ESAT-6 (E6), given as a Bacillus Calmette-Guérin (BCG)-prime boost regimen, confers superior long-term protection against the hypervirulent Mtb HN878 infection, compared to BCG or BCG-E6. Taking advantage of protective efficacy lead-out, we found that ESAT-6-specific multifunctional CD4+IFN-γ+IL-17+ T-cells optimally correlated with protection level against Mtb infection both pre-and post-challenge. Macrophages treated with the supernatant of re-stimulated lung cells from HSP90-E6-immunised mice significantly restricted Mtb growth, and this phenomenon was abrogated by neutralising anti-IFN-γ and/or anti-IL-17 antibodies. We identified a previously unrecognised role for IFN-γ/IL-17 synergism in linking anti-mycobacterial phagosomal activity to enhance host control against Mtb infection. The implications of our findings highlight the fundamental rationale for why and how Th17 responses are essential in the control of Mtb, and for the development of novel anti-TB subunit vaccines.
Keywords: Mycobacterium tuberculosis; BCG-prime boost; IFN-γ/IL-17; multifunctional T cells; phagosome maturation.

Polyfunctional CD4 T-cells correlate with in vitro mycobacterial growth inhibition following Mycobacterium bovis BCG-vaccination of infants - Smith, Steven G.; Zelmer, Andrea; Blitz, Rose; Fletcher, Helen A.; Dockrell, Hazel M. (Vaccine, 2016)
BACKGROUND: Vaccination with Bacillus Calmette Guerin (BCG) protects infants against childhood tuberculosis however the immune mechanisms involved are not well understood. Further elucidation of the infant immune response to BCG will aid with the identification of immune correlates of protection against tuberculosis and with the design of new improved vaccines. The purpose of this study was to investigate BCG-induced CD4+ T-cell responses in blood samples from infants for cytokine secretion profiles thought to be important for protection against tuberculosis and compare these to PBMC-mediated in vitro mycobacterial growth inhibition. METHODS: Blood from BCG-vaccinated or unvaccinated infants was stimulated overnight with Mycobacterium tuberculosis (M. tb) purified protein derivative (PPD) or controls and intracellular cytokine staining and flow cytometry used to measure CD4+T-cell responses. PBMC cryopreserved at the time of sample collection were thawed and incubated with live BCG for four days following which inhibition of BCG growth was determined. RESULTS: PPD-specific IFNγ+TNFα+IL-2+CD4+T-cells represented the dominant T-cell response at 4monthsand1yearafter infant BCG. These responses were undetectable in age-matched unvaccinated infants. IL-17+CD4+T-cells were significantly more frequent in vaccinated infants at 4monthsbut not at 1-year post-BCG. PBMC-mediated inhibition of mycobacterial growth was significantly enhanced at 4monthspost-BCG as compared to unvaccinated controls. In an analysis of all samples with both datasets available, mycobacterial growth inhibition correlated significantly with the frequency of polyfunctional (IFNγ+TNFα+IL-2+) CD4+T-cells. CONCLUSIONS: These data suggest that BCG vaccination of infants induces specific polyfunctional T-helper-1 and T-helper-17 responses and the ability, in the PBMC compartment, to inhibit the growth of mycobacteria in vitro. We also demonstrate that polyfunctional T-helper-1 cells may play a role in growth inhibition as evidenced by a significant correlation between the two.
Keywords: Humans; Flow Cytometry; BCG Vaccine; Female; Interferon-gamma; Cytokines; CD4-Positive T-Lymphocytes; Leukocytes, Mononuclear; Male; Lymphocyte Activation; Mycobacterium bovis; BCG; Th17 Cells; Tuberculin; Interleukin-2; Infant; Infants; Mycobacterial growth inhibition; Polyfunctional; T-cells

B cells and antibodies in the defense against Mycobacterium tuberculosis infection - Achkar, Jacqueline M.; Chan, John; Casadevall, Arturo (Immunological Reviews, 2015)
Better understanding of the immunological components and their interactions necessary to prevent or control Mycobacterium tuberculosis (Mtb) infection in humans is critical for tuberculosis (TB) vaccine development strategies. Although the contributory role of humoral immunity in the protection against Mtb infection and disease is less defined than the role of T cells, it has been well-established for many other intracellular pathogens. Here we update and discuss the increasing evidence and the mechanisms of B cells and antibodies in the defense against Mtb infection. We posit that B cells and antibodies have a variety of potential protective roles at each stage of Mtb infection and postulate that such roles should be considered in the development strategies for TB vaccines and other immune-based interventions.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; tuberculosis; Immunity, Innate; Immunity, Cellular; antibodies; B-Lymphocytes; Immunity, Humoral; B lymphocytes; Cell Communication; immunity; immunoglobulins

Updates on antibody functions in Mycobacterium tuberculosis infection and their relevance for developing a vaccine against tuberculosis - Achkar, Jacqueline M.; Prados-Rosales, Rafael (Current Opinion in Immunology, 2018)
A more effective vaccine to control tuberculosis (TB), a major global public health problem, is urgently needed. Current vaccine candidates focus predominantly on eliciting cell-mediated immunity but other arms of the immune system also contribute to protection against TB. We review here recent studies that enhance our current knowledge of antibody-mediated functions against Mycobacterium tuberculosis. These findings, which contribute to the increasing evidence that antibodies have a protective role against TB, include demonstrations that firstly distinct human antibody Fc glycosylation patterns, found in latent M. tuberculosis infection but not in active TB, influence the efficacy of the host to control M. tuberculosis infection, secondly antibody isotype influences human antibody functions, and thirdly that antibodies targeting M. tuberculosis surface antigens are protective. We discuss these findings in the context of TB vaccine development and highlight the need for further research on antibody-mediated immunity in M. tuberculosis infection.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Antigens, Bacterial; Tuberculosis; Glycosylation; Immunity, Humoral; Latent Tuberculosis; Vaccination

Phage display for epitope determination: a paradigm for identifying receptor-ligand interactions - Rowley, Merrill J.; O'Connor, Karen; Wijeyewickrema, Lakshmi (Biotechnology Annual Review, 2004)
Antibodies that react with many different molecular species of protein and non-protein nature are widely studied in biology and have particular utilities, but the precise epitopes recognized are seldom well defined. The definition of epitopes by X-ray crystallography of the antigen-antibody complex, the gold standard procedure, has shown that most antibody epitopes are conformational and specified by interactions with topographic determinants on the surface of the antigenic molecule. Techniques available for the definition of such epitopes are limited. Phage display using either gene-specific libraries, or random peptide libraries, provides a powerful technique for an approach to epitope identification. The technique can identify amino acids on protein antigens that are critical for antibody binding and, further, the isolation of peptide motifs that are both structural and functional mimotopes of both protein and non-protein antigens. This review discusses techniques used to isolate such mimotopes, to confirm their specificity, and to characterize peptide epitopes. Moreover there are direct practical applications to deriving epitopes or mimotopes by sequence, notably the development of new diagnostic reagents, or therapeutic agonist or antagonist molecules. The techniques developed for mapping of antibody epitopes are applicable to probing the origins of autoimmune diseases and certain cancers by identifying "immunofootprints" of unknown initiating agents, as we discuss herein, and are directly applicable to examination of a wider range of receptor-ligand interactions.
Keywords: Binding Sites; Protein Binding; Receptors, Cell Surface; Ligands; Epitopes; Epitope Mapping; Protein Interaction Mapping; Peptide Library

Purified protein derivatives of tuberculin--past, present, and future - Yang, Hongliang; Kruh-Garcia, Nicole A.; Dobos, Karen M. (FEMS immunology and medical microbiology, 2012)
The tuberculin skin test, which involves monitoring the immune reaction to an injection of purified protein derivative (PPD), has been the most widely used method for detecting infection with Mycobacterium tuberculosis since its development in 1930s. Until recently, the molecular composition of PPD was unknown. This thwarted the discovery of improved skin testing reagents and drastically hindered efforts to define the mechanism of action. Proteomic evaluation of PPD combined with a detailed analysis in the guinea pig model of tuberculosis led to further definition of the molecular composition of PPD. This communication reviews the history and current status of PPD, in addition to describing candidate next-generation PPD reagents, based on the use of an individual protein or protein cocktails.
Keywords: Humans; Animals; Tuberculosis Vaccines; Tuberculosis; Guinea Pigs; Tuberculin; Tuberculin Test; History, 20th Century; History, 21st Century

Latently and uninfected healthcare workers exposed to TB make protective antibodies against Mycobacterium tuberculosis - Li, Hao; Wang, Xing-Xing; Wang, Bin; Fu, Lei; Liu, Guan; Lu, Yu; Cao, Min; Huang, Hairong; Javid, Babak (Proceedings of the National Academy of Sciences of the United States of America, 2017)
The role of Igs in natural protection against infection by Mycobacterium tuberculosis (Mtb), the causative agent of TB, is controversial. Although passive immunization with mAbs generated against mycobacterial antigens has shown protective efficacy in murine models of infection, studies in B cell-depleted animals only showed modest phenotypes. We do not know if humans make protective antibody responses. Here, we investigated whether healthcare workers in a Beijing TB hospital-who, although exposed to suprainfectious doses of pathogenic Mtb, remain healthy-make antibody responses that are effective in protecting against infection by Mtb. We tested antibodies isolated from 48 healthcare workers and compared these with 12 patients with active TB. We found that antibodies from 7 of 48 healthcare workers but none from active TB patients showed moderate protection against Mtb in an aerosol mouse challenge model. Intriguingly, three of seven healthcare workers who made protective antibody responses had no evidence of prior TB infection by IFN-γ release assay. There was also good correlation between protection observed in vivo and neutralization of Mtb in an in vitro human whole-blood assay. Antibodies mediating protection were directed against the surface of Mtb and depended on both immune complexes and CD4+ T cells for efficacy. Our results indicate that certain individuals make protective antibodies against Mtb and challenge paradigms about the nature of an effective immune response to TB.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Mice; Disease Models, Animal; Female; antibodies; Adult; Male; Middle Aged; TB; Mice, Inbred BALB C; humoral immunity; immune complex; Mice, Nude; Occupational Exposure; Physicians; TB restrictors

IFN-γ-independent immune markers of Mycobacterium tuberculosis exposure - Lu, Lenette L.; Smith, Malisa T.; Yu, Krystle K. Q.; Luedemann, Corinne; Suscovich, Todd J.; Grace, Patricia S.; Cain, Adam; Yu, Wen Han; McKitrick, Tanya R.; Lauffenburger, Douglas; Cummings, Richard D.; Mayanja-Kizza, Harriet; et al. (Nature Medicine, 2019)
Exposure to Mycobacterium tuberculosis (Mtb) results in heterogeneous clinical outcomes including primary progressive tuberculosis and latent Mtb infection (LTBI). Mtb infection is identified using the tuberculin skin test and interferon-γ (IFN-γ) release assay IGRA, and a positive result may prompt chemoprophylaxis to prevent progression to tuberculosis. In the present study, we report on a cohort of Ugandan individuals who were household contacts of patients with TB. These individuals were highly exposed to Mtb but tested negative disease by IFN-γ release assay and tuberculin skin test, 'resisting' development of classic LTBI. We show that 'resisters' possess IgM, class-switched IgG antibody responses and non-IFN-γ T cell responses to the Mtb-specific proteins ESAT6 and CFP10, immunologic evidence of exposure to Mtb. Compared to subjects with classic LTBI, 'resisters' display enhanced antibody avidity and distinct Mtb-specific IgG Fc profiles. These data reveal a distinctive adaptive immune profile among Mtb-exposed subjects, supporting an expanded definition of the host response to Mtb exposure, with implications for public health and the design of clinical trials.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Female; Interferon-gamma; Biomarkers; CD4-Positive T-Lymphocytes; Adult; Latent Tuberculosis; Male; Young Adult; Child; Tuberculin Test; Cohort Studies; Interferon-gamma Release Tests; Uganda

IFN-γ-independent immune markers of Mycobacterium tuberculosis exposure - Lu, Lenette L.; Smith, Malisa T.; Yu, Krystle K. Q.; Luedemann, Corinne; Suscovich, Todd J.; Grace, Patricia S.; Cain, Adam; Yu, Wen Han; McKitrick, Tanya R.; Lauffenburger, Douglas; Cummings, Richard D.; Mayanja-Kizza, Harriet; et al. (Nature Medicine, 2019)
Exposure to Mycobacterium tuberculosis (Mtb) results in heterogeneous clinical outcomes including primary progressive tuberculosis and latent Mtb infection (LTBI). Mtb infection is identified using the tuberculin skin test and interferon-γ (IFN-γ) release assay IGRA, and a positive result may prompt chemoprophylaxis to prevent progression to tuberculosis. In the present study, we report on a cohort of Ugandan individuals who were household contacts of patients with TB. These individuals were highly exposed to Mtb but tested negative disease by IFN-γ release assay and tuberculin skin test, 'resisting' development of classic LTBI. We show that 'resisters' possess IgM, class-switched IgG antibody responses and non-IFN-γ T cell responses to the Mtb-specific proteins ESAT6 and CFP10, immunologic evidence of exposure to Mtb. Compared to subjects with classic LTBI, 'resisters' display enhanced antibody avidity and distinct Mtb-specific IgG Fc profiles. These data reveal a distinctive adaptive immune profile among Mtb-exposed subjects, supporting an expanded definition of the host response to Mtb exposure, with implications for public health and the design of clinical trials.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Female; Interferon-gamma; Biomarkers; CD4-Positive T-Lymphocytes; Adult; Latent Tuberculosis; Male; Young Adult; Child; Tuberculin Test; Cohort Studies; Interferon-gamma Release Tests; Uganda

Beyond binding: antibody effector functions in infectious diseases - Lu, Lenette L.; Suscovich, Todd J.; Fortune, Sarah M.; Alter, Galit (Nature Reviews. Immunology, 2018)
Antibodies play an essential role in host defence against pathogens by recognizing microorganisms or infected cells. Although preventing pathogen entry is one potential mechanism of protection, antibodies can control and eradicate infections through a variety of other mechanisms. In addition to binding and directly neutralizing pathogens, antibodies drive the clearance of bacteria, viruses, fungi and parasites via their interaction with the innate and adaptive immune systems, leveraging a remarkable diversity of antimicrobial processes locked within our immune system. Specifically, antibodies collaboratively form immune complexes that drive sequestration and uptake of pathogens, clear toxins, eliminate infected cells, increase antigen presentation and regulate inflammation. The diverse effector functions that are deployed by antibodies are dynamically regulated via differential modification of the antibody constant domain, which provides specific instructions to the immune system. Here, we review mechanisms by which antibody effector functions contribute to the balance between microbial clearance and pathology and discuss tractable lessons that may guide rational vaccine and therapeutic design to target gaps in our infectious disease armamentarium.
Keywords: Humans; Antibodies; Adaptive Immunity; Immunity, Innate; Antigen Presentation; Inflammation; Antigen-Antibody Complex; Bacterial Toxins; Immunoglobulin Constant Regions; Infections

Functions of Antibodies - Forthal, Donald N. (Microbiology Spectrum, 2014)
Antibodies can impact pathogens in the presence or in the absence of effector cells or effector molecules such as complement, and experiments can often sort out with precision the mechanisms by which an antibody inhibits a pathogen in vitro. In addition, in vivo models, particularly those engineered to knock in or knock out effector cells or effector molecules, are excellent tools for understanding antibody functions. However, it is highly likely that multiple antibody functions occur simultaneously or sequentially in the presence of an infecting organism in vivo. The most critical incentive for measuring antibody functions is to provide a basis for vaccine development and for the development of therapeutic antibodies. In this respect, some functions, such as virus neutralization, serve to inhibit the acquisition of a pathogen or limit its pathogenesis. However, antibodies can also enhance replication or contribute to pathogenesis. This review emphasizes those antibody functions that are potentially beneficial to the host. In addition, this review will focus on the effects of antibodies on organisms themselves, rather than on the toxins the organisms may produce.
Keywords: Humans; Animals; Antibodies; Communicable Diseases; Vaccines

Structural and immunological principles leading to chemically synthesized, multiantigenic, multistage, minimal subunit-based vaccine development - Patarroyo, Manuel Elkin; Bermúdez, Adriana; Patarroyo, Manuel Alfonso (Chemical Reviews, 2011)
Keywords: Humans; Models, Molecular; Immunization; Vaccines; Vaccines, Subunit

Immune protection-inducing protein structures (IMPIPS) against malaria: the weapons needed for beating Odysseus - Patarroyo, Manuel E.; Patarroyo, Manuel A.; Pabón, Laura; Curtidor, Hernando; Poloche, Luis A. (Vaccine, 2015)
The review covers the functional and structural approach followed by our group for more than 34 years in the search for a methodology that allows the rational design of chemically synthesised vaccines. An analogy between Odysseus, the cunning hero of the epic poem Odyssey by Homer, and the elusive Plasmodium parasite has been made, to review our research group's main considerations when developing a rational methodology for designing second generation, modified peptide-based, minimal subunit, multi-antigen, multi-stage, chemically synthesised vaccines against Plasmodium falciparum malaria.
Keywords: Amino Acid Sequence; Humans; Peptides; Vaccines, Synthetic; Protein Conformation; Synthetic peptides; Malaria Vaccines; Malaria, Falciparum; Plasmodium falciparum; Protozoan Proteins; IMPIPS; Life Cycle Stages; Malaria vaccine; Modified peptides

Association of Human Antibodies to Arabinomannan With Enhanced Mycobacterial Opsonophagocytosis and Intracellular Growth Reduction - Chen, Tingting; Blanc, Caroline; Eder, Anke Z.; Prados-Rosales, Rafael; Souza, Ana Camila Oliveira; Kim, Ryung S.; Glatman-Freedman, Aharona; Joe, Maju; Bai, Yu; Lowary, Todd L.; Tanner, Rachel; Brennan, Michael J.; et al. (The Journal of Infectious Diseases, 2016)
BACKGROUND: The relevance of antibodies (Abs) in the defense against Mycobacterium tuberculosis infection remains uncertain. We investigated the role of Abs to the mycobacterial capsular polysaccharide arabinomannan (AM) and its oligosaccharide (OS) fragments in humans. METHODS: Sera obtained from 29 healthy adults before and after primary or secondary bacillus Calmette-Guerin (BCG) vaccination were assessed for Ab responses to AM via enzyme-linked immunosorbent assays, and to AM OS epitopes via novel glycan microarrays. Effects of prevaccination and postvaccination sera on BCG phagocytosis and intracellular survival were assessed in human macrophages. RESULTS: Immunoglobulin G (IgG) responses to AM increased significantly 4-8 weeks after vaccination (P < .01), and sera were able to opsonize BCG and M. tuberculosis grown in both the absence and the presence of detergent. Phagocytosis and intracellular growth inhibition were significantly enhanced when BCG was opsonized with postvaccination sera (P < .01), and these enhancements correlated significantly with IgG titers to AM (P < .05), particularly with reactivity to 3 AM OS epitopes (P < .05). Furthermore, increased phagolysosomal fusion was observed with postvaccination sera. CONCLUSIONS: Our results provide further evidence for a role of Ab-mediated immunity to tuberculosis and suggest that IgG to AM, especially to some of its OS epitopes, could contribute to the defense against mycobacterial infection in humans.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Protein Binding; Immunoglobulin G; tuberculosis; BCG Vaccine; Adult; Microbial Viability; Phagocytosis; Enzyme-Linked Immunosorbent Assay; antibody-mediated immunity; bacterial capsule; human antibodies; immune response; immunoglobulin; Mannans; Microarray Analysis; Mycobacterium bovis BCG; oligosaccharide; Opsonin Proteins; polysaccharide

Targeting the bacteria-host interface: strategies in anti-adhesion therapy - Krachler, Anne Marie; Orth, Kim (Virulence, 2013)
Bacterial infections are a major cause of morbidity and mortality worldwide and are increasingly problematic to treat due to the rise in antibiotic-resistant strains. It becomes more and more challenging to develop new antimicrobials that are able to withstand the ever-increasing repertoire of bacterial resistance mechanisms. This necessitates the development of alternative approaches to prevent and treat bacterial infections. One of the first steps during bacterial infection is adhesion of the pathogen to host cells. A pathogen's ability to colonize and invade host tissues strictly depends on this process. Thus, interference with adhesion (anti-adhesion therapy) is an efficient way to prevent or treat bacterial infections. As a basis to present different strategies to interfere with pathogen adhesion, this review briefly introduces general concepts of bacterial attachment to host cells. We further discuss advantages and disadvantages of anti-adhesion treatments and issues that are in need of improvement so as to make anti-adhesion compounds a more broadly applicable alternative to conventional antimicrobials.
Keywords: Humans; Host-Pathogen Interactions; Bacterial Adhesion; Anti-Bacterial Agents; Bacterial Vaccines; Bacteria; anti-adhesion treatment; anti-adhesive; antimicrobial therapy; bacterial adhesion; host–pathogen interactions

"The Impact of Mycobacterium tuberculosis Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" - Meeting report - Boggiano, Cesar; Eichelberg, Katrin; Ramachandra, Lakshmi; Shea, Jaqueline; Ramakrishnan, Lalita; Behar, Samuel; Ernst, Joel D.; Porcelli, Steven A.; Maeurer, Markus; Kornfeld, Hardy (Vaccine, 2017)
Tuberculosis (TB) is the major cause of death from infectious diseases around the world, particularly in HIV infected individuals. TB vaccine design and development have been focused on improving Bacille Calmette-Guérin (BCG) and evaluating recombinant and viral vector expressed Mycobacterium tuberculosis (Mtb) proteins, for boosting BCG-primed immunity, but these approaches have not yet yielded significant improvements over the modest effects of BCG in protecting against infection or disease. On March 7-8, 2016, the National Institute of Allergy and Infectious Diseases (NIAID) convened a workshop on "The Impact of Mtb Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" with the goal of defining immune mechanisms that could be targeted through novel research approaches, to inform vaccine design and immune therapeutic interventions for prevention of TB. The workshop addressed early infection events, the impact of Mtb evolution on the development and maintenance of an adaptive immune response, and the factors that influence protection against and progression to active disease. Scientific gaps and areas of study to revitalize and accelerate TB vaccine design were discussed and prioritized. These included a comprehensive evaluation of innate and Mtb-specific adaptive immune responses in the lung at different stages of disease; determining the role of B cells and antibodies (Abs) during Mtb infection; development of better assays to measure Mtb burden following exposure, infection, during latency and after treatment, and approaches to improving current animal models to study Mtb immunogenicity, TB disease and transmission.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; Vaccine; Immune evasion; Immune Evasion; Drug Discovery

Human isotype-dependent inhibitory antibody responses against Mycobacterium tuberculosis - Zimmermann, Natalie; Thormann, Verena; Hu, Bo; Köhler, Anne-Britta; Imai-Matsushima, Aki; Locht, Camille; Arnett, Eusondia; Schlesinger, Larry S.; Zoller, Thomas; Schürmann, Mariana; Kaufmann, Stefan He; Wardemann, Hedda (EMBO molecular medicine, 2016)
Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B-cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB-exposed healthcare workers. The data suggest that the acute plasmablast response to MTB originates from reactivated memory B cells and indicates a mucosal origin. Through functional analyses, we identified MTB inhibitory antibodies against mycobacterial antigens including virulence factors that play important roles in host cell infection. The inhibitory activity of anti-MTB antibodies was directly linked to their isotype. Monoclonal as well as purified serum IgA antibodies showed MTB blocking activity independently of Fc alpha receptor expression, whereas IgG antibodies promoted the host cell infection. Together, the data provide molecular insights into the human antibody response to MTB and may thereby facilitate the design of protective vaccination strategies.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; antibodies; Antibodies, Monoclonal; Antibody Formation; B cells; B-Lymphocytes; Immunoglobulin Isotypes; infection; isotype

Human isotype-dependent inhibitory antibody responses against Mycobacterium tuberculosis - Zimmermann, Natalie; Thormann, Verena; Hu, Bo; Köhler, Anne-Britta; Imai-Matsushima, Aki; Locht, Camille; Arnett, Eusondia; Schlesinger, Larry S.; Zoller, Thomas; Schürmann, Mariana; Kaufmann, Stefan He; Wardemann, Hedda (EMBO molecular medicine, 2016)
Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B-cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB-exposed healthcare workers. The data suggest that the acute plasmablast response to MTB originates from reactivated memory B cells and indicates a mucosal origin. Through functional analyses, we identified MTB inhibitory antibodies against mycobacterial antigens including virulence factors that play important roles in host cell infection. The inhibitory activity of anti-MTB antibodies was directly linked to their isotype. Monoclonal as well as purified serum IgA antibodies showed MTB blocking activity independently of Fc alpha receptor expression, whereas IgG antibodies promoted the host cell infection. Together, the data provide molecular insights into the human antibody response to MTB and may thereby facilitate the design of protective vaccination strategies.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; antibodies; Antibodies, Monoclonal; Antibody Formation; B cells; B-Lymphocytes; Immunoglobulin Isotypes; infection; isotype

Mycobacterium tuberculosis promotes apoptosis in human neutrophils by activating caspase-3 and altering expression of Bax/Bcl-xL via an oxygen-dependent pathway - Perskvist, Nasrin; Long, Min; Stendahl, Olle; Zheng, Limin (Journal of Immunology (Baltimore, Md.: 1950), 2002)
In addition to direct bactericidal activities, such as phagocytosis and generation of reactive oxygen species (ROS), neutrophils can regulate the inflammatory response by undergoing apoptosis. We found that infection of human neutrophils with Mycobacterium tuberculosis (Mtb) induced rapid cell death displaying the characteristic features of apoptosis such as morphologic changes, phosphatidylserine exposure, and DNA fragmentation. Both a virulent (H37Rv) and an attenuated (H37Ra) strain of Mtb were equally effective in inducing apoptosis. Pretreatment of neutrophils with antioxidants or an inhibitor of NADPH oxidase markedly blocked Mtb-induced apoptosis but did not affect spontaneous apoptosis. Activation of caspase-3 was evident in neutrophils undergoing spontaneous apoptosis, but it was markedly augmented and accelerated during Mtb-induced apoptosis. The Mtb-induced apoptosis was associated with a speedy and transient increase in expression of Bax protein, a proapoptotic member of the Bcl-2 family, and a more prominent reduction in expression of the antiapoptotic protein Bcl-x(L). Pretreatment with an inhibitor of NADPH oxidase distinctly suppressed the Mtb-stimulated activation of caspase-3 and alteration of Bax/Bcl-x(L) expression in neutrophils. These results indicate that infection with Mtb causes ROS-dependent alteration of Bax/Bcl-x(L) expression and activation of caspase-3, and thereby induces apoptosis in human neutrophils. Moreover, we found that phagocytosis of Mtb-induced apoptotic neutrophils markedly increased the production of proinflammatory cytokine TNF-alpha by human macrophages. Therefore, the ROS-dependent apoptosis in Mtb-stimulated neutrophils may represent an important host defense mechanism aimed at selective removal of infected cells at the inflamed site, which in turn aids the functional activities of local macrophages.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Cells, Cultured; Neutrophils; Virulence; Vaccines, Attenuated; Macrophage Activation; Phagocytosis; Apoptosis; Reactive Oxygen Species; Tumor Necrosis Factor-alpha; Proto-Oncogene Proteins c-bcl-2; Down-Regulation; Enzyme Inhibitors; bcl-2-Associated X Protein; bcl-X Protein; Caspase 3; Caspases; Enzyme Activation; Onium Compounds; Oxygen; Proto-Oncogene Proteins

Measuring Cell Death by Propidium Iodide Uptake and Flow Cytometry - Crowley, Lisa C.; Scott, Adrian P.; Marfell, Brooke J.; Boughaba, Jeanne A.; Chojnowski, Grace; Waterhouse, Nigel J. (Cold Spring Harbor Protocols, 2016)
Propidium iodide (PI) is a small fluorescent molecule that binds to DNA but cannot passively traverse into cells that possess an intact plasma membrane. PI uptake versus exclusion can be used to discriminate dead cells, in which plasma membranes become permeable regardless of the mechanism of death, from live cells with intact membranes. PI is excited by wavelengths between 400 and 600 nm and emits light between 600 and 700 nm, and is therefore compatible with lasers and photodetectors commonly available in flow cytometers. This protocol for PI staining can be used to quantitate cell death in most modern research facilities and universities.
Keywords: Humans; Animals; Flow Cytometry; Fluorescent Dyes; Cell Death; Intercalating Agents; Propidium; Staining and Labeling

How Neutrophil Extracellular Traps Become Visible - de Buhr, Nicole; von Köckritz-Blickwede, Maren (Journal of Immunology Research, 2016)
Neutrophil extracellular traps (NETs) have been identified as a fundamental innate immune defense mechanism against different pathogens. NETs are characterized as released nuclear DNA associated with histones and granule proteins, which form an extracellular web-like structure that is able to entrap and occasionally kill certain microbes. Furthermore, NETs have been shown to contribute to several noninfectious disease conditions when released by activated neutrophils during inflammation. The identification of NETs has mainly been succeeded by various microscopy techniques, for example, immunofluorescence microscopy, transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Since the last years the development and improvement of new immunofluorescence-based techniques enabled optimized visualization and quantification of NETs. On the one hand in vitro live-cell imaging led to profound new ideas about the mechanisms involved in the formation and functionality of NETs. On the other hand different intravital, in vivo, and in situ microscopy techniques led to deeper insights into the role of NET formation during health and disease. This paper presents an overview of the main used microscopy techniques to visualize NETs and describes their advantages as well as disadvantages.
Keywords: Humans; Microscopy; Neutrophil Activation; DNA; Extracellular Traps; Histones; Microscopy, Electron; Microscopy, Fluorescence

Role of neutrophils in tuberculosis: A bird's eye view - Hilda, J. Nancy; Das, Sulochana; Tripathy, Srikanth P.; Hanna, Luke Elizabeth (Innate Immunity, 2020)
Neutrophils are innate immune cells implicated in the process of killing Mycobacterium tuberculosis early during infection. Once the mycobacteria enter the human system, neutrophils sense and engulf them. By secreting bactericidal enzymes and α-defensins like human neutrophil peptides loaded in their granule armory, neutrophils kill the pathogen. Peripheral blood neutrophils secrete a wide range of cytokines like IL-8, IL-1-β and IFN-γ in response to mycobacterial infection. Thus they signal and activate distant immune cells thereby informing them of prevailing infection. The activated monocytes, dendritic cells and T cells further continue the immune response. As a final call, neutrophils release neutrophil extracellular traps in circulation which can trap mycobacteria in patients with active pulmonary tuberculosis. Extensive neutrophilic response is associated with inflammation, pulmonary destruction, and pathology. For example, inappropriate phagocytosis of mycobacteria-infected neutrophils can damage host cells due to necrosis of neutrophils, leading to chronic inflammation and tissue damage. This dual nature of neutrophils makes them double-edged swords during tuberculosis, and hence data available on neutrophil functions against mycobacterium are controversial and non-uniform. This article reviews the role of neutrophils in tuberculosis infection and highlights research gaps that need to be addressed. We focus on our understanding of new research ideologies targeting neutrophils (a) in the early stages of infection for boosting specific immune functions or (b) in the later stages of infection to prevent inflammatory conditions mediated by activated neutrophils. This would plausibly lead to the development of better tuberculosis vaccines and therapeutics in the future.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; tuberculosis; Neutrophils; Cytokines; Immunity, Innate; Phagocytosis; Apoptosis; Neutrophil Activation; macrophages; apoptosis; immune response; Extracellular Traps; alpha-Defensins; phagocytosis

M. tuberculosis-Induced Necrosis of Infected Neutrophils Promotes Bacterial Growth Following Phagocytosis by Macrophages - Dallenga, Tobias; Repnik, Urska; Corleis, Björn; Eich, Jacqueline; Reimer, Rudolph; Griffiths, Gareth W.; Schaible, Ulrich E. (Cell Host & Microbe, 2017)
Neutrophils represent the main infected cell population in the lungs of active tuberculosis patients. Efficient removal of infected and dying neutrophils is required to protect the surrounding tissue from bioactive neutrophil molecules and subsequent pathological sequelae. While the removal of apoptotic M. tuberculosis (Mtb)-infected cells, or efferocytosis, is considered beneficial for host defense, little is known about Mtb-infected necrotic neutrophils. We found that Mtb induces necrosis of human neutrophils in an ESX-1-dependent manner, and neutrophil-produced reactive oxygen species (ROS) drive this necrosis. Neutrophil necrosis was required for Mtb growth after uptake of infected neutrophils by human macrophages. Pharmacological inhibition of ROS production could prevent necrosis and restore the capability of macrophages to control Mtb growth, thereby identifying a potential host-directed therapy target. Taken together, necrosis represents the starting point for a vicious cycle including the uptake of infected necrotic cells by other phagocytes, Mtb growth therein, and sustained infection.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Macrophages; tuberculosis; Necrosis; Neutrophils; Coculture Techniques; Adult; Middle Aged; Adolescent; Aged; Phagocytosis; Apoptosis; host-directed therapy; neutrophils; Reactive Oxygen Species; necrosis; macrophages; cell death; efferocytosis; ESAT-6; Primary Cell Culture; respiratory burst; Single-Cell Analysis

Macrophages acquire neutrophil granules for antimicrobial activity against intracellular pathogens - Tan, Belinda H.; Meinken, Christoph; Bastian, Max; Bruns, Heiko; Legaspi, Annaliza; Ochoa, Maria Teresa; Krutzik, Stephan R.; Bloom, Barry R.; Ganz, Tomas; Modlin, Robert L.; Stenger, Steffen (Journal of Immunology (Baltimore, Md.: 1950), 2006)
A key target of many intracellular pathogens is the macrophage. Although macrophages can generate antimicrobial activity, neutrophils have been shown to have a key role in host defense, presumably by their preformed granules containing antimicrobial agents. Yet the mechanism by which neutrophils can mediate antimicrobial activity against intracellular pathogens such as Mycobacterium tuberculosis has been a long-standing enigma. We demonstrate that apoptotic neutrophils and purified granules inhibit the growth of extracellular mycobacteria. Phagocytosis of apoptotic neutrophils by macrophages results in decreased viability of intracellular M. tuberculosis. Concomitant with uptake of apoptotic neutrophils, granule contents traffic to early endosomes, and colocalize with mycobacteria. Uptake of purified granules alone decreased growth of intracellular mycobacteria. Therefore, the transfer of antimicrobial peptides from neutrophils to macrophages provides a cooperative defense strategy between innate immune cells against intracellular pathogens and may complement other pathways that involve delivery of antimicrobial peptides to macrophages.
Keywords: Humans; Mycobacterium tuberculosis; Neutrophils; Biomarkers; Phagocytosis; Phagosomes; Apoptosis; Endosomes; Cytoplasmic Granules; Macrophages, Alveolar; alpha-Defensins; Blood Bactericidal Activity; Extracellular Space; Growth Inhibitors; Intracellular Fluid

Efferocytosis of Apoptotic Neutrophils Enhances Control of Mycobacterium tuberculosis in HIV-Coinfected Macrophages in a Myeloperoxidase-Dependent Manner - Andersson, Anna-Maria; Larsson, Marie; Stendahl, Olle; Blomgran, Robert (Journal of Innate Immunity, 2020)
Tuberculosis remains a big threat, with 1.6 million deaths in 2017, including 0.3 million deaths among patients with HIV. The risk of developing active disease increases considerably during an HIV coinfection. Alveolar macrophages are the first immune cells to encounter the causative agent Mycobacterium tuberculosis, but during the granuloma formation other cells are recruited in order to combat the bacteria. Here, we have investigated the effect of efferocytosis of apoptotic neutrophils by M. tuberculosis and HIV-coinfected macrophages in a human in vitro system. We found that the apo-ptotic neutrophils enhanced the control of M. tuberculosis in single and HIV-coinfected macrophages, and that this was dependent on myeloperoxidase (MPO) and reactive oxygen species in an autophagy-independent manner. We show that MPO remains active in the apoptotic neutrophils and can be harnessed by infected macrophages. In addition, MPO inhibition removed the suppression in M. tuberculosis growth caused by the apoptotic neutrophils. Antimycobacterial components from apoptotic neutrophils could thus increase the microbicidal activity of macrophages during an M. tuberculosis/HIV coinfection. This cooperation between innate immune cells could thereby be a way to compensate for the impaired adaptive immunity against M. tuberculosis seen during a concurrent HIV infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Tuberculosis; Neutrophils; Apoptosis; Coinfection; HIV; HIV-1; Myeloperoxidase; Peroxidase; Reactive oxygen species

M. tuberculosis-Induced Necrosis of Infected Neutrophils Promotes Bacterial Growth Following Phagocytosis by Macrophages - Dallenga, Tobias; Repnik, Urska; Corleis, Björn; Eich, Jacqueline; Reimer, Rudolph; Griffiths, Gareth W.; Schaible, Ulrich E. (Cell Host & Microbe, 2017)
Neutrophils represent the main infected cell population in the lungs of active tuberculosis patients. Efficient removal of infected and dying neutrophils is required to protect the surrounding tissue from bioactive neutrophil molecules and subsequent pathological sequelae. While the removal of apoptotic M. tuberculosis (Mtb)-infected cells, or efferocytosis, is considered beneficial for host defense, little is known about Mtb-infected necrotic neutrophils. We found that Mtb induces necrosis of human neutrophils in an ESX-1-dependent manner, and neutrophil-produced reactive oxygen species (ROS) drive this necrosis. Neutrophil necrosis was required for Mtb growth after uptake of infected neutrophils by human macrophages. Pharmacological inhibition of ROS production could prevent necrosis and restore the capability of macrophages to control Mtb growth, thereby identifying a potential host-directed therapy target. Taken together, necrosis represents the starting point for a vicious cycle including the uptake of infected necrotic cells by other phagocytes, Mtb growth therein, and sustained infection.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Macrophages; tuberculosis; Necrosis; Neutrophils; Coculture Techniques; Adult; Middle Aged; Adolescent; Aged; Phagocytosis; Apoptosis; host-directed therapy; neutrophils; Reactive Oxygen Species; necrosis; macrophages; cell death; efferocytosis; ESAT-6; Primary Cell Culture; respiratory burst; Single-Cell Analysis

[Neutrophil extracellular traps (NET), consequence of a cellular suicide] - Yam-Puc, Juan Carlos; García-Marín, Liliana; Sánchez-Torres, Luvia Enid (Gaceta Medica De Mexico, 2012)
Recently it was discovered that neutrophils can generate extracellular fibers called NET (neutrophil extracellular traps), which are composed of a skeleton of DNA “decorated” with many cytoplasmic –including enzymes– and nuclear components.The NET are a physical barrier that prevent the spread of microorganisms and facilitate the cell death by promoting a high local concentration of antimicrobial molecules. On the other hand, the fibrous structure limits the damage to the tissue where they are generated by restricting the range of molecules that are released by the neutrophil. This paper describes this new form of cell death and the implications this may have on different diseases.
Keywords: Humans; Neutrophils; Autophagy

[Discovery of the neutrophil extracellular traps begins a new stage in the study of neutrophil morphogenesis and function] - Perova, M. D.; Shubich, M. G. (Morfologiia (Saint Petersburg, Russia), 2011)
The purpose of the present review was to analyze the accumulating evidence regarding recently discovered novel defense mechanism of neutrophils - capacity to form neutrophil extracellular traps (NETs). Contact with pathogenic microbes and/or exposure to proinflammatory cytokines trigger the respiratory burst in the neutrophils with a subsequent initiation of a cell death (NETosis) which differs from apoptosis and necrosis. NETs are formed by the fibrils of decondensed chromatin (DNA/ histones), released from the neutrophil, which is closely associated with the antimicrobial proteins of cytoplasmic granules. Due to its three-dimensional structure, NETs are capable of retaining the microorganisms (bacteria, fungi and protozoa), while high local concentration of the antimicrobial substances provides their killing. The review presents the evidence of a potential defensive role of NETs in infectious diseases, traumas and surgical operations, as well as during the early stage of a repair process. Considering the role played by neutrophils in the immune response orientation via pentraxin-3 (PTX3), including the switching to adaptive immunity, it is necessary to study the subsequent interaction of DNA/histone exrtacellular structures with the tissue microenvironment.
Keywords: Humans; Neutrophils; Immunity, Innate; Phagocytosis; Cell Death; Extracellular Space; Morphogenesis

Non-canonical PI3K-Cdc42-Pak-Mek-Erk Signaling Promotes Immune-Complex-Induced Apoptosis in Human Neutrophils - Chu, Julia Y.; Dransfield, Ian; Rossi, Adriano G.; Vermeren, Sonja (Cell Reports, 2016)
Neutrophils are peripheral blood leukocytes that represent the first line of immune cell defense against bacterial and fungal infections but are also crucial players in the generation of the inflammatory response. Many neutrophil cell surface receptors regulate important cellular processes via activation of agonist-activated PI3Ks. We show here that activation of human neutrophils with insoluble immune complexes drives a previously uncharacterized, PI3K-dependent, non-canonical, pro-apoptotic signaling pathway, FcγR-PI3Kβ/δ-Cdc42-Pak-Mek-Erk. This is a rare demonstration of Ras/Raf-independent activation of Erk and of PI3K-mediated activation of Cdc42. In addition, comparative analysis of immune-complex- and fMLF-induced signaling uncovers key differences in pathways used by human and murine neutrophils. The non-canonical pathway we identify in this study may be important for the resolution of inflammation in chronic inflammatory diseases that rely on immune-complex-driven neutrophil activation.
Keywords: Humans; Animals; Mice; Neutrophils; Receptors, IgG; Signal Transduction; Apoptosis; Antigen-Antibody Complex; Neutrophil Activation; Adaptor Proteins, Signal Transducing; Cytoskeletal Proteins; Elafin; Extracellular Signal-Regulated MAP Kinases; MAP Kinase Kinase Kinases; p21-Activated Kinases; rho GTP-Binding Proteins

IgG subclasses and allotypes: from structure to effector functions - Vidarsson, Gestur; Dekkers, Gillian; Rispens, Theo (Frontiers in Immunology, 2014)
Of the five immunoglobulin isotypes, immunoglobulin G (IgG) is most abundant in human serum. The four subclasses, IgG1, IgG2, IgG3, and IgG4, which are highly conserved, differ in their constant region, particularly in their hinges and upper CH2 domains. These regions are involved in binding to both IgG-Fc receptors (FcγR) and C1q. As a result, the different subclasses have different effector functions, both in terms of triggering FcγR-expressing cells, resulting in phagocytosis or antibody-dependent cell-mediated cytotoxicity, and activating complement. The Fc-regions also contain a binding epitope for the neonatal Fc receptor (FcRn), responsible for the extended half-life, placental transport, and bidirectional transport of IgG to mucosal surfaces. However, FcRn is also expressed in myeloid cells, where it participates in both phagocytosis and antigen presentation together with classical FcγR and complement. How these properties, IgG-polymorphisms and post-translational modification of the antibodies in the form of glycosylation, affect IgG-function will be the focus of the current review.
Keywords: Fc receptors; genetic; glycosylation; IgG; immunoglobulin G; neonatal Fc receptor; polymorphism

Type I and type II Fc receptors regulate innate and adaptive immunity - Pincetic, Andrew; Bournazos, Stylianos; DiLillo, David J.; Maamary, Jad; Wang, Taia T.; Dahan, Rony; Fiebiger, Benjamin-Maximillian; Ravetch, Jeffrey V. (Nature Immunology, 2014)
Antibodies produced in response to a foreign antigen are characterized by polyclonality, not only in the diverse epitopes to which their variable domains bind but also in the various effector molecules to which their constant regions (Fc domains) engage. Thus, the antibody's Fc domain mediates diverse effector activities by engaging two distinct classes of Fc receptors (type I and type II) on the basis of the two dominant conformational states that the Fc domain may adopt. These conformational states are regulated by the differences among antibody subclasses in their amino acid sequence and by the complex, biantennary Fc-associated N-linked glycan. Here we discuss the diverse downstream proinflammatory, anti-inflammatory and immunomodulatory consequences of the engagement of type I and type II Fc receptors in the context of infectious, autoimmune, and neoplastic disorders.
Keywords: Amino Acid Sequence; Humans; Antibodies; Immunoglobulin G; Protein Structure, Tertiary; Protein Conformation; Adaptive Immunity; Immunity, Innate; Glycosylation; Immunoglobulin Fc Fragments; Receptors, IgG; Antigen Presentation; Vaccination; Neoplasms; Autoimmune Diseases

Antibody Fc Glycosylation Discriminates Between Latent and Active Tuberculosis - Lu, Lenette L.; Das, Jishnu; Grace, Patricia S.; Fortune, Sarah M.; Restrepo, Blanca I.; Alter, Galit (The Journal of Infectious Diseases, 2020)
BACKGROUND: Mycobacterium tuberculosis remains a global health problem and clinical management is complicated by difficulty in discriminating between latent infection and active disease. While M. tuberculosis-reactive antibody levels are heterogeneous, studies suggest that levels of IgG glycosylation differ between disease states. Here we extend this observation across antibody domains and M. tuberculosis specificities to define changes with the greatest resolving power. METHODS: Capillary electrophoretic glycan analysis was performed on bulk non-antigen-specific IgG, bulk Fc domain, bulk Fab domain, and purified protein derivative (PPD)- and Ag85A-specific IgG from subjects with latent (n = 10) and active (n = 20) tuberculosis. PPD-specific isotype/subclass, PPD-specific antibody-dependent phagocytosis, cellular cytotoxicity, and natural killer cell activation were assessed. Discriminatory potentials of antibody features were evaluated individually and by multivariate analysis. RESULTS: Parallel profiling of whole, Fc, and Fab domain-specific IgG glycosylation pointed to enhanced differential glycosylation on the Fc domain. Differential glycosylation was observed across antigen-specific antibody populations. Multivariate modeling highlighted Fc domain glycan species as the top discriminatory features, with combined PPD IgG titers and Fc domain glycans providing the highest classification accuracy. CONCLUSIONS: Differential glycosylation occurs preferentially on the Fc domain, providing significant discriminatory power between different states of M. tuberculosis infection and disease.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Immunoglobulin G; Tuberculosis; tuberculosis; Female; antibodies; Adult; Glycosylation; Immunoglobulin Fc Fragments; Latent Tuberculosis; Male; Middle Aged; Polysaccharides; Adolescent; Aged; Tuberculin; Fc effector function; glycosylation; Acyltransferases; diagnostics; Electrophoresis, Capillary; Immunoglobulin Fab Fragments

Antibody Subclass and Glycosylation Shift Following Effective TB Treatment - Grace, Patricia S.; Dolatshahi, Sepideh; Lu, Lenette L.; Cain, Adam; Palmieri, Fabrizio; Petrone, Linda; Fortune, Sarah M.; Ottenhoff, Tom H. M.; Lauffenburger, Douglas A.; Goletti, Delia; Joosten, Simone A.; Alter, Galit (Frontiers in Immunology, 2021)
With an estimated 25% of the global population infected with Mycobacterium tuberculosis (Mtb), tuberculosis (TB) remains a leading cause of death by infectious diseases. Humoral immunity following TB treatment is largely uncharacterized, and antibody profiling could provide insights into disease resolution. Here we focused on the distinctive TB-specific serum antibody features in active TB disease (ATB) and compared them with latent TB infection (LTBI) or treated ATB (txATB). As expected, di-galactosylated glycan structures (lacking sialic acid) found on IgG-Fc differentiated LTBI from ATB, but also discriminated txATB from ATB. Moreover, TB-specific IgG4 emerged as a novel antibody feature that correlated with active disease, elevated in ATB, but significantly diminished after therapy. These findings highlight 2 novel TB-specific antibody changes that track with the resolution of TB and may provide key insights to guide TB therapy.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Antigens, Bacterial; Immunoglobulin G; Tuberculosis; tuberculosis; Antitubercular Agents; Neutrophils; Female; antibodies; Glycosylation; Immunoglobulin Fc Fragments; Latent Tuberculosis; Male; Polysaccharides; Phagocytosis; Fc-glycosylation; IgG4; Killer Cells, Natural; TB therapy

Incidencia de tuberculosis en pacientes que reciben fármacos anti-TNF( - Gruss, Ana; Contrera, Mariela; Piñeiro, Natalia; Perna, Abayubá; Gambogi, Rosana; Alemán, Alicia; Correa, Fernando; Albornoz, Henri; Gruss, Ana; Contrera, Mariela; Piñeiro, Natalia; Perna, Abayubá; et al. (Revista Médica del Uruguay, 2020)

IMPIPS: The Immune Protection-Inducing Protein Structure Concept in the Search for Steric-Electron and Topochemical Principles for Complete Fully-Protective Chemically Synthesised Vaccine Development - Patarroyo, Manuel Elkin; Bermúdez, Adriana; Alba, Martha Patricia; Vanegas, Magnolia; Moreno-Vranich, Armando; Poloche, Luis Antonio; Patarroyo, Manuel Alfonso (PLOS ONE, 2015)
Determining immune protection-inducing protein structures (IMPIPS) involves defining the stereo-electron and topochemical characteristics which are essential in MHC-p-TCR complex formation. Modified high activity binding peptides (mHABP) were thus synthesised to produce a large panel of IMPIPS measuring 26.5 ±3.5Å between the farthest atoms fitting into Pockets 1 to 9 of HLA-DRβ1* structures. They displayed a polyproline II-like (PPIIL) structure with their backbone O and N atoms orientated to establish H-bonds with specific residues from HLA-DRβ1*-peptide binding regions (PBR). Residues having specific charge and gauche+ orientation regarding p3χ1, p5χ2, and p7χ1 angles determined appropriate rotamer orientation for perfectly fitting into the TCR to induce an appropriate immune response. Immunological assays in Aotus monkeys involving IMPIPS mixtures led to promising results; taken together with the aforementioned physicochemical principles, non-interfering, long-lasting, protection-inducing, multi-epitope, multistage, minimal subunit-based chemically-synthesised peptides can be designed against diseases scourging humankind.
Keywords: Antibodies; Vaccines; Plasmodium; Antigens; Immune response; Monkeys; Parasitic diseases; Vaccine development

SignalP 4.0: discriminating signal peptides from transmembrane regions - Petersen, Thomas Nordahl; Brunak, Søren; von Heijne, Gunnar; Nielsen, Henrik (Nature Methods, 2011)
Keywords: Bioinformatics; Proteomic analysis

A self-consistent method for the analysis of protein secondary structure from circular dichroism - Sreerama, N.; Woody, R. W. (Analytical Biochemistry, 1993)
A self-consistent procedure for estimating the secondary structure content from circular dichroism spectra of proteins is presented. In this method the spectrum of the protein to be analyzed is included in the basis set and an initial guess is made for the unknown structure as a first approximation. The resulting matrix equation is solved using the singular value decomposition algorithm and the initial guess is replaced by the solution. The process is repeated until self-consistency is attained. The best features of the variable selection and the locally linearized methods are incorporated in this procedure. We have applied this method to examine the inconsistencies in the CD data, to compare the predictions with different ranges and resolutions of the CD data, and to compare different assignments of secondary structures from X-ray structure analyses in the context of secondary structure predictions. The results are compared using the root mean square differences and correlation coefficients. The results obtained are as good as or better than the previous analyses. For most of the proteins considered the self-consistent solutions obtained with different initial guesses were similar. We find the Kabsch and Sander protein crystal structure analysis to be most suitable for our prediction method.
Keywords: Circular Dichroism; Protein Structure, Secondary; X-Ray Diffraction; Proteins

7 - The Genetics of Disorders Affecting the Premature Newborn - Prosnitz, Aaron R.; Gruen, Jeffrey R.; Bhandari, Vineet (Emery and Rimoin's Principles and Practice of Medical Genetics and Genomics (Seventh Edition), 2022)
The pathogenesis of disorders that affect prematurely born infants is complex and likely involves multiple gene–environment interactions. The studies described in this chapter investigated variations in candidate genes in a wide distribution of sample sizes for the six most common disorders of preterm infants: respiratory distress syndrome, bronchopulmonary dysplasia, patent ductus arteriosus, intraventricular hemorrhage, retinopathy of prematurity, and necrotizing enterocolitis. These disorders account for most of the morbidity and mortality due to premature birth. Shared common factors for these disorders of prematurity include those involved in vasculogenesis, inflammation, infection, growth, and protection from reactive oxygen species. Not surprisingly, most of these six common disorders of prematurity have been studied with the same list of genes involved in vascular development, growth and inflammation: ACE, Factor V, Factor XIII, Prothrombin, VEGF, IGF-1R, IL-1β, IL-4Rα, IL-6, IL-10, TNF-α, TNF-β, TGF-β, and surfactant proteins A and B. These studies, while generally underpowered, suggest that variations in these genes contribute to their pathogenesis and suggest shared pathways.
Keywords: BPD; IVH; NEC; PDA; Preterm neonate; RDS; ROP

Cellular and Molecular Immunology - 10th Edition (2022)

Towards a systems understanding of MHC class I and MHC class II antigen presentation - Neefjes, Jacques; Jongsma, Marlieke L. M.; Paul, Petra; Bakke, Oddmund (Nature Reviews. Immunology, 2011)
The molecular details of antigen processing and presentation by MHC class I and class II molecules have been studied extensively for almost three decades. Although the basic principles of these processes were laid out approximately 10 years ago, the recent years have revealed many details and provided new insights into their control and specificity. MHC molecules use various biochemical reactions to achieve successful presentation of antigenic fragments to the immune system. Here we present a timely evaluation of the biology of antigen presentation and a survey of issues that are considered unresolved. The continuing flow of new details into our understanding of the biology of MHC class I and class II antigen presentation builds a system involving several cell biological processes, which is discussed in this Review.
Keywords: Humans; Peptide Fragments; Animals; Structure-Activity Relationship; Mice; Models, Immunological; Antigen Presentation; Dendritic Cells; Histocompatibility Antigens Class I; Histocompatibility Antigens Class II; RNA, Small Interfering; Biological Transport; Endoplasmic Reticulum; Genes, MHC Class I; Genes, MHC Class II; Multiprotein Complexes; Polymorphism, Genetic; Proteasome Endopeptidase Complex; Systems Theory

Initiation and regulation of T-cell responses in tuberculosis - Urdahl, K. B.; Shafiani, S.; Ernst, J. D. (Mucosal Immunology, 2011)
Tuberculosis (TB) poses a great challenge to immunologists, as it represents a chronic infection characterized by persistence of the pathogen despite development of antigen-specific immune responses. Among the characteristics of adaptive immune responses to Mycobacterium tuberculosis is a delay in the onset of detectable T-cell responses, in both humans and experimental animals. Recent studies have revealed mechanisms that contribute to this delay, including pathogen inhibition of apoptosis, delayed migration of dendritic cells from the lungs to the local lymph node, and influence of regulatory T cells. In addition, novel features of M. tuberculosis antigen-specific T-cell differentiation have been discovered, which reveal pathways that limit and promote immune control of infection. Taken together, these results highlight the need for additional basic research and provide optimism for the development of TB vaccines with greater efficacy.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Cell Differentiation; Tuberculosis, Pulmonary; Adaptive Immunity; T-Lymphocyte Subsets; Dendritic Cells; Immune Evasion; Apoptosis; T-Lymphocytes, Regulatory; Cell Movement

The role of B cells and humoral immunity in Mycobacterium tuberculosis infection - Kozakiewicz, Lee; Phuah, Jiayao; Flynn, Joanne; Chan, John (Advances in Experimental Medicine and Biology, 2013)
Tuberculosis (TB) remains a serious threat to public health, causing 2 million deaths annually world-wide. The control of TB has been hindered by the requirement of long duration of treatment involving multiple chemotherapeutic agents, the increased susceptibility to Mycobacterium tuberculosis infection in the HIV-infected population, and the development of multi-drug resistant and extensively resistant strains of tubercle bacilli. An efficacious and cost-efficient way to control TB is the development of effective anti-TB vaccines. This measure requires thorough understanding of the immune response to M. tuberculosis. While the role of cell-mediated immunity in the development of protective immune response to the tubercle bacillus has been well established, the role of B cells in this process is not clearly understood. Emerging evidence suggests that B cells and humoral immunity can modulate the immune response to various intracellular pathogens, including M. tuberculosis. These lymphocytes form conspicuous aggregates in the lungs of tuberculous humans, non-human primates, and mice, which display features of germinal center B cells. In murine TB, it has been shown that B cells can regulate the level of granulomatous reaction, cytokine production, and the T cell response. This chapter discusses the potential mechanisms by which specific functions of B cells and humoral immunity can shape the immune response to intracellular pathogens in general, and to M. tuberculosis in particular. Knowledge of the B cell-mediated immune response to M. tuberculosis may lead to the design of novel strategies, including the development of effective vaccines, to better control TB.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Macrophages; Tuberculosis; Mice; Primates; T-Lymphocyte Subsets; Models, Immunological; Immunity, Cellular; Latent Tuberculosis; Receptors, IgG; Lymphocyte Activation; Species Specificity; Germinal Center; Lymphocyte Cooperation; Antigen-Presenting Cells; B-Lymphocyte Subsets; Lymphokines; Tuberculoma

Evaluation of methods for the prediction of membrane spanning regions - Möller, S.; Croning, M. D.; Apweiler, R. (Bioinformatics (Oxford, England), 2001)
MOTIVATION: A variety of tools are available to predict the topology of transmembrane proteins. To date no independent evaluation of the performance of these tools has been published. A better understanding of the strengths and weaknesses of the different tools would guide both the biologist and the bioinformatician to make better predictions of membrane protein topology. RESULTS: Here we present an evaluation of the performance of the currently best known and most widely used methods for the prediction of transmembrane regions in proteins. Our results show that TMHMM is currently the best performing transmembrane prediction program.
Keywords: Membrane Proteins; Computational Biology; Models, Molecular; Protein Conformation; Software; Solubility; Databases as Topic; Protein Sorting Signals

Large-scale in vitro expansion of polyclonal human switched-memory B lymphocytes - PubMed (2022)

T cell anergy - Schwartz, Ronald H. (Annual Review of Immunology, 2003)
T cell anergy is a tolerance mechanism in which the lymphocyte is intrinsically functionally inactivated following an antigen encounter, but remains alive for an extended period of time in a hyporesponsive state. Models of T cell anergy affecting both CD4(+) and CD8(+) cells fall into two broad categories. One, clonal anergy, is principally a growth arrest state, whereas the other, adaptive tolerance or in vivo anergy, represents a more generalized inhibition of proliferation and effector functions. The former arises from incomplete T cell activation, is mostly observed in previously activated T cells, is maintained by a block in the Ras/MAP kinase pathway, can be reversed by IL-2 or anti-OX40 signaling, and usually does not result in the inhibition of effector functions. The latter is most often initiated in naïve T cells in vivo by stimulation in an environment deficient in costimulation or high in coinhibition. Adaptive tolerance can be induced in the thymus or in the periphery. The cells proliferate and differentiate to varying degrees and then downregulate both functions in the face of persistent antigen. The state involves an early block in tyrosine kinase activation, which predominantly inhibits calcium mobilization, and an independent mechanism that blocks signaling through the IL-2 receptor. Adaptive tolerance reverses in the absence of antigen. Aspects of both of the anergic states are found in regulatory T cells, possibly preventing them from dominating initial immune responses to foreign antigens and shutting down such responses prematurely.
Keywords: Humans; Animals; Mice; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Models, Immunological; T-Lymphocytes; Antigen Presentation; Adoptive Transfer; Antigens, CD; Abatacept; Adaptation, Physiological; Antigens, Differentiation; Clonal Anergy; CTLA-4 Antigen; Immunoconjugates; Intercellular Adhesion Molecule-1

T cell anergy, exhaustion, senescence, and stemness in the tumor microenvironment - Crespo, Joel; Sun, Haoyu; Welling, Theodore H.; Tian, Zhigang; Zou, Weiping (Current Opinion in Immunology, 2013)
Human tumors progress despite the presence of tumor associated antigen (TAA)-specific T cells. Many different molecular and cellular mechanisms contribute to the failure of T cells to eradicate the tumor. These include immune suppressive networks that impair ongoing T cell function and enable tumor escape. Recent studies have started to reveal the nature of effector T cells in the tumor microenvironment. In this article we discuss T cell anergy, exhaustion, senescence, and stemness, and review the phenotype of dysfunctional T cell subsets and the underlying molecular mechanisms in the tumor microenvironments. We suggest that targeting T cell dysfunctional mechanisms and introducing/promoting T cell stemness are important approaches to treat patients with cancer.
Keywords: Humans; Animals; T-Lymphocytes; Neoplasms; Cellular Senescence; Clonal Anergy; Stem Cells; Tumor Microenvironment

Rethinking peripheral T cell tolerance: checkpoints across a T cell's journey - ElTanbouly, Mohamed A.; Noelle, Randolph J. (Nature Reviews. Immunology, 2021)
Following their exit from the thymus, T cells are endowed with potent effector functions but must spare host tissue from harm. The fate of these cells is dictated by a series of checkpoints that regulate the quality and magnitude of T cell-mediated immunity, known as tolerance checkpoints. In this Perspective, we discuss the mediators and networks that control the six main peripheral tolerance checkpoints throughout the life of a T cell: quiescence, ignorance, anergy, exhaustion, senescence and death. At the naive T cell stage, two intrinsic checkpoints that actively maintain tolerance are quiescence and ignorance. In the presence of co-stimulation-deficient T cell activation, anergy is a dominant hallmark that mandates T cell unresponsiveness. When T cells are successfully stimulated and reach the effector stage, exhaustion and senescence can limit excessive inflammation and prevent immunopathology. At every stage of the T cell's journey, cell death exists as a checkpoint to limit clonal expansion and to terminate unrestrained responses. Here, we compare and contrast the T cell tolerance checkpoints and discuss their specific roles, with the aim of providing an integrated view of T cell peripheral tolerance and fate regulation.
Keywords: Humans; T-Lymphocytes; Immunologic Memory; Apoptosis; Cellular Senescence; Cell Death; Clonal Anergy; Peripheral Tolerance

Crystal structure of a superantigen bound to MHC class II displays zinc and peptide dependence - Petersson, K.; Håkansson, M.; Nilsson, H.; Forsberg, G.; Svensson, L. A.; Liljas, A.; Walse, B. (The EMBO journal, 2001)
The three-dimensional structure of a bacterial superantigen, Staphylococcus aureus enterotoxin H (SEH), bound to human major histocompatibility complex (MHC) class II (HLA-DR1) has been determined by X-ray crystallography to 2.6 A resolution (1HXY). The superantigen binds on top of HLA-DR1 in a completely different way from earlier co-crystallized superantigens from S.aureus. SEH interacts with high affinity through a zinc ion with the beta1 chain of HLA-DR1 and also with the peptide presented by HLA-DR1. The structure suggests that all superantigens interacting with MHC class II in a zinc-dependent manner present the superantigen in a common way. This suggests a new model for ternary complex formation with the T-cell receptor (TCR), in which a contact between the TCR and the MHC class II is unlikely.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Protein Structure, Secondary; Models, Molecular; Protein Structure, Tertiary; Protein Conformation; Recombinant Proteins; Crystallography, X-Ray; HLA-DR1 Antigen; Sequence Alignment; Sequence Homology, Amino Acid; Cloning, Molecular; Enterotoxins; Staphylococcus aureus; Superantigens; Zinc; Zinc Fingers

Inflammatory Cytokines in Cancer: Comprehensive Understanding and Clinical Progress in Gene Therapy - Lan, Tianxia; Chen, Li; Wei, Xiawei (Cells, 2021)
The relationship between chronic inflammation and neoplastic diseases is not fully understood. The inflammatory microenvironment of a tumor is an intricate network that consists of numerous types of cells, cytokines, enzymes and signaling pathways. Recent evidence shows that the crucial components of cancer-related inflammation are involved in a coordinated system to influence the development of cancer, which may shed light on the development of potential anticancer therapies. Since the last century, considerable effort has been devoted to developing gene therapies for life-threatening diseases. When it comes to modulating the inflammatory microenvironment for cancer therapy, inflammatory cytokines are the most efficient targets. In this manuscript, we provide a comprehensive review of the relationship between inflammation and cancer development, especially focusing on inflammatory cytokines. We also summarize the clinical trials for gene therapy targeting inflammatory cytokines for cancer treatment. Future perspectives concerned with new gene-editing technology and novel gene delivery systems are finally provided.

Role of Cardiac Macrophages on Cardiac Inflammation, Fibrosis and Tissue Repair - Lafuse, William P.; Wozniak, Daniel J.; Rajaram, Murugesan V. S. (Cells, 2020)
The immune system plays a pivotal role in the initiation, development and resolution of inflammation following insult or damage to organs. The heart is a vital organ which supplies nutrients and oxygen to all parts of the body. Heart failure (HF) has been conventionally described as a disease associated with cardiac tissue damage caused by systemic inflammation, arrhythmia and conduction defects. Cardiac inflammation and subsequent tissue damage is orchestrated by the infiltration and activation of various immune cells including neutrophils, monocytes, macrophages, eosinophils, mast cells, natural killer cells, and T and B cells into the myocardium. After tissue injury, monocytes and tissue-resident macrophages undergo marked phenotypic and functional changes, and function as key regulators of tissue repair, regeneration and fibrosis. Disturbance in resident macrophage functions such as uncontrolled production of inflammatory cytokines, growth factors and inefficient generation of an anti-inflammatory response or unsuccessful communication between macrophages and epithelial and endothelial cells and fibroblasts can lead to aberrant repair, persistent injury, and HF. Therefore, in this review, we discuss the role of cardiac macrophages on cardiac inflammation, tissue repair, regeneration and fibrosis.
Keywords: Humans; Animals; Macrophages; Cytokines; Inflammation; Arrhythmias, Cardiac; cardiac inflammation; cardiac macrophages; Diabetic Cardiomyopathies; fibrosis; Fibrosis; Heart; Heart Injuries; Homeostasis; Hypertension; Intercellular Signaling Peptides and Proteins; Mitochondria; Myocardium; Regeneration; tissue repair

Wound repair and regeneration - Reinke, J. M.; Sorg, H. (European Surgical Research. Europaische Chirurgische Forschung. Recherches Chirurgicales Europeennes, 2012)
The skin is the biggest organ of the human being and has many functions. Therefore, the healing of a skin wound displays an extraordinary mechanism of cascading cellular functions which is unique in nature. As healing and regeneration processes take place in all parts of the human body, this review focuses on the healing processes of the skin and highlights the classical wound healing phases. While regeneration describes the specific substitution of the tissue, i.e. the superficial epidermis, mucosa or fetal skin, skin repair displays an unspecific form of healing in which the wound heals by fibrosis and scar formation. The first stage of acute wound healing is dedicated to hemostasis and the formation of a provisional wound matrix, which occurs immediately after injury and is completed after some hours. Furthermore, this phase initiates the inflammatory process. The inflammatory phase of the wound healing cascade gets activated during the coagulation phase and can roughly be divided into an early phase with neutrophil recruitment and a late phase with the appearance and transformation of monocytes. In the phase of proliferation the main focus of the healing process lies in the recovering of the wound surface, the formation of granulation tissue and the restoration of the vascular network. Therefore, next to the immigration of local fibroblasts along the fibrin network and the beginning of reepithelialization from the wound edges, neovascularization and angiogenesis get activated by capillary sprouting. The formation of granulation tissue stops through apoptosis of the cells, characterizing a mature wound as avascular as well as acellular. During the maturation of the wound the components of the extracellular matrix undergo certain changes. The physiological endpoint of mammalian wound repair displays the formation of a scar, which is directly linked to the extent of the inflammatory process throughout wound healing.
Keywords: Humans; Inflammation; Regeneration; Blood Coagulation; Cell Proliferation; Cicatrix; Hemostasis; Neovascularization, Physiologic; Skin; Wound Healing

TNF-α Coordinates Hematopoietic Stem Cell Survival and Myeloid Regeneration - Yamashita, Masayuki; Passegué, Emmanuelle (Cell Stem Cell, 2019)
Inflammation coordinates tissue regeneration via damaged cell removal and stem cell activation. Hematopoietic stem cells (HSCs) survive inflammatory stress that kills other blood cells, but the mechanisms underlying this effect remain poorly understood. Here, we find that tumor necrosis factor α (TNF-α) acts differently on HSCs and progenitors, thus facilitating hematopoietic clearance and promoting regeneration. We show that while inducing myeloid progenitor apoptosis, TNF-α promotes HSC survival and myeloid differentiation by activating a strong and specific p65-nuclear factor κB (NF-κB)-dependent gene program that primarily prevents necroptosis rather than apoptosis, induces immunomodulatory functions, and poises HSCs for myeloid cell production. These TNF-α-driven mechanisms are critical for HSC response to inflammatory stress but are also hijacked in aged and malignant HSCs. Our results reveal several TNF-α-mediated pro-survival mechanisms unique to HSCs, highlight an important role for necroptosis in HSC killing, and establish TNF-α as a major pro-survival and pro-regeneration factor for HSCs.
Keywords: Humans; Animals; Cell Differentiation; Cell Survival; Mice; Immunomodulation; Mice, Inbred C57BL; Myeloid Cells; Mice, Knockout; Gene Expression Regulation; Apoptosis; Inflammation; Tumor Necrosis Factor-alpha; Hematopoietic Stem Cells; TNF-α; Regeneration; Cell Self Renewal; cIAP2; hematopoietic stem cells; HSCs; inflammation; leukemia; myeloid regeneration; necroptosis; Necroptosis; NF-kappa B; NF-κB; PD-L1; stem cell activation

Redressing the interactions between stem cells and immune system in tissue regeneration - Fang, Jiankai; Feng, Chao; Chen, Wangwang; Hou, Pengbo; Liu, Zhanhong; Zuo, Muqiu; Han, Yuyi; Xu, Chenchang; Melino, Gerry; Verkhratsky, Alexei; Wang, Ying; Shao, Changshun; et al. (Biology Direct, 2021)
Skeletal muscle has an extraordinary regenerative capacity reflecting the rapid activation and effective differentiation of muscle stem cells (MuSCs). In the course of muscle regeneration, MuSCs are reprogrammed by immune cells. In turn, MuSCs confer immune cells anti-inflammatory properties to resolve inflammation and facilitate tissue repair. Indeed, MuSCs can exert therapeutic effects on various degenerative and inflammatory disorders based on their immunoregulatory ability, including effects primed by interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α). At the molecular level, the tryptophan metabolites, kynurenine or kynurenic acid, produced by indoleamine 2,3-dioxygenase (IDO), augment the expression of TNF-stimulated gene 6 (TSG6) through the activation of the aryl hydrocarbon receptor (AHR). In addition, insulin growth factor 2 (IGF2) produced by MuSCs can endow maturing macrophages oxidative phosphorylation (OXPHOS)-dependent anti-inflammatory functions. Herein, we summarize the current understanding of the immunomodulatory characteristics of MuSCs and the issues related to their potential applications in pathological conditions, including COVID-19.
Keywords: Humans; Animals; Macrophages; Cell Differentiation; Mice; Interferon-gamma; Immunomodulation; Inflammation; Tumor Necrosis Factor-alpha; Immune System; COVID-19; Stem Cells; Regeneration; Cell Proliferation; Cell Adhesion Molecules; Immune cells; Indoleamine-Pyrrole 2,3,-Dioxygenase; Insulin-Like Growth Factor II; Kynurenic Acid; Kynurenine; Muscle repair; Muscles; MuSCs; Oxidative Phosphorylation; Receptors, Aryl Hydrocarbon; Tissue regeneration; Tryptophan

IL-6: regulator of Treg/Th17 balance - Kimura, Akihiro; Kishimoto, Tadamitsu (European Journal of Immunology, 2010)
IL-6 is a pleiotropic cytokine involved in the physiology of virtually every organ system. Recent studies have demonstrated that IL-6 has a very important role in regulating the balance between IL-17-producing Th17 cells and regulatory T cells (Treg). The two T-cell subsets play prominent roles in immune functions: Th17 cell is a key player in the pathogenesis of autoimmune diseases and protection against bacterial infections, while Treg functions to restrain excessive effector T-cell responses. IL-6 induces the development of Th17 cells from naïve T cells together with TGF-beta; in contrast, IL-6 inhibits TGF-beta-induced Treg differentiation. Dysregulation or overproduction of IL-6 leads to autoimmune diseases such as multiple sclerosis (MS) and rheumatoid arthritis (RA), in which Th17 cells are considered to be the primary cause of pathology. Given the critical role of IL-6 in altering the balance between Treg and Th17 cells, controlling IL-6 activities is potentially an effective approach in the treatment of various autoimmune and inflammatory diseases. Here, we review the role of IL-6 in regulating Th17/Treg balance and describe the critical functions of IL-6 and Th17 in immunity and immune-pathology.
Keywords: Humans; Animals; Cell Differentiation; Immunomodulation; T-Lymphocytes, Helper-Inducer; Interleukin-17; T-Lymphocytes, Regulatory; Autoimmune Diseases; Interleukin-6; Transforming Growth Factor beta; Homeostasis; Bacterial Infections

Effector and memory T-cell differentiation: implications for vaccine development - Kaech, Susan M.; Wherry, E. John; Ahmed, Raft (Nature Reviews. Immunology, 2002)
Recent work shows that after stimulation with antigen, CD4+ and CD8+ T cells embark on a programme of proliferation that is closely linked with the acquisition of effector functions and leads ultimately to memory-cell formation. Here, we discuss the signals required for commitment to this programme of development and the factors that might influence its progression. Models of the pathways of effector and memory T-cell differentiation are discussed, and we highlight the implications of this new understanding for the optimization of vaccine strategies.
Keywords: Humans; Animals; Cell Differentiation; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; T-Lymphocytes; Immunologic Memory; Vaccines

TCR signal strength controls the differentiation of CD4+ effector and memory T cells - Snook, Jeremy P.; Kim, Chulwoo; Williams, Matthew A. (Science immunology, 2018)
CD4+ T cell responses are composed of heterogeneous TCR signals that influence the acquisition of effector and memory characteristics. We sought to define early TCR-dependent activation events that control T cell differentiation. A polyclonal panel of TCRs specific for the same viral antigen demonstrated substantial variability in TCR signal strength, expression of CD25 and activation of NFAT and NFκB. Following viral infection, strong TCR signals corresponded to Th1 differentiation, whereas Tfh and memory T cell differentiation were most efficient when TCR signals were comparatively lower. We observed substantial heterogeneity in TCR-dependent CD25 expression in vivo, and the vast majority of CD4+ memory T cells were derived from CD25lo effector cells that displayed decreased TCR signaling in vivo. Nevertheless, memory T cells derived from either CD25lo or CD25hi effector cells responded vigorously to rechallenge, indicating that while early clonal differences in CD25 expression predicted memory T cell numbers, they did not predict memory T cell function on a per cell basis. Gene transcription analysis demonstrated expression clustering based on CD25 expression and enrichment of transcripts associated with enhanced Tfh and memory development within CD25lo effector cells. Direct enhancement of TCR signaling via knockdown of SHP-1, a tyrosine phosphatase that suppresses early TCR signaling events, favored the differentiation of Th1 effector and memory cells. We conclude that strong TCR signals during early T cell activation favor terminal Th1 differentiation over long-term Th1 and Tfh memory responses., Strong TCR signals favor the differentiation of short-lived effector Th1 cells over long-lived memory T cells.

Memory T cells: strategies for optimizing tumor immunotherapy - Liu, Qingjun; Sun, Zhongjie; Chen, Ligong (Protein & Cell, 2020)
Several studies have demonstrated that memory T cells including stem cell memory (Tscm) T cells and central memory (Tcm) T cells show superior persistence and antitumor immunity compared with effector memory T (Tem) cells and effector T (Teff) cells. Furthermore, the Tcm/Teff ratio has been reported to be a predictive biomarker of immune responses against some tumors. Thus, a system-level understanding of the mechanisms underlying the differentiation of effector and memory T cells is of increasing importance for developing immunological strategies against various tumors. This review focuses on recent advances in efficacy against tumors, the origin, formation mechanisms of memory T cells, and the role of the gut microbiota in memory T cell formation. Furthermore, we summarize strategies to generate memory T cells in (ex) vivo that, might be applicable in clinical practice.

Effect of cellular aging on memory T-cell homeostasis - Swain, Arpit C.; Borghans, José A.M.; de Boer, Rob J. (Frontiers in Immunology, 2022)
The fact that T-cell numbers remain relatively stable throughout life, and that T-cell proliferation rates increase during lymphopenia, has led to the consensus that T-cell numbers are regulated in a density-dependent manner. Competition for resources among memory T cells has been proposed to underlie this ‘homeostatic’ regulation. We first review how two classic models of resource competition affect the T-cell receptor (TCR) diversity of the memory T-cell pool. First, ‘global’ competition for cytokines leads to a skewed repertoire that tends to be dominated by the very first immune response. Second, additional ‘cognate’ competition for specific antigens results in a very diverse and stable memory T-cell pool, allowing every antigen to be remembered, which we therefore define as the ‘gold-standard’. Because there is limited evidence that memory T cells of the same specificity compete more strongly with each other than with memory T cells of different specificities, i.e., for ‘cognate’ competition, we investigate whether cellular aging could account for a similar level of TCR diversity. We define cellular aging as a declining cellular fitness due to reduced proliferation. We find that the gradual erosion of previous T-cell memories due to cellular aging allows for better establishment of novel memories and for a much higher level of TCR diversity compared to global competition. A small continual source (either from stem-cell-like memory T-cells or from naive T-cells due to repeated antigen exposure) improves the diversity of the memory T-cell pool, but remarkably, only in the cellular aging model. We further show that the presence of a source keeps the inflation of chronic memory responses in check by maintaining the immune memories to non-chronic antigens. We conclude that cellular aging along with a small source provides a novel and immunologically realistic mechanism to achieve and maintain the ‘gold-standard’ level of TCR diversity in the memory T-cell pool.

TCR signal strength controls the differentiation of CD4+ effector and memory T cells - Snook, Jeremy P.; Kim, Chulwoo; Williams, Matthew A. (Science immunology, 2018)
CD4+ T cell responses are composed of heterogeneous TCR signals that influence the acquisition of effector and memory characteristics. We sought to define early TCR-dependent activation events that control T cell differentiation. A polyclonal panel of TCRs specific for the same viral antigen demonstrated substantial variability in TCR signal strength, expression of CD25 and activation of NFAT and NFκB. Following viral infection, strong TCR signals corresponded to Th1 differentiation, whereas Tfh and memory T cell differentiation were most efficient when TCR signals were comparatively lower. We observed substantial heterogeneity in TCR-dependent CD25 expression in vivo, and the vast majority of CD4+ memory T cells were derived from CD25lo effector cells that displayed decreased TCR signaling in vivo. Nevertheless, memory T cells derived from either CD25lo or CD25hi effector cells responded vigorously to rechallenge, indicating that while early clonal differences in CD25 expression predicted memory T cell numbers, they did not predict memory T cell function on a per cell basis. Gene transcription analysis demonstrated expression clustering based on CD25 expression and enrichment of transcripts associated with enhanced Tfh and memory development within CD25lo effector cells. Direct enhancement of TCR signaling via knockdown of SHP-1, a tyrosine phosphatase that suppresses early TCR signaling events, favored the differentiation of Th1 effector and memory cells. We conclude that strong TCR signals during early T cell activation favor terminal Th1 differentiation over long-term Th1 and Tfh memory responses., Strong TCR signals favor the differentiation of short-lived effector Th1 cells over long-lived memory T cells.

Memory T cells: strategies for optimizing tumor immunotherapy - Liu, Qingjun; Sun, Zhongjie; Chen, Ligong (Protein & Cell, 2020)
Several studies have demonstrated that memory T cells including stem cell memory (Tscm) T cells and central memory (Tcm) T cells show superior persistence and antitumor immunity compared with effector memory T (Tem) cells and effector T (Teff) cells. Furthermore, the Tcm/Teff ratio has been reported to be a predictive biomarker of immune responses against some tumors. Thus, a system-level understanding of the mechanisms underlying the differentiation of effector and memory T cells is of increasing importance for developing immunological strategies against various tumors. This review focuses on recent advances in efficacy against tumors, the origin, formation mechanisms of memory T cells, and the role of the gut microbiota in memory T cell formation. Furthermore, we summarize strategies to generate memory T cells in (ex) vivo that, might be applicable in clinical practice.

Effect of cellular aging on memory T-cell homeostasis - Swain, Arpit C.; Borghans, José A.M.; de Boer, Rob J. (Frontiers in Immunology, 2022)
The fact that T-cell numbers remain relatively stable throughout life, and that T-cell proliferation rates increase during lymphopenia, has led to the consensus that T-cell numbers are regulated in a density-dependent manner. Competition for resources among memory T cells has been proposed to underlie this ‘homeostatic’ regulation. We first review how two classic models of resource competition affect the T-cell receptor (TCR) diversity of the memory T-cell pool. First, ‘global’ competition for cytokines leads to a skewed repertoire that tends to be dominated by the very first immune response. Second, additional ‘cognate’ competition for specific antigens results in a very diverse and stable memory T-cell pool, allowing every antigen to be remembered, which we therefore define as the ‘gold-standard’. Because there is limited evidence that memory T cells of the same specificity compete more strongly with each other than with memory T cells of different specificities, i.e., for ‘cognate’ competition, we investigate whether cellular aging could account for a similar level of TCR diversity. We define cellular aging as a declining cellular fitness due to reduced proliferation. We find that the gradual erosion of previous T-cell memories due to cellular aging allows for better establishment of novel memories and for a much higher level of TCR diversity compared to global competition. A small continual source (either from stem-cell-like memory T-cells or from naive T-cells due to repeated antigen exposure) improves the diversity of the memory T-cell pool, but remarkably, only in the cellular aging model. We further show that the presence of a source keeps the inflation of chronic memory responses in check by maintaining the immune memories to non-chronic antigens. We conclude that cellular aging along with a small source provides a novel and immunologically realistic mechanism to achieve and maintain the ‘gold-standard’ level of TCR diversity in the memory T-cell pool.

Mycobacterium tuberculosis-Induced Neutrophil Extracellular Traps Activate Human Macrophages - Braian, Clara; Hogea, Valentin; Stendahl, Olle (Journal of Innate Immunity, 2013)
Neutrophils activated by Mycobacterium tuberculosis (Mtb) form neutrophil extracellular traps (NETs), containing DNA and several biologically active cytosolic and granular proteins. These NETs may assist in the innate immune defense against different pathogens. We investigated whether the NET-forming neutrophils mediate an activating signal to macrophages during the early multicellular inflammatory reaction and granuloma formation. Mtb-induced NETs were found to be reactive oxygen species dependent and phagocytosis dependent. A neutrophil elastase inhibitor also delayed NET formation. However, NET formation occurred independently of Mtb-induced apoptosis. We observed close interactions between macrophages and Mtb-activated neutrophils, where macrophages bound and phagocytosed NETs. Significant secretion of the cytokines interleukin (IL)-6, tumor necrosis factor-α, IL-1β and IL-10 were detected from macrophages cocultured with NETs from Mtb-activated but not phorbol myristate acetate-activated neutrophils. NETs binding heat shock protein 72 (Hsp72) or recombinant Hsp72 were able to trigger cytokine release from macrophages. Only Mtb-induced NETs contained Hsp72, suggesting that these NETs can transfer this danger signal to adjacent macrophages. We propose that Hsp72 sequestered in NETs plays an important role in the interaction between neutrophils and macrophages during the early innate immune phase of an Mtb infection. The immunomodulatory role of NETs and proteins derived from them may influence not only chronic inflammation during tuberculosis but also immune regulation and autoimmunity.

Peculiarities of cell death mechanisms in neutrophils - Geering, B.; Simon, H.-U. (Cell Death & Differentiation, 2011)
Analyses of neutrophil death mechanisms have revealed many similarities with other cell types; however, a few important molecular features make these cells unique executors of cell death mechanisms. For instance, in order to fight invading pathogens, neutrophils possess a potent machinery to produce reactive oxygen species (ROS), the phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. Evidence is emerging that these ROS are crucial in the execution of most neutrophil cell death mechanisms. Likewise, neutrophils exhibit many diverse granules that are packed with cytotoxic mediators. Of those, cathepsins were recently shown to activate pro-apoptotic B-cell lymphoma-2 (Bcl-2) family members and caspases, thus acting on apoptosis regulators. Moreover, neutrophils have few mitochondria, which hardly participate in ATP synthesis, as neutrophils gain energy from glycolysis. In spite of relatively low levels of cytochrome c in these cells, the mitochondrial death pathway is functional. In addition to these pecularities defining neutrophil death pathways, neutrophils are terminally differentiated cells, hence they do not divide but undergo apoptosis shortly after maturation. The initial trigger of this spontaneous apoptosis remains to be determined, but may result from low transcription and translation activities in mature neutrophils. Due to the unique biological characteristics of neutrophils, pharmacological intervention of inflammation has revealed unexpected and sometimes disappointing results when neutrophils were among the prime target cells during therapy. In this study, we review the current and emerging models of neutrophil cell death mechanisms with a focus on neutrophil peculiarities.
Keywords: Neutrophils; Cell death

Immune complex-induced apoptosis and concurrent immune complex clearance are anti-inflammatory neutrophil functions - Karmakar, Utsa; Chu, Julia Y.; Sundaram, Kruthika; Astier, Anne L.; Garside, Hannah; Hansen, Carsten G.; Dransfield, Ian; Vermeren, Sonja (Cell Death & Disease, 2021)
Persistent neutrophilic inflammation drives host damage in autoimmune diseases that are characterized by abundant immune complexes. Insoluble immune complexes (iICs) potently activate pro-inflammatory neutrophil effector functions. We and others have shown that iICs also promote resolution of inflammation via stimulation of neutrophil apoptosis. We demonstrate here that iICs trigger FcγRIIa-dependent neutrophil macropinocytosis, leading to the rapid uptake, and subsequent degradation of iICs. We provide evidence that concurrent iIC-induced neutrophil apoptosis is distinct from phagocytosis-induced cell death. First, uptake of iICs occurs by FcγRII-stimulated macropinocytosis, rather than phagocytosis. Second, production of reactive oxygen species, but not iIC-internalization is a pre-requisite for iIC-induced neutrophil apoptosis. Our findings identify a previously unknown mechanism by which neutrophils can remove pro-inflammatory iICs from the circulation. Together iIC clearance and iIC-induced neutrophil apoptosis may act to prevent the potential escalation of neutrophilic inflammation in response to iICs.

Targeting dendritic cells to accelerate T-cell activation overcomes a bottleneck in tuberculosis vaccine efficacy - Griffiths, Kristin L.; Ahmed, Mushtaq; Das, Shibali; Gopal, Radha; Horne, William; Connell, Terry D.; Moynihan, Kelly D.; Kolls, Jay K.; Irvine, Darrell J.; Artyomov, Maxim N.; Rangel-Moreno, Javier; Khader, Shabaana A. (Nature Communications, 2016)
The development of a tuberculosis (TB) vaccine that induces sterilizing immunity to Mycobacterium tuberculosis infection has been elusive. Absence of sterilizing immunity induced by TB vaccines may be due to delayed activation of mucosal dendritic cells (DCs), and subsequent delay in antigen presentation and activation of vaccine-induced CD4+ T-cell responses. Here we show that pulmonary delivery of activated M. tuberculosis antigen-primed DCs into vaccinated mice, at the time of M. tuberculosis exposure, can overcome the delay in accumulation of vaccine-induced CD4+ T-cell responses. In addition, activating endogenous host CD103+ DCs and the CD40-CD40L pathway can similarly induce rapid accumulation of vaccine-induced lung CD4+ T-cell responses and limit early M. tuberculosis growth. Thus, our study provides proof of concept that targeting mucosal DCs can accelerate vaccine-induced T-cell responses on M. tuberculosis infection, and provide insights to overcome bottlenecks in TB vaccine efficacy.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis, Pulmonary; Mice; Female; CD4-Positive T-Lymphocytes; Mice, Inbred C57BL; Male; Antigen Presentation; Lymphocyte Activation; Adoptive Transfer; Antigens, CD; Dendritic Cells; Integrin alpha Chains; Mice, 129 Strain; Mice, Knockout; Mice, Transgenic

OX40 Ligand Contributes to Human Lupus Pathogenesis by Promoting T Follicular Helper Response - Jacquemin, Clément; Schmitt, Nathalie; Contin-Bordes, Cécile; Liu, Yang; Narayanan, Priya; Seneschal, Julien; Maurouard, Typhanie; Dougall, David; Davizon, Emily Spence; Dumortier, Hélène; Douchet, Isabelle; Raffray, Loïc; et al. (Immunity, 2015)
Increased activity of T follicular helper (Tfh) cells plays a major pathogenic role in systemic lupus erythematosus (SLE). However, the mechanisms that cause aberrant Tfh cell responses in SLE remain elusive. Here we showed the OX40 ligand (OX40L)-OX40 axis contributes to the aberrant Tfh response in SLE. OX40L was expressed by myeloid antigen-presenting cells (APCs), but not B cells, in blood and in inflamed tissues in adult and pediatric SLE patients. The frequency of circulating OX40L-expressing myeloid APCs positively correlated with disease activity and the frequency of ICOS(+) blood Tfh cells in SLE. OX40 signals promoted naive and memory CD4(+) T cells to express multiple Tfh cell molecules and were sufficient to induce them to become functional B cell helpers. Immune complexes containing RNA induced OX40L expression on myeloid APCs via TLR7 activation. Our study provides a rationale to target the OX40L-OX40 axis as a therapeutic modality for SLE.
Keywords: Humans; Cell Differentiation; Cells, Cultured; Female; Cytokines; B-Lymphocytes; Adult; Male; Middle Aged; Young Adult; Adolescent; Aged; Antigen Presentation; Disease Progression; Immunologic Memory; Inducible T-Cell Co-Stimulator Protein; Lupus Erythematosus, Systemic; Lymphocyte Activation; Molecular Targeted Therapy; Myeloid Cells; OX40 Ligand; Receptors, OX40; RNA; Signal Transduction; T-Lymphocytes, Helper-Inducer; Toll-Like Receptor 7

A Functional Role for Antibodies in Tuberculosis - Lu, Lenette L.; Chung, Amy W.; Rosebrock, Tracy R.; Ghebremichael, Musie; Yu, Wen Han; Grace, Patricia S.; Schoen, Matthew K.; Tafesse, Fikadu; Martin, Constance; Leung, Vivian; Mahan, Alison E.; Sips, Magdalena; et al. (Cell, 2016)
While a third of the world carries the burden of tuberculosis, disease control has been hindered by a lack of tools, including a rapid, point-of-care diagnostic and a protective vaccine. In many infectious diseases, antibodies (Abs) are powerful biomarkers and important immune mediators. However, in Mycobacterium tuberculosis (Mtb) infection, a discriminatory or protective role for humoral immunity remains unclear. Using an unbiased antibody profiling approach, we show that individuals with latent tuberculosis infection (Ltb) and active tuberculosis disease (Atb) have distinct Mtb-specific humoral responses, such that Ltb infection is associated with unique Ab Fc functional profiles, selective binding to FcγRIII, and distinct Ab glycosylation patterns. Moreover, compared to Abs from Atb, Abs from Ltb drove enhanced phagolysosomal maturation, inflammasome activation, and, most importantly, macrophage killing of intracellular Mtb. Combined, these data point to a potential role for Fc-mediated Ab effector functions, tuned via differential glycosylation, in Mtb control.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; tuberculosis; Female; antibodies; Adult; Fc-receptors; Glycosylation; Immunity, Humoral; Immunoglobulin Fc Fragments; inflammasome; innate immunity; Latent Tuberculosis; Macrophage Activation; Male; Middle Aged; Polysaccharides; Protein Array Analysis; Receptors, IgG; Young Adult

Human isotype-dependent inhibitory antibody responses against Mycobacterium tuberculosis - Zimmermann, Natalie; Thormann, Verena; Hu, Bo; Köhler, Anne-Britta; Imai-Matsushima, Aki; Locht, Camille; Arnett, Eusondia; Schlesinger, Larry S.; Zoller, Thomas; Schürmann, Mariana; Kaufmann, Stefan He; Wardemann, Hedda (EMBO molecular medicine, 2016)
Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B-cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB-exposed healthcare workers. The data suggest that the acute plasmablast response to MTB originates from reactivated memory B cells and indicates a mucosal origin. Through functional analyses, we identified MTB inhibitory antibodies against mycobacterial antigens including virulence factors that play important roles in host cell infection. The inhibitory activity of anti-MTB antibodies was directly linked to their isotype. Monoclonal as well as purified serum IgA antibodies showed MTB blocking activity independently of Fc alpha receptor expression, whereas IgG antibodies promoted the host cell infection. Together, the data provide molecular insights into the human antibody response to MTB and may thereby facilitate the design of protective vaccination strategies.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; antibodies; Antibodies, Monoclonal; Antibody Formation; B cells; B-Lymphocytes; Immunoglobulin Isotypes; infection; isotype

Development of a murine mycobacterial growth inhibition assay for evaluating vaccines against Mycobacterium tuberculosis - Parra, Marcela; Yang, Amy L.; Lim, JaeHyun; Kolibab, Kristopher; Derrick, Steven; Cadieux, Nathalie; Perera, Liyanage P.; Jacobs, William R.; Brennan, Michael; Morris, Sheldon L. (Clinical and vaccine immunology: CVI, 2009)
The development and characterization of new tuberculosis (TB) vaccines has been impeded by the lack of reproducible and reliable in vitro assays for measuring vaccine activity. In this study, we developed a murine in vitro mycobacterial growth inhibition assay for evaluating TB vaccines that directly assesses the capacity of immune splenocytes to control the growth of Mycobacterium tuberculosis within infected macrophages. Using this in vitro assay, protective immune responses induced by immunization with five different types of TB vaccine preparations (Mycobacterium bovis BCG, an attenuated M. tuberculosis mutant strain, a DNA vaccine, a modified vaccinia virus strain Ankara [MVA] construct expressing four TB antigens, and a TB fusion protein formulated in adjuvant) can be detected. Importantly, the levels of vaccine-induced mycobacterial growth-inhibitory responses seen in vitro after 1 week of coculture correlated with the protective immune responses detected in vivo at 28 days postchallenge in a mouse model of pulmonary tuberculosis. In addition, similar patterns of cytokine expression were evoked at day 7 of the in vitro culture by immune splenocytes taken from animals immunized with the different TB vaccines. Among the consistently upregulated cytokines detected in the immune cocultures are gamma interferon, growth differentiation factor 15, interleukin-21 (IL-21), IL-27, and tumor necrosis factor alpha. Overall, we have developed an in vitro functional assay that may be useful for screening and comparing new TB vaccine preparations, investigating vaccine-induced protective mechanisms, and assessing manufacturing issues, including product potency and stability.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Macrophages; Tuberculosis; Mice; Cytokines; Coculture Techniques; Leukocytes, Mononuclear

Non-tuberculous mycobacteria have diverse effects on BCG efficacy against Mycobacterium tuberculosis - Poyntz, Hazel C.; Stylianou, Elena; Griffiths, Kristin L.; Marsay, Leanne; Checkley, Anna M.; McShane, Helen (Tuberculosis (Edinburgh, Scotland), 2014)
The efficacy of Bacillus Calmette-Guerin (BCG) vaccination in protection against pulmonary tuberculosis (TB) is highly variable between populations. One possible explanation for this variability is increased exposure of certain populations to non-tuberculous mycobacteria (NTM). This study used a murine model to determine the effect that exposure to NTM after BCG vaccination had on the efficacy of BCG against aerosol Mycobacterium tuberculosis challenge. The effects of administering live Mycobacterium avium (MA) by an oral route and killed MA by a systemic route on BCG-induced protection were evaluated. CD4+ and CD8+ T cell responses were profiled to define the immunological mechanisms underlying any effect on BCG efficacy. BCG efficacy was enhanced by exposure to killed MA administered by a systemic route; T helper 1 and T helper 17 responses were associated with increased protection. BCG efficacy was reduced by exposure to live MA administered by the oral route; T helper 2 cells were associated with reduced protection. These findings demonstrate that exposure to NTM can induce opposite effects on BCG efficacy depending on route of exposure and viability of NTM. A reproducible model of NTM exposure would be valuable in the evaluation of novel TB vaccine candidates.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Tuberculosis, Pulmonary; BCG Vaccine; Female; Adjuvants, Immunologic; Cytokines; Lymph Nodes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Administration, Inhalation; Administration, Oral; Aerosols; Bacillus Calmette-Geurin; Immunity, Cellular; Mice, Inbred C57BL; Mouse model; Mycobacterium avium; Mycobacterium avium Complex; Non-tuberculous mycobacteria; Spleen; Th1 Cells; Vaccines, Attenuated; Vaccines, Live, Unattenuated

Non-Human Primate Models of Tuberculosis - Peña, Juliet C.; Ho, Wen-Zhe (Microbiology Spectrum, 2016)
Among the animal models of tuberculosis (TB), the non-human primates, particularly rhesus macaques (Macaca fascicularis) and cynomolgus macaques (Macaca mulatta), share the greatest anatomical and physiological similarities with humans. Macaques are highly susceptible to Mycobacterium tuberculosis infection and manifest the complete spectrum of clinical and pathological manifestations of TB as seen in humans. Therefore, the macaque models have been used extensively for investigating the pathogenesis of M. tuberculosis infection and for preclinical testing of drugs and vaccines against TB. This review focuses on published major studies that exemplify how the rhesus and cynomolgus macaques have enhanced and may continue to advance global efforts in TB research.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; Antitubercular Agents; Drug Evaluation, Preclinical; Disease Models, Animal; Macaca fascicularis; Macaca mulatta

Computational and Empirical Studies Predict Mycobacterium tuberculosis-Specific T Cells as a Biomarker for Infection Outcome - Marino, Simeone; Gideon, Hannah P.; Gong, Chang; Mankad, Shawn; McCrone, John T.; Lin, Philana Ling; Linderman, Jennifer J.; Flynn, JoAnne L.; Kirschner, Denise E. (PLoS computational biology, 2016)
Identifying biomarkers for tuberculosis (TB) is an ongoing challenge in developing immunological correlates of infection outcome and protection. Biomarker discovery is also necessary for aiding design and testing of new treatments and vaccines. To effectively predict biomarkers for infection progression in any disease, including TB, large amounts of experimental data are required to reach statistical power and make accurate predictions. We took a two-pronged approach using both experimental and computational modeling to address this problem. We first collected 200 blood samples over a 2- year period from 28 non-human primates (NHP) infected with a low dose of Mycobacterium tuberculosis. We identified T cells and the cytokines that they were producing (single and multiple) from each sample along with monkey status and infection progression data. Machine learning techniques were used to interrogate the experimental NHP datasets without identifying any potential TB biomarker. In parallel, we used our extensive novel NHP datasets to build and calibrate a multi-organ computational model that combines what is occurring at the site of infection (e.g., lung) at a single granuloma scale with blood level readouts that can be tracked in monkeys and humans. We then generated a large in silico repository of in silico granulomas coupled to lymph node and blood dynamics and developed an in silico tool to scale granuloma level results to a full host scale to identify what best predicts Mycobacterium tuberculosis (Mtb) infection outcomes. The analysis of in silico blood measures identifies Mtb-specific frequencies of effector T cell phenotypes at various time points post infection as promising indicators of infection outcome. We emphasize that pairing wetlab and computational approaches holds great promise to accelerate TB biomarker discovery.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Computational Biology; Algorithms; Tuberculosis, Pulmonary; Lung; Macaca fascicularis; Cytokines; Biomarkers; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Computer Simulation; Databases, Factual; Models, Immunological; T-Lymphocytes

Immunology studies in non-human primate models of tuberculosis - Flynn, JoAnne L.; Gideon, Hannah P.; Mattila, Joshua T.; Lin, Philana Ling (Immunological Reviews, 2015)
Non-human primates, primarily macaques, have been used to study tuberculosis for decades. However, in the last 15 years, this model has been refined substantially to allow careful investigations of the immune response and host-pathogen interactions in Mycobacterium tuberculosis infection. Low-dose challenge with fully virulent strains in cynomolgus macaques result in the full clinical spectrum seen in humans, including latent and active infection. Reagents from humans are usually cross-reactive with macaques, further facilitating the use of this model system to study tuberculosis. Finally, macaques develop the spectrum of granuloma types seen in humans, providing a unique opportunity to investigate bacterial and host factors at the local (lung and lymph node) level. Here, we review the past decade of immunology and pathology studies in macaque models of tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; tuberculosis; Primates; Disease Models, Animal; Granuloma; Adaptive Immunity; Cytokines; granuloma; Immunity, Innate; immunology; Immunomodulation; lymph node; Lymph Nodes; Macaca; macaque; non-human primate; Patient Outcome Assessment; Positron-Emission Tomography; T-Lymphocyte Subsets; Tomography, X-Ray Computed

Testing the H56 Vaccine Delivered in 4 Different Adjuvants as a BCG-Booster in a Non-Human Primate Model of Tuberculosis - Billeskov, Rolf; Tan, Esterlina V.; Cang, Marjorie; Abalos, Rodolfo M.; Burgos, Jasmin; Pedersen, Bo Vestergaard; Christensen, Dennis; Agger, Else Marie; Andersen, Peter (PloS One, 2016)
The search for new and improved tuberculosis (TB) vaccines has focused on IFN-γ both for selecting antigens and for evaluating vaccine delivery strategies. The essential role of IFN-γ in endogenous host protection is well established, but it is still uncertain whether this also holds true for vaccine protection. Here we evaluate the H56 fusion protein vaccine as a BCG booster in a non-human primate (NHP) model of TB that closely recapitulates human TB pathogenesis. To date, only a handful of novel adjuvants have been tested in the NHP model of TB, and therefore we administered H56 in 3 novel cationic liposome adjuvants of increasing immunogenicity (CAF01, CAF04, CAF05) and compared them to H56 in the IC31® adjuvant previously reported to promote protection in this model. The individual clinical parameters monitored during infection (weight, ESR, X-ray) all correlated with survival, and boosting BCG with H56 in all adjuvants resulted in better survival rates compared to BCG alone. The adjuvants promoted IFN-γ-responses of increasing intensity as measured by ELISPOT in the peripheral blood, but the level of vaccine-specific IFN-γ production did not correlate with or predict disease outcome. This study's main outcome underscores the importance of the choice of adjuvant for TB subunit vaccines, and secondly it highlights the need for better correlates of protection in preclinical models of TB.
Keywords: Animals; Tuberculosis; BCG Vaccine; Disease Models, Animal; Adjuvants, Immunologic; Immunization, Secondary; Interferon-gamma; Macaca fascicularis; Recombinant Fusion Proteins; Survival Analysis

Animal Models of Tuberculosis: Guinea Pigs - Clark, Simon; Hall, Yper; Williams, Ann (Cold Spring Harbor Perspectives in Medicine, 2015)
The progression of the disease that follows infection of guinea pigs with Mycobacterium tuberculosis displays many features of human tuberculosis (TB), and the guinea pig model of TB has been used for more than 100 years as a research tool to understand and describe disease mechanisms. Changes in the bacterial burden and pathology following infection can be readily monitored and used to evaluate the impact of TB interventions. Demonstration of the protective efficacy of vaccines in the low-dose aerosol guinea pig model is an important component of the preclinical data package for novel vaccines in development, and there is a continual need to improve the model to facilitate progression of vaccines to the clinic. Development of better tools with which to dissect the immune responses of guinea pigs is a focus of current research., Guinea pigs have been used for more than 100 years in tuberculosis research and display many characteristics of the human disease. They continue to play an important role in the development of new drugs and vaccines.

The Guinea Pig as a Model of Infectious Diseases - PMC

The guinea pig as a model of infectious diseases - Padilla-Carlin, Danielle J.; McMurray, David N.; Hickey, Anthony J. (Comparative Medicine, 2008)
The words 'guinea pig' are synonymous with scientific experimentation, but much less is known about this species than many other laboratory animals. This animal model has been used for approximately 200 y and was the first to be used in the study of infectious diseases such as tuberculosis and diphtheria. Today the guinea pig is used as a model for a number of infectious bacterial diseases, including pulmonary, sexually transmitted, ocular and aural, gastrointestinal, and other infections that threaten the lives of humans. Most studies on the immune response to these diseases, with potential therapies and vaccines, have been conducted in animal models (for example, mouse) that may have less similarity to humans because of the large number of immunologic reagents available for these other species. This review presents some of the diseases for which the guinea pig is regarded as the premier model to study infections because of its similarity to humans with regard to symptoms and immune response. Furthermore, for diseases in which guinea pigs share parallel pathogenesis of disease with humans, they are potentially the best animal model for designing treatments and vaccines. Future studies of immune regulation of these diseases, novel therapies, and preventative measures require the development of new immunologic reagents designed specifically for the guinea pig.
Keywords: Humans; Animals; Guinea Pigs; Disease Models, Animal; Communicable Diseases

Beijing sublineages of Mycobacterium tuberculosis differ in pathogenicity in the guinea pig - Kato-Maeda, Midori; Shanley, Crystal A.; Ackart, David; Jarlsberg, Leah G.; Shang, Shaobin; Obregon-Henao, Andres; Harton, Marisabel; Basaraba, Randall J.; Henao-Tamayo, Marcela; Barrozo, Joyce C.; Rose, Jordan; Kawamura, L. Masae; et al. (Clinical and vaccine immunology: CVI, 2012)
The Beijing family of Mycobacterium tuberculosis strains is part of lineage 2 (also known as the East Asian lineage). In clinical studies, we have observed that isolates from the sublineage RD207 of lineage 2 were more readily transmitted among humans. To investigate the basis for this difference, we tested representative strains with the characteristic Beijing spoligotype from four of the five sublineages of lineage 2 in the guinea pig model and subjected these strains to comparative whole-genome sequencing. The results of these studies showed that all of the clinical strains were capable of growing and causing lung pathology in guinea pigs after low-dose aerosol exposure. Differences between the abilities of the four sublineages to grow in the lungs of these animals were not overt, but members of RD207 were significantly more pathogenic, resulting in severe lung damage. The RD207 strains also induced much higher levels of markers associated with regulatory T cells and showed a significant loss of activated T cells in the lungs over the course of the infections. Whole-genome sequencing of the strains revealed mutations specific for RD207 which may explain this difference. Based on these data, we hypothesize that the sublineages of M. tuberculosis are associated with distinct pathological and clinical phenotypes and that these differences influence the transmissibility of particular M. tuberculosis strains in human populations.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Sequence Analysis, DNA; Guinea Pigs; Disease Models, Animal; Female; Genome, Bacterial; Genotype; Histocytochemistry; Lung; Molecular Typing; Virulence

Replacing, reducing and refining the use of animals in tuberculosis vaccine research - Tanner, Rachel; McShane, Helen (ALTEX, 2017)
Tuberculosis (TB) remains a serious global health threat and an improved vaccine is urgently needed. New candidate TB vaccines are tested using preclinical animal models such as mice, guinea pigs, cattle and non-human primates. Animals are routinely infected with virulent Mycobacterium tuberculosis (Mtb) in challenge experiments to evaluate protective efficacy, raising ethical issues regarding the procedure of infection itself, symptoms of disease and humane end-points. We summarize the importance and limitations of animal models in TB vaccine research and review current alternatives and modifications in the context of the NC3Rs framework for replacing, reducing and refining the use of animals for scientific purposes.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; vaccine; BCG Vaccine; Cattle; Guinea Pigs; Mice; Primates; Disease Models, Animal; 3Rs; animal models; Animal Testing Alternatives; Mtb challenge; Research

Mouse models of human TB pathology: roles in the analysis of necrosis and the development of host-directed therapies - Kramnik, Igor; Beamer, Gillian (Seminars in Immunopathology, 2016)
A key aspect of TB pathogenesis that maintains Mycobacterium tuberculosis in the human population is the ability to cause necrosis in pulmonary lesions. As co-evolution shaped M . tuberculosis (M.tb) and human responses, the complete TB disease profile and lesion manifestation are not fully reproduced by any animal model. However, animal models are absolutely critical to understand how infection with virulent M.tb generates outcomes necessary for the pathogen transmission and evolutionary success. In humans, a wide spectrum of TB outcomes has been recognized based on clinical and epidemiological data. In mice, there is clear genetic basis for susceptibility. Although the spectra of human and mouse TB do not completely overlap, comparison of human TB with mouse lesions across genetically diverse strains firmly establishes points of convergence. By embracing the genetic heterogeneity of the mouse population, we gain tremendous advantage in the quest for suitable in vivo models. Below, we review genetically defined mouse models that recapitulate a key element of M.tb pathogenesis-induction of necrotic TB lesions in the lungs-and discuss how these models may reflect TB stratification and pathogenesis in humans. The approach ensures that roles that mouse models play in basic and translational TB research will continue to increase allowing researchers to address fundamental questions of TB pathogenesis and bacterial physiology in vivo using this well-defined, reproducible, and cost-efficient system. Combination of the new generation mouse models with advanced imaging technologies will also allow rapid and inexpensive assessment of experimental vaccines and therapies prior to testing in larger animals and clinical trials.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Antitubercular Agents; Mice; Animal models; Disease Models, Animal; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Granuloma; Host-directed therapies; Inbred mice; Mechanisms; Necrosis; Neutrophils; Receptors, Somatostatin; sst1

A review of preclinical animal models utilised for TB vaccine evaluation in the context of recent human efficacy data - McShane, Helen; Williams, Ann (Tuberculosis (Edinburgh, Scotland), 2014)
There is an urgent need for an improved TB vaccine. Vaccine development is hindered by the lack of immune correlates and uncertain predictive value of preclinical animal models. As data become available from human efficacy trials, there is an opportunity to evaluate the predictive value of the criteria used to select candidate vaccines. Here we review the efficacy in animal models of the MVA85A candidate vaccine in light of recent human efficacy data and propose refinements to the preclinical models with the aim of increasing their predictive value for human efficacy.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Drug Design; Vaccine; BCG Vaccine; Cattle; Clinical; Drug Evaluation, Preclinical; Efficacy; Guinea Pigs; Mice; Models, Animal; MVA85A; Practice Guidelines as Topic; Pre-clinical; Primates; Vaccines, DNA

Characterising Mycobacterium tuberculosis Rv1510c protein and determining its sequences that specifically bind to two target cell lines - Vera-Bravo, Ricardo; Torres, Elizabeth; Valbuena, John J.; Ocampo, Marisol; Rodríguez, Luis E.; Puentes, Alvaro; García, Javier E.; Curtidor, Hernando; Cortés, Jimena; Vanegas, Magnolia; Rivera, Zuly J.; Díaz, Andrea; et al. (Biochemical and Biophysical Research Communications, 2005)
The process of Mycobacterium tuberculosis infection of the macrophage implies a very little-known initial recognition and adherence step, important for mycobacterial survival; many proteins even remain like hypothetical. The Rv1510c gene, encoding a putatively conserved membrane protein, was investigated by analysing the M. tuberculosis genome sequence data reported by Cole et al. and a previous report that used PCR assays to show that the Rv1510 gene was only present in M. tuberculosis. This article confirmed all the above and identified the transcribed gene in M. tuberculosis, Mycobacterium africanum, and in M. tuberculosis clinical isolates. Antibodies raised against peptides from this protein recognised a 44 kDa band, corresponding to Rv1510c theoretical mass (44,294 Da). Assays involving synthetic peptides covering the whole protein binding to U937 and A549 cell lines led to recognising five high activity binding peptides in the Rv1510 protein: 11094, 11095, 11105, 11108, and 11111. Their affinity constants and Hill coefficients were determined by using U937 cells. Cross-linking assays performed with some of these HABPs showed that they specifically bound to a U937 cell line 51 kDa protein, but not to Hep G2 or red blood cell proteins, showing this interaction's specificity.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Base Sequence; Binding Sites; Cell Line; Circular Dichroism; Cross-Linking Reagents; DNA, Bacterial; Genes, Bacterial; Humans; Kinetics; Membrane Proteins; Molecular Sequence Data; Molecular Weight; Mycobacterium tuberculosis; Peptide Fragments; U937 Cells

Mycobacterium tuberculosis H37Rv LpqG Protein Peptides Can Inhibit Mycobacterial Entry through Specific Interactions - Sánchez-Barinas, Christian David; Ocampo, Marisol; Vanegas, Magnolia; Castañeda-Ramirez, Jeimmy Johana; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Molecules (Basel, Switzerland), 2018)
Mycobacterium tuberculosis is the causative agent of tuberculosis, a disease causing major mortality worldwide. As part of a systematic methodology for studying M. tuberculosis surface proteins which might be involved in host-pathogen interactions, our group found that LpqG surface protein (Rv3623) found in M. tuberculosis complex strains was located on the mycobacterial envelope and that peptide 16661 (21SGCDSHNSGSLGADPRQVTVY40) had high specific binding to U937 monocyte-derived macrophages and inhibited mycobacterial entry to such cells in a concentration-dependent way. A region having high specific binding to A549 alveolar epithelial cells was found which had low mycobacterial entry inhibition. As suggested in previous studies, relevant sequences in the host-pathogen interaction do not induce an immune response and peptides characterised as HABPs are poorly recognised by sera from individuals regardless of whether they have been in contact with M. tuberculosis. Our approach to designing a synthetic, multi-epitope anti-tuberculosis vaccine has been based on identifying sequences involved in different proteins' mycobacteria-target cell interaction and modifying their sequence to improve their immunogenic characteristics, meaning that peptide 16661 sequence should be considered in such design.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Mycobacterium tuberculosis; Peptide Fragments; Cell Line, Tumor; Computational Biology; Protein Binding; synthetic peptide; Macrophages; Models, Molecular; Transcription, Genetic; Protein Conformation; Gene Expression Regulation, Bacterial; Antitubercular Agents; lipoprotein; LpqG; mycobacterial entry inhibition; Rv3623; vaccine

Peptides from the Mycobacterium tuberculosis Rv1980c protein involved in human cell infection: insights into new synthetic subunit vaccine candidates - Rodríguez, Diana; Vizcaíno, Carolina; Ocampo, Marisol; Curtidor, Hernando; Pinto, Marta; Elkin Patarroyo, Manuel; Alfonso Patarroyo, Manuel (Biological Chemistry, 2010)
Mycobacterium tuberculosis infection continues to be a major cause of morbidity and mortality throughout the world. The vast complexity of the intracellular pathogen M. tuberculosis and the diverse mechanisms by which it can invade host cells highlight the importance of developing a fully protective vaccine. Our vaccine development strategy consists of including fragments from multiple mycobacterial proteins involved in cell invasion. The aim of this study was to identify high activity binding peptides (HABPs) in the immunogenic protein Rv1980c from M. tuberculosis H37Rv with the ability to inhibit mycobacterial invasion into U937 monocyte-derived macrophages and A549 cells. The presence and transcription of the Rv1980c gene was assessed in members belonging to the M. tuberculosis complex and other nontuberculous mycobacteria by PCR and RT-PCR, respectively. Cell surface localization was confirmed by immuno-electron microscopy. Three peptides binding with high activity to U937 cells and one to A549 cells were identified. HABPs 31100, 31101, and 31107 inhibited invasion of M. tuberculosis into A549 and U937 cells and therefore could be promising candidates for the design of a subunit-based antituberculous vaccine.
Keywords: Bacterial Proteins; Binding Sites; Humans; Mycobacterium tuberculosis; Peptide Fragments; Blotting, Western; Models, Molecular; Transcription, Genetic; Vaccines, Synthetic; Bacterial Vaccines; Alveolar Epithelial Cells; Cells, Cultured

Mycobacterium tuberculosis H37Rv LpqG Protein Peptides Can Inhibit Mycobacterial Entry through Specific Interactions - Sánchez-Barinas, Christian David; Ocampo, Marisol; Vanegas, Magnolia; Castañeda-Ramirez, Jeimmy Johana; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Molecules (Basel, Switzerland), 2018)
Mycobacterium tuberculosis is the causative agent of tuberculosis, a disease causing major mortality worldwide. As part of a systematic methodology for studying M. tuberculosis surface proteins which might be involved in host-pathogen interactions, our group found that LpqG surface protein (Rv3623) found in M. tuberculosis complex strains was located on the mycobacterial envelope and that peptide 16661 (21SGCDSHNSGSLGADPRQVTVY40) had high specific binding to U937 monocyte-derived macrophages and inhibited mycobacterial entry to such cells in a concentration-dependent way. A region having high specific binding to A549 alveolar epithelial cells was found which had low mycobacterial entry inhibition. As suggested in previous studies, relevant sequences in the host-pathogen interaction do not induce an immune response and peptides characterised as HABPs are poorly recognised by sera from individuals regardless of whether they have been in contact with M. tuberculosis. Our approach to designing a synthetic, multi-epitope anti-tuberculosis vaccine has been based on identifying sequences involved in different proteins' mycobacteria-target cell interaction and modifying their sequence to improve their immunogenic characteristics, meaning that peptide 16661 sequence should be considered in such design.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Mycobacterium tuberculosis; Peptide Fragments; Cell Line, Tumor; Computational Biology; Protein Binding; synthetic peptide; Macrophages; Models, Molecular; Transcription, Genetic; Protein Conformation; Gene Expression Regulation, Bacterial; Antitubercular Agents; lipoprotein; LpqG; mycobacterial entry inhibition; Rv3623; vaccine

Specific interaction between Mycobacterium tuberculosis lipoprotein-derived peptides and target cells inhibits mycobacterial entry in vitro - Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Chemical Biology & Drug Design, 2014)
Tuberculosis (TB) continues being one of the diseases having the greatest mortality rates around the world, 8.7 million cases having been reported in 2011. An efficient vaccine against TB having a great impact on public health is an urgent need. Usually, selecting antigens for vaccines has been based on proteins having immunogenic properties for patients suffering TB and having had promising results in mice and non-human primates. Our approach has been based on a functional approach involving the pathogen-host interaction in the search for antigens to be included in designing an efficient, minimal, subunit-based anti-TB vaccine. This means that Mycobacterium tuberculosis has mainly been involved in studies and that lipoproteins represent an important kind of protein on the cell envelope which can also contribute towards this pathogen's virulence. This study has assessed the expression of four lipoproteins from M. tuberculosis H37Rv, that is, Rv1411c (LprG), Rv1911c (LppC), Rv2270 (LppN) and Rv3763 (LpqH), and the possible biological activity of peptides derived from these. Five peptides were found for these proteins which had high specific binding to both alveolar A549 epithelial cells and U937 monocyte-derived macrophages which were able to significantly inhibit mycobacterial entry to these cells in vitro.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Peptides; Antibodies; antituberculosis vaccine; Cell Line, Tumor; Computational Biology; high activity binding peptide; Host-Pathogen Interactions; Lipoproteins; Microspheres; multi-epitope vaccine; Protein Binding; Protein Structure, Secondary; synthetic peptide

The Mycobacterium tuberculosis membrane protein Rv0180c: Evaluation of peptide sequences implicated in mycobacterial invasion of two human cell lines - Cáceres, Silvia Marcela; Ocampo, Marisol; Arévalo-Pinzón, Gabriela; Jimenez, Ronald Andrés; Patarroyo, Manuel Elkin; Patarroyo, Manuel Alfonso (Peptides, 2011)
The identification and characterization of hypothetical membrane proteins from Mycobacterium tuberculosis have led to a better understanding of the mechanisms used by this pathogen to invade and survive inside host cells. This study assessed the presence, transcription, localization and possible biological activity of the conserved hypothetical protein Rv0180c from M. tuberculosis. Bioinformatics analyses indicated that Rv0180c contains a signal peptide, six possible transmembrane helices and a Plasmodium Export Element (PEXEL)-like motif. PCR analyses showed the presence of the Rv0180c gene in strains from the M. tuberculosis complex; but transcription was not detected in Mycobacterium microti. Sera against synthetic peptides of Rv0180c recognized two protein bands in M. tuberculosis H37Rv sonicate: a ∼48-kDa band close to the predicted molecular mass of Rv0180c (47.6 kDa), and a 63-kDa band probably caused by protein modifications. Moreover, the same sera located the protein on the surface of M. tuberculosis H37Rv bacilli by immunoelectron microscopy. Twenty-three synthetic peptides spanning the entire length of Rv0180c were tested for their ability to bind to U937 and A549 cells, finding nine high-activity binding peptides (HABPs) specific for both cell types, two HABPs specific for A549 cells (namely 31032 and 31044) and two HABPs specific for U937 cells (namely 31025 and 31041). HABPs inhibited invasion of M. tuberculosis H37Rv into A549 or U937 cells by significant percentages and facilitated internalization of latex beads in A549 cells. The Rv0180c HABPs herein reported could be preliminary candidates to be assessed as components of a multiepitope, chemically synthesized, subunit-based vaccine against tuberculosis.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Circular Dichroism; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Microscopy, Immunoelectron; Peptides; Transcription, Genetic

Functional characterization of Mycobacterium tuberculosis Rv2969c membrane protein - Patarroyo, Manuel A.; Plaza, David F.; Ocampo, Marisol; Curtidor, Hernando; Forero, Martha; Rodriguez, Luis E.; Patarroyo, Manuel E. (Biochemical and Biophysical Research Communications, 2008)
Identifying Mycobacterium tuberculosis membrane proteins involved in binding to and invasion of host cells is important in designing subunit-based anti-tuberculosis vaccines. The Rv2969c gene sequence was identified by PCR in M. tuberculosis complex strains, being transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra, and M. bovis BCG. Rabbits immunized with synthetic peptides from highly specific conserved regions of this protein produced antibodies recognizing 27 and 29 kDa bands in M. tuberculosis lysate, which is consistent with the molecular weight of the Rv2969c gene product in M. tuberculosis H37Rv. Immunoelectron microscopy revealed the protein was localized on the bacillus surface. Four and three specific high activity binding peptides (HABPs) to the A549 alveolar epithelial and U937 monocyte cell lines were found, respectively. Two of the HABPs found inhibited M. tuberculosis invasion of A549 cells, suggesting that these peptides might be good candidates to be included in a multiepitopic, subunit-based anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Cell Line; Genes, Bacterial; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Tuberculosis Vaccines

Peptides derived from the Mycobacterium tuberculosis Rv1490 surface protein implicated in inhibition of epithelial cell entry: potential vaccine candidates? - Patarroyo, Manuel A.; Curtidor, Hernando; Plaza, David F.; Ocampo, Marisol; Reyes, Claudia; Saboya, Obeimar; Barrera, Gloria; Patarroyo, Manuel E. (Vaccine, 2008)
This study reports the Rv1490 gene presence and transcription in members of the Mycobacterium tuberculosis complex, and characterises the encoded Rv1490 putative membrane protein in M. tuberculosis H37Rv. Rv1490 derived peptides were synthesised and their A549 and U937 cell binding ability was tested, finding five high activity binding peptides (HABPs) for A549 and five for U937. Only two HABPs (11060 and 11073) were shared by both cell lines, both of which affected M. tuberculosis' invading ability to target cells, thus indicating an important role for these sequences in M. tuberculosis entry to A549 alveolar epithelial cells and supporting their inclusion in further studies on the development of a subunit-based multi-epitopic, chemically synthesised anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Peptides; Rabbits; Protein Binding; Bacterial Adhesion; Epithelial Cells; Microscopy, Electron, Transmission

Characterizing the Mycobacterium tuberculosis Rv2707 protein and determining its sequences which specifically bind to two human cell lines - Chapeton-Montes, Julie A.; Plaza, David F.; Curtidor, Hernando; Forero, Martha; Vanegas, Magnolia; Patarroyo, Manuel E.; Patarroyo, Manuel A. (Protein Science: A Publication of the Protein Society, 2008)
The Rv2707 gene encoding a putative alanine- and leucine-rich protein was found to be present in all Mycobacterium tuberculosis complex strains (by PCR) and its transcription was shown by RT-PCR in all but M. bovis and M. microti. Antibodies raised against Rv2707 peptides specifically recognized the native protein by Western blot and were able to locate this protein on the M. tuberculosis membrane by immunoelectron microscopy. A549 and U937 cells lines were used in binding assays involving synthetic peptides covering the whole Rv2707 protein. High A549 cell-binding peptide 16083 (281 QEEWPAPATHAHRLGNWLKAY 300) was identified. Peptides 16072 (61 LFGPDTLPAIEKSALSTAHSY 80) and 16084 (301 RIGVGTTTYSSTAQHSAVAA 320) presented high specific binding to both A549 and U937 cells. Cross-linking assays revealed that peptide 16084 specifically bound to a 40-kDa and a 50-kDa U937 cell membrane protein. High activity binding peptides (HABPs) 16083 and 16084 were able to inhibit M. tuberculosis invasion of A549 cells. Our results suggest that these sequences could be part of the binding sites used by the bacillus for interacting with target cells, and thus represent good candidates to be tested in a future subunit-based, multiepitope, antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Peptide Fragments; U937 Cells; Microscopy, Immunoelectron; Cell Line, Tumor; Computational Biology; Protein Binding

The Mycobacterium tuberculosis membrane protein Rv2560--biochemical and functional studies - Plaza, David F.; Curtidor, Hernando; Patarroyo, Manuel A.; Chapeton-Montes, Julie A.; Reyes, Claudia; Barreto, Jose; Patarroyo, Manuel E. (The FEBS journal, 2007)
The characterization of membrane proteins having no identified function in Mycobacterium tuberculosis is important for a better understanding of the biology of this pathogen. In this work, the biological activity of the Rv2560 protein was characterized and evaluated. Primers used in PCR and RT-PCR assays revealed that the gene encoding protein Rv2560 is present in M. tuberculosis complex strains, but transcribed in only some of them. Sera obtained from rabbits inoculated with polymer peptides from this protein recognized a 33 kDa band in the M. tuberculosis lysate and a membrane fraction corresponding to the predicted molecular mass (33.1 kDa) of this protein. Immunoelectron microscopy analysis found this protein on the mycobacterial membrane. Sixteen peptides covering its entire length were chemically synthesized and tested for their ability to bind to A549 and U937 cells. Peptide 11024 (121VVALSDRATTAYTNTSGVSS140) showed high specific binding to both cell types (dissociation constants of 380 and 800 nm, respectively, and positive receptor-ligand interaction cooperativity), whereas peptide 11033 (284LIGIPVAALIHVYTYRKLSGG304) displayed high binding activity to A549 cells only. Cross-linking assays showed the specific binding of peptide 11024 to a 54 kDa membrane protein on U937. Invasion inhibition assays, in the presence of shared high-activity binding peptide identified for U937 and A549 cells, presented maximum inhibition percentages of 50.53% and 58.27%, respectively. Our work highlights the relevance of the Rv2560 protein in the M. tuberculosis invasion process of monocytes and epithelial cells, and represents a fundamental step in the rational selection of new antigens to be included as components in a multiepitope, subunit-based, chemically synthesized, antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Circular Dichroism; DNA, Bacterial; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Animals; Microscopy, Immunoelectron; Rabbits; Cell Line, Tumor; Protein Binding; Blotting, Western; Sequence Analysis, Protein; Immune Sera; Flow Cytometry; Immunization; Polymerase Chain Reaction; Sequence Analysis, DNA; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

Mycobacterium tuberculosis Rv2536 protein implicated in specific binding to human cell lines - García, Javier; Puentes, Alvaro; Rodríguez, Luis; Ocampo, Marisol; Curtidor, Hernando; Vera, Ricardo; Lopez, Ramses; Valbuena, John; Cortes, Jimena; Vanegas, Magnolia; Barrero, Carlos; Patarroyo, Manuel A.; et al. (Protein Science: A Publication of the Protein Society, 2005)
The gene encoding the Mycobacterium tuberculosis Rv2536 protein is present in the Mycobacterium tuberculosis complex (as assayed by PCR) and transcribed (as determined by RT-PCR) in M. tuberculosis H37Rv, M. tuberculosis H37Ra, M. bovis BCG, and M. africanum strains. Rabbits immunized with synthetic polymer peptides from this protein produced antibodies specifically recognizing a 25-kDa band in mycobacterial sonicate. U937 and A549 cells were used in binding assays involving 20-amino-acid-long synthetic peptides covering the whole Rv2536 protein sequence. Peptide 11207 (161DVFSAVRADDSPTGEMQVAQY180) presented high specific binding to both types of cells; the binding was saturable and presented nanomolar affinity constants. Cross-linking assays revealed that this peptide specifically binds to 50 kDa U937 cell membrane and 45 kDa A549 cell membrane proteins.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Cell Line; Circular Dichroism; Cross-Linking Reagents; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Animals; Rabbits; Gene Expression Regulation, Bacterial; Immune Sera

Peptides derived from Mycobacterium tuberculosis Rv2301 protein are involved in invasion to human epithelial cells and macrophages - Ocampo, M.; Rodríguez, D. M.; Curtidor, H.; Vanegas, M.; Patarroyo, M. A.; Patarroyo, M. E. (Amino Acids, 2012)
The specific function of putative cut2 protein (or CFP25), encoded by the Rv2301 gene from Mycobacterium tuberculosis H37Rv, has not been identified yet. The aim of this study was to assess some of CFP25 characteristics and its possible biological role in Mycobacterium tuberculosis H37Rv invasion process to target cells. Molecular assays indicated that the gene encoding Rv2301 is present and transcribed in M. tuberculosis complex strains. The presence of Rv2301 protein over the bacilli surface was confirmed by Western blot and immunoelectron microscopy analyses, using goats sera inoculated with synthetic peptides derived from Rv2301 protein. Receptor-ligand binding assays with carcinomic human alveolar basal epithelial cells (A549) and macrophages derived from human histolytic lymphoma monocytes (U937) allowed us to identify five high activity binding peptides (HABPs) in both cell lines, and two additional HABPs only in A549 cells. U937 HABPs binding interactions were characterized by saturation assays, finding dissociation constants (Kd) within the nanomolar range and positive cooperativity (nH>1). Inhibition assays were performed to assess the possible biological role of Rv2301 identified HABPs, finding that some of them were able to inhibit invasion at a 5 μM concentration, compared with the cytochalasin control. On the other hand, HABPs, and especially HABP 36507 located at the N-terminus of the protein, facilitated the internalization of fluorescent latex beads into A549 cells. These findings are of vital importance for the rational selection of Rv2301 HABPs, to be included as components of an antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Binding Sites; Humans; Kinetics; Molecular Sequence Data; Mycobacterium tuberculosis; Microscopy, Immunoelectron; Peptides; Cell Line, Tumor; Protein Binding; Antigens, Bacterial; Epithelial Cells; Macrophages; Blotting, Western; Cytochalasins; Organ Specificity; Tuberculosis, Pulmonary

The role of Mycobacterium tuberculosis Rv3166c protein-derived high-activity binding peptides in inhibiting invasion of human cell lines - Ocampo, Marisol; Aristizábal-Ramírez, Daniel; Rodríguez, Diana M.; Muñoz, Marina; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Protein engineering, design & selection: PEDS, 2012)
Given the urgent need for designing a new antituberculosis vaccine conferring total protection on patients of all ages, following the line of research adopted by our institute, this work has identified Mycobacterium tuberculosis (Mtb) Rv3166c protein high-activity binding peptides (HABPs) which are able to inhibit bacterial invasion of U937 (monocyte-derived macrophages) and A549 (type II alveolar epithelial cells) cell lines. The presence and transcription of the rv3166c gene in the Mtb species complex was confirmed by polymerase chain reaction (PCR) and reverse transcriptase-PCR; Rv3166c expression was evaluated by western blot and cellular localisation confirmed by immunoelectron microscopy. Its presence was mainly determined on cell surface. Sixteen peptides covering its entire length were chemically synthesised and tested for their ability to bind to U937 and A549 cells. Two U937 HABPs were identified and three for A549, one of them being shared by both cell lines. The four HABPs found inhibited Mtb entry by 15.07-94.06%. These results led us to including Rv3166c HABPs as candidates for further studies contributing towards the search for a multiepitope, chemically synthesised, subunit-based antituberculosis vaccine.
Keywords: Antibodies, Bacterial; Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; U937 Cells; Animals; Microscopy, Immunoelectron; Rabbits; Tuberculosis Vaccines; Macrophages; Pulmonary Alveoli

Identifying putative Mycobacterium tuberculosis Rv2004c protein sequences that bind specifically to U937 macrophages and A549 epithelial cells - Forero, Martha; Puentes, Alvaro; Cortés, Jimena; Castillo, Fabio; Vera, Ricardo; Rodríguez, Luis E.; Valbuena, John; Ocampo, Marisol; Curtidor, Hernando; Rosas, Jaiver; García, Javier; Barrera, Gloria; et al. (Protein Science: A Publication of the Protein Society, 2005)
Virulence and immunity are still poorly understood in Mycobacterium tuberculosis. The H37Rv M. tuberculosis laboratory strain genome has been completely sequenced, and this along with proteomic technology represent powerful tools contributing toward studying the biology of target cell interaction with a facultative bacillus and designing new strategies for controlling tuberculosis. Rv2004c is a putative M. tuberculosis protein that could have specific mycobacterial functions. This study has revealed that the encoding gene is present in all mycobacterium species belonging to the M. tuberculosis complex. Rv2004c gene transcription was observed in all of this complex's strains except Mycobacterium bovis and Mycobacterium microti. Rv2004c protein expression was confirmed by using antibodies able to recognize a 54-kDa molecule by immunoblotting, and its location was detected on the M. tuberculosis surface by transmission electron microscopy, suggesting that it is a mycobacterial surface protein. Binding assays led to recognizing high activity binding peptides (HABP); five HABPs specifically bound to U937 cells, and six specifically bound to A549 cells. HABP circular dichroism suggested that they had an alpha-helical structure. HABP-target cell interaction was determined to be specific and saturable; some of them also displayed greater affinity for A549 cells than U937 cells. The critical amino acids directly involved in their interaction with U937 cells were also determined. Two probable receptor molecules were found on U937 cells and five on A549 for the two HABPs analyzed. These observations have important biological significance for studying bacillus-target cell interactions and implications for developing strategies for controlling this disease.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Binding Sites; Cell Line; Circular Dichroism; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Peptides; Epithelial Cells; Macrophages; Receptors, Cell Surface; Reverse Transcriptase Polymerase Chain Reaction; Cell Wall; Sequence Analysis, Protein

Peptides from the Mycobacterium tuberculosis Rv1980c protein involved in human cell infection: insights into new synthetic subunit vaccine candidates - Rodríguez, Diana; Vizcaíno, Carolina; Ocampo, Marisol; Curtidor, Hernando; Pinto, Marta; Elkin Patarroyo, Manuel; Alfonso Patarroyo, Manuel (Biological Chemistry, 2010)
Mycobacterium tuberculosis infection continues to be a major cause of morbidity and mortality throughout the world. The vast complexity of the intracellular pathogen M. tuberculosis and the diverse mechanisms by which it can invade host cells highlight the importance of developing a fully protective vaccine. Our vaccine development strategy consists of including fragments from multiple mycobacterial proteins involved in cell invasion. The aim of this study was to identify high activity binding peptides (HABPs) in the immunogenic protein Rv1980c from M. tuberculosis H37Rv with the ability to inhibit mycobacterial invasion into U937 monocyte-derived macrophages and A549 cells. The presence and transcription of the Rv1980c gene was assessed in members belonging to the M. tuberculosis complex and other nontuberculous mycobacteria by PCR and RT-PCR, respectively. Cell surface localization was confirmed by immuno-electron microscopy. Three peptides binding with high activity to U937 cells and one to A549 cells were identified. HABPs 31100, 31101, and 31107 inhibited invasion of M. tuberculosis into A549 and U937 cells and therefore could be promising candidates for the design of a subunit-based antituberculous vaccine.
Keywords: Bacterial Proteins; Binding Sites; Humans; Mycobacterium tuberculosis; Peptide Fragments; Blotting, Western; Models, Molecular; Transcription, Genetic; Vaccines, Synthetic; Bacterial Vaccines; Alveolar Epithelial Cells; Cells, Cultured

Peptides derived from the Mycobacterium tuberculosis Rv1490 surface protein implicated in inhibition of epithelial cell entry: potential vaccine candidates? - Patarroyo, Manuel A.; Curtidor, Hernando; Plaza, David F.; Ocampo, Marisol; Reyes, Claudia; Saboya, Obeimar; Barrera, Gloria; Patarroyo, Manuel E. (Vaccine, 2008)
This study reports the Rv1490 gene presence and transcription in members of the Mycobacterium tuberculosis complex, and characterises the encoded Rv1490 putative membrane protein in M. tuberculosis H37Rv. Rv1490 derived peptides were synthesised and their A549 and U937 cell binding ability was tested, finding five high activity binding peptides (HABPs) for A549 and five for U937. Only two HABPs (11060 and 11073) were shared by both cell lines, both of which affected M. tuberculosis' invading ability to target cells, thus indicating an important role for these sequences in M. tuberculosis entry to A549 alveolar epithelial cells and supporting their inclusion in further studies on the development of a subunit-based multi-epitopic, chemically synthesised anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Peptides; Rabbits; Protein Binding; Bacterial Adhesion; Epithelial Cells; Microscopy, Electron, Transmission

Computational prediction and experimental assessment of secreted/surface proteins from Mycobacterium tuberculosis H37Rv - Vizcaíno, Carolina; Restrepo-Montoya, Daniel; Rodríguez, Diana; Niño, Luis F.; Ocampo, Marisol; Vanegas, Magnolia; Reguero, María T.; Martínez, Nora L.; Patarroyo, Manuel E.; Patarroyo, Manuel A. (PLoS computational biology, 2010)
The mycobacterial cell envelope has been implicated in the pathogenicity of tuberculosis and therefore has been a prime target for the identification and characterization of surface proteins with potential application in drug and vaccine development. In this study, the genome of Mycobacterium tuberculosis H37Rv was screened using Machine Learning tools that included feature-based predictors, general localizers and transmembrane topology predictors to identify proteins that are potentially secreted to the surface of M. tuberculosis, or to the extracellular milieu through different secretory pathways. The subcellular localization of a set of 8 hypothetically secreted/surface candidate proteins was experimentally assessed by cellular fractionation and immunoelectron microscopy (IEM) to determine the reliability of the computational methodology proposed here, using 4 secreted/surface proteins with experimental confirmation as positive controls and 2 cytoplasmic proteins as negative controls. Subcellular fractionation and IEM studies provided evidence that the candidate proteins Rv0403c, Rv3630, Rv1022, Rv0835, Rv0361 and Rv0178 are secreted either to the mycobacterial surface or to the extracellular milieu. Surface localization was also confirmed for the positive controls, whereas negative controls were located on the cytoplasm. Based on statistical learning methods, we obtained computational subcellular localization predictions that were experimentally assessed and allowed us to construct a computational protocol with experimental support that allowed us to identify a new set of secreted/surface proteins as potential vaccine candidates.
Keywords: Antibodies, Bacterial; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Computational Biology; Epitopes, B-Lymphocyte; Bacterial Outer Membrane Proteins; Artificial Intelligence; Cell Fractionation; Electrophoresis, Polyacrylamide Gel; Escherichia coli; Immunoblotting; Models, Statistical; Mycobacterium smegmatis; Sonication; Subcellular Fractions

Mycobacterium tuberculosis surface protein Rv0227c contains high activity binding peptides which inhibit cell invasion - Rodríguez, Diana Marcela; Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel Elkin; Patarroyo, Manuel Alfonso (Peptides, 2012)
Mycobacterium tuberculosis surface proteins involved in target cell invasion may be identified as a strategy for developing subunit-based, chemically-synthesized vaccines. The Rv0227c protein was thus selected to assess its role in the invasion and infection of Mycobacterium tuberculosis target cells. Results revealed Rv0227c localization on mycobacterial surface by immunoelectron microscopy and Western blot. Receptor-ligand assays using 20-mer, non-overlapping peptides covering the complete Rv0227c protein sequence revealed three high activity binding peptides for U937 phagocytic cells and seven for A549 cells. Peptide 16944 significantly inhibited mycobacterial entry to both cell lines while 16943 and 16949 only managed to inhibit entrance to U937 cells and 16951 to A549 cells. The Jnet bioinformatics tool predicted secondary structure elements for the complete protein, agreeing with elements determined for such chemically-synthesized peptides. It was thus concluded that high activity binding peptides which were able to inhibit mycobacterial entry to target cells are of great importance when selecting peptide candidates for inclusion in an anti-tuberculosis vaccine.
Keywords: Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; U937 Cells; Microscopy, Immunoelectron; Peptides; Blotting, Western; Bacterial Vaccines; Cell Survival; Dose-Response Relationship, Drug; Reverse Transcriptase Polymerase Chain Reaction; Structure-Activity Relationship; Tumor Cells, Cultured

The Mycobacterium tuberculosis membrane protein Rv0180c: Evaluation of peptide sequences implicated in mycobacterial invasion of two human cell lines - Cáceres, Silvia Marcela; Ocampo, Marisol; Arévalo-Pinzón, Gabriela; Jimenez, Ronald Andrés; Patarroyo, Manuel Elkin; Patarroyo, Manuel Alfonso (Peptides, 2011)
The identification and characterization of hypothetical membrane proteins from Mycobacterium tuberculosis have led to a better understanding of the mechanisms used by this pathogen to invade and survive inside host cells. This study assessed the presence, transcription, localization and possible biological activity of the conserved hypothetical protein Rv0180c from M. tuberculosis. Bioinformatics analyses indicated that Rv0180c contains a signal peptide, six possible transmembrane helices and a Plasmodium Export Element (PEXEL)-like motif. PCR analyses showed the presence of the Rv0180c gene in strains from the M. tuberculosis complex; but transcription was not detected in Mycobacterium microti. Sera against synthetic peptides of Rv0180c recognized two protein bands in M. tuberculosis H37Rv sonicate: a ∼48-kDa band close to the predicted molecular mass of Rv0180c (47.6 kDa), and a 63-kDa band probably caused by protein modifications. Moreover, the same sera located the protein on the surface of M. tuberculosis H37Rv bacilli by immunoelectron microscopy. Twenty-three synthetic peptides spanning the entire length of Rv0180c were tested for their ability to bind to U937 and A549 cells, finding nine high-activity binding peptides (HABPs) specific for both cell types, two HABPs specific for A549 cells (namely 31032 and 31044) and two HABPs specific for U937 cells (namely 31025 and 31041). HABPs inhibited invasion of M. tuberculosis H37Rv into A549 or U937 cells by significant percentages and facilitated internalization of latex beads in A549 cells. The Rv0180c HABPs herein reported could be preliminary candidates to be assessed as components of a multiepitope, chemically synthesized, subunit-based vaccine against tuberculosis.
Keywords: Amino Acid Sequence; Bacterial Proteins; Cell Line; Circular Dichroism; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Microscopy, Immunoelectron; Peptides; Transcription, Genetic

Mycobacterium tuberculosis PE9 protein has high activity binding peptides which inhibit target cell invasion - Díaz, Diana P.; Ocampo, Marisol; Pabón, Laura; Herrera, Chonny; Patarroyo, Manuel A.; Munoz, Marina; Patarroyo, Manuel E. (International Journal of Biological Macromolecules, 2016)
PE/PPE proteins are involved in several processes during Mycobacterium tuberculosis (Mtb) infection of target cells; studying them is extremely interesting as they are the only ones from the Mycobacterium genus, they abound in pathogenic species such as Mtb and their function remains yet unknown. The PE9 protein (Rv1088) was characterised, the rv1088 gene was identified by PCR in Mtb complex strains and its expression and localisation on mycobacterial surface was confirmed by Western blot and immunoelectron microscopy. Bioinformatics tools were used for predicting PE9 protein structural aspects and experimental study involved the circular dichroism of synthetic peptides. The peptides were tested in binding assays involving U937 and A549 cells; two high activity binding peptides (HABPs) were found for both cell lines (39226-(1)MSYMIATPAALTAAATDIDGI(21) and 39232-(125)YQRHFGTGGQPEFRQHSEHRR(144)), one for U937 (39231-(104)YAGAGRRQRRRRSGDGQWRLRQ(124)) and one for A549 (39230-(83)YGTGVFRRRRGRQTVTAAEHRA(103)). HABP 39232 inhibited mycobacterial entry to A549 cells (∼70%) and U937 cells (∼50%), peptides 39226 and 39231 inhibited entry to U937 cells (∼60% and 80%, respectively) and peptide 39230 inhibited entry to A549 cells (∼60%). This emphasised HABPs' functional importance in recognition between Mtb H37Rv and target cell receptors. These peptide sequences could be involved in invasion and were recognised by the host's immune system, thereby highlighting their use when designing an efficient anti-tuberculosis multiantigenic vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Mycobacterium tuberculosis; Peptides; Computational Biology; Protein Binding; Epithelial Cells; Macrophages; Tuberculosis; Models, Molecular; Transcription, Genetic; A549 Cells; Synthetic peptide; Protein Conformation; PE9 protein; Protein Transport; Substrate Specificity

Rv1268c protein peptide inhibiting Mycobacterium tuberculosis H37Rv entry to target cells - Ocampo, Marisol; Rodríguez, Deisy Carolina; Rodríguez, Jorge; Bermúdez, Maritza; Muñoz, Claudia Marina; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Bioorganic & Medicinal Chemistry, 2013)
Tuberculosis (TB) remains one of the most worrying infectious diseases affecting public health around the world; 8.7 million new TB cases were reported in 2011. The search for an Mycobacterium tuberculosis H37Rv protein sequence which is functionally important in host-pathogen interaction has been proposed for developing a new vaccine which will allow efficient and safe control of the spread of this disease. The present study thus reports the results obtained for the Rv1268c protein described in the M. tuberculosis H37Rv genome as a hypothetical unknown, probably secreted, protein based on a highly robust, specific, sensitive and functional approach to the search for potential epitopes to be included in an anti-tuberculosis vaccine. Rv1268c presence was determined by immunoblotting after obtaining polyclonal sera against mycobacterial total sonicate or subcellular fractions. Such sera were used in electron immunomicroscopy (EIM) for confirming protein localisation on the M. tuberculosis envelop by recognising colloidal gold-labelled immunoglobulin. Screening assays revealed the presence of two sequences having high binding activity: one binding A549 alveolar epithelial cells ((141)TGMAALEQYLGSGHAVIVSI(160)) and other binding U937 monocyte-derived macrophages ((21)AVALGLASPADAAAGTMYGD(40)). Such sequences' ability to inhibit mycobacterial entry during in vitro assays was analysed. The structure of synthetic peptides binding to target cells was also determined, bearing in mind the structure-function relationship. These results, together with those obtained for other proteins, have been involved in selecting peptides which might be included in a subunit-based anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Circular Dichroism; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Peptides; Rabbits; Cell Line, Tumor; Host-Pathogen Interactions; Anti-tuberculosis vaccine; Entry inhibition; Gold; Immunoglobulins; Receptor–ligand interaction; Recombinant Proteins; Rv1268c; Sub-cellular localization; Synthetic peptides; Target cell

Validating subcellular localization prediction tools with mycobacterial proteins - Restrepo-Montoya, Daniel; Vizcaíno, Carolina; Niño, Luis F.; Ocampo, Marisol; Patarroyo, Manuel E.; Patarroyo, Manuel A. (BMC bioinformatics, 2009)
BACKGROUND: The computational prediction of mycobacterial proteins' subcellular localization is of key importance for proteome annotation and for the identification of new drug targets and vaccine candidates. Several subcellular localization classifiers have been developed over the past few years, which have comprised both general localization and feature-based classifiers. Here, we have validated the ability of different bioinformatics approaches, through the use of SignalP 2.0, TatP 1.0, LipoP 1.0, Phobius, PA-SUB 2.5, PSORTb v.2.0.4 and Gpos-PLoc, to predict secreted bacterial proteins. These computational tools were compared in terms of sensitivity, specificity and Matthew's correlation coefficient (MCC) using a set of mycobacterial proteins having less than 40% identity, none of which are included in the training data sets of the validated tools and whose subcellular localization have been experimentally confirmed. These proteins belong to the TBpred training data set, a computational tool specifically designed to predict mycobacterial proteins. RESULTS: A final validation set of 272 mycobacterial proteins was obtained from the initial set of 852 mycobacterial proteins. According to the results of the validation metrics, all tools presented specificity above 0.90, while dispersion sensitivity and MCC values were above 0.22. PA-SUB 2.5 presented the highest values; however, these results might be biased due to the methodology used by this tool. PSORTb v.2.0.4 left 56 proteins out of the classification, while Gpos-PLoc left just one protein out. CONCLUSION: Both subcellular localization approaches had high predictive specificity and high recognition of true negatives for the tested data set. Among those tools whose predictions are not based on homology searches against SWISS-PROT, Gpos-PLoc was the general localization tool with the best predictive performance, while SignalP 2.0 was the best tool among the ones using a feature-based approach. Even though PA-SUB 2.5 presented the highest metrics, it should be taken into account that this tool was trained using all proteins reported in SWISS-PROT, which includes the protein set tested in this study, either as a BLAST search or as a training model.
Keywords: Bacterial Proteins; Computational Biology; Algorithms; Databases, Protein; Mycobacterium; Software

Mce4F Mycobacterium tuberculosis protein peptides can inhibit invasion of human cell lines - Rodríguez, Deisy Carolina; Ocampo, Marisol; Varela, Yahson; Curtidor, Hernando; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Pathogens and Disease, 2015)
This work was aimed at studying the Mycobacterium tuberculosis H37Rv Rv3494c protein, taking into account that it belongs to the mammalian cell entry family (mce) which is thought to have important functions in the disease's pathogenesis. The protein was characterized in silico; its presence on mycobacterial surface was confirmed by immunoelectron microscopy. High-activity binding peptides (HABPs) were identified by binding assays with (125)I; their ability to inhibit mycobacterial entry to two cell lines (U937 alveolar macrophages and A549 epithelial cells) was ascertained and their role in bacterial entry was confirmed by fluorescent microsphere internalization assay. This protein's predicted alpha-helix structure was confirmed by circular dichroism of its peptides. All HABPs inhibited mycobacterial entry to cells and that the 38379 peptide ((201)IDQAGPFLQAQIRAGGDIKSY(220)) had high binding ability and inhibited the mycobacterial entry to both cell lines assayed here. Rv3494c peptides 38370 ((21)LSVMAIFYLRLPATFGIGTY(40)), 38373 ((81)HMRLNSGTAIPSNVTATVRSY(100)) and 38379 ((201)IDQAGPFLQAQIRAGGDIKSY(220)) showed to be HABP and inhibited mycobacterial entry to A549 cells and peptide 38382 ((261)RPSFPALAASLANLGRVGVIY(280)) bind to U937 and inhibited the mycobacterial entry to this cell line; all of these sequences play an important role in cell line recognition and invasion, and may thus be considered in the search for prophylactic candidates against tuberculosis.
Keywords: Cell Line; Circular Dichroism; Humans; Membrane Proteins; Mycobacterium tuberculosis; Microscopy, Immunoelectron; Protein Binding; Antigens, Bacterial; Epithelial Cells; Macrophages; Anti-Bacterial Agents; Mycobacterium tuberculosis H37Rv; Biological Products; Endocytosis; HABP; inhibition and invasion assay; Protein Conformation; Rv3494c protein; tuberculosis

Identifying and characterising PPE7 (Rv0354c) high activity binding peptides and their role in inhibiting cell invasion - Díaz, Diana P.; Ocampo, Marisol; Varela, Yahson; Curtidor, Hernando; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Molecular and Cellular Biochemistry, 2017)
This study was aimed at characterising the PPE7 protein from the PE/PPE protein family. The presence and transcription of the rv0354c gene in the Mycobacterium tuberculosis complex was determined and the subcellular localisation of the PPE7 protein on mycobacterial membrane was confirmed by immunoelectron microscope. Two peptides were identified as having high binding activity (HABPs) and were tested in vitro regarding the invasion of Mycobacterium tuberculosis H37Rv. HABP 39224 inhibited invasion in A549 epithelial cells and U937 macrophages by more than 50%, whilst HABP 39225 inhibited invasion by 40% in U937 cells. HABP 39224, located in the protein's C-terminal region, has a completely conserved amino acid sequence in M. tuberculosis complex species and could be selected as a base peptide when designing a subunit-based, anti-tuberculosis vaccine.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; U937 Cells; Tuberculosis Vaccines; A549 Cells; Cell Membrane; High activity binding peptide; Mycobacterium tuberculosis H37Rv; PPE7 protein; Synthetic peptide

Towards designing a synthetic antituberculosis vaccine: The Rv3587c peptide inhibits mycobacterial entry to host cells - Carabali-Isajar, Mary Lilian; Ocampo, Marisol; Rodriguez, Deisy Carolina; Vanegas, Magnolia; Curtidor, Hernando; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Bioorganic & Medicinal Chemistry, 2018)
Mycobacterium tuberculosis is considered one of the most successful pathogens in the history of mankind, having caused 1.7 million deaths in 2016. The amount of resistant and extensively resistant strains has increased; BCG has been the only vaccine to be produced in more than 100 years though it is still unable to prevent the disease's most disseminated form in adults; pulmonary tuberculosis. The search is thus still on-going for candidate antigens for an antituberculosis vaccine. This paper reports the use of a logical and rational methodology for finding such antigens, this time as peptides derived from the Rv3587c membrane protein. Bioinformatics tools were used for predicting mycobacterial surface location and Rv3587c protein structure whilst circular dichroism was used for determining its peptides' secondary structure. Receptor-ligand assays identified 4 high activity binding peptides (HABPs) binding specifically to A549 alveolar epithelial cells and U937 monocyte-derived macrophages, covering the region between amino acids 116 and 193. Their capability for inhibiting Mtb H37Rv invasion was evaluated. The recognition of antibodies from individuals suffering active and latent tuberculosis and from healthy individuals was observed in HABPs capable of avoiding mycobacterial entry to host cells. The results showed that 8 HABPs inhibited such invasion, two of them being common for both cell lines: 39265 (155VLAAYVYSLDNKRLWSNLDT173) and 39266 (174APSNETLVKTFSPGEQVTTY192). Peptide 39265 was the least recognised by antibodies from the individuals' sera evaluated in each group. According to the model proposed by FIDIC regarding synthetic vaccine development, peptide 39265 has become a candidate antigen for an antituberculosis vaccine.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; Peptide Fragments; Tuberculosis Vaccines; Cell Line, Tumor; Computational Biology; Host-Pathogen Interactions; Protein Structure, Secondary; Antigens, Bacterial; HABPs; Bioinformatics; Drug Design; Invasion assay; Protein Structure, Tertiary; Receptors, Cell Surface; Rv3587c; Vaccine; Vaccines, Synthetic

Cell-Peptide Specific Interaction Can Inhibit Mycobacterium tuberculosis H37Rv Infection - Rodríguez, Deisy Carolina; Ocampo, Marisol; Reyes, Cesar; Arévalo-Pinzón, Gabriela; Munoz, Marina; Patarroyo, Manuel Alfonso; Patarroyo, Manuel Elkin (Journal of Cellular Biochemistry, 2016)
Studying proteins from the M. tuberculosis H37Rv envelop is important for understanding host-pathogen interaction regarding bacterial infection and survival within a host; such knowledge is indispensable regarding studies aimed at developing drugs or vaccines against tuberculosis, a disease which continues to cause more than one million deaths worldwide every year. The present work presents a study of the Rv3705c protein which has been described as being an outer protein. Several servers and bioinformatics' tools were used for predicting its location on mycobacterial surface and a 3D model of the protein was obtained which was then compared to experimental circular dichroism results for its peptides. PCR assays were used for corroborating rv3705c gene presence and transcription in a laboratory strain and immunoblotting and electron microscopy were used for confirming protein localisation on cell envelop. Receptor-ligand assays revealed two peptides having high specific binding (HABPs); peptide 38485 ((121)DRAFHRVVDRTVGTSGQTTA(140)) bound to both cell lines used as infection target (U937 and A549 epithelial cell line-derived macrophages) and 38488 ((181)RLRENVLLQAKVTQSGNAGP(200)) bound to U937 cells. It was found that peptide 38485 provided significant inhibition regarding mycobacterial entry to both cell lines in in vitro assays. These results led to proposing peptide 38485 as one of the epitopes to be used in future studies aimed at characterising the immune response of functionally important synthetic peptides which could be included in developing a synthetic anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Peptides; Cell Line, Tumor; Host-Pathogen Interactions; Protein Binding; Protein Structure, Secondary; Antigens, Bacterial; Epithelial Cells; Macrophages; Anti-Bacterial Agents; Bacterial Outer Membrane Proteins; BIOINFORMATICS; Cell Differentiation; CIRCULAR DICHROISM; Gene Expression; HIGH ACTIVITY BINDING PEPTIDE (HABP); INHIBITION ASSAY; Models, Molecular; RECEPTOR-LIGAND ASSAY; Transcription, Genetic

Mycobacterium tuberculosis Rv0679c protein sequences involved in host-cell infection: potential TB vaccine candidate antigen - Cifuentes, Diana P.; Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Forero, Martha; Patarroyo, Manuel E.; Patarroyo, Manuel A. (BMC microbiology, 2010)
BACKGROUND: To date, the function of many hypothetical membrane proteins of Mycobacterium tuberculosis is still unknown and their involvement in pathogen-host interactions has not been yet clearly defined. In this study, the biological activity of peptides derived from the hypothetical membrane protein Rv0679c of M. tuberculosis and their involvement in pathogen-host interactions was assessed. Transcription of the Rv0679c gene was studied in 26 Mycobacterium spp. Strains. Antibodies raised against putative B-cell epitopes of Rv0679c were used in Western blot and immunoelectron microscopy assays. Synthetic peptides spanning the entire length of the protein were tested for their ability to bind to A549 and U937 cells. High-activity binding peptides (HABPs) identified in Rv0679c were tested for their ability to inhibit mycobacterial invasion into cells. RESULTS: The gene encoding Rv0679c was detected in all strains of the M. tuberculosis complex (MTC), but was only transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra and M. africanum. Anti-Rv0679c antibodies specifically recognized the protein in M. tuberculosis H37Rv sonicate and showed its localization on mycobacterial surface. Four HABPs inhibited invasion of M. tuberculosis to target cells by up to 75%. CONCLUSIONS: The results indicate that Rv0679c HABPs and in particular HABP 30979 could be playing an important role during M. tuberculosis invasion of host cells, and therefore could be interesting research targets for studies aimed at developing strategies to control tuberculosis.
Keywords: Antibodies, Bacterial; Bacterial Proteins; Cell Line; Humans; Mycobacterium tuberculosis; Microscopy, Immunoelectron; Tuberculosis Vaccines; Host-Pathogen Interactions; Protein Binding; Antigens, Bacterial; Epithelial Cells; Blotting, Western; Epitopes, B-Lymphocyte; Gene Expression Profiling; Monocytes; Virulence Factors

Antibodies targeting Mycobacterium tuberculosis peptides inhibit mycobacterial entry to infection target cells - Carabali-Isajar, Mary L.; Ocampo, Marisol; Varela, Yahson; Díaz-Arévalo, Diana; Patarroyo, Manuel A.; Patarroyo, Manuel E. (International Journal of Biological Macromolecules, 2020)
The humoral immunity regarding tuberculosis can contribute towards controlling the mycobacteria and the disease. Antigens mediating such type of immunity should thus be evaluated for formulating anti-tuberculosis vaccines. The antigen recognition of seven peptides derived from proteins on Mtb H37Rv envelope and a further seven peptides modified from them was evaluated in sera taken from people suffering Mtb infection and others free from it. Peptide sequences' ability to inhibit Mtb entry to human macrophages was determined in vitro and, after isolating peptide-specific IgG antibodies, it was ascertained which ones were exercising such inhibitory function. Aotus were inoculated with the modified peptides for evaluating the activity of the antibodies so produced. Human QTF+ and QTF- sera recognised some of the peptides and inhibited Mtb entry. The same effect was seen with peptide-specific IgG regarding all the native sequences and modified ones. Sera taken from inoculated Aotus was also able to reduce the pathogen's entry. The data showed that some peptides evaluated in this study could induce antibodies able to inhibit the pathogen's entry to human macrophages, i.e. they could represent candidates for part of an anti-tuberculosis vaccine. The methodology used here complements the evaluation of promising antigens for designing effective vaccines.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; U937 Cells; Animals; Peptides; Antibodies; Macrophages; Aotidae; HABPs; Immunoglobulin G; Inhibition assay; Tuberculosis; Vacccine

Functional, biochemical and 3D studies of Mycobacterium tuberculosis protein peptides for an effective anti-tuberculosis vaccine - Ocampo, Marisol; Patarroyo, Manuel A.; Vanegas, Magnolia; Alba, Martha P.; Patarroyo, Manuel E. (Critical Reviews in Microbiology, 2014)
Tuberculosis (TB) is an air-born, transmissible disease, having an estimated 9.4 million new TB cases worldwide in 2009. Eventual control of this disease by developing a safe and efficient new vaccine able to detain its spread will have an enormous impact on public health policy. Selecting potential antigens to be included in a multi-epitope, minimal subunit-based, chemically-synthesized vaccine containing the minimum sequences needed for blocking mycobacterial interaction with host cells is a complex task due to the multiple mechanisms involved in M. tuberculosis infection and the mycobacterium's immune evasion mechanisms. Our methodology, described here takes into account a highly robust, specific, sensitive and functional approach to the search for potential epitopes to be included in an anti-TB vaccine; it has been based on identifying short mycobacterial protein fragments using synthetic peptides having high affinity interaction with alveolar epithelial cells (A549) and monocyte-derived macrophages (U937) which are able to block the microorganism's entry to target cells in in vitro assays. This manuscript presents a review of the results obtained with some of the MTB H37Rv proteins studied to date, aimed at using these high activity binding peptides (HABPs) as platforms to be included in a minimal subunit-based, multiepitope, chemically-synthesized, antituberculosis vaccine.
Keywords: Bacterial Proteins; Cell Line; Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Antigens, Bacterial; Bacterial Adhesion; Epithelial Cells; Macrophages

Specific interaction between Mycobacterium tuberculosis lipoprotein-derived peptides and target cells inhibits mycobacterial entry in vitro - Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Chemical Biology & Drug Design, 2014)
Tuberculosis (TB) continues being one of the diseases having the greatest mortality rates around the world, 8.7 million cases having been reported in 2011. An efficient vaccine against TB having a great impact on public health is an urgent need. Usually, selecting antigens for vaccines has been based on proteins having immunogenic properties for patients suffering TB and having had promising results in mice and non-human primates. Our approach has been based on a functional approach involving the pathogen-host interaction in the search for antigens to be included in designing an efficient, minimal, subunit-based anti-TB vaccine. This means that Mycobacterium tuberculosis has mainly been involved in studies and that lipoproteins represent an important kind of protein on the cell envelope which can also contribute towards this pathogen's virulence. This study has assessed the expression of four lipoproteins from M. tuberculosis H37Rv, that is, Rv1411c (LprG), Rv1911c (LppC), Rv2270 (LppN) and Rv3763 (LpqH), and the possible biological activity of peptides derived from these. Five peptides were found for these proteins which had high specific binding to both alveolar A549 epithelial cells and U937 monocyte-derived macrophages which were able to significantly inhibit mycobacterial entry to these cells in vitro.
Keywords: Amino Acid Sequence; Bacterial Proteins; Humans; Molecular Sequence Data; Mycobacterium tuberculosis; U937 Cells; Peptides; Antibodies; antituberculosis vaccine; Cell Line, Tumor; Computational Biology; high activity binding peptide; Host-Pathogen Interactions; Lipoproteins; Microspheres; multi-epitope vaccine; Protein Binding; Protein Structure, Secondary; synthetic peptide

Functional characterization of Mycobacterium tuberculosis Rv2969c membrane protein - Patarroyo, Manuel A.; Plaza, David F.; Ocampo, Marisol; Curtidor, Hernando; Forero, Martha; Rodriguez, Luis E.; Patarroyo, Manuel E. (Biochemical and Biophysical Research Communications, 2008)
Identifying Mycobacterium tuberculosis membrane proteins involved in binding to and invasion of host cells is important in designing subunit-based anti-tuberculosis vaccines. The Rv2969c gene sequence was identified by PCR in M. tuberculosis complex strains, being transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra, and M. bovis BCG. Rabbits immunized with synthetic peptides from highly specific conserved regions of this protein produced antibodies recognizing 27 and 29 kDa bands in M. tuberculosis lysate, which is consistent with the molecular weight of the Rv2969c gene product in M. tuberculosis H37Rv. Immunoelectron microscopy revealed the protein was localized on the bacillus surface. Four and three specific high activity binding peptides (HABPs) to the A549 alveolar epithelial and U937 monocyte cell lines were found, respectively. Two of the HABPs found inhibited M. tuberculosis invasion of A549 cells, suggesting that these peptides might be good candidates to be included in a multiepitopic, subunit-based anti-tuberculosis vaccine.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Cell Line; Genes, Bacterial; Humans; Membrane Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Tuberculosis Vaccines

Mycobacterium tuberculosis Rv0679c protein sequences involved in host-cell infection: Potential TB vaccine candidate antigen - Cifuentes, Diana P; Ocampo, Marisol; Curtidor, Hernando; Vanegas, Magnolia; Forero, Martha; Patarroyo, Manuel E; Patarroyo, Manuel A (BMC Microbiology, 2010)
Background To date, the function of many hypothetical membrane proteins of Mycobacterium tuberculosis is still unknown and their involvement in pathogen-host interactions has not been yet clearly defined. In this study, the biological activity of peptides derived from the hypothetical membrane protein Rv0679c of M. tuberculosis and their involvement in pathogen-host interactions was assessed. Transcription of the Rv0679c gene was studied in 26 Mycobacterium spp. Strains. Antibodies raised against putative B-cell epitopes of Rv0679c were used in Western blot and immunoelectron microscopy assays. Synthetic peptides spanning the entire length of the protein were tested for their ability to bind to A549 and U937 cells. High-activity binding peptides (HABPs) identified in Rv0679c were tested for their ability to inhibit mycobacterial invasion into cells. Results The gene encoding Rv0679c was detected in all strains of the M. tuberculosis complex (MTC), but was only transcribed in M. tuberculosis H37Rv, M. tuberculosis H37Ra and M. africanum. Anti-Rv0679c antibodies specifically recognized the protein in M. tuberculosis H37Rv sonicate and showed its localization on mycobacterial surface. Four HABPs inhibited invasion of M. tuberculosis to target cells by up to 75%. Conclusions The results indicate that Rv0679c HABPs and in particular HABP 30979 could be playing an important role during M. tuberculosis invasion of host cells, and therefore could be interesting research targets for studies aimed at developing strategies to control tuberculosis.

Characterizing the Mycobacterium tuberculosis Rv2707 protein and determining its sequences which specifically bind to two human cell lines - Chapeton-Montes, Julie A.; Plaza, David F.; Curtidor, Hernando; Forero, Martha; Vanegas, Magnolia; Patarroyo, Manuel E.; Patarroyo, Manuel A. (Protein Science : A Publication of the Protein Society, 2008)
The Rv2707 gene encoding a putative alanine- and leucine-rich protein was found to be present in all Mycobacterium tuberculosis complex strains (by PCR) and its transcription was shown by RT-PCR in all but M. bovis and M. microti. Antibodies raised against Rv2707 peptides specifically recognized the native protein by Western blot and were able to locate this protein on the M. tuberculosis membrane by immunoelectron microscopy. A549 and U937 cells lines were used in binding assays involving synthetic peptides covering the whole Rv2707 protein. High A549 cell-binding peptide 16083 (281QEEWPAPATHAHRLGNWLKAY300) was identified. Peptides 16072 (61LFGPDTLPAIEKSALSTAHSY80) and 16084 (301RIGVGTTTYSSTAQHSAVAA320) presented high specific binding to both A549 and U937 cells. Cross-linking assays revealed that peptide 16084 specifically bound to a 40-kDa and a 50-kDa U937 cell membrane protein. High activity binding peptides (HABPs) 16083 and 16084 were able to inhibit M. tuberculosis invasion of A549 cells. Our results suggest that these sequences could be part of the binding sites used by the bacillus for interacting with target cells, and thus represent good candidates to be tested in a future subunit-based, multiepitope, antituberculosis vaccine.

Characterising Mycobacterium tuberculosis Rv1510c protein and determining its sequences that specifically bind to two target cell lines - Vera-Bravo, Ricardo; Torres, Elizabeth; Valbuena, John J.; Ocampo, Marisol; Rodríguez, Luis E.; Puentes, Alvaro; García, Javier E.; Curtidor, Hernando; Cortés, Jimena; Vanegas, Magnolia; Rivera, Zuly J.; Díaz, Andrea; et al. (Biochemical and Biophysical Research Communications, 2005)
The process of Mycobacterium tuberculosis infection of the macrophage implies a very little-known initial recognition and adherence step, important for mycobacterial survival; many proteins even remain like hypothetical. The Rv1510c gene, encoding a putatively conserved membrane protein, was investigated by analysing the M. tuberculosis genome sequence data reported by Cole et al. and a previous report that used PCR assays to show that the Rv1510 gene was only present in M. tuberculosis. This article confirmed all the above and identified the transcribed gene in M. tuberculosis, Mycobacterium africanum, and in M. tuberculosis clinical isolates. Antibodies raised against peptides from this protein recognised a 44 kDa band, corresponding to Rv1510c theoretical mass (44,294 Da). Assays involving synthetic peptides covering the whole protein binding to U937 and A549 cell lines led to recognising five high activity binding peptides in the Rv1510 protein: 11094, 11095, 11105, 11108, and 11111. Their affinity constants and Hill coefficients were determined by using U937 cells. Cross-linking assays performed with some of these HABPs showed that they specifically bound to a U937 cell line 51 kDa protein, but not to Hep G2 or red blood cell proteins, showing this interaction's specificity.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Base Sequence; Binding Sites; Cell Line; Circular Dichroism; Cross-Linking Reagents; DNA, Bacterial; Genes, Bacterial; Humans; Kinetics; Membrane Proteins; Molecular Sequence Data; Molecular Weight; Mycobacterium tuberculosis; Peptide Fragments; U937 Cells

Identifying putative Mycobacterium tuberculosis Rv2004c protein sequences that bind specifically to U937 macrophages and A549 epithelial cells - Forero, Martha; Puentes, Álvaro; Cortés, Jimena; Castillo, Fabio; Vera, Ricardo; Rodríguez, Luis E.; Valbuena, John; Ocampo, Marisol; Curtidor, Hernando; Rosas, Jaiver; García, Javier; Barrera, Gloria; et al. (Protein Science : A Publication of the Protein Society, 2005)
Virulence and immunity are still poorly understood in Mycobacterium tuberculosis. The H37Rv M. tuberculosis laboratory strain genome has been completely sequenced, and this along with proteomic technology represent powerful tools contributing toward studying the biology of target cell interaction with a facultative bacillus and designing new strategies for controlling tuberculosis. Rv2004c is a putative M. tuberculosis protein that could have specific mycobacterial functions. This study has revealed that the encoding gene is present in all mycobacterium species belonging to the M. tuberculosis complex. Rv2004c gene transcription was observed in all of this complex’s strains except Mycobacterium bovis and Mycobacterium microti. Rv2004c protein expression was confirmed by using antibodies able to recognize a 54-kDa molecule by immunoblotting, and its location was detected on the M. tuberculosis surface by transmission electron microscopy, suggesting that it is a mycobacterial surface protein. Binding assays led to recognizing high activity binding peptides (HABP); five HABPs specifically bound to U937 cells, and six specifically bound to A549 cells. HABP circular dichroism suggested that they had an α-helical structure. HABP–target cell interaction was determined to be specific and saturable; some of them also displayed greater affinity for A549 cells than U937 cells. The critical amino acids directly involved in their interaction with U937 cells were also determined. Two probable receptor molecules were found on U937 cells and five on A549 for the two HABPs analyzed. These observations have important biological significance for studying bacillus–target cell interactions and implications for developing strategies for controlling this disease.

Mycobacterium tuberculosis Rv2536 protein implicated in specific binding to human cell lines - García, Javier; Puentes, Alvaro; Rodríguez, Luis; Ocampo, Marisol; Curtidor, Hernando; Vera, Ricardo; Lopez, Ramses; Valbuena, John; Cortes, Jimena; Vanegas, Magnolia; Barrero, Carlos; Patarroyo, Manuel A.; et al. (Protein Science : A Publication of the Protein Society, 2005)
The gene encoding the Mycobacterium tuberculosis Rv2536 protein is present in the Mycobacterium tuberculosis complex (as assayed by PCR) and transcribed (as determined by RT-PCR) in M. tuberculosis H37Rv, M. tuberculosis H37Ra, M. bovis BCG, and M. africanum strains. Rabbits immunized with synthetic polymer peptides from this protein produced antibodies specifically recognizing a 25-kDa band in mycobacterial sonicate. U937 and A549 cells were used in binding assays involving 20-amino-acid-long synthetic peptides covering the whole Rv2536 protein sequence. Peptide 11207 (161DVFSAVRADDSPTGEMQVAQY180) presented high specific binding to both types of cells; the binding was saturable and presented nanomolar affinity constants. Cross-linking assays revealed that this peptide specifically binds to 50 kDa U937 cell membrane and 45 kDa A549 cell membrane proteins.

Prospects in Mycobacterium bovis Bacille Calmette et Guérin (BCG) Vaccine Diversity and Delivery: Why does BCG fail to protect against Tuberculosis? - Moliva, Juan I.; Turner, Joanne; Torrelles, Jordi B. (Vaccine, 2015)
Mycobacterium tuberculosis (M.tb) infection leads to active tuberculosis (TB), a disease that kills one human every 18 seconds. Current therapies available to combat TB include chemotherapy and the preventative vaccine Mycobacterium bovis Bacille Calmette et Guérin (BCG). Increased reporting of drug resistant M.tb strains worldwide indicates that drug development cannot be the primary mechanism for eradication. BCG vaccination has been used globally for protection against childhood and disseminated TB, however, its efficacy at protecting against pulmonary TB in adult and aging populations is highly variable. In this regard, the immune response generated by BCG vaccination is incapable of sterilizing the lung post M.tb infection as indicated by the large proportion of individuals with latent TB infection that have received BCG. Although many new TB vaccine candidates have entered the development pipeline, only a few have moved to human clinical trials; where they showed no efficacy and/or were withdrawn due to safety regulations. These trials highlight our limited understanding of protective immunity against the development of active TB. Here, we discuss current vaccination strategies and their impact on the generation and sustainability of protective immunity against TB.

Global Tuberculosis Report 2022
Global Tuberculosis Report 2022

Tuberculosis vaccination needs to avoid 'decoy' immune reactions - Ivanyi, Juraj (Tuberculosis (Edinburgh, Scotland), 2021)
Current search for a new effective vaccine against tuberculosis involves selected antigens, vectors and adjuvants. These are being evaluated usually by their booster inoculation following priming with Bacillus Calmette-Guerin. The purpose of this article is to point out, that despite being attenuated of virulence, priming with BCG may still involve immune mechanisms, which are not favourable for protection against active disease. It is postulated, that the responsible 'decoy' constituents selected during the evolution of pathogenic tubercle bacilli may be involved in the evasion from bactericidal host resistance and stimulate immune responses of a cytokine phenotype, which lead to the transition from latent closed granulomas to reactivation with infectious lung cavities. The decoy mechanisms appear as favourable for most infected subjects but leading in a minority of cases to pathology which can effectively transmit the infection. It is proposed that construction and development of new vaccine candidates could benefit from avoiding decoy-type immune mechanisms.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Vaccination; Immunology; Pathogenesis

Mechanisms of M. tuberculosis Immune Evasion as Challenges to TB Vaccine Design - Ernst, Joel D. (Cell Host & Microbe, 2018)
Tuberculosis (TB) is a large global health problem, in part because of the long period of coevolution of the pathogen, Mycobacterium tuberculosis, and its human host. A major factor that sustains the global epidemic of TB is the lack of a sufficiently effective vaccine. While basic mechanisms of immunity that protect against TB have been identified, attempts to improve immunity to TB by vaccination have been disappointing. This Review discusses the mechanisms used by M. tuberculosis to evade innate and adaptive immunity and that likely limit the efficacy of vaccines developed to date. Despite multiple mechanisms of immune evasion, recent trials have indicated that effective TB vaccines remain an attainable goal. This Review discusses how knowledge from other systems can inform improvements on current vaccine approaches.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; BCG Vaccine; Granuloma; Adaptive Immunity; Immunity, Innate; T-Lymphocytes; Vaccines, Attenuated; Immune Evasion; Clinical Trials as Topic

Mycobacterium tuberculosis GroEL2 Modulates Dendritic Cell Responses - Georgieva, Maria; Sia, Jonathan Kevin; Bizzell, Erica; Madan-Lala, Ranjna; Rengarajan, Jyothi (Infection and Immunity, 2018)
Mycobacterium tuberculosis successfully subverts the host immune response to promote disease progression. In addition to its known intracellular niche in macrophages, M. tuberculosis interferes with the functions of dendritic cells (DCs), which are the primary antigen-presenting cells of the immune system. We previously showed that M. tuberculosis dampens proinflammatory responses and impairs DC functions through the cell envelope-associated serine protease Hip1. Here we present data showing that M. tuberculosis GroEL2, a substrate of Hip1, modulates DC functions. The full-length GroEL2 protein elicited robust proinflammatory responses from DCs and promoted DC maturation and antigen presentation to T cells. In contrast, the cleaved form of GroEL2, which predominates in M. tuberculosis, was poorly immunostimulatory and was unable to promote DC maturation and antigen presentation. Moreover, DCs exposed to full-length, but not cleaved, GroEL2 induced strong antigen-specific gamma interferon (IFN-γ), interleukin-2 (IL-2), and IL-17A cytokine responses from CD4+ T cells. Moreover, the expression of cleaved GroEL2 in the hip1 mutant restored the robust T cell responses to wild-type levels, suggesting that proteolytic cleavage of GroEL2 allows M. tuberculosis to prevent optimal DC-T cell cross talk during M. tuberculosis infection.
Keywords: Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Tuberculosis; Disease Models, Animal; Cytokines; Mice, Inbred C57BL; Dendritic Cells; Immune Evasion; Chaperonin 60; dendritic cells; Proteolysis

Mycobacterium tuberculosis Exploits a Molecular Off Switch of the Immune System for Intracellular Survival - von Both, Ulrich; Berk, Maurice; Agapow, Paul-Michael; Wright, Joseph D.; Git, Anna; Hamilton, Melissa Shea; Goldgof, Greg; Siddiqui, Nazneen; Bellos, Evangelos; Wright, Victoria J.; Coin, Lachlan J.; Newton, Sandra M.; et al. (Scientific Reports, 2018)
Mycobacterium tuberculosis (M. tuberculosis) survives and multiplies inside human macrophages by subversion of immune mechanisms. Although these immune evasion strategies are well characterised functionally, the underlying molecular mechanisms are poorly understood. Here we show that during infection of human whole blood with M. tuberculosis, host gene transcriptional suppression, rather than activation, is the predominant response. Spatial, temporal and functional characterisation of repressed genes revealed their involvement in pathogen sensing and phagocytosis, degradation within the phagolysosome and antigen processing and presentation. To identify mechanisms underlying suppression of multiple immune genes we undertook epigenetic analyses. We identified significantly differentially expressed microRNAs with known targets in suppressed genes. In addition, after searching regions upstream of the start of transcription of suppressed genes for common sequence motifs, we discovered novel enriched composite sequence patterns, which corresponded to Alu repeat elements, transposable elements known to have wide ranging influences on gene expression. Our findings suggest that to survive within infected cells, mycobacteria exploit a complex immune "molecular off switch" controlled by both microRNAs and Alu regulatory elements.
Keywords: Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Tuberculosis; Gene Expression Profiling; Female; Adult; Male; Middle Aged; Gene Expression Regulation; Immunity; Oligonucleotide Array Sequence Analysis; MicroRNAs; Alu Elements; Epigenesis, Genetic

Mycobacterium tuberculosis Membrane Vesicles Inhibit T Cell Activation - Athman, Jaffre J.; Sande, Obondo J.; Groft, Sarah G.; Reba, Scott M.; Nagy, Nancy; Wearsch, Pamela A.; Richardson, Edward T.; Rojas, Roxana; Boom, W. Henry; Shukla, Supriya; Harding, Clifford V. (Journal of Immunology (Baltimore, Md.: 1950), 2017)
Mycobacterium tuberculosis utilizes multiple mechanisms to evade host immune responses, and inhibition of effector CD4+ T cell responses by M. tuberculosis may contribute to immune evasion. TCR signaling is inhibited by M. tuberculosis cell envelope lipoglycans, such as lipoarabinomannan and lipomannan, but a mechanism for lipoglycans to traffic from M. tuberculosis within infected macrophages to reach T cells is unknown. In these studies, we found that membrane vesicles produced by M. tuberculosis and released from infected macrophages inhibited the activation of CD4+ T cells, as indicated by reduced production of IL-2 and reduced T cell proliferation. Flow cytometry and Western blot demonstrated that lipoglycans from M. tuberculosis-derived bacterial vesicles (BVs) are transferred to T cells, where they inhibit T cell responses. Stimulation of CD4+ T cells in the presence of BVs induced expression of GRAIL, a marker of T cell anergy; upon restimulation, these T cells showed reduced ability to proliferate, confirming a state of T cell anergy. Furthermore, lipoarabinomannan was associated with T cells after their incubation with infected macrophages in vitro and when T cells were isolated from lungs of M. tuberculosis-infected mice, confirming the occurrence of lipoarabinomannan trafficking to T cells in vivo. These studies demonstrate a novel mechanism for the direct regulation of CD4+ T cells by M. tuberculosis lipoglycans conveyed by BVs that are produced by M. tuberculosis and released from infected macrophages. These lipoglycans are transferred to T cells to inhibit T cell responses, providing a mechanism that may promote immune evasion.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis; Cells, Cultured; Mice; Female; Lung; CD4-Positive T-Lymphocytes; Mice, Inbred C57BL; Lymphocyte Activation; Immune Evasion; Lipopolysaccharides; Clonal Anergy; Cell Proliferation; Secretory Vesicles

Macrophage-microbe interaction: lessons learned from the pathogen Mycobacterium tuberculosis - BoseDasgupta, Somdeb; Pieters, Jean (Seminars in Immunopathology, 2018)
Macrophages, being the cornerstone of the immune system, have adapted the ancient nutrient acquisition mechanism of phagocytosis to engulf various infectious organisms thereby helping to orchestrate an appropriate host response. Phagocytosis refers to the process of internalization and degradation of particulate material, damaged and senescent cells and microorganisms by specialized cells, after which the vesicle containing the ingested particle, the phagosome, matures into acidic phagolysosomes upon fusion with hydrolytic enzyme-containing lysosomes. The destructive power of the macrophage is further exacerbated through the induction of macrophage activation upon a variety of inflammatory stimuli. Despite being the end-point for many phagocytosed microbes, the macrophage can also serve as an intracellular survival niche for a number of intracellular microorganisms. One microbe that is particularly successful at surviving within macrophages is the pathogen Mycobacterium tuberculosis, which can efficiently manipulate the macrophage at several levels, including modulation of the phagocytic pathway as well as interfering with a number of immune activation pathways that normally would lead to eradication of the internalized bacilli. M. tuberculosis excels at circumventing destruction within macrophages, thus establishing itself successfully for prolonged times within the macrophage. In this contribution, we describe a number of general features of macrophages in the context of their function to clear an infection, and highlight the strategies employed by M. tuberculosis to counter macrophage attack. Interestingly, research on the evasion tactics employed by M. tuberculosis within macrophages not only helps to design strategies to curb tuberculosis, but also allows a better understanding of host cell biology.
Keywords: Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Macrophages; Tuberculosis; Organ Specificity; Cytokines; T-Lymphocytes; Macrophage Activation; Phagocytosis; Phagosomes; Inflammation; Proteasome Endopeptidase Complex; Pathogens

Mycobacterium tuberculosis associated with severe tuberculosis evades cytosolic surveillance systems and modulates IL-1β production - Sousa, Jeremy; Cá, Baltazar; Maceiras, Ana Raquel; Simões-Costa, Luisa; Fonseca, Kaori L.; Fernandes, Ana Isabel; Ramos, Angélica; Carvalho, Teresa; Barros, Leandro; Magalhães, Carlos; Chiner-Oms, Álvaro; Machado, Henrique; et al. (Nature Communications, 2020)
Genetic diversity of Mycobacterium tuberculosis affects immune responses and clinical outcomes of tuberculosis (TB). However, how bacterial diversity orchestrates immune responses to direct distinct TB severities is unknown. Here we study 681 patients with pulmonary TB and show that M. tuberculosis isolates from cases with mild disease consistently induce robust cytokine responses in macrophages across multiple donors. By contrast, bacteria from patients with severe TB do not do so. Secretion of IL-1β is a good surrogate of the differences observed, and thus to classify strains as probable drivers of different TB severities. Furthermore, we demonstrate that M. tuberculosis isolates that induce low levels of IL-1β production can evade macrophage cytosolic surveillance systems, including cGAS and the inflammasome. Isolates exhibiting this evasion strategy carry candidate mutations, generating sigA recognition boxes or affecting components of the ESX-1 secretion system. Therefore, we provide evidence that M. tuberculosis strains manipulate host-pathogen interactions to drive variable TB severities.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Animals; Macrophages; Cells, Cultured; Tuberculosis, Pulmonary; Mice; Female; Genome, Bacterial; Virulence; Cytokines; Immunomodulation; Male; Signal Transduction; Phylogeny; Immune Evasion; Cytosol; Inflammasomes; Interleukin-1beta; Mutation; Polymorphism, Single Nucleotide

Fighting Persistence: How Chronic Infections with Mycobacterium tuberculosis Evade T Cell-Mediated Clearance and New Strategies To Defeat Them - Ankley, Laurisa; Thomas, Sean; Olive, Andrew J. (Infection and Immunity, 2020)
Chronic bacterial infections are caused by pathogens that persist within their hosts and avoid clearance by the immune system. Treatment and/or detection of such pathogens is difficult, and the resulting pathologies are often deleterious or fatal. There is an urgent need to develop protective vaccines and host-directed therapies that synergize with antibiotics to prevent pathogen persistence and infection-associated pathologies. However, many persistent pathogens, such as Mycobacterium tuberculosis, actively target the very host pathways activated by vaccination. These immune evasion tactics blunt the effectiveness of immunization strategies and are impeding progress to control these infections throughout the world. Therefore, it is essential that M. tuberculosis immune evasion-related pathogen virulence strategies are considered to maximize the effectiveness of potential new treatments. In this review, we focus on how Mycobacterium tuberculosis infects antigen-presenting cells and evades effective immune clearance by the adaptive response through (i) manipulating antigen presentation, (ii) repressing T cell-activating costimulatory molecules, and (iii) inducing ligands that drive T cell exhaustion. In this context, we will examine the challenges that bacterial virulence strategies pose to developing new vaccines. We will then discuss new approaches that will help dissect M. tuberculosis immune evasion mechanisms and devise strategies to bypass them to promote long-term protection and prevent disease progression.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Tuberculosis; T-Lymphocytes; Antigen Presentation; Phagocytosis; Phagosomes; Immune Evasion; Antigen-Presenting Cells; immune evasion; intracellular pathogens; T cell; vaccine development

Mycobacterium tuberculosis cords within lymphatic endothelial cells to evade host immunity - Lerner, Thomas R.; Queval, Christophe J.; Lai, Rachel P.; Russell, Matthew Rg; Fearns, Antony; Greenwood, Daniel J.; Collinson, Lucy; Wilkinson, Robert J.; Gutierrez, Maximiliano G. (JCI insight, 2020)
The ability of Mycobacterium tuberculosis to form serpentine cords is intrinsically related to its virulence, but specifically how M. tuberculosis cording contributes to pathogenesis remains obscure. Here, we show that several M. tuberculosis clinical isolates form intracellular cords in primary human lymphatic endothelial cells (hLECs) in vitro and in the lymph nodes of patients with tuberculosis. We identified via RNA-Seq a transcriptional program that activated, in infected-hLECs, cell survival and cytosolic surveillance of pathogens pathways. Consistent with this, cytosolic access was required for intracellular M. tuberculosis cording. Mycobacteria lacking ESX-1 type VII secretion system or phthiocerol dimycocerosates expression, which failed to access the cytosol, were indeed unable to form cords within hLECs. Finally, we show that M. tuberculosis cording is a size-dependent mechanism used by the pathogen to avoid its recognition by cytosolic sensors and evade either resting or IFN-γ-induced hLEC immunity. These results explain the long-standing association between M. tuberculosis cording and virulence and how virulent mycobacteria use intracellular cording as strategy to successfully adapt and persist in the lymphatic tracts.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Virulence Factors; Cells, Cultured; Interferon-gamma; Immune Evasion; Infectious disease; Bacterial infections; Endothelial Cells; Lymph; Lysosomes; RNA-Seq; Vascular Biology

Effects of Mycobacterium tuberculosis Rv1096 on mycobacterial cell division and modulation on macrophages - Deng, Guoying; Ji, Na; Shi, Xiaoxia; Zhang, Wenli; Qin, Yuanhua; Sha, Shanshan; Yang, Shufeng; Ma, Yufang (Microbial Pathogenesis, 2020)
Mycobacterium tuberculosis is capable of escaping the clearance of immune system mainly due to its complex constituents of cell wall. Certain studies show that glycoproteins are involved in immune evasion and act as virulence factors. Peptidoglycan deacetylase Rv1096 is a member of mannosylated proteins. Previously, we reported Rv1096 protein contributed to the resistance of Mycobacterium smegmatis (M. smegmatis) to lysozyme, but more characterization of this protein is required where further intracellular function is unknown. Here, Rv1096 was heterologously over-expressed in the fast-growing and nonpathogenic M. smegmatis (named as M. smegmatis/Rv1096). We observed the morphological alterations in M. smegmatis/Rv1096 including an elongated rod-like shape and increased amounts of Z-rings, which implied that Rv1096 facilitated the cell growth and division. Moreover, a series of assays concerning the interaction between M. smegmatis/Rv1096 and host were carried out. The results showed that M. smegmatis/Rv1096 evaded the killing of macrophages due to the inhibition of phagosome-lysosome fusion, nicotinamide adenine dinucleotide phosphate oxidase activity and reactive oxygen species production. The secretion of interleukin-12 and tumor necrosis factor-α was also impaired by Rv1096. In addition, five putative interaction partners of Rv1096 were identified, which possibly cooperated with Rv1096 in cell division and immune regulation. These results suggested that Rv1096 had effects on mycobacterial division and might act as a virulence factor to mediate the immune evasion in macrophage during mycobacterial infection.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Host-Pathogen Interactions; Macrophages; Virulence Factors; Mycobacterium smegmatis; Cell Wall; Immune evasion; Microbial Viability; Immune Evasion; Cell Division; Peptidoglycan; Mycobacterium Infections; Reactive Oxygen Species; Interleukin-12; Tumor Necrosis Factor-alpha; Cell division; Histone Deacetylases; Macrophage; Rv1096

Identification of a Mycobacterium tuberculosis Cyclic Dinucleotide Phosphodiesterase Inhibitor - Karanja, Caroline W.; Yeboah, Kofi S.; Sintim, Herman O. (ACS infectious diseases, 2021)
Immune cells sense bacteria-derived c-di-GMP and c-di-AMP as well as host-derived cGAMP, which is synthesized by cGAS upon binding to the pathogen's DNA, to mount an immunological response (cytokine production) via the STING-TBK1 pathway. Successful pathogens, such as Mycobacterium tuberculosis and group B streptococcus, harbor phosphodiesterases (PDEs) that can cleave bacterial c-di-AMP as well as host-derived cGAMP to blunt the host's response to infection. Selective inhibitors of bacterial cyclic dinucleotide (CDN) PDEs are needed as tool compounds to study the role(s) of CDN PDEs during infection and they could also become bona fide antivirulence compounds, but there is a paucity of such compounds. Using a high-throughput assay, we identified six inhibitors of MTB CDN PDE (CdnP). The most potent inhibitor, C82 with an IC50 of ∼18 μM, did not inhibit the enzymatic activities of three other bacterial CDN PDEs (Yybt, RocR, and GBS-CdnP), a viral CDN PDE (poxin) or mammalian ENPP1.
Keywords: Mycobacterium tuberculosis; Animals; innate immune system; antivirulence therapy; cyclic dinucleotide; MTB immune evasion; MTB phosphodiesterases (CdnP); Nucleotidyltransferases; Phosphodiesterase Inhibitors; Streptococcus agalactiae

Several Routes to the Same Destination: Inhibition of Phagosome-Lysosome Fusion by Mycobacterium tuberculosis - Carranza, Claudia; Chavez-Galan, Leslie (The American Journal of the Medical Sciences, 2019)
Phagocytosis is necessary for antigen degradation and presentation, the activation of the adaptive immune response and the elimination of pathogenic micro-organisms. The phagosomal vacuole formed during phagocytosis requires a process of maturation that involves fusion with lysosomes, a decrease in luminal pH and the activation of the enzymes that eventually will destroy phagocytized micro-organisms. Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. This agent has developed various strategies to prevent phagosome maturation and persist indefinitely in latency mode. Herein, we review these strategies in the light of available experimental evidence. A better understanding of them may be essential in the development of more effective therapies against tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Adaptive Immunity; Phagocytosis; Phagosomes; Immune Evasion; Lysosomes; Evasion mechanism; Inhibition of phagosome-lysosome fusion

Editorial: The Autophagy Pathway: Bacterial Pathogen Immunity and Evasion - Jagannath, Chinnaswamy; McBride, Jere W.; Vergne, Isabelle (Frontiers in Immunology, 2021)
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Signal Transduction; Immune Evasion; Autophagy; autophagy; Bacteria; Staphylococcus aureus; Listeria monocytogenes; Bacterial Infections; Anaplasmataceae; host-directed therapies; immunometabolism; Salmonella typhimurium

Secretory proteins of Mycobacterium tuberculosis and their roles in modulation of host immune responses: focus on therapeutic targets - Pal, Ravi; Bisht, Manoj Kumar; Mukhopadhyay, Sangita (The FEBS journal, 2022)
Mycobacterium tuberculosis, the bacterium responsible for tuberculosis, is one of the most successful pathogens in human history. An extremely resilient cell wall and highly evolved and coordinated strategies for immune evasion have made it a very formidable pathogen. The secretory proteins of M. tuberculosis play a crucial role in its virulence and immune evasion. The secretory proteins are secreted through tightly regulated secretion systems and modulate the host immune responses through a plethora of strategies, including epigenetic reprogramming of infected cells, targeting antigen presentation, inhibition of phagosomal maturation, modulation of cytokine production, apoptosis and redox regulation, etc. Upon infection, the secretory proteins become localized into various cellular organelles, such as nucleus, cytoplasm, phagosomes and Golgi, bodies and hijack the host machineries through their wide gamut of functions, including kinase, phosphatase, methyl transferase activities and interaction with several host partners. In this review, we discuss the secretion systems, the functions of various secretory proteins of M. tuberculosis and their roles in modulating immune responses of the host. We also discuss the feasibility of their use as possible therapeutic targets. This information is likely to improve our understanding of the host-pathogen interaction and help in the design of effective anti-tuberculosis therapeutics.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Macrophages; Tuberculosis; Phagosomes; Immunity; host-pathogen interaction; modulation of immune responses; secretion system; secretory proteins; therapeutics

Host-Directed Therapies for Tuberculosis - Jeong, Eui-Kwon; Lee, Hyo-Ji; Jung, Yu-Jin (Pathogens (Basel, Switzerland), 2022)
Tuberculosis (TB) is one of the leading causes of death worldwide, consistently threatening public health. Conventional tuberculosis treatment requires a long-term treatment regimen and is associated with side effects. The efficacy of antitubercular drugs has decreased with the emergence of drug-resistant TB; therefore, the development of new TB treatment strategies is urgently needed. In this context, we present host-directed therapy (HDT) as an alternative to current tuberculosis therapy. Unlike antitubercular drugs that directly target Mycobacterium tuberculosis (Mtb), the causative agent of TB, HDT is an approach for treating TB that appropriately modulates host immune responses. HDT primarily aims to enhance the antimicrobial activity of the host in order to control Mtb infection and attenuate excessive inflammation in order to minimize tissue damage. Recently, research based on the repositioning of drugs for use in HDT has been in progress. Based on the overall immune responses against Mtb infection and the immune-evasion mechanisms of Mtb, this review examines the repositioned drugs available for HDT and their mechanisms of action.
Keywords: Mycobacterium tuberculosis; tuberculosis; host-directed therapy; drug repositioning

Manipulation and exploitation of host immune system by pathogenic Mycobacterium tuberculosis for its advantage - Mir, Manzoor A.; Mir, Bilkees; Kumawat, Manoj; Alkhanani, Mustfa; Jan, Ulfat (Future Microbiology, 2022)
Mycobacterium tuberculosis (Mtb) can become a long-term infection by evading the host immune response. Coevolution of Mtb with humans has resulted in its ability to hijack the host's immune systems in a variety of ways. So far, every Mtb defense strategy is essentially dependent on a subtle balance that, if shifted, can promote Mtb proliferation in the host, resulting in disease progression. In this review, the authors summarize many important and previously unknown mechanisms by which Mtb evades the host immune response. Besides recently found strategies by which Mtb manipulates the host molecular regulatory machinery of innate and adaptive immunity, including the intranuclear regulatory machinery, costimulatory molecules, the ubiquitin system and cellular intrinsic immune components will be discussed. A holistic understanding of these immune-evasion mechanisms is of foremost importance for the prevention, diagnosis and treatment of tuberculosis and will lead to new insights into tuberculosis pathogenesis and the development of more effective vaccines and treatment regimens.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; tuberculosis; Adaptive Immunity; Immunity, Innate; innate immunity; autophagy; Immune System; drug resistance; immune evasion; costimulation

Mycobacterium tuberculosis Rv1987 protein induces M2 polarization of macrophages through activating the PI3K/Akt1/mTOR signaling pathway - Sha, Shanshan; Shi, Yang; Tang, Yawei; Jia, Liqiu; Han, Xiuyan; Liu, Yuxin; Li, Xia; Ma, Yufang (Immunology and Cell Biology, 2021)
Mycobacterium tuberculosis (Mtb) can subvert host immune responses and survive in macrophages. Specific Mtb antigens play a critical role in this process. Rv1987, a secretory protein encoded by the gene rv1987 in the region of difference-2 (RD2) of the Mtb genome, is specifically expressed in pathogenic mycobacteria. Our previous work proved that Rv1987 induced a Th2 response in mice and enhanced mycobacterial survival in mouse lungs, but its effect on macrophages, the most important effector immune cell involved in killing Mtb, remains unclear. In this study, we used an M. smegmatis strain overexpressing Rv1987 protein to infect alveolar macrophages and the macrophage cell line RAW264.7 and analyzed the effect of Rv1987 protein on macrophage polarization. Rv1987 induced M2 polarization in macrophages both in vivo and in vitro. The bactericidal ability of these M2 polarized macrophages decreased remarkably, which resulted in the increased survival of bacteria in macrophages. Proteomics, RT-qPCR and western blotting results revealed that the PI3K/Akt1/mTOR signaling pathway was activated in Rv1987-induced M2 macrophages. Meanwhile, the SHIP molecule, a negative regulator of the PI3K/Akt1/mTOR signaling pathway, was significantly downregulated. These results suggest that Rv1987 plays an important role in modulating the host immune response and could be established as a potential drug target.
Keywords: Mycobacterium tuberculosis; Animals; Macrophages; Mice; Signal Transduction; Phosphatidylinositol 3-Kinases; immune evasion; Macrophage; M2 polarization; signaling transduction; TOR Serine-Threonine Kinases

Host immunity increases Mycobacterium tuberculosis reliance on cytochrome bd oxidase - Cai, Yi; Jaecklein, Eleni; Mackenzie, Jared S.; Papavinasasundaram, Kadamba; Olive, Andrew J.; Chen, Xinchun; Steyn, Adrie J. C.; Sassetti, Christopher M. (PLoS pathogens, 2021)
In order to sustain a persistent infection, Mycobacterium tuberculosis (Mtb) must adapt to a changing environment that is shaped by the developing immune response. This necessity to adapt is evident in the flexibility of many aspects of Mtb metabolism, including a respiratory chain that consists of two distinct terminal cytochrome oxidase complexes. Under the conditions tested thus far, the bc1/aa3 complex appears to play a dominant role, while the alternative bd oxidase is largely redundant. However, the presence of two terminal oxidases in this obligate pathogen implies that respiratory requirements might change during infection. We report that the cytochrome bd oxidase is specifically required for resisting the adaptive immune response. While the bd oxidase was dispensable for growth in resting macrophages and the establishment of infection in mice, this complex was necessary for optimal fitness after the initiation of adaptive immunity. This requirement was dependent on lymphocyte-derived interferon gamma (IFNγ), but did not involve nitrogen and oxygen radicals that are known to inhibit respiration in other contexts. Instead, we found that ΔcydA mutants were hypersusceptible to the low pH encountered in IFNγ-activated macrophages. Unlike wild type Mtb, cytochrome bd-deficient bacteria were unable to sustain a maximal oxygen consumption rate (OCR) at low pH, indicating that the remaining cytochrome bc1/aa3 complex is preferentially inhibited under acidic conditions. Consistent with this model, the potency of the cytochrome bc1/aa3 inhibitor, Q203, is dramatically enhanced at low pH. This work identifies a critical interaction between host immunity and pathogen respiration that influences both the progression of the infection and the efficacy of potential new TB drugs.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis; Mice; Immune Evasion; Adaptation, Physiological; Electron Transport Complex IV

Mycobacterium tuberculosis Rv3034c regulates mTORC1 and PPAR-γ dependant pexophagy mechanism to control redox levels in macrophages - Ganguli, Geetanjali; Pattanaik, Kali Prasad; Jagadeb, Manaswini; Sonawane, Avinash (Cellular Microbiology, 2020)
Mycobacterium tuberculosis survives inside the macrophages by employing several host immune evasion strategies. Here, we reported a novel mechanism in which M. tuberculosis acetyltransferase, encoded by Rv3034c, induces peroxisome homeostasis to regulate host oxidative stress levels to facilitate intracellular mycobacterial infection. Presence of M. tuberculosis Rv3034c induces the expression of peroxisome biogenesis and proliferation factors such as Pex3, Pex5, Pex19, Pex11b, Fis-1 and DLP-1; while depletion of Rv3034c decreased the expression of these molecules, thereby selective degradation of peroxisomes via pexophagy. Further studies revealed that M. tuberculosis Rv3034c inhibit induction of pexophagy mechanism by down-regulating the expression of pexophagy associated proteins (p-AMPKα, p-ULK-1, Atg5, Atg7, Beclin-1, LC3-II, TFEB and Keap-1) and adaptor molecules (NBR1 and p62). Inhibition was found to be dependent on the phosphorylation of mTORC1 and activation of peroxisome proliferator activated receptor-γ. In order to maintain intracellular homeostasis during oxidative stress, M. tuberculosis Rv3034c was found to induce degradation of dysfunctional and damaged peroxisomes through activation of Pex14 in infected macrophages. In conclusion, this is the first report which demonstrated that M. tuberculosis acetyltransferase regulate peroxisome homeostasis in response to intracellular redox levels to favour mycobacterial infection in macrophage.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Macrophages; Gene Expression Regulation; macrophages; Oxidative Stress; Cytoplasm; Macroautophagy; Mechanistic Target of Rapamycin Complex 1; Mtb; Oxidation-Reduction; peroxisome; pexophagy; PPAR gamma; redox levels

Rv1273c, an ABC transporter of Mycobacterium tuberculosis promotes mycobacterial intracellular survival within macrophages via modulating the host cell immune response - Gupta, Smita; Kumar, Arun; Singh, Kamal; Kumari, Richa; Sharma, Ajay; Singh, Rakesh K.; Pandey, Satyendra K.; Anupurba, Shampa (International Journal of Biological Macromolecules, 2020)
Mycobacterium proteins, especially cell wall associated proteins, interact with host macrophage to regulate the functions and cytokine production. So, identification and characterization of such proteins is essential for understanding tuberculosis pathogenesis. The role of the ABC transporter proteins in the pathophysiology and virulence of Mycobacterium tuberculosis is not clearly understood. In the present study, Rv1273c, an ABC transporter, has been expressed in a non-pathogenic and fast growing Mycobacterium smegmatis strain to explore its role in host pathogen interactions. Over expression of Rv1273c resulted in enhanced intracellular survival in macrophage as well as modified cell wall architecture. We found altered colony morphology and cell surface properties that might be linked with remodelling of bacterial cell wall which may help in the intracellular survival of mycobacterium. However, the enhanced intracellular survival was not found to be the consequence of an increased resistance to intracellular stresses. The activation of macrophage by Rv1273c was associated with perturbed cytokine production. Pharmacological inhibition experiment and western immunoblotting suggested that this altered cytokine profile was mediated possibly by NF-kB and p38 pathway in macrophage. Overall, the present findings indicated that Rv1273c enhanced mycobacterium persistence and mediated the evasion of immune responses during infection.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Macrophages; Cell Membrane; Mycobacterium smegmatis; Cell Wall; Gene Expression Regulation, Bacterial; Cytokines; Immunomodulation; Signal Transduction; Microbial Viability; Phenotype; Macrophage; ATP-Binding Cassette Transporters; Intracellular survival; Rv1273c

The Mycobacterium tuberculosis PE_PGRS Protein Family Acts as an Immunological Decoy to Subvert Host Immune Response - Sharma, Tarina; Alam, Anwar; Ehtram, Aquib; Rani, Anshu; Grover, Sonam; Ehtesham, Nasreen Z.; Hasnain, Seyed E. (International Journal of Molecular Sciences, 2022)
Mycobacterium tuberculosis (M.tb) is a successful pathogen that can reside within the alveolar macrophages of the host and can survive in a latent stage. The pathogen has evolved and developed multiple strategies to resist the host immune responses. M.tb escapes from host macrophage through evasion or subversion of immune effector functions. M.tb genome codes for PE/PPE/PE_PGRS proteins, which are intrinsically disordered, redundant and antigenic in nature. These proteins perform multiple functions that intensify the virulence competence of M.tb majorly by modulating immune responses, thereby affecting immune mediated clearance of the pathogen. The highly repetitive, redundant and antigenic nature of PE/PPE/PE_PGRS proteins provide a critical edge over other M.tb proteins in terms of imparting a higher level of virulence and also as a decoy molecule that masks the effect of effector molecules, thereby modulating immuno-surveillance. An understanding of how these proteins subvert the host immunological machinery may add to the current knowledge about M.tb virulence and pathogenesis. This can help in redirecting our strategies for tackling M.tb infections.
Keywords: Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; Host-Pathogen Interactions; Antigens, Bacterial; Macrophages; Tuberculosis; Virulence; Immunomodulation; Immune Evasion; TB; virulence; immune evasion; decoy antigens; Disease Susceptibility; glycine; Glycine; latency; pathogenicity

Mycobacterium tuberculosis PPE51 Inhibits Autophagy by Suppressing Toll-Like Receptor 2-Dependent Signaling - Strong, Emily J.; Wang, Jia; Ng, Tony W.; Porcelli, Steven A.; Lee, Sunhee (mBio, 2022)
Autophagy is an ubiquitous homeostatic pathway in mammalian cells and plays a significant role in host immunity. Substantial evidence indicates that the ability of Mycobacterium tuberculosis (Mtb) to successfully evade immune responses is partially due to inhibition of autophagic pathways. Our previous screening of Mtb transposon mutants identified the PPE51 protein as an important autophagy-inhibiting effector. We found that expression of PPE51, either by infecting bacteria or by direct expression in host cells, suppressed responses to potent autophagy-inducing stimuli and interfered with bacterial phagocytosis. This phenotype was associated with reduced activation of extracellular signal-regulated kinase 1/2 (ERK1/2), a key component of signaling pathways that stimulate autophagy. Multiple lines of evidence demonstrated that the effects of PPE51 are attributable to signal blocking by Toll-like receptor 2 (TLR2), a receptor with known involvement of activation of ERK1/2 and autophagy. Consistent with these results, mice with intact TLR2 signaling showed striking virulence attenuation for an Mtb ppe51 deletion mutant (Δ51) compared to wild-type Mtb, whereas infection of TLR2-deficient mice showed no such attenuation. Mice infected with Δ51 also displayed increased T cell responses to Mtb antigens and increased autophagy in infected lung tissues. Together, these results suggest that TLR2 activates relevant host immune functions during mycobacterial infection, which Mtb then evades through suppression of TLR2 signaling by PPE51. In addition to its previously identified function transporting substrates across the bacterial cell wall, our results demonstrate a direct role of PPE51 for evasion of both innate and adaptive immunity to Mtb. IMPORTANCE Tuberculosis is a significant global infectious disease caused by infection of the lungs with Mycobacterium tuberculosis, which resides and replicates mainly within host phagocytic cells. During coevolution with humans, Mtb has acquired various mechanisms to inhibit host cellular processes, including autophagy. Autophagy is a complex host cellular process that helps control intracellular infections by enhancing innate and adaptive immune responses. We identified the Mtb protein PPE51 as a mycobacterial effector that inhibits autophagy. We discovered TLR2 and mitogen-activated protein kinase signaling as the axis by which PPE51 mediates this effect. Autophagy regulation by PPE51, along with suppression of other TLR2-activated host cell functions, leads to increased bacterial survival in phagocytic cells and tissues of infected mice. A better understanding of how Mtb regulates autophagy and other host immune effectors could facilitate the design of new therapeutics or vaccines against tuberculosis.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis; Mice; Immunity, Innate; innate immunity; Autophagy; autophagy; Toll-Like Receptor 2; host-microbe interaction; mitogen-activated protein kinase ERK1/2; Toll-like receptor 2

Polymorphisms of human T cell epitopes of Mycobacterium tuberculosis indicate divergence of host immune pressure on different categories of proteins - Jiang, Yi; Liu, Haican; Dou, Xiangfeng; Zhao, Xiuqin; Li, Machao; Li, Guilian; Bai, Yun; Zhang, Wen; Lian, Lulu; Yu, Qin; Zhang, Jingrui; Wan, Kanglin (Life Sciences, 2018)
Mycobacterium tuberculosis is the most successful pathogen with multiple mechanisms to subvert host immune response, resulting in insidious disease. There are few studies on whether the bacteria undergo antigenic variation in response to host immune pressure. Studies on T cell epitopes of M. tuberculosis can help us further understand the mechanism of interaction between the bacteria and host immune system. Here, we selected 180 M. tuberculosis complex in China, amplified 462 experimentally verified human T cell epitopes, sequenced and compared the results to analyze the diversity of those epitopes. It proved that a large majority human T cell epitopes of M. tuberculosis are conserved. However, polymorphisms of T cell epitopes indicated different categories of proteins suffered divergence from host immune pressure. Moreover, Beijing strains are more conservative than non-Beijing strains in T cell epitopes, which might make them easier to transmit than non-Beijing strains.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Tuberculosis; Immune Evasion; Epitopes, T-Lymphocyte; Polymorphism, Genetic; China; Diversity; Human T cell epitopes

Methylation in Mycobacterium-host interaction and implications for novel control measures - Asaad, Mohammed; Abo-Kadoum, M. A.; Nzungize, Lambert; Uae, Moure; Nzaou, Stech A. E.; Xie, Jianping (Infection, Genetics and Evolution: Journal of Molecular Epidemiology and Evolutionary Genetics in Infectious Diseases, 2020)
Methylation epigenetically regulates many pivotal biological processes. Mycobacterium tuberculosis, the pathogen of tuberculosis, can modulate host methylome. The methylated genes, sites, signaling pathway, chromatin remodeling, especially the immune related genes such as cytokines and chemokines, drug resistance and vaccines efficacy relevant genes were summarized in this paper. The results showed that methylation plays important roles in immune evasion, pathogenesis, persistence, disease progression, active, drug responder and non-responder. This will inform better practice for the development of new drugs and vaccines to eradicate tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; Mycobacterium; Immune evasion; Immune Evasion; Gene Expression Regulation; Histones; Epigenesis, Genetic; Chromatin remodeling; DNA Methylation; Drug Resistance, Bacterial; Methylation

The immunology of other mycobacteria: M. ulcerans, M. leprae - Röltgen, Katharina; Pluschke, Gerd; Spencer, John Stewart; Brennan, Patrick Joseph; Avanzi, Charlotte (Seminars in Immunopathology, 2020)
Mycobacterial pathogens can be categorized into three broad groups: Mycobacterium tuberculosis complex causing tuberculosis, M. leprae and M. lepromatosis causing leprosy, and atypical mycobacteria, or non-tuberculous mycobacteria (NTM), responsible for a wide range of diseases. Among the NTMs, M. ulcerans is responsible for the neglected tropical skin disease Buruli ulcer (BU). Most pathogenic mycobacteria, including M. leprae, evade effector mechanisms of the humoral immune system by hiding and replicating inside host cells and are furthermore excellent modulators of host immune responses. In contrast, M. ulcerans replicates predominantly extracellularly, sheltered from host immune responses through the cytotoxic and immunosuppressive effects of mycolactone, a macrolide produced by the bacteria. In the year 2018, 208,613 new cases of leprosy and 2713 new cases of BU were reported to WHO, figures which are notoriously skewed by vast underreporting of these diseases.
Keywords: Humans; Mycobacterium; Immune evasion; Skin; Buruli ulcer; Buruli Ulcer; Diagnosis; Immunopathology; Leprosy; Mycobacterium ulcerans; Polarization of immune responses; Vaccine design

Molecular Basis Underlying Host Immunity Subversion by Mycobacterium tuberculosis PE/PPE Family Molecules - Yu, Xiaowen; Feng, Jing; Huang, Lu; Gao, Hongyan; Liu, Jinkun; Bai, Shutong; Wu, Bin; Xie, Jianping (DNA and cell biology, 2019)
Mycobacterium tuberculosis proline-glutamic acid (PE)/proline-proline-glutamic acid (PPE) family proteins, with >160 members, are crucial for virulence, cell wall, host cell fate, host Th1/Th2 balance, and CD8+ T cell recognition. Ca2+ signaling is involved in PE/PPE protein-mediated host-pathogen interaction. PE/PPE proteins also function in heme utilization and nitric oxide production. PE/PPE family proteins are intensively pursued as diagnosis biomarkers and vaccine components.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; vaccine; Virulence; Immune Evasion; diagnosis biomarker; Glutamic Acid; host immunity; Multigene Family; PE/PPE proteins; Proline; Proline-Rich Protein Domains

Inflammasomes, Autophagy, and Cell Death: The Trinity of Innate Host Defense against Intracellular Bacteria - Krakauer, Teresa (Mediators of Inflammation, 2019)
Inflammasome activation is an innate host defense mechanism initiated upon sensing pathogens or danger in the cytosol. Both autophagy and cell death are cell autonomous processes important in development, as well as in host defense against intracellular bacteria. Inflammasome, autophagy, and cell death pathways can be activated by pathogens, pathogen-associated molecular patterns (PAMPs), cell stress, and host-derived damage-associated molecular patterns (DAMPs). Phagocytosis and toll-like receptor (TLR) signaling induce reactive oxygen species (ROS), type I IFN, NFκB activation of proinflammatory cytokines, and the mitogen-activated protein kinase cascade. ROS and IFNγ are also prominent inducers of autophagy. Pathogens, PAMPs, and DAMPs activate TLRs and intracellular inflammasomes, inducing apoptotic and inflammatory caspases in a context-dependent manner to promote various forms of cell death to eliminate pathogens. Common downstream signaling molecules of inflammasomes, autophagy, and cell death pathways interact to initiate appropriate measures against pathogens and determine host survival as well as pathological consequences of infection. The integration of inflammasome activation, autophagy, and cell death is central to pathogen clearance. Various pathogens produce virulence factors to control inflammasomes, subvert autophagy, and modulate host cell death in order to evade host defense. This review highlights the interaction of inflammasomes, autophagy, and host cell death pathways in counteracting Burkholderia pseudomallei, the causative agent of melioidosis. Contrasting evasion strategies used by B. pseudomallei, Mycobacterium tuberculosis, and Legionella pneumophila to avoid and dampen these innate immune responses will be discussed.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Immunity, Innate; Signal Transduction; Phagocytosis; Apoptosis; Toll-Like Receptors; Mycobacterium Infections; Inflammation; Cytosol; Reactive Oxygen Species; Autophagy; Bacteria; Cell Death; Caspases; NF-kappa B; Inflammasomes; Interleukin-1beta; Burkholderia Infections; Burkholderia pseudomallei; Legionella pneumophila; Legionellosis

The role of epigenetics, bacterial and host factors in progression of Mycobacterium tuberculosis infection - Marimani, Musa; Ahmad, Aijaz; Duse, Adriano (Tuberculosis (Edinburgh, Scotland), 2018)
Tuberculosis (TB) infection caused by Mycobacterium tuberculosis (Mtb) is still a persistent global health problem, particularly in developing countries. The World Health Organization (WHO) reported a mortality rate of about 1.8 million worldwide due to TB complications in 2015. The Bacillus Calmette-Guérin (BCG) vaccine was introduced in 1921 and is still widely used to prevent TB development. This vaccine offers up to 80% protection against various forms of TB; however its efficacy against lung infection varies among different geographical settings. Devastatingly, the development of various forms of drug-resistant TB strains has significantly impaired the discovery of effective and safe anti-bacterial agents. Consequently, this necessitated discovery of new drug targets and novel anti-TB therapeutics to counter infection caused by various Mtb strains. Importantly, various factors that contribute to TB development have been identified and include bacterial resuscitation factors, host factors, environmental factors and genetics. Furthermore, Mtb-induced epigenetic changes also play a crucial role in evading the host immune response and leads to bacterial persistence and dissemination. Recently, the application of GeneXpert MTB/RIF® to rapidly diagnose and identify drug-resistant strains and discovery of different molecular markers that distinguish between latent and active TB infection has motivated and energised TB research. Therefore, this review article will briefly discuss the current TB state, highlight various mechanisms employed by Mtb to evade the host immune response as well as to discuss some modern molecular techniques that may potentially target and inhibit Mtb replication.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Antitubercular Agents; Genotype; Immune Evasion; Phenotype; Epigenesis, Genetic; Mutation; Drug Resistance, Bacterial; Bacillus calmette-guérin vaccine; Drug-resistance; New drug targets; Prognosis

TREM2 is a receptor for non-glycosylated mycolic acids of mycobacteria that limits anti-mycobacterial macrophage activation - Iizasa, Ei'ichi; Chuma, Yasushi; Uematsu, Takayuki; Kubota, Mio; Kawaguchi, Hiroaki; Umemura, Masayuki; Toyonaga, Kenji; Kiyohara, Hideyasu; Yano, Ikuya; Colonna, Marco; Sugita, Masahiko; Matsuzaki, Goro; et al. (Nature Communications, 2021)
Mycobacterial cell-wall glycolipids elicit an anti-mycobacterial immune response via FcRγ-associated C-type lectin receptors, including Mincle, and caspase-recruitment domain family member 9 (CARD9). Additionally, mycobacteria harbor immuno-evasive cell-wall lipids associated with virulence and latency; however, a mechanism of action is unclear. Here, we show that the DAP12-associated triggering receptor expressed on myeloid cells 2 (TREM2) recognizes mycobacterial cell-wall mycolic acid (MA)-containing lipids and suggest a mechanism by which mycobacteria control host immunity via TREM2. Macrophages respond to glycosylated MA-containing lipids in a Mincle/FcRγ/CARD9-dependent manner to produce inflammatory cytokines and recruit inducible nitric oxide synthase (iNOS)-positive mycobactericidal macrophages. Conversely, macrophages respond to non-glycosylated MAs in a TREM2/DAP12-dependent but CARD9-independent manner to recruit iNOS-negative mycobacterium-permissive macrophages. Furthermore, TREM2 deletion enhances Mincle-induced macrophage activation in vitro and inflammation in vivo and accelerates the elimination of mycobacterial infection, suggesting that TREM2-DAP12 signaling counteracts Mincle-FcRγ-CARD9-mediated anti-mycobacterial immunity. Mycobacteria, therefore, harness TREM2 for immune evasion.
Keywords: Humans; Membrane Proteins; Mycobacterium tuberculosis; Animals; Macrophages; Virulence Factors; Cells, Cultured; Cell Wall; Mice; Disease Models, Animal; Female; Latent Tuberculosis; Macrophage Activation; Male; Receptors, IgG; Mice, Knockout; Immune Evasion; Membrane Glycoproteins; Glycolipids; Mycolic Acids; Adaptor Proteins, Signal Transducing; Primary Cell Culture; CARD Signaling Adaptor Proteins; Lectins, C-Type; Receptors, Immunologic

Mycobacterium tuberculosis Prolyl Oligopeptidase Induces In vitro Secretion of Proinflammatory Cytokines by Peritoneal Macrophages - Portugal, Brina; Motta, Flávia N.; Correa, Andre F.; Nolasco, Diego O.; de Almeida, Hugo; Magalhães, Kelly G.; Atta, Ana L. V.; Vieira, Francisco D.; Bastos, Izabela M. D.; Santana, Jaime M. (Frontiers in Microbiology, 2017)
Tuberculosis (TB) is a disease that leads to death over 1 million people per year worldwide and the biological mediators of this pathology are poorly established, preventing the implementation of effective therapies to improve outcomes in TB. Host-bacterium interaction is a key step to TB establishment and the proteases produced by these microorganisms seem to facilitate bacteria invasion, migration and host immune response evasion. We presented, for the first time, the identification, biochemical characterization, molecular dynamics (MDs) and immunomodulatory properties of a prolyl oligopeptidase (POP) from Mycobacterium tuberculosis (POPMt). POP is a serine protease that hydrolyzes substrates with high specificity for proline residues and has already been characterized as virulence factor in infectious diseases. POPMt reveals catalytic activity upon N-Suc-Gly-Pro-Leu-Gly-Pro-AMC, a recognized POP substrate, with optimal activity at pH 7.5 and 37°C. The enzyme presents KM and Kcat/KM values of 108 μM and 21.838 mM-1 s-1, respectively. MDs showed that POPMt structure is similar to that of others POPs, which consists of a cylindrical architecture divided into an α/β hydrolase catalytic domain and a β-propeller domain. Finally, POPMt was capable of triggering in vitro secretion of proinflammatory cytokines by peritoneal macrophages, an event dependent on POPMt intact structure. Our data suggests that POPMt may contribute to an inflammatory response during M. tuberculosis infection.
Keywords: tuberculosis; fluorescence spectroscopy; molecular dynamic; Mycobacterium tuberculosis protease; proinflammatory cytokines; prolyl oligopeptidase; serine protease

Inhibition of Fatty Acid Oxidation Promotes Macrophage Control of Mycobacterium tuberculosis - Chandra, Pallavi; He, Li; Zimmerman, Matthew; Yang, Guozhe; Köster, Stefan; Ouimet, Mireille; Wang, Han; Moore, Kathyrn J.; Dartois, Véronique; Schilling, Joel D.; Philips, Jennifer A. (mBio, 2020)
Macrophage activation involves metabolic reprogramming to support antimicrobial cellular functions. How these metabolic shifts influence the outcome of infection by intracellular pathogens remains incompletely understood. Mycobacterium tuberculosis (Mtb) modulates host metabolic pathways and utilizes host nutrients, including cholesterol and fatty acids, to survive within macrophages. We found that intracellular growth of Mtb depends on host fatty acid catabolism: when host fatty acid β-oxidation (FAO) was blocked chemically with trimetazidine, a compound in clinical use, or genetically by deletion of the mitochondrial fatty acid transporter carnitine palmitoyltransferase 2 (CPT2), Mtb failed to grow in macrophages, and its growth was attenuated in mice. Mechanistic studies support a model in which inhibition of FAO generates mitochondrial reactive oxygen species, which enhance macrophage NADPH oxidase and xenophagy activity to better control Mtb infection. Thus, FAO inhibition promotes key antimicrobial functions of macrophages and overcomes immune evasion mechanisms of Mtb.IMPORTANCEMycobacterium tuberculosis (Mtb) is the leading infectious disease killer worldwide. We discovered that intracellular Mtb fails to grow in macrophages in which fatty acid β-oxidation (FAO) is blocked. Macrophages treated with FAO inhibitors rapidly generate a burst of mitochondria-derived reactive oxygen species, which promotes NADPH oxidase recruitment and autophagy to limit the growth of Mtb. Furthermore, we demonstrate the ability of trimetazidine to reduce pathogen burden in mice infected with Mtb. These studies will add to the knowledge of how host metabolism modulates Mtb infection outcomes.
Keywords: Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Cells, Cultured; Antitubercular Agents; Mice; Female; Cytokines; Mice, Inbred C57BL; innate immunity; Macrophage Activation; Reactive Oxygen Species; Lipid Metabolism; macrophages; Oxidation-Reduction; fatty acid oxidation; Fatty Acids; Metabolic Networks and Pathways; mitochondrial metabolism; NADPH oxidase; Trimetazidine

Utilization of Staphylococcal Immune Evasion Protein Sbi as a Novel Vaccine Adjuvant - Yang, Yi; Back, Catherine R.; Gräwert, Melissa A.; Wahid, Ayla A.; Denton, Harriet; Kildani, Rebecca; Paulin, Joshua; Wörner, Kristin; Kaiser, Wolgang; Svergun, Dmitri I.; Sartbaeva, Asel; Watts, Andrew G.; et al. (Frontiers in Immunology, 2018)
Co-ligation of the B cell antigen receptor with complement receptor 2 on B-cells via a C3d-opsonised antigen complex significantly lowers the threshold required for B cell activation. Consequently, fusions of antigens with C3d polymers have shown great potential in vaccine design. However, these linear arrays of C3d multimers do not mimic the natural opsonisation of antigens with C3d. Here we investigate the potential of using the unique complement activating characteristics of Staphylococcal immune-evasion protein Sbi to develop a pro-vaccine approach that spontaneously coats antigens with C3 degradation products in a natural way. We show that Sbi rapidly triggers the alternative complement pathway through recruitment of complement regulators, forming tripartite complexes that act as competitive antagonists of factor H, resulting in enhanced complement consumption. These functional results are corroborated by the structure of the complement activating Sbi-III-IV:C3d:FHR-1 complex. Finally, we demonstrate that Sbi, fused with Mycobacterium tuberculosis antigen Ag85b, causes efficient opsonisation with C3 fragments, thereby enhancing the immune response significantly beyond that of Ag85b alone, providing proof of concept for our pro-vaccine approach.
Keywords: Bacterial Proteins; Animals; Antigens, Bacterial; Models, Molecular; Protein Conformation; Structure-Activity Relationship; Immunization; vaccine; Mice; Disease Models, Animal; Adjuvants, Immunologic; Recombinant Fusion Proteins; Mice, Knockout; Immune Evasion; Carrier Proteins; Acyltransferases; immune evasion; adjuvant; complement; Staphycoccus aureus; Staphylococcal Infections; Staphylococcal Vaccines; Staphylococcus

Antigenic Variation and Immune Escape in the MTBC - Ernst, Joel D. (Advances in Experimental Medicine and Biology, 2017)
Microbes that infect other organisms encounter host immune responses, and must overcome or evade innate and adaptive immune responses to successfully establish infection. Highly successful microbial pathogens, including M. tuberculosis, are able to evade adaptive immune responses (mediated by antibodies and/or T lymphocytes) and thereby establish long-term chronic infection. One mechanism that diverse pathogens use to evade adaptive immunity is antigenic variation, in which structural variants emerge that alter recognition by established immune responses and allow those pathogens to persist and/or to infect previously-immune hosts. Despite the wide use of antigenic variation by diverse pathogens, this mechanism appears to be infrequent in M. tuberculosis, as indicated by findings that known and predicted human T cell epitopes in this organism are highly conserved, although there are exceptions. These findings have implications for diagnostic tests that are based on measuring host immune responses, and for vaccine design and development.
Keywords: Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Genome, Bacterial; Adaptive Immunity; Immunity, Innate; T-Lymphocytes; Immune Evasion; Gene Expression Regulation; Epitopes, T-Lymphocyte; HLA Antigens; Antigenic Variation; Antigenic variation, Immune Escape, T lymphocytes, Epitopes, Antibodies, Tuberculosis; Conserved Sequence; Selection, Genetic

Predicted Structural Variability of Mycobacterium tuberculosis PPE18 Protein With Immunological Implications Among Clinical Strains - Hakim, Jill M. C.; Yang, Zhenhua (Frontiers in Microbiology, 2020)
Recent advancements in vaccinology have led to the development of the M72/AS01E subunit vaccine, of which the major component is the Mycobacterium tuberculosis (MTB) PPE18 protein. Previous studies have demonstrated the genetic variability of the gene encoding PPE18 protein and the resulting peptide changes in diverse clinical strains of MTB; however, none have modeled the structural changes resulting from these peptide changes and their immunological implications. In this study, we investigated the structural predictions of 29 variant PPE18 proteins previously reported. We found evidence that PPE18 is at least a two-domain protein, with a highly conserved first domain and a largely variable second domain that has different coevolutionary clusters. Further, we investigated putative epitope sites in the clinical variants of PPE18 using prediction software. We found a negative relationship between T-cell epitope number and residue variability, while B-cell epitope likelihood was positively correlated with residue variability. Moreover, we found far more residues in the second domain predicted to be B-cell epitopes compared with the first domain. These results suggest an important functional role of the first domain and a role in immune evasion for the second, which extends our knowledge base of the basic biology of the PPE18 protein and indicates the need for further study into non-traditional immunological responses to TB.
Keywords: Mycobacterium tuberculosis; epitope prediction; immune evasion; in silico structural prediction; PPE18

E3 Ligase FBXW7 Facilitates Mycobacterium Immune Evasion by Modulating TNF-α Expression - Song, Jingrui; Chao, Jin; Hu, Xiaohong; Wen, Xin; Ding, Cairong; Li, Dan; Zhang, Ding; Han, Shanshan; Yu, Xiang; Yan, Bo; Jin, Zhu; Song, Yinhong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Tumor necrosis factor alpha (TNF-α) is a crucial factor in the control of Mycobacterium tuberculosis (Mtb) infection. Pathogenic mycobacteria can inhibit and/or regulate host cell TNF-α production in a variety of ways to evade antituberculosis (anti-TB) immunity as well as facilitate immune escape. However, the mechanisms by which TNF-α expression in host cells is modulated to the benefit of mycobacteria is still an interesting topic and needs further study. Here, we report that macrophages infected with Mycobacterium marinum (Mm)-a close relative of Mtb-upregulated the expression of E3 ubiquitin ligase FBXW7. Specific silencing FBXW7 with small interfering RNA (siRNA) significantly elevates TNF-α expression and eventually promotes the elimination of intracellular bacteria. In turn, overexpression of FBXW7 in Raw264.7 macrophages markedly decreased TNF-α production. Furthermore, partial inhibition of FBXW7 in an Mm-infected murine model significantly reduced TNF-α tissue content, alleviated tissue damage as well as reduced the bacterial load of mouse tails. Finally, FBXW7 could decrease TNF-α in a K63-linked ubiquitin signaling dependent manner. Taken together, our study uncovered a previously unknown role of FBXW7 in regulating TNF-α dynamics during mycobacterial infection, which provides new insights into understanding the role of FBXW7 in anti-tuberculosis immunity and its related clinical significance.
Keywords: Mycobacterium tuberculosis; Animals; Mice; granuloma; Immune Evasion; Mycobacterium marinum; Tumor Necrosis Factor-alpha; mycobacteria; TNF-α; F-Box-WD Repeat-Containing Protein 7; FBXW7; Ubiquitin-Protein Ligases; ubiquitination

Bacterial Virulence Factors: Secreted for Survival - Sharma, Aditya Kumar; Dhasmana, Neha; Dubey, Neha; Kumar, Nishant; Gangwal, Aakriti; Gupta, Meetu; Singh, Yogendra (Indian Journal of Microbiology, 2017)
Virulence is described as an ability of an organism to infect the host and cause a disease. Virulence factors are the molecules that assist the bacterium colonize the host at the cellular level. These factors are either secretory, membrane associated or cytosolic in nature. The cytosolic factors facilitate the bacterium to undergo quick adaptive-metabolic, physiological and morphological shifts. The membrane associated virulence factors aid the bacterium in adhesion and evasion of the host cell. The secretory factors are important components of bacterial armoury which help the bacterium wade through the innate and adaptive immune response mounted within the host. In extracellular pathogens, the secretory virulence factors act synergistically to kill the host cells. In this review, we revisit the role of some of the secreted virulence factors of two human pathogens: Mycobacterium tuberculosis-an intracellular pathogen and Bacillus anthracis-an extracellular pathogen. The advances in research on the role of secretory factors of these pathogens during infection are discussed.
Keywords: Tuberculosis; Mycobacterium; Virulence; Anthrax; Bacillus; Phosphatases

Mycobacterium bovis induces mitophagy to suppress host xenophagy for its intracellular survival - Song, Yinjuan; Ge, Xin; Chen, Yulan; Hussain, Tariq; Liang, Zhengmin; Dong, Yuhui; Wang, Yuanzhi; Tang, Chengyuan; Zhou, Xiangmei (Autophagy, 2022)
Mitophagy is a selective autophagy mechanism for eliminating damaged mitochondria and plays a crucial role in the immune evasion of some viruses and bacteria. Here, we report that Mycobacterium bovis (M. bovis) utilizes host mitophagy to suppress host xenophagy to enhance its intracellular survival. M. bovis is the causative agent of animal tuberculosis and human tuberculosis. In the current study, we show that M. bovis induces mitophagy in macrophages, and the induction of mitophagy is impaired by PINK1 knockdown, indicating the PINK1-PRKN/Parkin pathway is involved in the mitophagy induced by M. bovis. Moreover, the survival of M. bovis in macrophages and the lung bacterial burden of mice are restricted by the inhibition of mitophagy and are enhanced by the induction of mitophagy. Confocal microscopy analysis reveals that induction of mitophagy suppresses host xenophagy by competitive utilization of p-TBK1. Overall, our results suggest that induction of mitophagy enhances M. bovis growth while inhibition of mitophagy improves growth restriction. The findings provide a new insight for understanding the intracellular survival mechanism of M. bovis in the host.Abbreviations: BMDM: mouse bone marrow-derived macrophage; BNIP3: BCL2/adenovirus E1B interacting protein 3; BNIP3L/NIX: BCL2/adenovirus E1B interacting protein 3-like; BCL2L13: BCL2-like 13 (apoptosis facilitator); CCCP: carbonyl cyanide m-cholorophenyl hydrazone; FUNDC1: FUN14 domain-containing 1; FKBP8: FKBP506 binding protein 8; HCV: hepatitis C virus; HBV: hepatitis B virus; IFN: interferon; L. monocytogenes: Listeria monocytogenes; M. bovis: Mycobacterium bovis; Mtb: Mycobacterium tuberculosis; Mdivi-1: mitochondrial division inhibitor 1; PINK1: PTEN-induced putative kinase 1; TBK1: TANK-binding kinase 1; TUFM: Tu translation elongation factor, mitochondrial; TEM: transmission electron microscopy.
Keywords: Membrane Proteins; Animals; Macrophages; Mice; Mycobacterium bovis; Macrophage; Macroautophagy; Mitochondrial Proteins; mitophagy; Mitophagy; p-TBK1; xenophagy

Mycobacterium tuberculosis Virulent Factor ESAT-6 Drives Macrophage Differentiation Toward the Pro-inflammatory M1 Phenotype and Subsequently Switches It to the Anti-inflammatory M2 Phenotype - Refai, Amira; Gritli, Sami; Barbouche, Mohamed-Ridha; Essafi, Makram (Frontiers in Cellular and Infection Microbiology, 2018)
Tuberculosis, a human infectious disease caused by Mycobacterium tuberculosis (M.tb), is still a major cause of morbidity and mortality worldwide. The success of M.tb as a pathogen relies mainly on its ability to divert the host innate immune responses. One way by which M.tb maintains a persistent infection in a "silent" granuloma is to inhibit inflammation and induce an immunoregulatory phenotype in host macrophages (MΦs). However, M.tb effectors governing the switch of MΦs from the pro-inflammatory M1 to the anti-inflammatory M2 phenotype remain to be determined. The Early Secreted Antigenic Target 6 kDa or ESAT-6, has been implicated in the virulence and pathogenesis of tuberculosis. Here, we investigated roles of ESAT-6 in MΦ differentiation and polarization. We found that treatment of human monocytes with ESAT-6 did not interfere with differentiation of M1 MΦs. However, ESAT-6 promoted differentiation of M0 and M2 MΦs toward the M1 phenotype, as indicated by secretion of pro-inflammatory cytokines IL-6, IL-12, and TNF-α, and induction of a typical M1 transcriptional signature. Interestingly, we found that ESAT-6 switched terminal full activation of M1 polarized MΦs to the M2 phenotype. Indeed, in the pro-inflammatory M1 MΦs, ESAT-6 was able to inhibit IL-12 and TNF-α secretion and stimulate that of IL-10. Moreover, gene expression profiling of these cells showed that ESAT-6 induced downregulation of M1 MΦ cell surface molecules CD80 and CD86, transcription factors IRF5 and c-MAF, cytokines IL-12, IL-10, and IL-6, as well as chemokines CXCL10 and CXCL1. Overall, our findings suggest ESAT-6 as being one of the effectors used by M.tb to induce the pro-inflammatory M1 phenotype at the primo-infection; a prerequisite step to promote granuloma formation and subsequently drive the phenotype switch of MΦ polarization from M1 to M2 at a later stage of the infection. Our study improves current knowledge regarding mechanisms of virulence of M.tb and may be helpful to develop novel tools targeting ESAT-6 for a better and more efficient treatment of tuberculosis.
Keywords: Bacterial Proteins; Humans; Host-Pathogen Interactions; Antigens, Bacterial; Macrophages; Gene Expression Profiling; Virulence Factors; Cell Differentiation; tuberculosis; Cells, Cultured; Cytokines; Immune Evasion; Phenotype; Immune Tolerance; macrophages; ESAT-6; M. tuberculosis; polarization

Molecular mechanisms of bacteria induced autophagy and its escape strategies - Sharma, Saroj; Tiwari, Monalisa; Tiwari, Vishvanath (Future Microbiology, 2020)
Keywords: Humans; Mycobacterium tuberculosis; Animals; Immune Evasion; Autophagy; Bacteria; Bacterial Infections; Salmonella typhimurium; Acinetobacter baumannii; bacteria-induced autophagy; bacterial escape strategies; Bacterial Physiological Phenomena; reproductive niches

PE_PGRS: Vital proteins in promoting mycobacterial survival and modulating host immunity and metabolism - Xie, Yan; Zhou, Yidan; Liu, Sheng; Zhang, Xiao-Lian (Cellular Microbiology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (M. tb), is the leading infectious cause of mortality worldwide. One of the key reasons for M. tb pathogenesis is the capability of M. tb to evade immune elimination and survive in macrophage, eventually causing chronic infection. However the pathogenicity mechanism of M. tb is not unclear yet, and thus diagnosis and therapy for TB remains a challenge. The genome of M. tb, encodes a unique protein family known as the PGRS family, with largely unexplored functions. Recently, an increasing number of reports have shown that the PE_PGRS proteins play critical roles in bacterial pathogenesis and immune evasion. The PE_PGRS protein family, characterized by a special N-terminal PE (Pro (P)-Glu (E) motif) domain and a C-terminal PGRS (Polymorphic GC-rich Repetitive Sequences) domain, is restricted mainly to pathogenic mycobacteria. Here we summarize current literature on the PE_PGRS as vital proteins in promoting bacterial survival and modulating host immunity, cell death and metabolism. We also highlight the potential of PE_PGRS as novel targets of anti-mycobacterial interventions for TB control.
Keywords: Bacterial Proteins; Humans; Membrane Proteins; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Antigens, Bacterial; Macrophages; Tuberculosis; Antigen Presentation; Immune Evasion; Autophagy; immunity; Lipid Metabolism; Cell Death; Lysosomes; bacterial survival; metabolism; PE_PGRS

IFN-β: A Contentious Player in Host-Pathogen Interaction in Tuberculosis - Sabir, Naveed; Hussain, Tariq; Shah, Syed Zahid Ali; Zhao, Deming; Zhou, Xiangmei (International Journal of Molecular Sciences, 2017)
Tuberculosis (TB) is a major health threat to the human population worldwide. The etiology of the disease is Mycobacterium tuberculosis (Mtb), a highly successful intracellular pathogen. It has the ability to manipulate the host immune response and to make the intracellular environment suitable for its survival. Many studies have addressed the interactions between the bacteria and the host immune cells as involving many immune mediators and other cellular players. Interferon-β (IFN-β) signaling is crucial for inducing the host innate immune response and it is an important determinant in the fate of mycobacterial infection. The role of IFN-β in protection against viral infections is well established and has been studied for decades, but its role in mycobacterial infections remains much more complicated and debatable. The involvement of IFN-β in immune evasion mechanisms adopted by Mtb has been an important area of investigation in recent years. These advances have widened our understanding of the pro-bacterial role of IFN-β in host-pathogen interactions. This pro-bacterial activity of IFN-β appears to be correlated with its anti-inflammatory characteristics, primarily by antagonizing the production and function of interleukin 1β (IL-1β) and interleukin 18 (IL-18) through increased interleukin 10 (IL-10) production and by inhibiting the nucleotide-binding domain and leucine-rich repeat protein-3 (NLRP3) inflammasome. Furthermore, it also fails to provoke a proper T helper 1 (Th1) response and reduces the expression of major histocompatibility complex II (MHC-II) and interferon-γ receptors (IFNGRs). Here we will review some studies to provide a paradigm for the induction, regulation, and role of IFN-β in mycobacterial infection. Indeed, recent studies suggest that IFN-β plays a role in Mtb survival in host cells and its downregulation may be a useful therapeutic strategy to control Mtb infection.
Keywords: Humans; Animals; Host-Pathogen Interactions; Tuberculosis; Interleukin-1beta; fate of infection; Interferon-beta; interferon-β (IFN-β); interleukin-1β (IL-1β); Mycobacterium tuberculosis (Mtb); NLR Family, Pyrin Domain-Containing 3 Protein; nucleotide-binding domain and leucine-rich repeat protein-3 (NLRP3)

Suppression of Toll-like receptor 2-mediated proinflammatory responses by Mycobacterium tuberculosis protein Rv3529c - Bandyopadhyay, Upasana; Chadha, Attinder; Gupta, Priya; Tiwari, Brijendra; Bhattacharyya, Kausik; Popli, Sonam; Raman, Rajagopal; Brahamachari, Vani; Singh, Yogendra; Malhotra, Pawan; Natarajan, Krishnamurthy (Journal of Leukocyte Biology, 2017)
Microorganisms are known to devise various strategies to thwart protective responses by the host. One such strategy is to incorporate sequences and domains in their genes/proteins that have similarity to various domains of the host proteins. In this study, we report that Mycobacterium tuberculosis protein Rv3529c exhibits significant similarity to the death domain of the TLR pathway adaptor protein MyD88. Incubation of macrophages with Rv3529c specifically inhibited TLR2-mediated proinflammatory responses. This included attenuated oxidative burst, reduced phosphorylation of MAPK-ERK, reduced activation of transcription factor NF-κB and reduced secretion of proinflammatory cytokines IFN-γ, IL-6, and IL-17A with a concomitant increased secretion of suppressor cytokines IL-10 and TGF-β. Importantly, Rv3529c significantly inhibited TLR2-induced association of MyD88 with IRAK1 by competitively binding with IRAK1. Further, Rv3529c mediated inhibition of apoptosis and phagosome-lysosome fusion. Lastly, incubation of macrophages with Rv3529c increased bacterial burden inside macrophages. The data presented show another strategy evolved by M. tuberculosis toward immune evasion that centers on incorporating sequences in proteins that are similar to crucial proteins in the innate immune system of the host.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Animals; Macrophages; tuberculosis; Mice; Interferon-gamma; Signal Transduction; Phagosomes; Immune Evasion; Gene Expression Regulation; Bacterial Load; Respiratory Burst; Interleukin-17; mycobacteria; Interleukin-6; Transforming Growth Factor beta; Toll-Like Receptor 2; Interleukin-1 Receptor-Associated Kinases; Interleukin-10; immune response; Primary Cell Culture; NF-kappa B; Lysosomes; Membrane Fusion; Mitogen-Activated Protein Kinase Kinases; molecular mimicry; Molecular Mimicry; Myeloid Differentiation Factor 88; Protein Domains

The role of epigenetics, bacterial and host factors in progression of Mycobacterium tuberculosis infection - Marimani, Musa; Ahmad, Aijaz; Duse, Adriano (Tuberculosis (Edinburgh, Scotland), 2018)
Tuberculosis (TB) infection caused by Mycobacterium tuberculosis (Mtb) is still a persistent global health problem, particularly in developing countries. The World Health Organization (WHO) reported a mortality rate of about 1.8 million worldwide due to TB complications in 2015. The Bacillus Calmette-Guérin (BCG) vaccine was introduced in 1921 and is still widely used to prevent TB development. This vaccine offers up to 80% protection against various forms of TB; however its efficacy against lung infection varies among different geographical settings. Devastatingly, the development of various forms of drug-resistant TB strains has significantly impaired the discovery of effective and safe anti-bacterial agents. Consequently, this necessitated discovery of new drug targets and novel anti-TB therapeutics to counter infection caused by various Mtb strains. Importantly, various factors that contribute to TB development have been identified and include bacterial resuscitation factors, host factors, environmental factors and genetics. Furthermore, Mtb-induced epigenetic changes also play a crucial role in evading the host immune response and leads to bacterial persistence and dissemination. Recently, the application of GeneXpert MTB/RIF® to rapidly diagnose and identify drug-resistant strains and discovery of different molecular markers that distinguish between latent and active TB infection has motivated and energised TB research. Therefore, this review article will briefly discuss the current TB state, highlight various mechanisms employed by Mtb to evade the host immune response as well as to discuss some modern molecular techniques that may potentially target and inhibit Mtb replication.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Antitubercular Agents; Genotype; Immune Evasion; Phenotype; Epigenesis, Genetic; Mutation; Drug Resistance, Bacterial; Bacillus calmette-guérin vaccine; Drug-resistance; New drug targets; Prognosis

Revisión INMUNOLOGÍA Y MANIFESTACIONES DICIEMBRE Y ENERO (Google Docs)
MANIFESTACIONES CLÍNICAS ASOCIADAS CON LA RESPUESTA INMUNE EN TUBERCULOSIS (CLINICAL MANIFESTATIONS ASSOCIATED TO IMMUNE RESPONSE IN TUBERCULOSIS) Mary Lilián Carabali-Isajara,b, Oscar Hernán Rodríguez-Bejaranod, María Alejandra Izquierdoc, Tatiana Amadoa, Manuel Alfonso Patarroyoa,f,g , Jua...

Revisiting the role of the granuloma in tuberculosis - Ramakrishnan, Lalita (Nature Reviews. Immunology, 2012)
The granuloma, which is a compact aggregate of immune cells, is the hallmark structure of tuberculosis. It is historically regarded as a host-protective structure that 'walls off' the infecting mycobacteria. This Review discusses surprising new discoveries--from imaging studies coupled with genetic manipulations--that implicate the innate immune mechanisms of the tuberculous granuloma in the expansion and dissemination of infection. It also covers why the granuloma can fail to eradicate infection even after adaptive immunity develops. An understanding of the mechanisms and impact of tuberculous granuloma formation can guide the development of therapies to modulate granuloma formation. Such therapies might be effective for tuberculosis as well as for other granulomatous diseases.
Keywords: Humans; Animals; Tuberculosis; Granuloma; Immunity, Innate

The role of the granuloma in expansion and dissemination of early tuberculous infection - Davis, J. Muse; Ramakrishnan, Lalita (Cell, 2009)
Granulomas, organized aggregates of immune cells, form in response to persistent stimuli and are hallmarks of tuberculosis. Tuberculous granulomas have long been considered host-protective structures formed to contain infection. However, work in zebrafish infected with Mycobacterium marinum suggests that granulomas contribute to early bacterial growth. Here we use quantitative intravital microscopy to reveal distinct steps of granuloma formation and assess their consequence for infection. Intracellular mycobacteria use the ESX-1/RD1 virulence locus to induce recruitment of new macrophages to, and their rapid movement within, nascent granulomas. This motility enables multiple arriving macrophages to efficiently find and phagocytose infected macrophages undergoing apoptosis, leading to rapid, iterative expansion of infected macrophages and thereby bacterial numbers. The primary granuloma then seeds secondary granulomas via egress of infected macrophages. Our direct observations provide insight into how pathogenic mycobacteria exploit the granuloma during the innate immune phase for local expansion and systemic dissemination.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Virulence Factors; Granuloma; Phagocytosis; Mycobacterium Infections, Nontuberculous; Apoptosis; Chemotaxis; Mycobacterium Infections; Mycobacterium marinum; Zebrafish

Apoptotic vesicles crossprime CD8 T cells and protect against tuberculosis - Winau, Florian; Weber, Stephan; Sad, Subash; de Diego, Juana; Hoops, Silvia Locatelli; Breiden, Bernadette; Sandhoff, Konrad; Brinkmann, Volker; Kaufmann, Stefan H. E.; Schaible, Ulrich E. (Immunity, 2006)
CD8 T lymphocytes are important effectors in protective immunity against Mycobacterium tuberculosis. We recently characterized the detour pathway of CD8 T cell activation in tuberculosis mediated by apoptotic vesicles from infected cells that transport mycobacterial antigens to dendritic cells (DCs). Here we demonstrate that apoptotic vesicles from mycobacteria-infected macrophages stimulate CD8 T cells in vivo. Homing of DCs to draining lymph nodes was critically required for effective crosspriming. Subsequent fate of vesicle-associated antigens in recipient DCs was characterized by endosomal mechanisms predominating over proteasomal processing. In addition, vesicle processing depended on the presence of saposins to disintegrate apoptotic membranes. Apoptotic vesicles displayed potent adjuvant activity by stimulating through Toll-like receptors (TLR). Ultimately, vaccination with vesicles from infected cells induced protection against M. tuberculosis infection. Taken together, we propose the detour pathway to represent a genuine immunological mechanism mediating crosspriming of CD8 T cells in vivo and protection against tuberculosis.
Keywords: Animals; Macrophages; Tuberculosis; BCG Vaccine; Mice; Adjuvants, Immunologic; CD8-Positive T-Lymphocytes; Dendritic Cells; Mycobacterium bovis; Vaccination; Apoptosis; Cross-Priming; Endosomes; Saposins; Toll-Like Receptors

The tuberculous granuloma: an unsuccessful host defence mechanism providing a safety shelter for the bacteria? - Silva Miranda, Mayra; Breiman, Adrien; Allain, Sophie; Deknuydt, Florence; Altare, Frederic (Clinical & Developmental Immunology, 2012)
One of the main features of the immune response to M. Tuberculosis is the formation of an organized structure called granuloma. It consists mainly in the recruitment at the infectious stage of macrophages, highly differentiated cells such as multinucleated giant cells, epithelioid cells and Foamy cells, all these cells being surrounded by a rim of lymphocytes. Although in the first instance the granuloma acts to constrain the infection, some bacilli can actually survive inside these structures for a long time in a dormant state. For some reasons, which are still unclear, the bacilli will reactivate in 10% of the latently infected individuals, escape the granuloma and spread throughout the body, thus giving rise to clinical disease, and are finally disseminated throughout the environment. In this review we examine the process leading to the formation of the granulomatous structures and the different cell types that have been shown to be part of this inflammatory reaction. We also discuss the different in vivo and in vitro models available to study this fascinating immune structure.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Disease Models, Animal; Granuloma

Tuberculosis pathogenesis and immunity - Philips, Jennifer A.; Ernst, Joel D. (Annual Review of Pathology, 2012)
Despite the development of potentially curative chemotherapy, tuberculosis (TB) continues to cause increasing worldwide morbidity and is a leading cause of human mortality in the developing world. Recent advances in bacterial molecular genetics, immunology, and human genetics have yielded insight into the molecular determinants of virulence, the immune responses that are essential for restricting progressive disease, and the determinants of immunopathology in TB. Despite these advances, a large knowledge gap still exists that limits the development and testing of new interventions, including novel drugs and efficacious vaccines. This review focuses on our current knowledge of TB pathogenesis and immunity that has been derived from in vitro and in vivo studies. In addition, it highlights topics that need to be better understood to provide improved means of controlling TB worldwide.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; Adaptive Immunity; Immunity, Innate

How can immunology contribute to the control of tuberculosis? - Kaufmann, S. H. (Nature Reviews. Immunology, 2001)
Tuberculosis poses a significant threat to mankind. Multidrug-resistant strains are on the rise, and Mycobacterium tuberculosis infection is often associated with human immunodeficiency virus infection. Satisfactory control of tuberculosis can only be achieved using a highly efficacious vaccine. Tuberculosis is particularly challenging for the immune system. The intracellular location of the pathogen shields it from antibodies, and a variety of T-cell subpopulations must be activated to challenge the bacterium's resistance to antibacterial defence mechanisms. A clear understanding of the immune responses that control the pathogen will be important for achieving optimal immunity, and information provided by functional genome analysis of M. tuberculosis will be vital in the design of a future vaccine.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; BCG Vaccine; Mice; Disease Models, Animal; Models, Immunological; T-Lymphocytes

Tuberculosis - Pai, Madhukar; Behr, Marcel A.; Dowdy, David; Dheda, Keertan; Divangahi, Maziar; Boehme, Catharina C.; Ginsberg, Ann; Swaminathan, Soumya; Spigelman, Melvin; Getahun, Haileyesus; Menzies, Dick; Raviglione, Mario (Nature Reviews. Disease Primers, 2016)
Tuberculosis (TB) is an airborne infectious disease caused by organisms of the Mycobacterium tuberculosis complex. Although primarily a pulmonary pathogen, M. tuberculosis can cause disease in almost any part of the body. Infection with M. tuberculosis can evolve from containment in the host, in which the bacteria are isolated within granulomas (latent TB infection), to a contagious state, in which the patient will show symptoms that can include cough, fever, night sweats and weight loss. Only active pulmonary TB is contagious. In many low-income and middle-income countries, TB continues to be a major cause of morbidity and mortality, and drug-resistant TB is a major concern in many settings. Although several new TB diagnostics have been developed, including rapid molecular tests, there is a need for simpler point-of-care tests. Treatment usually requires a prolonged course of multiple antimicrobials, stimulating efforts to develop shorter drug regimens. Although the Bacillus Calmette-Guérin (BCG) vaccine is used worldwide, mainly to prevent life-threatening TB in infants and young children, it has been ineffective in controlling the global TB epidemic. Thus, efforts are underway to develop newer vaccines with improved efficacy. New tools as well as improved programme implementation and financing are necessary to end the global TB epidemic by 2035.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Antitubercular Agents; BCG Vaccine

Dissecting the mycobacterial cell envelope and defining the composition of the native mycomembrane - Chiaradia, Laura; Lefebvre, Cyril; Parra, Julien; Marcoux, Julien; Burlet-Schiltz, Odile; Etienne, Gilles; Tropis, Maryelle; Daffé, Mamadou (Scientific Reports, 2017)
The mycobacterial envelope is unique, containing the so-called mycomembrane (MM) composed of very-long chain fatty acids, mycolic acids (MA). Presently, the molecular composition of the MM remains unproven, due to the diversity of methods used for determining its composition. The plasma membranes (PM) and the native MM-containing cell walls (MMCW) of two rapid-growing mycobacterial species, Mycobacterium aurum and M. smegmatis, were isolated from their cell lysates by differential ultracentrifugation. Transmission electron microscopy and biochemical analyses demonstrated that the two membranes were virtually pure. Bottom-up quantitative proteomics study indicated a different distribution of more than 2,100 proteins between the PM and MMCW. Among these, the mannosyltransferase PimB, galactofuranosyltransferase GlfT2, Cytochrome p450 and ABC transporter YjfF, were most abundant in the PM, which also contain lipoglycans, phospholipids, including phosphatidylinositol mannosides, and only a tiny amount of other glycolipids. Antigen85 complex proteins, porins and the putative transporters MCE protein family were mostly found in MMCW fraction that contains MA esterifying arabinogalactan, constituting the inner leaflet of MM. Glycolipids, phospholipids and lipoglycans, together with proteins, presumably composed the outer leaflet of the MM, a lipid composition that differs from that deduced from the widely used extraction method of mycobacterial cells with dioctylsulfosuccinate sodium.
Keywords: Bacterial Proteins; Membrane Proteins; Cell Membrane; Mycobacterium; Cell Wall; Biomarkers; Lipopolysaccharides; Membrane Lipids; Models, Biological; Multienzyme Complexes; NADH, NADPH Oxidoreductases; Proteomics

How sisters grow apart: mycobacterial growth and division - Kieser, Karen J.; Rubin, Eric J. (Nature Reviews. Microbiology, 2014)
Mycobacterium tuberculosis, which is the aetiological agent of tuberculosis, owes much of its success as a pathogen to its unique cell wall and unusual mechanism of growth, which facilitate its adaptation to the human host and could have a role in clinical latency. Asymmetric growth and division increase population heterogeneity, which may promote antibiotic tolerance and the fitness of single cells. In this Review, we describe the unusual mechanisms of mycobacterial growth, cell wall biogenesis and division, and discuss how these processes might affect the survival of M. tuberculosis in vivo and contribute to the persistence of infection.
Keywords: Mycobacterium tuberculosis; Mycobacterium; Cell Wall; Cell Division; Peptidoglycan

Morphological characterization of Mycobacterium tuberculosis in a MODS culture for an automatic diagnostics through pattern recognition - Alva, Alicia; Aquino, Fredy; Gilman, Robert H.; Olivares, Carlos; Requena, David; Gutiérrez, Andrés H.; Caviedes, Luz; Coronel, Jorge; Larson, Sandra; Sheen, Patricia; Moore, David A. J.; Zimic, Mirko (PloS One, 2013)
Tuberculosis control efforts are hampered by a mismatch in diagnostic technology: modern optimal diagnostic tests are least available in poor areas where they are needed most. Lack of adequate early diagnostics and MDR detection is a critical problem in control efforts. The Microscopic Observation Drug Susceptibility (MODS) assay uses visual recognition of cording patterns from Mycobacterium tuberculosis (MTB) to diagnose tuberculosis infection and drug susceptibility directly from a sputum sample in 7-10 days with a low cost. An important limitation that laboratories in the developing world face in MODS implementation is the presence of permanent technical staff with expertise in reading MODS. We developed a pattern recognition algorithm to automatically interpret MODS results from digital images. The algorithm using image processing, feature extraction and pattern recognition determined geometrical and illumination features used in an object-model and a photo-model to classify TB-positive images. 765 MODS digital photos were processed. The single-object model identified MTB (96.9% sensitivity and 96.3% specificity) and was able to discriminate non-tuberculous mycobacteria with a high specificity (97.1% M. avium, 99.1% M. chelonae, and 93.8% M. kansasii). The photo model identified TB-positive samples with 99.1% sensitivity and 99.7% specificity. This algorithm is a valuable tool that will enable automatic remote diagnosis using Internet or cellphone telephony. The use of this algorithm and its further implementation in a telediagnostics platform will contribute to both faster TB detection and MDR TB determination leading to an earlier initiation of appropriate treatment.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Algorithms; Antitubercular Agents; Bacteriological Techniques; Microbial Sensitivity Tests; Microscopy; Pattern Recognition, Automated; Sensitivity and Specificity

Human and animal infections with Mycobacterium microti, Scotland - Xavier Emmanuel, Francis; Seagar, Amie-Louise; Doig, Christine; Rayner, Alan; Claxton, Pauline; Laurenson, Ian (Emerging Infectious Diseases, 2007)
During 1994-2005, we isolated Mycobacterium microti from 5 animals and 4 humans. Only 1 person was immunocompromised. Spoligotyping showed 3 patterns: vole type, llama type, and a new variant llama type.
Keywords: Humans; Animals; Anti-Bacterial Agents; Mycobacterium; Female; Adult; Male; Middle Aged; Aged; Polymorphism, Restriction Fragment Length; Camelids, New World; Cats; Drug Resistance; Ferrets; Mustelidae; Mycobacterium Infections, Nontuberculous; Scotland

Two cases of Mycobacterium microti derived tuberculosis in HIV-negative immunocompetent patients - Niemann, S.; Richter, E.; Dalügge-Tamm, H.; Schlesinger, H.; Graupner, D.; Königstein, B.; Gurath, G.; Greinert, U.; Rüsch-Gerdes, S. (Emerging Infectious Diseases, 2000)
We describe two cases of Mycobacterium microti infection causing pulmonary tuberculosis (TB) in HIV-seronegative immunocompetent patients in Germany. The isolates were identified as M. microti of the llama and vole types, according to spoligotype patterns. Our data demonstrate that M. microti can cause severe pulmonary TB in immunocompetent patients.
Keywords: Humans; Mycobacterium; Tuberculosis, Pulmonary; Antitubercular Agents; Male; Middle Aged; Germany; HIV Seronegativity; Immunocompetence; Microbial Sensitivity Tests; Radiography

Diagnosis of Mycobacterium microti infections among humans by using novel genetic markers - van Soolingen, D.; van der Zanden, A. G.; de Haas, P. E.; Noordhoek, G. T.; Kiers, A.; Foudraine, N. A.; Portaels, F.; Kolk, A. H.; Kremer, K.; van Embden, J. D. (Journal of Clinical Microbiology, 1998)
As a result of DNA typing of Mycobacterium microti isolates from animals in the United Kingdom and The Netherlands, we diagnosed four human M. microti infections. These are the first M. microti infections among humans to be reported. Three of the patients were immunocompromised and suffered from generalized forms of tuberculosis. The fourth patient was a 34-year-old immunocompetent male with a persistent cough and undefined X-ray abnormalities. Two of the M. microti infections were recognized by their IS6110 restriction fragment length polymorphism (RFLP) patterns, which showed a high degree of similarity with those of M. microti strains isolated from a pig and a ferret in The Netherlands. The two other human M. microti infections were recognized by using the recently developed DNA fingerprinting method, "spoligotyping," directly on clinical material. All M. microti isolates from the United Kingdom and The Netherlands were found to contain an exceptionally short genomic direct repeat region, resulting in identical two-spacer sequence reactions in spoligotyping. In contrast, the highly similar IS6110 RFLP patterns of the vole strains from the United Kingdom differed considerably from the RFLPs of all M. microti strains isolated in The Netherlands, suggesting that geographic isolation led to divergent strains in the United Kingdom and on the continent.
Keywords: DNA, Bacterial; Humans; Animals; Tuberculosis; Mycobacterium; Polymerase Chain Reaction; Mice; Adult; Male; Bacterial Typing Techniques; Child; DNA Fingerprinting; Genetic Markers; Immunocompromised Host; Netherlands; Polymorphism, Restriction Fragment Length

Overview and phylogeny of Mycobacterium tuberculosis complex organisms: implications for diagnostics and legislation of bovine tuberculosis - Rodriguez-Campos, Sabrina; Smith, Noel H.; Boniotti, Maria B.; Aranaz, Alicia (Research in Veterinary Science, 2014)
Members of the Mycobacterium tuberculosis complex (MTBC) cause a serious disease with similar pathology, tuberculosis; in this review, bovine tuberculosis will be considered as disease caused by any member of the MTBC in bovids. Bovine tuberculosis is responsible for significant economic loss due to costly eradication programs and trade limitations and poses a threat to both endangered and protected species as well as to public health. We here give an overview on all members of the MTBC, focusing on their isolation from different animal hosts. We also review the recent advances made in elucidating the evolutionary and phylogenetic relationships of members of the MTBC. Because the nomenclature of the MTBC is controversial, its members have been considered species, subspecies or ecotypes, this review discusses the possible implications for diagnostics and the legal consequences of naming of new species.
Keywords: Mycobacterium tuberculosis; Animals; Cattle; Phylogeny; Mycobacterium bovis; Bovine tuberculosis; Europe; Legislation; Legislation, Veterinary; Mycobacterium caprae; Mycobacterium tuberculosis complex; Phenotype; Terminology as Topic; Tuberculosis, Bovine

Virulence factors of the Mycobacterium tuberculosis complex - PubMed

INS. Instituto Nacional de Salud. Boletín Informativo Semanal Semana Epi : 46. 2022.

Tuberculosis - OPS/OMS | Organización Panamericana de la Salud
La tuberculosis (TB) es una enfermedad infecciosa que suele afectar a los pulmones y es causada por una bacteria (Mycobacterium tuberculosis). Se transmite de una persona a otra a través de gotitas de aerosol suspendidas en el aire expulasadas por personas con enfermedad pulmonar activa. La infección por M. tuberculosis suele ser asintomática en personas sanas, dado que su sistema inmunitario actúa formando una barrera alrededor de la bacteria.

Towards the development of a fully protective Plasmodium falciparum antimalarial vaccine - Patarroyo, Manuel E.; Bermúdez, Adriana; Moreno-Vranich, Armando (Expert Review of Vaccines, 2012)
If ever there were a truism then it would be that a completely protective Plasmodium falciparum malaria vaccine is desperately needed. Our institute has devoted all its efforts during the last 30 years to developing a fully protective, minimal subunit-based, multiepitope, multistage (targeting sporozoite and merozoite proteins), chemically synthesized antimalarial vaccine, given that peptides with high binding activity to their corresponding host cells (liver cells or red blood cells) form the springboard for vaccine design. However, such conserved high activity binding peptides have to be specifically modified to render them into highly immunogenic and protection-inducing peptides since they are immunologically silent. These modifications, analyzed at the 3D structural level by (1)H-NMR, allow them a better fit into the MHC II-peptide-T-cell receptor complex to induce an appropriate immune response, providing a rational and logical approach (analyzed at the single atom level) for vaccine development, particularly in the field of malaria.
Keywords: Humans; Protein Conformation; Drug Discovery; Vaccines, Subunit; Magnetic Resonance Spectroscopy; Malaria Vaccines; Malaria, Falciparum; Plasmodium falciparum

Structural and immunological principles leading to chemically synthesized, multiantigenic, multistage, minimal subunit-based vaccine development - Patarroyo, Manuel Elkin; Bermúdez, Adriana; Patarroyo, Manuel Alfonso (Chemical Reviews, 2011)
Keywords: Humans; Models, Molecular; Immunization; Vaccines; Vaccines, Subunit

In vitro mycobacterial growth inhibition assays: A tool for the assessment of protective immunity and evaluation of tuberculosis vaccine efficacy - Tanner, Rachel; O'Shea, Matthew K.; Fletcher, Helen A.; McShane, Helen (Vaccine, 2016)
Tuberculosis (TB) continues to pose a serious global health threat, and the current vaccine, BCG, has variable efficacy. However, the development of a more effective vaccine is severely hampered by the lack of an immune correlate of protection. Candidate vaccines are currently evaluated using preclinical animal models, but experiments are long and costly and it is unclear whether the outcomes are predictive of efficacy in humans. Unlike measurements of single immunological parameters, mycobacterial growth inhibition assays (MGIAs) represent an unbiased functional approach which takes into account a range of immune mechanisms and their complex interactions. Such a controlled system offers the potential to evaluate vaccine efficacy and study mediators of protective immunity against Mycobacterium tuberculosis (M.tb). This review discusses the underlying principles and relative merits and limitations of the different published MGIAs, their demonstrated abilities to measure mycobacterial growth inhibition and vaccine efficacy, and what has been learned about the immune mechanisms involved.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Vaccine; Bacteriological Techniques; Immunity; MGIA; Mycobacterial growth inhibition assay

Mycobacterial growth inhibition in murine splenocytes as a surrogate for protection against Mycobacterium tuberculosis (M. tb) - Marsay, Leanne; Matsumiya, Magali; Tanner, Rachel; Poyntz, Hazel; Griffiths, Kristin L.; Stylianou, Elena; Marsh, Philip D.; Williams, Ann; Sharpe, Sally; Fletcher, Helen; McShane, Helen (Tuberculosis (Edinburgh, Scotland), 2013)
Development of an improved vaccine against tuberculosis (TB) is hindered by the lack of a surrogate of protection. Efficacy of new TB vaccines in humans can only be evaluated by expensive and time consuming efficacy trials within TB endemic areas. It is critical that vaccines with the greatest potential to protect are selected for these trials. Mycobacterial growth inhibition assays (MGIAs) have been developed with the hope that these in-vitro functional assays will correlate with protection, which could aid in the selection of the best vaccine candidates. The present study describes the use of the BACTEC system to perform MGIAs in mice. We demonstrate reproducible mycobacterial growth inhibition in splenocytes from BCG immunised mice compared with unimmunised mice (P < 0.023), which corresponded with in-vivo efficacy against Mycobacterium tuberculosis (M. tb) challenge. Microarray data showed extensive differential gene expression in splenocyte responses to ex-vivo BCG stimulation between unimmunised and BCG-immunised mice. TH1 responses, including IFN-γ, nitric oxide synthase (NOS2) and Interleukin -17 (IL-17) expression were enhanced in BCG immunised mice, indicating a possible mechanism for mycobacterial growth inhibition. Further investigation into whether the BACTEC MGIA can be used as a surrogate of protection in humans and preclinical animal models is now warranted.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Vaccine; Cells, Cultured; BCG Vaccine; Mice; Disease Models, Animal; Female; Cytokines; Mice, Inbred C57BL; Spleen; Mycobacterium bovis; BCG; Colony Count, Microbial; Gene expression; Gene Expression Regulation; In-vitro assay; Inflammation Mediators

Optimisation of a murine splenocyte mycobacterial growth inhibition assay using virulent Mycobacterium tuberculosis - Jensen, Christina; Lindebo Holm, Line; Svensson, Erik; Aagaard, Claus; Ruhwald, Morten (Scientific Reports, 2017)
In the absence of a validated correlate of protection or robust animal models for human tuberculosis, Mycobacterial growth inhibition assays (MGIAs) aim to assess vaccines ability to inhibit mycobacterial growth in-vitro. We optimised a reproducible murine splenocyte MGIA based on in-vitro infection with ﻿virulent Mycobacterium tuberculosis (M.tb) Erdman. We identified splenocyte viability as a problem in state-of-art MGIA protocols, which can be improved by simple changes in culture conditions (viability increase from 21% to 46% at last day of culture). The growth inhibitory potential in mice immunised with either BCG, H56:CAF01 or H56:CAF01 administered side-by-side with BCG was significantly better compared to placebo in all groups (0.3 log10 CFU [±0.2, p = 0.049], 0.5 [±0.2, p = 0.016] and 0.6 [±0.1, p = 0.0007], respectively) corresponding to the levels of in-vivo protection. Unexpectedly the CAF01 adjuvant control group also induced significant growth inhibition of 0.3 log10 CFU (±0.2, p = 0.047). Finally, we explored vaccine-associated T cell effector functions. Despite presence of high levels of vaccine-specific T cells, we found no increase in CD4+ T cell number or cytokine expression profile, nor a difference in cytokine levels in the supernatant after four days culture with or without M.tb. Spontaneous IFN-γ release correlated with growth inhibition levels (p = 0.02), however the cellular source was not found.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Mice; Female; Virulence; Cytokines; T-Lymphocytes; Spleen; Mycobacterium bovis; Vaccination

"The Impact of Mycobacterium tuberculosis Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" - Meeting report - Boggiano, Cesar; Eichelberg, Katrin; Ramachandra, Lakshmi; Shea, Jaqueline; Ramakrishnan, Lalita; Behar, Samuel; Ernst, Joel D.; Porcelli, Steven A.; Maeurer, Markus; Kornfeld, Hardy (Vaccine, 2017)
Tuberculosis (TB) is the major cause of death from infectious diseases around the world, particularly in HIV infected individuals. TB vaccine design and development have been focused on improving Bacille Calmette-Guérin (BCG) and evaluating recombinant and viral vector expressed Mycobacterium tuberculosis (Mtb) proteins, for boosting BCG-primed immunity, but these approaches have not yet yielded significant improvements over the modest effects of BCG in protecting against infection or disease. On March 7-8, 2016, the National Institute of Allergy and Infectious Diseases (NIAID) convened a workshop on "The Impact of Mtb Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" with the goal of defining immune mechanisms that could be targeted through novel research approaches, to inform vaccine design and immune therapeutic interventions for prevention of TB. The workshop addressed early infection events, the impact of Mtb evolution on the development and maintenance of an adaptive immune response, and the factors that influence protection against and progression to active disease. Scientific gaps and areas of study to revitalize and accelerate TB vaccine design were discussed and prioritized. These included a comprehensive evaluation of innate and Mtb-specific adaptive immune responses in the lung at different stages of disease; determining the role of B cells and antibodies (Abs) during Mtb infection; development of better assays to measure Mtb burden following exposure, infection, during latency and after treatment, and approaches to improving current animal models to study Mtb immunogenicity, TB disease and transmission.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; Vaccine; Immune evasion; Immune Evasion; Drug Discovery

Evasion of Innate and Adaptive Immunity by Mycobacterium tuberculosis - Goldberg, Michael F.; Saini, Neeraj K.; Porcelli, Steven A. (Microbiology Spectrum, 2014)
Through thousands of years of reciprocal coevolution, Mycobacterium tuberculosis has become one of humanity's most successful pathogens, acquiring the ability to establish latent or progressive infection and persist even in the presence of a fully functioning immune system. The ability of M. tuberculosis to avoid immune-mediated clearance is likely to reflect a highly evolved and coordinated program of immune evasion strategies that interfere with both innate and adaptive immunity. These include the manipulation of their phagosomal environment within host macrophages, the selective avoidance or engagement of pattern recognition receptors, modulation of host cytokine production, and the manipulation of antigen presentation to prevent or alter the quality of T-cell responses. In this article we review an extensive array of published studies that have begun to unravel the sophisticated program of specific mechanisms that enable M. tuberculosis and other pathogenic mycobacteria to persist and replicate in the face of considerable immunological pressure from their hosts. Unraveling the mechanisms by which M. tuberculosis evades or modulates host immune function is likely to be of major importance for the development of more effective new vaccines and targeted immunotherapy against tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Adaptive Immunity; Immunity, Innate; Phagosomes; Immune Evasion

Molecular basis of mycobacterial survival in macrophages - Awuh, Jane Atesoh; Flo, Trude Helen (Cellular and molecular life sciences: CMLS, 2017)
Macrophages play an essential role in the immune system by ingesting and degrading invading pathogens, initiating an inflammatory response and instructing adaptive immune cells, and resolving inflammation to restore homeostasis. More interesting is the fact that some bacteria have evolved to use macrophages as a natural habitat and tools of spread in the host, e.g., Mycobacterium tuberculosis (Mtb) and some non-tuberculous mycobacteria (NTM). Mtb is considered one of humanity's most successful pathogens and is the causal agent of tuberculosis, while NTMs cause opportunistic infections all of which are of significant public health concern. Here, we describe mechanisms by which intracellular pathogens, with an emphasis on mycobacteria, manipulate macrophage functions to circumvent killing and live inside these cells even under considerable immunological pressure. Such macrophage functions include the selective evasion or engagement of pattern recognition receptors, production of cytokines, reactive oxygen and nitrogen species, phagosome maturation, as well as other killing mechanisms like autophagy and cell death. A clear understanding of host responses elicited by a specific pathogen and strategies employed by the microbe to evade or exploit these is of significant importance for the development of effective vaccines and targeted immunotherapy against persistent intracellular infections like tuberculosis.
Keywords: Humans; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Mycobacterium; Immune evasion; Inflammatory signaling; Intracellular pathogens; Microbial Viability; Phagocytosis; Phagosome maturation; Phagosomes

Mycobacterium tuberculosis: ecology and evolution of a human bacterium - Bañuls, Anne-Laure; Sanou, Adama; Van Anh, Nguyen Thi; Godreuil, Sylvain (Journal of Medical Microbiology, 2015)
Some species of the Mycobacterium tuberculosis complex (MTBC), particularly Mycobacterium tuberculosis, which causes human tuberculosis (TB), are the first cause of death linked to a single pathogen worldwide. In the last decades, evolutionary studies have much improved our knowledge on MTBC history and have highlighted its long co-evolution with humans. Its ability to remain latent in humans, the extraordinary proportion of asymptomatic carriers (one-third of the entire human population), the deadly epidemics and the observed increasing level of resistance to antibiotics are proof of its evolutionary success. Many MTBC molecular signatures show not only that these bacteria are a model of adaptation to humans but also that they have influenced human evolution. Owing to the unbalance between the number of asymptomatic carriers and the number of patients with active TB, some authors suggest that infection by MTBC could have a protective role against active TB disease and also against other pathologies. However, it would be inappropriate to consider these infectious pathogens as commensals or symbionts, given the level of morbidity and mortality caused by TB.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Biological Evolution; Phylogeny

Immune complex-induced apoptosis and concurrent immune complex clearance are anti-inflammatory neutrophil functions - Karmakar, Utsa; Chu, Julia Y.; Sundaram, Kruthika; Astier, Anne L.; Garside, Hannah; Hansen, Carsten G.; Dransfield, Ian; Vermeren, Sonja (Cell Death & Disease, 2021)
Persistent neutrophilic inflammation drives host damage in autoimmune diseases that are characterized by abundant immune complexes. Insoluble immune complexes (iICs) potently activate pro-inflammatory neutrophil effector functions. We and others have shown that iICs also promote resolution of inflammation via stimulation of neutrophil apoptosis. We demonstrate here that iICs trigger FcγRIIa-dependent neutrophil macropinocytosis, leading to the rapid uptake, and subsequent degradation of iICs. We provide evidence that concurrent iIC-induced neutrophil apoptosis is distinct from phagocytosis-induced cell death. First, uptake of iICs occurs by FcγRII-stimulated macropinocytosis, rather than phagocytosis. Second, production of reactive oxygen species, but not iIC-internalization is a pre-requisite for iIC-induced neutrophil apoptosis. Our findings identify a previously unknown mechanism by which neutrophils can remove pro-inflammatory iICs from the circulation. Together iIC clearance and iIC-induced neutrophil apoptosis may act to prevent the potential escalation of neutrophilic inflammation in response to iICs.

Peculiarities of cell death mechanisms in neutrophils - Geering, B.; Simon, H.-U. (Cell Death & Differentiation, 2011)
Analyses of neutrophil death mechanisms have revealed many similarities with other cell types; however, a few important molecular features make these cells unique executors of cell death mechanisms. For instance, in order to fight invading pathogens, neutrophils possess a potent machinery to produce reactive oxygen species (ROS), the phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. Evidence is emerging that these ROS are crucial in the execution of most neutrophil cell death mechanisms. Likewise, neutrophils exhibit many diverse granules that are packed with cytotoxic mediators. Of those, cathepsins were recently shown to activate pro-apoptotic B-cell lymphoma-2 (Bcl-2) family members and caspases, thus acting on apoptosis regulators. Moreover, neutrophils have few mitochondria, which hardly participate in ATP synthesis, as neutrophils gain energy from glycolysis. In spite of relatively low levels of cytochrome c in these cells, the mitochondrial death pathway is functional. In addition to these pecularities defining neutrophil death pathways, neutrophils are terminally differentiated cells, hence they do not divide but undergo apoptosis shortly after maturation. The initial trigger of this spontaneous apoptosis remains to be determined, but may result from low transcription and translation activities in mature neutrophils. Due to the unique biological characteristics of neutrophils, pharmacological intervention of inflammation has revealed unexpected and sometimes disappointing results when neutrophils were among the prime target cells during therapy. In this study, we review the current and emerging models of neutrophil cell death mechanisms with a focus on neutrophil peculiarities.
Keywords: Neutrophils; Cell death

Mycobacterium tuberculosis-Induced Neutrophil Extracellular Traps Activate Human Macrophages - Braian, Clara; Hogea, Valentin; Stendahl, Olle (Journal of Innate Immunity, 2013)
Neutrophils activated by Mycobacterium tuberculosis (Mtb) form neutrophil extracellular traps (NETs), containing DNA and several biologically active cytosolic and granular proteins. These NETs may assist in the innate immune defense against different pathogens. We investigated whether the NET-forming neutrophils mediate an activating signal to macrophages during the early multicellular inflammatory reaction and granuloma formation. Mtb-induced NETs were found to be reactive oxygen species dependent and phagocytosis dependent. A neutrophil elastase inhibitor also delayed NET formation. However, NET formation occurred independently of Mtb-induced apoptosis. We observed close interactions between macrophages and Mtb-activated neutrophils, where macrophages bound and phagocytosed NETs. Significant secretion of the cytokines interleukin (IL)-6, tumor necrosis factor-α, IL-1β and IL-10 were detected from macrophages cocultured with NETs from Mtb-activated but not phorbol myristate acetate-activated neutrophils. NETs binding heat shock protein 72 (Hsp72) or recombinant Hsp72 were able to trigger cytokine release from macrophages. Only Mtb-induced NETs contained Hsp72, suggesting that these NETs can transfer this danger signal to adjacent macrophages. We propose that Hsp72 sequestered in NETs plays an important role in the interaction between neutrophils and macrophages during the early innate immune phase of an Mtb infection. The immunomodulatory role of NETs and proteins derived from them may influence not only chronic inflammation during tuberculosis but also immune regulation and autoimmunity.

Effect of cellular aging on memory T-cell homeostasis - Swain, Arpit C.; Borghans, José A.M.; de Boer, Rob J. (Frontiers in Immunology, 2022)
The fact that T-cell numbers remain relatively stable throughout life, and that T-cell proliferation rates increase during lymphopenia, has led to the consensus that T-cell numbers are regulated in a density-dependent manner. Competition for resources among memory T cells has been proposed to underlie this ‘homeostatic’ regulation. We first review how two classic models of resource competition affect the T-cell receptor (TCR) diversity of the memory T-cell pool. First, ‘global’ competition for cytokines leads to a skewed repertoire that tends to be dominated by the very first immune response. Second, additional ‘cognate’ competition for specific antigens results in a very diverse and stable memory T-cell pool, allowing every antigen to be remembered, which we therefore define as the ‘gold-standard’. Because there is limited evidence that memory T cells of the same specificity compete more strongly with each other than with memory T cells of different specificities, i.e., for ‘cognate’ competition, we investigate whether cellular aging could account for a similar level of TCR diversity. We define cellular aging as a declining cellular fitness due to reduced proliferation. We find that the gradual erosion of previous T-cell memories due to cellular aging allows for better establishment of novel memories and for a much higher level of TCR diversity compared to global competition. A small continual source (either from stem-cell-like memory T-cells or from naive T-cells due to repeated antigen exposure) improves the diversity of the memory T-cell pool, but remarkably, only in the cellular aging model. We further show that the presence of a source keeps the inflation of chronic memory responses in check by maintaining the immune memories to non-chronic antigens. We conclude that cellular aging along with a small source provides a novel and immunologically realistic mechanism to achieve and maintain the ‘gold-standard’ level of TCR diversity in the memory T-cell pool.

Memory T cells: strategies for optimizing tumor immunotherapy - Liu, Qingjun; Sun, Zhongjie; Chen, Ligong (Protein & Cell, 2020)
Several studies have demonstrated that memory T cells including stem cell memory (Tscm) T cells and central memory (Tcm) T cells show superior persistence and antitumor immunity compared with effector memory T (Tem) cells and effector T (Teff) cells. Furthermore, the Tcm/Teff ratio has been reported to be a predictive biomarker of immune responses against some tumors. Thus, a system-level understanding of the mechanisms underlying the differentiation of effector and memory T cells is of increasing importance for developing immunological strategies against various tumors. This review focuses on recent advances in efficacy against tumors, the origin, formation mechanisms of memory T cells, and the role of the gut microbiota in memory T cell formation. Furthermore, we summarize strategies to generate memory T cells in (ex) vivo that, might be applicable in clinical practice.

TCR signal strength controls the differentiation of CD4+ effector and memory T cells - Snook, Jeremy P.; Kim, Chulwoo; Williams, Matthew A. (Science immunology, 2018)
CD4+ T cell responses are composed of heterogeneous TCR signals that influence the acquisition of effector and memory characteristics. We sought to define early TCR-dependent activation events that control T cell differentiation. A polyclonal panel of TCRs specific for the same viral antigen demonstrated substantial variability in TCR signal strength, expression of CD25 and activation of NFAT and NFκB. Following viral infection, strong TCR signals corresponded to Th1 differentiation, whereas Tfh and memory T cell differentiation were most efficient when TCR signals were comparatively lower. We observed substantial heterogeneity in TCR-dependent CD25 expression in vivo, and the vast majority of CD4+ memory T cells were derived from CD25lo effector cells that displayed decreased TCR signaling in vivo. Nevertheless, memory T cells derived from either CD25lo or CD25hi effector cells responded vigorously to rechallenge, indicating that while early clonal differences in CD25 expression predicted memory T cell numbers, they did not predict memory T cell function on a per cell basis. Gene transcription analysis demonstrated expression clustering based on CD25 expression and enrichment of transcripts associated with enhanced Tfh and memory development within CD25lo effector cells. Direct enhancement of TCR signaling via knockdown of SHP-1, a tyrosine phosphatase that suppresses early TCR signaling events, favored the differentiation of Th1 effector and memory cells. We conclude that strong TCR signals during early T cell activation favor terminal Th1 differentiation over long-term Th1 and Tfh memory responses., Strong TCR signals favor the differentiation of short-lived effector Th1 cells over long-lived memory T cells.

Effect of cellular aging on memory T-cell homeostasis - Swain, Arpit C.; Borghans, José A.M.; de Boer, Rob J. (Frontiers in Immunology, 2022)
The fact that T-cell numbers remain relatively stable throughout life, and that T-cell proliferation rates increase during lymphopenia, has led to the consensus that T-cell numbers are regulated in a density-dependent manner. Competition for resources among memory T cells has been proposed to underlie this ‘homeostatic’ regulation. We first review how two classic models of resource competition affect the T-cell receptor (TCR) diversity of the memory T-cell pool. First, ‘global’ competition for cytokines leads to a skewed repertoire that tends to be dominated by the very first immune response. Second, additional ‘cognate’ competition for specific antigens results in a very diverse and stable memory T-cell pool, allowing every antigen to be remembered, which we therefore define as the ‘gold-standard’. Because there is limited evidence that memory T cells of the same specificity compete more strongly with each other than with memory T cells of different specificities, i.e., for ‘cognate’ competition, we investigate whether cellular aging could account for a similar level of TCR diversity. We define cellular aging as a declining cellular fitness due to reduced proliferation. We find that the gradual erosion of previous T-cell memories due to cellular aging allows for better establishment of novel memories and for a much higher level of TCR diversity compared to global competition. A small continual source (either from stem-cell-like memory T-cells or from naive T-cells due to repeated antigen exposure) improves the diversity of the memory T-cell pool, but remarkably, only in the cellular aging model. We further show that the presence of a source keeps the inflation of chronic memory responses in check by maintaining the immune memories to non-chronic antigens. We conclude that cellular aging along with a small source provides a novel and immunologically realistic mechanism to achieve and maintain the ‘gold-standard’ level of TCR diversity in the memory T-cell pool.

Memory T cells: strategies for optimizing tumor immunotherapy - Liu, Qingjun; Sun, Zhongjie; Chen, Ligong (Protein & Cell, 2020)
Several studies have demonstrated that memory T cells including stem cell memory (Tscm) T cells and central memory (Tcm) T cells show superior persistence and antitumor immunity compared with effector memory T (Tem) cells and effector T (Teff) cells. Furthermore, the Tcm/Teff ratio has been reported to be a predictive biomarker of immune responses against some tumors. Thus, a system-level understanding of the mechanisms underlying the differentiation of effector and memory T cells is of increasing importance for developing immunological strategies against various tumors. This review focuses on recent advances in efficacy against tumors, the origin, formation mechanisms of memory T cells, and the role of the gut microbiota in memory T cell formation. Furthermore, we summarize strategies to generate memory T cells in (ex) vivo that, might be applicable in clinical practice.

TCR signal strength controls the differentiation of CD4+ effector and memory T cells - Snook, Jeremy P.; Kim, Chulwoo; Williams, Matthew A. (Science immunology, 2018)
CD4+ T cell responses are composed of heterogeneous TCR signals that influence the acquisition of effector and memory characteristics. We sought to define early TCR-dependent activation events that control T cell differentiation. A polyclonal panel of TCRs specific for the same viral antigen demonstrated substantial variability in TCR signal strength, expression of CD25 and activation of NFAT and NFκB. Following viral infection, strong TCR signals corresponded to Th1 differentiation, whereas Tfh and memory T cell differentiation were most efficient when TCR signals were comparatively lower. We observed substantial heterogeneity in TCR-dependent CD25 expression in vivo, and the vast majority of CD4+ memory T cells were derived from CD25lo effector cells that displayed decreased TCR signaling in vivo. Nevertheless, memory T cells derived from either CD25lo or CD25hi effector cells responded vigorously to rechallenge, indicating that while early clonal differences in CD25 expression predicted memory T cell numbers, they did not predict memory T cell function on a per cell basis. Gene transcription analysis demonstrated expression clustering based on CD25 expression and enrichment of transcripts associated with enhanced Tfh and memory development within CD25lo effector cells. Direct enhancement of TCR signaling via knockdown of SHP-1, a tyrosine phosphatase that suppresses early TCR signaling events, favored the differentiation of Th1 effector and memory cells. We conclude that strong TCR signals during early T cell activation favor terminal Th1 differentiation over long-term Th1 and Tfh memory responses., Strong TCR signals favor the differentiation of short-lived effector Th1 cells over long-lived memory T cells.

Effector and memory T-cell differentiation: implications for vaccine development - Kaech, Susan M.; Wherry, E. John; Ahmed, Raft (Nature Reviews. Immunology, 2002)
Recent work shows that after stimulation with antigen, CD4+ and CD8+ T cells embark on a programme of proliferation that is closely linked with the acquisition of effector functions and leads ultimately to memory-cell formation. Here, we discuss the signals required for commitment to this programme of development and the factors that might influence its progression. Models of the pathways of effector and memory T-cell differentiation are discussed, and we highlight the implications of this new understanding for the optimization of vaccine strategies.
Keywords: Humans; Animals; Cell Differentiation; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; T-Lymphocytes; Immunologic Memory; Vaccines

IL-6: regulator of Treg/Th17 balance - Kimura, Akihiro; Kishimoto, Tadamitsu (European Journal of Immunology, 2010)
IL-6 is a pleiotropic cytokine involved in the physiology of virtually every organ system. Recent studies have demonstrated that IL-6 has a very important role in regulating the balance between IL-17-producing Th17 cells and regulatory T cells (Treg). The two T-cell subsets play prominent roles in immune functions: Th17 cell is a key player in the pathogenesis of autoimmune diseases and protection against bacterial infections, while Treg functions to restrain excessive effector T-cell responses. IL-6 induces the development of Th17 cells from naïve T cells together with TGF-beta; in contrast, IL-6 inhibits TGF-beta-induced Treg differentiation. Dysregulation or overproduction of IL-6 leads to autoimmune diseases such as multiple sclerosis (MS) and rheumatoid arthritis (RA), in which Th17 cells are considered to be the primary cause of pathology. Given the critical role of IL-6 in altering the balance between Treg and Th17 cells, controlling IL-6 activities is potentially an effective approach in the treatment of various autoimmune and inflammatory diseases. Here, we review the role of IL-6 in regulating Th17/Treg balance and describe the critical functions of IL-6 and Th17 in immunity and immune-pathology.
Keywords: Humans; Animals; Cell Differentiation; Immunomodulation; T-Lymphocytes, Helper-Inducer; Interleukin-17; T-Lymphocytes, Regulatory; Autoimmune Diseases; Interleukin-6; Transforming Growth Factor beta; Homeostasis; Bacterial Infections

Redressing the interactions between stem cells and immune system in tissue regeneration - Fang, Jiankai; Feng, Chao; Chen, Wangwang; Hou, Pengbo; Liu, Zhanhong; Zuo, Muqiu; Han, Yuyi; Xu, Chenchang; Melino, Gerry; Verkhratsky, Alexei; Wang, Ying; Shao, Changshun; et al. (Biology Direct, 2021)
Skeletal muscle has an extraordinary regenerative capacity reflecting the rapid activation and effective differentiation of muscle stem cells (MuSCs). In the course of muscle regeneration, MuSCs are reprogrammed by immune cells. In turn, MuSCs confer immune cells anti-inflammatory properties to resolve inflammation and facilitate tissue repair. Indeed, MuSCs can exert therapeutic effects on various degenerative and inflammatory disorders based on their immunoregulatory ability, including effects primed by interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α). At the molecular level, the tryptophan metabolites, kynurenine or kynurenic acid, produced by indoleamine 2,3-dioxygenase (IDO), augment the expression of TNF-stimulated gene 6 (TSG6) through the activation of the aryl hydrocarbon receptor (AHR). In addition, insulin growth factor 2 (IGF2) produced by MuSCs can endow maturing macrophages oxidative phosphorylation (OXPHOS)-dependent anti-inflammatory functions. Herein, we summarize the current understanding of the immunomodulatory characteristics of MuSCs and the issues related to their potential applications in pathological conditions, including COVID-19.
Keywords: Humans; Animals; Macrophages; Cell Differentiation; Mice; Interferon-gamma; Immunomodulation; Inflammation; Tumor Necrosis Factor-alpha; Immune System; COVID-19; Stem Cells; Regeneration; Cell Proliferation; Cell Adhesion Molecules; Immune cells; Indoleamine-Pyrrole 2,3,-Dioxygenase; Insulin-Like Growth Factor II; Kynurenic Acid; Kynurenine; Muscle repair; Muscles; MuSCs; Oxidative Phosphorylation; Receptors, Aryl Hydrocarbon; Tissue regeneration; Tryptophan

TNF-α Coordinates Hematopoietic Stem Cell Survival and Myeloid Regeneration - Yamashita, Masayuki; Passegué, Emmanuelle (Cell Stem Cell, 2019)
Inflammation coordinates tissue regeneration via damaged cell removal and stem cell activation. Hematopoietic stem cells (HSCs) survive inflammatory stress that kills other blood cells, but the mechanisms underlying this effect remain poorly understood. Here, we find that tumor necrosis factor α (TNF-α) acts differently on HSCs and progenitors, thus facilitating hematopoietic clearance and promoting regeneration. We show that while inducing myeloid progenitor apoptosis, TNF-α promotes HSC survival and myeloid differentiation by activating a strong and specific p65-nuclear factor κB (NF-κB)-dependent gene program that primarily prevents necroptosis rather than apoptosis, induces immunomodulatory functions, and poises HSCs for myeloid cell production. These TNF-α-driven mechanisms are critical for HSC response to inflammatory stress but are also hijacked in aged and malignant HSCs. Our results reveal several TNF-α-mediated pro-survival mechanisms unique to HSCs, highlight an important role for necroptosis in HSC killing, and establish TNF-α as a major pro-survival and pro-regeneration factor for HSCs.
Keywords: Humans; Animals; Cell Differentiation; Cell Survival; Mice; Immunomodulation; Mice, Inbred C57BL; Myeloid Cells; Mice, Knockout; Gene Expression Regulation; Apoptosis; Inflammation; Tumor Necrosis Factor-alpha; Hematopoietic Stem Cells; TNF-α; Regeneration; Cell Self Renewal; cIAP2; hematopoietic stem cells; HSCs; inflammation; leukemia; myeloid regeneration; necroptosis; Necroptosis; NF-kappa B; NF-κB; PD-L1; stem cell activation

Wound repair and regeneration - Reinke, J. M.; Sorg, H. (European Surgical Research. Europaische Chirurgische Forschung. Recherches Chirurgicales Europeennes, 2012)
The skin is the biggest organ of the human being and has many functions. Therefore, the healing of a skin wound displays an extraordinary mechanism of cascading cellular functions which is unique in nature. As healing and regeneration processes take place in all parts of the human body, this review focuses on the healing processes of the skin and highlights the classical wound healing phases. While regeneration describes the specific substitution of the tissue, i.e. the superficial epidermis, mucosa or fetal skin, skin repair displays an unspecific form of healing in which the wound heals by fibrosis and scar formation. The first stage of acute wound healing is dedicated to hemostasis and the formation of a provisional wound matrix, which occurs immediately after injury and is completed after some hours. Furthermore, this phase initiates the inflammatory process. The inflammatory phase of the wound healing cascade gets activated during the coagulation phase and can roughly be divided into an early phase with neutrophil recruitment and a late phase with the appearance and transformation of monocytes. In the phase of proliferation the main focus of the healing process lies in the recovering of the wound surface, the formation of granulation tissue and the restoration of the vascular network. Therefore, next to the immigration of local fibroblasts along the fibrin network and the beginning of reepithelialization from the wound edges, neovascularization and angiogenesis get activated by capillary sprouting. The formation of granulation tissue stops through apoptosis of the cells, characterizing a mature wound as avascular as well as acellular. During the maturation of the wound the components of the extracellular matrix undergo certain changes. The physiological endpoint of mammalian wound repair displays the formation of a scar, which is directly linked to the extent of the inflammatory process throughout wound healing.
Keywords: Humans; Inflammation; Regeneration; Blood Coagulation; Cell Proliferation; Cicatrix; Hemostasis; Neovascularization, Physiologic; Skin; Wound Healing

Role of Cardiac Macrophages on Cardiac Inflammation, Fibrosis and Tissue Repair - Lafuse, William P.; Wozniak, Daniel J.; Rajaram, Murugesan V. S. (Cells, 2020)
The immune system plays a pivotal role in the initiation, development and resolution of inflammation following insult or damage to organs. The heart is a vital organ which supplies nutrients and oxygen to all parts of the body. Heart failure (HF) has been conventionally described as a disease associated with cardiac tissue damage caused by systemic inflammation, arrhythmia and conduction defects. Cardiac inflammation and subsequent tissue damage is orchestrated by the infiltration and activation of various immune cells including neutrophils, monocytes, macrophages, eosinophils, mast cells, natural killer cells, and T and B cells into the myocardium. After tissue injury, monocytes and tissue-resident macrophages undergo marked phenotypic and functional changes, and function as key regulators of tissue repair, regeneration and fibrosis. Disturbance in resident macrophage functions such as uncontrolled production of inflammatory cytokines, growth factors and inefficient generation of an anti-inflammatory response or unsuccessful communication between macrophages and epithelial and endothelial cells and fibroblasts can lead to aberrant repair, persistent injury, and HF. Therefore, in this review, we discuss the role of cardiac macrophages on cardiac inflammation, tissue repair, regeneration and fibrosis.
Keywords: Humans; Animals; Macrophages; Cytokines; Inflammation; Arrhythmias, Cardiac; cardiac inflammation; cardiac macrophages; Diabetic Cardiomyopathies; fibrosis; Fibrosis; Heart; Heart Injuries; Homeostasis; Hypertension; Intercellular Signaling Peptides and Proteins; Mitochondria; Myocardium; Regeneration; tissue repair

Inflammatory Cytokines in Cancer: Comprehensive Understanding and Clinical Progress in Gene Therapy - Lan, Tianxia; Chen, Li; Wei, Xiawei (Cells, 2021)
The relationship between chronic inflammation and neoplastic diseases is not fully understood. The inflammatory microenvironment of a tumor is an intricate network that consists of numerous types of cells, cytokines, enzymes and signaling pathways. Recent evidence shows that the crucial components of cancer-related inflammation are involved in a coordinated system to influence the development of cancer, which may shed light on the development of potential anticancer therapies. Since the last century, considerable effort has been devoted to developing gene therapies for life-threatening diseases. When it comes to modulating the inflammatory microenvironment for cancer therapy, inflammatory cytokines are the most efficient targets. In this manuscript, we provide a comprehensive review of the relationship between inflammation and cancer development, especially focusing on inflammatory cytokines. We also summarize the clinical trials for gene therapy targeting inflammatory cytokines for cancer treatment. Future perspectives concerned with new gene-editing technology and novel gene delivery systems are finally provided.

Crystal structure of a superantigen bound to MHC class II displays zinc and peptide dependence - Petersson, K.; Håkansson, M.; Nilsson, H.; Forsberg, G.; Svensson, L. A.; Liljas, A.; Walse, B. (The EMBO journal, 2001)
The three-dimensional structure of a bacterial superantigen, Staphylococcus aureus enterotoxin H (SEH), bound to human major histocompatibility complex (MHC) class II (HLA-DR1) has been determined by X-ray crystallography to 2.6 A resolution (1HXY). The superantigen binds on top of HLA-DR1 in a completely different way from earlier co-crystallized superantigens from S.aureus. SEH interacts with high affinity through a zinc ion with the beta1 chain of HLA-DR1 and also with the peptide presented by HLA-DR1. The structure suggests that all superantigens interacting with MHC class II in a zinc-dependent manner present the superantigen in a common way. This suggests a new model for ternary complex formation with the T-cell receptor (TCR), in which a contact between the TCR and the MHC class II is unlikely.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Protein Structure, Secondary; Models, Molecular; Protein Structure, Tertiary; Protein Conformation; Recombinant Proteins; Crystallography, X-Ray; HLA-DR1 Antigen; Sequence Alignment; Sequence Homology, Amino Acid; Cloning, Molecular; Enterotoxins; Staphylococcus aureus; Superantigens; Zinc; Zinc Fingers

Rethinking peripheral T cell tolerance: checkpoints across a T cell's journey - ElTanbouly, Mohamed A.; Noelle, Randolph J. (Nature Reviews. Immunology, 2021)
Following their exit from the thymus, T cells are endowed with potent effector functions but must spare host tissue from harm. The fate of these cells is dictated by a series of checkpoints that regulate the quality and magnitude of T cell-mediated immunity, known as tolerance checkpoints. In this Perspective, we discuss the mediators and networks that control the six main peripheral tolerance checkpoints throughout the life of a T cell: quiescence, ignorance, anergy, exhaustion, senescence and death. At the naive T cell stage, two intrinsic checkpoints that actively maintain tolerance are quiescence and ignorance. In the presence of co-stimulation-deficient T cell activation, anergy is a dominant hallmark that mandates T cell unresponsiveness. When T cells are successfully stimulated and reach the effector stage, exhaustion and senescence can limit excessive inflammation and prevent immunopathology. At every stage of the T cell's journey, cell death exists as a checkpoint to limit clonal expansion and to terminate unrestrained responses. Here, we compare and contrast the T cell tolerance checkpoints and discuss their specific roles, with the aim of providing an integrated view of T cell peripheral tolerance and fate regulation.
Keywords: Humans; T-Lymphocytes; Immunologic Memory; Apoptosis; Cellular Senescence; Cell Death; Clonal Anergy; Peripheral Tolerance

T cell anergy, exhaustion, senescence, and stemness in the tumor microenvironment - Crespo, Joel; Sun, Haoyu; Welling, Theodore H.; Tian, Zhigang; Zou, Weiping (Current Opinion in Immunology, 2013)
Human tumors progress despite the presence of tumor associated antigen (TAA)-specific T cells. Many different molecular and cellular mechanisms contribute to the failure of T cells to eradicate the tumor. These include immune suppressive networks that impair ongoing T cell function and enable tumor escape. Recent studies have started to reveal the nature of effector T cells in the tumor microenvironment. In this article we discuss T cell anergy, exhaustion, senescence, and stemness, and review the phenotype of dysfunctional T cell subsets and the underlying molecular mechanisms in the tumor microenvironments. We suggest that targeting T cell dysfunctional mechanisms and introducing/promoting T cell stemness are important approaches to treat patients with cancer.
Keywords: Humans; Animals; T-Lymphocytes; Neoplasms; Cellular Senescence; Clonal Anergy; Stem Cells; Tumor Microenvironment

T cell anergy - Schwartz, Ronald H. (Annual Review of Immunology, 2003)
T cell anergy is a tolerance mechanism in which the lymphocyte is intrinsically functionally inactivated following an antigen encounter, but remains alive for an extended period of time in a hyporesponsive state. Models of T cell anergy affecting both CD4(+) and CD8(+) cells fall into two broad categories. One, clonal anergy, is principally a growth arrest state, whereas the other, adaptive tolerance or in vivo anergy, represents a more generalized inhibition of proliferation and effector functions. The former arises from incomplete T cell activation, is mostly observed in previously activated T cells, is maintained by a block in the Ras/MAP kinase pathway, can be reversed by IL-2 or anti-OX40 signaling, and usually does not result in the inhibition of effector functions. The latter is most often initiated in naïve T cells in vivo by stimulation in an environment deficient in costimulation or high in coinhibition. Adaptive tolerance can be induced in the thymus or in the periphery. The cells proliferate and differentiate to varying degrees and then downregulate both functions in the face of persistent antigen. The state involves an early block in tyrosine kinase activation, which predominantly inhibits calcium mobilization, and an independent mechanism that blocks signaling through the IL-2 receptor. Adaptive tolerance reverses in the absence of antigen. Aspects of both of the anergic states are found in regulatory T cells, possibly preventing them from dominating initial immune responses to foreign antigens and shutting down such responses prematurely.
Keywords: Humans; Animals; Mice; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Models, Immunological; T-Lymphocytes; Antigen Presentation; Adoptive Transfer; Antigens, CD; Abatacept; Adaptation, Physiological; Antigens, Differentiation; Clonal Anergy; CTLA-4 Antigen; Immunoconjugates; Intercellular Adhesion Molecule-1

Large-scale in vitro expansion of polyclonal human switched-memory B lymphocytes - PubMed

Evaluation of methods for the prediction of membrane spanning regions - Möller, S.; Croning, M. D.; Apweiler, R. (Bioinformatics (Oxford, England), 2001)
MOTIVATION: A variety of tools are available to predict the topology of transmembrane proteins. To date no independent evaluation of the performance of these tools has been published. A better understanding of the strengths and weaknesses of the different tools would guide both the biologist and the bioinformatician to make better predictions of membrane protein topology. RESULTS: Here we present an evaluation of the performance of the currently best known and most widely used methods for the prediction of transmembrane regions in proteins. Our results show that TMHMM is currently the best performing transmembrane prediction program.
Keywords: Membrane Proteins; Computational Biology; Models, Molecular; Protein Conformation; Software; Solubility; Databases as Topic; Protein Sorting Signals

The role of B cells and humoral immunity in Mycobacterium tuberculosis infection - Kozakiewicz, Lee; Phuah, Jiayao; Flynn, Joanne; Chan, John (Advances in Experimental Medicine and Biology, 2013)
Tuberculosis (TB) remains a serious threat to public health, causing 2 million deaths annually world-wide. The control of TB has been hindered by the requirement of long duration of treatment involving multiple chemotherapeutic agents, the increased susceptibility to Mycobacterium tuberculosis infection in the HIV-infected population, and the development of multi-drug resistant and extensively resistant strains of tubercle bacilli. An efficacious and cost-efficient way to control TB is the development of effective anti-TB vaccines. This measure requires thorough understanding of the immune response to M. tuberculosis. While the role of cell-mediated immunity in the development of protective immune response to the tubercle bacillus has been well established, the role of B cells in this process is not clearly understood. Emerging evidence suggests that B cells and humoral immunity can modulate the immune response to various intracellular pathogens, including M. tuberculosis. These lymphocytes form conspicuous aggregates in the lungs of tuberculous humans, non-human primates, and mice, which display features of germinal center B cells. In murine TB, it has been shown that B cells can regulate the level of granulomatous reaction, cytokine production, and the T cell response. This chapter discusses the potential mechanisms by which specific functions of B cells and humoral immunity can shape the immune response to intracellular pathogens in general, and to M. tuberculosis in particular. Knowledge of the B cell-mediated immune response to M. tuberculosis may lead to the design of novel strategies, including the development of effective vaccines, to better control TB.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Macrophages; Tuberculosis; Mice; Primates; T-Lymphocyte Subsets; Models, Immunological; Immunity, Cellular; Latent Tuberculosis; Receptors, IgG; Lymphocyte Activation; Species Specificity; Germinal Center; Lymphocyte Cooperation; Antigen-Presenting Cells; B-Lymphocyte Subsets; Lymphokines; Tuberculoma

Initiation and regulation of T-cell responses in tuberculosis - Urdahl, K. B.; Shafiani, S.; Ernst, J. D. (Mucosal Immunology, 2011)
Tuberculosis (TB) poses a great challenge to immunologists, as it represents a chronic infection characterized by persistence of the pathogen despite development of antigen-specific immune responses. Among the characteristics of adaptive immune responses to Mycobacterium tuberculosis is a delay in the onset of detectable T-cell responses, in both humans and experimental animals. Recent studies have revealed mechanisms that contribute to this delay, including pathogen inhibition of apoptosis, delayed migration of dendritic cells from the lungs to the local lymph node, and influence of regulatory T cells. In addition, novel features of M. tuberculosis antigen-specific T-cell differentiation have been discovered, which reveal pathways that limit and promote immune control of infection. Taken together, these results highlight the need for additional basic research and provide optimism for the development of TB vaccines with greater efficacy.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Cell Differentiation; Tuberculosis, Pulmonary; Adaptive Immunity; T-Lymphocyte Subsets; Dendritic Cells; Immune Evasion; Apoptosis; T-Lymphocytes, Regulatory; Cell Movement

Towards a systems understanding of MHC class I and MHC class II antigen presentation - Neefjes, Jacques; Jongsma, Marlieke L. M.; Paul, Petra; Bakke, Oddmund (Nature Reviews. Immunology, 2011)
The molecular details of antigen processing and presentation by MHC class I and class II molecules have been studied extensively for almost three decades. Although the basic principles of these processes were laid out approximately 10 years ago, the recent years have revealed many details and provided new insights into their control and specificity. MHC molecules use various biochemical reactions to achieve successful presentation of antigenic fragments to the immune system. Here we present a timely evaluation of the biology of antigen presentation and a survey of issues that are considered unresolved. The continuing flow of new details into our understanding of the biology of MHC class I and class II antigen presentation builds a system involving several cell biological processes, which is discussed in this Review.
Keywords: Humans; Peptide Fragments; Animals; Structure-Activity Relationship; Mice; Models, Immunological; Antigen Presentation; Dendritic Cells; Histocompatibility Antigens Class I; Histocompatibility Antigens Class II; RNA, Small Interfering; Biological Transport; Endoplasmic Reticulum; Genes, MHC Class I; Genes, MHC Class II; Multiprotein Complexes; Polymorphism, Genetic; Proteasome Endopeptidase Complex; Systems Theory

Cellular and Molecular Immunology - 10th Edition

7 - The Genetics of Disorders Affecting the Premature Newborn - Prosnitz, Aaron R.; Gruen, Jeffrey R.; Bhandari, Vineet (Emery and Rimoin's Principles and Practice of Medical Genetics and Genomics (Seventh Edition), 2022)
The pathogenesis of disorders that affect prematurely born infants is complex and likely involves multiple gene–environment interactions. The studies described in this chapter investigated variations in candidate genes in a wide distribution of sample sizes for the six most common disorders of preterm infants: respiratory distress syndrome, bronchopulmonary dysplasia, patent ductus arteriosus, intraventricular hemorrhage, retinopathy of prematurity, and necrotizing enterocolitis. These disorders account for most of the morbidity and mortality due to premature birth. Shared common factors for these disorders of prematurity include those involved in vasculogenesis, inflammation, infection, growth, and protection from reactive oxygen species. Not surprisingly, most of these six common disorders of prematurity have been studied with the same list of genes involved in vascular development, growth and inflammation: ACE, Factor V, Factor XIII, Prothrombin, VEGF, IGF-1R, IL-1β, IL-4Rα, IL-6, IL-10, TNF-α, TNF-β, TGF-β, and surfactant proteins A and B. These studies, while generally underpowered, suggest that variations in these genes contribute to their pathogenesis and suggest shared pathways.
Keywords: BPD; IVH; NEC; PDA; Preterm neonate; RDS; ROP

A self-consistent method for the analysis of protein secondary structure from circular dichroism - Sreerama, N.; Woody, R. W. (Analytical Biochemistry, 1993)
A self-consistent procedure for estimating the secondary structure content from circular dichroism spectra of proteins is presented. In this method the spectrum of the protein to be analyzed is included in the basis set and an initial guess is made for the unknown structure as a first approximation. The resulting matrix equation is solved using the singular value decomposition algorithm and the initial guess is replaced by the solution. The process is repeated until self-consistency is attained. The best features of the variable selection and the locally linearized methods are incorporated in this procedure. We have applied this method to examine the inconsistencies in the CD data, to compare the predictions with different ranges and resolutions of the CD data, and to compare different assignments of secondary structures from X-ray structure analyses in the context of secondary structure predictions. The results are compared using the root mean square differences and correlation coefficients. The results obtained are as good as or better than the previous analyses. For most of the proteins considered the self-consistent solutions obtained with different initial guesses were similar. We find the Kabsch and Sander protein crystal structure analysis to be most suitable for our prediction method.
Keywords: Circular Dichroism; Protein Structure, Secondary; X-Ray Diffraction; Proteins

SignalP 4.0: discriminating signal peptides from transmembrane regions - Petersen, Thomas Nordahl; Brunak, Søren; von Heijne, Gunnar; Nielsen, Henrik (Nature Methods, 2011)
Keywords: Bioinformatics; Proteomic analysis

IMPIPS: The Immune Protection-Inducing Protein Structure Concept in the Search for Steric-Electron and Topochemical Principles for Complete Fully-Protective Chemically Synthesised Vaccine Development - Patarroyo, Manuel Elkin; Bermúdez, Adriana; Alba, Martha Patricia; Vanegas, Magnolia; Moreno-Vranich, Armando; Poloche, Luis Antonio; Patarroyo, Manuel Alfonso (PLOS ONE, 2015)
Determining immune protection-inducing protein structures (IMPIPS) involves defining the stereo-electron and topochemical characteristics which are essential in MHC-p-TCR complex formation. Modified high activity binding peptides (mHABP) were thus synthesised to produce a large panel of IMPIPS measuring 26.5 ±3.5Å between the farthest atoms fitting into Pockets 1 to 9 of HLA-DRβ1* structures. They displayed a polyproline II-like (PPIIL) structure with their backbone O and N atoms orientated to establish H-bonds with specific residues from HLA-DRβ1*-peptide binding regions (PBR). Residues having specific charge and gauche+ orientation regarding p3χ1, p5χ2, and p7χ1 angles determined appropriate rotamer orientation for perfectly fitting into the TCR to induce an appropriate immune response. Immunological assays in Aotus monkeys involving IMPIPS mixtures led to promising results; taken together with the aforementioned physicochemical principles, non-interfering, long-lasting, protection-inducing, multi-epitope, multistage, minimal subunit-based chemically-synthesised peptides can be designed against diseases scourging humankind.
Keywords: Antibodies; Vaccines; Plasmodium; Antigens; Immune response; Monkeys; Parasitic diseases; Vaccine development

Incidencia de tuberculosis en pacientes que reciben fármacos anti-TNF( - Gruss, Ana; Contrera, Mariela; Piñeiro, Natalia; Perna, Abayubá; Gambogi, Rosana; Alemán, Alicia; Correa, Fernando; Albornoz, Henri; Gruss, Ana; Contrera, Mariela; Piñeiro, Natalia; Perna, Abayubá; et al. (Revista Médica del Uruguay, 2020)

Antibody Subclass and Glycosylation Shift Following Effective TB Treatment - Grace, Patricia S.; Dolatshahi, Sepideh; Lu, Lenette L.; Cain, Adam; Palmieri, Fabrizio; Petrone, Linda; Fortune, Sarah M.; Ottenhoff, Tom H. M.; Lauffenburger, Douglas A.; Goletti, Delia; Joosten, Simone A.; Alter, Galit (Frontiers in Immunology, 2021)
With an estimated 25% of the global population infected with Mycobacterium tuberculosis (Mtb), tuberculosis (TB) remains a leading cause of death by infectious diseases. Humoral immunity following TB treatment is largely uncharacterized, and antibody profiling could provide insights into disease resolution. Here we focused on the distinctive TB-specific serum antibody features in active TB disease (ATB) and compared them with latent TB infection (LTBI) or treated ATB (txATB). As expected, di-galactosylated glycan structures (lacking sialic acid) found on IgG-Fc differentiated LTBI from ATB, but also discriminated txATB from ATB. Moreover, TB-specific IgG4 emerged as a novel antibody feature that correlated with active disease, elevated in ATB, but significantly diminished after therapy. These findings highlight 2 novel TB-specific antibody changes that track with the resolution of TB and may provide key insights to guide TB therapy.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Antigens, Bacterial; Immunoglobulin G; Tuberculosis; tuberculosis; Antitubercular Agents; Neutrophils; Female; antibodies; Glycosylation; Immunoglobulin Fc Fragments; Latent Tuberculosis; Male; Polysaccharides; Phagocytosis; Fc-glycosylation; IgG4; Killer Cells, Natural; TB therapy

Antibody Fc Glycosylation Discriminates Between Latent and Active Tuberculosis - Lu, Lenette L.; Das, Jishnu; Grace, Patricia S.; Fortune, Sarah M.; Restrepo, Blanca I.; Alter, Galit (The Journal of Infectious Diseases, 2020)
BACKGROUND: Mycobacterium tuberculosis remains a global health problem and clinical management is complicated by difficulty in discriminating between latent infection and active disease. While M. tuberculosis-reactive antibody levels are heterogeneous, studies suggest that levels of IgG glycosylation differ between disease states. Here we extend this observation across antibody domains and M. tuberculosis specificities to define changes with the greatest resolving power. METHODS: Capillary electrophoretic glycan analysis was performed on bulk non-antigen-specific IgG, bulk Fc domain, bulk Fab domain, and purified protein derivative (PPD)- and Ag85A-specific IgG from subjects with latent (n = 10) and active (n = 20) tuberculosis. PPD-specific isotype/subclass, PPD-specific antibody-dependent phagocytosis, cellular cytotoxicity, and natural killer cell activation were assessed. Discriminatory potentials of antibody features were evaluated individually and by multivariate analysis. RESULTS: Parallel profiling of whole, Fc, and Fab domain-specific IgG glycosylation pointed to enhanced differential glycosylation on the Fc domain. Differential glycosylation was observed across antigen-specific antibody populations. Multivariate modeling highlighted Fc domain glycan species as the top discriminatory features, with combined PPD IgG titers and Fc domain glycans providing the highest classification accuracy. CONCLUSIONS: Differential glycosylation occurs preferentially on the Fc domain, providing significant discriminatory power between different states of M. tuberculosis infection and disease.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Immunoglobulin G; Tuberculosis; tuberculosis; Female; antibodies; Adult; Glycosylation; Immunoglobulin Fc Fragments; Latent Tuberculosis; Male; Middle Aged; Polysaccharides; Adolescent; Aged; Tuberculin; Fc effector function; glycosylation; Acyltransferases; diagnostics; Electrophoresis, Capillary; Immunoglobulin Fab Fragments

Type I and type II Fc receptors regulate innate and adaptive immunity - Pincetic, Andrew; Bournazos, Stylianos; DiLillo, David J.; Maamary, Jad; Wang, Taia T.; Dahan, Rony; Fiebiger, Benjamin-Maximillian; Ravetch, Jeffrey V. (Nature Immunology, 2014)
Antibodies produced in response to a foreign antigen are characterized by polyclonality, not only in the diverse epitopes to which their variable domains bind but also in the various effector molecules to which their constant regions (Fc domains) engage. Thus, the antibody's Fc domain mediates diverse effector activities by engaging two distinct classes of Fc receptors (type I and type II) on the basis of the two dominant conformational states that the Fc domain may adopt. These conformational states are regulated by the differences among antibody subclasses in their amino acid sequence and by the complex, biantennary Fc-associated N-linked glycan. Here we discuss the diverse downstream proinflammatory, anti-inflammatory and immunomodulatory consequences of the engagement of type I and type II Fc receptors in the context of infectious, autoimmune, and neoplastic disorders.
Keywords: Amino Acid Sequence; Humans; Antibodies; Immunoglobulin G; Protein Structure, Tertiary; Protein Conformation; Adaptive Immunity; Immunity, Innate; Glycosylation; Immunoglobulin Fc Fragments; Receptors, IgG; Antigen Presentation; Vaccination; Neoplasms; Autoimmune Diseases

IgG subclasses and allotypes: from structure to effector functions - Vidarsson, Gestur; Dekkers, Gillian; Rispens, Theo (Frontiers in Immunology, 2014)
Of the five immunoglobulin isotypes, immunoglobulin G (IgG) is most abundant in human serum. The four subclasses, IgG1, IgG2, IgG3, and IgG4, which are highly conserved, differ in their constant region, particularly in their hinges and upper CH2 domains. These regions are involved in binding to both IgG-Fc receptors (FcγR) and C1q. As a result, the different subclasses have different effector functions, both in terms of triggering FcγR-expressing cells, resulting in phagocytosis or antibody-dependent cell-mediated cytotoxicity, and activating complement. The Fc-regions also contain a binding epitope for the neonatal Fc receptor (FcRn), responsible for the extended half-life, placental transport, and bidirectional transport of IgG to mucosal surfaces. However, FcRn is also expressed in myeloid cells, where it participates in both phagocytosis and antigen presentation together with classical FcγR and complement. How these properties, IgG-polymorphisms and post-translational modification of the antibodies in the form of glycosylation, affect IgG-function will be the focus of the current review.
Keywords: Fc receptors; genetic; glycosylation; IgG; immunoglobulin G; neonatal Fc receptor; polymorphism

Non-canonical PI3K-Cdc42-Pak-Mek-Erk Signaling Promotes Immune-Complex-Induced Apoptosis in Human Neutrophils - Chu, Julia Y.; Dransfield, Ian; Rossi, Adriano G.; Vermeren, Sonja (Cell Reports, 2016)
Neutrophils are peripheral blood leukocytes that represent the first line of immune cell defense against bacterial and fungal infections but are also crucial players in the generation of the inflammatory response. Many neutrophil cell surface receptors regulate important cellular processes via activation of agonist-activated PI3Ks. We show here that activation of human neutrophils with insoluble immune complexes drives a previously uncharacterized, PI3K-dependent, non-canonical, pro-apoptotic signaling pathway, FcγR-PI3Kβ/δ-Cdc42-Pak-Mek-Erk. This is a rare demonstration of Ras/Raf-independent activation of Erk and of PI3K-mediated activation of Cdc42. In addition, comparative analysis of immune-complex- and fMLF-induced signaling uncovers key differences in pathways used by human and murine neutrophils. The non-canonical pathway we identify in this study may be important for the resolution of inflammation in chronic inflammatory diseases that rely on immune-complex-driven neutrophil activation.
Keywords: Humans; Animals; Mice; Neutrophils; Receptors, IgG; Signal Transduction; Apoptosis; Antigen-Antibody Complex; Neutrophil Activation; Adaptor Proteins, Signal Transducing; Cytoskeletal Proteins; Elafin; Extracellular Signal-Regulated MAP Kinases; MAP Kinase Kinase Kinases; p21-Activated Kinases; rho GTP-Binding Proteins

[Discovery of the neutrophil extracellular traps begins a new stage in the study of neutrophil morphogenesis and function] - Perova, M. D.; Shubich, M. G. (Morfologiia (Saint Petersburg, Russia), 2011)
The purpose of the present review was to analyze the accumulating evidence regarding recently discovered novel defense mechanism of neutrophils - capacity to form neutrophil extracellular traps (NETs). Contact with pathogenic microbes and/or exposure to proinflammatory cytokines trigger the respiratory burst in the neutrophils with a subsequent initiation of a cell death (NETosis) which differs from apoptosis and necrosis. NETs are formed by the fibrils of decondensed chromatin (DNA/ histones), released from the neutrophil, which is closely associated with the antimicrobial proteins of cytoplasmic granules. Due to its three-dimensional structure, NETs are capable of retaining the microorganisms (bacteria, fungi and protozoa), while high local concentration of the antimicrobial substances provides their killing. The review presents the evidence of a potential defensive role of NETs in infectious diseases, traumas and surgical operations, as well as during the early stage of a repair process. Considering the role played by neutrophils in the immune response orientation via pentraxin-3 (PTX3), including the switching to adaptive immunity, it is necessary to study the subsequent interaction of DNA/histone exrtacellular structures with the tissue microenvironment.
Keywords: Humans; Neutrophils; Immunity, Innate; Phagocytosis; Cell Death; Extracellular Space; Morphogenesis

[Neutrophil extracellular traps (NET), consequence of a cellular suicide] - Yam-Puc, Juan Carlos; García-Marín, Liliana; Sánchez-Torres, Luvia Enid (Gaceta Medica De Mexico, 2012)
Recently it was discovered that neutrophils can generate extracellular fibers called NET (neutrophil extracellular traps), which are composed of a skeleton of DNA “decorated” with many cytoplasmic –including enzymes– and nuclear components.The NET are a physical barrier that prevent the spread of microorganisms and facilitate the cell death by promoting a high local concentration of antimicrobial molecules. On the other hand, the fibrous structure limits the damage to the tissue where they are generated by restricting the range of molecules that are released by the neutrophil. This paper describes this new form of cell death and the implications this may have on different diseases.
Keywords: Humans; Neutrophils; Autophagy

M. tuberculosis-Induced Necrosis of Infected Neutrophils Promotes Bacterial Growth Following Phagocytosis by Macrophages - Dallenga, Tobias; Repnik, Urska; Corleis, Björn; Eich, Jacqueline; Reimer, Rudolph; Griffiths, Gareth W.; Schaible, Ulrich E. (Cell Host & Microbe, 2017)
Neutrophils represent the main infected cell population in the lungs of active tuberculosis patients. Efficient removal of infected and dying neutrophils is required to protect the surrounding tissue from bioactive neutrophil molecules and subsequent pathological sequelae. While the removal of apoptotic M. tuberculosis (Mtb)-infected cells, or efferocytosis, is considered beneficial for host defense, little is known about Mtb-infected necrotic neutrophils. We found that Mtb induces necrosis of human neutrophils in an ESX-1-dependent manner, and neutrophil-produced reactive oxygen species (ROS) drive this necrosis. Neutrophil necrosis was required for Mtb growth after uptake of infected neutrophils by human macrophages. Pharmacological inhibition of ROS production could prevent necrosis and restore the capability of macrophages to control Mtb growth, thereby identifying a potential host-directed therapy target. Taken together, necrosis represents the starting point for a vicious cycle including the uptake of infected necrotic cells by other phagocytes, Mtb growth therein, and sustained infection.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Macrophages; tuberculosis; Necrosis; Neutrophils; Coculture Techniques; Adult; Middle Aged; Adolescent; Aged; Phagocytosis; Apoptosis; host-directed therapy; neutrophils; Reactive Oxygen Species; necrosis; macrophages; cell death; efferocytosis; ESAT-6; Primary Cell Culture; respiratory burst; Single-Cell Analysis

Efferocytosis of Apoptotic Neutrophils Enhances Control of Mycobacterium tuberculosis in HIV-Coinfected Macrophages in a Myeloperoxidase-Dependent Manner - Andersson, Anna-Maria; Larsson, Marie; Stendahl, Olle; Blomgran, Robert (Journal of Innate Immunity, 2020)
Tuberculosis remains a big threat, with 1.6 million deaths in 2017, including 0.3 million deaths among patients with HIV. The risk of developing active disease increases considerably during an HIV coinfection. Alveolar macrophages are the first immune cells to encounter the causative agent Mycobacterium tuberculosis, but during the granuloma formation other cells are recruited in order to combat the bacteria. Here, we have investigated the effect of efferocytosis of apoptotic neutrophils by M. tuberculosis and HIV-coinfected macrophages in a human in vitro system. We found that the apo-ptotic neutrophils enhanced the control of M. tuberculosis in single and HIV-coinfected macrophages, and that this was dependent on myeloperoxidase (MPO) and reactive oxygen species in an autophagy-independent manner. We show that MPO remains active in the apoptotic neutrophils and can be harnessed by infected macrophages. In addition, MPO inhibition removed the suppression in M. tuberculosis growth caused by the apoptotic neutrophils. Antimycobacterial components from apoptotic neutrophils could thus increase the microbicidal activity of macrophages during an M. tuberculosis/HIV coinfection. This cooperation between innate immune cells could thereby be a way to compensate for the impaired adaptive immunity against M. tuberculosis seen during a concurrent HIV infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Tuberculosis; Neutrophils; Apoptosis; Coinfection; HIV; HIV-1; Myeloperoxidase; Peroxidase; Reactive oxygen species

Macrophages acquire neutrophil granules for antimicrobial activity against intracellular pathogens - Tan, Belinda H.; Meinken, Christoph; Bastian, Max; Bruns, Heiko; Legaspi, Annaliza; Ochoa, Maria Teresa; Krutzik, Stephan R.; Bloom, Barry R.; Ganz, Tomas; Modlin, Robert L.; Stenger, Steffen (Journal of Immunology (Baltimore, Md.: 1950), 2006)
A key target of many intracellular pathogens is the macrophage. Although macrophages can generate antimicrobial activity, neutrophils have been shown to have a key role in host defense, presumably by their preformed granules containing antimicrobial agents. Yet the mechanism by which neutrophils can mediate antimicrobial activity against intracellular pathogens such as Mycobacterium tuberculosis has been a long-standing enigma. We demonstrate that apoptotic neutrophils and purified granules inhibit the growth of extracellular mycobacteria. Phagocytosis of apoptotic neutrophils by macrophages results in decreased viability of intracellular M. tuberculosis. Concomitant with uptake of apoptotic neutrophils, granule contents traffic to early endosomes, and colocalize with mycobacteria. Uptake of purified granules alone decreased growth of intracellular mycobacteria. Therefore, the transfer of antimicrobial peptides from neutrophils to macrophages provides a cooperative defense strategy between innate immune cells against intracellular pathogens and may complement other pathways that involve delivery of antimicrobial peptides to macrophages.
Keywords: Humans; Mycobacterium tuberculosis; Neutrophils; Biomarkers; Phagocytosis; Phagosomes; Apoptosis; Endosomes; Cytoplasmic Granules; Macrophages, Alveolar; alpha-Defensins; Blood Bactericidal Activity; Extracellular Space; Growth Inhibitors; Intracellular Fluid

M. tuberculosis-Induced Necrosis of Infected Neutrophils Promotes Bacterial Growth Following Phagocytosis by Macrophages - Dallenga, Tobias; Repnik, Urska; Corleis, Björn; Eich, Jacqueline; Reimer, Rudolph; Griffiths, Gareth W.; Schaible, Ulrich E. (Cell Host & Microbe, 2017)
Neutrophils represent the main infected cell population in the lungs of active tuberculosis patients. Efficient removal of infected and dying neutrophils is required to protect the surrounding tissue from bioactive neutrophil molecules and subsequent pathological sequelae. While the removal of apoptotic M. tuberculosis (Mtb)-infected cells, or efferocytosis, is considered beneficial for host defense, little is known about Mtb-infected necrotic neutrophils. We found that Mtb induces necrosis of human neutrophils in an ESX-1-dependent manner, and neutrophil-produced reactive oxygen species (ROS) drive this necrosis. Neutrophil necrosis was required for Mtb growth after uptake of infected neutrophils by human macrophages. Pharmacological inhibition of ROS production could prevent necrosis and restore the capability of macrophages to control Mtb growth, thereby identifying a potential host-directed therapy target. Taken together, necrosis represents the starting point for a vicious cycle including the uptake of infected necrotic cells by other phagocytes, Mtb growth therein, and sustained infection.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Macrophages; tuberculosis; Necrosis; Neutrophils; Coculture Techniques; Adult; Middle Aged; Adolescent; Aged; Phagocytosis; Apoptosis; host-directed therapy; neutrophils; Reactive Oxygen Species; necrosis; macrophages; cell death; efferocytosis; ESAT-6; Primary Cell Culture; respiratory burst; Single-Cell Analysis

Role of neutrophils in tuberculosis: A bird's eye view - Hilda, J. Nancy; Das, Sulochana; Tripathy, Srikanth P.; Hanna, Luke Elizabeth (Innate Immunity, 2020)
Neutrophils are innate immune cells implicated in the process of killing Mycobacterium tuberculosis early during infection. Once the mycobacteria enter the human system, neutrophils sense and engulf them. By secreting bactericidal enzymes and α-defensins like human neutrophil peptides loaded in their granule armory, neutrophils kill the pathogen. Peripheral blood neutrophils secrete a wide range of cytokines like IL-8, IL-1-β and IFN-γ in response to mycobacterial infection. Thus they signal and activate distant immune cells thereby informing them of prevailing infection. The activated monocytes, dendritic cells and T cells further continue the immune response. As a final call, neutrophils release neutrophil extracellular traps in circulation which can trap mycobacteria in patients with active pulmonary tuberculosis. Extensive neutrophilic response is associated with inflammation, pulmonary destruction, and pathology. For example, inappropriate phagocytosis of mycobacteria-infected neutrophils can damage host cells due to necrosis of neutrophils, leading to chronic inflammation and tissue damage. This dual nature of neutrophils makes them double-edged swords during tuberculosis, and hence data available on neutrophil functions against mycobacterium are controversial and non-uniform. This article reviews the role of neutrophils in tuberculosis infection and highlights research gaps that need to be addressed. We focus on our understanding of new research ideologies targeting neutrophils (a) in the early stages of infection for boosting specific immune functions or (b) in the later stages of infection to prevent inflammatory conditions mediated by activated neutrophils. This would plausibly lead to the development of better tuberculosis vaccines and therapeutics in the future.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; tuberculosis; Neutrophils; Cytokines; Immunity, Innate; Phagocytosis; Apoptosis; Neutrophil Activation; macrophages; apoptosis; immune response; Extracellular Traps; alpha-Defensins; phagocytosis

How Neutrophil Extracellular Traps Become Visible - de Buhr, Nicole; von Köckritz-Blickwede, Maren (Journal of Immunology Research, 2016)
Neutrophil extracellular traps (NETs) have been identified as a fundamental innate immune defense mechanism against different pathogens. NETs are characterized as released nuclear DNA associated with histones and granule proteins, which form an extracellular web-like structure that is able to entrap and occasionally kill certain microbes. Furthermore, NETs have been shown to contribute to several noninfectious disease conditions when released by activated neutrophils during inflammation. The identification of NETs has mainly been succeeded by various microscopy techniques, for example, immunofluorescence microscopy, transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Since the last years the development and improvement of new immunofluorescence-based techniques enabled optimized visualization and quantification of NETs. On the one hand in vitro live-cell imaging led to profound new ideas about the mechanisms involved in the formation and functionality of NETs. On the other hand different intravital, in vivo, and in situ microscopy techniques led to deeper insights into the role of NET formation during health and disease. This paper presents an overview of the main used microscopy techniques to visualize NETs and describes their advantages as well as disadvantages.
Keywords: Humans; Microscopy; Neutrophil Activation; DNA; Extracellular Traps; Histones; Microscopy, Electron; Microscopy, Fluorescence

Measuring Cell Death by Propidium Iodide Uptake and Flow Cytometry - Crowley, Lisa C.; Scott, Adrian P.; Marfell, Brooke J.; Boughaba, Jeanne A.; Chojnowski, Grace; Waterhouse, Nigel J. (Cold Spring Harbor Protocols, 2016)
Propidium iodide (PI) is a small fluorescent molecule that binds to DNA but cannot passively traverse into cells that possess an intact plasma membrane. PI uptake versus exclusion can be used to discriminate dead cells, in which plasma membranes become permeable regardless of the mechanism of death, from live cells with intact membranes. PI is excited by wavelengths between 400 and 600 nm and emits light between 600 and 700 nm, and is therefore compatible with lasers and photodetectors commonly available in flow cytometers. This protocol for PI staining can be used to quantitate cell death in most modern research facilities and universities.
Keywords: Humans; Animals; Flow Cytometry; Fluorescent Dyes; Cell Death; Intercalating Agents; Propidium; Staining and Labeling

Mycobacterium tuberculosis promotes apoptosis in human neutrophils by activating caspase-3 and altering expression of Bax/Bcl-xL via an oxygen-dependent pathway - Perskvist, Nasrin; Long, Min; Stendahl, Olle; Zheng, Limin (Journal of Immunology (Baltimore, Md.: 1950), 2002)
In addition to direct bactericidal activities, such as phagocytosis and generation of reactive oxygen species (ROS), neutrophils can regulate the inflammatory response by undergoing apoptosis. We found that infection of human neutrophils with Mycobacterium tuberculosis (Mtb) induced rapid cell death displaying the characteristic features of apoptosis such as morphologic changes, phosphatidylserine exposure, and DNA fragmentation. Both a virulent (H37Rv) and an attenuated (H37Ra) strain of Mtb were equally effective in inducing apoptosis. Pretreatment of neutrophils with antioxidants or an inhibitor of NADPH oxidase markedly blocked Mtb-induced apoptosis but did not affect spontaneous apoptosis. Activation of caspase-3 was evident in neutrophils undergoing spontaneous apoptosis, but it was markedly augmented and accelerated during Mtb-induced apoptosis. The Mtb-induced apoptosis was associated with a speedy and transient increase in expression of Bax protein, a proapoptotic member of the Bcl-2 family, and a more prominent reduction in expression of the antiapoptotic protein Bcl-x(L). Pretreatment with an inhibitor of NADPH oxidase distinctly suppressed the Mtb-stimulated activation of caspase-3 and alteration of Bax/Bcl-x(L) expression in neutrophils. These results indicate that infection with Mtb causes ROS-dependent alteration of Bax/Bcl-x(L) expression and activation of caspase-3, and thereby induces apoptosis in human neutrophils. Moreover, we found that phagocytosis of Mtb-induced apoptotic neutrophils markedly increased the production of proinflammatory cytokine TNF-alpha by human macrophages. Therefore, the ROS-dependent apoptosis in Mtb-stimulated neutrophils may represent an important host defense mechanism aimed at selective removal of infected cells at the inflamed site, which in turn aids the functional activities of local macrophages.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Cells, Cultured; Neutrophils; Virulence; Vaccines, Attenuated; Macrophage Activation; Phagocytosis; Apoptosis; Reactive Oxygen Species; Tumor Necrosis Factor-alpha; Proto-Oncogene Proteins c-bcl-2; Down-Regulation; Enzyme Inhibitors; bcl-2-Associated X Protein; bcl-X Protein; Caspase 3; Caspases; Enzyme Activation; Onium Compounds; Oxygen; Proto-Oncogene Proteins

Human isotype-dependent inhibitory antibody responses against Mycobacterium tuberculosis - Zimmermann, Natalie; Thormann, Verena; Hu, Bo; Köhler, Anne-Britta; Imai-Matsushima, Aki; Locht, Camille; Arnett, Eusondia; Schlesinger, Larry S.; Zoller, Thomas; Schürmann, Mariana; Kaufmann, Stefan He; Wardemann, Hedda (EMBO molecular medicine, 2016)
Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B-cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB-exposed healthcare workers. The data suggest that the acute plasmablast response to MTB originates from reactivated memory B cells and indicates a mucosal origin. Through functional analyses, we identified MTB inhibitory antibodies against mycobacterial antigens including virulence factors that play important roles in host cell infection. The inhibitory activity of anti-MTB antibodies was directly linked to their isotype. Monoclonal as well as purified serum IgA antibodies showed MTB blocking activity independently of Fc alpha receptor expression, whereas IgG antibodies promoted the host cell infection. Together, the data provide molecular insights into the human antibody response to MTB and may thereby facilitate the design of protective vaccination strategies.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; antibodies; Antibodies, Monoclonal; Antibody Formation; B cells; B-Lymphocytes; Immunoglobulin Isotypes; infection; isotype

Human isotype-dependent inhibitory antibody responses against Mycobacterium tuberculosis - Zimmermann, Natalie; Thormann, Verena; Hu, Bo; Köhler, Anne-Britta; Imai-Matsushima, Aki; Locht, Camille; Arnett, Eusondia; Schlesinger, Larry S.; Zoller, Thomas; Schürmann, Mariana; Kaufmann, Stefan He; Wardemann, Hedda (EMBO molecular medicine, 2016)
Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B-cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB-exposed healthcare workers. The data suggest that the acute plasmablast response to MTB originates from reactivated memory B cells and indicates a mucosal origin. Through functional analyses, we identified MTB inhibitory antibodies against mycobacterial antigens including virulence factors that play important roles in host cell infection. The inhibitory activity of anti-MTB antibodies was directly linked to their isotype. Monoclonal as well as purified serum IgA antibodies showed MTB blocking activity independently of Fc alpha receptor expression, whereas IgG antibodies promoted the host cell infection. Together, the data provide molecular insights into the human antibody response to MTB and may thereby facilitate the design of protective vaccination strategies.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; antibodies; Antibodies, Monoclonal; Antibody Formation; B cells; B-Lymphocytes; Immunoglobulin Isotypes; infection; isotype

"The Impact of Mycobacterium tuberculosis Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" - Meeting report - Boggiano, Cesar; Eichelberg, Katrin; Ramachandra, Lakshmi; Shea, Jaqueline; Ramakrishnan, Lalita; Behar, Samuel; Ernst, Joel D.; Porcelli, Steven A.; Maeurer, Markus; Kornfeld, Hardy (Vaccine, 2017)
Tuberculosis (TB) is the major cause of death from infectious diseases around the world, particularly in HIV infected individuals. TB vaccine design and development have been focused on improving Bacille Calmette-Guérin (BCG) and evaluating recombinant and viral vector expressed Mycobacterium tuberculosis (Mtb) proteins, for boosting BCG-primed immunity, but these approaches have not yet yielded significant improvements over the modest effects of BCG in protecting against infection or disease. On March 7-8, 2016, the National Institute of Allergy and Infectious Diseases (NIAID) convened a workshop on "The Impact of Mtb Immune Evasion on Protective Immunity: Implications for TB Vaccine Design" with the goal of defining immune mechanisms that could be targeted through novel research approaches, to inform vaccine design and immune therapeutic interventions for prevention of TB. The workshop addressed early infection events, the impact of Mtb evolution on the development and maintenance of an adaptive immune response, and the factors that influence protection against and progression to active disease. Scientific gaps and areas of study to revitalize and accelerate TB vaccine design were discussed and prioritized. These included a comprehensive evaluation of innate and Mtb-specific adaptive immune responses in the lung at different stages of disease; determining the role of B cells and antibodies (Abs) during Mtb infection; development of better assays to measure Mtb burden following exposure, infection, during latency and after treatment, and approaches to improving current animal models to study Mtb immunogenicity, TB disease and transmission.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; Vaccine; Immune evasion; Immune Evasion; Drug Discovery

Targeting the bacteria-host interface: strategies in anti-adhesion therapy - Krachler, Anne Marie; Orth, Kim (Virulence, 2013)
Bacterial infections are a major cause of morbidity and mortality worldwide and are increasingly problematic to treat due to the rise in antibiotic-resistant strains. It becomes more and more challenging to develop new antimicrobials that are able to withstand the ever-increasing repertoire of bacterial resistance mechanisms. This necessitates the development of alternative approaches to prevent and treat bacterial infections. One of the first steps during bacterial infection is adhesion of the pathogen to host cells. A pathogen's ability to colonize and invade host tissues strictly depends on this process. Thus, interference with adhesion (anti-adhesion therapy) is an efficient way to prevent or treat bacterial infections. As a basis to present different strategies to interfere with pathogen adhesion, this review briefly introduces general concepts of bacterial attachment to host cells. We further discuss advantages and disadvantages of anti-adhesion treatments and issues that are in need of improvement so as to make anti-adhesion compounds a more broadly applicable alternative to conventional antimicrobials.
Keywords: Humans; Host-Pathogen Interactions; Bacterial Adhesion; Anti-Bacterial Agents; Bacterial Vaccines; Bacteria; anti-adhesion treatment; anti-adhesive; antimicrobial therapy; bacterial adhesion; host–pathogen interactions

Association of Human Antibodies to Arabinomannan With Enhanced Mycobacterial Opsonophagocytosis and Intracellular Growth Reduction - Chen, Tingting; Blanc, Caroline; Eder, Anke Z.; Prados-Rosales, Rafael; Souza, Ana Camila Oliveira; Kim, Ryung S.; Glatman-Freedman, Aharona; Joe, Maju; Bai, Yu; Lowary, Todd L.; Tanner, Rachel; Brennan, Michael J.; et al. (The Journal of Infectious Diseases, 2016)
BACKGROUND: The relevance of antibodies (Abs) in the defense against Mycobacterium tuberculosis infection remains uncertain. We investigated the role of Abs to the mycobacterial capsular polysaccharide arabinomannan (AM) and its oligosaccharide (OS) fragments in humans. METHODS: Sera obtained from 29 healthy adults before and after primary or secondary bacillus Calmette-Guerin (BCG) vaccination were assessed for Ab responses to AM via enzyme-linked immunosorbent assays, and to AM OS epitopes via novel glycan microarrays. Effects of prevaccination and postvaccination sera on BCG phagocytosis and intracellular survival were assessed in human macrophages. RESULTS: Immunoglobulin G (IgG) responses to AM increased significantly 4-8 weeks after vaccination (P < .01), and sera were able to opsonize BCG and M. tuberculosis grown in both the absence and the presence of detergent. Phagocytosis and intracellular growth inhibition were significantly enhanced when BCG was opsonized with postvaccination sera (P < .01), and these enhancements correlated significantly with IgG titers to AM (P < .05), particularly with reactivity to 3 AM OS epitopes (P < .05). Furthermore, increased phagolysosomal fusion was observed with postvaccination sera. CONCLUSIONS: Our results provide further evidence for a role of Ab-mediated immunity to tuberculosis and suggest that IgG to AM, especially to some of its OS epitopes, could contribute to the defense against mycobacterial infection in humans.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Protein Binding; Immunoglobulin G; tuberculosis; BCG Vaccine; Adult; Microbial Viability; Phagocytosis; Enzyme-Linked Immunosorbent Assay; antibody-mediated immunity; bacterial capsule; human antibodies; immune response; immunoglobulin; Mannans; Microarray Analysis; Mycobacterium bovis BCG; oligosaccharide; Opsonin Proteins; polysaccharide

Immune protection-inducing protein structures (IMPIPS) against malaria: the weapons needed for beating Odysseus - Patarroyo, Manuel E.; Patarroyo, Manuel A.; Pabón, Laura; Curtidor, Hernando; Poloche, Luis A. (Vaccine, 2015)
The review covers the functional and structural approach followed by our group for more than 34 years in the search for a methodology that allows the rational design of chemically synthesised vaccines. An analogy between Odysseus, the cunning hero of the epic poem Odyssey by Homer, and the elusive Plasmodium parasite has been made, to review our research group's main considerations when developing a rational methodology for designing second generation, modified peptide-based, minimal subunit, multi-antigen, multi-stage, chemically synthesised vaccines against Plasmodium falciparum malaria.
Keywords: Amino Acid Sequence; Humans; Peptides; Vaccines, Synthetic; Protein Conformation; Synthetic peptides; Malaria Vaccines; Malaria, Falciparum; Plasmodium falciparum; Protozoan Proteins; IMPIPS; Life Cycle Stages; Malaria vaccine; Modified peptides

Structural and immunological principles leading to chemically synthesized, multiantigenic, multistage, minimal subunit-based vaccine development - Patarroyo, Manuel Elkin; Bermúdez, Adriana; Patarroyo, Manuel Alfonso (Chemical Reviews, 2011)
Keywords: Humans; Models, Molecular; Immunization; Vaccines; Vaccines, Subunit

Functions of Antibodies - Forthal, Donald N. (Microbiology Spectrum, 2014)
Antibodies can impact pathogens in the presence or in the absence of effector cells or effector molecules such as complement, and experiments can often sort out with precision the mechanisms by which an antibody inhibits a pathogen in vitro. In addition, in vivo models, particularly those engineered to knock in or knock out effector cells or effector molecules, are excellent tools for understanding antibody functions. However, it is highly likely that multiple antibody functions occur simultaneously or sequentially in the presence of an infecting organism in vivo. The most critical incentive for measuring antibody functions is to provide a basis for vaccine development and for the development of therapeutic antibodies. In this respect, some functions, such as virus neutralization, serve to inhibit the acquisition of a pathogen or limit its pathogenesis. However, antibodies can also enhance replication or contribute to pathogenesis. This review emphasizes those antibody functions that are potentially beneficial to the host. In addition, this review will focus on the effects of antibodies on organisms themselves, rather than on the toxins the organisms may produce.
Keywords: Humans; Animals; Antibodies; Communicable Diseases; Vaccines

Beyond binding: antibody effector functions in infectious diseases - Lu, Lenette L.; Suscovich, Todd J.; Fortune, Sarah M.; Alter, Galit (Nature Reviews. Immunology, 2018)
Antibodies play an essential role in host defence against pathogens by recognizing microorganisms or infected cells. Although preventing pathogen entry is one potential mechanism of protection, antibodies can control and eradicate infections through a variety of other mechanisms. In addition to binding and directly neutralizing pathogens, antibodies drive the clearance of bacteria, viruses, fungi and parasites via their interaction with the innate and adaptive immune systems, leveraging a remarkable diversity of antimicrobial processes locked within our immune system. Specifically, antibodies collaboratively form immune complexes that drive sequestration and uptake of pathogens, clear toxins, eliminate infected cells, increase antigen presentation and regulate inflammation. The diverse effector functions that are deployed by antibodies are dynamically regulated via differential modification of the antibody constant domain, which provides specific instructions to the immune system. Here, we review mechanisms by which antibody effector functions contribute to the balance between microbial clearance and pathology and discuss tractable lessons that may guide rational vaccine and therapeutic design to target gaps in our infectious disease armamentarium.
Keywords: Humans; Antibodies; Adaptive Immunity; Immunity, Innate; Antigen Presentation; Inflammation; Antigen-Antibody Complex; Bacterial Toxins; Immunoglobulin Constant Regions; Infections

IFN-γ-independent immune markers of Mycobacterium tuberculosis exposure - Lu, Lenette L.; Smith, Malisa T.; Yu, Krystle K. Q.; Luedemann, Corinne; Suscovich, Todd J.; Grace, Patricia S.; Cain, Adam; Yu, Wen Han; McKitrick, Tanya R.; Lauffenburger, Douglas; Cummings, Richard D.; Mayanja-Kizza, Harriet; et al. (Nature Medicine, 2019)
Exposure to Mycobacterium tuberculosis (Mtb) results in heterogeneous clinical outcomes including primary progressive tuberculosis and latent Mtb infection (LTBI). Mtb infection is identified using the tuberculin skin test and interferon-γ (IFN-γ) release assay IGRA, and a positive result may prompt chemoprophylaxis to prevent progression to tuberculosis. In the present study, we report on a cohort of Ugandan individuals who were household contacts of patients with TB. These individuals were highly exposed to Mtb but tested negative disease by IFN-γ release assay and tuberculin skin test, 'resisting' development of classic LTBI. We show that 'resisters' possess IgM, class-switched IgG antibody responses and non-IFN-γ T cell responses to the Mtb-specific proteins ESAT6 and CFP10, immunologic evidence of exposure to Mtb. Compared to subjects with classic LTBI, 'resisters' display enhanced antibody avidity and distinct Mtb-specific IgG Fc profiles. These data reveal a distinctive adaptive immune profile among Mtb-exposed subjects, supporting an expanded definition of the host response to Mtb exposure, with implications for public health and the design of clinical trials.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Female; Interferon-gamma; Biomarkers; CD4-Positive T-Lymphocytes; Adult; Latent Tuberculosis; Male; Young Adult; Child; Tuberculin Test; Cohort Studies; Interferon-gamma Release Tests; Uganda

IFN-γ-independent immune markers of Mycobacterium tuberculosis exposure - Lu, Lenette L.; Smith, Malisa T.; Yu, Krystle K. Q.; Luedemann, Corinne; Suscovich, Todd J.; Grace, Patricia S.; Cain, Adam; Yu, Wen Han; McKitrick, Tanya R.; Lauffenburger, Douglas; Cummings, Richard D.; Mayanja-Kizza, Harriet; et al. (Nature Medicine, 2019)
Exposure to Mycobacterium tuberculosis (Mtb) results in heterogeneous clinical outcomes including primary progressive tuberculosis and latent Mtb infection (LTBI). Mtb infection is identified using the tuberculin skin test and interferon-γ (IFN-γ) release assay IGRA, and a positive result may prompt chemoprophylaxis to prevent progression to tuberculosis. In the present study, we report on a cohort of Ugandan individuals who were household contacts of patients with TB. These individuals were highly exposed to Mtb but tested negative disease by IFN-γ release assay and tuberculin skin test, 'resisting' development of classic LTBI. We show that 'resisters' possess IgM, class-switched IgG antibody responses and non-IFN-γ T cell responses to the Mtb-specific proteins ESAT6 and CFP10, immunologic evidence of exposure to Mtb. Compared to subjects with classic LTBI, 'resisters' display enhanced antibody avidity and distinct Mtb-specific IgG Fc profiles. These data reveal a distinctive adaptive immune profile among Mtb-exposed subjects, supporting an expanded definition of the host response to Mtb exposure, with implications for public health and the design of clinical trials.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Female; Interferon-gamma; Biomarkers; CD4-Positive T-Lymphocytes; Adult; Latent Tuberculosis; Male; Young Adult; Child; Tuberculin Test; Cohort Studies; Interferon-gamma Release Tests; Uganda

Latently and uninfected healthcare workers exposed to TB make protective antibodies against Mycobacterium tuberculosis - Li, Hao; Wang, Xing-Xing; Wang, Bin; Fu, Lei; Liu, Guan; Lu, Yu; Cao, Min; Huang, Hairong; Javid, Babak (Proceedings of the National Academy of Sciences of the United States of America, 2017)
The role of Igs in natural protection against infection by Mycobacterium tuberculosis (Mtb), the causative agent of TB, is controversial. Although passive immunization with mAbs generated against mycobacterial antigens has shown protective efficacy in murine models of infection, studies in B cell-depleted animals only showed modest phenotypes. We do not know if humans make protective antibody responses. Here, we investigated whether healthcare workers in a Beijing TB hospital-who, although exposed to suprainfectious doses of pathogenic Mtb, remain healthy-make antibody responses that are effective in protecting against infection by Mtb. We tested antibodies isolated from 48 healthcare workers and compared these with 12 patients with active TB. We found that antibodies from 7 of 48 healthcare workers but none from active TB patients showed moderate protection against Mtb in an aerosol mouse challenge model. Intriguingly, three of seven healthcare workers who made protective antibody responses had no evidence of prior TB infection by IFN-γ release assay. There was also good correlation between protection observed in vivo and neutralization of Mtb in an in vitro human whole-blood assay. Antibodies mediating protection were directed against the surface of Mtb and depended on both immune complexes and CD4+ T cells for efficacy. Our results indicate that certain individuals make protective antibodies against Mtb and challenge paradigms about the nature of an effective immune response to TB.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Mice; Disease Models, Animal; Female; antibodies; Adult; Male; Middle Aged; TB; Mice, Inbred BALB C; humoral immunity; immune complex; Mice, Nude; Occupational Exposure; Physicians; TB restrictors

Purified protein derivatives of tuberculin--past, present, and future - Yang, Hongliang; Kruh-Garcia, Nicole A.; Dobos, Karen M. (FEMS immunology and medical microbiology, 2012)
The tuberculin skin test, which involves monitoring the immune reaction to an injection of purified protein derivative (PPD), has been the most widely used method for detecting infection with Mycobacterium tuberculosis since its development in 1930s. Until recently, the molecular composition of PPD was unknown. This thwarted the discovery of improved skin testing reagents and drastically hindered efforts to define the mechanism of action. Proteomic evaluation of PPD combined with a detailed analysis in the guinea pig model of tuberculosis led to further definition of the molecular composition of PPD. This communication reviews the history and current status of PPD, in addition to describing candidate next-generation PPD reagents, based on the use of an individual protein or protein cocktails.
Keywords: Humans; Animals; Tuberculosis Vaccines; Tuberculosis; Guinea Pigs; Tuberculin; Tuberculin Test; History, 20th Century; History, 21st Century

Phage display for epitope determination: a paradigm for identifying receptor-ligand interactions - Rowley, Merrill J.; O'Connor, Karen; Wijeyewickrema, Lakshmi (Biotechnology Annual Review, 2004)
Antibodies that react with many different molecular species of protein and non-protein nature are widely studied in biology and have particular utilities, but the precise epitopes recognized are seldom well defined. The definition of epitopes by X-ray crystallography of the antigen-antibody complex, the gold standard procedure, has shown that most antibody epitopes are conformational and specified by interactions with topographic determinants on the surface of the antigenic molecule. Techniques available for the definition of such epitopes are limited. Phage display using either gene-specific libraries, or random peptide libraries, provides a powerful technique for an approach to epitope identification. The technique can identify amino acids on protein antigens that are critical for antibody binding and, further, the isolation of peptide motifs that are both structural and functional mimotopes of both protein and non-protein antigens. This review discusses techniques used to isolate such mimotopes, to confirm their specificity, and to characterize peptide epitopes. Moreover there are direct practical applications to deriving epitopes or mimotopes by sequence, notably the development of new diagnostic reagents, or therapeutic agonist or antagonist molecules. The techniques developed for mapping of antibody epitopes are applicable to probing the origins of autoimmune diseases and certain cancers by identifying "immunofootprints" of unknown initiating agents, as we discuss herein, and are directly applicable to examination of a wider range of receptor-ligand interactions.
Keywords: Binding Sites; Protein Binding; Receptors, Cell Surface; Ligands; Epitopes; Epitope Mapping; Protein Interaction Mapping; Peptide Library

Updates on antibody functions in Mycobacterium tuberculosis infection and their relevance for developing a vaccine against tuberculosis - Achkar, Jacqueline M.; Prados-Rosales, Rafael (Current Opinion in Immunology, 2018)
A more effective vaccine to control tuberculosis (TB), a major global public health problem, is urgently needed. Current vaccine candidates focus predominantly on eliciting cell-mediated immunity but other arms of the immune system also contribute to protection against TB. We review here recent studies that enhance our current knowledge of antibody-mediated functions against Mycobacterium tuberculosis. These findings, which contribute to the increasing evidence that antibodies have a protective role against TB, include demonstrations that firstly distinct human antibody Fc glycosylation patterns, found in latent M. tuberculosis infection but not in active TB, influence the efficacy of the host to control M. tuberculosis infection, secondly antibody isotype influences human antibody functions, and thirdly that antibodies targeting M. tuberculosis surface antigens are protective. We discuss these findings in the context of TB vaccine development and highlight the need for further research on antibody-mediated immunity in M. tuberculosis infection.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Antigens, Bacterial; Tuberculosis; Glycosylation; Immunity, Humoral; Latent Tuberculosis; Vaccination

B cells and antibodies in the defense against Mycobacterium tuberculosis infection - Achkar, Jacqueline M.; Chan, John; Casadevall, Arturo (Immunological Reviews, 2015)
Better understanding of the immunological components and their interactions necessary to prevent or control Mycobacterium tuberculosis (Mtb) infection in humans is critical for tuberculosis (TB) vaccine development strategies. Although the contributory role of humoral immunity in the protection against Mtb infection and disease is less defined than the role of T cells, it has been well-established for many other intracellular pathogens. Here we update and discuss the increasing evidence and the mechanisms of B cells and antibodies in the defense against Mtb infection. We posit that B cells and antibodies have a variety of potential protective roles at each stage of Mtb infection and postulate that such roles should be considered in the development strategies for TB vaccines and other immune-based interventions.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; tuberculosis; Immunity, Innate; Immunity, Cellular; antibodies; B-Lymphocytes; Immunity, Humoral; B lymphocytes; Cell Communication; immunity; immunoglobulins

Polyfunctional CD4 T-cells correlate with in vitro mycobacterial growth inhibition following Mycobacterium bovis BCG-vaccination of infants - Smith, Steven G.; Zelmer, Andrea; Blitz, Rose; Fletcher, Helen A.; Dockrell, Hazel M. (Vaccine, 2016)
BACKGROUND: Vaccination with Bacillus Calmette Guerin (BCG) protects infants against childhood tuberculosis however the immune mechanisms involved are not well understood. Further elucidation of the infant immune response to BCG will aid with the identification of immune correlates of protection against tuberculosis and with the design of new improved vaccines. The purpose of this study was to investigate BCG-induced CD4+ T-cell responses in blood samples from infants for cytokine secretion profiles thought to be important for protection against tuberculosis and compare these to PBMC-mediated in vitro mycobacterial growth inhibition. METHODS: Blood from BCG-vaccinated or unvaccinated infants was stimulated overnight with Mycobacterium tuberculosis (M. tb) purified protein derivative (PPD) or controls and intracellular cytokine staining and flow cytometry used to measure CD4+T-cell responses. PBMC cryopreserved at the time of sample collection were thawed and incubated with live BCG for four days following which inhibition of BCG growth was determined. RESULTS: PPD-specific IFNγ+TNFα+IL-2+CD4+T-cells represented the dominant T-cell response at 4monthsand1yearafter infant BCG. These responses were undetectable in age-matched unvaccinated infants. IL-17+CD4+T-cells were significantly more frequent in vaccinated infants at 4monthsbut not at 1-year post-BCG. PBMC-mediated inhibition of mycobacterial growth was significantly enhanced at 4monthspost-BCG as compared to unvaccinated controls. In an analysis of all samples with both datasets available, mycobacterial growth inhibition correlated significantly with the frequency of polyfunctional (IFNγ+TNFα+IL-2+) CD4+T-cells. CONCLUSIONS: These data suggest that BCG vaccination of infants induces specific polyfunctional T-helper-1 and T-helper-17 responses and the ability, in the PBMC compartment, to inhibit the growth of mycobacteria in vitro. We also demonstrate that polyfunctional T-helper-1 cells may play a role in growth inhibition as evidenced by a significant correlation between the two.
Keywords: Humans; Flow Cytometry; BCG Vaccine; Female; Interferon-gamma; Cytokines; CD4-Positive T-Lymphocytes; Leukocytes, Mononuclear; Male; Lymphocyte Activation; Mycobacterium bovis; BCG; Th17 Cells; Tuberculin; Interleukin-2; Infant; Infants; Mycobacterial growth inhibition; Polyfunctional; T-cells

Antigen-Specific IFN-γ/IL-17-Co-Producing CD4+ T-Cells Are the Determinants for Protective Efficacy of Tuberculosis Subunit Vaccine - Choi, Han-Gyu; Kwon, Kee Woong; Choi, Seunga; Back, Yong Woo; Park, Hye-Soo; Kang, Soon Myung; Choi, Eunsol; Shin, Sung Jae; Kim, Hwa-Jung (Vaccines, 2020)
The antigen-specific Th17 responses in the lungs for improved immunity against Mycobacterium tuberculosis (Mtb) infection are incompletely understood. Tuberculosis (TB) vaccine candidate HSP90-ESAT-6 (E6), given as a Bacillus Calmette-Guérin (BCG)-prime boost regimen, confers superior long-term protection against the hypervirulent Mtb HN878 infection, compared to BCG or BCG-E6. Taking advantage of protective efficacy lead-out, we found that ESAT-6-specific multifunctional CD4+IFN-γ+IL-17+ T-cells optimally correlated with protection level against Mtb infection both pre-and post-challenge. Macrophages treated with the supernatant of re-stimulated lung cells from HSP90-E6-immunised mice significantly restricted Mtb growth, and this phenomenon was abrogated by neutralising anti-IFN-γ and/or anti-IL-17 antibodies. We identified a previously unrecognised role for IFN-γ/IL-17 synergism in linking anti-mycobacterial phagosomal activity to enhance host control against Mtb infection. The implications of our findings highlight the fundamental rationale for why and how Th17 responses are essential in the control of Mtb, and for the development of novel anti-TB subunit vaccines.
Keywords: Mycobacterium tuberculosis; BCG-prime boost; IFN-γ/IL-17; multifunctional T cells; phagosome maturation.

IFN-γ-independent control of M. tuberculosis requires CD4 T cell-derived GM-CSF and activation of HIF-1α - Van Dis, Erik; Fox, Douglas M.; Morrison, Huntly M.; Fines, Daniel M.; Babirye, Janet Peace; McCann, Lily H.; Rawal, Sagar; Cox, Jeffery S.; Stanley, Sarah A. (PLoS pathogens, 2022)
The prevailing model of protective immunity to tuberculosis is that CD4 T cells produce the cytokine IFN-γ to activate bactericidal mechanisms in infected macrophages. Although IFN-γ-independent CD4 T cell based control of M. tuberculosis infection has been demonstrated in vivo it is unclear whether CD4 T cells are capable of directly activating macrophages to control infection in the absence of IFN-γ. We developed a co-culture model using CD4 T cells isolated from the lungs of infected mice and M. tuberculosis-infected murine bone marrow-derived macrophages (BMDMs) to investigate mechanisms of CD4 dependent control of infection. We found that even in the absence of IFN-γ signaling, CD4 T cells drive macrophage activation, M1 polarization, and control of infection. This IFN-γ-independent control of infection requires activation of the transcription factor HIF-1α and a shift to aerobic glycolysis in infected macrophages. While HIF-1α activation following IFN-γ stimulation requires nitric oxide, HIF-1α-mediated control in the absence of IFN-γ is nitric oxide-independent, indicating that distinct pathways can activate HIF-1α during infection. We show that CD4 T cell-derived GM-CSF is required for IFN-γ-independent control in BMDMs, but that recombinant GM-CSF is insufficient to control infection in BMDMs or alveolar macrophages and does not rescue the absence of control by GM-CSF-deficient T cells. In contrast, recombinant GM-CSF controls infection in peritoneal macrophages, induces lipid droplet biogenesis, and also requires HIF-1α for control. These results advance our understanding of CD4 T cell-mediated immunity to M. tuberculosis, reveal important differences in immune activation of distinct macrophage types, and outline a novel mechanism for the activation of HIF-1α. We establish a previously unknown functional link between GM-CSF and HIF-1α and provide evidence that CD4 T cell-derived GM-CSF is a potent bactericidal effector.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Mice; Interferon-gamma; CD4-Positive T-Lymphocytes; Nitric Oxide; Granulocyte-Macrophage Colony-Stimulating Factor; Hypoxia-Inducible Factor 1, alpha Subunit

CD4 T Cell-Derived IFN-γ Plays a Minimal Role in Control of Pulmonary Mycobacterium tuberculosis Infection and Must Be Actively Repressed by PD-1 to Prevent Lethal Disease - Sakai, Shunsuke; Kauffman, Keith D.; Sallin, Michelle A.; Sharpe, Arlene H.; Young, Howard A.; Ganusov, Vitaly V.; Barber, Daniel L. (PLoS pathogens, 2016)
IFN-γ-producing CD4 T cells are required for protection against Mycobacterium tuberculosis (Mtb) infection, but the extent to which IFN-γ contributes to overall CD4 T cell-mediated protection remains unclear. Furthermore, it is not known if increasing IFN-γ production by CD4 T cells is desirable in Mtb infection. Here we show that IFN-γ accounts for only ~30% of CD4 T cell-dependent cumulative bacterial control in the lungs over the first six weeks of infection, but >80% of control in the spleen. Moreover, increasing the IFN-γ-producing capacity of CD4 T cells by ~2 fold exacerbates lung infection and leads to the early death of the host, despite enhancing control in the spleen. In addition, we show that the inhibitory receptor PD-1 facilitates host resistance to Mtb by preventing the detrimental over-production of IFN-γ by CD4 T cells. Specifically, PD-1 suppressed the parenchymal accumulation of and pathogenic IFN-γ production by the CXCR3+KLRG1-CX3CR1- subset of lung-homing CD4 T cells that otherwise mediates control of Mtb infection. Therefore, the primary role for T cell-derived IFN-γ in Mtb infection is at extra-pulmonary sites, and the host-protective subset of CD4 T cells requires negative regulation of IFN-γ production by PD-1 to prevent lethal immune-mediated pathology.
Keywords: Mycobacterium tuberculosis; Animals; Blotting, Western; Tuberculosis, Pulmonary; Flow Cytometry; Mice; Disease Models, Animal; Interferon-gamma; Cytokines; CD4-Positive T-Lymphocytes; Mice, Inbred C57BL; Adoptive Transfer; Mice, Knockout; Enzyme-Linked Immunosorbent Assay; Programmed Cell Death 1 Receptor

Susceptibility to Intracellular Infections: Contributions of TNF to Immune Defense - Li, Xinying; Körner, Heinrich; Liu, Xiaoying (Frontiers in Microbiology, 2020)
An interesting puzzle is the fact that an infection of a tumor necrosis factor α (TNF)-deficient host with pathogens such as bacteria or parasites that reside intracellularly inevitably ends fatally. Is this due to one specific role of TNF in the immune defense or are different functions responsible for this outcome? In this review we provide an update of the functions of TNF in the defense against the intracellular pathogens Listeria monocytogenes, Mycobacterium tuberculosis, and Leishmania major. Furthermore, we discuss the role of TNF in the generation of proinflammatory macrophages in mouse models of infection and summarize briefly the potential consequences of anti-TNF treatment for infectious diseases.
Keywords: Mycobacterium tuberculosis; Leishmania major; Listeria monocytogenes; macrophage polarization; TNF

Mycobacterium tuberculosis induces high production of nitric oxide in coordination with production of tumour necrosis factor-alpha in patients with fresh active tuberculosis but not in MDR tuberculosis - Sharma, Sadhna; Sharma, Monika; Roy, Sugata; Kumar, Praveen; Bose, Mridula (Immunology and Cell Biology, 2004)
Mycobacterium tuberculosis is an intracellular pathogen that readily survives and replicates in human macrophages. Host cells have developed various mycobactericidal and immunoregulatory mechanisms, such as the production of nitric oxide and inflammatory cytokines to control intracellular replication of M. tuberculosis. Inducible nitric oxide synthase (iNOS) is transcriptionally under the control of IFN-gamma and TNF-alpha. IL-12 provides a crucial link between activated mononuclear phagocytes and T cells by regulating the production of IFN-gamma. In this study, we investigated the production of nitric oxide (NO), TNF-alpha and IL-12 by the peripheral blood monocytes (PB Mn) of patients suffering from multidrug-resistant tuberculosis (MDR-TB). The cells were infected with M. tuberculosis and stimulated with IFN-gamma or activated with mycobacterial subcellular components. The results were compared with those from cases of newly diagnosed TB and healthy controls. Nitric oxide production was significantly depressed in PB Mn from MDR-TB patients. Infected monocytes from newly diagnosed TB patients produced significantly higher levels of NO as compared to those from MDR-TB patients or normal controls. The subcellular fraction of M. tuberculosis-like whole cell lysate (WCL), culture filtrate protein (CFP) and lipoarabinomannan (LAM) induced higher concentrations of NO release in PB Mn from newly diagnosed TB patients as compared to those from MDR-TB patients. Cell culture supernatant from PB Mn assayed at 48 h after infection or stimulation demonstrated significantly depressed release of TNF-alpha and IL-12 from MDR-TB cases as compared to the fresh cases. We observed a definite correlation between nitric oxide release and TNF-alpha production, irrespective of low or high production in MDR-TB or fresh cases, respectively. The present data suggest that peripheral blood monocytes of MDR-TB patients typically show signs of immunosuppression. Whether such immunodepression is the cause or the effect of MDR-TB merits further investigation.
Keywords: Humans; Mycobacterium tuberculosis; Monocytes; Tuberculosis, Pulmonary; Female; Interferon-gamma; Adult; Male; Interleukin-12; Tumor Necrosis Factor-alpha; Tuberculosis, Multidrug-Resistant; Nitric Oxide

Plasma levels of tumor necrosis factor-alpha, interferon-gamma, inducible nitric oxide synthase, and 3-nitrotyrosine in drug-resistant and drug-sensitive pulmonary tuberculosis patients, Ibadan, Nigeria - Bolajoko, Elizabeth Bosede; Arinola, Olatunbosun Ganiyu; Odaibo, Georgina Njideka; Maiga, Mamoudou (International Journal of Mycobacteriology, 2020)
BACKGROUND: Nigeria is one of the countries with a high burden of tuberculosis (TB) in the world. TB associated inflammation is reported to be central to progression from latent TB to active TB or drug sensitive TB (DSTB) to drug resistant TB (DRTB). Inflammatory cytokines, especially interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α), act synergistically in the control of TB infection. They activate macrophages to produce effector molecules such as inducible nitric oxide synthase (iNOS), nitric oxide, and ultimately 3-nitrotyrosines(3-NTs), which are involved in the control of TB. This study investigated the potential involvement of TNF-α, IFN-γ, iNOS, and 3-NT in differentiating DRTB and DSTB in Ibadan, Nigeria. METHODS: One hundred participants above 18 years were recruited into this study and were grouped as follows: 32 DRTB, 34 DSTB, and 34 apparently healthy controls. Plasma from the patients was used for the analyses of inflammatory (TNF α and IFN-γ) and oxidative stress (iNOS and 3-NT) biomarkers using the ELISA. Mann-Whitney test was applied for the statistical test. RESULTS: Mean levels of plasma TNF-α, IFN-γ, iNOS, and 3-NT were higher in DRTB (19.74 ± 3.62 pg/mL, 4.41 ± 0.96 pg/mL, 1791.07 ± 419.42 pg/mL, and 20.27 ± 1.80 ng/mL, respectively) and DSTB (17.02 ± 1.84 pg/mL, 5.59 ± 1.40 pg/mL, 2823.42 ± 685.32 pg/mL, and 25.06 ± 2.15 ng/mL, respectively) compared with controls (12.18 ± 0.92 pg/mL, 1.58 ± 0.21 pg/mL, 1275.86 ± 166.12 pg/mL, and 19.98 ± 1.23 ng/mL, respectively). In addition, higher plasma levels of IFN-γ (P > 0.05), iNOS (P > 0.05), and 3-NT (P < 0.05) were observed in DSTB compared with DRTB patients. CONCLUSION: The 3-NT may be used as differentiating markers of DSTB from DRTB.
Keywords: Humans; Tuberculosis, Pulmonary; Interferon-gamma; Biomarkers; Adult; Middle Aged; Young Adult; Adolescent; Aged; Inflammation; Tumor Necrosis Factor-alpha; Tuberculosis, Multidrug-Resistant; pulmonary tuberculosis; Nitric Oxide Synthase Type II; Oxidative Stress; 3-nitrotyrosine; inducible nitric oxide synthase; inflammatory cytokines; Nigeria; Tyrosine

Mycobacterium tuberculosis SufR responds to nitric oxide via its 4Fe-4S cluster and regulates Fe-S cluster biogenesis for persistence in mice - Anand, Kushi; Tripathi, Ashutosh; Shukla, Kaustubh; Malhotra, Nitish; Jamithireddy, Anil Kumar; Jha, Rajiv Kumar; Chaudhury, Susmit Narayan; Rajmani, Raju S.; Ramesh, Arati; Nagaraja, Valakunja; Gopal, Balasubramanian; Nagaraju, Ganesh; et al. (Redox Biology, 2021)
The persistence of Mycobacterium tuberculosis (Mtb) is a major problem in managing tuberculosis (TB). Host-generated nitric oxide (NO) is perceived as one of the signals by Mtb to reprogram metabolism and respiration for persistence. However, the mechanisms involved in NO sensing and reorganizing Mtb's physiology are not fully understood. Since NO damages iron-sulfur (Fe-S) clusters of essential enzymes, the mechanism(s) involved in regulating Fe-S cluster biogenesis could help Mtb persist in host tissues. Here, we show that a transcription factor SufR (Rv1460) senses NO via its 4Fe-4S cluster and promotes persistence of Mtb by mobilizing the Fe-S cluster biogenesis system; suf operon (Rv1460-Rv1466). Analysis of anaerobically purified SufR by UV-visible spectroscopy, circular dichroism, and iron-sulfide estimation confirms the presence of a 4Fe-4S cluster. Atmospheric O2 and H2O2 gradually degrade the 4Fe-4S cluster of SufR. Furthermore, electron paramagnetic resonance (EPR) analysis demonstrates that NO directly targets SufR 4Fe-4S cluster by forming a protein-bound dinitrosyl-iron-dithiol complex. DNase I footprinting, gel-shift, and in vitro transcription assays confirm that SufR directly regulates the expression of the suf operon in response to NO. Consistent with this, RNA-sequencing of MtbΔsufR demonstrates deregulation of the suf operon under NO stress. Strikingly, NO inflicted irreversible damage upon Fe-S clusters to exhaust respiratory and redox buffering capacity of MtbΔsufR. Lastly, MtbΔsufR failed to recover from a NO-induced non-growing state and displayed persistence defect inside immune-activated macrophages and murine lungs in a NO-dependent manner. Data suggest that SufR is a sensor of NO that supports persistence by reprogramming Fe-S cluster metabolism and bioenergetics.
Keywords: Mycobacterium tuberculosis; Animals; Mice; Nitric Oxide; Dinitrosyl-iron-dithiol complex; Electron Spin Resonance Spectroscopy; Gene regulation; Hydrogen Peroxide; Inducible nitric oxide synthase; Iron-Sulfur Proteins; Operon; Redox potential; Spare respiratory capacity; Transcriptomics

The Immune Escape Mechanisms of Mycobacterium Tuberculosis - Zhai, Weijie; Wu, Fengjuan; Zhang, Yiyuan; Fu, Yurong; Liu, Zhijun (International Journal of Molecular Sciences, 2019)
Epidemiological data from the Center of Disease Control (CDC) and the World Health Organization (WHO) statistics in 2017 show that 10.0 million people around the world became sick with tuberculosis. Mycobacterium tuberculosis (MTB) is an intracellular parasite that mainly attacks macrophages and inhibits their apoptosis. It can become a long-term infection in humans, causing a series of pathological changes and clinical manifestations. In this review, we summarize innate immunity including the inhibition of antioxidants, the maturation and acidification of phagolysosomes and especially the apoptosis and autophagy of macrophages. Besides, we also elaborate on the adaptive immune response and the formation of granulomas. A thorough understanding of these escape mechanisms is of major importance for the prevention, diagnosis and treatment of tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; immunology; Phagosomes; Immune Evasion; Apoptosis; Autophagy; macrophages; apoptosis; immune escape; Oxidative Stress

Mycobacterium Tuberculosis and Interactions with the Host Immune System: Opportunities for Nanoparticle Based Immunotherapeutics and Vaccines - Bekale, Raymonde B.; Du Plessis, Su-Mari; Hsu, Nai-Jen; Sharma, Jyoti R.; Sampson, Samantha L.; Jacobs, Muazzam; Meyer, Mervin; Morse, Gene D.; Dube, Admire (Pharmaceutical Research, 2018)
Tuberculosis (TB) caused by Mycobacterium tuberculosis remains a deadly infectious disease. The thin pipeline of new drugs for TB, the ineffectiveness in adults of the only vaccine available, i.e. the Bacillus Calmette-Guerin vaccine, and increasing global antimicrobial resistance, has reinvigorated interest in immunotherapies. Nanoparticles (NPs) potentiate the effect of immune modulating compounds (IMC), enabling cell targeting, improved transfection of antigens, enhanced compound stability and provide opportunities for synergistic action, via delivery of multiple IMCs. In this review we describe work performed in the application of NPs towards achieving immune modulation for TB treatment and vaccination. Firstly, we present a comprehensive review of M. tuberculosis and how the bacterium modulates the host immune system. We find that current work suggest great promise of NP based immunotherapeutics as novel treatments and vaccination systems. There is need to intensify research efforts in this field, and rationally design novel NP immunotherapeutics based on current knowledge of the mycobacteriology and immune escape mechanisms employed by M. tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Tuberculosis; Vaccination; Immunotherapy; Immune System; immunotherapeutic nanoparticles; immunotherapy for tuberculosis; nanoparticle based host directed therapy; Nanoparticles; nanoparticles and vaccination

Stealth Strategies of Mycobacterium tuberculosis for Immune Evasion - Naeem, Muhammad Ahsan; Ahmad, Waqas; Tyagi, Rohit; Akram, Qaiser; Younus, Muhammad; Liu, Xilin (Current Issues in Molecular Biology, 2021)
Tuberculosis is a devastating disease causing high mortality all over the world, especially in the developing countries. Mycobacterium tuberculosis (M. tb) is the causative agent of tuberculosis which replicates in the intracellular environment of host macrophages. Although the host immune system is capable of completely eliminating the pathogen, co-evolution of M. tb with humans has resulted in its ability to hijack the host innate and adaptive immune systems in numerous ways. Limited recent progress has been made in the understanding of M. tb immune escape mechanisms, hence exploration of survival strategies of M. tb has been critically reviewed with an insight into understanding its pathogenesis. We summarized the recent studies regarding the modulation of innate immune response, adaptive immune response, epigenetics and the role of miRNA. All of these advancements suggest that M. tb is well-familiarize with the host immune system and possess the ability to hijack it for intracellular survival.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Macrophages; Tuberculosis; Adaptive Immunity; Immunity, Innate; Immune Evasion; MicroRNAs

Preexisting Heterogeneity of Inducible Nitric Oxide Synthase Expression Drives Differential Growth of Mycobacterium tuberculosis in Macrophages - Rutschmann, Ophélie; Toniolo, Chiara; McKinney, John D. (mBio, 2022)
Mycobacterium tuberculosis infection is initiated by the inhalation and implantation of bacteria in the lung alveoli, where they are phagocytosed by macrophages. Even a single bacterium may be sufficient to initiate infection. Thereafter, the clinical outcome is highly variable between individuals, ranging from sterilization to active disease, for reasons that are not well understood. Here, we show that the rate of intracellular bacterial growth varies markedly between individual macrophages, and this heterogeneity is driven by cell-to-cell variation of inducible nitric oxide synthase (iNOS) activity. At the single-cell level, iNOS expression fluctuates over time, independent of infection or activation with gamma interferon. We conclude that chance encounters between individual bacteria and host cells randomly expressing different levels of an antibacterial gene can determine the outcome of single-cell infections, which may explain why some exposed individuals clear the bacteria while others develop progressive disease. IMPORTANCE In this report, we demonstrate that fluctuations in the expression of antimicrobial genes can define how single host cells control bacterial infections. We show that preexisting cell-to-cell variation in the expression of a single gene, that for inducible nitric oxide synthase, is sufficient to explain why some macrophages kill intracellular M. tuberculosis while others fail to control bacterial replication, possibly leading to disease progression. We introduce the concept that chance encounters between heterogeneous bacteria and host cells can determine the outcome of a host-pathogen interaction. This concept is particularly relevant for all the infectious diseases in which the number of interacting pathogens and host cells is small at some point during the infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Anti-Bacterial Agents; Interferon-gamma; innate immunity; Nitric Oxide; Nitric Oxide Synthase; macrophages; gamma interferon (IFN-γ); heterogeneity; inducible nitric oxide synthase (iNOS); microscopy; Nitric Oxide Synthase Type II; single-cell; time-lapse

Host-directed therapy to combat mycobacterial infections - Kilinç, Gül; Saris, Anno; Ottenhoff, Tom H. M.; Haks, Mariëlle C. (Immunological Reviews, 2021)
Upon infection, mycobacteria, such as Mycobacterium tuberculosis (Mtb) and nontuberculous mycobacteria (NTM), are recognized by host innate immune cells, triggering a series of intracellular processes that promote mycobacterial killing. Mycobacteria, however, have developed multiple counter-strategies to persist and survive inside host cells. By manipulating host effector mechanisms, including phagosome maturation, vacuolar escape, autophagy, antigen presentation, and metabolic pathways, pathogenic mycobacteria are able to establish long-lasting infection. Counteracting these mycobacteria-induced host modifying mechanisms can be accomplished by host-directed therapeutic (HDT) strategies. HDTs offer several major advantages compared to conventional antibiotics: (a) HDTs can be effective against both drug-resistant and drug-susceptible bacteria, as well as potentially dormant mycobacteria; (b) HDTs are less likely to induce bacterial drug resistance; and (c) HDTs could synergize with, or shorten antibiotic treatment by targeting different pathways. In this review, we will explore host-pathogen interactions that have been identified for Mtb for which potential HDTs impacting both innate and adaptive immunity are available, and outline those worthy of future research. We will also discuss possibilities to target NTM infection by HDT, although current knowledge regarding host-pathogen interactions for NTM is limited compared to Mtb. Finally, we speculate that combinatorial HDT strategies can potentially synergize to achieve optimal mycobacterial host immune control.
Keywords: Mycobacterium tuberculosis; Host-Pathogen Interactions; Anti-Bacterial Agents; Mycobacterium avium; host-directed therapy; Autophagy; drug resistance; nontuberculous mycobacteria; Nontuberculous Mycobacteria

Mycobacterium tuberculosis (MTB)-stimulated production of nitric oxide by human alveolar macrophages and relationship of nitric oxide production to growth inhibition of MTB - Rich, E. A.; Torres, M.; Sada, E.; Finegan, C. K.; Hamilton, B. D.; Toossi, Z. (Tubercle and Lung Disease: The Official Journal of the International Union Against Tuberculosis and Lung Disease, 1997)
SETTING: Although nitric oxide (NO) is a major proximate mediator of microbicidal activity in murine macrophages against intracellular pathogens including mycobacteria, its production by and effector role in human macrophages is not clear. OBJECTIVE: To determine the capacity of Mycobacterium tuberculosis (MTB) to stimulate NO in human monocytes (MN) and alveolar macrophages (AM) and to assess the relationship between NO production and intracellular growth of MTB. DESIGN: NO production (measured as nitrite) by MTB (H37Ra)-infected macrophages and intracellular growth of MTB were measured in cells from 17 healthy subjects. RESULTS: MTB (5:1, MTB:cells) stimulated little to no NO by MN, but induced NO in AM at days 4 and 7 after infection. There was, however, variability in the response by AM to MTB: among seven subjects MTB-induced NO was low (4 +/- 2 microM, mean +/- SE); six subjects were moderate (56 +/- 11); four subjects were high (502 +/- 167). NO synthase inhibitors inhibited the production of NO by AM but did not significantly affect the intracellular growth of MTB, although a trend towards increased intracellular growth was seen on day 4 of culture. Intracellular growth of MTB in AM from low NO producers was significantly higher than that in AM from moderate NO producers, P < or = 0.05. Inducible NO synthase (iNOS) mRNA by RT-PCR was constitutively expressed by both MN and AM, but was further stimulated by MTB in AM > MN; MTB-induced iNOS protein was present in both MN and AM by Western blot analysis. CONCLUSION: Thus, MTB-infected human AM are capable of producing NO and NO production correlates with intracellular growth inhibition of MTB in AM suggesting that NO may serve either directly or indirectly as a mycobactericidal mediator in human tissue macrophages.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Reverse Transcriptase Polymerase Chain Reaction; Female; Adult; Male; Middle Aged; Colony Count, Microbial; RNA, Messenger; Cell Culture Techniques; Nitric Oxide; Nitric Oxide Synthase; Enzyme Inhibitors; Macrophages, Alveolar

Nitric Oxide in the Pathogenesis and Treatment of Tuberculosis - Jamaati, Hamidreza; Mortaz, Esmaeil; Pajouhi, Zeinab; Folkerts, Gert; Movassaghi, Mehrnaz; Moloudizargari, Milad; Adcock, Ian M.; Garssen, Johan (Frontiers in Microbiology, 2017)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is globally known as one of the most important human pathogens. Mtb is estimated to infect nearly one third of the world's population with many subjects having a latent infection. Thus, from an estimated 2 billion people infected with Mtb, less than 10% may develop symptomatic TB. This indicates that the host immune system may constrain pathogen replication in most infected individuals. On entering the lungs of the host, Mtb initially encounters resident alveolar macrophages which can engulf and subsequently eliminate intracellular microbes via a plethora of bactericidal mechanisms including the generation of free radicals such as reactive oxygen and nitrogen species. Nitric oxide (NO), a key anti-mycobacterial molecule, is detected in the exhaled breath of patients infected with Mtb. Recent knowledge regarding the regulatory role of NO in airway function and Mtb proliferation paves the way of exploiting the beneficial effects of this molecule for the treatment of airway diseases. Here, we discuss the importance of NO in the pathogenesis of TB, the diagnostic use of exhaled and urinary NO in Mtb infection and the potential of NO-based treatments.
Keywords: Mycobacterium; drug-resistance; macrophages; nitric oxide; nitric oxide donors; non-tuberculous mycobacteria

The Role of Nitric Oxide in Mycobacterial Infections - Yang, Chul-Su; Yuk, Jae-Min; Jo, Eun-Kyeong (Immune Network : Official Journal of the Korean Society for Immunology and Biological Response Modifiers, 2009)
Although tuberculosis poses a significant health threat to the global population, it is a challenge to develop new and effective therapeutic strategies. Nitric oxide (NO) and inducible NO synthase (iNOS) are important in innate immune responses to various intracellular bacterial infections, including mycobacterial infections. It is generally recognized that reactive nitrogen intermediates play an effective role in host defense mechanisms against tuberculosis. In a murine model of tuberculosis, NO plays a crucial role in antimycobacterial activity; however, it is controversial whether NO is critically involved in host defense against Mycobacterium tuberculosis in humans. Here, we review the roles of NO in host defense against murine and human tuberculosis. We also discuss the specific roles of NO in the central nervous system and lung epithelial cells during mycobacterial infection. A greater understanding of these defense mechanisms in human tuberculosis will aid in the development of new strategies for the treatment of disease.

Mycobacterium Growth Inhibition Assay of Human Alveolar Macrophages as a Correlate of Immune Protection Following Mycobacterium bovis Bacille Calmette-Guérin Vaccination - Radloff, Juliane; Heyckendorf, Jan; van der Merwe, Lize; Sanchez Carballo, Patricia; Reiling, Norbert; Richter, Elvira; Lange, Christoph; Kalsdorf, Barbara (Frontiers in Immunology, 2018)
BACKGROUND: In order to eliminate tuberculosis (TB), an effective vaccine is urgently needed to prevent infection with Mycobacterium tuberculosis. A key obstacle for the development of novel TB vaccines is the lack of surrogate markers for immune protection against M. tuberculosis. METHODS: We investigated growth rates of M. tuberculosis in the mycobacterial growth inhibition assay (MGIA) as a marker for mycobacterial growth control of human bronchoalveolar lavage (BALC) and peripheral blood mononuclear cells (PBMC) before and after vaccination with Mycobacterium bovis Bacille Calmette-Guérin (BCG) of healthy adult volunteers. RESULTS: Vaccination induced a positive response (p < 0.001) to purified protein derivate (PPD) in 58.8% of the individuals in an interferon-γ release assay-ELISpot. Intraindividual evaluation of the MGIA growth rates before and after M. bovis BCG-vaccination revealed no significant difference in time to culture positivity before and after vaccination in BALC (p = 0.604) and PBMC (p = 0.199). The magnitude of the PPD-response induced by M. bovis BCG-vaccination did not correlate with growth control in BALC and PBMC (correlation = 0.468, 95% CI: -0.016 to 0.775). CONCLUSION: In conclusion, M. bovis BCG-vaccination-induced mycobacterial-specific cytokine immune response does not result in functional immune control against M. tuberculosis in the MGIA.
Keywords: tuberculosis; vaccine; mycobacterial growth inhibition assay; Bacille Calmette–Guérin; interferon-γ release assay immune response; vitamin D

A Case for Antibodies as Mechanistic Correlates of Immunity in Tuberculosis - Kawahara, Jeffrey Y.; Irvine, Edward B.; Alter, Galit (Frontiers in Immunology, 2019)
Tuberculosis infects one quarter of the world's population and is the leading cause of death by a single infectious agent, responsible for a reported 1.3 million deaths in 2017. While Mycobacterium tuberculosis is treatable with antibiotic therapy, the increased prevalence of drug resistance, coupled with the variable efficacy of the only widely approved vaccine, has highlighted the need for creative approaches to therapeutic and vaccine development. Historically, a productive immune response to M. tuberculosis has been thought to be nearly entirely cell-mediated, with humoral immunity being largely dismissed. However, in this review, we will discuss the historical skepticism surrounding the role of the humoral immune response to M. tuberculosis, and examine more recent evidence suggesting that antibodies may play a valuable role in host defense against the pathogen. Despite the amount of data portraying antibodies in a negative light, emerging data have begun to highlight the unexpected role of antibodies in M. tuberculosis control. Specifically, it has become clear that antibody features of both the variable and constant domain (Fc) ultimately determine the extent to which antibodies modulate disease. Thus, a more precise definition of the antigen-binding and innate immune recruiting functions of antibodies that contribute to M. tuberculosis restriction, are sure to help guide the development of next-generation therapeutics and vaccines to curb this global epidemic.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; Immunity, Innate; antibodies; Immunity, Humoral; Immunoglobulin Fc Fragments; Antigen Presentation; humoral immunity; cell-mediated immunity; Fc effector function; innate immune system

Whole genome profiling refines a panel of correlates to predict vaccine efficacy against Mycobacterium tuberculosis - Kurtz, Sherry L.; Gardina, Paul J.; Myers, Timothy G.; Rydén, Patrik; Elkins, Karen L. (Tuberculosis (Edinburgh, Scotland), 2020)
New vaccines are needed to combat the public health threat posed by M. tuberculosis (M. tb), but no correlates have been defined to aid vaccine development. Using mouse models, we previously developed an in vitro system that measures the ability of M. tb-immune lymphocytes to control bacterial replication during co-culture with M. tb-infected macrophages. We demonstrated that the degree of in vitro growth control by lymphocytes from mice given vaccines of varying efficacy reflected the relative degree of in vivo protection against lethal challenge. Further, using targeted analyses of gene expression in lymphocytes recovered from co-cultures, we found mediators whose relative expression also correlated with in vitro and in vivo outcomes. Here we advanced those findings by employing genome-wide expression analyses. We first screened splenocytes recovered from co-cultures by microarray, revealing additional genes whose expression correlated with protection. After applying pathway analyses to down-select gene candidates, we used both splenocytes and peripheral blood lymphocytes to validate microarray findings by qRT-PCR. We then subjected data from top candidates to rigorous statistical analyses. Resulting correlate candidates, including CXCL9, IFN-γ, and CCL5, significantly predicted protection with high specificity. These findings therefore refine and extend a panel of relevant immune correlates to advance vaccine development.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Macrophages; Gene Expression Profiling; Vaccine; Cells, Cultured; Interferon-gamma; Biomarkers; T-Lymphocytes; Mice, Inbred C57BL; Coculture Techniques; Male; Vaccination; Gene expression; Oligonucleotide Array Sequence Analysis; Transcriptome; Chemokine CCL5; Chemokine CXCL9; Correlates; Genome-Wide Association Study; T lymphocytes

Intracellular growth of Mycobacterium tuberculosis after macrophage cell death leads to serial killing of host cells - Mahamed, Deeqa; Boulle, Mikael; Ganga, Yashica; Mc Arthur, Chanelle; Skroch, Steven; Oom, Lance; Catinas, Oana; Pillay, Kelly; Naicker, Myshnee; Rampersad, Sanisha; Mathonsi, Colisile; Hunter, Jessica; et al. (eLife, 2017)
A hallmark of pulmonary tuberculosis is the formation of macrophage-rich granulomas. These may restrict Mycobacterium tuberculosis (Mtb) growth, or progress to central necrosis and cavitation, facilitating pathogen growth. To determine factors leading to Mtb proliferation and host cell death, we used live cell imaging to track Mtb infection outcomes in individual primary human macrophages. Internalization of Mtb aggregates caused macrophage death, and phagocytosis of large aggregates was more cytotoxic than multiple small aggregates containing similar numbers of bacilli. Macrophage death did not result in clearance of Mtb. Rather, it led to accelerated intracellular Mtb growth regardless of prior activation or macrophage type. In contrast, bacillary replication was controlled in live phagocytes. Mtb grew as a clump in dead cells, and macrophages which internalized dead infected cells were very likely to die themselves, leading to a cell death cascade. This demonstrates how pathogen virulence can be achieved through numbers and aggregation states.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Endocytosis; Cells, Cultured; human; Cell Death; computational biology; human macrophages; infection dynamics; infectious disease; Intravital Microscopy; live cell imaging; microbiology; necrosis; systems biology

Intracellular growth of Mycobacterium tuberculosis after macrophage cell death leads to serial killing of host cells - Mahamed, Deeqa; Boulle, Mikael; Ganga, Yashica; Mc Arthur, Chanelle; Skroch, Steven; Oom, Lance; Catinas, Oana; Pillay, Kelly; Naicker, Myshnee; Rampersad, Sanisha; Mathonsi, Colisile; Hunter, Jessica; et al. (eLife, 2017)
A hallmark of pulmonary tuberculosis is the formation of macrophage-rich granulomas. These may restrict Mycobacterium tuberculosis (Mtb) growth, or progress to central necrosis and cavitation, facilitating pathogen growth. To determine factors leading to Mtb proliferation and host cell death, we used live cell imaging to track Mtb infection outcomes in individual primary human macrophages. Internalization of Mtb aggregates caused macrophage death, and phagocytosis of large aggregates was more cytotoxic than multiple small aggregates containing similar numbers of bacilli. Macrophage death did not result in clearance of Mtb. Rather, it led to accelerated intracellular Mtb growth regardless of prior activation or macrophage type. In contrast, bacillary replication was controlled in live phagocytes. Mtb grew as a clump in dead cells, and macrophages which internalized dead infected cells were very likely to die themselves, leading to a cell death cascade. This demonstrates how pathogen virulence can be achieved through numbers and aggregation states.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Endocytosis; Cells, Cultured; human; Cell Death; computational biology; human macrophages; infection dynamics; infectious disease; Intravital Microscopy; live cell imaging; microbiology; necrosis; systems biology

The in vitro direct mycobacterial growth inhibition assay (MGIA) for the early evaluation of TB vaccine candidates and assessment of protective immunity: a protocol for non-human primate cells - Tanner, Rachel; Hoogkamer, Emily; Bitencourt, Julia; White, Andrew; Boot, Charelle; Sombroek, Claudia C.; Harris, Stephanie A.; O'Shea, Matthew K.; Wright, Daniel; Wittenberg, Rachel; Sarfas, Charlotte; Satti, Iman; et al. (F1000Research, 2021)
The only currently available approach to early efficacy testing of tuberculosis (TB) vaccine candidates is in vivo preclinical challenge models. These typically include mice, guinea pigs and non-human primates (NHPs), which must be exposed to virulent M.tb in a 'challenge' experiment following vaccination in order to evaluate protective efficacy. This procedure results in disease development and is classified as 'Moderate' in severity under EU legislation and UK ASPA licensure. Furthermore, experiments are relatively long and animals must be maintained in high containment level facilities, making them relatively costly. We describe an in vitro protocol for the direct mycobacterial growth inhibition assay (MGIA) for use in the macaque model of TB vaccine development with the aim of overcoming some of these limitations. Importantly, using an in vitro assay in place of in vivo M.tb challenge represents a significant refinement to the existing procedure for early vaccine efficacy testing. Peripheral blood mononuclear cell and autologous serum samples collected from vaccinated and unvaccinated control animals are co-cultured with mycobacteria in a 48-well plate format for 96 hours. Adherent monocytes are then lysed to release intracellular mycobacteria which is quantified using the BACTEC MGIT system and colony-forming units determined relative to an inoculum control and stock standard curve. We discuss related optimisation and characterisation experiments, and review evidence that the direct NHP MGIA provides a biologically relevant model of vaccine-induced protection. The potential end-users of the NHP MGIA are academic and industry organisations that conduct the assessment of TB vaccine candidates and associated protective immunity using the NHP model. This approach aims to provide a method for high-throughput down-selection of vaccine candidates going forward to in vivo efficacy testing, thus expediting the development of a more efficacious TB vaccine and offering potential refinement and reduction to the use of NHPs for this purpose.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; Guinea Pigs; Mice; Primates; 3Rs; macaque; non-human primate; Leukocytes, Mononuclear; vaccines; mycobacterial growth inhibition assay; refinement

Macrophage Heterogeneity in the Immunopathogenesis of Tuberculosis - Marakalala, Mohlopheni J.; Martinez, Fernando O.; Plüddemann, Annette; Gordon, Siamon (Frontiers in Microbiology, 2018)
Macrophages play a central role in tuberculosis, as the site of primary infection, inducers and effectors of inflammation, innate and adaptive immunity, as well as mediators of tissue destruction and repair. Early descriptions by pathologists have emphasized their morphological heterogeneity in granulomas, followed by delineation of T lymphocyte-dependent activation of anti-mycobacterial resistance. More recently, powerful genetic and molecular tools have become available to describe macrophage cellular properties and their role in host-pathogen interactions. In this review we discuss aspects of macrophage heterogeneity relevant to the pathogenesis of tuberculosis and, conversely, lessons that can be learnt from mycobacterial infection, with regard to the immunobiological functions of macrophages in homeostasis and disease.
Keywords: Mycobacterium tuberculosis; tuberculosis; immunopathogenesis; macrophage; macrophage heterogeneity4; pulmonary

B-Cells and Antibodies as Contributors to Effector Immune Responses in Tuberculosis - Rijnink, Willemijn F.; Ottenhoff, Tom H. M.; Joosten, Simone A. (Frontiers in Immunology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is still a major threat to mankind, urgently requiring improved vaccination and therapeutic strategies to reduce TB-disease burden. Most present vaccination strategies mainly aim to induce cell-mediated immunity (CMI), yet a series of independent studies has shown that B-cells and antibodies (Abs) may contribute significantly to reduce the mycobacterial burden. Although early studies using B-cell knock out animals did not support a major role for B-cells, more recent studies have provided new evidence that B-cells and Abs can contribute significantly to host defense against Mtb. B-cells and Abs exist in many different functional subsets, each equipped with unique functional properties. In this review, we will summarize current evidence on the contribution of B-cells and Abs to immunity toward Mtb, their potential utility as biomarkers, and their functional contribution to Mtb control.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; antibodies; B-Lymphocytes; Immunity, Humoral; B-cells; biomarker; humoral immunity

CD4+/CD8+ double-positive T cells: more than just a developmental stage? - Overgaard, Nana H.; Jung, Ji-Won; Steptoe, Raymond J.; Wells, James W. (Journal of Leukocyte Biology, 2015)
CD4(+)/CD8(+) DP thymocytes are a well-described T cell developmental stage within the thymus. However, once differentiated, the CD4(+) lineage or the CD8(+) lineage is generally considered to be fixed. Nevertheless, mature CD4(+)/CD8(+) DP T cells have been described in the blood and peripheral lymphoid tissues of numerous species, as well as in numerous disease settings, including cancer. The expression of CD4 and CD8 is regulated by a very strict transcriptional program involving the transcription factors Runx3 and ThPOK. Initially thought to be mutually exclusive within CD4(+) and CD8(+) T cells, CD4(+)/CD8(+) T cell populations, outside of the thymus, have recently been described to express concurrently ThPOK and Runx3. Considerable heterogeneity exists within the CD4(+)/CD8(+) DP T cell pool, and the function of CD4(+)/CD8(+) T cell populations remains controversial, with conflicting reports describing cytotoxic or suppressive roles for these cells. In this review, we describe how transcriptional regulation, lineage of origin, heterogeneity of CD4 and CD8 expression, age, species, and specific disease settings influence the functionality of this rarely studied T cell population.
Keywords: Humans; Animals; Cell Differentiation; T-Lymphocyte Subsets; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; cytotoxic potential; immune regulation; T cell plasticity

CD4CD8 Double Positive T cell responses during Mycobacterium tuberculosis infection in cynomolgus macaques - Diedrich, Collin Richard; Gideon, Hannah Priyadarshini; Rutledge, Tara; Baranowski, Tonilynn Marie; Maiello, Pauline; Myers, Amy J.; Lin, Philana Ling (Journal of Medical Primatology, 2019)
BACKGROUND: Tuberculosis (TB) kills millions of people every year. CD4 and CD8 T cells are critical in the immune response against TB. T cells expressing both CD4 and CD8 (CD4CD8 T cells) are functionally active and have not been examined in the context of TB. METHODS: We examine peripheral blood mononuclear cells (PBMC) and bronchoalveolar lavage cells (BAL) and lung granulomas from 28 cynomolgus macaques during Mycobacterium tuberculosis (Mtb) infection. RESULTS: CD4CD8 T cells increase in frequency during early Mtb infection in PBMC and BAL from pre-infection. Peripheral, airway, and lung granuloma CD4CD8 T cells have distinct patterns and greater cytokine production than CD4 or CD8 T cells. CONCLUSION: Our data suggest that CD4CD8 T cells transient the blood and airways early during infection to reach the granulomas where they are involved directly in the host response to Mtb.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; tuberculosis; Disease Models, Animal; Granuloma; Macaca fascicularis; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; mycobacteria; T cells; CD4CD8; Leukocytes

Apoptotic vesicles crossprime CD8 T cells and protect against tuberculosis - Winau, Florian; Weber, Stephan; Sad, Subash; de Diego, Juana; Hoops, Silvia Locatelli; Breiden, Bernadette; Sandhoff, Konrad; Brinkmann, Volker; Kaufmann, Stefan H. E.; Schaible, Ulrich E. (Immunity, 2006)
CD8 T lymphocytes are important effectors in protective immunity against Mycobacterium tuberculosis. We recently characterized the detour pathway of CD8 T cell activation in tuberculosis mediated by apoptotic vesicles from infected cells that transport mycobacterial antigens to dendritic cells (DCs). Here we demonstrate that apoptotic vesicles from mycobacteria-infected macrophages stimulate CD8 T cells in vivo. Homing of DCs to draining lymph nodes was critically required for effective crosspriming. Subsequent fate of vesicle-associated antigens in recipient DCs was characterized by endosomal mechanisms predominating over proteasomal processing. In addition, vesicle processing depended on the presence of saposins to disintegrate apoptotic membranes. Apoptotic vesicles displayed potent adjuvant activity by stimulating through Toll-like receptors (TLR). Ultimately, vaccination with vesicles from infected cells induced protection against M. tuberculosis infection. Taken together, we propose the detour pathway to represent a genuine immunological mechanism mediating crosspriming of CD8 T cells in vivo and protection against tuberculosis.
Keywords: Animals; Macrophages; Tuberculosis; BCG Vaccine; Mice; Adjuvants, Immunologic; CD8-Positive T-Lymphocytes; Dendritic Cells; Mycobacterium bovis; Vaccination; Apoptosis; Cross-Priming; Endosomes; Saposins; Toll-Like Receptors

Interleukin-10 promotes Mycobacterium tuberculosis disease progression in CBA/J mice - Beamer, Gillian L.; Flaherty, David K.; Assogba, Barnabe D.; Stromberg, Paul; Gonzalez-Juarrero, Mercedes; de Waal Malefyt, Rene; Vesosky, Bridget; Turner, Joanne (Journal of Immunology (Baltimore, Md.: 1950), 2008)
IL-10 is a potent immunomodulatory cytokine that affects innate and acquired immune responses. The immunological consequences of IL-10 production during pulmonary tuberculosis (TB) are currently unknown, although IL-10 has been implicated in reactivation TB in humans and with TB disease in mice. Using Mycobacterium tuberculosis-susceptible CBA/J mice, we show that blocking the action of IL-10 in vivo during chronic infection stabilized the pulmonary bacterial load and improved survival. Furthermore, this beneficial outcome was highly associated with the recruitment of T cells to the lungs and enhanced T cell IFN-gamma production. Our results indicate that IL-10 promotes TB disease progression. These findings have important diagnostic and/or therapeutic implications for the prevention of reactivation TB in humans.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Mice; Female; Lung; Interferon-gamma; T-Lymphocytes; Chronic Disease; Interleukin-10

Pleiotropic Effect of IL-6 Produced by B-Lymphocytes During Early Phases of Adaptive Immune Responses Against TB Infection - Linge, Irina; Tsareva, Anastasiya; Kondratieva, Elena; Dyatlov, Alexander; Hidalgo, Juan; Zvartsev, Ruslan; Apt, Alexander (Frontiers in Immunology, 2022)
The role of B cells migrating to the lung and forming follicles during tuberculosis (TB) inflammation is still the subject of debate. In addition to their antibody production and antigen-presenting functions, B cells secrete different cytokines and chemokines, thus participating in complex networks of innate and adaptive immunity. Importantly, lung B-cells produce high amounts of the pleiotropic gp130 cytokine IL-6. Its role during TB infection remains controversial, partly due to the fact that IL-6 is produced by different cell types. To investigate the impact of IL-6 produced by B cells on TB susceptibility and immune responses, we established a mouse strain with specific IL-6 deficiency in B cells (CD19cre-IL-6fl/fl, B-IL-6KO) on the B6 genetic background. Selective abrogation of IL-6 in B cells resulted in shortening the lifespan of TB-infected B-IL-6KO mice compare to the wild-type controls. We provide evidence that at the initial TB stages B cells serve as a critical source of IL-6. In the lung, the effect of IL-6 deficiency in B cells is associated rather with B and T cell functioning, than with macrophage polarization. TB-infected B-IL-6KO mice displayed diminished sizes of B cells themselves, CD4+IFN-γ+, Th17+, and CD4+CXCR5+ follicular T cell populations. The pleiotropic effect of B-cell-derived IL-6 on T-cells demonstrated in our study bridges two major lymphocyte populations and sheds some light on B- and T-cells interactions during the stage of anti-TB response when the host switches on a plethora of acquired immune reactions.
Keywords: Mycobacterium tuberculosis; Animals; tuberculosis; Tuberculosis, Pulmonary; Mice; Female; Adaptive Immunity; Mice, Inbred C57BL; B-Lymphocytes; T cells; Interleukin-6; Ablation Techniques; B-cells; IL-6; lung inflammation

Early IL-10 promotes vasculature-associated CD4+ T cells unable to control Mycobacterium tuberculosis infection - Ferreira, Catarina M.; Barbosa, Ana Margarida; Barreira-Silva, Palmira; Silvestre, Ricardo; Cunha, Cristina; Carvalho, Agostinho; Rodrigues, Fernando; Correia-Neves, Margarida; Castro, António G.; Torrado, Egídio (JCI insight, 2021)
Cytokine-producing CD4+ T cells play a crucial role in the control of Mycobacterium tuberculosis infection; however, there is a delayed appearance of effector T cells in the lungs following aerosol infection. The immunomodulatory cytokine IL-10 antagonizes control of M. tuberculosis infection through mechanisms associated with reduced CD4+ T cell responses. Here, we show that IL-10 overexpression only before the onset of the T cell response impaired control of M. tuberculosis growth; during chronic infection, IL-10 overexpression reduced the CD4+ T cell response without affecting the outcome of infection. IL-10 overexpression early during infection did not, we found, significantly impair the kinetics of CD4+ T cell priming and effector differentiation. However, CD4+ T cells primed and differentiated in an IL-10-enriched environment displayed reduced expression of CXCR3 and, because they did not migrate into the lung parenchyma, their ability to control infection was limited. Importantly, these CD4+ T cells maintained their vasculature phenotype and were unable to control infection, even after adoptive transfer into low IL-10 settings. Together our data support a model wherein, during M. tuberculosis infection, IL-10 acts intrinsically on T cells, impairing their parenchymal migratory capacity and ability to engage with infected phagocytic cells, thereby impeding control of infection.
Keywords: Humans; Animals; Tuberculosis; Mice; Female; Cytokines; CD4-Positive T-Lymphocytes; Male; Adaptive immunity; Immunology; Infectious disease; Interleukin-10

Relevance of TNF-α, IL-6 and IRAK1 gene expression for assessing disease severity and therapy effects in tuberculosis patients - Buha, Ivana; Škodrić-Trifunović, Vesna; Adžić-Vukičević, Tatjana; Ilić, Aleksandra; Blanka-Protić, Ana; Stjepanovic, Mihailo; Anđelković, Marina; Vreća, Miša; Milin-Lazović, Jelena; Spasovski, Vesna; Pavlović, Sonja (Journal of Infection in Developing Countries, 2019)
INTRODUCTION: Tuberculosis (TBC) is a contagious chronic respiratory disease which despite the known cause, Mycobacterium tuberculosis (Mtb), and many decades of successful therapy, remains one of the leading global health problems. Immune responses against Mtb infection involve both of types of immunity, but cellular immunity, in which certain cytokines and Th1 cells play a key role, is crucial. A better understanding of the functions of the cytokine network involved in the state and progression of TBC could identify specific molecular markers for monitoring of disease activity as well as therapy outcomes in TBC patients. METHODOLOGY: We investigated expression of TNF-α, IL-6 and IRAK1 genes using an RT-qPCR technique in peripheral blood mononuclear cells of 33 TBC patients and 10 healthy individuals. RESULTS: Comparison between TBC patients and healthy individuals revealed statistically significant differences for all analyzed genes. The levels of expression of TNF-α and IL-6 mRNA were higher, while the level of IRAK1 mRNA was lower in the TBC group compared to controls. Moreover, a strong positive correlation was observed between TNF-α and IL-6 gene expression. When clinical parameters were analyzed, increased levels of TNF-α mRNA were detected in patients with a longer duration of therapy (>2 months) compared to those with a shorter therapy duration (< 2 months), and in patients without anemia. CONCLUSIONS: Our results indicate that the inflammatory genes we examined play a crucial role in the pathogenesis of tuberculosis, and that the expression of the TNF-α gene could be a marker for monitoring the clinical effect of the ant-tuberculosis drugs during therapy.
Keywords: Humans; Tuberculosis, Pulmonary; Female; Biomarkers; Adult; Male; Middle Aged; Aged; Inflammation Mediators; Tumor Necrosis Factor-alpha; Interleukin-6; Real-Time Polymerase Chain Reaction; Transcriptome; cytokines; gene expression; Interleukin-1 Receptor-Associated Kinases; monitoring therapy; pulmonary tuberculosis

Lethal tuberculosis in interleukin-6-deficient mutant mice - Ladel, C. H.; Blum, C.; Dreher, A.; Reifenberg, K.; Kopf, M.; Kaufmann, S. H. (Infection and Immunity, 1997)
Tuberculosis is a chronic infectious disease which causes major health problems globally. Acquired resistance is mediated by T lymphocytes and executed by activated macrophages. In vitro studies have emphasized the importance of macrophage activation for mycobacterial growth inhibition. In vivo, the protective host response is focused on granulomatous lesions in which Mycobacterium tuberculosis is contained. A cellular immune response of the T helper 1 (Th1) type is considered central for control of tuberculosis. Using interleukin-6 (IL-6)-deficient mice, we here demonstrate a crucial role of this pluripotent cytokine in protection against M. tuberculosis but not against Mycobacterium bovis BCG. Infection with M. tuberculosis was lethal for the IL-6-deficient mice at inocula that were still controlled by IL-6-competent mice. Spleen cells from M. tuberculosis-infected IL-6-/- mouse mutants produced elevated levels of IL-4 and reduced levels of gamma interferon compared to the control levels. Cytofluorometric analyses of spleen cells from M. tuberculosis-infected mice revealed more-profound alterations in T-cell ratios in IL-6-/- mice than in control mice. We assume that IL-6 contributes to host resistance by its proinflammatory activity and by its influence on cytokine secretion.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Mice; Female; Interferon-gamma; Mice, Inbred C57BL; Male; Mycobacterium bovis; Interleukin-12; Tumor Necrosis Factor-alpha; Interleukin-4; Interleukin-6; Immunophenotyping

Role of interleukin 6 in innate immunity to Mycobacterium tuberculosis infection - Martinez, Alejandra N.; Mehra, Smriti; Kaushal, Deepak (The Journal of Infectious Diseases, 2013)
BACKGROUND: Mycobacterium tuberculosis can grow in the hostile intracellular environment of macrophages by actively evading macrophage-associated antibacterial activities. The stress response factor SigH contributes to this process by modulating β-chemokine and interleukin 6 (Il6) expression. Hence, Il6 is of critical importance for acquired immunity against M. tuberculosis infection. Here, we attempted to better characterize the role of Il6 in the immune response to M. tuberculosis infection. METHODS: A small interfering RNA-based approach was used to silence expression of the Il6 transcript in host macrophages infected with a wild-type strain of M. tuberculosis or an attenuated mutant strain of M. tuberculosis (Mtb:Δ-sigH). The outcome was measured by the analysis of bacterial burden and transcriptome-wide analysis of host gene expression. Transcriptome results were confirmed via quantitative polymerase chain reaction and enzyme-linked immunosorbent assay. RESULTS: Wild type and Mtb:Δ-sigH infection of host macrophages in which Il6 had been silenced resulted in increased expression of interferon-inducible genes, especially those involved in type I interferon signaling. The expression of Ly-6 genes was significantly higher in cells infected with Mtb:Δ-sigH, compared with those infected with the wild-type strain (P < .05). CONCLUSIONS: M. tuberculosis regulates host Il6 production to inhibit type I interferon signaling and, consequently, disease progression. Mtb:Δ-sigH is associated with delayed activation of macrophages, compared with the wild-type strain, and with delayed inflammatory stimuli as consequence. These findings have important implications for improving understanding of the mechanisms behind M. tuberculosis virulence and pathogenesis and provide an initial road map to further investigate the mechanisms that may account for the deleterious effects of type I interferons in M. tuberculosis infection.
Keywords: Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis; Mice; Immunity, Innate; Mice, Inbred C57BL; Macrophage Activation; Gene Expression Regulation; Bacterial Load; Inflammation; Transfection; Enzyme-Linked Immunosorbent Assay; RNA, Messenger; Interleukin-6; Chemokine CXCL2; Gene Silencing; Interferon Type I; Oligonucleotide Array Sequence Analysis; Real-Time Polymerase Chain Reaction; RNA, Small Interfering; Toll-Like Receptor 2; Transcriptome

Transforming growth factor-beta induces development of the T(H)17 lineage - Mangan, Paul R.; Harrington, Laurie E.; O'Quinn, Darrell B.; Helms, Whitney S.; Bullard, Daniel C.; Elson, Charles O.; Hatton, Robin D.; Wahl, Sharon M.; Schoeb, Trenton R.; Weaver, Casey T. (Nature, 2006)
A new lineage of effector CD4+ T cells characterized by production of interleukin (IL)-17, the T-helper-17 (T(H)17) lineage, was recently described based on developmental and functional features distinct from those of classical T(H)1 and T(H)2 lineages. Like T(H)1 and T(H)2, T(H)17 cells almost certainly evolved to provide adaptive immunity tailored to specific classes of pathogens, such as extracellular bacteria. Aberrant T(H)17 responses have been implicated in a growing list of autoimmune disorders. T(H)17 development has been linked to IL-23, an IL-12 cytokine family member that shares with IL-12 a common subunit, IL-12p40 (ref. 8). The IL-23 and IL-12 receptors also share a subunit, IL-12Rbeta1, that pairs with unique, inducible components, IL-23R and IL-12Rbeta2, to confer receptor responsiveness. Here we identify transforming growth factor-beta (TGF-beta) as a cytokine critical for commitment to T(H)17 development. TGF-beta acts to upregulate IL-23R expression, thereby conferring responsiveness to IL-23. Although dispensable for the development of IL-17-producing T cells in vitro and in vivo, IL-23 is required for host protection against a bacterial pathogen, Citrobacter rodentium. The action of TGF-beta on naive T cells is antagonized by interferon-gamma and IL-4, thus providing a mechanism for divergence of the T(H)1, T(H)2 and T(H)17 lineages.
Keywords: Animals; Cell Differentiation; Mice; Interferon-gamma; Th1 Cells; Receptors, Interleukin; Interleukin-4; Th2 Cells; Interleukin-17; Forkhead Transcription Factors; Cell Lineage; Interleukin-23; Interleukin-23 Subunit p19; Interleukins; Transforming Growth Factor beta

Activation-induced inhibition of interleukin 6-mediated T cell survival and signal transducer and activator of transcription 1 signaling - Teague, T. K.; Schaefer, B. C.; Hildeman, D.; Bender, J.; Mitchell, T.; Kappler, J. W.; Marrack, P. (The Journal of Experimental Medicine, 2000)
The cytokines interleukin (IL)-2, IL-4, IL-6, IL-7, and IL-15 have all previously been shown to inhibit resting T cell death in vitro. We have found a difference in the response of T cells to IL-6, depending on the activation status of the cells. IL-6 inhibited the death of naive T cells, but had no effect on the death of either superantigen-activated T cells, or T cells bearing memory markers. This was true even when the resting and activated T cells were isolated from the same animal; thus, the determining factor for IL-6 insensitivity was the activation status or activation history of the cell, and not the milieu in the animal from which the cells were isolated. Activated T cells expressed lower levels of IL-6 receptors on their surfaces, yet there were sufficient levels of receptors for signaling, as we observed similar levels of signal transducer and activator of transcription (Stat)3 phosphorylation in resting and activated T cells treated with IL-6. However, there was profound inhibition of IL-6-induced Stat1 phosphorylation in activated T cells compared with resting T cells. These data suggest that there is activation-induced inhibition of IL-6 receptor signaling in T cells. This inhibition appears to be specific for some but not all of the IL-6-mediated signaling cascades in these cells.
Keywords: Animals; Cell Survival; Cells, Cultured; Mice; Female; Cytokines; T-Lymphocyte Subsets; Mice, Inbred C57BL; Immunologic Memory; Lymphocyte Activation; Signal Transduction; Mice, Transgenic; STAT1 Transcription Factor; Interleukin-6; DNA-Binding Proteins; Phosphorylation; STAT3 Transcription Factor; Trans-Activators; Carrier Proteins; Cell Death; Dose-Response Relationship, Immunologic; Down-Regulation; Immunophenotyping; Interphase; Mice, Inbred BALB C; Receptors, Interleukin-6; Repressor Proteins; Suppressor of Cytokine Signaling 1 Protein; Suppressor of Cytokine Signaling Proteins; Transcription Factor AP-1

Stat3 activation is responsible for IL-6-dependent T cell proliferation through preventing apoptosis: generation and characterization of T cell-specific Stat3-deficient mice - Takeda, K.; Kaisho, T.; Yoshida, N.; Takeda, J.; Kishimoto, T.; Akira, S. (Journal of Immunology (Baltimore, Md.: 1950), 1998)
Stat3, a member of STAT, is activated by a variety of cytokines such as IL-6 family of cytokines, granulocyte CSF, epidermal growth factor, and leptin. A recent study with mice genetically deficient in the Stat3 gene has revealed its important role in the early embryogenesis. To assess the function of Stat3 in adult tissues, we disrupted the Stat3 gene specifically in T cells by conditional gene targeting using Cre-loxP system. In Stat3-deficient T cells, IL-6-induced proliferation was severely impaired. IL-6 did not enhance cell cycle progression, but prevented apoptosis of normal T cells. In contrast, IL-6 did not prevent apoptosis of Stat3-deficient T cells. Antiapoptotic protein, Bcl-2, was normally up-regulated in response to IL-6 even in Stat3-deficient T cells. These results demonstrate that Stat3 activation is involved in IL-6-dependent T cell proliferation through prevention of apoptosis independently of Bcl-2.
Keywords: Amino Acid Sequence; Base Sequence; Molecular Sequence Data; Animals; Organ Specificity; Mice; Recombinant Fusion Proteins; Cytokines; T-Lymphocytes; Lymphocyte Activation; Mice, Knockout; Cell Division; Apoptosis; Interleukin-6; Cell Cycle; DNA-Binding Proteins; Gene Expression Regulation, Developmental; Gene Targeting; Genes, bcl-2; Integrases; Lymphocyte Specific Protein Tyrosine Kinase p56(lck); Phosphorylation; Promoter Regions, Genetic; Protein Processing, Post-Translational; Proto-Oncogene Proteins c-bcl-2; STAT3 Transcription Factor; Trans-Activators; Viral Proteins

The wolf in sheep's clothing: the role of interleukin-6 in immunity, inflammation and cancer - Naugler, Willscott E.; Karin, Michael (Trends in Molecular Medicine, 2008)
Recent discoveries involving the cytokine interleukin (IL)-6 have originated from diverse disciplines, revealing roles in biological processes that are likewise varied. The most novel findings suggest a connection between inflammation and diseases, such as insulin resistance associated with diabetes mellitus and cancer, which had not or only weakly been appreciated previously. The IL-6 pathway is one of the mechanisms linking inflammation to these disease processes. In addition, new evidence points toward IL-6 as one of the mediators coordinating the interface between adaptive and innate immunity. Here, we review the evidence linking IL-6 to inflammatory diseases and cancer.
Keywords: Humans; Animals; Mice; Immunity, Innate; Signal Transduction; Inflammation; Neoplasms; Aging; Inflammatory Bowel Diseases; Insulin Resistance; Interleukin-6; Obesity; Rheumatic Fever

Mycobacterium bovis BCG-specific Th17 cells confer partial protection against Mycobacterium tuberculosis infection in the absence of gamma interferon - Wozniak, Teresa M.; Saunders, Bernadette M.; Ryan, Anthony A.; Britton, Warwick J. (Infection and Immunity, 2010)
Protective immunity against tuberculosis (TB) requires the integrated response of a network of lymphocytes. Both gamma interferon (IFN-γ)- and interleukin 17 (IL-17)-secreting CD4(+) T cells have been identified in subjects with latent TB infection and during experimental Mycobacterium tuberculosis infection, but the contribution of Th17 cells to protective immunity is unclear. To examine their protective effects in vivo, we transferred mycobacterium-specific IL-17- and IFN-γ-secreting CD4(+) T cells isolated from M. tuberculosis BCG-immunized IL-12p40(-/-) and IFN-γ(-/-) or wild-type mice, respectively, into M. tuberculosis-infected IL-12p40(-/-) or RAG(-/-) mice. In the absence of IL-12 and IL-23, neither IL-17-secreting (Th17) nor IFN-γ-secreting (Th1) BCG-specific T cells expanded or provided protection against M. tuberculosis. In RAG(-/-) recipients with an intact IL-12/IL-23 axis, both Th17 and Th1 cells were activated and induced significant protection against M. tuberculosis. The reduction in the bacterial load following transfer of IFN-γ(-/-) Th17 cells was associated with significant prolongation of survival compared to recipients of naïve IFN-γ(-/-) T cells. This effect was at the cost of an increased inflammatory infiltrate characterized by an excess of neutrophils. Therefore, Th17 cells can provide IFN-γ-independent protection against M. tuberculosis, and this effect may contribute to the early control of M. tuberculosis infection.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; BCG Vaccine; Mice; Female; Interferon-gamma; Mice, Inbred C57BL; Mice, Knockout; Mycobacterium bovis; Gene Expression Regulation; Th2 Cells; Interleukin-17

Th17 and regulatory T cells in mediating and restraining inflammation - Littman, Dan R.; Rudensky, Alexander Y. (Cell, 2010)
The vertebrate immune system is poised in a state of equilibrium that permits accurate and rapid protective responses against pathogens but curtails potential for causing harm to the host through targeting of "self" and provoking overexuberant inflammatory processes. In this Review we discuss this balance achieved in large part by interactions of different classes of T lymphocytes that have potent pro- or anti-inflammatory activity in the context of genetic and environmental factors, particularly the commensal microbiota.
Keywords: T-Lymphocytes, Helper-Inducer; Inflammation; T-Lymphocytes, Regulatory; Bacteria; Immune Tolerance; Intestinal Mucosa

The biological functions of T helper 17 cell effector cytokines in inflammation - Ouyang, Wenjun; Kolls, Jay K.; Zheng, Yan (Immunity, 2008)
T helper 17 (Th17) cells belong to a recently identified T helper subset, in addition to the traditional Th1 and Th2 subsets. These cells are characterized as preferential producers of interleukin-17A (IL-17A), IL-17F, IL-21, and IL-22. Th17 cells and their effector cytokines mediate host defensive mechanisms to various infections, especially extracellular bacteria infections, and are involved in the pathogenesis of many autoimmune diseases. The receptors for IL-17 and IL-22 are broadly expressed on various epithelial tissues. The effector cytokines of Th17 cells, therefore, mediate the crucial crosstalk between immune system and tissues, and play indispensable roles in tissue immunity.
Keywords: Humans; Animals; Cytokines; T-Lymphocyte Subsets; Signal Transduction; T-Lymphocytes, Helper-Inducer; Inflammation Mediators; Interleukin-17; Lymphocyte Cooperation

T Follicular Helper Cell Biology: A Decade of Discovery and Diseases - Crotty, Shane (Immunity, 2019)
Helping B cells and antibody responses is a major function of CD4+ T cells. It has been 10 years since the publication of Bcl6 as the lineage-defining transcription factor for T follicular helper (Tfh) differentiation and the requirement of Tfh cells as the specialized subset of CD4+ T cells needed for germinal centers (the microanatomical sites of B cell mutation and antibody affinity maturation) and related B cell responses. A great deal has been learned about Tfh cells in the past 10 years, particularly regarding their roles in a surprising range of diseases. Advances in the understanding of Tfh cell differentiation and function are discussed, as are the understanding of Tfh cells in infectious diseases, vaccines, autoimmune diseases, allergies, atherosclerosis, organ transplants, and cancer. This includes discussion of Tfh cells in the human immune system. Based on the discoveries to date, the next decade of Tfh research surely holds many more surprises. VIDEO ABSTRACT.
Keywords: Humans; Cell Differentiation; Communicable Diseases; B-Lymphocytes; T-Lymphocytes, Helper-Inducer; Autoimmune Diseases; Atherosclerosis; Germinal Center; Hypersensitivity; Proto-Oncogene Proteins c-bcl-6

IL-4 subverts mycobacterial containment in Mycobacterium tuberculosis-infected human macrophages - Pooran, Anil; Davids, Malika; Nel, Andrew; Shoko, Aubrey; Blackburn, Jonathan; Dheda, Keertan (The European Respiratory Journal, 2019)
Protective immunity against Mycobacterium tuberculosis is poorly understood. The role of interleukin (IL)-4, the archetypal T-helper type 2 (Th2) cytokine, in the immunopathogenesis of human tuberculosis remains unclear.Blood and/or bronchoalveolar lavage fluid (BAL) were obtained from participants with pulmonary tuberculosis (TB) (n=23) and presumed latent TB infection (LTBI) (n=22). Messenger RNA expression levels of interferon (IFN)-γ, IL-4 and its splice variant IL-4δ2 were determined by real-time PCR. The effect of human recombinant (hr)IL-4 on mycobacterial survival/containment (CFU·mL-1) was evaluated in M. tuberculosis-infected macrophages co-cultured with mycobacterial antigen-primed effector T-cells. Regulatory T-cell (Treg) and Th1 cytokine levels were evaluated using flow cytometry.In blood, but not BAL, IL-4 mRNA levels (p=0.02) and the IL-4/IFN-γ ratio (p=0.01) was higher in TB versus LTBI. hrIL-4 reduced mycobacterial containment in infected macrophages (p<0.008) in a dose-dependent manner and was associated with an increase in Tregs (p<0.001), but decreased CD4+Th1 cytokine levels (CD4+IFN-γ+ p<0.001; CD4+TNFα+ p=0.01). Blocking IL-4 significantly neutralised mycobacterial containment (p=0.03), CD4+IFNγ+ levels (p=0.03) and Treg expression (p=0.03).IL-4 can subvert mycobacterial containment in human macrophages, probably via perturbations in Treg and Th1-linked pathways. These data may have implications for the design of effective TB vaccines and host-directed therapies.
Keywords: Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Macrophages; Recombinant Proteins; Cells, Cultured; Tuberculosis, Pulmonary; Interferon-gamma; Cytokines; CD4-Positive T-Lymphocytes; Th1 Cells; Coculture Techniques; Latent Tuberculosis; Inflammation; Immunotherapy; Interleukin-4; Th2 Cells; T-Lymphocytes, Regulatory; RNA, Messenger; Bronchoalveolar Lavage Fluid

Tuberculosis associated with tumor necrosis factor-α antagonists, case description and analysis of reported cases in Colombia - Galvis, Leandro; Sánchez, Ángel Y.; Jurado, Leonardo F.; Murcia, Martha I. (Biomédica, 2018)
Tumor necrosis factor-α (TNF-α) is an important fundamental cytokine during the immune response against cancer and infections such as tuberculosis. This molecule also plays a key pathogenic role in complex and difficult-to-treat diseases such as rheumatoid arthritis, ankylosing spondylitis, Crohn’s disease, psoriasis and ulcerative colitis. The treatment of these diseases frequently needs TNF-α antagonists, which has been related to an increased risk of developing tuberculosis, mycoses, and other severe infections.We report the case of a 68-year-old man with Crohn’s disease, who developed  disseminated tuberculosis due to anti-TNF-α immunosuppressive therapy. The diagnosis was based on the histopathological findings and molecular biology assays.We discuss the clinical presentation and workup of this case, and we present a comparative analysis of tuberculosis cases associated with anti-TNF-α reported in Colombia during the last 10 years emphasizing on the diagnosis and treatment of latent tuberculosis.
Keywords: Mycobacterium tuberculosis; Colombia; Anti TNF; Artritis Reumatoide; Enfermedad de Crohn; Espondilitis Anquilosante; Síndrome de Sjögren; Tuberculosis Latente

Incidencia de tuberculosis en pacientes que reciben fármacos anti-TNF( - Gruss, Ana; Contrera, Mariela; Piñeiro, Natalia; Perna, Abayubá; Gambogi, Rosana; Alemán, Alicia; Correa, Fernando; Albornoz, Henri; Gruss, Ana; Contrera, Mariela; Piñeiro, Natalia; Perna, Abayubá; et al. (Revista Médica del Uruguay, 2020)

Tumor necrosis factor neutralization results in disseminated disease in acute and latent Mycobacterium tuberculosis infection with normal granuloma structure in a cynomolgus macaque model - Lin, Philana Ling; Myers, Amy; Smith, Le'Kneitah; Bigbee, Carolyn; Bigbee, Matthew; Fuhrman, Carl; Grieser, Heather; Chiosea, Ion; Voitenek, Nikolai N.; Capuano, Saverio V.; Klein, Edwin; Flynn, JoAnne L. (Arthritis and Rheumatism, 2010)
OBJECTIVE: An increased risk of tuberculosis has been documented in humans treated with tumor necrosis factor alpha (TNFalpha)-neutralizing agents. In murine models, impaired signaling by TNF causes exacerbation of both acute and chronic infection associated with aberrant granuloma formation and maintenance. This study was undertaken to investigate immune modulation in the setting of TNF neutralization in primary and latent tuberculosis in a non-human primate model. METHODS: Cynomolgus macaques 4 years of age or older were infected with Mycobacterium tuberculosis and subjected to clinical, microbiologic, immunologic, and radiographic examinations. Monkeys were classified as having active or latent disease 6-8 months after infection, based on clinical criteria. Monkeys used in acute infection studies were randomized to receive either adalimumab (prior to and during infection) or no treatment. Monkeys with latent infection that were randomized to receive TNF-neutralizing agent were given either an inhibitor of soluble TNF, recombinant methionyl human soluble TNF receptor I (p55-TNFRI), or adalimumab. Control monkeys with latent infection were given no treatment or saline. Data from previously studied monkeys with active or latent disease were also used for comparison. RESULTS: Administration of TNF-neutralizing agents prior to M tuberculosis infection resulted in fulminant and disseminated disease by 8 weeks after infection. Neutralization of TNF in latently infected cynomolgus macaques caused reactivation in a majority of animals as determined by gross pathologic examination and bacterial burden. A spectrum of dissemination was noted, including extrapulmonary disease. Surprisingly, monkeys that developed primary and reactivation tuberculosis after TNF neutralization had similar granuloma structure and composition to that of control monkeys with active disease. TNF neutralization was associated with increased levels of interleukin-12, decreased levels of CCL4, increased chemokine receptor expression, and reduced mycobacteria-induced interferon-gamma production in blood but not in the affected mediastinal lymph nodes. Finally, the first signs of reactivation often occurred in thoracic lymph nodes. CONCLUSION: These findings have important clinical implications for determining the mechanism of TNF neutralization-related tuberculosis.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Disease Models, Animal; Granuloma; Interferon-gamma; Macaca fascicularis; Antibodies, Monoclonal; Interleukin-12; Tumor Necrosis Factor-alpha; Chronic Disease; Interleukin-2; Acute Disease; Adalimumab; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Chemokine CCL4; Immunosuppression Therapy; Interleukin-8; Tuberculosis, Lymph Node

Tumor necrosis factor-alpha is required in the protective immune response against Mycobacterium tuberculosis in mice - Flynn, J. L.; Goldstein, M. M.; Chan, J.; Triebold, K. J.; Pfeffer, K.; Lowenstein, C. J.; Schreiber, R.; Mak, T. W.; Bloom, B. R. (Immunity, 1995)
Understanding the immunological mechanisms of protection and pathogenesis in tuberculosis remains problematic. We have examined the extent to which tumor necrosis factor-alpha (TNF alpha) contributes to this disease using murine models in which the action of TNF alpha is inhibited. TNF alpha was neutralized in vivo by monoclonal antibody; in addition, a mouse strain with a disruption in the gene for the 55 kDa TNF receptor was used. The data from both models established that TNF alpha and the 55 kDa TNF receptor are essential for protection against tuberculosis in mice, and for reactive nitrogen production by macrophages early in infection. Granulomas were formed in equal numbers in control and experimental mice, but necrosis was observed only in mice deficient in TNF alpha or TNF receptor. TNF alpha and the 55 kDa TNF receptor are necessary conditions for protection against murine M. tuberculosis infection, but are not solely responsible for the tissue damage observed.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Immunization; Polymerase Chain Reaction; BCG Vaccine; Mice; Granuloma; Female; Lung; Mice, Inbred C57BL; Antibodies, Monoclonal; Tumor Necrosis Factor-alpha; Immunohistochemistry; Amino Acid Oxidoreductases; Nitric Oxide Synthase; Receptors, Tumor Necrosis Factor

The Role of Tumor Necrosis Factor Alpha (TNF-α) in Autoimmune Disease and Current TNF-α Inhibitors in Therapeutics - Jang, Dan-In; Lee, A.-Hyeon; Shin, Hye-Yoon; Song, Hyo-Ryeong; Park, Jong-Hwi; Kang, Tae-Bong; Lee, Sang-Ryong; Yang, Seung-Hoon (International Journal of Molecular Sciences, 2021)
Tumor necrosis factor alpha (TNF-α) was initially recognized as a factor that causes the necrosis of tumors, but it has been recently identified to have additional important functions as a pathological component of autoimmune diseases. TNF-α binds to two different receptors, which initiate signal transduction pathways. These pathways lead to various cellular responses, including cell survival, differentiation, and proliferation. However, the inappropriate or excessive activation of TNF-α signaling is associated with chronic inflammation and can eventually lead to the development of pathological complications such as autoimmune diseases. Understanding of the TNF-α signaling mechanism has been expanded and applied for the treatment of immune diseases, which has resulted in the development of effective therapeutic tools, including TNF-α inhibitors. Currently, clinically approved TNF-α inhibitors have shown noticeable potency in a variety of autoimmune diseases, and novel TNF-α signaling inhibitors are being clinically evaluated. In this review, we briefly introduce the impact of TNF-α signaling on autoimmune diseases and its inhibitors, which are used as therapeutic agents against autoimmune diseases.
Keywords: Humans; Animals; Signal Transduction; Tumor Necrosis Factor-alpha; Chronic Disease; autoimmune diseases; Autoimmune Diseases; Immunologic Factors; inflammatory bowel disease; psoriatic arthritis; rheumatoid arthritis; TNF-α; TNF-α inhibitors

Ubiquilin 1 Promotes IFN-γ-Induced Xenophagy of Mycobacterium tuberculosis - Sakowski, Erik T.; Koster, Stefan; Portal Celhay, Cynthia; Park, Heidi S.; Shrestha, Elina; Hetzenecker, Stefanie E.; Maurer, Katie; Cadwell, Ken; Philips, Jennifer A. (PLoS pathogens, 2015)
The success of Mycobacterium tuberculosis (Mtb) as a pathogen rests upon its ability to grow intracellularly in macrophages. Interferon-gamma (IFN-γ) is critical in host defense against Mtb and stimulates macrophage clearance of Mtb through an autophagy pathway. Here we show that the host protein ubiquilin 1 (UBQLN1) promotes IFN-γ-mediated autophagic clearance of Mtb. Ubiquilin family members have previously been shown to recognize proteins that aggregate in neurodegenerative disorders. We find that UBQLN1 can interact with Mtb surface proteins and associates with the bacilli in vitro. In IFN-γ activated macrophages, UBQLN1 co-localizes with Mtb and promotes the anti-mycobacterial activity of IFN-γ. The association of UBQLN1 with Mtb depends upon the secreted bacterial protein, EsxA, which is involved in permeabilizing host phagosomes. In autophagy-deficient macrophages, UBQLN1 accumulates around Mtb, consistent with the idea that it marks bacilli that traffic through the autophagy pathway. Moreover, UBQLN1 promotes ubiquitin, p62, and LC3 accumulation around Mtb, acting independently of the E3 ligase parkin. In summary, we propose a model in which UBQLN1 recognizes Mtb and in turn recruits the autophagy machinery thereby promoting intracellular control of Mtb. Thus, polymorphisms in ubiquilins, which are known to influence susceptibility to neurodegenerative illnesses, might also play a role in host defense against Mtb.
Keywords: Mycobacterium tuberculosis; Animals; Macrophages; Mice; Interferon-gamma; Phagosomes; Autophagy; Adaptor Proteins, Signal Transducing; Adaptor Proteins, Vesicular Transport; Autophagy-Related Proteins

Pulmonary epithelial cells are a source of interferon-gamma in response to Mycobacterium tuberculosis infection - Sharma, Monika; Sharma, Sadhna; Roy, Sugata; Varma, Saurabh; Bose, Mridula (Immunology and Cell Biology, 2007)
Recent report from our laboratory showed that A549 cells representing alveolar epithelial cells produce chemokine interleukin-8 and nitric oxide (NO) when challenged with Mycobacterium tuberculosis. Interferon-gamma (IFN-gamma) played a critical role in priming these cells to generate NO in vitro. In the present study, we report that M. tuberculosis-infected A549 cells are capable of elaborating IFN-gamma as shown by enzyme-linked immunosorbent assay and intracellular staining for IFN-gamma. Secretion profile indicated that M. tuberculosis-infected A549 released significantly high concentration of IFN-gamma at 48 and 72 h post-infection. Low level of IFN-gamma release was also seen to be induced by gamma-irradiated M. tuberculosis and subcellular components of M. tuberculosis. Cell surface receptor analysis showed that the M. tuberculosis-infected A549 cells expressed enhanced levels of IFN-gamma receptors. This observation suggests that the endogenously produced IFN-gamma in response to M. tuberculosis infection plays a role in intracellular regulation of innate immunity against intracellular pathogen such as M. tuberculosis. This observation is further strengthened by the fact that infected A549 cells expressed signal transducer and activator of transcription 1 (STAT1), an important mediator for IFN-gamma signaling pathway, leading to expression of inducible NO synthase and subsequent release of NO in sufficient concentration to be mycobactericidal. Our results show that production of IFN-gamma and enhanced expression of IFN-gamma receptors by infected A549 cells is a local phenomenon occurring as de novo intracellular activity, in response to M. tuberculosis infection. To the best of our knowledge, this is the first report to show that A549 cells interact actively with M. tuberculosis to produce IFN-gamma that might play an important role in innate immunity against tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Epithelial Cells; Pulmonary Alveoli; Tuberculosis, Pulmonary; Lung; Interferon-gamma; Nitric Oxide; STAT1 Transcription Factor

Induction of nitric oxide release from the human alveolar epithelial cell line A549: an in vitro correlate of innate immune response to Mycobacterium tuberculosis - Roy, Sugata; Sharma, Sadhna; Sharma, Monika; Aggarwal, Ramesh; Bose, Mridula (Immunology, 2004)
In view of the presence of a large number of epithelial cells in the alveoli of the lung and their ability to produce various cytokines and chemokines, the possible role of alveolar epithelial cells in the innate immune response to tuberculosis was examined. The human alveolar epithelial cell line A549 was used as a model. The ability of A549 cells to induce nitric oxide (NO) in response to Mycobacterium tuberculosis infection was taken as an in vitro correlate of innate immunity. M. tuberculosis infection induced A549 cells to produce significant levels of NO and to express inducible nitric oxide synthase mRNA at 48 hr of infection. However, the amount of NO released at this point was not mycobactericidal. Cytokine stimulation (interferon-γ, tumour necrosis factor-α, interleukin-1β, alone or in combination) of the infected A549 cells induced a higher concentration of NO. The study of colony-forming units (CFU) as a measure of the mycobactericidal capacity of A549 cells revealed a reduction in CFU of M. tuberculosis by 39·29% (from 10·62 ± 0·48 – 6·392 ± 0·54) following cytokine stimulation of the infected cells. Interestingly γ-irradiated M. tuberculosis H37Rv could also induce higher than basal level of NO. Therefore we examined mycobacterial antigenic components for their possible role in NO production. We observed that A549 cells produced significantly higher amounts of NO at 48 hr when treated with mycobacterial whole cell lysates, cell wall or cell membrane preparations. The release of NO and the resultant mycobactericidal activity could be further enhanced by simultaneously conditioning the M. tuberculosis infected A549 cells with cytokine and mycobacterial components. These results suggest that alveolar epithelial cells respond to their microenvironment, which is constituted of various cytokines and macrophage-processed antigens and may contribute to the innate immune response to tuberculosis.

Induction of nitric oxide release from the human alveolar epithelial cell line A549: an in vitro correlate of innate immune response to Mycobacterium tuberculosis - PubMed

Ubiquilin 1 Promotes IFN-γ-Induced Xenophagy of Mycobacterium tuberculosis - PubMed

Vitamin D is required for IFN-gamma-mediated antimicrobial activity of human macrophages - Fabri, Mario; Stenger, Steffen; Shin, Dong-Min; Yuk, Jae-Min; Liu, Philip T.; Realegeno, Susan; Lee, Hye-Mi; Krutzik, Stephan R.; Schenk, Mirjam; Sieling, Peter A.; Teles, Rosane; Montoya, Dennis; et al. (Science Translational Medicine, 2011)
Control of tuberculosis worldwide depends on our understanding of human immune mechanisms, which combat the infection. Acquired T cell responses are critical for host defense against microbial pathogens, yet the mechanisms by which they act in humans remain unclear. We report that T cells, by the release of interferon-γ (IFN-γ), induce autophagy, phagosomal maturation, the production of antimicrobial peptides such as cathelicidin, and antimicrobial activity against Mycobacterium tuberculosis in human macrophages via a vitamin D-dependent pathway. IFN-γ induced the antimicrobial pathway in human macrophages cultured in vitamin D-sufficient sera, but not in sera from African-Americans that have lower amounts of vitamin D and who are more susceptible to tuberculosis. In vitro supplementation of vitamin D-deficient serum with 25-hydroxyvitamin D3 restored IFN-γ-induced antimicrobial peptide expression, autophagy, phagosome-lysosome fusion, and antimicrobial activity. These results suggest a mechanism in which vitamin D is required for acquired immunity to overcome the ability of intracellular pathogens to evade macrophage-mediated antimicrobial responses. The present findings underscore the importance of adequate amounts of vitamin D in all human populations for sustaining both innate and acquired immunity against infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Tuberculosis; Monocytes; Interferon-gamma; Lymphocyte Activation; Models, Biological; Autophagy; Anti-Infective Agents; Antimicrobial Cationic Peptides; Calcifediol; Vitamin D

IL-2 Restores T-Cell Dysfunction Induced by Persistent Mycobacterium tuberculosis Antigen Stimulation - Liu, Xun; Li, Fei; Niu, Hongxia; Ma, Lan; Chen, Jianzhu; Zhang, Ying; Peng, Liang; Gan, Chao; Ma, Xingming; Zhu, Bingdong (Frontiers in Immunology, 2019)
Tuberculosis (TB) is a chronic disease mainly caused by Mycobacterium tuberculosis. The function of T cells usually decreased and even exhausted in severe TB such as multiple drug resistant TB (MDR-TB), which might lead to the failure of treatment in return. The mechanism of T cell dysfunction in TB is still not clear. In this study we set up a mouse model of T cell dysfunction by persistent M. tuberculosis antigen stimulation and investigated the therapeutic role of interleukin 2 (IL-2) in it. C57BL/6 mice were primed with Mycobacterium bovis Bacillus Calmette-Guérin (BCG) and boosted repeatedly with a combination of M. tuberculosis fusion proteins Mtb10.4-HspX (MH) plus ESAT6-Ag85B-MPT64 <190-198>-Mtb8.4-Rv2626c (LT70) or MH plus ESAT6 and CFP10 with adjuvant of N, N'-dimethyl-N, N'-dioctadecylammonium bromide (DDA) plus polyinosinic-polycytidylic acid (Poly I:C). Following persistent antigen stimulation, the mice were treated with IL-2 and the therapeutic effects were analyzed. The results showed that compared with the mice that received transient antigen stimulation (boost twice), persistent antigen stimulation (boost more than 10 times) resulted in decrease of antigen specific IFN-γ and IL-2 production, reduction of memory CD8+ T cells, over-expression of immune checkpoint programmed cell death protein 1 (PD-1), and impaired the protective immunity against bacterial challenge. Treating the T cell functionally exhausted mice with IL-2 restored antigen-specific T cell responses and protective efficacy. In conclusion, persistent stimulation with M. tuberculosis antigens induced T cell dysfunction, which could be restored by complement of IL-2.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Animals; Antigens, Bacterial; Mice; Female; Interferon-gamma; Recombinant Fusion Proteins; CD8-Positive T-Lymphocytes; Mycobacterium bovis; Tuberculosis, Multidrug-Resistant; Interleukin-2; antigen persistence; IL-2; T cell dysfunction; T cell exhaustion

Signaling and Function of Interleukin-2 in T Lymphocytes - Ross, Sarah H.; Cantrell, Doreen A. (Annual Review of Immunology, 2018)
The discovery of interleukin-2 (IL-2) changed the molecular understanding of how the immune system is controlled. IL-2 is a pleiotropic cytokine, and dissecting the signaling pathways that allow IL-2 to control the differentiation and homeostasis of both pro- and anti-inflammatory T cells is fundamental to determining the molecular details of immune regulation. The IL-2 receptor couples to JAK tyrosine kinases and activates the STAT5 transcription factors. However, IL-2 does much more than control transcriptional programs; it is a key regulator of T cell metabolic programs. The development of global phosphoproteomic approaches has expanded the understanding of IL-2 signaling further, revealing the diversity of phosphoproteins that may be influenced by IL-2 in T cells. However, it is increasingly clear that within each T cell subset, IL-2 will signal within a framework of other signal transduction networks that together will shape the transcriptional and metabolic programs that determine T cell fate.
Keywords: Humans; Animals; Cell Differentiation; Cytokines; T-Lymphocyte Subsets; Biomarkers; T-Lymphocytes; Lymphocyte Activation; Signal Transduction; cytokine signaling; interleukin-2; Interleukin-2; JAK1/3; Janus Kinases; Phosphatidylinositol 3-Kinases; PI3K; STAT5 Transcription Factor

How Superantigens Bind MHC - Van Kaer, Luc (Journal of Immunology (Baltimore, Md.: 1950), 2018)
Keywords: Humans; Peptide Fragments; Animals; Protein Binding; Antigens, Bacterial; T-Lymphocytes; Lymphocyte Activation; Enterotoxins; Superantigens; Clonal Deletion; Histocompatibility Antigens; Minor Lymphocyte Stimulatory Antigens; Receptors, Antigen, T-Cell, alpha-beta

Crystal structure of a superantigen bound to MHC class II displays zinc and peptide dependence - Petersson, K.; Håkansson, M.; Nilsson, H.; Forsberg, G.; Svensson, L. A.; Liljas, A.; Walse, B. (The EMBO journal, 2001)
The three-dimensional structure of a bacterial superantigen, Staphylococcus aureus enterotoxin H (SEH), bound to human major histocompatibility complex (MHC) class II (HLA-DR1) has been determined by X-ray crystallography to 2.6 A resolution (1HXY). The superantigen binds on top of HLA-DR1 in a completely different way from earlier co-crystallized superantigens from S.aureus. SEH interacts with high affinity through a zinc ion with the beta1 chain of HLA-DR1 and also with the peptide presented by HLA-DR1. The structure suggests that all superantigens interacting with MHC class II in a zinc-dependent manner present the superantigen in a common way. This suggests a new model for ternary complex formation with the T-cell receptor (TCR), in which a contact between the TCR and the MHC class II is unlikely.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Protein Structure, Secondary; Models, Molecular; Protein Structure, Tertiary; Protein Conformation; Recombinant Proteins; Crystallography, X-Ray; HLA-DR1 Antigen; Sequence Alignment; Sequence Homology, Amino Acid; Cloning, Molecular; Enterotoxins; Staphylococcus aureus; Superantigens; Zinc; Zinc Fingers

Quantitative predictions of peptide binding to any HLA-DR molecule of known sequence: NetMHCIIpan - Nielsen, Morten; Lundegaard, Claus; Blicher, Thomas; Peters, Bjoern; Sette, Alessandro; Justesen, Sune; Buus, Søren; Lund, Ole (PLoS computational biology, 2008)
CD4 positive T helper cells control many aspects of specific immunity. These cells are specific for peptides derived from protein antigens and presented by molecules of the extremely polymorphic major histocompatibility complex (MHC) class II system. The identification of peptides that bind to MHC class II molecules is therefore of pivotal importance for rational discovery of immune epitopes. HLA-DR is a prominent example of a human MHC class II. Here, we present a method, NetMHCIIpan, that allows for pan-specific predictions of peptide binding to any HLA-DR molecule of known sequence. The method is derived from a large compilation of quantitative HLA-DR binding events covering 14 of the more than 500 known HLA-DR alleles. Taking both peptide and HLA sequence information into account, the method can generalize and predict peptide binding also for HLA-DR molecules where experimental data is absent. Validation of the method includes identification of endogenously derived HLA class II ligands, cross-validation, leave-one-molecule-out, and binding motif identification for hitherto uncharacterized HLA-DR molecules. The validation shows that the method can successfully predict binding for HLA-DR molecules-even in the absence of specific data for the particular molecule in question. Moreover, when compared to TEPITOPE, currently the only other publicly available prediction method aiming at providing broad HLA-DR allelic coverage, NetMHCIIpan performs equivalently for alleles included in the training of TEPITOPE while outperforming TEPITOPE on novel alleles. We propose that the method can be used to identify those hitherto uncharacterized alleles, which should be addressed experimentally in future updates of the method to cover the polymorphism of HLA-DR most efficiently. We thus conclude that the presented method meets the challenge of keeping up with the MHC polymorphism discovery rate and that it can be used to sample the MHC "space," enabling a highly efficient iterative process for improving MHC class II binding predictions.
Keywords: Amino Acid Sequence; Binding Sites; Humans; Molecular Sequence Data; Protein Binding; Algorithms; Databases, Protein; Sequence Analysis, Protein; Alleles; HLA-DR Antigens; Major Histocompatibility Complex; Sequence Alignment; Reproducibility of Results; Predictive Value of Tests; Protein Interaction Mapping

Patho-Physiology of Aging and Immune-Senescence: Possible Correlates With Comorbidity and Mortality in Middle-Aged and Old COVID-19 Patients - Farheen, Saba; Agrawal, Sudhanshu; Zubair, Swaleha; Agrawal, Anshu; Jamal, Fauzia; Altaf, Ishrat; Kashif Anwar, Abu; Umair, Syed Mohammad; Owais, Mohammad (Frontiers in Aging, 2021)
During the last 2 years, the entire world has been severely devastated by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic (COVID-19) as it resulted in several million deaths across the globe. While the virus infects people indiscriminately, the casualty risk is higher mainly in old, and middle-aged COVID-19 patients. The incidences of COVID-19 associated co-morbidity and mortality have a great deal of correlation with the weakened and malfunctioning immune systems of elderly people. Presumably, due to the physiological changes associated with aging and because of possible comorbidities such as diabetes, hypertension, obesity, cardiovascular, and lung diseases, which are more common in elderly people, may be considered as the reason making the elderly vulnerable to the infection on one hand, and COVID-19 associated complications on the other. The accretion of senescent immune cells not only contributes to the deterioration of host defense, but also results in elevated inflammatory phenotype persuaded immune dysfunction. In the present review, we envisage to correlate functioning of the immune defense of older COVID-19 patients with secondary/super infection, increased susceptibility or aggravation against already existing cancer, infectious, autoimmune, and other chronic inflammatory diseases. Moreover, we have discussed how age-linked modulations in the immune system affect therapeutic response against administered drugs as well as immunological response to various prophylactic measures including vaccination in the elderly host. The present review also provides an insight into the intricate pathophysiology of the aging and the overall immune response of the host to SARS-CoV-2 infection. A better understanding of age-related immune dysfunction is likely to help us in the development of targeted preemptive strategies for deadly COVID-19 in elderly patients.
Keywords: comorbidities; COVID-19; immunosenescence; inflammaging; innate and adaptive immune system; SARS-CoV-2

T cell ageing: effects of age on development, survival & function - Salam, Nasir; Rane, Sanket; Das, Rituparna; Faulkner, Matthew; Gund, Rupali; Kandpal, Usha; Lewis, Virginia; Mattoo, Hamid; Prabhu, Savit; Ranganathan, Vidya; Durdik, Jeannine; George, Anna; et al. (The Indian Journal of Medical Research, 2013)
Age associated decline of the immune system continues to be a major health concern. All components of innate and adaptive immunity are adversely affected to lesser or greater extent by ageing resulting in an overall decline of immunocompetence. As a result in the aged population, there is increased susceptibility to infection, poor responses to vaccination, and increased incidence of autoreactivity. There is an increasing focus on the role of T cells during ageing because of their impact on the overall immune responses. A steady decline in the production of fresh naïve T cells, more restricted T cell receptor (TCR) repertoire and weak activation of T cells are some of the effects of ageing. In this review we summarize our present understanding of the effects of ageing on naïve CD4 T cells and potential approaches for therapeutic interventions to restore protective immunity in the aged population.
Keywords: Humans; Adaptive Immunity; Immunity, Innate; CD4-Positive T-Lymphocytes; Receptors, Antigen, T-Cell; Aging; Cellular Senescence; Hematopoietic Stem Cells; Thymus Gland

Plasmodium vivax Pv12 B-cell epitopes and HLA-DRβ1*-dependent T-cell epitopes in vitro antigenicity - Yepes-Pérez, Yoelis; López, Carolina; Suárez, Carlos Fernando; Patarroyo, Manuel Alfonso (PloS One, 2018)
Malaria is an infectious disease caused by parasites from the genus Plasmodium (P. falciparum and P. vivax are responsible for 90% of all clinical cases); it is widely distributed throughout the world's tropical and subtropical regions. The P. vivax Pv12 protein is involved in invasion, is expressed on merozoite surface and has been recognised by antibodies from individuals exposed to the disease. In this study, B- and T-cell epitopes from Pv12 were predicted and characterised to advance in the design of a peptide-based vaccine against malaria. For evaluating the humoral response of individuals exposed to natural P. vivax infection from two endemic areas in Colombia, BepiPred-1.0 software was used for selecting B-cell epitopes. B-cell epitope 39038 displayed the greatest recognition by naturally-acquired antibodies and induced an IgG2/IgG4 response. NetMHCIIpan-3.1 prediction software was used for selecting peptides having high affinity binding for HLA-DRβ1* allele lineages and this was confirmed by in-vitro binding assays. T-epitopes 39113 and 39117 triggered a memory T-cell response (Stimulation Index≥2) and significant cytokine production. Combining in-silico, in-vitro and functional assays, two Pv12 protein regions (containing peptides 39038, 39040, 39113 and 39117) have thus been characterised as promising vaccine candidates against P. vivax malaria.
Keywords: Humans; Computational Biology; Epitopes, B-Lymphocyte; Immunity, Humoral; Epitopes, T-Lymphocyte; Enzyme-Linked Immunosorbent Assay; Colombia; HLA-DR beta-Chains; Plasmodium vivax

Allele frequency net 2015 update: new features for HLA epitopes, KIR and disease and HLA adverse drug reaction associations - González-Galarza, Faviel F.; Takeshita, Louise Y. C.; Santos, Eduardo J. M.; Kempson, Felicity; Maia, Maria Helena Thomaz; da Silva, Andrea Luciana Soares; Teles e Silva, André Luiz; Ghattaoraya, Gurpreet S.; Alfirevic, Ana; Jones, Andrew R.; Middleton, Derek (Nucleic Acids Research, 2015)
It has been 12 years since the Allele Frequency Net Database (AFND; http://www.allelefrequencies.net) was first launched, providing the scientific community with an online repository for the storage of immune gene frequencies in different populations across the world. There have been a significant number of improvements from the first version, making AFND a primary resource for many clinical and scientific areas including histocompatibility, immunogenetics, pharmacogenetics and anthropology studies, among many others. The most widely used part of AFND stores population frequency data (alleles, genes or haplotypes) related to human leukocyte antigens (HLA), killer-cell immunoglobulin-like receptors (KIR), major histocompatibility complex class I chain-related genes (MIC) and a number of cytokine gene polymorphisms. AFND now contains >1400 populations from more than 10 million healthy individuals. Here, we report how the main features of AFND have been updated to include a new section on 'HLA epitope' frequencies in populations, a new section capturing the results of studies identifying HLA associations with adverse drug reactions (ADRs) and one for the examination of infectious and autoimmune diseases associated with KIR polymorphisms-thus extending AFND to serve a new user base in these growing areas of research. New criteria on data quality have also been included.
Keywords: Humans; Histocompatibility Antigens Class I; Internet; Epitopes; Databases, Genetic; Disease; Drug-Related Side Effects and Adverse Reactions; Gene Frequency; HLA Antigens; Receptors, KIR

Induction of apoptosis in human neutrophils by Mycobacterium tuberculosis is dependent on mature bacterial lipoproteins - Persson, Alexander; Blomgran-Julinder, Robert; Eklund, Daniel; Lundström, Charlotte; Stendahl, Olle (Microbial Pathogenesis, 2009)
Modulation of immune cell apoptosis is a key evasion strategy utilized by Mycobacterium tuberculosis (Mtb). To be able to multiply within macrophages, the bacterium delays apoptosis and down-regulates pro-inflammatory activation in these cells, whereas apoptosis is rapidly induced in the potently bactericidal neutrophils. Initial host-pathogen interactions between neutrophils and Mtb, subsequently leading to apoptosis, need to be investigated to understand the early features during Mtb infections. Opsonized Mtb were readily phagocytosed, and the immuno-mediated phagocytosis triggered early activation of anti-apoptotic Akt in the neutrophils but the bacteria still induced apoptosis to the same extent as non-phagocytosed Mtb. Mtb-induced apoptosis was strictly dependent on NADPH oxidase-generated reactive oxygen species, compounds shown to damage lysosomal granules. Despite this, we found no involvement of damaged azurophilic granules in Mtb-induced apoptosis in human neutrophils. Instead, the Mtb-induced apoptosis was p38 MAPK dependent and induced through the mitochondrial pathway. Moreover, Mtb deficient of mature lipoproteins lacked the determinants required for induction of neutrophil apoptosis. These results show that Mtb exert a strong intrinsic capacity to induce apoptosis in neutrophils that is capable of overcoming the anti-apoptotic signaling in the cell.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Lipoproteins; Tuberculosis; Cells, Cultured; Neutrophils; Phagocytosis; Apoptosis; p38 Mitogen-Activated Protein Kinases

Large-scale in vitro expansion of polyclonal human switched-memory B lymphocytes - Néron, Sonia; Roy, Annie; Dumont, Nellie (PloS One, 2012)
Polyclonal preparations of therapeutic immunoglobulins, namely intravenous immunoglobulins (IVIg), are essential in the treatment of immunodeficiency and are increasingly used for the treatment of autoimmune and inflammatory diseases. Currently, patients' accessibility to IVIg depends exclusively upon volunteer blood donations followed by the fractionation of pooled human plasma obtained from thousands of individuals. Presently, there are no in vitro cell culture procedures allowing the preparation of polyclonal human antibodies. All in vitro human therapeutic antibodies that are currently generated are based on monoclonal antibodies, which are mostly issued from genetic engineering or single cell antibody technologies. Here, we describe an in vitro cell culture system, using CD40-CD154 interactions, that leads to a 1×10(6)-fold expansion of switched memory B lymphocytes in approximately 50 days. These expanded cells secrete polyclonal IgG, which distribution into IgG(1), IgG(2), IgG(3) and IgG(4) is similar to that of normal human serum. Such in vitro generated IgG showed relatively low self-reactivity since they interacted moderately with only 24 human antigens among a total of 9484 targets. Furthermore, up to one liter of IgG secreting cells can be produced in about 40 days. This experimental model, providing large-scale expansion of human B lymphocytes, represents a critical step toward the in vitro production of polyclonal human IgG and a new method for the ex vivo expansion of B cells for therapeutic purposes.
Keywords: Humans; Immunoglobulin G; B-Lymphocytes; Immunologic Memory; Reproducibility of Results; CD40 Antigens; CD40 Ligand; Cell Culture Techniques; Immunoglobulin A; Immunoglobulin Class Switching; Immunoglobulin E; Immunoglobulin gamma-Chains

Bacterial Ghosts of Escherichia coli Drive Efficient Maturation of Bovine Monocyte-Derived Dendritic Cells - Hajam, Irshad Ahmed; Dar, Pervaiz Ahmad; Appavoo, Elamurugan; Kishore, Subodh; Bhanuprakash, Veerakyathappa; Ganesh, Kondabattula (PloS One, 2015)
Bacterial ghosts (BGs) are empty cell envelopes derived from Gram-negative bacteria. They not only represent a potential platform for development of novel vaccines but also provide a tool for efficient adjuvant and antigen delivery system. In the present study, we investigated the interaction between BGs of Escherichia coli (E. coli) and bovine monocyte-derived dendritic cells (MoDCs). MoDCs are highly potent antigen-presenting cells and have the potential to act as a powerful tool for manipulating the immune system. We generated bovine MoDCs in vitro from blood monocytes using E. coli expressed bovine GM-CSF and IL-4 cytokines. These MoDCs displayed typical morphology and functions similar to DCs. We further investigated the E. coli BGs to induce maturation of bovine MoDCs in comparison to E. coli lipopolysaccharide (LPS). We observed the maturation marker molecules such as MHC-II, CD80 and CD86 were induced early and at higher levels in BG stimulated MoDCs as compared to the LPS stimulated MoDCs. BG mediated stimulation induced significantly higher levels of cytokine expression in bovine MoDCs than LPS. Both pro-inflammatory (IL-12 and TNF-α) and anti-inflammatory (IL-10) cytokines were induced in MoDCs after BGs stimulation. We further analysed the effects of BGs on the bovine MoDCs in an allogenic mixed lymphocyte reaction (MLR). We found the BG-treated bovine MoDCs had significantly (p<0.05) higher capacity to stimulate allogenic T cell proliferation in MLR as compared to the LPS. Taken together, these findings demonstrate the E. coli BGs induce a strong activation and maturation of bovine MoDCs.
Keywords: Kinetics; Animals; Monocytes; Cell Differentiation; Transcription, Genetic; Escherichia coli; Cattle; Cytokines; Antigen Presentation; Dendritic Cells; Phenotype; Lipopolysaccharides; Lymphocyte Culture Test, Mixed; Plasmids; RNA, Messenger

The use of carboxyfluorescein diacetate succinimidyl ester (CFSE) to monitor lymphocyte proliferation - Quah, Benjamin J. C.; Parish, Christopher R. (Journal of Visualized Experiments: JoVE, 2010)
Carboxyfluorescein succinimidyl ester (CFSE) is an effective and popular means to monitor lymphocyte division. CFSE covalently labels long-lived intracellular molecules with the fluorescent dye, carboxyfluorescein. Thus, when a CFSE-labeled cell divides, its progeny are endowed with half the number of carboxyfluorescein-tagged molecules and thus each cell division can be assessed by measuring the corresponding decrease in cell fluorescence via Flow cytometry. The capacity of CFSE to label lymphocyte populations with a high fluorescent intensity of exceptionally low variance, coupled with its low cell toxicity, make it an ideal dye to measure cell division. Since it is a fluorescein-based dye it is also compatible with a broad range of other fluorochromes making it applicable to multi-color flow cytometry. This article describes the procedures typically used for labeling mouse lymphocytes for the purpose of monitoring up to 8 cell divisions. These labeled cells can be used both for in vitro and in vivo studies.
Keywords: Animals; Flow Cytometry; Mice; Cell Division; Fluoresceins; Fluorescent Dyes; Lymphocytes; Succinimides

Improved methods for predicting peptide binding affinity to MHC class II molecules - Jensen, Kamilla Kjaergaard; Andreatta, Massimo; Marcatili, Paolo; Buus, Søren; Greenbaum, Jason A.; Yan, Zhen; Sette, Alessandro; Peters, Bjoern; Nielsen, Morten (Immunology, 2018)
Major histocompatibility complex class II (MHC-II) molecules are expressed on the surface of professional antigen-presenting cells where they display peptides to T helper cells, which orchestrate the onset and outcome of many host immune responses. Understanding which peptides will be presented by the MHC-II molecule is therefore important for understanding the activation of T helper cells and can be used to identify T-cell epitopes. We here present updated versions of two MHC-II-peptide binding affinity prediction methods, NetMHCII and NetMHCIIpan. These were constructed using an extended data set of quantitative MHC-peptide binding affinity data obtained from the Immune Epitope Database covering HLA-DR, HLA-DQ, HLA-DP and H-2 mouse molecules. We show that training with this extended data set improved the performance for peptide binding predictions for both methods. Both methods are publicly available at www.cbs.dtu.dk/services/NetMHCII-2.3 and www.cbs.dtu.dk/services/NetMHCIIpan-3.2.
Keywords: Amino Acid Sequence; Humans; Computational Biology; Protein Binding; Databases, Protein; Epitopes, T-Lymphocyte; Reproducibility of Results; Epitopes; Oligopeptides; affinity predictions; Epitope Mapping; Histocompatibility Antigens Class II; immunogenic peptides; MHC binding specificity; peptide-MHC binding; T-cell epitope

Emerging rules for subunit-based, multiantigenic, multistage chemically synthesized vaccines - Patarroyo, Manuel E.; Patarroyo, Manuel A. (Accounts of Chemical Research, 2008)
Seventeen million people die of transmittable diseases and 2/3 of the world's population suffer them annually. Malaria, tuberculosis, AIDS, hepatitis, and reemerging and new diseases are a great threat to humankind. A logical and rational approach for vaccine development is thus desperately needed. Protein chemistry provides the best tools for tackling these problems. The tremendous complexity of microbes, the different pathways they use for invading host cells, and the immune responses they induce can only be resolved by using the minimum subunit-based (chemically produced approximately 20-mer peptides), multiantigenic (most proteins involved in invasion), multistage (different invasion mechanisms) vaccine development approach. The most lethal form of malaria caused by Plasmodium falciparum (killing 3 million and affecting 500 million people worldwide annually) was used as target disease since many of its proteins, its invasion pathways, and its genome have been described recently. A New World primate (the Aotus monkey) is highly susceptibly to human malaria; its immune system molecules are 80-100% identical to those of its human counterpart, making it an excellent model for vaccine development. Chemically synthesized approximately 20-mer peptides, covering all the P. falciparum malaria proteins involved in red blood cell (RBC) invasion were synthesized by the classical t-Boc technology (based on synthetic SPf66 antimalarial vaccine information for identifying targets) and assayed in a highly sensitive, specific, and robust test for detecting receptor-ligand interactions between high-activity binding peptides (HABPs) and RBCs. HABPs were identified, some in which the molecule displays genetic variability (to be discarded due to their tremendous complexity) and elicits a strain-specific immune response and others that are conserved (no amino acid sequence variation). Conserved HABPs were synthesized in a polymeric form by adding cysteines at their N- and C-terminal ends to be used for monkey immunization. They became nonimmunogenic (no antibodies were induced) nonprotection inducers (monkeys were not protected against P. falciparum malaria challenge with a highly infective strain) suggesting a code of immunological silence or nonresponsiveness for these conserved HABPs. A large number of monkey trials involving a considerable number of Aotus monkeys were performed to break this code of immunological silence by replacing critical residues (determined by glycine peptide analogue scanning) to find that the following amino acid changes had to be made to render them antibody and protection inducing: F<-->R; W<-->Y; L<-->H; I<-->N; M<-->K; P<-->D; Q<-->E; C<-->T. The three-dimensional (3D) structure of >100 of these native modified HABPs (determined by (1)H NMR) revealed that the following structural changes had all to be achieved to allow a better fit into the major histocompatibility complex class II (MHC II)-peptide-TCR complex to properly activate the immune system: alpha-helix shortening, modifying their beta-turn, adopting segmental alpha-helix configuration, changing residue orientation, and increasing the distance of those residues fitting into the MHC II molecules from antigen-presenting cells. More than 100 such highly immunogenic, protection-inducing (against P. falciparum malaria) modified HABPs have been identified to date with this methodology, showing that it could lead to developing a highly effective subunit-based, multiantigenic, multistage synthetic vaccine against diseases scourging humankind, malaria being one of them.
Keywords: Humans; Animals; Vaccines, Subunit; Malaria Vaccines; Malaria, Falciparum; Plasmodium falciparum; Aotus trivirgatus; Antigens, Protozoan

Analyzing protein circular dichroism spectra for accurate secondary structures - Johnson, W. C. (Proteins, 1999)
We have developed an algorithm to analyze the circular dichroism of proteins for secondary structure. Its hallmark is tremendous flexibility in creating the basis set, and it also combines the ideas of many previous workers. We also present a new basis set containing the CD spectra of 22 proteins with secondary structures from high quality X-ray diffraction data. High flexibility is obtained by doing the analysis with a variable selection basis set of only eight proteins. Many variable selection basis sets fail to give a good analysis, but good analyses can be selected without any a priori knowledge by using the following criteria: (1) the sum of secondary structures should be close to 1.0, (2) no fraction of secondary structure should be less than -0.03, (3) the reconstructed CD spectrum should fit the original CD spectrum with only a small error, and (4) the fraction of alpha-helix should be similar to that obtained using all the proteins in the basis set. This algorithm gives a root mean square error for the predicted secondary structure for the proteins in the basis set of 3.3% for alpha-helix, 2.6% for 3(10)-helix, 4.2% for beta-strand, 4.2% for beta-turn, 2.7% for poly(L-proline) II type 3(1)-helix, and 5.1% for other structures when compared with the X-ray structure.
Keywords: Circular Dichroism; Protein Structure, Secondary; Algorithms; X-Ray Diffraction

Estimation of the number of alpha-helical and beta-strand segments in proteins using circular dichroism spectroscopy - Sreerama, N.; Venyaminov, S. Y.; Woody, R. W. (Protein Science: A Publication of the Protein Society, 1999)
A simple approach to estimate the number of alpha-helical and beta-strand segments from protein circular dichroism spectra is described. The alpha-helix and beta-sheet conformations in globular protein structures, assigned by DSSP and STRIDE algorithms, were divided into regular and distorted fractions by considering a certain number of terminal residues in a given alpha-helix or beta-strand segment to be distorted. The resulting secondary structure fractions for 29 reference proteins were used in the analyses of circular dichroism spectra by the SELCON method. From the performance indices of the analyses, we determined that, on an average, four residues per alpha-helix and two residues per beta-strand may be considered distorted in proteins. The number of alpha-helical and beta-strand segments and their average length in a given protein were estimated from the fraction of distorted alpha-helix and beta-strand conformations determined from the analysis of circular dichroism spectra. The statistical test for the reference protein set shows the high reliability of such a classification of protein secondary structure. The method was used to analyze the circular dichroism spectra of four additional proteins and the predicted structural characteristics agree with the crystal structure data.
Keywords: Circular Dichroism; Animals; Protein Structure, Secondary; Computer Simulation; Databases, Factual; Crystallography, X-Ray; Colicins; Green Fluorescent Proteins; Luminescent Proteins; Rats

A self-consistent method for the analysis of protein secondary structure from circular dichroism - PubMed

Estimation of globular protein secondary structure from circular dichroism - Provencher, S. W.; Glöckner, J. (Biochemistry, 1981)
A new method is developed in which a circular dichroism (CD) spectrum is analyzed directly as a linear combination of the CD spectra (from 190 to 240 nm) of 16 proteins whose secondary structures are known from X-ray crystallography. This avoids the dilemma encountered in previous methods of trying to define single reference CD spectra that were supposed to characterize such broad and variable classes as helix, beta sheet, beta turn, and "remainder". It also permits a more accurate and flexible analysis. The usual instability in using so many parameters is automatically controlled by a simple constrained statistical regularization procedure (similar to ridge regression). Sixteen tests were made by removing 1 spectrum at a time from the set of 16 and analyzing it in terms of the other 15. The product moment correlation coefficients between the computed fractions of helix, beta sheet, beta turn, and remainder and the fractions from the X-ray data were 0.96, 0.94, 0.31,, and 0.49, respectively. Thus, the helix and beta-sheet accuracy is very good. (The corresponding values calculated by a previous method with four reference spectra were 0.85, 0.25, --0.31, and 0.46.).
Keywords: Circular Dichroism; Protein Conformation; Globulins; Spectrophotometry, Ultraviolet; X-Ray Diffraction

B-Pred, a structure based B-cell epitopes prediction server - Giacò, Luciano; Amicosante, Massimo; Fraziano, Maurizio; Gherardini, Pier Federico; Ausiello, Gabriele; Helmer-Citterich, Manuela; Colizzi, Vittorio; Cabibbo, Andrea (Advances and applications in bioinformatics and chemistry: AABC, 2012)
The ability to predict immunogenic regions in selected proteins by in-silico methods has broad implications, such as allowing a quick selection of potential reagents to be used as diagnostics, vaccines, immunotherapeutics, or research tools in several branches of biological and biotechnological research. However, the prediction of antibody target sites in proteins using computational methodologies has proven to be a highly challenging task, which is likely due to the somewhat elusive nature of B-cell epitopes. This paper proposes a web-based platform for scoring potential immunological reagents based on the structures or 3D models of the proteins of interest. The method scores a protein's peptides set, which is derived from a sliding window, based on the average solvent exposure, with a filter on the average local model quality for each peptide. The platform was validated on a custom-assembled database of 1336 experimentally determined epitopes from 106 proteins for which a reliable 3D model could be obtained through standard modeling techniques. Despite showing poor sensitivity, this method can achieve a specificity of 0.70 and a positive predictive value of 0.29 by combining these two simple parameters. These values are slightly higher than those obtained with other established sequence-based or structure-based methods that have been evaluated using the same epitopes dataset. This method is implemented in a web server called B-Pred, which is accessible at http://immuno.bio.uniroma2.it/bpred. The server contains a number of original features that allow users to perform personalized reagent searches by manipulating the sliding window's width and sliding step, changing the exposure and model quality thresholds, and running sequential queries with different parameters. The B-Pred server should assist experimentalists in the rational selection of epitope antigens for a wide range of applications.
Keywords: B-cell epitopes; bioinformatics; epitope prediction; immunoinformatics; web server

Solid Phase Peptide Synthesis. I. The Synthesis of a Tetrapeptide - Merrifield, R. B. (Journal of the American Chemical Society, 1963)

General method for the rapid solid-phase synthesis of large numbers of peptides: specificity of antigen-antibody interaction at the level of individual amino acids - Houghten, R. A. (Proceedings of the National Academy of Sciences of the United States of America, 1985)
A novel yet simple method is described that facilitates the synthesis of large numbers of peptides to the extent that the synthesis process need no longer be the limiting factor in many studies involving peptides. By using the methods described, 10-20 mg of 248 different 13-residue peptides representing single amino acid variants of a segment of the hemagglutinin protein (HA1) have been prepared and characterized in less than 4 weeks. Through examination of the binding of these analogs to monoclonal antibodies raised against residues 75-110 of HA1, it was found that a single amino acid, aspartic acid at position 101, is of unique importance to the interaction. Two other residues, aspartic acid-104 and alanine-106, were found to play a lesser but significant role in the binding interaction. Other single positional residue variations appear to be of little or no importance.
Keywords: Amino Acid Sequence; Structure-Activity Relationship; Antibodies, Monoclonal; Enzyme-Linked Immunosorbent Assay; Antibody Specificity; Antigens, Viral; Epitopes; Oligopeptides; Orthomyxoviridae

Laboratory maintenance of Mycobacterium tuberculosis - Larsen, Michelle H.; Biermann, Karolin; Jacobs, William R. (Current Protocols in Microbiology, 2007)
This unit includes protocols for the laboratory maintenance of Mycobacterium tuberculosis, including growth on liquid and solid media as well as recommendations for long-term strain storage. Considerations for working with M. tuberculosis at Biosafety Level 3 containment are also discussed.
Keywords: Humans; Mycobacterium tuberculosis; Bacteriological Techniques; Clinical Laboratory Techniques; Containment of Biohazards; Culture Media; Specimen Handling

Evaluation of methods for the prediction of membrane spanning regions - Möller, S.; Croning, M. D.; Apweiler, R. (Bioinformatics (Oxford, England), 2001)
MOTIVATION: A variety of tools are available to predict the topology of transmembrane proteins. To date no independent evaluation of the performance of these tools has been published. A better understanding of the strengths and weaknesses of the different tools would guide both the biologist and the bioinformatician to make better predictions of membrane protein topology. RESULTS: Here we present an evaluation of the performance of the currently best known and most widely used methods for the prediction of transmembrane regions in proteins. Our results show that TMHMM is currently the best performing transmembrane prediction program.
Keywords: Membrane Proteins; Computational Biology; Models, Molecular; Protein Conformation; Software; Solubility; Databases as Topic; Protein Sorting Signals

Support Vector Machine-based method for predicting subcellular localization of mycobacterial proteins using evolutionary information and motifs - Rashid, Mamoon; Saha, Sudipto; Raghava, Gajendra Ps (BMC bioinformatics, 2007)
BACKGROUND: In past number of methods have been developed for predicting subcellular location of eukaryotic, prokaryotic (Gram-negative and Gram-positive bacteria) and human proteins but no method has been developed for mycobacterial proteins which may represent repertoire of potent immunogens of this dreaded pathogen. In this study, attempt has been made to develop method for predicting subcellular location of mycobacterial proteins. RESULTS: The models were trained and tested on 852 mycobacterial proteins and evaluated using five-fold cross-validation technique. First SVM (Support Vector Machine) model was developed using amino acid composition and overall accuracy of 82.51% was achieved with average accuracy (mean of class-wise accuracy) of 68.47%. In order to utilize evolutionary information, a SVM model was developed using PSSM (Position-Specific Scoring Matrix) profiles obtained from PSI-BLAST (Position-Specific Iterated BLAST) and overall accuracy achieved was of 86.62% with average accuracy of 73.71%. In addition, HMM (Hidden Markov Model), MEME/MAST (Multiple Em for Motif Elicitation/Motif Alignment and Search Tool) and hybrid model that combined two or more models were also developed. We achieved maximum overall accuracy of 86.8% with average accuracy of 89.00% using combination of PSSM based SVM model and MEME/MAST. Performance of our method was compared with that of the existing methods developed for predicting subcellular locations of Gram-positive bacterial proteins. CONCLUSION: A highly accurate method has been developed for predicting subcellular location of mycobacterial proteins. This method also predicts very important class of proteins that is membrane-attached proteins. This method will be useful in annotating newly sequenced or hypothetical mycobacterial proteins. Based on above study, a freely accessible web server TBpred http://www.imtech.res.in/raghava/tbpred/ has been developed.
Keywords: Amino Acid Sequence; Bacterial Proteins; Molecular Sequence Data; Mycobacterium tuberculosis; Databases, Protein; Artificial Intelligence; Subcellular Fractions; Sequence Analysis, Protein; Pattern Recognition, Automated; Sequence Alignment; Amino Acid Motifs

PSORTb v.2.0: expanded prediction of bacterial protein subcellular localization and insights gained from comparative proteome analysis - Gardy, J. L.; Laird, M. R.; Chen, F.; Rey, S.; Walsh, C. J.; Ester, M.; Brinkman, F. S. L. (Bioinformatics (Oxford, England), 2005)
MOTIVATION: PSORTb v.1.1 is the most precise bacterial localization prediction tool available. However, the program's predictive coverage and recall are low and the method is only applicable to Gram-negative bacteria. The goals of the present work are as follows: increase PSORTb's coverage while maintaining the existing precision level, expand it to include Gram-positive bacteria and then carry out a comparative analysis of localization. RESULTS: An expanded database of proteins of known localization and new modules using frequent subsequence-based support vector machines was introduced into PSORTb v.2.0. The program attains a precision of 96% for Gram-positive and Gram-negative bacteria and predictive coverage comparable to other tools for whole proteome analysis. We show that the proportion of proteins at each localization is remarkably consistent across species, even in species with varying proteome size. AVAILABILITY: Web-based version: http://www.psort.org/psortb. Standalone version: Available through the website under GNU General Public License. CONTACT: psort-mail@sfu.ca, brinkman@sfu.ca SUPPLEMENTARY INFORMATION: http://www.psort.org/psortb/supplementaryinfo.html.
Keywords: Bacterial Proteins; Gene Expression Profiling; Algorithms; Software; Subcellular Fractions; Sequence Analysis, Protein; Sequence Alignment; Gram-Negative Bacteria; Gram-Positive Bacteria; Proteome

SignalP 4.0: discriminating signal peptides from transmembrane regions - Petersen, Thomas Nordahl; Brunak, Søren; von Heijne, Gunnar; Nielsen, Henrik (Nature Methods, 2011)
Keywords: Computational Biology; Cell Membrane; Algorithms; Software; Protein Sorting Signals

Domain enhanced lookup time accelerated BLAST - Boratyn, Grzegorz M.; Schäffer, Alejandro A.; Agarwala, Richa; Altschul, Stephen F.; Lipman, David J.; Madden, Thomas L. (Biology Direct, 2012)
BACKGROUND: BLAST is a commonly-used software package for comparing a query sequence to a database of known sequences; in this study, we focus on protein sequences. Position-specific-iterated BLAST (PSI-BLAST) iteratively searches a protein sequence database, using the matches in round i to construct a position-specific score matrix (PSSM) for searching the database in round i + 1. Biegert and Söding developed Context-sensitive BLAST (CS-BLAST), which combines information from searching the sequence database with information derived from a library of short protein profiles to achieve better homology detection than PSI-BLAST, which builds its PSSMs from scratch. RESULTS: We describe a new method, called domain enhanced lookup time accelerated BLAST (DELTA-BLAST), which searches a database of pre-constructed PSSMs before searching a protein-sequence database, to yield better homology detection. For its PSSMs, DELTA-BLAST employs a subset of NCBI's Conserved Domain Database (CDD). On a test set derived from ASTRAL, with one round of searching, DELTA-BLAST achieves a ROC5000 of 0.270 vs. 0.116 for CS-BLAST. The performance advantage diminishes in iterated searches, but DELTA-BLAST continues to achieve better ROC scores than CS-BLAST. CONCLUSIONS: DELTA-BLAST is a useful program for the detection of remote protein homologs. It is available under the "Protein BLAST" link at http://blast.ncbi.nlm.nih.gov.
Keywords: Computational Biology; Protein Structure, Tertiary; Algorithms; Databases, Protein; Software; Sequence Analysis, Protein; Sensitivity and Specificity; Time Factors; Sequence Alignment; Internet; Reproducibility of Results; ROC Curve; Search Engine; Sequence Homology, Amino Acid

discriminating signal peptides from transmembrane regions - Search Results - PubMed

Domain enhanced lookup time accelerated BLAST - PubMed

Inhibition of mycobacterial growth in vitro following primary but not secondary vaccination with Mycobacterium bovis BCG - Fletcher, Helen A.; Tanner, Rachel; Wallis, Robert S.; Meyer, Joel; Manjaly, Zita-Rose; Harris, Stephanie; Satti, Iman; Silver, Richard F.; Hoft, Dan; Kampmann, Beate; Walker, K. Barry; Dockrell, Hazel M.; et al. (Clinical and vaccine immunology: CVI, 2013)
Despite the widespread use of the Mycobacterium bovis BCG vaccine, there are more than 9 million new cases of tuberculosis (TB) every year, and there is an urgent need for better TB vaccines. TB vaccine candidates are selected for evaluation based in part on the detection of an antigen-specific gamma interferon (IFN-γ) response. The measurement of mycobacterial growth in blood specimens obtained from subjects immunized with investigational TB vaccines may be a better in vitro correlate of in vivo vaccine efficacy. We performed a clinical study with 30 United Kingdom adults who were followed for 6 months to evaluate the abilities of both a whole-blood- and a novel peripheral blood mononuclear cell (PBMC)-based mycobacterial growth inhibition assay to measure a response to primary vaccination and revaccination with BCG. Using cryopreserved PBMCs, we observed a significant improvement in mycobacterial growth inhibition following primary vaccination but no improvement in growth inhibition following revaccination with BCG (P < 0.05). Mycobacterial growth inhibition following primary BCG vaccination was not correlated with purified protein derivative (PPD) antigen-specific IFN-γ enzyme-linked immunospot (ELISPOT) responses. We demonstrate that a mycobacterial growth inhibition assay can detect improved capacity to control growth following primary immunization, but not revaccination, with BCG. This is the first study to demonstrate that an in vitro growth inhibition assay can identify a difference in vaccine responses by comparing both primary and secondary BCG vaccinations, suggesting that in vitro growth inhibition assays may serve as better surrogates of clinical efficacy than the assays currently used for the assessment of candidate TB vaccines.
Keywords: Humans; BCG Vaccine; Female; Leukocytes, Mononuclear; Adult; Male; Middle Aged; Young Adult; Adolescent; Mycobacterium bovis; Vaccination; Healthy Volunteers; United Kingdom

In vitro measurement of protective mycobacterial immunity: antigen-specific expansion of T cells capable of inhibiting intracellular growth of bacille Calmette-Guérin - Worku, S.; Hoft, D. F. (Clinical Infectious Diseases: An Official Publication of the Infectious Diseases Society of America, 2000)
We investigated the ability of T cells expanded with mycobacterial antigens from healthy purified protein derivative-reactive donors and bacille Calmette-Guérin (BCG)-vaccinated volunteers to inhibit intracellular growth of BCG. Peripheral blood mononuclear cells were incubated for 7 days with mycobacterial whole lysate, live BCG, tetanus toxoid as control antigen, or medium alone. Autologous monocytes were separated by plastic adherence, allowed to mature for 6 days, and infected with BCG before serving as target cells. Expanded effector cells were cocultured with target cells for 72 h. Cocultures were then treated with 0.2% saponin to lyse infected monocytes and release intracellular BCG. Quantities of viable BCG present in these lysates were studied by colony-forming unit counting and radiometric labeling. We reproducibly found that lymphocytes expanded with mycobacterial whole lysate or live BCG significantly inhibited the intracellular growth of BCG, compared with lymphocytes expanded with tetanus toxoid or rested in medium. In addition, BCG vaccination enhanced the ability of T cells to inhibit intracellular mycobacterial growth in 3 of 5 volunteers. This assay may be useful for estimates of protective immunity induced by tuberculosis vaccines in human trials.
Keywords: Humans; Antigens, Bacterial; Monocytes; BCG Vaccine; T-Lymphocytes; Male; Immunologic Memory; Lymphocyte Activation; Mycobacterium bovis; Vaccination; Tuberculin; Tuberculin Test

A practical in vitro growth inhibition assay for the evaluation of TB vaccines - Kolibab, Kristopher; Parra, Marcela; Yang, Amy L.; Perera, Liyanage P.; Derrick, Steven C.; Morris, Sheldon L. (Vaccine, 2009)
New vaccines and novel immunization strategies are needed to improve the control of the global tuberculosis epidemic. To facilitate vaccine development, we have been creating in vitro mycobacterial intra-macrophage growth inhibition assays. Here we describe the development of an in vitro assay designed for BSL-2 laboratories which measures the capacity of vaccine-induced immune splenocytes to control the growth of isoniazid-resistant Mycobacterium bovis BCG (INH(r) BCG). The use of the INH(r) BCG as the infecting organism allows the discrimination of BCG bacilli used in murine vaccinations from BCG used in the in vitro assay. In this study, we showed that protective immune responses evoked by four different types of Mycobacterium tuberculosis vaccines [BCG, an ESAT6/Antigen 85B fusion protein formulated in DDA/MPL adjuvant, a DNA vaccine expressing the same fusion protein, and a TB Modified Vaccinia Ankara construct expressing four TB antigens (MVA-4TB)] were detected. Importantly, the levels of vaccine-induced protective immunity seen in the in vitro assay correlated with the results from in vivo protection studies in the mouse model of pulmonary tuberculosis. Furthermore, the growth inhibition data for the INH(r) BCG assay was similar to the previously reported results for a M. tuberculosis infection assay. The cytokine expression profiles at day 7 of the INH(r) BCG growth inhibition studies were also similar but not identical to the cytokine patterns detected in earlier M. tuberculosis co-culture assays. Overall, we have shown that a BSL-2 compatible in vitro growth inhibition assay using INH(r) BCG as the intra-macrophage target organism should be useful in developing and evaluating new TB immunization strategies.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Mice; Vaccines, DNA; Female

A new tool for tuberculosis vaccine screening: Ex vivo Mycobacterial Growth Inhibition Assay indicates BCG-mediated protection in a murine model of tuberculosis - Zelmer, Andrea; Tanner, Rachel; Stylianou, Elena; Damelang, Timon; Morris, Sheldon; Izzo, Angelo; Williams, Ann; Sharpe, Sally; Pepponi, Ilaria; Walker, Barry; Hokey, David A.; McShane, Helen; et al. (BMC infectious diseases, 2016)
BACKGROUND: In the absence of a validated animal model and/or an immune correlate which predict vaccine-mediated protection, large-scale clinical trials are currently the only option to prove efficacy of new tuberculosis candidate vaccines. Tools to facilitate testing of new tuberculosis (TB) vaccines are therefore urgently needed. METHODS: We present here an optimized ex vivo mycobacterial growth inhibition assay (MGIA) using a murine Mycobacterium tuberculosis infection model. This assay assesses the combined ability of host immune cells to inhibit mycobacterial growth in response to vaccination. C57BL/6 mice were immunized with Bacillus Calmette-Guérin (BCG) and growth inhibition of mycobacteria by splenocytes was assessed. Mice were also challenged with Mycobacterium tuberculosis Erdman, and bacterial burden was assessed in lungs and spleen. RESULTS: Using the growth inhibition assay, we find a reduction in BCG CFU of 0.3-0.8 log10 after co-culture with murine splenocytes from BCG vaccinated versus naïve C57BL/6 mice. BCG vaccination in our hands led to a reduction in bacterial burden after challenge with Mycobacterium tuberculosis of approx. 0.7 log10 CFU in lung and approx. 1 log10 CFU in spleen. This effect was also seen when using Mycobacterium smegmatis as the target of growth inhibition. An increase in mycobacterial numbers was found when splenocytes from interferon gamma-deficient mice were used, compared to wild type controls, indicating that immune mechanisms may also be investigated using this assay. CONCLUSIONS: We believe that the ex vivo mycobacterial growth inhibition assay could be a useful tool to help assess vaccine efficacy in future, alongside other established methods. It could also be a valuable tool for determination of underlying immune mechanisms.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Mycobacterium smegmatis; BCG Vaccine; Drug Evaluation, Preclinical; Mice; Disease Models, Animal; Female; Interferon-gamma; Mice, Inbred C57BL; Spleen; Coculture Techniques; Mycobacterium bovis; Vaccination; Colony Count, Microbial; Vaccines; Growth inhibition assay; Mice, Mutant Strains; Mycobacteria

Human Leukocyte Antigen (HLA)-DRB1*15:01 and HLA-DRB5*01:01 Present Complementary Peptide Repertoires - Scholz, Erika Margaret; Marcilla, Miguel; Daura, Xavier; Arribas-Layton, David; James, Eddie A.; Alvarez, Iñaki (Frontiers in Immunology, 2017)
Human leukocyte antigen (HLA)-DR15 is a haplotype associated with multiple sclerosis. It contains the two DRB* genes DRB1*1501 (DR2b) and DRB5*0101 (DR2a). The reported anchor motif of the corresponding HLA-DR molecules was determined in 1994 based on a small number of peptide ligands and binding assays. DR2a could display a set of peptides complementary to that presented by DR2b or, alternatively, a similar peptide repertoire but recognized in a different manner by T cells. It is known that DR2a and DR2b share some peptide ligands, although the degree of similarity of their associated peptidomes remains unclear. In addition, the contribution of each molecule to the global peptide repertoire presented by the HLA-DR15 haplotype has not been evaluated. We used mass spectrometry to analyze the peptide pools bound to DR2a and DR2b, identifying 169 and 555 unique peptide ligands of DR2a and DR2b, respectively. The analysis of these sets of peptides allowed the refinement of the corresponding binding motifs revealing novel anchor residues that had been overlooked in previous analyses. Moreover, the number of shared ligands between both molecules was low, indicating that DR2a and DR2b present complementary peptide repertoires to T cells. Finally, our analysis suggests that, quantitatively, both molecules contribute to the peptide repertoire presented by cells expressing the HLA-DR15 haplotype.
Keywords: binding motif; human leukocyte antigen-DR; mass spectrometry; multiple sclerosis; peptidome

Crystal structure of the HLA-DM-HLA-DR1 complex defines mechanisms for rapid peptide selection - Pos, Wouter; Sethi, Dhruv K.; Call, Melissa J.; Schulze, Monika-Sarah E. D.; Anders, Anne-Kathrin; Pyrdol, Jason; Wucherpfennig, Kai W. (Cell, 2012)
HLA-DR molecules bind microbial peptides in an endosomal compartment and present them on the cell surface for CD4 T cell surveillance. HLA-DM plays a critical role in the endosomal peptide selection process. The structure of the HLA-DM-HLA-DR complex shows major rearrangements of the HLA-DR peptide-binding groove. Flipping of a tryptophan away from the HLA-DR1 P1 pocket enables major conformational changes that position hydrophobic HLA-DR residues into the P1 pocket. These conformational changes accelerate peptide dissociation and stabilize the empty HLA-DR peptide-binding groove. Initially, incoming peptides have access to only part of the HLA-DR groove and need to compete with HLA-DR residues for access to the P2 site and the hydrophobic P1 pocket. This energetic barrier creates a rapid and stringent selection process for the highest-affinity binders. Insertion of peptide residues into the P2 and P1 sites reverses the conformational changes, terminating selection through DM dissociation.
Keywords: Amino Acid Sequence; Humans; Molecular Sequence Data; Animals; Models, Molecular; Protein Conformation; Crystallography, X-Ray; HLA-D Antigens; HLA-DR1 Antigen; Hydrophobic and Hydrophilic Interactions; Protein Interaction Domains and Motifs; Sequence Alignment

Structural analysis of the HLA-DR, -DQ, and -DP alleles on the celiac disease-associated HLA-DR3 (DRw17) haplotype - Kagnoff, M. F.; Harwood, J. I.; Bugawan, T. L.; Erlich, H. A. (Proceedings of the National Academy of Sciences of the United States of America, 1989)
Celiac disease is strongly associated with the HLA class II D-region serologic markers DR3 (DRw17) and DQw2. Moreover, by restriction fragment length polymorphism analysis, greater than 90% of DR3 (DRw17), DQw2 celiac disease patients have a polymorphic 4.0-kilobase Rsa I DP B gene DNA fragment. The present study sought to determine if there is a unique HLA class II D-region A or B gene structural variant on the DR3 (DRw17) haplotype found in celiac disease. The polymorphic second exons of the coding DRB, DQA and DQB, and DPA and DPB genes in celiac disease patients with the DR3 (DRw17) haplotype were sequenced after amplification by the polymerase chain reaction. To define the DP B genes associated with celiac disease, the second exons of the coding DP B genes from 27 celiac disease patients were amplified similarly and probed by using a panel of sequence specific oligonucleotides. The HLA-DR, -DQ, and -DP A and B gene second exon sequences of celiac disease patients were noted to be identical to sequences that can be found also, although at a significantly lower frequency, in unaffected individuals. This is compatible with a disease model wherein the HLA class II genes on the DR3 (DRw17) haplotype are necessary, but not sufficient, for the phenotypic expression of celiac disease. Analysis of the DP B genes revealed a significant increase in the frequency of the alleles DPB1 and DPB3 in celiac disease. Furthermore, the increased frequency of the 4.0-kilobase Rsa I DP B gene restriction fragment length polymorphism in celiac disease can be accounted for by the overrepresentation in disease of the alleles DPB1 and DPB3. The HLA-associated susceptibility to celiac disease appears to be multigenic, with specific, but structurally normal, allelic variants in the DP and DQ/DR subregions contributing to disease susceptibility.
Keywords: Amino Acid Sequence; Cell Line; Humans; Molecular Sequence Data; Genetic Variation; Alleles; Celiac Disease; DNA-Directed DNA Polymerase; Gene Amplification; Haplotypes; HLA-DP Antigens; HLA-DQ Antigens; HLA-DR Antigens; HLA-DR3 Antigen; Major Histocompatibility Complex

Structural Insights Into HLA-DM Mediated MHC II Peptide Exchange - Painter, Corrie A.; Stern, Lawrence J. (Current Topics in Biochemical Research, 2011)
Antigen presentation by class II MHC proteins (MHC-II) is a critical component of the adaptive immune response to foreign pathogens. Our understanding of how antigens are presented has been greatly enhanced by crystallographic studies of MHC-II-peptide complexes, which have shown a canonical extended conformation of peptide antigens within the peptide-binding domain of MHC-II. However, a detailed understanding of the peptide loading process, which is mediated by the accessory molecule HLA-DM (DM), remains unresolved. MHC-II proteins appear to undergo conformational changes during the peptide loading/exchange process that have not been clearly described in a structural context. In the absence of a crystal structure for the DM-MHC-II complex, mutational studies have provided a low resolution understanding as to how these molecules interact. This review will focus on structural and biochemical studies of the MHC-II-peptide interaction, and on studies of the DM-MHC-II interaction, with an emphasis on identifying structural features important for the mechanism of DM mediated peptide catalysis.
Keywords: Antigen Presentation; H2-M; HLA-DP; HLA-DQ; HLA-DR; I-A; I-E; Immune Response; MHC protein

Double dimer peptide constructs are immunogenic and protective against Plasmodium falciparum in the experimental Aotus monkey model - Rivera, Z.; Granados, G.; Pinto, M.; Varón, D.; Carvajal, C.; Chaves, F.; Calvo, J.; Rodríguez, R.; Guzmán, F.; Patarroyo, M. E. (The Journal of Peptide Research: Official Journal of the American Peptide Society, 2002)
Multiple antigen peptide constructs (MAPs) have been used to obtain defined multimeric peptide molecules useful in the development of possible synthetic malaria vaccines. In this context, a method was developed, named double dimer constructs (DDCs), involving the direct synthesis of a dimeric peptide with a C-terminal cysteine. A tetrameric molecule was then obtained by oxidation of sulfhydryl groups. Dimer synthesis was optimized using a Fmoc/tBu strategy, dimers were purified by HPLC, oxidized with DMSO and characterized by HPLC and MALDI-TOF-MS. The tetramers or DDCs obtained by this method were used as immunogens in the search for a possible malaria vaccine. It was found that they were immunogenic in the experimental Aotus monkey model, and were able to induce protective immunity when challenged experimentally with a highly infective Plasmodium falciparum malaria strain.
Keywords: Amino Acid Sequence; Molecular Sequence Data; Animals; Plasmodium falciparum; Aotus trivirgatus; Antigens, Protozoan; Dimerization; Fluorescent Antibody Technique, Indirect

IMPIPS: the immune protection-inducing protein structure concept in the search for steric-electron and topochemical principles for complete fully-protective chemically synthesised vaccine development - PubMed

Steric-electronic effects in malarial peptides inducing sterile immunity - Moreno-Vranich, Armando; Patarroyo, Manuel E. (Biochemical and Biophysical Research Communications, 2012)
Conserved Plasmodium falciparum high activity binding peptides' (HABPs) most relevant proteins involved in malaria parasite invasion are immunologically silent; critical binding residues must therefore be specifically replaced to render them highly immunogenic and protection-inducing. Such changes have a tremendous impact on these peptides' steric-electronic effects, such as modifications to peptide length peptide bonds and electronic orbitals' disposition, to allow a better fit into immune system MHCII molecules and better interaction with the TCR which might account for the final immunological outcome.
Keywords: Animals; Peptides; Protein Conformation; Immunity; Plasmodium falciparum; Receptors, Antigen, T-Cell; Malaria; Aotus trivirgatus; Electrons; Immune System

Recent advances in the development of a chemically synthesised anti-malarial vaccine - Curtidor, Hernando; Patarroyo, Manuel E.; Patarroyo, Manuel A. (Expert Opinion on Biological Therapy, 2015)
INTRODUCTION: Obtaining an effective antimalarial vaccine has represented one of the biggest public health challenges over the last 50 years. Despite efforts by many laboratories around the world using whole-organism, recombinant proteins and genome-based approaches, the results have been disappointing. One of the main problems when designing an antimalarial vaccine is the poor immunogenicity induced by the functionally relevant and conserved protein regions of the parasite. AREAS COVERED: This review focuses on the logical and rational methodology followed to identify Plasmodium falciparum conserved functional regions with the ability to bind to target cells conserved high activity binding peptides (cHABPs) and the physicochemical and immunological characteristics that should be taken into account for modifying them into highly immunogenic and protection-inducing peptides (mHABPs) into highly immunogenic and protection-inducing in Aotus monkeys. EXPERT OPINION: The functional approach taken to develop a fully protective, minimal subunit-based, multiantigenic, multistage and synthetic peptide-based antimalarial vaccine has shown promising results. The clear relationship observed between mHABPs structure and their immunological properties highlights the challenges and opportunities arising from this methodology, as well as the universal principles and rules derived therefrom.
Keywords: Humans; Peptides; Protein Binding; Vaccines, Synthetic; Recombinant Proteins; vaccine; Vaccines, Subunit; Malaria Vaccines; Plasmodium falciparum; malaria; Malaria; Plasmodium; Protozoan Proteins; rational design; synthetic peptides

Computational prediction and experimental assessment of secreted/surface proteins from Mycobacterium tuberculosis H37Rv - Vizcaíno, Carolina; Restrepo-Montoya, Daniel; Rodríguez, Diana; Niño, Luis F.; Ocampo, Marisol; Vanegas, Magnolia; Reguero, María T.; Martínez, Nora L.; Patarroyo, Manuel E.; Patarroyo, Manuel A. (PLoS computational biology, 2010)
The mycobacterial cell envelope has been implicated in the pathogenicity of tuberculosis and therefore has been a prime target for the identification and characterization of surface proteins with potential application in drug and vaccine development. In this study, the genome of Mycobacterium tuberculosis H37Rv was screened using Machine Learning tools that included feature-based predictors, general localizers and transmembrane topology predictors to identify proteins that are potentially secreted to the surface of M. tuberculosis, or to the extracellular milieu through different secretory pathways. The subcellular localization of a set of 8 hypothetically secreted/surface candidate proteins was experimentally assessed by cellular fractionation and immunoelectron microscopy (IEM) to determine the reliability of the computational methodology proposed here, using 4 secreted/surface proteins with experimental confirmation as positive controls and 2 cytoplasmic proteins as negative controls. Subcellular fractionation and IEM studies provided evidence that the candidate proteins Rv0403c, Rv3630, Rv1022, Rv0835, Rv0361 and Rv0178 are secreted either to the mycobacterial surface or to the extracellular milieu. Surface localization was also confirmed for the positive controls, whereas negative controls were located on the cytoplasm. Based on statistical learning methods, we obtained computational subcellular localization predictions that were experimentally assessed and allowed us to construct a computational protocol with experimental support that allowed us to identify a new set of secreted/surface proteins as potential vaccine candidates.
Keywords: Antibodies, Bacterial; Mycobacterium tuberculosis; Animals; Microscopy, Immunoelectron; Peptides; Rabbits; Computational Biology; Epitopes, B-Lymphocyte; Bacterial Outer Membrane Proteins; Artificial Intelligence; Cell Fractionation; Electrophoresis, Polyacrylamide Gel; Escherichia coli; Immunoblotting; Models, Statistical; Mycobacterium smegmatis; Sonication; Subcellular Fractions

Validating subcellular localization prediction tools with mycobacterial proteins - Restrepo-Montoya, Daniel; Vizcaíno, Carolina; Niño, Luis F.; Ocampo, Marisol; Patarroyo, Manuel E.; Patarroyo, Manuel A. (BMC bioinformatics, 2009)
BACKGROUND: The computational prediction of mycobacterial proteins' subcellular localization is of key importance for proteome annotation and for the identification of new drug targets and vaccine candidates. Several subcellular localization classifiers have been developed over the past few years, which have comprised both general localization and feature-based classifiers. Here, we have validated the ability of different bioinformatics approaches, through the use of SignalP 2.0, TatP 1.0, LipoP 1.0, Phobius, PA-SUB 2.5, PSORTb v.2.0.4 and Gpos-PLoc, to predict secreted bacterial proteins. These computational tools were compared in terms of sensitivity, specificity and Matthew's correlation coefficient (MCC) using a set of mycobacterial proteins having less than 40% identity, none of which are included in the training data sets of the validated tools and whose subcellular localization have been experimentally confirmed. These proteins belong to the TBpred training data set, a computational tool specifically designed to predict mycobacterial proteins. RESULTS: A final validation set of 272 mycobacterial proteins was obtained from the initial set of 852 mycobacterial proteins. According to the results of the validation metrics, all tools presented specificity above 0.90, while dispersion sensitivity and MCC values were above 0.22. PA-SUB 2.5 presented the highest values; however, these results might be biased due to the methodology used by this tool. PSORTb v.2.0.4 left 56 proteins out of the classification, while Gpos-PLoc left just one protein out. CONCLUSION: Both subcellular localization approaches had high predictive specificity and high recognition of true negatives for the tested data set. Among those tools whose predictions are not based on homology searches against SWISS-PROT, Gpos-PLoc was the general localization tool with the best predictive performance, while SignalP 2.0 was the best tool among the ones using a feature-based approach. Even though PA-SUB 2.5 presented the highest metrics, it should be taken into account that this tool was trained using all proteins reported in SWISS-PROT, which includes the protein set tested in this study, either as a BLAST search or as a training model.
Keywords: Bacterial Proteins; Computational Biology; Algorithms; Databases, Protein; Mycobacterium; Software

Tuberculosis vaccines: Opportunities and challenges - Zhu, Bingdong; Dockrell, Hazel M.; Ottenhoff, Tom H. M.; Evans, Thomas G.; Zhang, Ying (Respirology (Carlton, Vic.), 2018)
Tuberculosis (TB) is a serious disease around the world. Bacillus Calmette-Guérin (BCG) is the only TB vaccine licensed for use in human beings, and is effective in protecting infants and children against severe miliary and meningeal TB. However, BCG's protective efficacy is variable in adults. Novel TB vaccine candidates being developed include whole-cell vaccines (recombinant BCG (rBCG), attenuated Mycobacterium tuberculosis, killed M. tuberculosis or Mycobacterium vaccae), adjuvanted protein subunit vaccines, viral vector-delivered subunit vaccines, plasmid DNA vaccines, RNA-based vaccines etc. At least 12 novel TB vaccine candidates are now in clinical trials, including killed M. vaccae, rBCG ΔureC::hly, adjuvanted fusion proteins M72 and H56 and viral vectored MVA85A. Unfortunately, in TB, there are no correlates of vaccine-induced protection, although cell-mediated immune responses such as interferon-gamma (IFN-γ) production are widely used to assess vaccine's immunogenicity. Recent studies suggested that central memory T cells and local secreted IgA correlated with protection against TB disease. Clinical TB vaccine efficacy trials should invest in identifying correlates of protection, and evaluate new TB biomarkers emerging from human and animal studies. Accumulating new knowledge on M. tuberculosis antigens and immune profiles correlating with protection or disease risk will be of great help in designing next generation of TB vaccines.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; tuberculosis; BCG Vaccine; Vaccines, DNA; Adjuvants, Immunologic; Biomarkers; Vaccines, Attenuated; Clinical Trials as Topic; immunity; biomarkers; clinical trials; Immunogenicity, Vaccine; vaccines; Vaccines, Inactivated

TB Vaccine Pipeline - WGNV (Working Group on New TB Vaccines)
TB Vaccine Pipeline TB Vaccine Pipeline Sortable Pipeline This Pipeline currently provides information on vaccine candidates in clinical development. Information on candidates in preclinical developments is currently being collected. These candidates will be added to the Pipeline when the information is available. If you would like to submit a vaccine candidate for inclusion in the…

Deciphering the biology of Mycobacterium tuberculosis from the complete genome sequence - Cole, S. T.; Brosch, R.; Parkhill, J.; Garnier, T.; Churcher, C.; Harris, D.; Gordon, S. V.; Eiglmeier, K.; Gas, S.; Barry, C. E.; Tekaia, F.; Badcock, K.; et al. (Nature, 1998)
Countless millions of people have died from tuberculosis, a chronic infectious disease caused by the tubercle bacillus. The complete genome sequence of the best-characterized strain of Mycobacterium tuberculosis, H37Rv, has been determined and analysed in order to improve our understanding of the biology of this slow-growing pathogen and to help the conception of new prophylactic and therapeutic interventions. The genome comprises 4,411,529 base pairs, contains around 4,000 genes, and has a very high guanine + cytosine content that is reflected in the biased amino-acid content of the proteins. M. tuberculosis differs radically from other bacteria in that a very large portion of its coding capacity is devoted to the production of enzymes involved in lipogenesis and lipolysis, and to two new families of glycine-rich proteins with a repetitive structure that may represent a source of antigenic variation.
Keywords: Humans; Molecular Sequence Data; Mycobacterium tuberculosis; Tuberculosis; Sequence Analysis, DNA; Genome, Bacterial; Chromosome Mapping; Chromosomes, Bacterial; Drug Resistance, Microbial; Lipid Metabolism

CD1b Tetramers Broadly Detect T Cells That Correlate With Mycobacterial Exposure but Not Tuberculosis Disease State - Lopez, Kattya; Iwany, Sarah K.; Suliman, Sara; Reijneveld, Josephine F.; Ocampo, Tonatiuh A.; Jimenez, Judith; Calderon, Roger; Lecca, Leonid; Murray, Megan B.; Moody, D. Branch; Van Rhijn, Ildiko (Frontiers in Immunology, 2020)
The non-polymorphic nature of CD1 proteins creates a situation in which T cells with invariant T cell receptors (TCRs), like CD1d-specific NKT cells, are present in all humans. CD1b is an abundant protein on human dendritic cells that presents M. tuberculosis (Mtb) lipid antigens to T cells. Analysis of T cell clones suggested that semi-invariant TCRs exist in the CD1b system, but their prevalence in humans is not known. Here we used CD1b tetramers loaded with mycolic acid or glucose monomycolate to study polyclonal T cells from 150 Peruvian subjects. We found that CD1b tetramers loaded with mycolic acid or glucose monomycolate antigens stained TRAV1-2+ GEM T cells or TRBV4-1+ LDN5-like T cells in the majority of subjects tested, at rates ~10-fold lower than NKT cells. Thus, GEM T cells and LDN5-like T cells are a normal part of the human immune system. Unlike prior studies measuring MHC- or CD1b-mediated activation, this large-scale tetramer study found no significant differences in rates of CD1b tetramer-mycobacterial lipid staining of T cells among subjects with Mtb exposure, latent Mtb infection or active tuberculosis (TB) disease. In all subjects, including "uninfected" subjects, CD1b tetramer+ T cells expressed memory markers at high levels. However, among controls with lower mycobacterial antigen exposure in Boston, we found significantly lower frequencies of T cells staining with CD1b tetramers loaded with mycobacterial lipids. These data link CD1b-specific T cell detection to mycobacterial exposure, but not TB disease status, which potentially explains differences in outcomes among CD1-based clinical studies, which used control subjects with low Mtb exposure.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; tuberculosis; Female; T-Lymphocytes; Adult; Male; Middle Aged; Antigens, CD1; Glycolipids; mycobacteria; T cell receptor; CD1b; glycolipids; Leukocyte Common Antigens; Mycolic Acids; Receptors, Antigen, T-Cell; tetramer

CD1b Tetramers Identify T Cells that Recognize Natural and Synthetic Diacylated Sulfoglycolipids from Mycobacterium tuberculosis - James, Charlotte A.; Yu, Krystle K. Q.; Gilleron, Martine; Prandi, Jacques; Yedulla, Vijayendar R.; Moleda, Zuzanna Z.; Diamanti, Eleonora; Khan, Momin; Aggarwal, Varinder K.; Reijneveld, Josephine F.; Reinink, Peter; Lenz, Stefanie; et al. (Cell Chemical Biology, 2018)
Mycobacterial cell wall lipids bind the conserved CD1 family of antigen-presenting molecules and activate T cells via their T cell receptors (TCRs). Sulfoglycolipids (SGLs) are uniquely synthesized by Mycobacterium tuberculosis, but tools to study SGL-specific T cells in humans are lacking. We designed a novel hybrid synthesis of a naturally occurring SGL, generated CD1b tetramers loaded with natural or synthetic SGL analogs, and studied the molecular requirements for TCR binding and T cell activation. Two T cell lines derived using natural SGLs are activated by synthetic analogs independently of lipid chain length and hydroxylation, but differentially by saturation status. By contrast, two T cell lines derived using an unsaturated SGL synthetic analog were not activated by the natural antigen. Our data provide a bioequivalence hierarchy of synthetic SGL analogs and SGL-loaded CD1b tetramers. These reagents can now be applied to large-scale translational studies investigating the diagnostic potential of SGL-specific T cell responses or SGL-based vaccines.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Tuberculosis; Models, Molecular; tuberculosis; T-Lymphocytes; Lymphocyte Activation; Acylation; antigen-presentation; Antigens, CD1; CD1; Glycolipids; human; lipid antigen; mycobacteria; Protein Multimerization; T cell receptor; T cells

Lipoproteins are major targets of the polyclonal human T cell response to Mycobacterium tuberculosis - Seshadri, Chetan; Turner, Marie T.; Lewinsohn, David M.; Moody, D. Branch; Van Rhijn, Ildiko (Journal of Immunology (Baltimore, Md.: 1950), 2013)
Most vaccines and basic studies of T cell epitopes in Mycobacterium tuberculosis emphasize water-soluble proteins that are secreted into the extracellular space and presented in the context of MHC class II. Much less is known about the role of Ags retained within the cell wall. We used polyclonal T cells from infected humans to probe for responses to immunodominant Ags in the M. tuberculosis cell wall. We found that the magnitude of response to secreted or cell wall intrinsic compounds was similar among healthy controls, patients with latent tuberculosis, and patients with active tuberculosis. Individual responses to secreted Ags and cell wall extract were strongly correlated (r(2) = 0.495, p = 0.001), suggesting that T cells responding to cell wall and secreted Ags are present at similar frequency. Surprisingly, T cell stimulatory factors intrinsic to the cell wall partition into organic solvents; however, these responses are not explained by CD1-mediated presentation of lipids. Instead, we find that molecules soluble in organic solvents are dependent upon MHC class II and recognized by IFN-γ-secreting CD4(+) T cells. We reasoned that MHC class II-dependent Ags extracting into lipid mixtures might be found among triacylated lipoproteins present in mycobacteria. We used M. tuberculosis lacking prolipoprotein signal peptidase A (lspA), an enzyme required for lipoprotein synthesis, to demonstrate loss of polyclonal T cell responses. Our results demonstrate the use of bacterial genetics to identify lipoproteins as an unexpected and immunodominant class of cell wall-associated Ags targeted by the polyclonal human T cell response to M. tuberculosis.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Lipoproteins; Antigens, Bacterial; Cell Wall; Female; Adjuvants, Immunologic; T-Lymphocyte Subsets; Adult; Male; Middle Aged; Lymphocyte Activation; Clone Cells; Immunodominant Epitopes

Antibodies and tuberculosis: finally coming of age? - Li, Hao; Javid, Babak (Nature Reviews. Immunology, 2018)
Are antibodies important for protection against tuberculosis? The jury has been out for more than 100 years. B cell depletion in experimental Mycobacterium tuberculosis infection failed to identify a major role for these cells in immunity to tuberculosis. However, recent identification of naturally occurring antibodies in humans that are protective during M. tuberculosis infection has reignited the debate. Here, we discuss the evidence for a protective role for antibodies in tuberculosis and consider the feasibility of designing novel tuberculosis vaccines targeting humoral immunity.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; Immunity, Innate; Models, Immunological; B-Lymphocytes; Immunity, Humoral

B cells and antibodies in the defense against Mycobacterium tuberculosis infection - Achkar, Jacqueline M.; Chan, John; Casadevall, Arturo (Immunological Reviews, 2015)
Better understanding of the immunological components and their interactions necessary to prevent or control Mycobacterium tuberculosis (Mtb) infection in humans is critical for tuberculosis (TB) vaccine development strategies. Although the contributory role of humoral immunity in the protection against Mtb infection and disease is less defined than the role of T cells, it has been well-established for many other intracellular pathogens. Here we update and discuss the increasing evidence and the mechanisms of B cells and antibodies in the defense against Mtb infection. We posit that B cells and antibodies have a variety of potential protective roles at each stage of Mtb infection and postulate that such roles should be considered in the development strategies for TB vaccines and other immune-based interventions.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Tuberculosis; tuberculosis; Immunity, Innate; Immunity, Cellular; antibodies; B-Lymphocytes; Immunity, Humoral; B lymphocytes; Cell Communication; immunity; immunoglobulins

The role of B cells and humoral immunity in Mycobacterium tuberculosis infection - Chan, John; Mehta, Simren; Bharrhan, Sushma; Chen, Yong; Achkar, Jacqueline M.; Casadevall, Arturo; Flynn, JoAnne (Seminars in Immunology, 2014)
Mycobacterium tuberculosis remains a major public health burden. It is generally thought that while B cell- and antibody-mediated immunity plays an important role in host defense against extracellular pathogens, the primary control of intracellular microbes derives from cellular immune mechanisms. Studies on the immune regulatory mechanisms during infection with M. tuberculosis, a facultative intracellular organism, has established the importance of cell-mediated immunity in host defense during tuberculous infection. Emerging evidence suggest a role for B cell and humoral immunity in the control of intracellular pathogens, including obligatory species, through interactions with the cell-mediated immune compartment. Recent studies have shown that B cells and antibodies can significantly impact on the development of immune responses to the tubercle bacillus. In this review, we present experimental evidence supporting the notion that the importance of humoral and cellular immunity in host defense may not be entirely determined by the niche of the pathogen. A comprehensive approach that examines both humoral and cellular immunity could lead to better understanding of the immune response to M. tuberculosis.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Antibodies; Host-Pathogen Interactions; Tuberculosis; Tuberculosis, Pulmonary; Mice; Granuloma; Lung; Cytokines; Immunity, Cellular; B cells; B-Lymphocytes; Immunity, Humoral; Receptors, IgG; Antigen Presentation; FcγR; Immunoglobulin M

The methodology for determining the efficacy of antibody-mediated immunity - Casadevall, Arturo (Journal of Immunological Methods, 2004)
The basic method for evaluating the efficacy of antibody-mediated immunity (AMI) dates from the 1890s and involves the administration of specific Ab to an immunologically naïve host followed by microbial or toxin challenge. Other methods used to evaluate AMI involve correlating the presence of specific Ab with resistance to microbial disease and associating susceptibility to certain microbes with host immunoglobulin deficits. Unfortunately, each method has theoretical and practical problems that limit their usefulness when negative results are obtained. The application of hybridoma technology to investigate the efficacy of AMI has shown that it is possible to generate protective monoclonal antibodies even to microbes for which the standard methodologies indicate no role for AMI. Furthermore, studies with monoclonal antibodies suggest various explanations for the inability of standard methods to demonstrate the potential efficacy of AMI for certain pathogens.
Keywords: Humans; Animals; Antibodies; Models, Immunological; Antibody Formation; Bacteria; Time Factors

Towards new TB vaccines: What are the challenges? - Dockrell, Hazel M. (Pathogens and Disease, 2016)
New and effective tuberculosis (TB) vaccines are urgently needed to control pulmonary TB, and in particular to prevent the spread of drug-resistant strains of Mycobacterium tuberculosis. These drug-resistant strains can range from those resistant to first-line drugs to those that are almost impossible to treat. To develop new and effective vaccines for HIV and malaria has been difficult and it is proving to be just as challenging for TB. TB is a complicated disease with a spectrum from apparently controlled latent infection to active clinical disease and so different types of preventive or post-exposure vaccine may be needed. Identifying the most promising vaccine candidates to move into clinical trials is difficult, as we lack biomarker signatures that can predict protective efficacy. There is a risk that the failure of the MVA-85A vaccine to show efficacy when given to previously BCG-vaccinated South African infants will impact on the resources available for the development and trials of other candidate TB vaccines. Continued support for the development of new TB vaccines should remain a priority as an effective vaccine would bring huge public health benefits.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; BCG Vaccine; Clinical Trials as Topic; Outcome Assessment, Health Care; Tuberculosis, Multidrug-Resistant

Trained immunity contributes to the prevention of Mycobacterium tuberculosis infection, a novel role of autophagy - Zhou, Jie; Lv, Jingzhu; Carlson, Chelsea; Liu, Hui; Wang, Hongtao; Xu, Tao; Wu, Fengjiao; Song, Chuanwang; Wang, Xiaojing; Wang, Ting; Qian, Zhongqing (Emerging Microbes & Infections, 2021)
Mycobacterium tuberculosis (M. tuberculosis) is the pathogen which causes tuberculosis (TB), a significant human public health threat. Co-infection of M. tuberculosis and the human immunodeficiency virus (HIV), emergence of drug resistant M. tuberculosis, and failure to develop highly effective TB vaccines have limited control of the TB epidemic. Trained immunity is an enhanced innate immune response which functions independently of the adaptive/acquired immune system and responds non-specifically to reinfection with invading agents. Recently, several studies have found trained immunity has the capability to control and eliminate M. tuberculosis infection. Over the past decades, however, the consensus was adaptive immunity is the only protective mechanism by which hosts inhibit M. tuberculosis growth. Furthermore, autophagy plays an essential role in the development of trained immunity. Further investigation of trained immunity, M. tuberculosis infection, and the role of autophagy in this process provide new possibilities for vaccine development. In this review, we present the general characteristics of trained immunity and autophagy. We additionally summarize several examples where initiation of trained immunity contributes to the prevention of M. tuberculosis infection and propose future directions for research in this area.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; vaccine; Adaptive Immunity; Immunity, Innate; Immunologic Memory; Vaccination; Autophagy; autophagy; epigenetic reprogramming; mycobacterium tuberculosis; trained immunity

New vaccines for tuberculosis - Kaufmann, Stefan H. E.; Hussey, Gregory; Lambert, Paul-Henri (Lancet (London, England), 2010)
New vaccines are urgently needed if we want to reach the goal of substantially reducing the incidence of tuberculosis by 2050. Despite a steady increase in funding over the past decade, there is still a striking financial shortfall for vaccine research and development for tuberculosis. Yet, around ten vaccine candidates have left the laboratory stage and entered clinical trials. These vaccines are either aimed at replacing the present vaccine, BCG, or at enhancing immunity induced by BCG. However, these pre-exposure candidates are designed for prevention of disease and will therefore neither eradicate the pathogen, nor prevent stable infection. Long-term vaccination strategies need to target these more ambitious goals. Even though vaccine development will have a price, the return of investment will greatly exceed original costs.
Keywords: Humans; Tuberculosis Vaccines; Tuberculosis; BCG Vaccine

New tuberculosis vaccines - Martín Montañés, Carlos; Gicquel, Brigitte (Enfermedades Infecciosas Y Microbiologia Clinica, 2011)
The current tuberculosis (TB) vaccine, bacille Calmette-Guerin (BCG), is a live vaccine used worldwide, as it protects against severe forms of the disease, saving thousands of lives every year, but its efficacy against pulmonary forms of TB, responsible for transmission of the diseases, is variable. For more than 80 years now no new TB vaccines have been successfully developed. Over the last decade the effort of the scientific community has resulted in the design and construction of promising vaccine candidates. The goal is to develop a new generation of vaccines effective against respiratory forms of the disease. We will focus this review on new prophylactic vaccine candidates that aim to prevent TB diseases. Two are the main strategies used to improve the immunity conferred by the current BCG vaccine, by boosting it with new subunit vaccines, and a second strategy is focused on the construction of new more effective live vaccines, capable to replace the current BCG and to be used as prime vaccines. After rigorous preclinical studies in different animal models new TB vaccine candidates enter in clinical trials in humans. First, a small Phase I for safety followed by immunological evaluation in Phase II trials and finally evaluated in large population Phase III efficacy trials in endemic countries. At present BCG prime and boost with different subunit vaccine candidates are the more advanced assessed in Phase II. Two prime vaccines (based on recombinant BCG) have been successfully evaluated for safety in Phase I trials. A short number of live attenuated vaccines are in advance preclinical studies and the candidates ready to enter Phase I safety trials are produced under current good manufacturing practices.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Drug Design; BCG Vaccine; Drug Evaluation, Preclinical; Practice Guidelines as Topic; Vaccines, Attenuated; Adult; Vaccination; Vaccines, Subunit; Child; Clinical Trials as Topic; Consensus Development Conferences as Topic

Tuberculosis vaccine: A journey from BCG to present - Fatima, Samreen; Kumari, Anjna; Das, Gobardhan; Dwivedi, Ved Prakash (Life Sciences, 2020)
Tuberculosis (TB) is the leading cause of death worldwide due to an infectious disease, causing around 1.6 million deaths each year. This situation has become more complicated by the emergence of drug-resistant Mycobacterium tuberculosis (M.tb) and HIV-TB co-infection, which has significantly worsened TB prognosis and treatment. Despite years of intensive research, Bacille Calmette-Guerin (BCG) remains the only licensed vaccine and has variable efficacy. It provides protection against childhood TB but is not effective in adult pulmonary TB. As a result of intense research in understanding TB vaccinology, there are many new vaccine candidates in clinical development and many more in pre-clinical trials which aim either to replace or boost BCG vaccine. This review discusses the history of BCG vaccine development and summarizes limitations of the current vaccine strategy and recent advances in improving BCG immunization along with other new vaccines in clinical trials which are promising candidates for the future tuberculosis vaccinology program.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; Vaccine; BCG Vaccine; Cytokines; Adult; Vaccination; BCG; Child; Age Factors; Memory cells; T helper cells

CD4(+)CD25(+)FoxP3(+) regulatory T cells suppress Mycobacterium tuberculosis immunity in patients with active disease - Chen, Xinchun; Zhou, Boping; Li, Meizhong; Deng, Qunyi; Wu, Xueqiong; Le, Xiaohua; Wu, Chi; Larmonier, Nicolas; Zhang, Wei; Zhang, Hongmei; Wang, Huosheng; Katsanis, Emmanuel (Clinical Immunology (Orlando, Fla.), 2007)
CD4(+)CD25(+) regulatory T cells (Treg) play a central role in the prevention of autoimmunity and in the control of immune responses by down-regulating the function of effector CD4(+) or CD8(+) T cells. The role of Treg in Mycobacterium tuberculosis infection and persistence is inadequately documented. Therefore, the current study was designed to determine whether CD4(+)CD25(+)FoxP3(+) regulatory T cells may modulate immunity against human tuberculosis (TB). Our results indicate that the number of CD4(+)CD25(+)FoxP3(+) Treg increases in the blood or at the site of infection in active TB patients. The frequency of CD4(+)CD25(+)FoxP3(+) Treg in pleural fluid inversely correlates with local MTB-specific immunity (p<0.002). These CD4(+)CD25(+)FoxP3(+) T lymphocytes isolated from the blood and pleural fluid are capable of suppressing MTB-specific IFN-gamma and IL-10 production in TB patients. Therefore, CD4(+)CD25(+)FoxP3(+) Treg expanded in TB patients suppress M. tuberculosis immunity and may therefore contribute to the pathogenesis of human TB.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis, Pulmonary; Flow Cytometry; Antitubercular Agents; Cytokines; T-Lymphocyte Subsets; Adult; Middle Aged; Enzyme-Linked Immunosorbent Assay; Forkhead Transcription Factors; Immunohistochemistry; Interleukin-2 Receptor alpha Subunit; Pleural Effusion; T-Lymphocytes, Regulatory; Tuberculosis, Pleural

Pro- and anti-apoptotic CD95 signaling in T cells - Paulsen, Maren; Janssen, Ottmar (Cell communication and signaling: CCS, 2011)
The TNF receptor superfamily member CD95 (Fas, APO-1, TNFRSF6) is known as the prototypic death receptor in and outside the immune system. In fact, many mechanisms involved in apoptotic signaling cascades were solved by addressing consequences and pathways initiated by CD95 ligation in activated T cells or other "CD95-sensitive" cell populations. As an example, the binding of the inducible CD95 ligand (CD95L) to CD95 on activated T lymphocytes results in apoptotic cell death. This activation-induced cell death was implicated in the control of immune cell homeostasis and immune response termination. Over the past years, however, it became evident that CD95 acts as a dual function receptor that also exerts anti-apoptotic effects depending on the cellular context. Early observations of a potential non-apoptotic role of CD95 in the growth control of resting T cells were recently reconsidered and revealed quite unexpected findings regarding the costimulatory capacity of CD95 for primary T cell activation. It turned out that CD95 engagement modulates TCR/CD3-driven signal initiation in a dose-dependent manner. High doses of immobilized CD95 agonists or cellular CD95L almost completely silence T cells by blocking early TCR-induced signaling events. In contrast, under otherwise unchanged conditions, lower amounts of the same agonists dramatically augment TCR/CD3-driven activation and proliferation. In the present overview, we summarize these recent findings with a focus on the costimulatory capacity of CD95 in primary T cells and discuss potential implications for the T cell compartment and the interplay between T cells and CD95L-expressing cells including antigen-presenting cells.

CD8- and CD95/95L-dependent mechanisms of resistance in mice with chronic pulmonary tuberculosis - Turner, J.; D'Souza, C. D.; Pearl, J. E.; Marietta, P.; Noel, M.; Frank, A. A.; Appelberg, R.; Orme, I. M.; Cooper, A. M. (American Journal of Respiratory Cell and Molecular Biology, 2001)
The role of CD8 T lymphocytes in the immune response to Mycobacterium tuberculosis infection remains enigmatic, with persuasive reports of both cytolytic and noncytolytic (cytokine-mediated) responses to infection. To address the importance of the cytolytic mechanisms, mice with targeted disruptions for CD8 and perforin or with gene mutations in the CD95/ CD95L signaling pathway were exposed to pulmonary infection. All mice tested showed no differences in their ability to contain the growth of infection during the early phase of disease. As the chronic phase of the disease ensued, however, both CD8- and CD95/CD95L-deficient mice gradually lost their ability to limit bacterial growth. This was associated with a tendency toward pyogenic inflammation in the lung. This tendency was not seen in the perforin gene-disrupted mice. In CD8 gene-disrupted mice, the ability to generate interferon-gamma secreting T cells was unimpaired. Although these cells were capable of entering the lung they were unable to influence the increasing bacterial load in this organ.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Flow Cytometry; Mice; Lung; Interferon-gamma; Immunity, Innate; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Mice, Inbred C57BL; Signal Transduction; Mice, Knockout; Fas Ligand Protein; fas Receptor; Ligands; Membrane Glycoproteins; CD4 Antigens; Chronic Disease; Enzyme-Linked Immunosorbent Assay

Mycobacterium tuberculosis-specific CD8+ T cells require perforin to kill target cells and provide protection in vivo - Woodworth, Joshua S.; Wu, Ying; Behar, Samuel M. (Journal of Immunology (Baltimore, Md.: 1950), 2008)
Optimal immunity to Mycobacterium tuberculosis (Mtb) infection requires CD8(+) T cells, and several current Mtb vaccine candidates are being engineered to elicit enhanced CD8(+) T cell responses. However, the function of these T cells and the mechanism by which they provide protection is still unknown. We have previously shown that CD8(+) T cells specific for the mycobacterial Ags CFP10 and TB10.4 accumulate in the lungs of mice following Mtb infection and have cytolytic activity in vivo. In this study, we determine which cytolytic pathways are used by these CD8(+) T cells during Mtb infection. We find that Mtb-specific CD8(+) T cells lacking perforin have reduced cytolytic capacity in vivo. In the absence of perforin, the residual cytolytic activity is CD95 and TNFR dependent. This is particularly true in Mtb-infected lung tissue where disruption of both perforin and CD95 eliminates target cell lysis. Moreover, adoptive transfer of immune CD8(+) T cells isolated from wild-type, but not perforin-deficient mice, protect recipient mice from Mtb infection. We conclude that CD8(+) T cells elicited following Mtb infection use several cytolytic pathways in a hierarchical and compensatory manner dominated by perforin-mediated cytolysis. Finally, although several cytolytic pathways are available, adoptively transferred Mtb-specific CD8(+) T cells require perforin-mediated cytolysis to protect animals from infection. These data show that CD8(+) T cell-mediated protection during Mtb infection requires more than the secretion of IFN-gamma and specifically defines the CD8(+) cytolytic mechanisms utilized and required in vivo.
Keywords: Amino Acid Sequence; Molecular Sequence Data; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Mice; Female; CD4-Positive T-Lymphocytes; Mice, Inbred C57BL; Adoptive Transfer; Mice, Knockout; Mice, Transgenic; Perforin; T-Lymphocytes, Cytotoxic; Cytotoxicity Tests, Immunologic; Epitopes, T-Lymphocyte; Histocompatibility Antigens Class I

Th1 and Th17 Cells in Tuberculosis: Protection, Pathology, and Biomarkers - Lyadova, I. V.; Panteleev, A. V. (Mediators of Inflammation, 2015)
The outcome of Mycobacterium tuberculosis (Mtb) infection ranges from a complete pathogen clearance through asymptomatic latent infection (LTBI) to active tuberculosis (TB) disease. It is now understood that LTBI and active TB represent a continuous spectrum of states with different degrees of pathogen "activity," host pathology, and immune reactivity. Therefore, it is important to differentiate LTBI and active TB and identify active TB stages. CD4(+) T cells play critical role during Mtb infection by mediating protection, contributing to inflammation, and regulating immune response. Th1 and Th17 cells are the main effector CD4(+) T cells during TB. Th1 cells have been shown to contribute to TB protection by secreting IFN-γ and activating antimycobacterial action in macrophages. Th17 induce neutrophilic inflammation, mediate tissue damage, and thus have been implicated in TB pathology. In recent years new findings have accumulated that alter our view on the role of Th1 and Th17 cells during Mtb infection. This review discusses these new results and how they can be implemented for TB diagnosis and monitoring.
Keywords: Humans; Animals; Host-Pathogen Interactions; Cell Differentiation; Tuberculosis, Pulmonary; Mice; Interferon-gamma; Cytokines; Biomarkers; Th1 Cells; Latent Tuberculosis; Lymphocyte Activation; Th17 Cells; Interleukin-17

An antimicrobial activity of cytolytic T cells mediated by granulysin - Stenger, S.; Hanson, D. A.; Teitelbaum, R.; Dewan, P.; Niazi, K. R.; Froelich, C. J.; Ganz, T.; Thoma-Uszynski, S.; Melián, A.; Bogdan, C.; Porcelli, S. A.; Bloom, B. R.; et al. (Science (New York, N.Y.), 1998)
Cytolytic T lymphocytes (CTLs) kill intracellular pathogens by a granule-dependent mechanism. Granulysin, a protein found in granules of CTLs, reduced the viability of a broad spectrum of pathogenic bacteria, fungi, and parasites in vitro. Granulysin directly killed extracellular Mycobacterium tuberculosis, altering the membrane integrity of the bacillus, and, in combination with perforin, decreased the viability of intracellular M. tuberculosis. The ability of CTLs to kill intracellular M. tuberculosis was dependent on the presence of granulysin in cytotoxic granules, defining a mechanism by which T cells directly contribute to immunity against intracellular pathogens.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Macrophages; Cell Membrane; Recombinant Proteins; Cells, Cultured; Membrane Glycoproteins; Microscopy, Confocal; Antigens, Differentiation, T-Lymphocyte; Cytoplasmic Granules; Cytotoxicity, Immunologic; Microscopy, Electron, Scanning; Perforin; Pore Forming Cytotoxic Proteins; T-Lymphocytes, Cytotoxic

T helper 2 cytokines inhibit autophagic control of intracellular Mycobacterium tuberculosis - Harris, James; De Haro, Sergio A.; Master, Sharon S.; Keane, Joseph; Roberts, Esteban A.; Delgado, Monica; Deretic, Vojo (Immunity, 2007)
Autophagy is a recently recognized immune effector mechanism against intracellular pathogens. The role of autophagy in innate immunity has been well established, but the extent of its regulation by the adaptive immune response is less well understood. The T helper 1 (Th1) cell cytokine IFN-gamma induces autophagy in macrophages to eliminate Mycobacterium tuberculosis. Here, we report that Th2 cytokines affect autophagy in macrophages and their ability to control intracellular M. tuberculosis. IL-4 and IL-13 abrogated autophagy and autophagy-mediated killing of intracellular mycobacteria in murine and human macrophages. Inhibition of starvation-induced autophagy by IL-4 and IL-13 was dependent on Akt signaling, whereas the inhibition of IFN-gamma-induced autophagy was Akt independent and signal transducer and activator of transcription 6 (STAT6) dependent. These findings establish a mechanism through which Th1-Th2 polarization differentially affects the immune control of intracellular pathogens.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Animals; Macrophages; Immunoblotting; Flow Cytometry; Mice; Interferon-gamma; Cytokines; Phagosomes; Autophagy; Interleukin-13; Interleukin-4; Microscopy, Confocal; Proto-Oncogene Proteins c-akt; STAT6 Transcription Factor; Th2 Cells; Transfection

Alternative activation of macrophages: mechanism and functions - Gordon, Siamon; Martinez, Fernando O. (Immunity, 2010)
The concept of an alternative pathway of macrophage activation has stimulated interest in its definition, mechanism, and functional significance in homeostasis and disease. We assess recent research in this field, argue for a restricted definition, and explore pathways by which the T helper 2 (Th2) cell cytokines interleukin-4 (IL-4) and IL-13 mediate their effects on macrophage cell biology, their biosynthesis, and responses to a normal and pathological microenvironment. The stage is now set to gain deeper insights into the role of alternatively activated macrophages in immunobiology.
Keywords: Humans; Animals; Macrophages; Cytokines; Macrophage Activation; Signal Transduction; Models, Biological; Neoplasms; Receptors, Interleukin

CXCR5⁺ T helper cells mediate protective immunity against tuberculosis - Slight, Samantha R.; Rangel-Moreno, Javier; Gopal, Radha; Lin, Yinyao; Fallert Junecko, Beth A.; Mehra, Smriti; Selman, Moises; Becerril-Villanueva, Enrique; Baquera-Heredia, Javier; Pavon, Lenin; Kaushal, Deepak; Reinhart, Todd A.; et al. (The Journal of Clinical Investigation, 2013)
One third of the world's population is infected with Mycobacterium tuberculosis (Mtb). Although most infected people remain asymptomatic, they have a 10% lifetime risk of developing active tuberculosis (TB). Thus, the current challenge is to identify immune parameters that distinguish individuals with latent TB from those with active TB. Using human and experimental models of Mtb infection, we demonstrated that organized ectopic lymphoid structures containing CXCR5+ T cells were present in Mtb-infected lungs. In addition, we found that in experimental Mtb infection models, the presence of CXCR5+ T cells within ectopic lymphoid structures was associated with immune control. Furthermore, in a mouse model of Mtb infection, we showed that activated CD4+CXCR5+ T cells accumulated in Mtb-infected lungs and produced proinflammatory cytokines. Mice deficient in Cxcr5 had increased susceptibility to TB due to defective T cell localization within the lung parenchyma. We demonstrated that CXCR5 expression in T cells mediated correct T cell localization within TB granulomas, promoted efficient macrophage activation, protected against Mtb infection, and facilitated lymphoid follicle formation. These data demonstrate that CD4+CXCR5+ T cells play a protective role in the immune response against TB and highlight their potential use for future TB vaccine design and therapy.
Keywords: Humans; Animals; Tuberculosis, Pulmonary; Mice; Disease Models, Animal; Female; Lung; Cytokines; T-Lymphocyte Subsets; Latent Tuberculosis; Macrophage Activation; Male; Lymphocyte Activation; T-Lymphocytes, Helper-Inducer; Mice, Knockout; Mice, Transgenic; Inflammation Mediators; Granuloma, Respiratory Tract; Lymphoid Tissue; Receptors, CXCR5

Virulence factors of the Mycobacterium tuberculosis complex - Forrellad, Marina A.; Klepp, Laura I.; Gioffré, Andrea; Sabio y García, Julia; Morbidoni, Hector R.; Santangelo, María de la Paz; Cataldi, Angel A.; Bigi, Fabiana (Virulence, 2013)
The Mycobacterium tuberculosis complex (MTBC) consists of closely related species that cause tuberculosis in both humans and animals. This illness, still today, remains to be one of the leading causes of morbidity and mortality throughout the world. The mycobacteria enter the host by air, and, once in the lungs, are phagocytated by macrophages. This may lead to the rapid elimination of the bacillus or to the triggering of an active tuberculosis infection. A large number of different virulence factors have evolved in MTBC members as a response to the host immune reaction. The aim of this review is to describe the bacterial genes/proteins that are essential for the virulence of MTBC species, and that have been demonstrated in an in vivo model of infection. Knowledge of MTBC virulence factors is essential for the development of new vaccines and drugs to help manage the disease toward an increasingly more tuberculosis-free world.
Keywords: Mycobacterium tuberculosis; pathogen; virulence; virulence factors; virulence genes

Full article: Virulence factors of the Mycobacterium tuberculosis complex

Phenotype and functions of memory Tfh cells in human blood - Schmitt, Nathalie; Bentebibel, Salah-Eddine; Ueno, Hideki (Trends in Immunology, 2014)
Keywords: human blood; subsets; T follicular helper cells

Phenotype and functions of memory Tfh cells in human blood - PubMed

Life and death in the granuloma: immunopathology of tuberculosis - Saunders, Bernadette M.; Britton, Warwick J. (Immunology and Cell Biology, 2007)
During tuberculosis (TB) infection, the granuloma provides the microenvironment in which antigen-specific T cells colocate with and activate infected macrophages to inhibit the growth of Mycobacterium tuberculosis. Although the granuloma is the site for mycobacterial killing, virulent mycobacteria have developed a variety of mechanisms to resist this macrophage-mediated killing. These surviving mycobacteria become dormant, however, if host cellular immunity or the signals maintaining granuloma structure wane, or if mycobacteria resume replication, leading to reactivation of TB. This balance of life and death applies not only to the mycobacterium but also to the host macrophages that may undergo apoptosis or necrosis, leading to the characteristic caseous necrosis within the granuloma, and the potential spread of TB infection. The immunological factors controlling the development and maintenance of the granuloma will be reviewed.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Granuloma; CD4-Positive T-Lymphocytes; Immunity, Cellular; Microbial Viability; Models, Biological; Inflammation; Adaptation, Biological; Chemokines; Species Specificity; Tumor Necrosis Factor-alpha; Virus Latency

Role of Interferons in the Development of Diagnostics, Vaccines, and Therapy for Tuberculosis - Chin, Kai Ling; Anis, Fadhilah Zulkipli; Sarmiento, Maria E.; Norazmi, Mohd Nor; Acosta, Armando (Journal of Immunology Research, 2017)
Tuberculosis (TB) is an airborne infection caused by Mycobacterium tuberculosis (Mtb). About one-third of the world's population is latently infected with TB and 5-15% of them will develop active TB in their lifetime. It is estimated that each case of active TB may cause 10-20 new infections. Host immune response to Mtb is influenced by interferon- (IFN-) signaling pathways, particularly by type I and type II interferons (IFNs). The latter that consists of IFN-γ has been associated with the promotion of Th1 immune response which is associated with protection against TB. Although this aspect remains controversial at present due to the lack of established correlates of protection, currently, there are different prophylactic, diagnostic, and immunotherapeutic approaches in which IFNs play an important role. This review summarizes the main aspects related with the biology of IFNs, mainly associated with TB, as well as presents the main applications of these cytokines related to prophylaxis, diagnosis, and immunotherapy of TB.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; Antitubercular Agents; Mice; Interferon-gamma; Cytokines; Immunotherapy; Interferons

IFN-γ from CD4 T cells is essential for host survival and enhances CD8 T cell function during Mycobacterium tuberculosis infection - Green, Angela M.; Difazio, Robert; Flynn, Joanne L. (Journal of Immunology (Baltimore, Md.: 1950), 2013)
IFN-γ is necessary in both humans and mice for control of Mycobacterium tuberculosis. CD4 T cells are a significant source of IFN-γ during acute infection in mice and are required for control of bacterial growth and host survival. However, several other types of cells can and do produce IFN-γ during the course of the infection. We sought to determine whether IFN-γ from sources other than CD4 T cells was sufficient to control M. tuberculosis infection and whether CD4 T cells had a role in addition to IFN-γ production. To investigate the role of IFN-γ from CD4 T cells, a murine adoptive transfer model was developed in which all cells were capable of producing IFN-γ, with the exception of CD4 T cells. Our data in this system support that CD4 T cells are essential for control of infection, but also that IFN-γ from CD4 T cells is necessary for host survival and optimal long-term control of bacterial burden. In addition, IFN-γ from CD4 T cells was required for a robust CD8 T cell response. IFN-γ from T cells inhibited intracellular replication of M. tuberculosis in macrophages, suggesting IFN-γ may be necessary for intracellular bactericidal activity. Thus, although CD4 T cells play additional roles in the control of M. tuberculosis infection, IFN-γ is a major function by which these cells participate in resistance to tuberculosis.
Keywords: Mycobacterium tuberculosis; Animals; Cells, Cultured; Tuberculosis, Pulmonary; Mice; Interferon-gamma; Survival Analysis; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Mice, Inbred C57BL; Adoptive Transfer; Mice, 129 Strain; Mice, Knockout; Mice, Transgenic; Disease Resistance; Up-Regulation

Genetic dissection of immunity to mycobacteria: the human model - Casanova, Jean-Laurent; Abel, Laurent (Annual Review of Immunology, 2002)
Humans are exposed to a variety of environmental mycobacteria (EM), and most children are inoculated with live Bacille Calmette-Guérin (BCG) vaccine. In addition, most of the world's population is occasionally exposed to human-borne mycobacterial species, which are less abundant but more virulent. Although rarely pathogenic, mildly virulent mycobacteria, including BCG and most EM, may cause a variety of clinical diseases. Mycobacterium tuberculosis, M. leprae, and EM M. ulcerans are more virulent, causing tuberculosis, leprosy, and Buruli ulcer, respectively. Remarkably, only a minority of individuals develop clinical disease, even if infected with virulent mycobacteria. The interindividual variability of clinical outcome is thought to result in part from variability in the human genes that control host defense. In this well-defined microbiological and clinical context, the principles of mouse immunology and the methods of human genetics can be combined to facilitate the genetic dissection of immunity to mycobacteria. The natural infections are unique to the human model, not being found in any of the animal models of experimental infection. We review current genetic knowledge concerning the simple and complex inheritance of predisposition to mycobacterial diseases in humans. Rare patients with Mendelian disorders have been found to be vulnerable to BCG, a few EM, and M. tuberculosis. Most cases of presumed Mendelian susceptibility to these and other mycobacterial species remain unexplained. In the general population leprosy and tuberculosis have been shown to be associated with certain human genetic polymorphisms and linked to certain chromosomal regions. The causal vulnerability genes themselves have yet to be identified and their pathogenic alleles immunologically validated. The studies carried out to date have been fruitful, initiating the genetic dissection of protective immunity against a variety of mycobacterial species in natural conditions of infection. The human model has potential uses beyond the study of mycobacterial infections and may well become a model of choice for the investigation of immunity to infectious agents.
Keywords: Humans; Mycobacterium; Virulence; Interferon-gamma; Models, Immunological; Mycobacterium bovis; Immunity; Mycobacterium Infections; Environmental Microbiology; Immunologic Deficiency Syndromes; Interleukin-12

CD4+ T cells contain early extrapulmonary tuberculosis (TB) dissemination and rapid TB progression and sustain multieffector functions of CD8+ T and CD3- lymphocytes: mechanisms of CD4+ T cell immunity - Yao, Shuyu; Huang, Dan; Chen, Crystal Y.; Halliday, Lisa; Wang, Richard C.; Chen, Zheng W. (Journal of Immunology (Baltimore, Md.: 1950), 2014)
The possibility that CD4(+) T cells can act as "innate-like" cells to contain very early Mycobacterium tuberculosis dissemination and function as master helpers to sustain multiple effector functions of CD8(+) T cells and CD3(-) lymphocytes during development of adaptive immunity against primary tuberculosis (TB) has not been demonstrated. We showed that pulmonary M. tuberculosis infection of CD4-depleted macaques surprisingly led to very early extrapulmonary M. tuberculosis dissemination, whereas CD4 deficiency clearly resulted in rapid TB progression. CD4 depletion during M. tuberculosis infection revealed the ability of CD8(+) T cells to compensate and rapidly differentiate to Th17-like/Th1-like and cytotoxic-like effectors, but these effector functions were subsequently unsustainable due to CD4 deficiency. Whereas CD3(-) non-T lymphocytes in the presence of CD4(+) T cells developed predominant Th22-like and NK-like (perforin production) responses to M. tuberculosis infection, CD4 depletion abrogated these Th22-/NK-like effector functions and favored IL-17 production by CD3(-) lymphocytes. CD4-depleted macaques exhibited no or few pulmonary T effector cells constitutively producing IFN-γ, TNF-α, IL-17, IL-22, and perforin at the endpoint of more severe TB, but they presented pulmonary IL-4(+) T effectors. TB granulomas in CD4-depleted macaques contained fewer IL-22(+) and perforin(+) cells despite the presence of IL-17(+) and IL-4(+) cells. These results implicate a previously unknown innate-like ability of CD4(+) T cells to contain extrapulmonary M. tuberculosis dissemination at very early stage. Data also suggest that CD4(+) T cells are required to sustain multiple effector functions of CD8(+) T cells and CD3(-) lymphocytes and to prevent rapid TB progression during M. tuberculosis infection of nonhuman primates.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Macaca fascicularis; Cytokines; CD8-Positive T-Lymphocytes; Th1 Cells; Th17 Cells

Modulation of human neutrophil apoptosis by immune complexes - Gamberale, R.; Giordano, M.; Trevani, A. S.; Andonegui, G.; Geffner, J. R. (Journal of Immunology (Baltimore, Md.: 1950), 1998)
In the present study we examined whether immune complexes (IC) are able to modulate human neutrophil apoptosis. We observed different effects depending on the type of IC employed. Precipitating IC (pIC) and Ab-coated erythrocytes (E-IgG) triggered a marked stimulation of apoptosis, while heat-aggregated IgG and soluble IC, significantly delayed spontaneous apoptosis. Blocking Abs directed to Fcgamma receptor type II (FcgammaRII), but not to FcgammaRIII, markedly diminished the acceleration of apoptosis triggered by either pIC or E-IgG, supporting a critical role for FcgammaRII in apoptosis stimulation. This phenomenon, on the other hand, does not appear to involve IC phagocytosis or the participation of CR3. Acceleration of neutrophil apoptosis triggered by either pIC or E-IgG seems to require the activation of the respiratory burst, as suggested by 1) the ability of catalase to prevent apoptosis stimulation; 2) the effect of azide, an heme enzyme inhibitor, which dramatically enhanced apoptosis induced by pIC or E-IgG; and 3) the inability of pIC or E-IgG to accelerate apoptosis of neutrophils isolated from CGD patients. It is well established that IC affect the course of inflammation by inducing the release of inflammatory cytokines, proteolytic enzymes, oxidative agents, and other toxic molecules. Our results suggest that IC may also affect the course of inflammation by virtue of their ability to modulate neutrophil apoptosis.
Keywords: Humans; Immunoglobulin G; Neutrophils; Receptors, IgG; Phagocytosis; Apoptosis; Antigen-Antibody Complex; Calcium; Chemical Precipitation; Cytosol; Erythrocytes; Fas Ligand Protein; fas Receptor; Granulomatous Disease, Chronic; Hot Temperature; Ligands; Macrophage-1 Antigen; Membrane Glycoproteins; Neutrophil Activation; Reactive Oxygen Species; Respiratory Burst; Solubility

Effector Mechanisms of Neutrophils within the Innate Immune System in Response to Mycobacterium tuberculosis Infection - Warren, Eric; Teskey, Garrett; Venketaraman, Vishwanath (Journal of Clinical Medicine, 2017)
Neutrophils have a significant yet controversial role in the innate immune response to Mycobacterium tuberculosis (M. tb) infection, which is not yet fully understood. In addition to neutrophils' well-known effector mechanisms, they may also help control infection of M. tb through the formation of neutrophil extracellular traps (NETs), which are thought to further promote the killing of M. tb by resident alveolar macrophages. Cytokines such as IFN-γ have now been shown to serve an immunomodulatory role in neutrophil functioning in conjunction to its pro-inflammatory function. Additionally, the unique transcriptional changes of neutrophils may be used to differentiate between infection with M. tb and other bacterial and chronic rheumatological diseases such as Systemic Lupus Erythematosus. Adversely, during the innate immune response to M. tb, inappropriate phagocytosis of spent neutrophils can result in nonspecific damage to host cells due to necrotic lysis. Furthermore, some individuals have been shown to be more genetically susceptible to tuberculosis (TB) due to a "Trojan Horse" phenomenon whereby neutrophils block the ability of resident macrophages to kill M. tb. Despite these aforementioned negative consequences, through the scope of this review we will provide evidence to support the idea that neutrophils, while sometimes damaging, can also be an important component in warding off M. tb infection. This is exemplified in immunocompromised individuals, such as those with human immunodeficiency virus (HIV) infection or Type 2 diabetes mellitus. These individuals are at an increased risk of developing tuberculosis (TB) due to a diminished innate immune response associated with decreased levels of glutathione. Consequently, there has been a worldwide effort to limit and contain M. tb infection through the use of antibiotics and vaccinations. However, due to several significant limitations, the current bacille Calmette-Guerin vaccine (BCG, vaccine against TB) does not meet the criteria for universal utilization for all ages and populations across the globe. New research involving neutrophils has yielded a new vaccine called M. smegmatis-Ag85C-MPT51-HspX (mc²-CMX) that has been shown to elicit a humoral and cellular response against M. tb in mice that is superior to the BCG vaccine.
Keywords: Mycobacterium tuberculosis; Tuberculosis; Neutrophils; Cytokines; Innate immunity; M. tb; NETs; Phagocytosis-induced cell death; PMN; polymorphonuclear leukocytes; TB

Neutrophils in tuberculosis--first line of defence or booster of disease and targets for host-directed therapy? - Dallenga, Tobias; Schaible, Ulrich E. (Pathogens and Disease, 2016)
Necrotizing granulomas, exacerbating pathogenesis and neutrophil influx at the site of infection are hallmarks of active pulmonary tuberculosis (TB) in humans. The role of polymorphonuclear neutrophils (PMN) in host defence and TB pathogenesis has recently attracted broader interest. Association of infiltrating PMN, enhanced mycobacterial load and disease exacerbation in both, mice susceptible to experimental TB as well as in TB patients, link PMN to exacerbated pathology. Targeting PMN resulted in smaller lung lesions and reduced mycobacterial burden. Therefore, PMN-associated molecules represent interesting biomarkers to determine TB severity and treatment success. More importantly, PMN are putative targets for host-directed therapies (HDT) in TB. Due to the rise of multi- and extensively drug-resistant Mycobacterium tuberculosis isolates, HDT represent adjunct measures to support antibiotic treatment by ameliorating pathology and local host defences.
Keywords: Humans; Mycobacterium tuberculosis; Animals; tuberculosis; Tuberculosis, Pulmonary; Mice; Neutrophils; Cytokines; Bacterial Load; host-directed therapy; Inflammation; neutrophils; polymorphonuclear cells

Mycobacterium tuberculosis inhibits neutrophil apoptosis, leading to delayed activation of naive CD4 T cells - Blomgran, Robert; Desvignes, Ludovic; Briken, Volker; Ernst, Joel D. (Cell Host & Microbe, 2012)
Mycobacterium tuberculosis promotes its replication by inhibiting the apoptosis of infected macrophages. A proapoptotic M. tuberculosis mutant lacking nuoG, a subunit of the type I NADH dehydrogenase complex, exhibits attenuated growth in vivo, indicating that this virulence mechanism is essential. We show that M. tuberculosis also suppresses neutrophil apoptosis. Compared to wild-type, the nuoG mutant spread to a larger number of lung phagocytic cells. Consistent with the shorter lifespan of infected neutrophils, infection with the nuoG mutant resulted in fewer bacteria per infected neutrophil, accelerated bacterial acquisition by dendritic cells, earlier trafficking of these dendritic cells to lymph nodes, and faster CD4 T cell priming. Neutrophil depletion abrogated accelerated CD4 T cell priming by the nuoG mutant, suggesting that inhibiting neutrophil apoptosis delays adaptive immunity in tuberculosis. Thus, pathogen modulation of apoptosis is beneficial at multiple levels, and enhancing phagocyte apoptosis promotes CD4 as well as CD8 T cell responses.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Virulence Factors; Neutrophils; Lymph Nodes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Lymphocyte Activation; Dendritic Cells; Immune Evasion; Apoptosis; Bacterial Load; Gene Deletion

Acid resistance in Mycobacterium tuberculosis - Vandal, Omar H.; Nathan, Carl F.; Ehrt, Sabine (Journal of Bacteriology, 2009)
Keywords: Mycobacterium tuberculosis; Macrophages; Phagosomes; Models, Biological; Hydrogen-Ion Concentration

Enhanced secretion of interferon-γ by bovine γδ T cells induced by coculture with Mycobacterium bovis-infected dendritic cells: evidence for reciprocal activating signals - Price, Sally J; Hope, Jayne C (Immunology, 2009)
Evidence suggests that γδ T cells form part of the innate immune response to Mycobacterium bovis infection. Dendritic cells (DCs) are capable of secreting high levels of interleukin-12 (IL-12) following infection with mycobacteria and can induce interferon-γ (IFN-γ) secretion by natural killer and γδ T cells We investigated the innate interactions occurring between WC1+γδ T cells and M. bovis-infected DCs. Following coculture with M. bovis-infected DCs, secretion of IFN-γ and expression of CD25 and major histocompatibility complex class II on WC1+γδ T cells were significantly enhanced. Reciprocal enhancement of IL-12 secretion by the DCs was also observed and this interaction was found to be contact dependent. We hypothesize that there is an early, transient signal between the WC1+γδ T cells and the DCs, which promotes the synthesis of biologically active IL-12, and which is dependent upon cell–cell contact. Reciprocal signals including IL-12 are then delivered to WC1+γδ cells, which leads to the enhanced secretion of IFN-γ, and the up-regulation of activation markers and antigen presentation molecules by the WC1+γδ T cells. These interactions are likely to form a critical part of the T helper type 1-conditioning response of DCs to M. bovis.

Mycolic acid-specific T cells protect against Mycobacterium tuberculosis infection in a humanized transgenic mouse model - Zhao, Jie; Siddiqui, Sarah; Shang, Shaobin; Bian, Yao; Bagchi, Sreya; He, Ying; Wang, Chyung-Ru (eLife, 2015)
Group 1 CD1 molecules, CD1a, CD1b and CD1c, present lipid antigens from Mycobacterium tuberculosis (Mtb) to T cells. Mtb lipid-specific group 1 CD1-restricted T cells have been detected in Mtb-infected individuals. However, their role in protective immunity against Mtb remains unclear due to the absence of group 1 CD1 expression in mice. To overcome the challenge, we generated mice that expressed human group 1 CD1 molecules (hCD1Tg) and a CD1b-restricted, mycolic-acid specific TCR (DN1Tg). Using DN1Tg/hCD1Tg mice, we found that activation of DN1 T cells was initiated in the mediastinal lymph nodes and showed faster kinetics compared to Mtb Ag85B-specific CD4(+) T cells after aerosol infection with Mtb. Additionally, activated DN1 T cells exhibited polyfunctional characteristics, accumulated in lung granulomas, and protected against Mtb infection. Therefore, our findings highlight the vaccination potential of targeting group 1 CD1-restricted lipid-specific T cells against Mtb infection.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Antigens, Bacterial; Tuberculosis; Mice; immunology; T-Lymphocyte Subsets; Lymphocyte Activation; Mice, Transgenic; Antigens, CD1; CD1; Mycolic Acids; Receptors, Antigen, T-Cell; T lymphocytes; Mice, SCID; mouse; Mycobaterium tuberculosis; Mycolic acid

Total Synthesis of Mycobacterium tuberculosis Dideoxymycobactin-838 and Stereoisomers: Diverse CD1a-Restricted T Cells Display a Common Hierarchy of Lipopeptide Recognition - Cheng, Janice M. H.; Liu, Ligong; Pellicci, Daniel G.; Reddiex, Scott J. J.; Cotton, Rachel N.; Cheng, Tan-Yun; Young, David C.; Van Rhijn, Ildiko; Moody, D. Branch; Rossjohn, Jamie; Fairlie, David P.; Godfrey, Dale I.; et al. (Chemistry (Weinheim an Der Bergstrasse, Germany), 2017)
Mycobacterium tuberculosis produces dideoxymycobactin-838 (DDM-838), a lipopeptide that potently activates T cells upon binding to the MHC-like antigen-presenting molecule CD1a. M. tuberculosis produces DDM-838 in only trace amounts and a previous solid-phase synthesis provided sub-milligram quantities. We describe a high-yielding solution-phase synthesis of DDM-838 that features a Mitsunobu substitution that avoids yield-limiting epimerization at lysine during esterification, and amidation conditions that prevent double-bond isomerization of the Z-C20:1 acyl chain, and provides material with equivalent antigenicity to natural DDM-838. Isomers of DDM-838 that varied in stereochemistry at the central lysine and the C20:1 acyl chain were compared for their ability to be recognised by CD1a-restricted T cell receptors (TCRs). These TCRs, derived from unrelated human donors, exhibited a similar spectrum of reactivity towards the panel of DDM-838 isomers, highlighting the exquisite sensitivity of lipopeptide-reactive T cells for the natural DDM stereochemistry.
Keywords: Cell Line; Humans; Mycobacterium tuberculosis; Recombinant Proteins; Interferon-gamma; immunology; T-Lymphocytes; Antigens, CD1; T cells; antigens; Jurkat Cells; Lipopeptides; natural products; Oxazoles; peptidolipids; Stereoisomerism

A polymorphism in human CD1A is associated with susceptibility to tuberculosis - Seshadri, C.; Thuong, N. T. T.; Yen, N. T. B.; Bang, N. D.; Chau, T. T. H.; Thwaites, G. E.; Dunstan, S. J.; Hawn, T. R. (Genes and Immunity, 2014)
CD1 proteins are antigen-presenting molecules that evolved to present lipids rather than peptides to T cells. However, unlike major histocompatibility complex genes, CD1 genes show low rates of polymorphism and have not been clearly associated with human disease. We report that an intronic polymorphism in CD1A (rs411089) is associated with susceptibility to tuberculosis in two cohorts of Vietnamese adults (combined cohort odds ratio 1.78; 95% confidence interval: 1.24-2.57; P=0.001). These data strengthen the hypothesis that CD1A-mediated lipid antigen presentation is important for controlling tuberculosis in humans.
Keywords: Humans; Tuberculosis; Genetic Predisposition to Disease; Genotype; T-Lymphocytes; Antigens, CD1; Alleles; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Linkage Disequilibrium; Odds Ratio; Vietnam

Artificially induced MAIT cells inhibit M. bovis BCG but not M. tuberculosis during in vivo pulmonary infection - Yu, Huifeng; Yang, Amy; Derrick, Steven; Mak, Jeffrey Y. W.; Liu, Ligong; Fairlie, David P.; Cowley, Siobhan (Scientific Reports, 2020)
There is significant interest in targeting MAIT cells with immunostimulatory agents to enhance immune responses. Mycobacterium tuberculosis (M. tb.) is a pervasive respiratory disease that could benefit from treatments that augment immunity. Here we investigate the role of MAIT cells in M. tb. infection and the potential for MAIT cell-targeted immunotherapy to control bacterial burdens. We find that MAIT cells fail to substantially accumulate in the lungs during murine pulmonary M. bovis BCG and M. tb. infections but this defect is overcome by intranasal installation of a TLR2/6 agonist and a MAIT cell antigen. Although artificially induced MAIT cells produce important cytokines in both infections, they control BCG but not M. tb. growth in the lungs. Correspondingly, M. tb.-infected mouse macrophages are relatively resistant to MAIT cell antimicrobial activities in vitro. Thus, MAIT cell antigen-mediated immunotherapy for M. tb. presents a complex challenge.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Tuberculosis, Pulmonary; BCG Vaccine; Female; Lung; Cytokines; Mice, Inbred C57BL; Male; Mycobacterium bovis; Mucosal-Associated Invariant T Cells

Targeting Innate-Like T Cells in Tuberculosis - Huang, Shouxiong (Frontiers in Immunology, 2016)
Peptide-specific conventional T cells have been major targets for designing most antimycobacterial vaccines. Immune responses mediated by conventional T cells exhibit a delayed onset upon primary infection and are highly variable in different human populations. In contrast, innate-like T cells quickly respond to pathogens and display effector functions without undergoing extensive clonal expansion. Specifically, the activation of innate-like T cells depends on the promiscuous interaction of highly conserved antigen-presenting molecules, non-peptidic antigens, and likely semi-invariant T cell receptors. In antimicrobial immune responses, mucosal-associated invariant T cells are activated by riboflavin precursor metabolites presented by major histocompatibility complex-related protein I, while lipid-specific T cells including natural killer T cells are activated by lipid metabolites presented by CD1 proteins. Multiple innate-like T cell subsets have been shown to be protective or responsive in mycobacterial infections. Through rapid cytokine secretion, innate-like T cells function in early defense and memory response, offering novel advantages over conventional T cells in the design of anti-tuberculosis strategies.
Keywords: Mycobacterium tuberculosis; vaccine; CD1; antigen presentation; innate-like T cells; lipid; MR1; riboflavin metabolites

Changes in Mycobacterium tuberculosis-Specific Immunity With Influenza co-infection at Time of TB Diagnosis - Mendy, Joseph; Jarju, Sheikh; Heslop, Rhiannon; Bojang, Adama L.; Kampmann, Beate; Sutherland, Jayne S. (Frontiers in Immunology, 2018)
Background: Prior Influenza A viral (IAV) infection has been shown to increase susceptibility to tuberculosis (TB) and TB has also been shown to be a primary cause of death during pandemics, including the Spanish Influenza outbreak of 1918-1919. The majority of data has been obtained from mouse models, thus the aim of this study was to determine the impact of Flu co-infection on host immunity and disease severity in TB patients at diagnosis. Methods: Sputum from 282 patients with active TB were analyzed for presence of FluA/FluB RNA at presentation using multiplex PCR. Sputum RNA was also analyzed for Mycobacterium tuberculosis (Mtb) load using 16S RNA amplification. Supernatants from digested sputum and Mtb antigen-stimulated whole blood were analyzed using multiplex cytokine arrays and PBMC were analyzed for cytokine production from CD4+ T, CD8+ T and Mucosal Associated Invariant T cells (MAITs). Results: 12 (4.3%) of TB patients were found to have FluA or FluB viral RNA present in their sputum at the time of TB diagnosis. The TB/Flu co-infected patients had a significantly higher bacterial load compared to those with TB mono-infection (p = 0.0026). They had lower levels of IL17A in ex vivo sputum (p = 0.0275) and higher MCP-1 (CCL2) levels in the blood following PPD stimulation (p = 0.0267). TB/Flu co-infected subjects had significantly higher IFN-γ+IL-17+CD4+ and IFN-γ+IL-17-CD8+ cells compared to TB mono-infected subjects. Conclusions: These data show that Flu co-infection at time of TB diagnosis is associated with a higher bacterial load and differential cellular and soluble profiles. These findings show for the first time the impact of TB/Flu co-infection in a human cohort and support the potential benefit of Flu vaccination in TB-endemic settings.
Keywords: DNA, Bacterial; Humans; Mycobacterium tuberculosis; tuberculosis; Tuberculosis, Pulmonary; Female; Adult; Male; Young Adult; Bacterial Load; cytokines; Cohort Studies; Coinfection; bacterial load; flow cytometry; Gambia; influenza; Influenza A virus; Influenza B virus; Influenza, Human; RNA, Ribosomal, 16S; RNA, Viral; Sputum

MR1-restricted mucosal associated invariant T (MAIT) cells in the immune response to Mycobacterium tuberculosis - Gold, Marielle C.; Napier, Ruth J.; Lewinsohn, David M. (Immunological Reviews, 2015)
The intracellular pathogen Mycobacterium tuberculosis (Mtb) and its human host have long co-evolved. Although the host cellular immune response is critical to the control of the bacterium information on the specific contribution of different immune cell subsets in humans is incomplete. Mucosal associated invariant T (MAIT) cells are a prevalent and unique T-cell population in humans with the capacity to detect intracellular infection with bacteria including Mtb. MAIT cells detect bacterially derived metabolites presented by the evolutionarily conserved major histocompatibility complex-like molecule MR1. Here, we review recent advances in our understanding of this T-cell subset and address the potential roles for MR1-restricted T cells in the control, diagnosis, and therapy of tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; Tuberculosis; tuberculosis; T-Lymphocyte Subsets; Biological Evolution; Ligands; Histocompatibility Antigens Class I; Disease Susceptibility; MR1; mucosal associated invariant T cells (MAIT); Mucous Membrane

The frequency and dynamics of CD4+ mucosal-associated invariant T (MAIT) cells in active pulmonary tuberculosis - Xiong, Kunlong; Sun, Wenwen; Wang, Hongxiu; Xie, Jianping; Su, Bo; Fan, Lin (Cellular Immunology, 2021)
MAIT cells are unconventional innate-like T lymphocytes contributing to host immune protection against Mycobacteria tuberculosis (Mtb) infection. CD4- MAIT cells play a major role in immune protection against tuberculosis (TB), however, the role of CD4+ MAIT cells was elusive due to their low abundance. We firstly investigated the frequency and functions of CD4+ MAIT cells in pulmonary tuberculosis (PTB) patients before and after anti-TB treatment. We found that the frequency of Mtb-reactive CD4+ MAIT cells and IFN-γ, granzyme B (GrzB), CD69 expression on them were increased while LAG-3+ cells of them were decreased in PTB patients. After the treatment, the frequency of Mtb-reactive CD4+ MAIT cells and CD69, IFN-γ, GrzB expression on them were decreased while LAG-3 increased. The results indicated the expression profile is distinct between CD4+ MAIT cells and CD4- MAIT cells in PTB patients, the increased IFN-γ and GrzB expression of CD4+ MAIT cells play a role in anti-TB immunity.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Tuberculosis, Pulmonary; Female; Lung; Interferon-gamma; Adult; Male; Middle Aged; Young Adult; Adolescent; Lymphocyte Activation; CD4 Antigens; Mucosal-Associated Invariant T Cells; CD4; CD69; Granzyme B; Granzymes; IFN-γ; LAG-3; MAIT cells

Efficient 5-OP-RU-Induced Enrichment of Mucosa-Associated Invariant T Cells in the Murine Lung Does Not Enhance Control of Aerosol Mycobacterium tuberculosis Infection - Vorkas, Charles Kyriakos; Levy, Olivier; Skular, Miroslav; Li, Kelin; Aubé, Jeffrey; Glickman, Michael S. (Infection and Immunity, 2020)
Mucosa-associated invariant T (MAIT) cells are an innate-like T cell subset in mammals that recognize microbial vitamin B metabolites presented by the evolutionarily conserved major histocompatibility complex class I (MHC I)-related molecule, MR1. Emerging data suggest that MAIT cells may be an attractive target for vaccine-induced protection against bacterial infections because of their rapid cytotoxic responses at mucosal services to a widely conserved bacterial ligand. In this study, we tested whether a MAIT cell priming strategy could protect against aerosol Mycobacterium tuberculosis infection in mice. Intranasal costimulation with the lipopeptide Toll-like receptor (TLR)2/6 agonist, Pam2Cys (P2C), and the synthetic MR1 ligand, 5-OP-RU, resulted in robust expansion of MAIT cells in the lung. Although MAIT cell priming significantly enhanced MAIT cell activation and expansion early after M. tuberculosis challenge, these MAIT cells did not restrict M. tuberculosis bacterial load. MAIT cells were depleted by the onset of the adaptive immune response, with decreased detection of granzyme B+ and gamma interferon (IFN-γ)+ MAIT cells relative to that in uninfected P2C/5-OP-RU-treated mice. Decreasing the infectious inoculum, varying the time between priming and aerosol infection, and testing MAIT cell priming in nitric oxide synthase 2 (NOS2)-deficient mice all failed to reveal an effect of P2C/5-OP-RU-induced MAIT cells on M. tuberculosis control. We conclude that intranasal MAIT cell priming in mice induces early MAIT cell activation and expansion after M. tuberculosis exposure, without attenuating M. tuberculosis growth, suggesting that MAIT cell enrichment in the lung is not sufficient to control M. tuberculosis infection.
Keywords: Mycobacterium tuberculosis; Animals; Host-Pathogen Interactions; tuberculosis; Tuberculosis, Pulmonary; Mice; Disease Models, Animal; Immunity, Innate; Lymph Nodes; T-Lymphocyte Subsets; innate immunity; Lymphocyte Activation; Bacterial Load; Toll-Like Receptor 2; Nitric Oxide Synthase Type II; Mucosal-Associated Invariant T Cells; MAIT cells; Immunity, Mucosal; Respiratory Mucosa; Ribitol; Toll-Like Receptor 6; Uracil

Quantitative and Qualitative Perturbations of CD8+ MAITs in Healthy Mycobacterium tuberculosis-Infected Individuals - Pomaznoy, Mikhail; Kuan, Rebecca; Lindvall, Mikaela; Burel, Julie G.; Seumois, Grégory; Vijayanand, Pandurangan; Taplitz, Randy; Gilman, Robert H.; Saito, Mayuko; Lewinsohn, David M.; Sette, Alessandro; Peters, Bjoern; et al. (ImmunoHorizons, 2020)
CD8 T cells are considered important contributors to the immune response against Mycobacterium tuberculosis, yet limited information is currently known regarding their specific immune signature and phenotype. In this study, we applied a cell population transcriptomics strategy to define immune signatures of human latent tuberculosis infection (LTBI) in memory CD8 T cells. We found a 41-gene signature that discriminates between memory CD8 T cells from healthy LTBI subjects and uninfected controls. The gene signature was dominated by genes associated with mucosal-associated invariant T cells (MAITs) and reflected the lower frequency of MAITs observed in individuals with LTBI. There was no evidence for a conventional CD8 T cell-specific signature between the two cohorts. We, therefore, investigated MAITs in more detail based on Vα7.2 and CD161 expression and staining with an MHC-related protein 1 (MR1) tetramer. This revealed two distinct populations of CD8+Vα7.2+CD161+ MAITs: MR1 tetramer+ and MR1 tetramer-, which both had distinct gene expression compared with memory CD8 T cells. Transcriptomic analysis of LTBI versus noninfected individuals did not reveal significant differences for MR1 tetramer+ MAITs. However, gene expression of MR1 tetramer- MAITs showed large interindividual diversity and a tuberculosis-specific signature. This was further strengthened by a more diverse TCR-α and -β repertoire of MR1 tetramer- cells as compared with MR1 tetramer+ Thus, circulating memory CD8 T cells in subjects with latent tuberculosis have a reduced number of conventional MR1 tetramer+ MAITs as well as a difference in phenotype in the rare population of MR1 tetramer- MAITs compared with uninfected controls.
Keywords: Humans; Mycobacterium tuberculosis; Flow Cytometry; CD8-Positive T-Lymphocytes; Latent Tuberculosis; Histocompatibility Antigens Class I; Mucosal-Associated Invariant T Cells; Case-Control Studies; Minor Histocompatibility Antigens

Immunometabolism of Immune Cells in Mucosal Environment Drives Effector Responses against Mycobacterium tuberculosis - Tukiman, Mohd Hatimi; Norazmi, Mohd Nor (International Journal of Molecular Sciences, 2022)
Tuberculosis remains a major threat to global public health, with more than 1.5 million deaths recorded in 2020. Improved interventions against tuberculosis are urgently needed, but there are still gaps in our knowledge of the host-pathogen interaction that need to be filled, especially at the site of infection. With a long history of infection in humans, Mycobacterium tuberculosis (Mtb) has evolved to be able to exploit the microenvironment of the infection site to survive and grow. The immune cells are not only reliant on immune signalling to mount an effective response to Mtb invasion but can also be orchestrated by their metabolic state. Cellular metabolism was often overlooked in the past but growing evidence of its importance in the functions of immune cells suggests that it can no longer be ignored. This review aims to gain a better understanding of mucosal immunometabolism of resident effector cells, such as alveolar macrophages and mucosal-associated invariant T cells (MAIT cells), in response to Mtb infection and how Mtb manipulates them for its survival and growth, which could address our knowledge gaps while opening up new questions, and potentially be applied for future vaccination and therapeutic strategies.
Keywords: Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Tuberculosis; tuberculosis; Immunity, Innate; immunometabolism; Mucosal-Associated Invariant T Cells; glycolysis; gut-lung axis; innate and adaptive immune cells; oxidative phosphorylation

Effects of B Cell Depletion on Early Mycobacterium tuberculosis Infection in Cynomolgus Macaques - Phuah, Jiayao; Wong, Eileen A.; Gideon, Hannah P.; Maiello, Pauline; Coleman, M. Teresa; Hendricks, Matthew R.; Ruden, Rachel; Cirrincione, Lauren R.; Chan, John; Lin, Philana Ling; Flynn, JoAnne L. (Infection and Immunity, 2016)
Although recent studies in mice have shown that components of B cell and humoral immunity can modulate the immune responses against Mycobacterium tuberculosis, the roles of these components in human and nonhuman primate infections are unknown. The cynomolgus macaque (Macaca fascicularis) model of M. tuberculosis infection closely mirrors the infection outcomes and pathology in human tuberculosis (TB). The present study used rituximab, an anti-CD20 antibody, to deplete B cells in M. tuberculosis-infected macaques to examine the contribution of B cells and humoral immunity to the control of TB in nonhuman primates during the acute phase of infection. While there was no difference in the overall pathology, disease profession, and clinical outcome between the rituximab-treated and untreated macaques in acute infection, analyzing individual granulomas revealed that B cell depletion resulted in altered local T cell and cytokine responses, increased bacterial burden, and lower levels of inflammation. There were elevated frequencies of T cells producing interleukin-2 (IL-2), IL-10, and IL-17 and decreased IL-6 and IL-10 levels within granulomas from B cell-depleted animals. The effects of B cell depletion varied among granulomas in an individual animal, as well as among animals, underscoring the previously reported heterogeneity of local immunologic characteristics of tuberculous granulomas in nonhuman primates. Taken together, our data clearly showed that B cells can modulate the local granulomatous response in M. tuberculosis-infected macaques during acute infection. The impact of these alterations on disease progression and outcome in the chronic phase remains to be determined.
Keywords: Mycobacterium tuberculosis; Animals; Tuberculosis; Disease Models, Animal; Granuloma; Macaca fascicularis; T-Lymphocytes; B-Lymphocytes; Bacterial Load; Inflammation; Immunologic Factors; Leukocyte Reduction Procedures; Rituximab

Association of Human Antibodies to Arabinomannan With Enhanced Mycobacterial Opsonophagocytosis and Intracellular Growth Reduction | The Journal of Infectious Diseases | Oxford Academic

A novel human IgA monoclonal antibody protects against tuberculosis - Balu, Sucharitha; Reljic, Rajko; Lewis, Melanie J.; Pleass, Richard J.; McIntosh, Richard; van Kooten, Cees; van Egmond, Marjolein; Challacombe, Stephen; Woof, Jenny M.; Ivanyi, Juraj (Journal of Immunology (Baltimore, Md.: 1950), 2011)
Abs have been shown to be protective in passive immunotherapy of tuberculous infection using mouse experimental models. In this study, we report on the properties of a novel human IgA1, constructed using a single-chain variable fragment clone (2E9), selected from an Ab phage library. The purified Ab monomer revealed high binding affinities for the mycobacterial α-crystallin Ag and for the human FcαRI (CD89) IgA receptor. Intranasal inoculations with 2E9IgA1 and recombinant mouse IFN-γ significantly inhibited pulmonary H37Rv infection in mice transgenic for human CD89 but not in CD89-negative littermate controls, suggesting that binding to CD89 was necessary for the IgA-imparted passive protection. 2E9IgA1 added to human whole-blood or monocyte cultures inhibited luciferase-tagged H37Rv infection although not for all tested blood donors. Inhibition by 2E9IgA1 was synergistic with human rIFN-γ in cultures of purified human monocytes but not in whole-blood cultures. The demonstration of the mandatory role of FcαRI (CD89) for human IgA-mediated protection is important for understanding of the mechanisms involved and also for translation of this approach toward development of passive immunotherapy of tuberculosis.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis, Pulmonary; Mice; Antibodies, Monoclonal; Antigens, CD; Mice, Transgenic; Mycobacterium bovis; Immunoglobulin A; alpha-Crystallins; Binding Sites, Antibody; CHO Cells; Cricetinae; Cricetulus; Immunization, Passive; Receptors, Fc

Prevention of the post-chemotherapy relapse of tuberculous infection by combined immunotherapy - Buccheri, Simona; Reljic, Rajko; Caccamo, Nadia; Meraviglia, Serena; Ivanyi, Juraj; Salerno, Alfredo; Dieli, Francesco (Tuberculosis (Edinburgh, Scotland), 2009)
We report that a recently developed combined immunotherapy (CIT) has the capacity to prevent a spontaneous relapse of replicating Mycobacterium tuberculosis bacilli in the lungs of BALB/c, C57Bl/6 or C3H/HeJ strains of mice, following 4weeks of non-sterilising treatment with isoniazid and rifampicin. The CIT regimen, represented by recombinant IFNgamma, anti-alpha crystalline monoclonal IgA antibody and IL-4 neutralizing polyclonal antibody, reduced the 8-week relapse of viable bacterial counts in the lungs most significantly, when CIT was inoculated during the 5th week post infection, i.e. during the 3rd week of chemotherapy. Although CIT enhanced lung granuloma area, nitric oxide, cytokine and chemokine levels in lung washings significantly, these could not be directly associated with the beneficial effect of CIT on the degree of relapse in the lungs. These results represent a proof-of-principle, that the described CIT, when combined with chemotherapy, could have potential for future development of a shorter regimen of tuberculosis treatment.
Keywords: Mycobacterium tuberculosis; Animals; Antibodies; Recombinant Proteins; Tuberculosis, Pulmonary; Antitubercular Agents; Mice; Models, Animal; Adjuvants, Immunologic; Interferon-gamma; Mice, Inbred C57BL; Male; Colony Count, Microbial; Immunotherapy; Interleukin-4; Immunoglobulin A; Mice, Inbred BALB C; alpha-Crystallins; Combined Modality Therapy; Mice, Inbred C3H; Recurrence

A mycobacterial lipoarabinomannan specific monoclonal antibody and its F(ab') fragment prolong survival of mice infected with Mycobacterium tuberculosis - Hamasur, B.; Haile, M.; Pawlowski, A.; Schroder, U.; Kallenius, G.; Svenson, S. B. (Clinical and Experimental Immunology, 2004)
Lipoarabinomannan (LAM) is a major structural carbohydrate antigen of the outer surface of Mycobacterium tuberculosis. High antibody titres against LAM are often seen in active tuberculosis (TB). The role of such LAM-specific antibodies in the immune response against TB is unknown. Here we have investigated a monoclonal antibody (MoAb) SMITB14 of IgG1 subclass and its corresponding F(ab')(2) fragment directed against LAM from M. tuberculosis strain H37Rv. MoAb SMITB14 was shown by immunofluorescence to bind to whole cells of the clinical isolate M. tuberculosis strain Harlingen as well as to M. tuberculosis H37Rv. The binding of MoAb SMITB14 to LAM was inhibited by arabinomannan (AM) and oligosaccharides (5.2 kDa) derived from LAM, showing that the MoAb binds specifically to the AM carbohydrate portion of LAM. In passive protection experiments BALB/c mice were infected intravenously with M. tuberculosis Harlingen. MoAb SMITB14 was added intravenously either prior to, or together with, the bacteria. The antibody proved to be protective against the M. tuberculosis infection in terms of a dose-dependent reduction in bacterial load in spleens and lungs, reduced weight loss and, most importantly, increased long-term survival.
Keywords: Mycobacterium tuberculosis; Animals; Antigens, Bacterial; Tuberculosis; Mice; Female; Lung; Spleen; Antibodies, Monoclonal; Lipopolysaccharides; Dose-Response Relationship, Immunologic; Mice, Inbred BALB C; Immunoglobulin Fab Fragments; Antigens, Surface; Body Weight

Human Macrophages Exhibit GM-CSF Dependent Restriction of Mycobacterium tuberculosis Infection via Regulating Their Self-Survival, Differentiation and Metabolism - Mishra, Abhishek; Singh, Vipul K.; Jagannath, Chinnaswamy; Subbian, Selvakumar; Restrepo, Blanca I.; Gauduin, Marie-Claire; Khan, Arshad (Frontiers in Immunology, 2022)
GM-CSF is an important cytokine that regulates the proliferation of monocytes/macrophages and its various functions during health and disease. Although growing evidences support the notion that GM-CSF could play a major role in immunity against tuberculosis (TB) infection, the mechanism of GM-CSF mediated protective effect against TB remains largely unknown. Here in this study we examined the secreted levels of GM-CSF by human macrophages from different donors along with the GM-CSF dependent cellular processes that are critical for control of M. tuberculosis infection. While macrophage of different donors varied in their ability to produce GM-CSF, a significant correlation was observed between secreted levels of GM-CSF, survial of macrophages and intra-macrophage control of Mycobacterium tuberculosis bacilli. GM-CSF levels secreted by macrophages negatively correlated with the intra-macrophage M. tuberculosis burden, survival of infected host macrophages positively correlated with their GM-CSF levels. GM-CSF-dependent prolonged survival of human macrophages also correlated with significantly decreased bacterial burden and increased expression of self-renewal/cell-survival associated genes such as BCL-2 and HSP27. Antibody-mediated depletion of GM-CSF in macrophages resulted in induction of significantly elevated levels of apoptotic/necrotic cell death and a simultaneous decrease in autophagic flux. Additionally, protective macrophages against M. tuberculosis that produced more GM-CSF, induced a stronger granulomatous response and produced significantly increased levels of IL-1β, IL-12 and IL-10 and decreased levels of TNF-α and IL-6. In parallel, macrophages isolated from the peripheral blood of active TB patients exhibited reduced capacity to control the intracellular growth of M. tuberculosis and produced significantly lower levels of GM-CSF. Remarkably, as compared to healthy controls, macrophages of active TB patients exhibited significantly altered metabolic state correlating with their GM-CSF secretion levels. Altogether, these results suggest that relative levels of GM-CSF produced by human macrophages plays a critical role in preventing cell death and maintaining a protective differentiation and metabolic state of the host cell against M. tuberculosis infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Tuberculosis; Cell Differentiation; tuberculosis; Cytokines; autophagy; macrophages; Granulocyte-Macrophage Colony-Stimulating Factor; cell death; antigen presentation; cellular metabolism; granulocyte macrophage colony-stimulating factor

The role of antibodies in tuberculosis diagnosis, prophylaxis and therapy: a review from the ESGMYC study group - Melkie, Solomon Tibebu; Arias, Lilibeth; Farroni, Chiara; Jankovic Makek, Mateja; Goletti, Delia; Vilaplana, Cristina (European Respiratory Review: An Official Journal of the European Respiratory Society, 2022)
Tuberculosis (TB) is still responsible for the deaths of >1 million people yearly worldwide, and therefore its correct diagnosis is one of the key components of any TB eradication programme. However, current TB diagnostic tests have many limitations, and improved diagnostic accuracy is urgently needed. To improve the diagnostic performance of traditional serology, a combination of different Mycobacterium tuberculosis (MTB) antigens and different antibody isotypes has been suggested, with some showing promising performance for the diagnosis of active TB. Given the incomplete protection conferred by bacille Calmette-Guérin (BCG) vaccination against adult pulmonary TB, efforts to discover novel TB vaccines are ongoing. Efficacy studies from advanced TB vaccines designed to stimulate cell-mediated immunity failed to show protection, suggesting that they may not be sufficient and warranting the need for other types of immunity. The role of antibodies as tools for TB therapy, TB diagnosis and TB vaccine design is discussed. Finally, we propose that the inclusion of antibody-based TB vaccines in current clinical trials may be advisable to improve protection.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; Tuberculosis, Pulmonary; BCG Vaccine

Biorecognition and detection of antigens from Mycobacterium tuberculosis using a sandwich ELISA associated with magnetic nanoparticles - León-Janampa, Nancy; Shinkaruk, Svitlana; Gilman, Robert H.; Kirwan, Daniela E.; Fouquet, Eric; Szlosek, Magali; Sheen, Patricia; Zimic, Mirko (Journal of Pharmaceutical and Biomedical Analysis, 2022)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), is one of the 10 leading causes of death worldwide, especially in low-income areas. A rapid, low-cost diagnostic assay for TB with high sensitivity and specificity is not currently available. Bio-functionalized magnetic nanoparticles (MNPs) which are able to efficiently detect and concentrate biomolecules from complex biological samples, allows improving the diagnostic immunoassays. In this way, a proof-of-concept of MNP-based sandwich immunoassay was developed to detect various MTB protein antigens. The superficial and secretory antigenic proteins considered in this research were: CFP10, ESAT6, MTC28, MPT64, 38 kDa protein, Ag85B, and MoeX. The proteins were cloned and expressed in an E. coli system. Polyclonal antibodies (ab) against the recombinant antigens were elicited in rabbits and mice. Antibodies were immobilized on the surface of amine-silanized nanoparticles (MNP@Si). The functionalized MNP@Si@ab were tested in a colorimetric sandwich enzyme-linked immunosorbent assay (sELISA-MNP@Si@ab) to recognize the selected antigens in sputum samples. The selected MTB antigens were successfully detected in sputum from TB patients in a shorter time (~ 4 h) using the sELISA-MNP@Si@ab, compared to the conventional sELISA (~15 h) standardized in home. Moreover, the sELISA-MNP@Si@ab showed the higher sensitivity in the real biological samples from infected patients.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Rabbits; Antigens, Bacterial; Escherichia coli; Mice; Sensitivity and Specificity; Enzyme-Linked Immunosorbent Assay; Tuberculosis, Lymph Node; Active tuberculosis; Biofunctionalization; Immunoassay; Magnetic nanoparticle; Magnetite Nanoparticles; Polyclonal antibody; Recombinant protein

Monoclonal antibodies to lipoarabinomannan/arabinomannan - characteristics and implications for tuberculosis research and diagnostics - Corrigan, Devin T.; Ishida, Elise; Chatterjee, Delphi; Lowary, Todd L.; Achkar, Jacqueline M. (Trends in Microbiology, 2022)
Antibodies to the mycobacterial surface lipoglycan lipoarabinomannan (LAM) and its related capsular polysaccharide arabinomannan (AM) are increasingly important for investigations focused on both understanding mechanisms of protection against Mycobacterium tuberculosis (Mtb) and developing next-generation point-of-care tuberculosis (TB) diagnostics. We provide here an overview of the growing pipeline of monoclonal antibodies (mAbs) to LAM/AM. Old and new methodologies for their generation are reviewed and we outline and discuss their glycan epitope specificity and other features with implications for the TB field.
Keywords: mycobacteria; biomarker; antigen–antibody interactions; glycans; lipoglycans; oligosaccharides; point-of-care tests

Antibodies: what makes us stronger - Freund, Natalia T. (Human Vaccines & Immunotherapeutics, 2021)
Neutralizing antibodies are the basis of almost all approved prophylactic vaccines and the foundation of effective protection from pathogens, including the recently emerging SARS Coronavirus 2 (SARS-CoV-2). However, the contribution of antibodies to protection and to the course of the disease during first-time exposure to a pathogen is unknown. We analyzed the antibodies and B cell responses in severe and mild COVID-19 patients. Despite our primary assumption that high antibody titers contribute to a mild disease, we found that severe COVID-19 illness, and not mild infection, correlates with strong anti-viral antibody and memory B cell responses. This phenomenon was also demonstrated for anti-Mycobacterium tuberculosis inhibiting antibodies that we recently isolated from an actively infected Tuberculosis-sick donor. This correlation between disease severity and antibody responses can be explained by the fact that high viral loads drive B cell stimulation and generation of high-affinity antibodies that will be protective upon future encounter with the particular pathogen.
Keywords: Humans; tuberculosis; Antibody Formation; B cells; COVID-19; SARS-CoV-2; Antibodies, Neutralizing; Antibodies, Viral; neutralizing antibodies; Spike Glycoprotein, Coronavirus

Optimisation of human VH domain antibodies specific to Mycobacterium tuberculosis heat shock protein (HSP16.3) - Soong, Jia Xin; Chan, Soo Khim; Lim, Theam Soon; Choong, Yee Siew (Journal of Computer-Aided Molecular Design, 2019)
Mycobacterium tuberculosis (Mtb) 16.3 kDa heat shock protein 16.3 (HSP16.3) is a latency-associated antigen that can be targeted for latent tuberculosis (TB) diagnostic and therapeutic development. We have previously developed human VH domain antibodies (dAbs; clone E3 and F1) specific against HSP16.3. In this work, we applied computational methods to optimise and design the antibodies in order to improve the binding affinity with HSP16.3. The VH domain antibodies were first docked to the dimer form of HSP16.3 and further sampled using molecular dynamics simulation. The calculated binding free energy of the HSP16.3-dAb complexes showed non-polar interactions were responsible for the antigen-antibody association. Per-residue free energy decomposition and computational alanine scanning have identified one hotspot residue for E3 (Y391) and 4 hotspot residues for F1 (M394, Y396, R397 and M398). These hotspot residues were then mutated and evaluated by binding free energy calculations. Phage ELISA assay was carried out on the potential mutants (E3Y391W, F1M394E, F1R397N and F1M398Y). The experimental assay showed improved binding affinities of E3Y391W and F1M394E against HSP16.3 compared with the wild type E3 and F1. This case study has thus showed in silico methods are able to assist in optimisation or improvement of antibody-antigen binding.
Keywords: Bacterial Proteins; Humans; Antibodies; Protein Binding; Models, Molecular; Protein Conformation; Databases, Protein; Computer Simulation; Protein Domains; Antibody optimisation and design; Chaperonins; Computational alanine scanning; Human VH domain antibodies; Mycobacterium tuberculosis 16.3 kDa heat shock protein (HSP16.3); Per-residue energy decomposition; Point Mutation; Thermodynamics

Mycobacterium tuberculosis HN878 Infection Induces Human-Like B-Cell Follicles in Mice - Choreño-Parra, José Alberto; Bobba, Suhas; Rangel-Moreno, Javier; Ahmed, Mushtaq; Mehra, Smriti; Rosa, Bruce; Martin, John; Mitreva, Makedonka; Kaushal, Deepak; Zúñiga, Joaquín; Khader, Shabaana A. (The Journal of Infectious Diseases, 2020)
Specific spatial organization of granulomas within the lungs is crucial for protective anti-tuberculosis (TB) immune responses. However, only large animal models such as macaques are thought to reproduce the morphological hallmarks of human TB granulomas. In this study, we show that infection of mice with clinical "hypervirulent" Mycobacterium tuberculosis (Mtb) HN878 induces human-like granulomas composed of bacilli-loaded macrophages surrounded by lymphocytes and organized localization of germinal centers and B-cell follicles. Infection with laboratory-adapted Mtb H37Rv resulted in granulomas that are characterized by unorganized clusters of macrophages scattered between lymphocytes. An in-depth exploration of the functions of B cells within these follicles suggested diverse roles and the activation of signaling pathways associated with antigen presentation and immune cell recruitment. These findings support the use of clinical Mtb HN878 strain for infection in mice as an appropriate model to study immune parameters associated with human TB granulomas.
Keywords: Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis, Pulmonary; Granuloma; Lung; Virulence; Macaca mulatta; B-Lymphocytes; Mice, Knockout; Lymphocytes; pulmonary tuberculosis; B-cell follicles; human granulomatous diseases; Immunoglobulin mu-Chains; lung granuloma; Mycobacterium tuberculosis HN878

Updates on antibody functions in Mycobacterium tuberculosis infection and their relevance for developing a vaccine against tuberculosis - Achkar, Jacqueline M.; Prados-Rosales, Rafael (Current Opinion in Immunology, 2018)
A more effective vaccine to control tuberculosis (TB), a major global public health problem, is urgently needed. Current vaccine candidates focus predominantly on eliciting cell-mediated immunity but other arms of the immune system also contribute to protection against TB. We review here recent studies that enhance our current knowledge of antibody-mediated functions against Mycobacterium tuberculosis. These findings, which contribute to the increasing evidence that antibodies have a protective role against TB, include demonstrations that firstly distinct human antibody Fc glycosylation patterns, found in latent M. tuberculosis infection but not in active TB, influence the efficacy of the host to control M. tuberculosis infection, secondly antibody isotype influences human antibody functions, and thirdly that antibodies targeting M. tuberculosis surface antigens are protective. We discuss these findings in the context of TB vaccine development and highlight the need for further research on antibody-mediated immunity in M. tuberculosis infection.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Host-Pathogen Interactions; Antigens, Bacterial; Tuberculosis; Glycosylation; Immunity, Humoral; Latent Tuberculosis; Vaccination

Synergy between Th1 and Th2 responses during Mycobacterium tuberculosis infection: A review of current understanding - Abebe, Fekadu (International Reviews of Immunology, 2019)
Induction of Th1 (cell-mediated) immunity and associated production of IFN-γ by CD4+ T cells has been widely used as a marker of protective immunity against tuberculosis (TB). This is based on two assumptions. The first is the widely accepted view that Mycobacterium tuberculosis (Mtb), the causative agent of TB is an obligate intracellular pathogen, and the second is based on the Th1/Th2 paradigm, which posits that polarization of CD4+ T cells into type1 (cell-mediated) and type 2 (humoral) is central for proper induction of protective immunity against pathogens. However, almost all licensed vaccines currently in use are primarily anti-body based whether intracellular or extra-cellular. In addition, converging data from both animal models and humans indicate that the production of IFN-γ alone is not sufficient to confer protection against TB. In addition, a substantial body of the literature suggests that, in addition to Th1 cells, antibody classes and sub-classes are protective against TB. In a recent study, we have shown that there is a synergy between IFN-γ (cell-mediated) and IgA (humoral) in human population in an endemic setting. In this review, current data from both animal and human studies that support mixed Th1 and Th2 responses that are protective against Mtb and other pathogens are presented.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; Interferon-gamma; Th1 Cells; Th2 Cells; immunity; antibody; cell-mediated; synergy

Therapeutic Vaccines for Tuberculosis: An Overview - Bouzeyen, Rania; Javid, Babak (Frontiers in Immunology, 2022)
Tuberculosis (TB), caused by Mycobacterium tuberculosis is the world's deadliest bacterial infection, resulting in more than 1.4 million deaths annually. The emergence of drug-resistance to first-line antibiotic therapy poses a threat to successful treatment, and novel therapeutic options are required, particularly for drug-resistant tuberculosis. One modality emerging for TB treatment is therapeutic vaccination. As opposed to preventative vaccination - the aim of which is to prevent getting infected by M. tuberculosis or developing active tuberculosis, the purpose of therapeutic vaccination is as adjunctive treatment of TB or to prevent relapse following cure. Several candidate therapeutic vaccines, using killed whole-cell or live attenuated mycobacteria, mycobacterial fragments and viral vectored vaccines are in current clinical trials. Other modes of passive immunization, including monoclonal antibodies directed against M. tuberculosis antigens are in various pre-clinical stages of development. Here, we will discuss these various therapeutics and their proposed mechanisms of action. Although the full clinical utility of therapeutic vaccination for the treatment of tuberculosis is yet to be established, they hold potential as useful adjunct therapies.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; tuberculosis; BCG Vaccine; Vaccination; monoclonal antibody; mRNA vaccine; mycobacterium; prevention of recurrence; therapeutic vaccines

Mycobacterium tuberculosis in transplantation: Immunity sufficient to perpetuate disease? - Fishman, Jay A. (American Journal of Transplantation: Official Journal of the American Society of Transplantation and the American Society of Transplant Surgeons, 2019)
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; infectious disease; belatacept; editorial/personal viewpoint; immunobiology; immunosuppressant - fusion proteins and monoclonal antibodies; immunosuppression/immune modulation; Immunosuppressive Agents; infection - mycobacterial; infection and infectious agents; Kidney Transplantation; macrophage/monocyte biology; Retrospective Studies

Detection of anti-HspX antibodies and HspX protein in patient sera for the identification of recent latent infection by Mycobacterium tuberculosis - Castro-Garza, Jorge; García-Jacobo, Paola; Rivera-Morales, Lydia G.; Quinn, Frederick D.; Barber, James; Karls, Russell; Haas, Debra; Helms, Shelly; Gupta, Tuhina; Blumberg, Henry; Tapia, Jane; Luna-Cruz, Itza; et al. (PloS One, 2017)
Mycobacterium tuberculosis is a pathogen causing tuberculosis (TB) a spectrum of disease including acute and asymptomatic latent stages. Identifying and treating latently-infected patients constitutes one of the most important impediments to TB control efforts. Those individuals can remain undiagnosed for decades serving as potential reservoirs for disease reactivation. Tests for the accurate diagnosis of latent infection currently are unavailable. HspX protein (α-crystallin), encoded by Rv2031c gene, is produced in vitro by M. tuberculosis during stationary growth phase and hypoxic or acidic culture conditions. In this study, using standard, and Luminex xMAP® bead capture ELISA, respectively, we report on detection of anti-HspX IgG and IgM antibodies and HspX protein in sera from acute and latent TB patients. For the antibody screen, levels of IgG and IgM antibodies were similar between non-infected and active TB patients; however, individuals classified into the group with latent TB showed higher values of anti-HspX IgM (p = 0.003) compared to active TB patients. Using the bead capture antigen detection assay, HspX protein was detected in sera from 56.5% of putative latent cases (p< 0.050) compared to the background median with an average of 9,900 pg/ml and a range of 1,000 to 36,000 pg/ml. Thus, presence of anti-HspX IgM antibodies and HspX protein in sera may be markers of latent TB.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Immunoglobulin G; Tuberculosis; Female; Latent Tuberculosis; Male; Enzyme-Linked Immunosorbent Assay; Immunoglobulin M; alpha-Crystallins; Cross Reactions

Bcells and their regulatory functions during Tuberculosis: Latency and active disease - Loxton, Andre G. (Molecular Immunology, 2019)
Tuberculosis (TB) is a global epidemic with devastating consequences. Emerging evidence suggests that B-cells have the ability to modulate the immune response and understanding these roles during Mycobacterium tuberculosis (M.tb) infection can help to find new strategies to treat TB. The immune system of individuals with pulmonary TB form granulomas in the lung which controls the infection by inhibiting the M.tb growth and acts as a physical barrier. Thereafter, surviving M.tb become dormant and in most cases the host's immunity prevents TB reactivation. B-cells execute several immunological functions and are regarded as protective regulators of immune responses by antibody and cytokine production, as well as presenting antigen. Some of these B-cells, or regulatory B-cells, have been shown to express death-inducing ligands, such as Fas ligand (FasL). This expression and binding to the Fas receptor leads to apoptosis, a major immune regulation mechanism, in addition to the ability to induce T-cell tolerance. Here, I discuss the relevance of B-cells, in particular their non-humoral functions by addressing their regulatory properties during M.tb infection.
Keywords: Mycobacterium tuberculosis; Tuberculosis; Tuberculosis, Pulmonary; B-Lymphocytes; Lymphocyte Activation; Apoptosis; Fas Ligand Protein; fas Receptor; Virus Latency; B-cells; FasL; Latency; Non-humoral; Regulatory B-cells

Mycobacterium tuberculosis-specific plasmablast levels are differentially modulated in tuberculosis infection and disease - Gindeh, Awa; Owolabi, Olumuyiwa; Donkor, Simon; Sutherland, Jayne S. (Tuberculosis (Edinburgh, Scotland), 2020)
BACKGROUND: While T cell responses to Mycobacterium tuberculosis (Mtb) have been extensively studied, the role of B-cells and antibodies are less well characterised. The aim of this study was to assess levels of Mtb-specific IgG + plasmablasts across the Mtb infection spectrum. METHODS: Patients with active TB were analysed at baseline and 6 months of therapy (n = 20).Their exposed household contacts (HHC) included individuals with latent TB infection (LTBI; n = 20); evident at baseline; individuals with a negative Tuberculin Skin Test (TST) at baseline who became; positive at 6 months (converters; n = 11) and those who remained negative (non-converters; n = 10). An e x-vivo B-cell ELISPOT was performed to analyse plasmablast responses. RESULTS: Frequencies of ESAT-6/CFP-10 (EC)- but not Whole Cell Lysate (WCL)-specific plasmablasts were significantly higher in patients with active TB pre-treatment compared to post-treatment (p = 0.002) and compared to HHC with LTBI (p < 0.0001). Conversely, total IgG + plasmablasts were significantly decreased in TB patients at baseline. No difference was seen in levels of plasmablasts between TST converters and non-converters at baseline. CONCLUSIONS: We show that EC-specific plasmablast levels are differentially modulated during TB infection and disease, with levels highest during active TB. These data provide new insights into TB biomarker development and avenues for novel immune interventions.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Antigens, Bacterial; Tuberculosis; Antitubercular Agents; Female; Adult; Male; Middle Aged; Young Adult; Adolescent; Time Factors; Predictive Value of Tests; Immunology; B-Lymphocyte Subsets; Gambia; Enzyme-Linked Immunospot Assay; ESAT-6/CFP10; Mtb infection spectrum; Pilot Projects; Plasmablasts; Treatment Outcome

An Inflammatory Story: Antibodies in Tuberculosis Comorbidities - McLean, Milla R.; Lu, Lenette L.; Kent, Stephen J.; Chung, Amy W. (Frontiers in Immunology, 2019)
Mycobacterium tuberculosis (Mtb) resides in a quarter of the world's population and is the causative agent for tuberculosis (TB), the most common infectious reason of death in humans today. Although cellular immunity has been firmly established in the control of Mtb, there is growing evidence that antibodies may also modulate the infection. More specifically, certain antibody features are associated with inflammation and are divergent in different states of human infection and disease. Importantly, TB impacts not just the healthy but also those with chronic conditions. While HIV represents the quintessential comorbid condition for TB, recent epidemiological evidence shows that additional chronic conditions such as diabetes and kidney disease are rising. In fact, the prevalence of diabetes as a comorbid TB condition is now higher than that of HIV. These chronic diseases are themselves independently associated with pro-inflammatory immune states that encompass antibody profiles. This review discusses isotypes, subclasses, post-translational modifications and Fc-mediated functions of antibodies in TB infection and in the comorbid chronic conditions of HIV, diabetes, and kidney diseases. We propose that inflammatory antibody profiles, which are a marker of active TB, may be an important biomarker for detection of TB disease progression within comorbid individuals. We highlight the need for future studies to determine which inflammatory antibody profiles are the consequences of comorbidities and which may potentially contribute to TB reactivation.
Keywords: Humans; Mycobacterium tuberculosis; Antibodies; Tuberculosis; tuberculosis; Biomarkers; Immunoglobulin Isotypes; Glycosylation; Latent Tuberculosis; Inflammation Mediators; Coinfection; HIV; glycosylation; inflammation; antibody; co-infection; Comorbidity; diabetes; kidney disease

BCG-induced protection against Mycobacterium tuberculosis infection: Evidence, mechanisms, and implications for next-generation vaccines - Foster, Mitchell; Hill, Philip C.; Setiabudiawan, Todia Pediatama; Koeken, Valerie A. C. M.; Alisjahbana, Bachti; van Crevel, Reinout (Immunological Reviews, 2021)
The tuberculosis (TB) vaccine Bacillus Calmette-Guérin (BCG) was introduced 100 years ago, but as it provides insufficient protection against TB disease, especially in adults, new vaccines are being developed and evaluated. The discovery that BCG protects humans from becoming infected with Mycobacterium tuberculosis (Mtb) and not just from progressing to TB disease provides justification for considering Mtb infection as an endpoint in vaccine trials. Such trials would require fewer participants than those with disease as an endpoint. In this review, we first define Mtb infection and disease phenotypes that can be used for mechanistic studies and/or endpoints for vaccine trials. Secondly, we review the evidence for BCG-induced protection against Mtb infection from observational and BCG re-vaccination studies, and discuss limitations and variation of this protection. Thirdly, we review possible underlying mechanisms for BCG efficacy against Mtb infection, including alternative T cell responses, antibody-mediated protection, and innate immune mechanisms, with a specific focus on BCG-induced trained immunity, which involves epigenetic and metabolic reprogramming of innate immune cells. Finally, we discuss the implications for further studies of BCG efficacy against Mtb infection, including for mechanistic research, and their relevance to the design and evaluation of new TB vaccines.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis Vaccines; Tuberculosis; tuberculosis; vaccine; BCG Vaccine; T-Lymphocytes; innate immunity; BCG; epigenetics; phenotypes

Antibodies to Mycobacterium tuberculosis - Casadevall, Arturo (The New England Journal of Medicine, 2017)
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Immunoglobulin G; B-Lymphocytes; Immunity, Humoral; Receptors, Fc

Antibodies and tuberculosis: finally coming of age? - Li, Hao; Javid, Babak (Nature Reviews. Immunology, 2018)
Are antibodies important for protection against tuberculosis? The jury has been out for more than 100 years. B cell depletion in experimental Mycobacterium tuberculosis infection failed to identify a major role for these cells in immunity to tuberculosis. However, recent identification of naturally occurring antibodies in humans that are protective during M. tuberculosis infection has reignited the debate. Here, we discuss the evidence for a protective role for antibodies in tuberculosis and consider the feasibility of designing novel tuberculosis vaccines targeting humoral immunity.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Antigens, Bacterial; Tuberculosis; Immunity, Innate; Models, Immunological; B-Lymphocytes; Immunity, Humoral

Human antibodies targeting a Mycobacterium transporter protein mediate protection against tuberculosis - Watson, Avia; Li, Hao; Ma, Bingting; Weiss, Ronen; Bendayan, Daniele; Abramovitz, Lilach; Ben-Shalom, Noam; Mor, Michael; Pinko, Erica; Bar Oz, Michal; Wang, Zhenqi; Du, Fengjiao; et al. (Nature Communications, 2021)
Mycobacterium tuberculosis (Mtb) exposure drives antibody responses, but whether patients with active tuberculosis elicit protective antibodies, and against which antigens, is still unclear. Here we generate monoclonal antibodies from memory B cells of one patient to investigate the B cell responses during active infection. The antibodies, members of four distinct B cell clones, are directed against the Mtb phosphate transporter subunit PstS1. Antibodies p4-36 and p4-163 reduce Mycobacterium bovis-BCG and Mtb levels in an ex vivo human whole blood growth inhibition assay in an FcR-dependent manner; meanwhile, germline versions of p4-36 and p4-163 do not bind Mtb. Crystal structures of p4-36 and p4-170, complexed to PstS1, are determined at 2.1 Å and 2.4 Å resolution, respectively, to reveal two distinctive PstS1 epitopes. Lastly, a prophylactic p4-36 and p4-163 treatment in Mtb-infected Balb/c mice reduces bacterial lung burden by 50%. Our study shows that inhibitory anti-PstS1 B cell responses arise during active tuberculosis.
Keywords: Amino Acid Sequence; Antibodies, Bacterial; Bacterial Proteins; Humans; Mycobacterium tuberculosis; Animals; Protein Structure, Secondary; Tuberculosis; Models, Molecular; Structure-Activity Relationship; Antibodies, Monoclonal; B-Lymphocytes; Adult; Male; Immunologic Memory; Epitopes; Mice, Inbred BALB C; Membrane Transport Proteins; THP-1 Cells

B-Cells and Antibodies as Contributors to Effector Immune Responses in Tuberculosis - Rijnink, Willemijn F.; Ottenhoff, Tom H. M.; Joosten, Simone A. (Frontiers in Immunology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is still a major threat to mankind, urgently requiring improved vaccination and therapeutic strategies to reduce TB-disease burden. Most present vaccination strategies mainly aim to induce cell-mediated immunity (CMI), yet a series of independent studies has shown that B-cells and antibodies (Abs) may contribute significantly to reduce the mycobacterial burden. Although early studies using B-cell knock out animals did not support a major role for B-cells, more recent studies have provided new evidence that B-cells and Abs can contribute significantly to host defense against Mtb. B-cells and Abs exist in many different functional subsets, each equipped with unique functional properties. In this review, we will summarize current evidence on the contribution of B-cells and Abs to immunity toward Mtb, their potential utility as biomarkers, and their functional contribution to Mtb control.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; tuberculosis; antibodies; B-Lymphocytes; Immunity, Humoral; B-cells; biomarker; humoral immunity

Robust IgM responses following intravenous vaccination with Bacille Calmette–Guérin associate with prevention of Mycobacterium tuberculosis infection in macaques - Irvine, Edward B.; O’Neil, Anthony; Darrah, Patricia A.; Shin, Sally; Choudhary, Alok; Li, Wenjun; Honnen, William; Mehra, Smriti; Kaushal, Deepak; Gideon, Hannah Priyadarshini; Flynn, JoAnne L.; Roederer, Mario; et al. (Nature Immunology, 2021)
Development of an effective tuberculosis (TB) vaccine has suffered from an incomplete understanding of the correlates of protection against Mycobacterium tuberculosis (Mtb). Intravenous (i.v.) vaccination with Bacille Calmette–Guérin (BCG) provides nearly complete protection against TB in rhesus macaques, but the antibody response it elicits remains incompletely defined. Here we show that i.v. BCG drives superior antibody responses in the plasma and the lungs of rhesus macaques compared to traditional intradermal BCG administration. While i.v. BCG broadly expands antibody titers and functions, IgM titers in the plasma and lungs of immunized macaques are among the strongest markers of reduced bacterial burden. IgM was also enriched in macaques that received protective vaccination with an attenuated strain of Mtb. Finally, an Mtb-specific IgM monoclonal antibody reduced Mtb survival in vitro. Collectively, these data highlight the potential importance of IgM responses as a marker and mediator of protection against TB., Alter and colleagues show that IgM titers in the plasma and bronchoalveolar lavage fluid represent markers of reduced Mtb burden in rhesus macaques vaccinated intravenously with Bacille Calmette–Guérin.

TREM-2 promotes macrophage-mediated eradication of Pseudomonas aeruginosa via a PI3K/Akt pathway - Zhu, M.; Li, D.; Wu, Y.; Huang, X.; Wu, M. (Scandinavian Journal of Immunology, 2014)
Triggering receptor expressed on myeloid cells 2 (TREM-2) is a cell surface receptor abundantly expressed on myeloid lineage cells such as macrophages and dendritic cells. It is reported that TREM-2 functions as an inflammatory inhibitor in macrophages and dendritic cells. However, the role of TREM-2 in bacterial killing remains unclear. This study explored the role of TREM-2 in bacterial eradication of Pseudomonas aeruginosa (PA), a Gram-negative bacterium which causes various opportunistic infections. Phagocytosis assay assessed by flow cytometry suggested that TREM-2 was not involved in the uptake of PA by macrophages, while bacterial plate count data showed that TREM-2 was required for macrophage-mediated intracellular killing of PA. Moreover, our results demonstrated that TREM-2 promoted macrophage killing by enhancing reactive oxygen species (ROS), but not nitric oxygen (NO) production. Treatment with N-acetylcysteine, a ROS scavenger, diminished the TREM-2-mediated intracellular killing of PA. To further investigate the underlined mechanisms of TREM-2-promoted bacterial killing, we examined the activation of downstream mitogen-activated protein kinases and PI3K/Akt pathway. Western blot data showed that silencing of TREM-2 inhibited phosphorylation of Akt, but not ERK, JNK or P38. In addition, pretreatment with PI3K active product PIP3 DiC16 reversed the elevation of intracellular bacterial load in TREM-2-silenced macrophages, while PI3K inhibitor wortmannin restored the decline of bacterial load in TREM-2-overexpressed macrophages. These data together suggested that the TREM-2-mediated bacterial killing is dependent on the activation of PI3K/Akt signalling, which may provide a better understanding of the host antibacterial immune defence.
Keywords: Cell Line; Animals; Macrophages; Mice; Signal Transduction; Phagocytosis; Bacterial Load; Membrane Glycoproteins; Reactive Oxygen Species; Proto-Oncogene Proteins c-akt; p38 Mitogen-Activated Protein Kinases; Phosphatidylinositol 3-Kinases; Nitric Oxide; Phosphorylation; RNA, Small Interfering; Extracellular Signal-Regulated MAP Kinases; Receptors, Immunologic; Acetylcysteine; Androstadienes; JNK Mitogen-Activated Protein Kinases; Phosphatidylinositols; Phosphoinositide-3 Kinase Inhibitors; Pseudomonas aeruginosa; Pseudomonas Infections; RNA Interference; Wortmannin

Mucosal Therapy of Multi-Drug Resistant Tuberculosis With IgA and Interferon-γ - Tran, Andy C.; Diogo, Gil R.; Paul, Matthew J.; Copland, Alastair; Hart, Peter; Mehta, Nickita; Irvine, Edward B.; Mussá, Tufária; Drake, Pascal M. W.; Ivanyi, Juraj; Alter, Galit; Reljic, Rajko (Frontiers in Immunology, 2020)
New evidence has been emerging that antibodies can be protective in various experimental models of tuberculosis. Here, we report on protection against multidrug-resistant Mycobacterium tuberculosis (MDR-TB) infection using a combination of the human monoclonal IgA 2E9 antibody against the alpha-crystallin (Acr, HspX) antigen and mouse interferon-gamma in mice transgenic for the human IgA receptor, CD89. The effect of the combined mucosal IgA and IFN-γ; treatment was strongest (50-fold reduction) when therapy was applied at the time of infection, but a statistically significant reduction of lung bacterial load was observed even when the therapy was initiated once the infection had already been established. The protection involving enhanced phagocytosis and then neutrophil mediated killing of infected cells was IgA isotype mediated, because treatment with an IgG version of 2E9 antibody was not effective in human IgG receptor CD64 transgenic mice. The Acr antigen specificity of IgA antibodies for protection in humans has been indicated by their elevated serum levels in latent tuberculosis unlike the lack of IgA antibodies against the virulence-associated MPT64 antigen. Our results represent the first evidence for potential translation of mucosal immunotherapy for the management of MDR-TB.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; U937 Cells; Animals; Antigens, Bacterial; Tuberculosis; tuberculosis; Mice; Neutrophils; Lung; Interferon-gamma; Antibodies, Monoclonal; Receptors, IgG; Antigens, CD; Mice, Transgenic; Phagocytosis; Bacterial Load; Immunoglobulin A; drug resistance; Respiratory Mucosa; alpha-Crystallins; Receptors, Fc; THP-1 Cells; alpha crystallin; CD89 (Fc alpha/muR); Drug Resistance, Multiple; HspX; IgA; interferon-gamma; mAb—monoclonal antibody

Capsular glycan recognition provides antibody-mediated immunity against tuberculosis - Chen, Tingting; Blanc, Caroline; Liu, Yanyan; Ishida, Elise; Singer, Sarah; Xu, Jiayong; Joe, Maju; Jenny-Avital, Elizabeth R.; Chan, John; Lowary, Todd L.; Achkar, Jacqueline M. (The Journal of Clinical Investigation)
A better understanding of all immune components involved in protecting against Mycobacterium tuberculosis infection is urgently needed to inform strategies for novel immunotherapy and tuberculosis (TB) vaccine development. Although cell-mediated immunity is critical, increasing evidence supports that antibodies also have a protective role against TB. Yet knowledge of protective antigens is limited. Analyzing sera from 97 US immigrants at various stages of M. tuberculosis infection, we showed protective in vitro and in vivo efficacy of polyclonal IgG against the M. tuberculosis capsular polysaccharide arabinomannan (AM). Using recently developed glycan arrays, we established that anti-AM IgG induced in natural infection is highly heterogeneous in its binding specificity and differs in both its reactivity to oligosaccharide motifs within AM and its functions in bacillus Calmette-Guérin vaccination and/or in controlled (latent) versus uncontrolled (TB) M. tuberculosis infection. We showed that anti-AM IgG from asymptomatic but not from diseased individuals was protective and provided data suggesting a potential role of IgG2 and specific AM oligosaccharides. Filling a gap in the current knowledge of protective antigens in humans, our data support the key role of the M. tuberculosis surface glycan AM and suggest the importance of targeting specific glycan epitopes within AM in antibody-mediated immunity against TB.

Mycobacterium tuberculosis infection of host cells in space and time - Bussi, Claudio; Gutierrez, Maximiliano G (FEMS Microbiology Reviews, 2019)
Tuberculosis (TB) caused by the bacterial pathogen Mycobacterium tuberculosis (Mtb) remains one of the deadliest infectious diseases with over a billion deaths in the past 200 years (Paulson ). TB causes more deaths worldwide than any other single infectious agent, with 10.4 million new cases and close to 1.7 million deaths in 2017. The obstacles that make TB hard to treat and eradicate are intrinsically linked to the intracellular lifestyle of Mtb. Mtb needs to replicate within human cells to disseminate to other individuals and cause disease. However, we still do not completely understand how Mtb manages to survive within eukaryotic cells and why some cells are able to eradicate this lethal pathogen. Here, we summarise the current knowledge of the complex host cell-pathogen interactions in TB and review the cellular mechanisms operating at the interface between Mtb and the human host cell, highlighting the technical and methodological challenges to investigating the cell biology of human host cell-Mtb interactions., The review describes the complex dynamics underlying the interactions between Mycobacterium tuberculosis and the human host cell with an emphasis on the cell biology approaches and potential challenges to study these processes.

Prevention of tuberculosis infection and disease by local BCG in repeatedly exposed rhesus macaques - Dijkman, Karin; Sombroek, Claudia C.; Vervenne, Richard A. W.; Hofman, Sam O.; Boot, Charelle; Remarque, Edmond J.; Kocken, Clemens H. M.; Ottenhoff, Tom H. M.; Kondova, Ivanela; Khayum, Mohammed A.; Haanstra, Krista G.; Vierboom, Michel P. M.; et al. (Nature Medicine, 2019)
Tuberculosis (TB) remains the deadliest infectious disease1, and the widely used Bacillus Calmette-Guérin (BCG) vaccine fails to curb the epidemic. An improved vaccination strategy could provide a cost-effective intervention to break the transmission cycle and prevent antimicrobial resistance2,3. Limited knowledge of the host responses critically involved in protective immunity hampers the development of improved TB vaccination regimens. Therefore, assessment of new strategies in preclinical models to select the best candidate vaccines before clinical vaccine testing remains indispensable. We have previously established in rhesus macaques (Macaca mulatta) that pulmonary mucosal BCG delivery reduces TB disease where standard intradermal injection fails4,5. Here, we show that pulmonary BCG prevents infection by using a repeated limiting-dose Mycobacterium tuberculosis challenge model and identify polyfunctional T-helper type 17 (TH17) cells, interleukin-10 and immunoglobulin A as correlates of local protective immunity. These findings warrant further research into mucosal immunization strategies and their translation to clinical application to more effectively prevent the spread of TB.
Keywords: Animals; Tuberculosis; BCG Vaccine; Lung; Interferon-gamma; Macaca mulatta; Immunity, Humoral; Male; Vaccination; Bacterial Load; Dose-Response Relationship, Immunologic; Mucous Membrane

Defining Discriminatory Antibody Fingerprints in Active and Latent Tuberculosis - Nziza, Nadege; Cizmeci, Deniz; Davies, Leela; Irvine, Edward B.; Jung, Wonyeong; Fenderson, Brooke A.; de Kock, Marwou; Hanekom, Willem A.; Franken, Kees L. M. C.; Day, Cheryl L.; Ottenhoff, Tom H. M.; Alter, Galit (Frontiers in Immunology, 2022)
Tuberculosis (TB) is among the leading causes of death worldwide from a single infectious agent, second only to COVID-19 in 2020. TB is caused by infection with Mycobacterium tuberculosis (Mtb), that results either in a latent or active form of disease, the latter associated with Mtb spread. In the absence of an effective vaccine, epidemiologic modeling suggests that aggressive treatment of individuals with active TB (ATB) may curb spread. Yet, clinical discrimination between latent (LTB) and ATB remains a challenge. While antibodies are widely used to diagnose many infections, the utility of antibody-based tests to diagnose ATB has only regained significant traction recently. Specifically, recent interest in the humoral immune response to TB has pointed to potential differences in both targeted antigens and antibody features that can discriminate latent and active TB. Here we aimed to integrate these observations and broadly profile the humoral immune response across individuals with LTB or ATB, with and without HIV co-infection, to define the most discriminatory humoral properties and diagnose TB disease more easily. Using 209 Mtb antigens, striking differences in antigen-recognition were observed across latently and actively infected individuals that was modulated by HIV serostatus. However, ATB and LTB could be discriminated, irrespective of HIV-status, based on a combination of both antibody levels and Fc receptor-binding characteristics targeting both well characterized (like lipoarabinomannan, 38 kDa or antigen 85) but also novel Mtb antigens (including Rv1792, Rv1528, Rv2435C or Rv1508). These data reveal new Mtb-specific immunologic markers that can improve the classification of ATB versus LTB.

Antibody Fc Glycosylation Discriminates Between Latent and Active Tuberculosis - Lu, Lenette L.; Das, Jishnu; Grace, Patricia S.; Fortune, Sarah M.; Restrepo, Blanca I.; Alter, Galit (The Journal of Infectious Diseases, 2020)
BACKGROUND: Mycobacterium tuberculosis remains a global health problem and clinical management is complicated by difficulty in discriminating between latent infection and active disease. While M. tuberculosis-reactive antibody levels are heterogeneous, studies suggest that levels of IgG glycosylation differ between disease states. Here we extend this observation across antibody domains and M. tuberculosis specificities to define changes with the greatest resolving power. METHODS: Capillary electrophoretic glycan analysis was performed on bulk non-antigen-specific IgG, bulk Fc domain, bulk Fab domain, and purified protein derivative (PPD)- and Ag85A-specific IgG from subjects with latent (n = 10) and active (n = 20) tuberculosis. PPD-specific isotype/subclass, PPD-specific antibody-dependent phagocytosis, cellular cytotoxicity, and natural killer cell activation were assessed. Discriminatory potentials of antibody features were evaluated individually and by multivariate analysis. RESULTS: Parallel profiling of whole, Fc, and Fab domain-specific IgG glycosylation pointed to enhanced differential glycosylation on the Fc domain. Differential glycosylation was observed across antigen-specific antibody populations. Multivariate modeling highlighted Fc domain glycan species as the top discriminatory features, with combined PPD IgG titers and Fc domain glycans providing the highest classification accuracy. CONCLUSIONS: Differential glycosylation occurs preferentially on the Fc domain, providing significant discriminatory power between different states of M. tuberculosis infection and disease.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Antigens, Bacterial; Immunoglobulin G; Tuberculosis; tuberculosis; Female; antibodies; Adult; Glycosylation; Immunoglobulin Fc Fragments; Latent Tuberculosis; Male; Middle Aged; Polysaccharides; Adolescent; Aged; Tuberculin; Fc effector function; glycosylation; Acyltransferases; diagnostics; Electrophoresis, Capillary; Immunoglobulin Fab Fragments

Respiratory Immunization With a Whole Cell Inactivated Vaccine Induces Functional Mucosal Immunoglobulins Against Tuberculosis in Mice and Non-human Primates - Aguilo, Nacho; Uranga, Santiago; Mata, Elena; Tarancon, Raquel; Gómez, Ana Belén; Marinova, Dessislava; Otal, Isabel; Monzón, Marta; Badiola, Juan; Montenegro, Dolores; Puentes, Eugenia; Rodríguez, Esteban; et al. (Frontiers in Microbiology, 2020)
Vaccination through the natural route of infection represents an attractive immunization strategy in vaccinology. In the case of tuberculosis, vaccine delivery by the respiratory route has regained interest in recent years, showing efficacy in different animal models. In this context, respiratory vaccination triggers lung immunological mechanisms which are omitted when vaccines are administered by parenteral route. However, contribution of mucosal antibodies to vaccine- induced protection has been poorly studied. In the present study, we evaluated in mice and non-human primates (NHP) a novel whole cell inactivated vaccine (MTBVAC HK), by mucosal administration. MTBVAC HK given by intranasal route to BCG-primed mice substantially improved the protective efficacy conferred by subcutaneous BCG only. Interestingly, this improved protection was absent in mice lacking polymeric Ig receptor (pIgR), suggesting a crucial role of mucosal secretory immunoglobulins in protective immunity. Our study in NHP confirmed the ability of MTBVAC HK to trigger mucosal immunoglobulins. Importantly, in vitro assays demonstrated the functionality of these immunoglobulins to induce M. tuberculosis opsonization in the presence of human macrophages. Altogether, our results suggest that mucosal immunoglobulins can be induced by vaccination to improve protection against tuberculosis and therefore, they represent a promising target for next generation tuberculosis vaccines.

Memory B cells and tuberculosis - Lyashchenko, Konstantin P.; Vordermeier, H. Martin; Waters, W. Ray (Veterinary Immunology and Immunopathology, 2020)
Immunological memory is a central feature of adaptive immunity. Memory B cells are generated upon stimulation with antigen presented by follicular dendritic cells in the peripheral lymphoid tissues. This process typically involves class-switch recombination and somatic hypermutation and it can be dependent or independent on germinal centers or T cell help. The mature B cell memory pool is generally characterized by remarkable heterogeneity of functionally and phenotypically distinct sub-populations supporting multi-layer immune plasticity. Memory B cells found in human patients infected with Mycobacterium tuberculosis include IgD+ CD27+ and IgM+ CD27+ subsets. In addition, expansion of atypical memory B cells characterized by the lack of CD27 expression and by inability to respond to antigen-induced re-activation is documented in human tuberculosis. These functionally impaired memory B cells are believed to have adverse effects on host immunity. Human and animal studies demonstrate recruitment of antigen-activated B cells to the infection sites and their presence in lung granulomas where proliferating B cells are organized into discrete clusters resembling germinal centers of secondary lymphoid organs. Cattle studies show development of IgM+, IgG+, and IgA+ memory B cells in M. bovis infection with the ability to rapidly differentiate into antibody-producing plasma cells upon antigen re-exposure. This review discusses recent advances in research on generation, re-activation, heterogeneity, and immunobiological functions of memory B cells in tuberculosis. The role of memory B cells in post-skin test recall antibody responses in bovine tuberculosis and implications for development of improved immunodiagnostics are also reviewed.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Cattle; Adaptive Immunity; B cells; Immunologic Memory; Lymphocyte Activation; Mycobacterium bovis; Tuberculin; B-Lymphocyte Subsets; Antibody response; Immunological memory

B-Cells and Antibodies as Contributors to Effector Immune Responses in Tuberculosis - Rijnink, Willemijn F.; Ottenhoff, Tom H.M.; Joosten, Simone A. (Frontiers in Immunology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is still a major threat to mankind, urgently requiring improved vaccination and therapeutic strategies to reduce TB-disease burden. Most present vaccination strategies mainly aim to induce cell-mediated immunity (CMI), yet a series of independent studies has shown that B-cells and antibodies (Abs) may contribute significantly to reduce the mycobacterial burden. Although early studies using B-cell knock out animals did not support a major role for B-cells, more recent studies have provided new evidence that B-cells and Abs can contribute significantly to host defense against Mtb. B-cells and Abs exist in many different functional subsets, each equipped with unique functional properties. In this review, we will summarize current evidence on the contribution of B-cells and Abs to immunity toward Mtb, their potential utility as biomarkers, and their functional contribution to Mtb control.

A Mycobacterium tuberculosis Specific IgG3 Signature of Recurrent Tuberculosis - Fischinger, Stephanie; Cizmeci, Deniz; Shin, Sally; Davies, Leela; Grace, Patricia S.; Sivro, Aida; Yende-Zuma, Nonhlanhla; Streeck, Hendrik; Fortune, Sarah M.; Lauffenburger, Douglas A.; Naidoo, Kogieleum; Alter, Galit (Frontiers in Immunology, 2021)
South Africa has the highest prevalence of HIV and tuberculosis (TB) co-infection globally. Recurrent TB, caused by relapse or reinfection, makes up the majority of TB cases in South Africa, and HIV infected individuals have a greater likelihood of developing recurrent TB. Given that TB remains a leading cause of death for HIV infected individuals, and correlates of TB recurrence protection/risk have yet to be defined, here we sought to understand the antibody associated mechanisms of recurrent TB by investigating the humoral response in a longitudinal cohort of HIV co-infected individuals previously treated for TB with and without recurrent disease during follow-up, in order to identify antibody correlates of protection between individuals who do not have recurrent TB and individuals who do. We used a high-throughput, "systems serology" approach to profile biophysical and functional characteristics of antibodies targeting antigens from Mycobacterium tuberculosis (Mtb). Differences in antibody profiles were noted between individuals with and without recurrent TB, albeit these differences were largely observed close to the time of re-diagnosis. Individuals with recurrent TB had decreased Mtb-antigen specific IgG3 titers, but not other IgG subclasses or IgA, compared to control individuals. These data point to a potential role for Mtb-specific IgG3 responses as biomarkers or direct mediators of protective immunity against Mtb recurrence.
Keywords: Antibodies, Bacterial; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Immunoglobulin G; Tuberculosis, Pulmonary; Biomarkers; antibodies; Immunity, Humoral; Time Factors; Predictive Value of Tests; Coinfection; THP-1 Cells; High-Throughput Screening Assays; HIV Infections; IgG3; recurrence; recurrent tuberculosis; Reinfection; Serologic Tests; South Africa

Role of complement activation and antibody in the interaction between Mycobacterium tuberculosis and human macrophages - Manivannan, S.; Rao, Narayan V.; Ramanathan, V. D. (Indian Journal of Experimental Biology, 2012)
Mycobacterium tuberculosis-specific antibodies possess immunomodulatory effects during tuberculosis infection. Prior sensitization to environmental mycobacteria is known to suppress immune responses against BCG and M. tuberculosis. Mycobacteria-induced antibodies can influence events such as complement activation and phagocytosis during infectious process. In the present study role of anti-M. tuberculosis IgG (anti-M. tb IgG) antibody during interaction between M. tuberculosis and human macrophages mediated through complement has been examined in vitro. Anti-M. tb IgG antibody significantly enhanced complement activation by M. tuberculosis. Phagocytosis of M. tuberculosis by macrophages increased significantly in the presence of complement and/or antibody. Moreover, antibody enhanced phagocytosis in the presence of complement. Addition of antibody alone or in combination with complement also augmented intracellular viability of bacilli within macrophages. Results of this study showed that anti-mycobacterial antibody enhances complement activation and anti-M. tb IgG antibody probably modulates effects of complement during early stages of tuberculosis infection.
Keywords: Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Macrophages; Blotting, Western; Electrophoresis, Polyacrylamide Gel; Female; Adult; Male; Middle Aged; Enzyme-Linked Immunosorbent Assay; Complement Activation

The Role of Complement System and the Immune Response to Tuberculosis Infection - Jagatia, Heena; Tsolaki, Anthony G. (Medicina, 2021)
The complement system orchestrates a multi-faceted immune response to the invading pathogen, Mycobacterium tuberculosis. Macrophages engulf the mycobacterial bacilli through bacterial cell surface proteins or secrete proteins, which activate the complement pathway. The classical pathway is activated by C1q, which binds to antibody antigen complexes. While the alternative pathway is constitutively active and regulated by properdin, the direct interaction of properdin is capable of complement activation. The lectin-binding pathway is activated in response to bacterial cell surface carbohydrates such as mannose, fucose, and N-acetyl-d-glucosamine. All three pathways contribute to mounting an immune response for the clearance of mycobacteria. However, the bacilli can reside, persist, and evade clearance by the immune system once inside the macrophages using a number of mechanisms. The immune system can compartmentalise the infection into a granulomatous structure, which contains heterogenous sub-populations of M. tuberculosis. The granuloma consists of many types of immune cells, which aim to clear and contain the infection whilst sacrificing the affected host tissue. The full extent of the involvement of the complement system during infection with M. tuberculosis is not fully understood. Therefore, we reviewed the available literature on M. tuberculosis and other mycobacterial literature to understand the contribution of the complement system during infection.

Complement Protein C3 Binding to Mycobacterium tuberculosis Is Initiated by the Classical Pathway in Human Bronchoalveolar Lavage Fluid - Ferguson, J. Scott; Weis, Jeremy J.; Martin, Jennifer L.; Schlesinger, Larry S. (Infection and Immunity, 2004)
In high concentrations of fresh nonimmune human serum, Mycobacterium tuberculosis activates the alternative pathway of complement and binds C3 protein, resulting in enhanced phagocytosis by complement receptors on human alveolar macrophages. Yet in the lung, the alternative pathway of complement is relatively inactive compared to the classical pathway. To begin to determine whether C3 opsonophagocytosis of M. tuberculosis by alveolar macrophages can occur in the lung of the immunologically naive host, we characterized the binding of C3 to M. tuberculosis in different concentrations of fresh nonimmune human serum and concentrated human bronchoalveolar lavage fluid. Here we show that in human serum, C3 binding to M. tuberculosis is rapid, initiated by either the alternative pathway or the classical pathway, depending on the concentration of serum, and occurs by covalent linkages between the bacterial surface and the C3 cleavage products, C3b or C3bi. Human bronchoalveolar lavage fluid contains C3 protein and functional classical pathway activity that mediates the binding of C3 to the surface of M. tuberculosis. These studies provide evidence that when M. tuberculosis is first inhaled into the lungs of the human host, the bacterium is opsonized by C3 cleavage via classical pathway activation within the alveolus, providing a C3-dependent entry pathway into resident alveolar macrophages.

Multiple routes of complement activation by Mycobacterium bovis BCG - Carroll, Maria V.; Lack, Nathan; Sim, Edith; Krarup, Anders; Sim, Robert B. (Molecular Immunology, 2009)
Mycobacterium tuberculosis is the leading cause of infectious disease in humans in the world. It evades the host immune system by being phagocytosed by macrophages and residing intracellularly. Complement-dependent opsonisation of extracellular mycobacteria may assist them to enter macrophages. This work examines in detail the mechanisms of complement activation by whole mycobacteria using Mycobacterium bovis BCG as a model organism. M. bovis BCG directly activates the classical, lectin and alternative pathways, resulting in fixation of C3b onto macromolecules of the mycobacterial surface. Investigation into the classical pathway has shown direct binding of human C1q to whole mycobacteria in the absence of antibodies. Most human sera contain IgG and IgM-anti-(M. bovis BCG), and pre-incubation with human immunoglobulin enhances C1q binding to the bacteria. Therefore classical pathway activation is both antibody-independent and dependent. The bacteria also activate the alternative pathway in an antibody-independent manner, but Factor H also binds, suggesting some regulation of amplification by this pathway. For the lectin pathway we have demonstrated direct binding of both MBL and L-ficolin from human serum to whole mycobacteria and subsequent MASP2 activation. H-ficolin binding was not observed. No M. bovis BCG cell surface or secreted protease appears likely to influence complement activation. Together, these data provide a more detailed analysis of the mechanisms by which M. bovis BCG interacts with the complement system.
Keywords: Antibodies, Bacterial; Humans; Macrophages; Immunoglobulin G; Mycobacterium bovis; Immunoglobulin M; Complement Activation; Complement C1q; Complement C3b; Complement Factor H; Lectins; Mannose-Binding Lectin; Mannose-Binding Protein-Associated Serine Proteases

Properdin and Factor H: Opposing Players on the Alternative Complement Pathway “See-Saw” - Kouser, Lubna; Abdul-Aziz, Munirah; Nayak, Annapurna; Stover, Cordula; Sim, Robert; Kishore, Uday (Frontiers in Immunology, 2013)
Properdin and factor H are two key regulatory proteins having opposite functions in the alternative complement pathway. Properdin up-regulates the alternative pathway by stabilizing the C3bBb complex, whereas factor H downregulates the pathway by promoting proteolytic degradation of C3b. While factor H is mainly produced in the liver, there are several extrahepatic sources. In addition to the liver, factor H is also synthesized in fetal tubuli, keratinocytes, skin fibroblasts, ocular tissue, adipose tissue, brain, lungs, heart, spleen, pancreas, kidney, muscle, and placenta. Neutrophils are the major source of properdin, and it is also produced by monocytes, T cells and bone marrow progenitor cell line. Properdin is released by neutrophils from intracellular stores following stimulation by N-formyl-methionine-leucine-phenylalanine (fMLP) and tumor necrosis factor alpha (TNF-α). The HEP G2 cells derived from human liver has been found to produce functional properdin. Endothelial cells also produce properdin when induced by shear stress, thus is a physiological source for plasma properdin. The diverse range of extrahepatic sites for synthesis of these two complement regulators suggests the importance and need for local availability of the proteins. Here, we discuss the significance of the local synthesis of properdin and factor H. This assumes greater importance in view of recently identified unexpected and novel roles of properdin and factor H that are potentially independent of their involvement in complement regulation.

The Role of Complement System and the Immune Response to Tuberculosis Infection - Jagatia, Heena; Tsolaki, Anthony G. (Medicina, 2021)
The complement system orchestrates a multi-faceted immune response to the invading pathogen, Mycobacterium tuberculosis. Macrophages engulf the mycobacterial bacilli through bacterial cell surface proteins or secrete proteins, which activate the complement pathway. The classical pathway is activated by C1q, which binds to antibody antigen complexes. While the alternative pathway is constitutively active and regulated by properdin, the direct interaction of properdin is capable of complement activation. The lectin-binding pathway is activated in response to bacterial cell surface carbohydrates such as mannose, fucose, and N-acetyl-d-glucosamine. All three pathways contribute to mounting an immune response for the clearance of mycobacteria. However, the bacilli can reside, persist, and evade clearance by the immune system once inside the macrophages using a number of mechanisms. The immune system can compartmentalise the infection into a granulomatous structure, which contains heterogenous sub-populations of M. tuberculosis. The granuloma consists of many types of immune cells, which aim to clear and contain the infection whilst sacrificing the affected host tissue. The full extent of the involvement of the complement system during infection with M. tuberculosis is not fully understood. Therefore, we reviewed the available literature on M. tuberculosis and other mycobacterial literature to understand the contribution of the complement system during infection.

Complement C3 and Activated Fragment C3a Are Involved in Complement Activation and Anti-Bacterial Immunity - Wu, Meng; Jia, Bei-bei; Li, Mo-fei (Frontiers in Immunology, 2022)
In the complement system, C3 is a central component in complement activation, immune defense and immune regulation. In all pathways of complement activation, the pivotal step is conversion of the component C3 to C3b and C3a, which is responsible to eliminate the pathogen and opsonization. In this study, we examined the immunological properties of C3 and its activated fragment C3a from Japanese flounder (Paralichthys olivaceus) (PoC3 and PoC3a), a teleost species with important economic value. PoC3 is composed of 1655 amino acid residues, contains the six domains and highly conserved GCGEQ sequence of the C3 family. We found that PoC3 expression occurred in nine different tissues and was upregulated by bacterial challenge. In serum, PoC3 was able to bind to a broad-spectrum of bacteria, and purified native PoC3 could directly kill specific pathogen. When PoC3 expression in Japanese flounder was knocked down by siRNA, serum complement activity was significantly decreased, and bacterial replication in fish tissues was significantly increased. Recombinant PoC3a (rPoC3a) exhibited apparent binding capacities to bacteria and Japanese flounder peripheral blood leukocytes (PBL) and induce chemotaxis of PBL. Japanese flounder administered rPoC3a exhibited enhanced resistance against bacterial infection. Taken together, these results indicate that PoC3 is likely a key factor of complement activation, and PoC3 and PoC3a are required for optimal defense against bacterial infection in teleost.

Is the complement activation product C3a a proinflammatory molecule? Re-evaluating the evidence and the myth - Coulthard, Liam G.; Woodruff, Trent M. (Journal of Immunology (Baltimore, Md.: 1950), 2015)
The complement activation product C3a is often described as a proinflammatory mediator, alongside its downstream cousin, C5a. However, emerging studies show that C3a has several anti-inflammatory facets in vivo. For example, in the acute inflammatory response, C3a acts in direct opposition to C5a, through preventing the accumulation of neutrophils in inflamed tissues by independently regulating their mobilization. This acute, protective, and opposing activity of C3a to C5a is also illustrated in models of septicemia. In this article, we reinvestigate the discovery and original classification of C3a as a proinflammatory mediator and highlight the emerging studies demonstrating anti-inflammatory effects for C3a in the immune response. It is our hope that this review illuminates these apparently contradictory roles for C3a and challenges the general dogma surrounding C3a, which, historically, has ubiquitously been described as a proinflammatory mediator. In light of this, we urge investigators to use "inflammatory modulator" as the descriptor for C3a.
Keywords: Humans; Animals; Neutrophils; Inflammation Mediators; Inflammation; Complement C3; Complement C3a; Complement C5a; Neutrophil Infiltration

The complement C3-complement factor D-C3a receptor signalling axis regulates cardiac remodelling in right ventricular failure - Ito, Shogo; Hashimoto, Hisayuki; Yamakawa, Hiroyuki; Kusumoto, Dai; Akiba, Yohei; Nakamura, Takahiro; Momoi, Mizuki; Komuro, Jin; Katsuki, Toshiomi; Kimura, Mai; Kishino, Yoshikazu; Kashimura, Shin; et al. (Nature Communications, 2022)
Failure of the right ventricle plays a critical role in any type of heart failure. However, the mechanism remains unclear, and there is no specific therapy. Here, we show that the right ventricle predominantly expresses alternative complement pathway-related genes, including Cfd and C3aR1. Complement 3 (C3)-knockout attenuates right ventricular dysfunction and fibrosis in a mouse model of right ventricular failure. C3a is produced from C3 by the C3 convertase complex, which includes the essential component complement factor D (Cfd). Cfd-knockout mice also show attenuation of right ventricular failure. Moreover, the plasma concentration of CFD correlates with the severity of right ventricular failure in patients with chronic right ventricular failure. A C3a receptor (C3aR) antagonist dramatically improves right ventricular dysfunction in mice. In summary, we demonstrate the crucial role of the C3-Cfd-C3aR axis in right ventricular failure and highlight potential therapeutic targets for right ventricular failure., Right ventricular (RV) failure is clinically crucial, but there is no specific therapy. Here, the authors show that the complement alternative pathway is activated in RV failure and that blockade of the pathway ameliorates RV failure in mice.

Complement factor H interferes with Mycobacterium bovis BCG entry into macrophages and modulates the pro-inflammatory cytokine response - Abdul-Aziz, Munirah; Tsolaki, Anthony G.; Kouser, Lubna; Carroll, Maria V.; Al-Ahdal, Mohammed N.; Sim, Robert B.; Kishore, Uday (Immunobiology, 2016)
Mycobacterium tuberculosis is an accomplished intracellular pathogen, particularly within the macrophage and this is of the utmost importance in the host-pathogen stand-off observed in the granuloma during latent tuberculosis. Contact with innate immune molecules is one of the primary interactions that can occur with the pathogen M. tuberculosis once inhaled. Complement proteins may play a role in facilitating M. tuberculosis interactions with macrophages. Here, we demonstrate that factor H, a complement regulatory protein that down-regulates complement alternative pathway activation, binds directly to the model organism M. bovis BCG. Binding of factor H reaches saturation at 5-10μg of factor H/ml, well below the plasma level. C4 binding protein (C4BP) competed with factor H for binding to mycobacteria. Factor H was also found to inhibit uptake of M. bovis BCG by THP-1 macrophage cells in a dose-dependent manner. Real-time qPCR analysis showed stark differential responses of pro- and anti-inflammatory cytokines during the early stages of phagocytosis, as evident from elevated levels of TNF-α, IL-1β and IL-6, and a concomitant decrease in IL-10, TGF-β and IL-12 levels, when THP-1:BCG interaction took place in the presence of factor H. Our results suggest that factor H can interfere with mycobacterial entry into macrophages and modulate inflammatory cytokine responses, particularly during the initial stages of infection, thus affecting the extracellular survival of the pathogen. Our results offer novel insights into complement activation-independent functions of factor H during the host-pathogen interaction in tuberculosis.
Keywords: Humans; Cell Line, Tumor; Host-Pathogen Interactions; Macrophages; Tuberculosis; Mycobacterium; Cytokines; Phagocytosis; Mycobacterium bovis; Macrophage; Complement Factor H; Complement; Complement C4b-Binding Protein; Cytokine; Factor H

Defining trained immunity and its role in health and disease - Netea, Mihai G.; Domínguez-Andrés, Jorge; Barreiro, Luis B.; Chavakis, Triantafyllos; Divangahi, Maziar; Fuchs, Elaine; Joosten, Leo A. B.; van der Meer, Jos W. M.; Mhlanga, Musa M.; Mulder, Willem J. M.; Riksen, Niels P.; Schlitzer, Andreas; et al. (Nature Reviews. Immunology, 2020)
Immune memory is a defining feature of the acquired immune system, but activation of the innate immune system can also result in enhanced responsiveness to subsequent triggers. This process has been termed ‘trained immunity’, a de facto innate immune memory. Research in the past decade has pointed to the broad benefits of trained immunity for host defence but has also suggested potentially detrimental outcomes in immune-mediated and chronic inflammatory diseases. Here we define ‘trained immunity’ as a biological process and discuss the innate stimuli and the epigenetic and metabolic reprogramming events that shape the induction of trained immunity., Here a group of leaders in the field define our current understanding of ‘trained immunity’, which refers to the memory-type responses that occur in the innate immune system. The authors discuss our current understanding of the key epigenetic and metabolic processes involved in trained immunity and consider its relevance in immune-mediated diseases and cancer.

BCG Educates Hematopoietic Stem Cells to Generate Protective Innate Immunity against Tuberculosis - Kaufmann, Eva; Sanz, Joaquin; Dunn, Jonathan L.; Khan, Nargis; Mendonça, Laura E.; Pacis, Alain; Tzelepis, Fanny; Pernet, Erwan; Dumaine, Anne; Grenier, Jean-Christophe; Mailhot-Léonard, Florence; Ahmed, Eisha; et al. (Cell, 2018)
The dogma that adaptive immunity is the only arm of the immune response with memory capacity has been recently challenged by several studies demonstrating evidence for memory-like innate immune training. However, the underlying mechanisms and location for generating such innate memory responses in vivo remain unknown. Here, we show that access of Bacillus Calmette-Guérin (BCG) to the bone marrow (BM) changes the transcriptional landscape of hematopoietic stem cells (HSCs) and multipotent progenitors (MPPs), leading to local cell expansion and enhanced myelopoiesis at the expense of lymphopoiesis. Importantly, BCG-educated HSCs generate epigenetically modified macrophages that provide significantly better protection against virulent M. tuberculosis infection than naïve macrophages. By using parabiotic and chimeric mice, as well as adoptive transfer approaches, we demonstrate that training of the monocyte/macrophage lineage via BCG-induced HSC reprogramming is sustainable in vivo. Our results indicate that targeting the HSC compartment provides a novel approach for vaccine development.
Keywords: Cell Line; Animals; Tuberculosis; Cells, Cultured; Mice; Immunity, Innate; Mice, Inbred C57BL; Immunologic Memory; Mycobacterium bovis; BCG; epigenetic reprogramming; mycobacterium tuberculosis; trained immunity; Hematopoietic Stem Cells; Transcriptome; macrophages; Epigenesis, Genetic; Hematopoiesis; stem cells

M. tuberculosis Reprograms Hematopoietic Stem Cells to Limit Myelopoiesis and Impair Trained Immunity - Khan, Nargis; Downey, Jeffrey; Sanz, Joaquin; Kaufmann, Eva; Blankenhaus, Birte; Pacis, Alain; Pernet, Erwan; Ahmed, Eisha; Cardoso, Silvia; Nijnik, Anastasia; Mazer, Bruce; Sassetti, Christopher; et al. (Cell, 2020)
A greater understanding of hematopoietic stem cell (HSC) regulation is required for dissecting protective versus detrimental immunity to pathogens that cause chronic infections such as Mycobacterium tuberculosis (Mtb). We have shown that systemic administration of Bacille Calmette-Guérin (BCG) or β-glucan reprograms HSCs in the bone marrow (BM) via a type II interferon (IFN-II) or interleukin-1 (IL1) response, respectively, which confers protective trained immunity against Mtb. Here, we demonstrate that, unlike BCG or β-glucan, Mtb reprograms HSCs via an IFN-I response that suppresses myelopoiesis and impairs development of protective trained immunity to Mtb. Mechanistically, IFN-I signaling dysregulates iron metabolism, depolarizes mitochondrial membrane potential, and induces cell death specifically in myeloid progenitors. Additionally, activation of the IFN-I/iron axis in HSCs impairs trained immunity to Mtb infection. These results identify an unanticipated immune evasion strategy of Mtb in the BM that controls the magnitude and intrinsic anti-microbial capacity of innate immunity to infection.
Keywords: Kinetics; Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis; Transcription, Genetic; Necrosis; Lung; Mice, Inbred C57BL; Myeloid Cells; Signal Transduction; BCG; Immunity; trained immunity; Hematopoietic Stem Cells; Interferon Type I; macrophages; Homeostasis; Cell Proliferation; hematopoietic stem cells; necroptosis; Disease Susceptibility; Bone Marrow Cells; Iron; iron metabolism; monocytes; myelopoiesis; Myelopoiesis; type I IFN

Modulation of Myelopoiesis Progenitors Is an Integral Component of Trained Immunity - Mitroulis, Ioannis; Ruppova, Klara; Wang, Baomei; Chen, Lan-Sun; Grzybek, Michal; Grinenko, Tatyana; Eugster, Anne; Troullinaki, Maria; Palladini, Alessandra; Kourtzelis, Ioannis; Chatzigeorgiou, Antonios; Schlitzer, Andreas; et al. (Cell, 2018)
Trained innate immunity fosters a sustained favorable response of myeloid cells to a secondary challenge, despite their short lifespan in circulation. We thus hypothesized that trained immunity acts via modulation of hematopoietic stem and progenitor cells (HSPCs). Administration of β-glucan (prototypical trained-immunity-inducing agonist) to mice induced expansion of progenitors of the myeloid lineage, which was associated with elevated signaling by innate immune mediators, such as IL-1β and granulocyte-macrophage colony-stimulating factor (GM-CSF), and with adaptations in glucose metabolism and cholesterol biosynthesis. The trained-immunity-related increase in myelopoiesis resulted in a beneficial response to secondary LPS challenge and protection from chemotherapy-induced myelosuppression in mice. Therefore, modulation of myeloid progenitors in the bone marrow is an integral component of trained immunity, which to date, was considered to involve functional changes of mature myeloid cells in the periphery.
Keywords: Animals; Cells, Cultured; Mice; Immunity, Innate; Mice, Inbred C57BL; Male; Immunologic Memory; Granulocyte-Macrophage Colony-Stimulating Factor; inflammation; Interleukin-1beta; glycolysis; myelopoiesis; Myelopoiesis; beta-Glucans; cholesterol biosynthesis; GM-CSF; innate immune memory; interleukin-1β; Myeloid Progenitor Cells; myelosuppression; trained innate immunity; β-glucan

Mycobacterial growth inhibition is associated with trained innate immunity - Joosten, Simone A.; van Meijgaarden, Krista E.; Arend, Sandra M.; Prins, Corine; Oftung, Fredrik; Korsvold, Gro Ellen; Kik, Sandra V.; Arts, Rob J.W.; van Crevel, Reinout; Netea, Mihai G.; Ottenhoff, Tom H.M. (The Journal of Clinical Investigation)
The lack of defined correlates of protection hampers development of vaccines against tuberculosis (TB). In vitro mycobacterial outgrowth assays are thought to better capture the complexity of the human host/Mycobacterium tuberculosis (Mtb) interaction. Here, we used a mycobacterial growth inhibition assay (MGIA) based on peripheral blood mononuclear cells to investigate the capacity to control outgrowth of bacille Calmette-Guérin (BCG). Interestingly, strong control of BCG outgrowth was observed almost exclusively in individuals with recent exposure to Mtb, but not in (long-term) latent TB infection, and only modestly in BCG vaccinees. Mechanistically, control of mycobacterial outgrowth strongly correlated with the presence of a CD14dim monocyte population, but also required the presence of T cells. The nonclassical monocytes produced CXCL10, and CXCR3 receptor blockade inhibited the capacity to control BCG outgrowth. Expression of CXCR3 splice variants was altered in recently Mtb-exposed individuals. Cytokines previously associated with trained immunity were detected in MGIA supernatants, and CXCL9, CXCL10, and CXCL11 represent new markers of trained immunity. These data indicate that CXCR3 ligands are associated with trained immunity and are critical factors in controlling mycobacterial outgrowth. In conclusion, control of mycobacterial outgrowth early after exposure to Mtb is the result of trained immunity mediated by a CXCL10-producing nonclassical CD14dim monocyte subset.

β-Glucan Induces Protective Trained Immunity against Mycobacterium tuberculosis Infection: A Key Role for IL-1 - Moorlag, Simone J. C. F. M.; Khan, Nargis; Novakovic, Boris; Kaufmann, Eva; Jansen, Trees; van Crevel, Reinout; Divangahi, Maziar; Netea, Mihai G. (Cell Reports, 2020)
β-glucan is a potent inducer of epigenetic and functional reprogramming of innate immune cells, a process called "trained immunity," resulting in an enhanced host response against secondary infections. We investigate whether β-glucan exposure confers protection against pulmonary Mycobacterium tuberculosis (Mtb) infection. β-glucan induces trained immunity via histone modifications at gene promoters in human monocytes, which is accompanied by the enhanced production of proinflammatory cytokines upon secondary Mtb challenge and inhibition of Mtb growth. Mice treated with β-glucan are significantly protected against pulmonary Mtb infection, which is associated with the expansion of hematopoietic stem and progenitor cells in the bone marrow and increased myelopoiesis. The protective signature of β-glucan is mediated via IL-1 signaling, as β-glucan shows no protection in mice lacking a functional IL-1 receptor (IL1R-/-). The administration of β-glucan may be used as a novel strategy in the treatment of mycobacterial infections and possibly as an adjuvant to improve anti-tuberculosis vaccines.
Keywords: Humans; Mycobacterium tuberculosis; Animals; tuberculosis; Mice; Signal Transduction; Immunity; trained immunity; epigenetics; monocytes; beta-Glucans; innate immune memory; β-glucan; IL-1; Interleukin-1

Trained innate immunity and resistance to Mycobacterium tuberculosis infection - Koeken, V. a. C. M.; Verrall, A. J.; Netea, M. G.; Hill, P. C.; Crevel, R. van (Clinical Microbiology and Infection, 2019)
Keywords: Tuberculosis; Bacillus Calmette–Guérin; Early clearance; Infection; Trained immunity

Key recent advances in TB vaccine development and understanding of protective immune responses against Mycobacterium tuberculosis - Scriba, Thomas J.; Netea, Mihai G.; Ginsberg, Ann M. (Seminars in Immunology, 2020)
Tuberculosis is the leading infectious disease killer globally due to a single pathogen. Despite wide deployment of standard drug regimens, modern diagnostics and a vaccine (bacille Calmette Guerin, BCG), the global tuberculosis epidemic is inadequately controlled. Novel, effective vaccine(s) are a crucial element of the World Health Organization End TB Strategy. TB vaccine research and development has recently been catalysed by several factors, including a revised strategy focused first on preventing pulmonary TB in adolescents and adults who are the main source of transmission, and encouraging evaluations of novel efficacy endpoints. Renewed enthusiasm for TB vaccine research has also been stimulated by recent preclinical and clinical advancements. These include new insights into underlying protective immune responses, including potential roles for ‘trained’ innate immunity and Th1/Th17 CD4+ (and CD8+) T cells. The field has been further reinvigorated by two positive proof of concept efficacy trials: one evaluating a potential new use of BCG in preventing high risk populations from sustained Mycobacterium tuberculosis infection and the second evaluating a novel, adjuvanted, recombinant protein vaccine candidate (M72/AS01E) for prevention of disease in adults already infected. Fourteen additional candidates are currently in various phases of clinical evaluation and multiple approaches to next generation vaccines are in discovery and preclinical development. The two positive efficacy trials and recent studies in nonhuman primates have enabled the first opportunities to discover candidate vaccine-induced correlates of protection, an effort being undertaken by a broad research consortium.
Keywords: Adaptive immunity; Correlates of protection; Innate training; Tuberculosis (TB); Vaccine(s)

BCG Vaccination Induces Long-Term Functional Reprogramming of Human Neutrophils - Moorlag, Simone J. C. F. M.; Rodriguez-Rosales, Yessica Alina; Gillard, Joshua; Fanucchi, Stephanie; Theunissen, Kate; Novakovic, Boris; de Bont, Cynthia M.; Negishi, Yutaka; Fok, Ezio T.; Kalafati, Lydia; Verginis, Panayotis; Mourits, Vera P.; et al. (Cell Reports, 2020)
The tuberculosis vaccine bacillus Calmette-Guérin (BCG) protects against some heterologous infections, probably via induction of non-specific innate immune memory in monocytes and natural killer (NK) cells, a process known as trained immunity. Recent studies have revealed that the induction of trained immunity is associated with a bias toward granulopoiesis in bone marrow hematopoietic progenitor cells, but it is unknown whether BCG vaccination also leads to functional reprogramming of mature neutrophils. Here, we show that BCG vaccination of healthy humans induces long-lasting changes in neutrophil phenotype, characterized by increased expression of activation markers and antimicrobial function. The enhanced function of human neutrophils persists for at least 3 months after vaccination and is associated with genome-wide epigenetic modifications in trimethylation at histone 3 lysine 4. Functional reprogramming of neutrophils by the induction of trained immunity might offer novel therapeutic strategies in clinical conditions that could benefit from modulation of neutrophil effector function.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Monocytes; BCG Vaccine; Neutrophils; Female; Adaptive Immunity; Immunity, Innate; Adult; Male; Middle Aged; Aged; Vaccination; BCG; polymorphonuclear leukocytes; trained immunity; Killer Cells, Natural; epigenetics; innate immune memory; Cellular Reprogramming; neutrophil; nonspecific effects of vaccines

Resistance to Mycobacterium tuberculosis infection among highly TB exposed South African gold miners - Chihota, Violet N.; Ntshiqa, Thobani; Maenetje, Pholo; Mansukhani, Raoul; Velen, Kavindhran; Hawn, Thomas R.; Wallis, Robert; Grant, Alison D.; Churchyard, Gavin J.; Fielding, Katherine (PLOS ONE, 2022)
Background Despite high exposure to Mycobacterium tuberculosis, a small proportion of South African goldminers resist TB infection. We determined, among long-service gold miners i) the proportion who were TB uninfected and ii) epidemiological factors associated with being uninfected. Methods We enrolled HIV-negative gold miners aged 33–60 years with ≥15 years’ service and no history of TB or silicosis. Miners were defined as TB uninfected if i) QuantiFERON-TB Gold Plus (QFT-Plus) negative or ii) in a stricter definition, QFT-Plus-negative and zero-response on TST and as resisters if they were of Black/African ethnicity and negative on both tests. Logistic regression was used to identify epidemiological factors associated with being TB uninfected. Results Of 307 participants with a QFT-Plus result, median age was 48 years (interquartile range [IQR] 44–53), median time working underground was 24 years (IQR 18–28), 303 (99%) were male and 91 (30%) were QFT-Plus-negative. The odds of being TB uninfected was 52% lower for unskilled workers (adjusted odds ratio [aOR] 0.48; 95% confidence interval [CI] 0.27–0.85; p = 0.013). Among 281 participants of Black/African ethnicity, 71 (25%) were QFT-Plus negative. Miners with a BMI ≥30 were less likely to be TB uninfected (OR 0.38; 95% CI 0.18–0.80). Using the stricter definition, 44.3% (136/307) of all miners were classified as either TB uninfected (35; 26%) or infected, (101; 74%) and the associations remained similar. Among Black/African miners; 123 were classified as either TB uninfected (23; 19%) or infected (100; 81%) using the stricter definition. No epidemiological factors for being TB uninfected were identified. Conclusions Despite high cumulative exposure, a small proportion of miners appear to be resistant to TB infection and are without distinguishing epidemiological characteristics.
Keywords: Mycobacterium tuberculosis; Tuberculosis; Tuberculin; HIV; South Africa; Epidemiology; Ethnic epidemiology; Medical risk factors

Is Mycobacterium tuberculosis infection life long? | The BMJ

Is Mycobacterium tuberculosis infection life long? - Behr, Marcel A.; Edelstein, Paul H.; Ramakrishnan, Lalita (BMJ, 2019)
People with immunoreactivity to tuberculosis are thought to have lifelong asymptomatic infection and remain at risk for active tuberculosis. Marcel A Behr and colleagues argue that most of these people are no longer infected

Early Clearance of Mycobacterium tuberculosis Is Associated With Increased Innate Immune Responses - Verrall, Ayesha J.; Schneider, Marion; Alisjahbana, Bachti; Apriani, Lika; van Laarhoven, Arjan; Koeken, Valerie A. C. M.; van Dorp, Suszanne; Diadani, Emira; Utama, Fitri; Hannaway, Rachel F.; Indrati, Agnes; Netea, Mihai G.; et al. (The Journal of Infectious Diseases, 2020)
BACKGROUND: A proportion of tuberculosis (TB) case contacts do not become infected, even when heavily exposed. We studied the innate immune responses of TB case contacts to understand their role in protection against infection with Mycobacterium tuberculosis, termed "early clearance." METHODS: Indonesian household contacts of TB cases were tested for interferon-γ release assay (IGRA) conversion between baseline and 14 weeks post recruitment. Blood cell populations and ex vivo innate whole blood cytokine responses were measured at baseline and, in a subgroup, flow cytometry was performed at weeks 2 and 14. Immunological characteristics were measured for early clearers, defined as a persistently negative IGRA at 3 months, and converters, whose IGRA converted from negative to positive. RESULTS: Among 1347 case contacts, 317 were early clearers and 116 were converters. Flow cytometry showed a resolving innate cellular response from 2 to 14 weeks in persistently IGRA-negative contacts but not converters. There were no differences in cytokine responses to mycobacterial stimuli, but compared to converters, persistently IGRA-negative contacts produced more proinflammatory cytokines following heterologous stimulation with Escherichia coli and Streptococcus pneumoniae. CONCLUSIONS: Early clearance of M. tuberculosis is associated with enhanced heterologous innate immune responses similar to those activated during induction of trained immunity.
Keywords: Humans; Mycobacterium tuberculosis; Tuberculosis; Mycobacterium; Flow Cytometry; Female; Immunity, Innate; Adult; Male; Middle Aged; Interferon-gamma Release Tests; monocytes; trained innate immunity; BCG vaccine; Diagnostic Tests, Routine; early clearance; Indonesia; tuberculosis infection

Plasma metabolome predicts trained immunity responses after antituberculosis BCG vaccination - Koeken, Valerie A. C. M.; Qi, Cancan; Mourits, Vera P.; Bree, L. Charlotte J. de; Moorlag, Simone J. C. F. M.; Sonawane, Vidhisha; Lemmers, Heidi; Dijkstra, Helga; Joosten, Leo A. B.; Laarhoven, Arjan van; Xu, Cheng-Jian; Crevel, Reinout van; et al. (PLOS Biology, 2022)
The antituberculosis vaccine Bacillus Calmette–Guérin (BCG) induces nonspecific protection against heterologous infections, at least partly through induction of innate immune memory (trained immunity). The amplitude of the response to BCG is variable, but the factors that influence this response are poorly understood. Metabolites, either released by cells or absorbed from the gut, are known to influence immune responses, but whether they impact BCG responses is not known. We vaccinated 325 healthy individuals with BCG, and collected blood before, 2 weeks and 3 months after vaccination, to assess the influence of circulating metabolites on the immune responses induced by BCG. Circulating metabolite concentrations after BCG vaccination were found to have a more pronounced impact on trained immunity responses, such as the increase in IL-1β and TNF-α production upon Staphylococcus aureus stimulation, than on specific adaptive immune memory, assessed as IFN-γ production in response to Mycobacterium tuberculosis. Circulating metabolites at baseline were able to predict trained immunity responses at 3 months after vaccination and enrichment analysis based on the metabolites positively associated with trained immunity revealed enrichment of the tricarboxylic acid (TCA) cycle and glutamine metabolism, both of which were previously found to be important for trained immunity. Several new metabolic pathways that influence trained immunity were identified, among which taurine metabolism associated with BCG-induced trained immunity, a finding validated in functional experiments. In conclusion, circulating metabolites are important factors influencing BCG-induced trained immunity in humans. Modulation of metabolic pathways may be a novel strategy to improve vaccine and trained immunity responses.
Keywords: Cytokines; Immunity; Immune response; Cell-mediated immunity; Metabolic pathways; Metabolites; Metabolomics; Vaccination and immunization

Biosynthesis and export of bacterial lipopolysaccharides - Whitfield, Chris; Trent, M. Stephen (Annual Review of Biochemistry, 2014)
Lipopolysaccharide molecules represent a unique family of glycolipids based on a highly conserved lipid moiety known as lipid A. These molecules are produced by most gram-negative bacteria, in which they play important roles in the integrity of the outer-membrane permeability barrier and participate extensively in host-pathogen interplay. Few bacteria contain lipopolysaccharide molecules composed only of lipid A. In most forms, lipid A is glycosylated by addition of the core oligosaccharide that, in some bacteria, provides an attachment site for a long-chain O-antigenic polysaccharide. The complexity of lipopolysaccharide structures is reflected in the processes used for their biosynthesis and export. Rapid growth and cell division depend on the bacterial cell's capacity to synthesize and export lipopolysaccharide efficiently and in large amounts. We review recent advances in those processes, emphasizing the reactions that are essential for viability.
Keywords: Bacterial Proteins; Cell Membrane; Glycosylation; Polysaccharides; Lipopolysaccharides; Bacteria; Glycolipids; Gram-Negative Bacteria; Biological Transport; Bacterial Physiological Phenomena; Adenosine Triphosphate; biosynthesis; endotoxin; gram-negative bacteria; lipid A; macromolecular trafficking; O Antigens; outer membranes; Permeability

Dynamic modulation of innate immune response by varying dosages of lipopolysaccharide (LPS) in human monocytic cells - Morris, Matthew C.; Gilliam, Elizabeth A.; Button, Julia; Li, Liwu (The Journal of Biological Chemistry, 2014)
Innate monocytes and macrophages can be dynamically programmed into distinct states depending upon the strength of external stimuli. Innate programming may bear significant relevance to the pathogenesis and resolution of human inflammatory diseases. However, systems analyses with regard to the dynamic programming of innate leukocytes are lacking. In this study, we focused on the dynamic responses of human promonocytic THP-1 cells to lipopolysaccharide (LPS). We observed that varying dosages of LPS differentially modulate the expression of selected pro- and anti- inflammatory mediators such as IL-6 and IL-33. Super-low dosages of LPS preferentially induced the pro-inflammatory mediator IL-6, while higher dosages of LPS induced both IL-6 and IL-33. Mechanistically, we demonstrated that super-low and high doses of LPS cause differential activation of GSK3 and Akt, as well as the transcription factors FoxO1 and CREB. Inhibition of GSK3 enabled THP-1 cells to express IL-33 when challenged with super-low dose LPS. On the other hand, activation of CREB with adenosine suppressed IL-6 expression. Taken together, our study reveals a dynamic modulation of monocytic cells in response to varying dosages of endotoxin, and may shed light on our understanding of the dynamic balance that controls pathogenesis and resolution of inflammatory diseases.
Keywords: Base Sequence; Cell Line; Humans; Monocytes; Dose-Response Relationship, Drug; Immunity, Innate; Gene Expression Regulation; Inflammation Mediators; Lipopolysaccharides; Real-Time Polymerase Chain Reaction; inflammation; DNA Primers; Innate Immunity; Lipopolysaccharide (LPS); Monocyte; Systems Biology

Innate immune memory: Implications for host responses to damage-associated molecular patterns - Crișan, Tania O.; Netea, Mihai G.; Joosten, Leo A. B. (European Journal of Immunology, 2016)
Cells of the innate immune system build immunological memory via epigenetic reprogramming after stimulations with microbial ligands. This functional readjustment allows for enhanced nonspecific inflammatory responses upon secondary challenges, a process termed "trained immunity." The epigenomic blueprint of trained monocytes has been recently reported, which revealed several important immunologic and metabolic mechanisms that underlie these changes. Interestingly, similar long-term reprogramming of cytokine production has also been described to be induced by endogenous damage-associated molecular patterns (DAMPs). Here, we present an overview of the novel data showing that endogenous alarm signals associated with tissue damage and sterile inflammation can induce trained immunity through epigenetic regulation of transcriptional programs. We describe new and old evidence of persistent effects of DAMPs in driving inflammation and enforce the concept that the influence of tissue-derived signals is critical in adjusting the magnitude and type of immune response built by the host. The better characterization of trained immunity for the persistence of inflammation induced by DAMPs would provide new possibilities for intervention in aging and autoinflammatory disorders.
Keywords: Humans; Cytokines; Immunity, Innate; Immunologic Memory; Signal Transduction; Inflammation; Damage-associated molecular patterns ⋅ Epigenetics ⋅ Innate immune memory ⋅Trained immunity; Receptors, Pattern Recognition

Early clearance of Mycobacterium tuberculosis: a new frontier in prevention - Verrall, Ayesha J.; Netea, Mihai G.; Alisjahbana, Bachti; Hill, Philip C.; van Crevel, Reimout (Immunology, 2014)
Early clearance (EC) is the successful eradication of inhaled Mycobacterium tuberculosis before an adaptive immune response develops. Evidence for EC comes from case contact studies that consistently show that a proportion of heavily exposed individuals do not develop M. tuberculosis infection. Further support for the existence of this phenotype comes from genetic loci associated with tuberculin reactivity. In this review we discuss aspects of the innate response that may underpin EC and hypotheses that can be tested through field laboratory link studies in M. tuberculosis case contacts. Specifically, we consider mechanisms whereby alveolar macrophages recognize and kill intracellular M. tuberculosis, and how other cell types, such as neutrophils, natural killer T cells, mucosa-associated invariant T cells and cd T cells may assist. How EC may be impaired by HIV infection or vitamin D deficiency is also explored. As EC is a form of protective immunity, further study may advance the development of vaccines and immunotherapies to prevent M. tuberculosis infection.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis Vaccines; Tuberculosis; Cytokines; Immunity, Innate; T-Lymphocyte Subsets; Microbial Viability; Phagocytosis; Phenotype; Bacterial Load; Macrophages, Alveolar; Coinfection; HIV Infections; Vitamin D Deficiency

Innate immune memory: Implications for host responses to damage-associated molecular patterns - Crișan, Tania O.; Netea, Mihai G.; Joosten, Leo A. B. (European Journal of Immunology, 2016)
Cells of the innate immune system build immunological memory via epigenetic reprogramming after stimulations with microbial ligands. This functional readjustment allows for enhanced nonspecific inflammatory responses upon secondary challenges, a process termed "trained immunity." The epigenomic blueprint of trained monocytes has been recently reported, which revealed several important immunologic and metabolic mechanisms that underlie these changes. Interestingly, similar long-term reprogramming of cytokine production has also been described to be induced by endogenous damage-associated molecular patterns (DAMPs). Here, we present an overview of the novel data showing that endogenous alarm signals associated with tissue damage and sterile inflammation can induce trained immunity through epigenetic regulation of transcriptional programs. We describe new and old evidence of persistent effects of DAMPs in driving inflammation and enforce the concept that the influence of tissue-derived signals is critical in adjusting the magnitude and type of immune response built by the host. The better characterization of trained immunity for the persistence of inflammation induced by DAMPs would provide new possibilities for intervention in aging and autoinflammatory disorders.
Keywords: Humans; Cytokines; Immunity, Innate; Immunologic Memory; Signal Transduction; Inflammation; Damage-associated molecular patterns ⋅ Epigenetics ⋅ Innate immune memory ⋅Trained immunity; Receptors, Pattern Recognition

TLR4-NOX2 axis regulates the phagocytosis and killing of Mycobacterium tuberculosis by macrophages - Lv, Jingzhu; He, Xiaoyan; Wang, Hongtao; Wang, Zhaohua; Kelly, Gabriel T.; Wang, Xiaojing; Chen, Yin; Wang, Ting; Qian, Zhongqing (BMC pulmonary medicine, 2017)
BACKGROUND: Macrophages stand at the forefront of both innate and adapted immunity through their capacities to recognize, engulf, and eliminate foreign particles, and to stimulate adapted immune cells. They are also involved in controlling pro- and anti-inflammatory pathways. Macrophage activity against Mycobacterium tuberculosis (M. tuberculosis) has been shown to involve Toll-like receptor (TLR) activation and ROS production. Previous studies have shown that lipopolysaccharide (LPS), through TLR4, could activate macrophages, improve their bactericidal ROS production, and facilitate anti-infective immune responses. We sought to better understand the role of the TLR4-NOX2 axis in macrophage activation during M. tuberculosis infection. METHODS: THP-1 macrophages and PMA primed THP-1 macrophages [THP-1(A)] were treated with LPS and infected by M. tuberculosis. Cells were analyzed by flow cytometry for TLR4 expression, ROS production, phagocytosis, and killing of M. tuberculosis. Western blotting was used to analyze NOX2 expression. Inhibitors of the TLR4-NOX2 pathway were used to assess this pathway's role in these processes, and their role in LPS activation of macrophages. RESULTS: We found that THP1-derived macrophages or PMA primed THP-1 macrophages exhibit higher surface TLR4 levels and increased NOX2 expression levels following LPS treatment. M. tuberculosis infection reduced these levels, but LPS was able to limit the negative effects of M.tb. Additionally, LPS increases THP-1(A) cells' bactericidal activities including phagocytosis, ROS production, and destruction of M. tuberculosis. Significantly, all of these activities are impaired when TLR4 or NOX2 are inhibited. CONCLUSION: These studies demonstrate the importance of the TLR4-NOX2 axis in M. tuberculosis elimination by macrophages and may lead to novel therapies for tuberculosis and other bacterial infections.
Keywords: Cell Line; Humans; Animals; Macrophages; Tuberculosis; Signal Transduction; Phagocytosis; Lipopolysaccharides; TB; Tumor Necrosis Factor-alpha; Toll-Like Receptor 2; NADPH Oxidase 2; NOX2; TLR; Toll-Like Receptor 4

Intracellular signalling cascades regulating innate immune responses to Mycobacteria: branching out from Toll-like receptors - Jo, Eun-Kyeong; Yang, Chul-Su; Choi, Chul Hee; Harding, Clifford V. (Cellular Microbiology, 2007)
Toll-like receptors (TLRs) recognize Mycobacterium tuberculosis (Mtb) or Mtb components and initiate mononuclear phagocyte responses that influence both innate and adaptive immunity. Recent studies have revealed the intracellular signalling cascades involved in the TLR-initiated immune response to mycobacterial infection. Although both TLR2 and TLR4 have been implicated in host interactions with Mtb, the relationship between specific mycobacterial molecules and various signal transduction pathways is not well understood. This review will discuss recent studies indicating critical roles for mycobacteria and mycobacterial components in regulation of mitogen-activated protein kinases and related signal transduction pathways that govern the outcome of infection and antibacterial defence. To better understand the roles of infection-induced signalling cascades in molecular pathogenesis, future studies are needed to clarify mechanisms that integrate the multiple signalling pathways that are activated by engagement of TLRs by both individual mycobacterial molecules and whole mycobacteria. These efforts will allow for the development of novel diagnostic and therapeutic modalities for tuberculosis that targets the intracellular signalling pathways permitting the replication of this nefarious pathogen.
Keywords: Humans; Animals; Mycobacterium; Signal Transduction; Models, Biological; Toll-Like Receptors; Mycobacterium Infections; Mitogen-Activated Protein Kinases

Tuberculosis extrapulmonar, una revisión - Ramírez-Lapausa, M.; Menéndez-Saldaña, A.; Noguerado-Asensio, A. (Revista Española de Sanidad Penitenciaria, 2015)

Spinal tuberculosis: a review - Garg, Ravindra Kumar; Somvanshi, Dilip Singh (The Journal of Spinal Cord Medicine, 2011)
Spinal tuberculosis is a destructive form of tuberculosis. It accounts for approximately half of all cases of musculoskeletal tuberculosis. Spinal tuberculosis is more common in children and young adults. The incidence of spinal tuberculosis is increasing in developed nations. Genetic susceptibility to spinal tuberculosis has recently been demonstrated. Characteristically, there is destruction of the intervertebral disk space and the adjacent vertebral bodies, collapse of the spinal elements, and anterior wedging leading to kyphosis and gibbus formation. The thoracic region of vertebral column is most frequently affected. Formation of a 'cold' abscess around the lesion is another characteristic feature. The incidence of multi-level noncontiguous vertebral tuberculosis occurs more frequently than previously recognized. Common clinical manifestations include constitutional symptoms, back pain, spinal tenderness, paraplegia, and spinal deformities. For the diagnosis of spinal tuberculosis magnetic resonance imaging is more sensitive imaging technique than x-ray and more specific than computed tomography. Magnetic resonance imaging frequently demonstrates involvement of the vertebral bodies on either side of the disk, disk destruction, cold abscess, vertebral collapse, and presence of vertebral column deformities. Neuroimaging-guided needle biopsy from the affected site in the center of the vertebral body is the gold standard technique for early histopathological diagnosis. Antituberculous treatment remains the cornerstone of treatment. Surgery may be required in selected cases, e.g. large abscess formation, severe kyphosis, an evolving neurological deficit, or lack of response to medical treatment. With early diagnosis and early treatment, prognosis is generally good.
Keywords: Humans; Tomography, X-Ray Computed; Diagnosis, Differential; Magnetic Resonance Imaging; Tuberculosis, Spinal

Tuberculous meningitis: Diagnostic and therapeutic challenges - Chin, Jerome H. (Neurology. Clinical Practice, 2014)
Neurologists are often the first medical providers to evaluate patients with possible infectious meningitis. Knowledge of the clinical presentations and cerebrospinal fluid, microbiologic, and neuroimaging findings for different etiologies is essential to make a prompt diagnosis and initiate appropriate treatment. Tuberculosis is a common cause of meningitis in developing countries with a high prevalence of pulmonary tuberculosis. However, tuberculosis affects populations in every country and all neurologists need to be vigilant for possible cases of tuberculous meningitis presenting to their medical facilities. This article discusses the challenges of diagnosing and treating tuberculous meningitis and highlights recent advances in diagnostic technology.

Tuberculosis of the central nervous system - Garg, R. K. (Postgraduate Medical Journal, 1999)
Tuberculous involvement of the brain and spinal cord are common neurological disorders in developing countries and have recently shown a resurgence in developed ones. Tuberculous meningitis is an important manifestation and is associated with high morbidity and mortality. Diagnosis is based on clinical features, cerebrospinal fluid changes, and imaging characteristics. Bacteriological confirmation is not possible in all cases as serological tests do not have sufficient sensitivity and specificity. The polymerase chain reaction shows promise for the future. Appropriate chemotherapeutic agents should be administered as early as possible, although there is no unanimity concerning chemotherapeutic regimens or optimal duration of treatment. The patient's clinical stage at presentation is the most important prognostic factor. The role of corticosteroids is controversial but they should be administered to all patients presenting in stage III. Surgical procedures are directed at management of the hydrocephalus. Focal lesions, intracranial tuberculomas, and tuberculous abscesses, are usually located in cerebral or cerebellar hemispheres, uncommonly in brainstem and very rarely in spinal cord. They do not usually require surgical intervention and respond well to antituberculous treatment, along with corticosteroids.
Keywords: Humans; Tuberculosis; Tomography, X-Ray Computed; Central Nervous System Infections

Tuberculosis of the central nervous system - Garg, R. K. (Postgraduate Medical Journal, 1999)
Tuberculous involvement of the brain and spinal cord are common neurological disorders in developing countries and have recently shown a resurgence in developed ones. Tuberculous meningitis is an important manifestation and is associated with high morbidity and mortality. Diagnosis is based on clinical features, cerebrospinal fluid changes, and imaging characteristics. Bacteriological confirmation is not possible in all cases as serological tests do not have sufficient sensitivity and specificity. The polymerase chain reaction shows promise for the future. Appropriate chemotherapeutic agents should be administered as early as possible, although there is no unanimity concerning chemotherapeutic regimens or optimal duration of treatment. The patient's clinical stage at presentation is the most important prognostic factor. The role of corticosteroids is controversial but they should be administered to all patients presenting in stage III. Surgical procedures are directed at management of the hydrocephalus. Focal lesions, intracranial tuberculomas, and tuberculous abscesses, are usually located in cerebral or cerebellar hemispheres, uncommonly in brainstem and very rarely in spinal cord. They do not usually require surgical intervention and respond well to antituberculous treatment, along with corticosteroids.
Keywords: Humans; Tuberculosis; Tomography, X-Ray Computed; Central Nervous System Infections

Inhibition of Autophagy by MiR-30A Induced by Mycobacteria tuberculosis as a Possible Mechanism of Immune Escape in Human Macrophages - Chen, Zhi; Wang, Tongjian; Liu, Zhen; Zhang, Guangyu; Wang, Jinhe; Feng, Shisheng; Liang, Jianqin (Japanese Journal of Infectious Diseases, 2015)
The regulatory mechanism of miRNA induction in response to Mycobacterium tuberculosis (MTB) infection has not been clearly established. Autophagy has recently been identified as an effective way to control intracellular survival of MTB. In the present study, we demonstrate a novel role of miR-30A in the negative regulation of the autophagy-mediated anti-MTB response. We found that overexpression of miR-30A suppresses the elimination of intracellular MTB through the inhibition of autophagy. Furthermore, there was a negative correlation between concentrations of miR-30A and beclin-1 in MTB positive patients and miR-30A expression decreased after anti-TB treatment. Our results indicate that miR-30A plays a key role in immune response against MTB and, therefore, may serve as a potential target for future treatments of tuberculosis infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Autophagy; MicroRNAs

Protein Phosphatases of Pathogenic Bacteria: Role in Physiology and Virulence - Sajid, Andaleeb; Arora, Gunjan; Singhal, Anshika; Kalia, Vipin C.; Singh, Yogendra (Annual Review of Microbiology, 2015)
The role of protein phosphatases in pathogenic bacteria has been studied extensively over the last two decades. Ser/Thr and Tyr phosphatases are associated with growth and virulence of many bacteria. These phosphatases control kinase-mediated functions and return the proteins to their unmodified state. Biochemical, structural, and functional studies, in addition to extensive genetic characterization, have highlighted the importance of phosphatases in bacteria. However, questions remain regarding the mechanisms driving localization of secretory phosphatases to cellular compartments, identification of receptor phosphatase sensory signals, and a possible role of cofactors and ligands in their functions. This review focuses on the role of Ser/Thr- and Tyr-specific phosphatases present in pathogenic bacteria, with an emphasis on the regulation of basic cellular processes and virulence. Furthermore, we highlight their clinical importance and analyze the development of drugs targeting protein phosphatases.
Keywords: Virulence; Bacteria; Bacterial Physiological Phenomena; dephosphorylation; inhibitors; pathogens; Phosphoprotein Phosphatases; regulation; Ser/Thr phosphatases; Tyr phosphatases

Mycobacterium tuberculosis-secreted phosphatases: from pathogenesis to targets for TB drug development - Wong, Dennis; Chao, Joseph D.; Av-Gay, Yossef (Trends in Microbiology, 2013)
Mycobacterium tuberculosis (Mtb) infects human alveolar macrophages and relies on the inhibition of phagosome acidification and maturation. This is, in part, dependent on the disruption of host signaling networks within the macrophage. In recent years, Mtb-secreted protein- and lipid-phosphatases protein-tyrosine phosphatase A (PtpA), PtpB, and secreted acid phosphatase M (SapM) have been shown to contribute to Mtb pathogenicity. Here, we review the current knowledge on PtpA, PtpB, and SapM focusing on their ability to interfere with host functions. We further explore how these phosphatase-dependent host-pathogen interactions can be targeted for novel tuberculosis (TB) drug discovery and examine the ongoing development of inhibitors against these phosphatases.
Keywords: Bacterial Proteins; Humans; Mycobacterium tuberculosis; Host-Pathogen Interactions; Tuberculosis; Antitubercular Agents; Signal Transduction; Enzyme Inhibitors; Phosphoric Monoester Hydrolases

Protein kinase G from pathogenic mycobacteria promotes survival within macrophages - Walburger, Anne; Koul, Anil; Ferrari, Giorgio; Nguyen, Liem; Prescianotto-Baschong, Cristina; Huygen, Kris; Klebl, Bert; Thompson, Charles; Bacher, Gerald; Pieters, Jean (Science (New York, N.Y.), 2004)
Pathogenic mycobacteria resist lysosomal delivery after uptake into macrophages, allowing them to survive intracellularly. We found that the eukaryotic-like serine/threonine protein kinase G from pathogenic mycobacteria was secreted within macrophage phagosomes, inhibiting phagosome-lysosome fusion and mediating intracellular survival of mycobacteria. Inactivation of protein kinase G by gene disruption or chemical inhibition resulted in lysosomal localization and mycobacterial cell death in infected macrophages. Besides identifying a target for the control of mycobacterial infections, these findings suggest that pathogenic mycobacteria have evolved eukaryotic-like signal transduction mechanisms capable of modulating host cell trafficking pathways.
Keywords: Cell Line; Mycobacterium tuberculosis; Animals; Macrophages; Mycobacterium smegmatis; Mice; Signal Transduction; Phagosomes; Mycobacterium bovis; Gene Deletion; Enzyme Inhibitors; Lysosomes; Amides; Cyclic GMP-Dependent Protein Kinases; Thiophenes; Vacuoles

Mycobacterium tuberculosis ManLAM inhibits T-cell-receptor signaling by interference with ZAP-70, Lck and LAT phosphorylation - Mahon, Robert N.; Sande, Obondo J.; Rojas, Roxana E.; Levine, Alan D.; Harding, Clifford V.; Boom, W. Henry (Cellular Immunology, 2012)
Immune evasion is required for Mycobacterium tuberculosis to survive in the face of robust CD4(+) T cell responses. We have shown previously that M. tuberculosis cell wall glycolipids, including mannose capped lipoarabinomannan (ManLAM), directly inhibit polyclonal murine CD4(+) T cell activation by blocking ZAP-70 phosphorylation. We extended these studies to antigen-specific murine CD4(+) T cells and primary human T cells and found that ManLAM inhibited them as well. Lck and LAT phosphorylation also were inhibited by ManLAM without affecting their localization to lipid rafts. Inhibition of proximal TCR signaling was temperature sensitive, suggesting that ManLAM insertion into T cell membranes was required. Thus, M. tuberculosis ManLAM inhibits antigen-specific CD4(+) T cell activation by interfering with very early events in TCR signaling through ManLAM's insertion in T cell membranes.
Keywords: Humans; Membrane Proteins; Mycobacterium tuberculosis; Animals; Cells, Cultured; Mice; Female; T-Lymphocytes; Mice, Inbred C57BL; Signal Transduction; Lipopolysaccharides; Receptors, Antigen, T-Cell; Adaptor Proteins, Signal Transducing; Lymphocyte Specific Protein Tyrosine Kinase p56(lck); Phosphorylation; Membrane Microdomains; Phosphoproteins; ZAP-70 Protein-Tyrosine Kinase

Bacillary replication and macrophage necrosis are determinants of neutrophil recruitment in tuberculosis - Repasy, Teresa; Martinez, Nuria; Lee, Jinhee; West, Kim; Li, Wenjun; Kornfeld, Hardy (Microbes and Infection, 2015)
We previously determined that burst size necrosis is the chief mode of mononuclear cell death in the lungs of mice with tuberculosis. The present study explored the link between infection-induced necrosis of mononuclear phagocytes and neutrophil accumulation in the lungs of mice challenged with one of four Mycobacterium tuberculosis strains of increasing virulence (RvΔphoPR mutant, H37Ra, H37Rv and Erdman). At all time points studied, Erdman produced the highest bacterial load and the highest proportion and number of M. tuberculosis-infected neutrophils. These parameters, and the proportion of TUNEL-positive cells, tracked with virulence across all strains tested. Differences in neutrophil infection were not reflected by levels of chemoattractant cytokines in bronchoalveolar lavage fluid, while interferon-γ (reported to suppress neutrophil trafficking to the lung in tuberculosis) was highest in Erdman-infected mice. Treating Erdman-infected mice with ethambutol decreased the proportion of mononuclear phagocytes with high bacterial burden and the ratio of infected neutrophils to infected mononuclear cells in a dose-dependent manner. We propose that faster replicating M. tuberculosis strains cause more necrosis which in turn promotes neutrophil recruitment. Neutrophils infected with M. tuberculosis constitute a biomarker for poorly controlled bacterial replication, infection-induced mononuclear cell death, and increased severity of immune pathology in tuberculosis.
Keywords: Mycobacterium tuberculosis; Animals; Macrophages; Tuberculosis; Mice; Neutrophils; Virulence; Bacterial Load; Cell Death; Cell death; Neutrophil Infiltration

Inhibition of Autophagy by MiR-30A Induced by Mycobacteria tuberculosis as a Possible Mechanism of Immune Escape in Human Macrophages - Chen, Zhi; Wang, Tongjian; Liu, Zhen; Zhang, Guangyu; Wang, Jinhe; Feng, Shisheng; Liang, Jianqin (Japanese Journal of Infectious Diseases, 2015)
The regulatory mechanism of miRNA induction in response to Mycobacterium tuberculosis (MTB) infection has not been clearly established. Autophagy has recently been identified as an effective way to control intracellular survival of MTB. In the present study, we demonstrate a novel role of miR-30A in the negative regulation of the autophagy-mediated anti-MTB response. We found that overexpression of miR-30A suppresses the elimination of intracellular MTB through the inhibition of autophagy. Furthermore, there was a negative correlation between concentrations of miR-30A and beclin-1 in MTB positive patients and miR-30A expression decreased after anti-TB treatment. Our results indicate that miR-30A plays a key role in immune response against MTB and, therefore, may serve as a potential target for future treatments of tuberculosis infection.
Keywords: Humans; Mycobacterium tuberculosis; Macrophages; Autophagy; MicroRNAs

Alveolar Macrophages Provide an Early Mycobacterium tuberculosis Niche and Initiate Dissemination - Cohen, Sara B.; Gern, Benjamin H.; Delahaye, Jared L.; Adams, Kristin N.; Plumlee, Courtney R.; Winkler, Jessica K.; Sherman, David R.; Gerner, Michael Y.; Urdahl, Kevin B. (Cell Host & Microbe, 2018)
Mycobacterium tuberculosis (Mtb) infection is initiated in the distal airways, but the bacteria ultimately disseminate to the lung interstitium. Although various cell types, including alveolar macrophages (AM), neutrophils, and permissive monocytes, are known to be infected with Mtb, the initially infected cells as well as those that mediate dissemination from the alveoli to the lung interstitium are unknown. In this study, using a murine infection model, we reveal that early, productive Mtb infection occurs almost exclusively within airway-resident AM. Thereafter Mtb-infected, but not uninfected, AM localize to the lung interstitium through mechanisms requiring an intact Mtb ESX-1 secretion system. Relocalization of infected AM precedes Mtb uptake by recruited monocyte-derived macrophages and neutrophils. This dissemination process is driven by non-hematopoietic host MyD88/interleukin-1 receptor inflammasome signaling. Thus, interleukin-1-mediated crosstalk between Mtb-infected AM and non-hematopoietic cells promotes pulmonary Mtb infection by enabling infected cells to disseminate from the alveoli to the lung interstitium.
Keywords: Bacterial Proteins; Mycobacterium tuberculosis; Animals; Tuberculosis; Pulmonary Alveoli; Mice; Granuloma; granuloma; Immunity, Innate; Mice, Inbred C57BL; innate immunity; Mice, Knockout; Inflammation; pulmonary tuberculosis; Macrophages, Alveolar; Myeloid Differentiation Factor 88; IL-1; alveolar macrophages; ESX-1; lung; Receptors, Interleukin-1

Effect of BCG vaccination on childhood tuberculous meningitis and miliary tuberculosis worldwide: a meta-analysis and assessment of cost-effectiveness - Trunz, B. Bourdin; Fine, P. E. M.; Dye, C. (The Lancet, 2006)

Global Tuberculosis Report 2022 - WHO, 2022
Global Tuberculosis Report 2022

Early alveolar macrophage response and IL-1R-dependent T cell priming determine transmissibility of Mycobacterium tuberculosis strains - Lovey, Arianne; Verma, Sheetal; Kaipilyawar, Vaishnavi; Ribeiro-Rodrigues, Rodrigo; Husain, Seema; Palaci, Moises; Dietze, Reynaldo; Ma, Shuyi; Morrison, Robert D.; Sherman, David R.; Ellner, Jerrold J.; Salgame, Padmini (Nature Communications, 2022)
Mechanisms underlying variability in transmission of Mycobacterium tuberculosis strains remain undefined. By characterizing high and low transmission strains of M.tuberculosis in mice, we show here that high transmission M.tuberculosis strain induce rapid IL-1R-dependent alveolar macrophage migration from the alveolar space into the interstitium and that this action is key to subsequent temporal events of early dissemination of bacteria to the lymph nodes, Th1 priming, granulomatous response and bacterial control. In contrast, IL-1R-dependent alveolar macrophage migration and early dissemination of bacteria to lymph nodes is significantly impeded in infection with low transmission M.tuberculosis strain; these events promote the development of Th17 immunity, fostering neutrophilic inflammation and increased bacterial replication. Our results suggest that by inducing granulomas with the potential to develop into cavitary lesions that aids bacterial escape into the airways, high transmission M.tuberculosis strain is poised for greater transmissibility. These findings implicate bacterial heterogeneity as an important modifier of TB disease manifestations and transmission.
Keywords: Mycobacterium tuberculosis; Animals; Pulmonary Alveoli; Tuberculosis, Pulmonary; Mice; Female; Lymph Nodes; Th1 Cells; Lymphocyte Activation; Signal Transduction; Dendritic Cells; Th17 Cells; Macrophages, Alveolar; Cell Movement; Mice, Inbred C3H; Receptors, Interleukin-1 Type I

IFN-γ from CD4 T Cells Is Essential for Host Survival and Enhances CD8 T Cell Function during Mycobacterium tuberculosis Infection - Green, Angela M.; DiFazio, Robert; Flynn, JoAnne L. (The Journal of Immunology, 2013)
IFN-γ is necessary in both humans and mice for control of Mycobacterium tuberculosis. CD4 T cells are a significant source of IFN-γ during acute infection in mice and are required for control of bacterial growth and host survival. However, several other types of cells can and do produce IFN-γ during the course of the infection. We sought to determine whether IFN-γ from sources other than CD4 T cells was sufficient to control M. tuberculosis infection and whether CD4 T cells had a role in addition to IFN-γ production. To investigate the role of IFN-γ from CD4 T cells, a murine adoptive transfer model was developed in which all cells were capable of producing IFN-γ, with the exception of CD4 T cells. Our data in this system support that CD4 T cells are essential for control of infection, but also that IFN-γ from CD4 T cells is necessary for host survival and optimal long-term control of bacterial burden. In addition, IFN-γ from CD4 T cells was required for a robust CD8 T cell response. IFN-γ from T cells inhibited intracellular replication of M. tuberculosis in macrophages, suggesting IFN-γ may be necessary for intracellular bactericidal activity. Thus, although CD4 T cells play additional roles in the control of M. tuberculosis infection, IFN-γ is a major function by which these cells participate in resistance to tuberculosis.

B-Pred, a structure based B-cell epitopes prediction server - Giacò, Luciano; Amicosante, Massimo; Fraziano, Maurizio; Gherardini, Pier Federico; Ausiello, Gabriele; Helmer-Citterich, Manuela; Colizzi, Vittorio; Cabibbo, Andrea (Advances and applications in bioinformatics and chemistry: AABC, 2012)
The ability to predict immunogenic regions in selected proteins by in-silico methods has broad implications, such as allowing a quick selection of potential reagents to be used as diagnostics, vaccines, immunotherapeutics, or research tools in several branches of biological and biotechnological research. However, the prediction of antibody target sites in proteins using computational methodologies has proven to be a highly challenging task, which is likely due to the somewhat elusive nature of B-cell epitopes. This paper proposes a web-based platform for scoring potential immunological reagents based on the structures or 3D models of the proteins of interest. The method scores a protein's peptides set, which is derived from a sliding window, based on the average solvent exposure, with a filter on the average local model quality for each peptide. The platform was validated on a custom-assembled database of 1336 experimentally determined epitopes from 106 proteins for which a reliable 3D model could be obtained through standard modeling techniques. Despite showing poor sensitivity, this method can achieve a specificity of 0.70 and a positive predictive value of 0.29 by combining these two simple parameters. These values are slightly higher than those obtained with other established sequence-based or structure-based methods that have been evaluated using the same epitopes dataset. This method is implemented in a web server called B-Pred, which is accessible at http://immuno.bio.uniroma2.it/bpred. The server contains a number of original features that allow users to perform personalized reagent searches by manipulating the sliding window's width and sliding step, changing the exposure and model quality thresholds, and running sequential queries with different parameters. The B-Pred server should assist experimentalists in the rational selection of epitope antigens for a wide range of applications.
Keywords: B-cell epitopes; bioinformatics; epitope prediction; immunoinformatics; web server

Peptide-Based Vaccines for Tuberculosis - Gong, Wenping; Pan, Chao; Cheng, Peng; Wang, Jie; Zhao, Guangyu; Wu, Xueqiong (Frontiers in Immunology, 2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. As a result of the coronavirus disease 2019 (COVID-19) pandemic, the global TB mortality rate in 2020 is rising, making TB prevention and control more challenging. Vaccination has been considered the best approach to reduce the TB burden. Unfortunately, BCG, the only TB vaccine currently approved for use, offers some protection against childhood TB but is less effective in adults. Therefore, it is urgent to develop new TB vaccines that are more effective than BCG. Accumulating data indicated that peptides or epitopes play essential roles in bridging innate and adaptive immunity and triggering adaptive immunity. Furthermore, innovations in bioinformatics, immunoinformatics, synthetic technologies, new materials, and transgenic animal models have put wings on the research of peptide-based vaccines for TB. Hence, this review seeks to give an overview of current tools that can be used to design a peptide-based vaccine, the research status of peptide-based vaccines for TB, protein-based bacterial vaccine delivery systems, and animal models for the peptide-based vaccines. These explorations will provide approaches and strategies for developing safer and more effective peptide-based vaccines and contribute to achieving the WHO’s End TB Strategy.

Longer peptide can be accommodated in the MHC class I binding site by a protrusion mechanism - Stryhn, A.; Pedersen, L. O.; Holm, A.; Buus, S. (European Journal of Immunology, 2000)
According to current consensus, CD8(+) T cell responses are focused upon short peptide sequences (8-11 amino acids) presented by MHC class I molecules. This size restriction is thought to operate mostly at the level of peptide-MHC class I interaction. Crystal structures have shown that the free N and C termini of a bound peptide interact through hydrogen bonding networks to conserved residues at either end of the class I binding site. Accordingly, it is thought that the termini are fixed and that only minor variations in peptide size are possible through a central bulging mechanism. We find that this consensus view is not always correct as some peptide-MHC class I interaction will accept significant extensions. Furthermore, our results indicate that in some cases protrusion, rather than bulging, may be the mechanism of extension. Depending upon the particular peptide-MHC combination in question, such extensions can occur at either the N or C terminus (but never both at the same time). Finally, we show that MHC and T cell in some cases can detect the identity of the extension, i.e. that extensions may be part of the specificity of the T cell immune response. We suggest that such extensions may play a physiological role.
Keywords: Amino Acid Sequence; Humans; Molecular Sequence Data; Peptides; Tumor Cells, Cultured; CD8-Positive T-Lymphocytes; Antigen Presentation; Histocompatibility Antigens Class I

Analysis of Major Histocompatibility Complex-Bound HIV Peptides Identified from Various Cell Types Reveals Common Nested Peptides and Novel T Cell Responses - Rucevic, Marijana; Kourjian, Georgio; Boucau, Julie; Blatnik, Renata; Garcia Bertran, Wilfredo; Berberich, Matthew J.; Walker, Bruce D.; Riemer, Angelika B.; Le Gall, Sylvie (Journal of Virology, 2016)
Despite the critical role of epitope presentation for immune recognition, we still lack a comprehensive definition of HIV peptides presented by HIV-infected cells. Here we identified 107 major histocompatibility complex (MHC)-bound HIV peptides directly from the surface of live HIV-transfected 293T cells, HIV-infected B cells, and primary CD4 T cells expressing a variety of HLAs. The majority of peptides were 8 to 12 amino acids (aa) long and mostly derived from Gag and Pol. The analysis of the total MHC-peptidome and of HLA-A02-bound peptides identified new noncanonical HIV peptides of up to 16 aa that could not be predicted by HLA anchor scanning and revealed an heterogeneous surface peptidome. Nested sets of surface HIV peptides included optimal and extended HIV epitopes and peptides partly overlapping or distinct from known epitopes, revealing new immune responses in HIV-infected persons. Surprisingly, in all three cell types, a majority of Gag peptides derived from p15 rather than from the most immunogenic p24. The cytosolic degradation of peptide precursors in corresponding cells confirmed the generation of identified surface-nested peptides. Cytosolic degradation revealed peptides commonly produced in all cell types and displayed by various HLAs, peptides commonly produced in all cell types and selectively displayed by specific HLAs, and peptides produced in only one cell type. Importantly, we identified areas of proteins leading to common presentations of noncanonical peptides by several cell types with distinct HLAs. These peptides may benefit the design of immunogens, focusing T cell responses on relevant markers of HIV infection in the context of HLA diversity., IMPORTANCE The recognition of HIV-infected cells by immune T cells relies on the presentation of HIV-derived peptides by diverse HLA molecules at the surface of cells. The landscape of HIV peptides displayed by HIV-infected cells is not well defined. Considering the diversity of HLA molecules in the human population, it is critical for vaccine design to identify HIV peptides that may be displayed despite the HLA diversity. We identified 107 HIV peptides directly from the surface of three cell types infected with HIV. They corresponded to nested sets of HIV peptides of canonical and novel noncanonical lengths not predictable by the presence of HLA anchors. Importantly, we identified areas of HIV proteins leading to presentation of noncanonical peptides by several cell types with distinct HLAs. Including such peptides in vaccine immunogen may help to focus immune responses on common markers of HIV infection in the context of HLA diversity.

Defining the HLA class I‐associated viral antigen repertoire from HIV‐1‐infected human cells - Ternette, Nicola; Yang, Hongbing; Partridge, Thomas; Llano, Anuska; Cedeño, Samandhy; Fischer, Roman; Charles, Philip D.; Dudek, Nadine L.; Mothe, Beatriz; Crespo, Manuel; Fischer, William M.; Korber, Bette T. M.; et al. (European Journal of Immunology, 2016)
Recognition and eradication of infected cells by cytotoxic T lymphocytes is a key defense mechanism against intracellular pathogens. High‐throughput definition of HLA class I‐associated immunopeptidomes by mass spectrometry is an increasingly important analytical tool to advance our understanding of the induction of T‐cell responses against pathogens such as HIV‐1. We utilized a liquid chromatography tandem mass spectrometry workflow including de novo‐assisted database searching to define the HLA class I‐associated immunopeptidome of HIV‐1‐infected human cells. We here report for the first time the identification of 75 HIV‐1‐derived peptides bound to HLA class I complexes that were purified directly from HIV‐1‐infected human primary CD4+ T cells and the C8166 human T‐cell line. Importantly, one‐third of eluted HIV‐1 peptides had not been previously known to be presented by HLA class I. Over 82% of the identified sequences originated from viral protein regions for which T‐cell responses have previously been reported but for which the precise HLA class I‐binding sequences have not yet been defined. These results validate and expand the current knowledge of virus‐specific antigenic peptide presentation during HIV‐1 infection and provide novel targets for T‐cell vaccine development.

HLA variants have different preferences to present proteins with specific molecular functions which are complemented in frequent haplotypes - Karnaukhov, Vadim; Paes, Wayne; Woodhouse, Isaac B.; Partridge, Thomas; Nicastri, Annalisa; Brackenridge, Simon; Shcherbinin, Dmitrii; Chudakov, Dmitry M.; Zvyagin, Ivan V.; Ternette, Nicola; Koohy, Hashem; Borrow, Persephone; et al. (Frontiers in Immunology, 2022)
Human leukocyte antigen (HLA) genes are the most polymorphic loci in the human genome and code for proteins that play a key role in guiding adaptive immune responses by presenting foreign and self peptides (ligands) to T cells. Each person carries up to 6 HLA class I variants (maternal and paternal copies of HLA-A, HLA-B and HLA-C genes) and also multiple HLA class II variants, which cumulatively define the landscape of peptides presented to T cells. Each HLA variant has its own repertoire of presented peptides with a certain sequence motif which is mainly defined by peptide anchor residues (typically the second and the last positions for HLA class I ligands) forming key interactions with the peptide-binding groove of HLA. In this study, we aimed to characterize HLA binding preferences in terms of molecular functions of presented proteins. To focus on the ligand presentation bias introduced specifically by HLA-peptide interaction we performed large-scale in silico predictions of binding of all peptides from human proteome for a wide range of HLA variants and established which functions are characteristic for proteins that are more or less preferentially presented by different HLA variants using statistical calculations and gene ontology (GO) analysis. We demonstrated marked distinctions between HLA variants in molecular functions of preferentially presented proteins (e.g. some HLA variants preferentially present membrane and receptor proteins, while others – ribosomal and DNA-binding proteins) and reduced presentation of extracellular matrix and collagen proteins by the majority of HLA variants. To explain these observations we demonstrated that HLA preferentially presents proteins enriched in amino acids which are required as anchor residues for the particular HLA variant. Our observations can be extrapolated to explain the protective effect of certain HLA alleles in infectious diseases, and we hypothesize that they can also explain susceptibility to certain autoimmune diseases and cancers. We demonstrate that these differences lead to differential presentation of HIV, influenza virus, SARS-CoV-1 and SARS-CoV-2 proteins by various HLA alleles. Taking into consideration that HLA alleles are inherited in haplotypes, we hypothesized that haplotypes composed of a combination of HLA variants with different presentation preferences should be more advantageous as they allow presenting a larger repertoire of peptides and avoiding holes in immunopeptidome. Indeed, we demonstrated that HLA-A/HLA-B and HLA-A/HLA-C haplotypes which have a high frequency in the human population are comprised of HLA variants that are more distinct in terms of functions of preferentially presented proteins than the control pairs.

The Granuloma in Tuberculosis: Dynamics of a Host–Pathogen Collusion - Ehlers, Stefan; Schaible, Ulrich E. (Frontiers in Immunology, 2013)
A granuloma is defined as an inflammatory mononuclear cell infiltrate that, while capable of limiting growth of Mycobacterium tuberculosis, also provides a survival niche from which the bacteria may disseminate. The tuberculosis lesion is highly dynamic and shaped by both, immune response elements and the pathogen. In the granuloma, M. tuberculosis switches to a non-replicating but energy-generating life style whose detailed molecular characterization can identify novel targets for chemotherapy. To secure transmission to a new host, M. tuberculosis has evolved to drive T cell immunity to the point that necrotizing granulomas leak into bronchial cavities to facilitate expectoration of bacilli. From an evolutionary perspective it is therefore questionable whether vaccination and immunity enhancing strategies that merely mimic the natural immune response directed against M. tuberculosis infection can overcome pulmonary tuberculosis in the adult population. Juxtaposition of molecular pathology and immunology with microbial physiology and the use of novel imaging approaches afford an integrative view of the granuloma’s contribution to the life cycle of M. tuberculosis. This review revisits the different input of innate and adaptive immunity in granuloma biogenesis, with a focus on the co-evolutionary forces that redirect immune responses also to the benefit of the pathogen, i.e., its survival, propagation, and transmission.

Respuesta de inmunidad celular en la tuberculosis pulmonar: Revisión - Rivas-Santiago, Bruno; Vieyra-Reyes, Patricia; Araujo, Zaida (Investigación Clínica, 2005)

Respuesta inmunitaria en tuberculosis y el papel de los antígenos de secreción de Mycobacterium tuberculosis en la protección, patología y diagnóstico: Revisión - Araujo, Zaida; Acosta, Mariana; Escobar, Hemir; Baños, Ricardo; Fernández de Larrea, Carlos; Rivas-Santiago, Bruno (Investigación Clínica, 2008)

Respuesta inmune a la infección por Mycobacterium tuberculosis. Una revisión de la literatura (2001)

Respuesta inmune a la infección por Mycobacterium tuberculosis. Una revisión de la literatura - Figueroa, Ma Cecilia Eugenia García-Sancho (Revista del Instituto Nacional de Enfermedades Respiratorias, 2001)

Innate immunity in tuberculosis: host defense vs pathogen evasion - Liu, Cui Hua; Liu, Haiying; Ge, Baoxue (Cellular & Molecular Immunology, 2017)
The major innate immune cell types involved in tuberculosis (TB) infection are macrophages, dendritic cells (DCs), neutrophils and natural killer (NK) cells. These immune cells recognize the TB-causing pathogen Mycobacterium tuberculosis (Mtb) through various pattern recognition receptors (PRRs), including but not limited to Toll-like receptors (TLRs), Nod-like receptors (NLRs) and C-type lectin receptors (CLRs). Upon infection by Mtb, the host orchestrates multiple signaling cascades via the PRRs to launch a variety of innate immune defense functions such as phagocytosis, autophagy, apoptosis and inflammasome activation. In contrast, Mtb utilizes numerous exquisite strategies to evade or circumvent host innate immunity. Here we discuss recent research on major host innate immune cells, PRR signaling, and the cellular functions involved in Mtb infection, with a specific focus on the host’s innate immune defense and Mtb immune evasion. A better understanding of the molecular mechanisms underlying host–pathogen interactions could provide a rational basis for the development of effective anti-TB therapeutics.
Keywords: Antibodies; Vaccine; Immunology; Biomedicine; general; Medical Microbiology; Microbiology

Neutrophils in Tuberculosis: Heterogeneity Shapes the Way? - Lyadova, Irina V. (Mediators of Inflammation, 2017)
Infection with M. tuberculosis remains one of the most common infections in the world. The outcome of the infection depends on host ability to mount effective protection and balance inflammatory responses. Neutrophils are innate immune cells implicated in both processes. Accordingly, during M. tuberculosis infection, they play a dual role. Particularly, they contribute to the generation of effector T cells, participate in the formation of granuloma, and are directly involved in tissue necrosis, destruction, and infection dissemination. Neutrophils have a high bactericidal potential. However, data on their ability to eliminate M. tuberculosis are controversial, and the results of neutrophil depletion experiments are not uniform. Thus, the overall roles of neutrophils during M. tuberculosis infection and factors that determine these roles are not fully understood. This review analyzes data on neutrophil defensive and pathological functions during tuberculosis and considers hypotheses explaining the dualism of neutrophils during M. tuberculosis infection and tuberculosis disease.
Keywords: Humans; Mycobacterium tuberculosis; Animals; Tuberculosis; Granuloma; Neutrophils

Hypervirulent Mycobacterium tuberculosis strain triggers necrotic lung pathology associated with enhanced recruitment of neutrophils in resistant C57BL/6 mice - Almeida, Fabrício M.; Ventura, Thatiana L. B.; Amaral, Eduardo P.; Ribeiro, Simone C. M.; Calixto, Sanderson D.; Manhães, Marcelle R.; Rezende, Andreza L.; Souzal, Giliane S.; Carvalho, Igor S. de; Silva, Elisangela C.; Silva, Juliana Azevedo da; Carvalho, Eulógio C. Q.; et al. (PLOS ONE, 2017)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis (Mtb) that in most cases induces irreversible necrosis of lung tissue as a result of excessive inflammatory reactions. The murine model of TB in resistant C57BL/6 mice infected with reference Mtb strains is widely used in TB studies; however, these mice do not show a necrotic pathology, which restricts their use in studies of irreversible tissue damage. Recently, we demonstrated that necrotic lung lesions could be induced in the C57BL/6 mice by highly virulent Mtb strains belonging to the modern Beijing sublineage. However, the pathogenic mechanisms leading to necrosis in this model were not elucidated. In this study, we investigated the dynamics of lung lesions in mice infected with highly virulent Beijing Mtb strain M299, compared with those infected with laboratory Mtb strain H37Rv. The data demonstrate that necrotic lung lesions in mice infected by the strain M299 were associated with enhanced recruitment of myeloid cells, especially neutrophils, and increased levels of proinflammatory cytokines, consistent with exacerbated inflammation. High levels of IFN-γ production contributed to the control of bacterial growth. Further progression to chronic disease was associated with a reduction in the levels of inflammatory mediators in the lungs, the accumulation of foamy macrophages and partial healing of the necrotic tissue by fibrosis. At a late stage of disease, degradation of foamy cells resulted in the liberation of accumulated lipids and persisting bacilli and further activation of inflammation, which promoted lung consolidation. Overall, our studies show that C57BL/6 mice infected with highly virulent Mtb strain may serve as a TB model reproducing an exacerbated inflammatory response in a resistant host to hypervirulent mycobacteria, leading to irreversible necrotic lung lesions.
Keywords: Mycobacterium tuberculosis; Macrophages; Tuberculosis; Necrosis; Neutrophils; Cytokines; Inflammation; Mouse models

A new unifying theory of the pathogenesis of tuberculosis - Orme, Ian M. (Tuberculosis, 2014)
It is set in stone that Mycobacterium tuberculosis is a facultative intracellular bacterial parasite. This axiom drives our knowledge of the host response, the way we design vaccines against the organism by generating protective T cells, and to a lesser extent, the way we try to target anti-microbial drugs. The purpose of this article is to commit total heresy. I believe that M. tuberculosis can equally well be regarded as an extracellular pathogen and may in fact spend a large percentage of its human lung “life-cycle” in this environment. It is of course intracellular as well, but this may well be little more than a brief interlude after infection of a new host during which the bacterium must replicate to increase its chances of transmission and physiologically adapt prior to moving back to an extracellular phase. As a result, by focusing almost completely on just the intracellular phase, we may be making serious strategic errors in the way we try to intervene in this pathogenic process. It is my opinion that when a TB bacillus enters the lungs and starts to reside inside an alveolar macrophage, its central driving force is to switch on a process leading to lung necrosis, since it is only by this process that the local lung tissue can be destroyed and the bacillus can be exhaled and transmitted. I present here a new model of the pathogenesis of the disease that attempts to unify the pathogenic process of infection, disease, persistence [rather than latency], and reactivation.
Keywords: Tuberculosis; Latency; Persistence; Reactivation

Differential Effect of Viable Versus Necrotic Neutrophils on Mycobacterium tuberculosis Growth and Cytokine Induction in Whole Blood - Lowe, David M.; Demaret, Julie; Bangani, Nonzwakazi; Nakiwala, Justine K.; Goliath, Rene; Wilkinson, Katalin A.; Wilkinson, Robert J.; Martineau, Adrian R. (Frontiers in Immunology, 2018)
Neutrophils exert both positive and negative influences on the host response to tuberculosis, but the mechanisms by which these differential effects are mediated are unknown. We studied the impact of live and dead neutrophils on the control of Mycobacterium tuberculosis using a whole blood bioluminescence-based assay, and assayed supernatant cytokine concentrations using Luminex™ technology and ELISA. CD15+ granulocyte depletion from blood prior to infection with M. tuberculosis-lux impaired control of mycobacteria by 96 h, with a greater effect than depletion of CD4+, CD8+, or CD14+ cells (p < 0.001). Augmentation of blood with viable granulocytes significantly improved control of mycobacteria by 96 h (p = 0.001), but augmentation with necrotic granulocytes had the opposite effect (p = 0.01). Both augmentations decreased supernatant concentrations of tumor necrosis factor and interleukin (IL)-12 p40/p70, but necrotic granulocyte augmentation also increased concentrations of IL-10, G-CSF, GM-CSF, and CCL2. Necrotic neutrophil augmentation reduced phagocytosis of FITC-labeled M. bovis BCG by all phagocytes, whereas viable neutrophil augmentation specifically reduced early uptake by CD14+ cells. The immunosuppressive effect of dead neutrophils required necrotic debris rather than supernatant. We conclude that viable neutrophils enhance control of M. tuberculosis in blood, but necrotic neutrophils have the opposite effect—the latter associated with induction of IL-10, growth factors, and chemoattractants. Our findings suggest a mechanism by which necrotic neutrophils may exert detrimental effects on the host response in active tuberculosis.

Neutrophils in tuberculosis: friend or foe? - ScienceDirect

Neutrophils exert protection in the early tuberculous granuloma by oxidative killing of mycobacteria phagocytosed from infected macrophages - Yang, Chao-Tsung; Cambier, C. J.; Davis, J. Muse; Hall, Christopher J.; Crosier, Philip S.; Ramakrishnan, Lalita (Cell Host & Microbe, 2012)
Neutrophils are typically the first responders in host defense against invading pathogens, which they destroy by both oxidative and nonoxidative mechanisms. However, despite a longstanding recognition of neutrophil presence at disease sites in tuberculosis, their role in defense against mycobacteria is unclear. Here we exploit the genetic tractability and optical transparency of zebrafish to monitor neutrophil behavior and its consequences during infection with Mycobacterium marinum, a natural fish pathogen. In contrast to macrophages, neutrophils do not interact with mycobacteria at initial infection sites. Neutrophils are subsequently recruited to the nascent granuloma in response to signals from dying infected macrophages within the granuloma, which they phagocytose. Some neutrophils then rapidly kill the internalized mycobacteria through NADPH oxidase-dependent mechanisms. Our results provide a mechanistic link to the observed patterns of neutrophils in human tuberculous granulomas and the susceptibility of humans with chronic granulomatous disease to mycobacterial infection.
Keywords: Humans; Molecular Sequence Data; Animals; Macrophages; Sequence Analysis, DNA; Granuloma; Neutrophils; Microbial Viability; Mycobacterium marinum; Zebrafish; Oxidative Stress; Oxidation-Reduction; NADP; Oxidoreductases

Human tuberculosis and Mycobacterium tuberculosis complex: A review on genetic diversity, pathogenesis and omics approaches in host biomarkers discovery - Kanabalan, Renuga Devi; Lee, Le Jie; Lee, Tze Yan; Chong, Pei Pei; Hassan, Latiffah; Ismail, Rosnah; Chin, Voon Kin (Microbiological Research, 2021)
Mycobacterium tuberculosis complex (MTBC) refers to a group of mycobacteria encompassing nine members of closely related species that causes tuberculosis in animals and humans. Among the nine members, Mycobacterium tuberculosis (M. tuberculosis) remains the main causative agent for human tuberculosis that results in high mortality and morbidity globally. In general, MTBC species are low in diversity but exhibit distinctive biological differences and phenotypes among different MTBC lineages. MTBC species are likely to have evolved from a common ancestor through insertions/deletions processes resulting in species speciation with different degrees of pathogenicity. The pathogenesis of human tuberculosis is complex and remains poorly understood. It involves multi-interactions or evolutionary co-options between host factors and bacterial determinants for survival of the MTBC. Granuloma formation as a protection or survival mechanism in hosts by MTBC remains controversial. Additionally, MTBC species are capable of modulating host immune response and have adopted several mechanisms to evade from host immune attack in order to survive in humans. On the other hand, current diagnostic tools for human tuberculosis are inadequate and have several shortcomings. Numerous studies have suggested the potential of host biomarkers in early diagnosis of tuberculosis, in disease differentiation and in treatment monitoring. “Multi-omics” approaches provide holistic views to dissect the association of MTBC species with humans and offer great advantages in host biomarkers discovery. Thus, in this review, we seek to understand how the genetic variations in MTBC lead to species speciation with different pathogenicity. Furthermore, we also discuss how the host and bacterial players contribute to the pathogenesis of human tuberculosis. Lastly, we provide an overview of the journey of “omics” approaches in host biomarkers discovery in human tuberculosis and provide some interesting insights on the challenges and directions of “omics” approaches in host biomarkers innovation and clinical implementation.
Keywords: Pathogenesis; complex (MTBC); Genetic diversity; Host biomarkers; Omics

Pathological and protective roles of dendritic cells in Mycobacterium tuberculosis infection: Interaction between host immune responses and pathogen evasion - Kim, Hongmin; Shin, Sung Jae (Frontiers in Cellular and Infection Microbiology, 2022)
Dendritic cells (DCs) are principal defense components that play multifactorial roles in translating innate immune responses to adaptive immunity in Mycobacterium tuberculosis (Mtb) infections. The heterogeneous nature of DC subsets follows their altered functions by interacting with other immune cells, Mtb, and its products, enhancing host defense mechanisms or facilitating pathogen evasion. Thus, a better understanding of the immune responses initiated, promoted, and amplified or inhibited by DCs in Mtb infection is an essential step in developing anti-tuberculosis (TB) control measures, such as host-directed adjunctive therapy and anti-TB vaccines. This review summarizes the recent advances in salient DC subsets, including their phenotypic classification, cytokine profiles, functional alterations according to disease stages and environments, and consequent TB outcomes. A comprehensive overview of the role of DCs from various perspectives enables a deeper understanding of TB pathogenesis and could be useful in developing DC-based vaccines and immunotherapies.

Pipeline of vaccines (TBVI)

Tuberculosis: un enfoque de Derechos Humanos - Ugarte-Gil, César Augusto (Acta Médica Peruana, 2009)

Tuberculosis y género: cuando la diferencia comporta desigualdad - Goig, Jaime E Ollé; Canela-Soler, Jaume; Pinargote, Israel Molina; García, Xavier Casas
Introduction: Tuberculosis (TB) is still a significant health problem worldwide. There are very effective therapeutical regimens but sometimes they are difficult to administer. Objectives: To study the barriers encountered by female patients in concluding successfully their treatment due to the negative impact of their male partner or a close male family member. Material and methods: We reviewed the clinical records of the female TB patients treated in four centers of different countries (Bolivia, Uganda, Djibouti and Spain) in the past 25 years and chose six representative patients. Results: The six patients had significant difficulties in completing their treatment due to the negative influence of their partner or a close male family member and the social conditioning that still persist. Conclusions: Among female patients, the behavior of their partner or a close male family member may constitute a barrier for achieving a successful TB treatment. Measures must be adopted to minimize this negative impact.